A 3D In Vivo Model for Studying Human Renal Cystic Tissue and Mouse Kidney Slices - Bichlmayer, Eva Marie; Mahl, Lina; Hesse, Leo; Pion, Eric; Haller, Victoria; Moehwald, Andreas; Hackl, Christina; Werner, Jens M.; Schlitt, Hans J.; Schwarz, Siegfried; Kainz, Philipp; Brochhausen, Christoph; et al. (Cells, 2022)
(1) Background: Autosomal dominant polycystic kidney disease (ADPKD) is a frequent monogenic disorder that leads to progressive renal cyst growth and renal failure. Strategies to inhibit cyst growth in non-human cyst models have often failed in clinical trials. There is a significant need for models that enable studies of human cyst growth and drug trials. (2) Methods: Renal tissue from ADPKD patients who received a nephrectomy as well as adult mouse kidney slices were cultured on a chorioallantoic membrane (CAM) for one week. The cyst volume was monitored by microscopic and CT-based applications. The weight and angiogenesis were quantified. Morphometric and histological analyses were performed after the removal of the tissues from the CAM. (3) Results: The mouse and human renal tissue mostly remained vital for about one week on the CAM. The growth of cystic tissue was evaluated using microscopic and CT-based volume measurements, which correlated with weight and an increase in angiogenesis, and was accompanied by cyst cell proliferation. (4) Conclusions: The CAM model might bridge the gap between animal studies and clinical trials of human cyst growth, and provide a drug-testing platform for the inhibition of cyst enlargement. Real-time analyses of mouse kidney tissue may provide insights into renal physiology and reduce the need for animal experiments.
CRIS-Team Scopus Importer:2022-08-12
Keywords: 3D in vivo model; ADPKD; chorioallantoic membrane (CAM) model; human renal cystic tissue; mouse kidney slices; polycystic kidney disease

AA amyloidosis in inflammatory active malignant paraganglioma - Ihne, Sandra; Kircher, Malte; Papagianni, Aikaterini; Goetze, Oliver; Morbach, Caroline; Werner, Rudolf A.; Zeller, Daniel; Sommer, Claudia; Rosenwald, Andreas; Amann, Kerstin Ute; Linke, Reinhold P.; Lapa, Constantin; et al. (Amyloid-Journal of Protein Folding Disorders, 2022)
CRIS-Team WoS Importer:2022-02-11

Acid sphingomyelinase promotes endothelial stress response in systemic inflammation and sepsis - Chung, Ha-Yeun; Hupe, Daniel C.; Otto, Gordon P.; Sprenger, Marcel; Bunck, Alexander C.; Dorer, Michael J.; Bockmeyer, Clemens L.; Deigner, Hans-Peter; Graeler, Markus H.; Claus, Ralf A. (Molecular Medicine, 2016)
The pathophysiology of sepsis involves activation of acid sphingomyelinase (SMPD1) with subsequent generation of the bioactive mediator ceramide. We herein evaluated the hypothesis that the enzyme exerts biological effects in endothelial stress response. Plasma-secreted sphingomyelinase activity, ceramide generation and lipid raft formation were measured in human microcirculatory endothelial cells (HMEC-1) stimulated with serum obtained from sepsis patients. Clustering of receptors relevant for signal transduction was studied by immuno staining. The role of SMPD1 for macrodomain formation was tested by pharmacological inhibition. To confirm the involvement of the stress enzyme, direct inhibitors (amino bisphosphonates) and specific downregulation of the gene was tested with respect to ADAMTS13 expression and cytotoxicity. Plasma activity and amount of SMPD1 were increased in septic patients dependent on clinical severity. Increased breakdown of sphingomyelin to ceramide in HMECs was observed following stimulation with serum from sepsis patients in vitro. Hydrolysis of sphingomyelin, clustering of receptor complexes, such as the CD95L/Fas-receptor, as well as formation of ceramide enriched macrodomains was abrogated using functional inhibitors (desipramine and NB6). Strikingly, the stimulation of HMECs with serum obtained from sepsis patients or mixture of proinflammatory cytokines resulted in cytotoxicity and ADAMTS13 downregulation which was abrogated using desipramine, amino bisphosphonates and genetic inhibitors. SMPD1 is involved in the dysregulation of ceramide metabolism in endothelial cells leading to macrodomain formation, cytotoxicity and downregulation of ADAMTS13 expression. Functional inhibitors, such as desipramine, are capable to improve endothelial stress response during sepsis and might be considered as a pharmacological treatment strategy to favor the outcome.
EVALuna2:25519

A collagen-binding protein enables molecular imaging of kidney fibrosis in vivo - Baues, Maike; Klinkhammer, Barbara M.; Ehling, Josef; Gremse, Felix; van Zandvoort, Marc A.M.J.; Reutelingsperger, Chris P.M.; Daniel, Christoph; Amann, Kerstin Ute; Bábíčková, Janka; Kiessling, Fabian; Floege, Jürgen; Lammers, Twan; et al. (Kidney International, 2019)
Pathological deposition of collagen is a hallmark of kidney fibrosis. To illustrate this process we employed multimodal optical imaging to visualize and quantify collagen deposition in murine models of kidney fibrosis (ischemia-reperfusion or unilateral ureteral obstruction) using the collagen-binding adhesion protein CNA35. For in vivo imaging, we used hybrid computed tomography-fluorescence molecular tomography and CNA35 labeled with the near-infrared fluorophore Cy7. Upon intravenous injection, CNA35-Cy7 accumulation was significantly higher in fibrotic compared to non-fibrotic kidneys. This difference was not detected for a non-specific scrambled version of CNA35-Cy7. Ex vivo, on kidney sections of mice and patients with renal fibrosis, CNA35-FITC co-localized with fibrotic collagen type I and III, but not with the basement membrane collagen type IV. Following intravenous injection, CNA35-FITC bound to both interstitial and perivascular fibrotic areas. In line with this perivascular accumulation, we observed significant perivascular fibrosis in the mouse models and in biopsy sections from patients with chronic kidney disease using computer-based morphometry quantification. Thus, molecular imaging of collagen using CNA35 enabled specific non-invasive quantification of kidney fibrosis. Collagen imaging revealed significant perivascular fibrosis as a consistent component next to the more commonly assessed interstitial fibrosis. Our results lay the basis for further probe and protocol optimization towards the clinical translation of molecular imaging of kidney fibrosis.
CRIS-Team Scopus Importer:2019-12-17
Keywords: chronic kidney disease (CKD); collagen; extracellular matrix; molecular imaging; non-invasive imaging; renal fibrosis

Activated ERK1/2 increases CD44 in glomerular parietal epithelial cells leading to matrix expansion - Roeder, Sebastian S.; Barnes, Taylor J.; Lee, Jonathan S.; Kato, India; Eng, Diana G.; Kaverina, Natalya V.; Sunseri, Maria W.; Daniel, Christoph; Amann, Kerstin Ute; Pippin, Jeffrey W.; Shankland, Stuart J. (Kidney International, 2017)
The glycoprotein CD44 is barely detected in normal mouse and human glomeruli, but is increased in glomerular parietal epithelial cells following podocyte injury in focal segmental glomerulosclerosis (FSGS). To determine the biological role and regulation of CD44 in these cells, we employed an in vivo and in vitro approach. Experimental FSGS was induced in CD44 knockout and wild-type mice with a cytotoxic podocyte antibody. Albuminuria, focal and global glomerulosclerosis (periodic acid-Schiff stain), and collagen IV staining were lower in CD44 knockout compared with wild-type mice with FSGS. Parietal epithelial cells had lower migration from Bowman's capsule to the glomerular tuft in CD44 knockout mice with disease compared with wild type mice. In cultured murine parietal epithelial cells, overexpressing CD44 with a retroviral vector encoding CD44 was accompanied by significantly increased collagen IV expression and parietal epithelial cell migration. Because our results showed de novo co-staining for activated ERK1/2 (pERK) in parietal epithelial cells in experimental FSGS, and also in biopsies from patients with FSGS, two in vitro strategies were employed to prove that pERK regulated CD44 levels. First, mouse parietal epithelial cells were infected with a retroviral vector for the upstream kinase MEK-DD to increase pERK, which was accompanied by increased CD44 levels. Second, in CD44-overexpressing parietal epithelial cells, decreasing pERK with U0126 was accompanied by reduced CD44. Finally, parietal epithelial cell migration was higher in cells with increased and reduced in cells with decreased pERK. Thus, pERK is a regulator of CD44 expression, and increased CD44 expression leads to a pro-sclerotic and migratory parietal epithelial cell phenotype.
EVALuna2:25535

Activation of the receptor for advanced glycation end products induces nuclear inhibitor of protein phosphatase-1 suppression - Liebisch, Marita; Bondeva, Tzvetanka; Franke, Sybille; Daniel, Christoph; Amann, Kerstin Ute; Wolf, Gunter (Kidney International, 2014)
The activation of the receptor for advanced glycation end products (RAGE) is involved in the development of diabetic nephropathy. Analysis of protein phosphatase-1 indicated that advanced glycation end products did not affect its expression, but increased its phosphatase activity. Using differential display analysis we previously demonstrated that stimulation of RAGE in podocytes modulates the expression of numerous genes, among others nuclear inhibitor of protein phosphatase-1 (NIPP1). Here we found that silencing of NIPP1 induced podocyte hypertrophy, cell cycle arrest, and significantly increased protein phosphatase-1 activity. NIPP1 downregulation was associated with increased p27(Kip1) protein expression. Reporter assays revealed a transcriptional activation of nuclear factor-?B in podocytes after suppression of NIPP1. The protein level of NIPP1 was also significantly reduced in podocytes of diabetic mice. Blocking the RAGE in vivo by a soluble analog elevated the NIPP1 protein in podocytes of diabetic mice. Thus, activation of the RAGE by advanced glycation end products or other ligands suppresses NIPP1 expression in diabetic nephropathy, contributes to podocyte hypertrophy, and glomerular inflammation.
EVALuna2:25459

Acute interstitial nephritis after vaccination with BNT162b2 - Rieckmann, Sonja; Seibert, Felix S.; Hogeweg, Maximilian; Bertram, Sebastian; Doevelaar, Adrian A.N.; Amann, Kerstin Ute; Babel, Nina; Westhoff, Timm H. (Journal of Nephrology, 2022)
CRIS-Team Scopus Importer:2022-03-18
Keywords: BNT162b2; COVID-19; Interstitial nephritis; Kidney injury; Vaccination

Acute Kidney Allograft Injury Following Vitamin C Administration for Septic Shock - Mahling, Moritz; Köppen, Michael; Mühlbacher, Thomas; Amann, Kerstin Ute; Königsrainer, Alfred; Heyne, Nils; Häberle, Helene; Nadalin, Silvio; Guthoff, Martina (Kidney International Reports, 2020)
CRIS-Team Scopus Importer:2020-11-20

Acute respiratory and renal failure in a 20-year-old man - Heissner, K.; Riessen, R.; Horger, M.; Amann, Kerstin Ute; Haap, M. (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2015)
EVALuna2:25474

A deep-learning workflow to predict upper tract urothelial carcinoma protein-based subtypes from H&E slides supporting the prioritization of patients for molecular testing - Angeloni, Miriam; van Doeveren, Thomas; Lindner, Sophia; Volland, Patrick; Schmelmer, Jorina; Foersch, Sebastian; Matek, Christian; Stöhr, Robert; Geppert, Carol-Immanuel; Heers, Hendrik; Wach, Sven; Taubert, Helge; et al. (Journal of Pathology: Clinical Research, 2024)
Upper tract urothelial carcinoma (UTUC) is a rare and aggressive, yet understudied, urothelial carcinoma (UC). The more frequent UC of the bladder comprises several molecular subtypes, associated with different targeted therapies and overlapping with protein-based subtypes. However, if and how these findings extend to UTUC remains unclear. Artificial intelligence-based approaches could help elucidate UTUC's biology and extend access to targeted treatments to a wider patient audience. Here, UTUC protein-based subtypes were identified, and a deep-learning (DL) workflow was developed to predict them directly from routine histopathological H&E slides. Protein-based subtypes in a retrospective cohort of 163 invasive tumors were assigned by hierarchical clustering of the immunohistochemical expression of three luminal (FOXA1, GATA3, and CK20) and three basal (CD44, CK5, and CK14) markers. Cluster analysis identified distinctive luminal (N = 80) and basal (N = 42) subtypes. The luminal subtype mostly included pushing, papillary tumors, whereas the basal subtype diffusely infiltrating, non-papillary tumors. DL model building relied on a transfer-learning approach by fine-tuning a pre-trained ResNet50. Classification performance was measured via three-fold repeated cross-validation. A mean area under the receiver operating characteristic curve of 0.83 (95% CI: 0.67–0.99), 0.8 (95% CI: 0.62–0.99), and 0.81 (95% CI: 0.65–0.96) was reached in the three repetitions. High-confidence DL-based predicted subtypes showed significant associations (p < 0.001) with morphological features, i.e. tumor type, histological subtypes, and infiltration type. Furthermore, a significant association was found with programmed cell death ligand 1 (PD-L1) combined positive score (p < 0.001) and FGFR3 mutational status (p = 0.002), with high-confidence basal predictions containing a higher proportion of PD-L1 positive samples and high-confidence luminal predictions a higher proportion of FGFR3-mutated samples. Testing of the DL model on an independent cohort highlighted the importance to accommodate histological subtypes. Taken together, our DL workflow can predict protein-based UTUC subtypes, associated with the presence of targetable alterations, directly from H&E slides.
CRIS-Team Scopus Importer:2024-03-29
Keywords: deep-learning; digital pathology; immunohistochemistry; protein-based subtypes; targeted therapy; upper tract urothelial carcinoma; whole slide images

Adhesion GPCR Gpr126 (Adgrg6) Expression Profiling in Zebrafish, Mouse, and Human Kidney. - Cazorla-Vázquez, Salvador; Kösters, Peter; Bertz, Simone; Pfister, Frederick; Daniel, Christoph; Dedden, Mark; Zundler, Sebastian; Jobst-Schwan, Tilman; Amann, Kerstin Ute; Engel, Felix (Cells, 2023)
Adhesion G protein-coupled receptors (aGPCRs) comprise the second-largest class of GPCRs, the most common target for approved pharmacological therapies. aGPCRs play an important role in development and disease and have recently been associated with the kidney. Several aGPCRs are expressed in the kidney and some aGPCRs are either required for kidney development or their expression level is altered in diseased kidneys. Yet, general aGPCR function and their physiological role in the kidney are poorly understood. Here, we characterize in detail Gpr126 (Adgrg6) expression based on RNAscope® technology in zebrafish, mice, and humans during kidney development in adults. Gpr126 expression is enriched in the epithelial linage during nephrogenesis and persists in the adult kidney in parietal epithelial cells, collecting ducts, and urothelium. Single-cell RNAseq analysis shows that gpr126 expression is detected in zebrafish in a distinct ionocyte sub-population. It is co-detected selectively with slc9a3.2, slc4a4a, and trpv6, known to be involved in apical acid secretion, buffering blood or intracellular pH, and to maintain high cytoplasmic Ca2+ concentration, respectively. Furthermore, gpr126-expressing cells were enriched in the expression of potassium transporter kcnj1a.1 and gcm2, which regulate the expression of a calcium sensor receptor. Notably, the expression patterns of Trpv6, Kcnj1a.1, and Gpr126 in mouse kidneys are highly similar. Collectively, our approach permits a detailed insight into the spatio-temporal expression of Gpr126 and provides a basis to elucidate a possible role of Gpr126 in kidney physiology.
EVALuna2:539836
Keywords: adhesion GPCR; kidney development; Gpr126; parietal epithelial cell; collecting duct; urothelium; ionocytes; zebrafish; RNAscope

Adhesion GPCRs in Kidney Development and Disease - Cazorla-Vázquez, Salvador; Engel, Felix (Frontiers in Cell and Developmental Biology, 2018)
Chronic kidney disease (CKD) represents the fastest growing pathology worldwide with a prevalence of >10% in many countries. In addition, kidney cancer represents 5% of all new diagnosed cancers. As currently no effective therapies exist to restore kidney function after CKD- as well as cancer-induced renal damage, it is important to elucidate new regulators of kidney development and disease as new therapeutic targets. G protein-coupled receptors (GPCRs) represent the most successful class of pharmaceutical targets. In recent years adhesion GPCRs (aGPCRs), the second largest GPCR family, gained significant attention as they are present on almost all mammalian cells, are associated to a plethora of diseases and regulate important cellular processes. aGPCRs regulate for example cell polarity, mitotic spindle orientation, cell migration, and cell aggregation; all processes that play important roles in kidney development and/or disease. Moreover, polycystin-1, a major regulator of kidney development and disease, contains a GAIN domain, which is otherwise only found in aGPCRs. In this review, we assess the potential of aGPCRs as therapeutic targets for kidney disease. For this purpose we have summarized the available literature and analyzed data from the databases The Human Protein Atlas, EURExpress, Nephroseq, FireBrowse, cBioPortal for Cancer Genomics and the National Cancer Institute Genomic Data Commons data portal (NCIGDC). Our data indicate that most aGPCRs are expressed in different spatio-temporal patterns during kidney development and that altered aGPCR expression is associated with a variety of kidney diseases including CKD, diabetic nephropathy, lupus nephritis as well as renal cell carcinoma. We conclude that aGPCRs present a promising new class of therapeutic targets and/or might be useful as diagnostic markers in kidney disease.
EVALuna2:34820

Adhesion G Protein-Coupled Receptor Gpr126 (Adgrg6) Expression Profiling in Diseased Mouse, Rat, and Human Kidneys - Kösters, Peter; Cazorla Vázquez, Salvador; Krüger, René; Daniel, Christoph; Vonbrunn, Eva; Amann, Kerstin Ute; Engel, Felix (Cells, 2024)
Uncovering the function of understudied G protein-coupled receptors (GPCRs) provides a wealth of untapped therapeutic potential. The poorly understood adhesion GPCR Gpr126 (Adgrg6) is widely expressed in developing kidneys. In adulthood, Gpr126 expression is enriched in parietal epithelial cells (PECs) and epithelial cells of the collecting duct and urothelium. Whether Gpr126 plays a role in kidney disease remains unclear. Here, we characterized Gpr126 expression in diseased kidneys in mice, rats, and humans. RT-PCR data show that Gpr126 expression is altered in kidney disease. A quantitative RNAscope® analysis utilizing cell type-specific markers revealed that Gpr126 expression upon tubular damage is mainly increased in cell types expressing Gpr126 under healthy conditions as well as in cells of the distal and proximal tubules. Upon glomerular damage, an increase was mainly detected in PECs. Notably, Gpr126 expression was upregulated in an ischemia/reperfusion model within hours, while upregulation in a glomerular damage model was only detected after weeks. An analysis of kidney microarray data from patients with lupus nephritis, IgA nephropathy, focal segmental glomerulosclerosis (FSGS), hypertension, and diabetes as well as single-cell RNA-seq data from kidneys of patients with acute kidney injury and chronic kidney disease indicates that GPR126 expression is also altered in human kidney disease. In patients with FSGS, an RNAscope® analysis showed that GPR126 mRNA is upregulated in PECs belonging to FSGS lesions and proximal tubules. Collectively, we provide detailed insights into Gpr126 expression in kidney disease, indicating that GPR126 is a potential therapeutic target.
CRIS-Team Scopus Importer:2024-05-31
Keywords: adhesion GPCR; collecting duct; focal segmental glomerulosclerosis; Gpr126; human; kidney disease; parietal epithelial cell; RNAscope; urothelium

Advances in heart regeneration based on cardiomyocyte proliferation and regenerative potential of binucleated cardiomyocytes and polyploidization - Leone, Marina; Engel, Felix (Clinical Science, 2019)
One great achievement in medical practice is the reduction in acute mortality of myocardial infarction due to identifying risk factors, antiplatelet therapy, optimized hospitalization and acute percutaneous coronary intervention. Yet, the prevalence of heart failure is increasing presenting a major socio-economic burden. Thus, there is a great need for novel therapies that can reverse damage inflicted to the heart. In recent years, data have accumulated suggesting that induction of cardiomyocyte proliferation might be a future option for cardiac regeneration. Here, we review the relevant literature since September 2015 concluding that it remains a challenge to verify that a therapy induces indeed cardiomyocyte proliferation. Most importantly, it is unclear that the detected increase in cardiomyocyte cell cycle activity is required for an associated improved function. In addition, we review the literature regarding the evidence that binucleated and polyploid mononucleated cardiomyocytes can divide, and put this in context to other cell types. Our analysis shows that there is significant evidence that binucleated cardiomyocytes can divide. Yet, it remains elusive whether also polyploid mononucleated cardiomyocytes can divide, how efficient proliferation of binucleated cardiomyocytes can be induced, what mechanism regulates cell cycle progression in these cells, and what fate and physiological properties the daughter cells have. In summary, we propose to standardize and independently validate cardiac regeneration studies, encourage the field to study the proliferative potential of binucleated and polyploid mononucleated cardiomyocytes, and to determine whether induction of polyploidization can enhance cardiac function post-injury.
CRIS-Team Scopus Importer:2019-06-28
Keywords: binucleation; cell cycle; heart regeneration; polyploidy; proliferation

Afferent neurons of the kidney with impaired firing pattern in inflammation – role of sodium currents? - Lale, Nena; Ditting, Tilmann; Hilgers, Karl Friedrich; Linz, Peter; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Rodionova, Kristina (Pflügers Archiv: European Journal of Physiology, 2023)
Peripheral neurons with renal afferents exhibit a predominantly tonic firing pattern of higher frequency that is reduced to low frequencies (phasic firing pattern) in renal inflammation. We wanted to test the hypothesis that the reduction in firing activity during inflammation is due to high-activity tonic neurons switching from higher to low frequencies depending on altered sodium currents. We identified and cultivated afferent sensory neurons with renal projections from the dorsal root ganglia (Th11-L2). Cultivated neurons were incubated with the chemokine CXCL1 (1,5 nmol/ml) for 12 h. We characterized neurons as “tonic,” i.e., sustained action potential (AP) firing, or “phasic,” i.e., < 5 APs upon stimulation in the current clamp. Their membrane currents were investigated in a voltage clamp. Data analyzed: renal vs. non-renal and tonic vs. phasic neurons. Renal afferent neurons exposed to CXCL1 showed a decrease in tonic firing pattern (CXCL1: 35,6% vs. control: 57%, P < 0.05). Na+ and K+ currents were not different between control renal and non-renal DRG neurons. Phasic neurons exhibited higher Na+ and K+ currents than tonic resulting in shorter APs (3.7 ± 0.3 vs. 6.1 ± 0.6 ms, P < 0.01). In neurons incubated with CXCL1, Na+ and K+ peak current density increased in phasic (Na+: − 969 ± 47 vs. − 758 ± 47 nA/pF, P < 0.01; K+: 707 ± 22 vs. 558 ± 31 nA/pF, P < 0.01), but were unchanged in tonic neurons. Phasic neurons exposed to CXCL1 showed a broader range of Na+ currents ([− 365– − 1429 nA] vs. [− 412– − 4273 nA]; P < 0.05) similar to tonic neurons. After CXCL1 exposure, significant changes in phasic neurons were observed in sodium activation/inactivation as well as a wider distribution of Na+ currents characteristic of tonic neurons. These findings indicate a subgroup of tonic neurons besides mere tonic or phasic neurons exists able to exhibit a phasic activity pattern under pathological conditions.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Chemokine; Firing pattern; Phasic; Renal afferent nerve; Sodium currents; Tonic; Voltage-gated sodium channels

AFFERENT PEPTIDERGIC NERVE FIBERS - IMPORTANCE FOR THE SALT METABOLISM BEYOND THE KIDNEYS? - Ditting, Tilmann; Rodionova, Kristina; Reeh, Peter; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Ott, Christianroland; Veelken, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Afferent renal innervation in anti-Thy1.1 nephritis in rats - Rodionova, Kristina; Veelken, Roland; Hilgers, Karl Friedrich; Paulus, Eva Maria; Linz, Peter; Fischer, Michael J.M.; Schenker, Martina; Reeh, Peter; Tiegs, Gisa; Ott, Christian; Schmieder, Roland; Schiffer, Mario; et al. (American Journal of Physiology-Renal Physiology, 2020)
Afferent renal nerves exhibit a dual function controlling central sympathetic outflow via afferent electrical activity and influencing intrarenal immunological processes by releasing peptides such as calcitonin gene-related peptide (CGRP). We tested the hypothesis that increased afferent and efferent renal nerve activity occur with augmented release of CGRP in anti-Thy1.1 nephritis, in which enhanced CGRP release exacerbates inflammation. Nephritis was induced in Sprague-Dawley rats by intravenous injection of OX-7 antibody (1.75 mg/kg), and animals were investigated neurophysiologically, electrophysiologically, and pathomorphologically 6 days later. Nephritic rats exhibited proteinuria (169.3 ± 10.2 mg/24 h) with increased efferent renal nerve activity (14.7 ± 0.9 bursts/s vs. control 11.5 ± 0.9 bursts/s, n = 11, P < 0.05). However, afferent renal nerve activity (in spikes/s) decreased in nephritis (8.0 ± 1.8 Hz vs. control 27.4 ± 4.1 Hz, n = 11, P < 0.05). In patch-clamp recordings, neurons with renal afferents from nephritic rats showed a lower frequency of high activity following electrical stimulation (43.4% vs. 66.4% in controls, P < 0.05). In vitro assays showed that renal tissue from nephritic rats exhibited increased CGRP release via spontaneous (14 ± 3 pg/mL vs. 6.8 ± 2.8 pg/ml in controls, n = 7, P < 0.05) and stimulated mechanisms. In nephritic animals, marked infiltration of macrophages in the interstitium (26 ± 4 cells/mm2) and glomeruli (3.7 ± 0.6 cells/glomerular cross-section) occurred. Pretreatment with the CGRP receptor antagonist CGRP8-37 reduced proteinuria, infiltration, and proliferation. In nephritic rats, it can be speculated that afferent renal nerves lose their ability to properly control efferent sympathetic nerve activity while influencing renal inflammation through increased CGRP release.
CRIS-Team Scopus Importer:2020-11-13
Keywords: afferent renal neerves; calcitonin gene-related peptide; renal inflammation; renal innervation; sympathetic innervation

AFFERENT RENAL NERVE PATHWAYS IN RATS - RESPONSIVENESS TO HIGH SALT INTAKE - Rodionova, Kristina; Ditting, Tilmann; Fahrmeier, Franziska; Ott, Chirstian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

A High Fat Diet During Pregnancy and Lactation Induces Cardiac and Renal Abnormalities in GLUT4 +/- Male Mice - Kruse, Michael; Fiallo, Ariana; Tao, Jianling; Susztak, Katalin; Amann, Kerstin Ute; Katz, Ellen B.; Charron, Maureen J. (Kidney & Blood Pressure Research, 2017)
Altered nutrients during the in utero (IU) and/or lactation (L) period predispose offspring to cardio-renal diseases in adulthood. This study investigates the effect of a high fat diet (HFD) fed to female mice during IU/L on gene expression patterns associated with heart and kidney failure and hypertension in male offspring.Female wild type (WT) mice were fed either a HFD or control chow (C) prior to mating with males with a genetic heterozygous deletion of GLUT4 (G4+/-, a model of peripheral insulin resistance and hypertension) and throughout IU/L. After weaning male offspring were placed on a standard rodent chow until 24 weeks of age.All offspring exposed to a maternal HFD showed increased heart and kidney weight and reduced cardiac insulin responsiveness. G4+/- offspring on a HFD displayed early hypertension associated with increased renal gene expression of renin and the AT1- receptors compared to G4+/- on a C diet. This group showed decreased cardiac expression of key genes involved in fatty acid oxidation compared to WT on a C diet.These results indicate an interaction between a HFD diet and genotype during early life development that can enhance susceptibility to cardio-renal diseases later in life.
EVALuna2:25542

AKAP6 orchestrates the nuclear envelope microtubule-organizing center by linking golgi and nucleus via AKAP9 - Vergarajauregui, Silvia; Becker, Robert; Steffen, Ulrike; Sharkova, Maria; Esser, Tilman; Petzold, Jana; Billing, Florian; Kapiloff, Michael S.; Schett, Georg; Thievessen, Ingo; Engel, Felix (eLife, 2020)
The switch from centrosomal microtubule-organizing centers (MTOCs) to noncentrosomal MTOCs during differentiation is poorly understood. Here, we identify AKAP6 as key component of the nuclear envelope MTOC. In rat cardiomyocytes, AKAP6 anchors centrosomal proteins to the nuclear envelope through its spectrin repeats, acting as an adaptor between nesprin-1 alpha and Pcnt or AKAP9. In addition, AKAP6 and AKAP9 form a protein platform tethering the Golgi to the nucleus. Both Golgi and nuclear envelope exhibit MTOC activity utilizing either AKAP9, or Pcnt-AKAP9, respectively. AKAP6 is also required for formation and activity of the nuclear envelope MTOC in human osteoclasts. Moreover, ectopic expression of AKAP6 in epithelial cells is sufficient to recruit endogenous centrosomal proteins. Finally, AKAP6 is required for cardiomyocyte hypertrophy and osteoclast bone resorption activity. Collectively, we decipher the MTOC at the nuclear envelope as a bi-layered structure generating two pools of microtubules with AKAP6 as a key organizer.
CRIS-Team WoS Importer:2021-01-01

Akute Nierenschädigung bei Leberinsuffizienz – Fall 10/2016 - Werner, Christoph R.; Wagner, Verena; Sipos, Bence; Büttner-Herold, Maike; Amann, Kerstin Ute; Haap, Michael; Malek, Nisar P.; Bitzer, Michael; Artunc, Ferruh (Deutsche Medizinische Wochenschrift, 2016)
History and admission findings: We report on a 76-year-old man presenting with painless jaundice who developed dialysis-dependent acute kidney injury. Investigations: Biliary tract was examined with endoscopy, in addition kidney biopsy was performed. Diagnosis, treatment and course: A stenosing process could be seen in the biliary tract, leading to stent implantation. However, jaundice did not resolve. Kidney biopsy revealed bile casts indicating cholemic nephropathy. After switch of concomitant medication, hyperbilirubinemia resolved and kidney function was completely restored. Conclusion: Cholestatic liver disease can cause acute kidney injury by formation of bile casts in the tubuli defining cholemic nephropathy. Resolution of cholestasis can restore kidney functio
EVALuna2:25551

Akutes Nierenversagen, Raynaud-Phänomen und thrombotische Mikroangiopathie – wie passt das zusammen? - Hasan, C. W.; Scheel, M.; Baumgärtel, M. W.; Büttner-Herold, Maike; Friesicke, H. (Die Nephrologie, 2024)
CRIS-Team Scopus Importer:2025-02-04

A large-scale functional high-throughput screening identifies miR-515 and miR-519e as potent inducers of human iPSC-cardiomyocyte proliferation - Renikunta, H. V.; Lazarow, K.; Gong, Y.; Shukla, P. C.; Giral, H.; Kratzer, A.; Nageswaran, V.; Opitz, L.; Engel, Felix; Haghikia, A.; Paneni, F.; Von Kries, J. P.; et al. (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Alkali therapy protects renal function, suppresses inflammation, and improves cellular metabolism in kidney disease - Pastor Arroyo, Eva Maria; Yassini, Nima; Sakiri, Elif; Russo, Giancarlo; Bourgeois, Soline; Mohebbi, Nilufar; Amann, Kerstin Ute; Joller, Nicole; Wagner, Carsten A.; Imenez Silva, Pedro Henrique (Clinical Science, 2022)
Chronic kidney disease (CKD) affects approximately 10-13% of the population worldwide and halting its progression is a major clinical challenge. Metabolic acidosis is both a consequence and a possible driver of CKD progression. Alkali therapy counteracts these effects in CKD patients, but underlying mechanisms remain incompletely understood. Here we show that bicarbonate supplementation protected renal function in a murine CKD model induced by an oxalate-rich diet. Alkali therapy had no effect on the aldosterone-endothelin axis but promoted levels of the anti-aging protein klotho; moreover, it suppressed adhesion molecules required for immune cell invasion along with reducing T-helper cell and inflammatory monocyte invasion. Comparing transcriptomes from the murine crystallopathy model and from human biopsies of kidney transplant recipients (KTRs) suffering from acidosis with or without alkali therapy unveils parallel transcriptome responses mainly associated with lipid metabolism and oxidoreductase activity. Our data reveal novel pathways associated with acidosis in kidney disease and sensitive to alkali therapy and identifies potential targets through which alkali therapy may act on CKD and that may be amenable for more targeted therapies.
CRIS-Team Scopus Importer:2022-05-06
Keywords: acid-base balance; alkali therapy; chronic kidney disease; crystal nephropathy; inflammation; metabolism

ALLOGRAFT INFILTRATION AND MENINGOENCEPHALITIS BY SARS-COV-2 IN A PANCREAS-KIDNEY TRANSPLANT RECIPIENT - Doevelaar, A.; Seibert, F.; Bauer, F.; Stervbo, U.; Anft, M.; Rohn, B.; Winnekendonk, G.; Dittmer, U.; Schenker, P.; Amann, Kerstin Ute; Zgoura, P.; Viebahn, R.; et al. (TRANSPLANT INTERNATIONAL, 2020)
CRIS-Team WoS Importer:2020-11-06

Allograft infiltration and meningoencephalitis by SARS-CoV-2 in a pancreas-kidney transplant recipient - Westhoff, Timm H.; Seibert, Felix S.; Bauer, Frederic; Stervbo, Ulrik; Anft, Moritz; Doevelaar, Adrian A. N.; Rohn, Benjamin J.; Winnekendonk, Guido; Dittmer, Ulf; Schenker, Peter; Vonbrunn, Eva; Amann, Kerstin Ute; et al. (American Journal of Transplantation, 2020)
Severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) preferentially affects epithelia of the upper and lower respiratory tract. Thus, impairment of kidney function has been primarily attributed until now to secondary effects such as cytokine release or fluid balance disturbances. We provide evidence that SARS-CoV-2 can directly infiltrate a kidney allograft. A 69-year-old male, who underwent pancreas-kidney transplantation 13 years previously, presented to our hospital with coronavirus disease 2019 (COVID-19) pneumonia and impaired pancreas and kidney allograft function. Kidney biopsy was performed showing tubular damage and an interstitial mononuclear cell infiltrate. Reverse transcriptase polymerase chain reaction from the biopsy specimen was positive for SARS-CoV-2. In-situ hybridization revealed SARS-CoV-2 RNA in tubular cells and the interstitium. Subsequently, he had 2 convulsive seizures. Magnetic resonance tomography suggested meningoencephalitis, which was confirmed by SARS-CoV-2 RNA transcripts in the cerebrospinal fluid. The patient had COVID-19 pneumonia, meningoencephalitis, and nephritis. SARS-CoV-2 binds to its target cells through angiotensin-converting enzyme 2, which is expressed in a broad variety of tissues including the lung, brain, and kidney. SARS-CoV-2 thereby shares features with other human coronaviruses including SARS-CoV that were identified as pathogens beyond the respiratory tract as well. The present case should provide awareness that extrapulmonary symptoms in COVID-19 may be attributable to viral infiltration of diverse organs.
CRIS-Team Scopus Importer:2020-09-11

Alternative Splicing in Mechanically Stretched Podocytes as a Model of Glomerular Hypertension - Mattias, Francescapaola; Tsoy, Olga; Hammer, Elke; Gress, Alexander; Simm, Stefan; Lio, Chit Tong; Ameling, Sabine; Amann, Kerstin Ute; Dreher, Leonie; Wenzel, Ulrich; Kacprowski, Tim; List, Markus; et al. (Journal of the American Society of Nephrology, 2025)
Background: Alterations in pre-mRNA splicing are crucial to the pathophysiology of various diseases. However, the effects of alternative splicing of mRNA on podocytes in hypertensive nephropathy are still unknown. The Sys-CARE project aimed to identify alternative splicing events involved in the development and progression of glomerular hypertension. Methods: Murine podocytes were exposed to mechanical stretch, after which proteins and mRNA were analyzed by proteomics, RNA sequencing and several bioinformatic alternative splicing tools. Results: Using transcriptomic and proteomic analysis, we identified significant changes in gene expression and protein abundance due to mechanical stretch. RNA-Seq identified over 3,000 alternative spliced genes after mechanical stretch, including all types of alternative splicing events. Among these, 17 genes exhibited an alternative splicing event across four different splicing analysis tools. From this group, we focused on Myl6, a component of the myosin protein complex, and Shroom3, an actin-binding protein essential for podocyte function. We identified two Shroom3 isoforms with significant expression changes under mechanical stretch, which was validated by qRT-PCR and in situ hybridization. Additionally, we observed an expression switch of two Myl6 isoforms after mechanical stretch, accompanied by an alteration in the C-terminal amino acid sequence. Conclusions: A comprehensive RNA-Seq analysis of mechanically stretched podocytes identified novel potential podocyte-specific biomarkers and highlighted significant alternative splicing events, notably in the mRNA of Shroom3 and Myl6.
CRIS-Team Scopus Importer:2025-06-06

Alternative splicing of pericentrin contributes to cell cycle control in cardiomyocytes - Steinfeldt, Jakob; Becker, Robert; Vergarajauregui, Silvia; Engel, Felix (Journal of Cardiovascular Development and Disease, 2021)
Induction of cardiomyocyte proliferation is a promising option to regenerate the heart. Thus, it is important to elucidate mechanisms that contribute to the cell cycle arrest of mammalian cardiomyocytes. Here, we assessed the contribution of the pericentrin (Pcnt) S isoform to cell cycle arrest in postnatal cardiomyocytes. Immunofluorescence staining of Pcnt isoforms combined with SiRNA-mediated depletion indicates that Pcnt S preferentially localizes to the nuclear envelope, while the Pcnt B isoform is enriched at centrosomes. This is further supported by the localization of ectopically expressed FLAG-tagged Pcnt S and Pcnt B in postnatal cardiomyocytes. Analysis of centriole configuration upon Pcnt depletion revealed that Pcnt B but not Pcnt S is required for centriole cohesion. Importantly, ectopic expression of Pcnt S induced centriole splitting in a heterologous system, ARPE-19 cells, and was sufficient to impair DNA synthesis in C2C12 myoblasts. Moreover, Pcnt S depletion enhanced serum-induced cell cycle re-entry in postnatal cardiomyocytes. Analysis of mitosis, binucleation rate, and cell number suggests that Pcnt S depletion enhances serum-induced progression of postnatal cardiomyocytes through the cell cycle resulting in cell division. Collectively, our data indicate that alternative splicing of Pcnt contributes to the establishment of cardiomyocyte cell cycle arrest shortly after birth.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Cardiomyocyte; Cell cycle; Centriole splitting; Centrosome; Heart regeneration; Non-centrosomal microtubule organizing center; Pericentrin

A mutation within the SH2 domain of slp-76 regulates the tissue distribution and cytokine production of iNKT cells in mice - Danzer, Claudia Agnes; Koller, Anna; Baier, Julia; Arnold, Harald; Giessler, Claudia; Opoka, Robert; Schmidt, Stephanie; Willers, Maike; Mihai, Sidonia; Parsch, Hans; Wirtz, Stefan; Daniel, Christoph; et al. (European Journal of Immunology, 2016)
TCR ligation is critical for the selection, activation, and integrin expression of T lymphocytes. Here, we explored the role of the TCR adaptor protein slp-76 on iNKT-cell biology. Compared to B6 controls, slp-76(ace/ace) mice carrying a missense mutation (Thr428Ile) within the SH2-domain of slp-76 showed an increase in iNKT cells in the thymus and lymph nodes, but a decrease in iNKT cells in spleens and livers, along with reduced ADAP expression and cytokine response. A comparable reduction in iNKT cells was observed in the livers and spleens of ADAP-deficient mice. Like ADAP(-/-) iNKT cells, slp-76(ace/ace) iNKT cells were characterized by enhanced CD11b expression, correlating with an impaired induction of the TCR immediate-early gene Nur77 and a decreased adhesion to ICAM-1. Furthermore, CD11b-intrinsic effects inhibited cytokine release, concanavalin A-mediated inflammation, and iNKT-cell accumulation in the liver. Unlike B6 and ADAP(-/-) mice, the expression of the transcription factors Id3 and PLZF was reduced, whereas NP-1-expression was enhanced in slp-76(ace/ace) mice. Blockade of NP-1 decreased the recovery of iNKT cells from peripheral lymph nodes, identifying NP-1 as an iNKT-cell-specific adhesion factor. Thus, slp-76 contributes to the regulation of the tissue distribution, PLZF, and cytokine expression of iNKT cells via ADAP-dependent and -independent mechanisms.
EVALuna2:2050

Amyloid fibril structure from the vascular variant of systemic AA amyloidosis - Banerjee, Sambhasan; Baur, Julian; Daniel, Christoph; Pfeiffer, Peter Benedikt; Hitzenberger, Manuel; Kuhn, Lukas; Wiese, Sebastian; Bijzet, Johan; Haupt, Christian; Amann, Kerstin Ute; Zacharias, Martin; Hazenberg, Bouke P.C.; et al. (Nature Communications, 2022)
Systemic AA amyloidosis is a debilitating protein misfolding disease in humans and animals. In humans, it occurs in two variants that are called ‘vascular’ and ‘glomerular’, depending on the main amyloid deposition site in the kidneys. Using cryo electron microscopy, we here show the amyloid fibril structure underlying the vascular disease variant. Fibrils purified from the tissue of such patients are mainly left-hand twisted and contain two non-equal stacks of fibril proteins. They contrast in these properties to the fibrils from the glomerular disease variant which are right-hand twisted and consist of two structurally equal stacks of fibril proteins. Our data demonstrate that the different disease variants in systemic AA amyloidosis are associated with different fibril morphologies.
CRIS-Team Scopus Importer:2022-12-02

ANCA-positive IgA nephropathy in a patient with ANA-positive long-standing rheumatoid arthritis and type 1 diabetes. - Krasselt, Marco; Halbritter, Jan; Amann, Kerstin Ute; Baerwald, Christoph G.; Seifert, Olga (Clinical and Experimental Rheumatology, 2020)
EVALuna2:421408

ANCA-positive IgA nephropathy in a patient with ANA-positive long-standing rheumatoid arthritis and type 1 diabetes - Krasselt, Marco; Halbritter, Jan; Amann, Kerstin Ute; Baerwald, Christoph; Seifert, Olga (Clinical and Experimental Rheumatology, 2020)
CRIS-Team Scopus Importer:2020-06-05

ANCA-positive vasculitis as a secondary autoimmune disease after autologous stem cell transplantation for systemic sclerosis: a case report - Schmalzing, M; Amann, Kerstin Ute; Tony, H-P (Clinical and Experimental Rheumatology, 2014)
Autologous stem cell transplantation (SCT) is increasingly used to treat autoimmune diseases (AD), in particular systemic sclerosis (SSc). Secondary autoimmune diseases are a known complication after autologous stem cell transplantations for any cause. A 43-year-old man had received an autologous stem cell transplantation for an aggressive diffuse cutaneous SSc. After mobilisation with cyclophosphamide and Granulocyte-Colony-Stimulating Factor stem cells were CD34-selected. The patient received a conditioning regimen with cyclophosphamide and Antithymocyte globulin. He had an excellent response with the modified Rodnan Skin Score decreasing from 34 to 3. One year and 4 months after SCT mild erythrocyturia without acanthocytes and proteinuria were seen for the first time on routine urinalysis. During the following year erythrocyturia increased to 131 erythrocytes /?l and protein excretion to 628 mg/g creatinine. At that time, acanthocytes of 25% finally could be detected. Due to the clearly nephritic constellation in urinalysis a renal biopsy was performed, which revealed mild global and focal-segmental sclerosing and focal-segmental proliferative glomerulonephritis without any signs of a IgA-nephropathy. The result was compatible with a renal manifestation of a small-vessel vasculitis. During the following laboratory workup ANCA of a perinuclear pattern with specificity for myeloperoxidase in high titers could be detected. Therefore the diagnosis of a p-ANCA-positive glomerulonephritis was established. As treatment, the patient received Rituximab, which turned out to be effective. We provide the first report of a patient who developed a p-ANCA-associated vasculitis after autologous stem cell transplantation for an autoimmune disease, namely systemic sclerosis.
EVALuna2:25472

Angiostatic immune reaction in colorectal carcinoma: Impact on survival and perspectives for antiangiogenic therapy - Naschberger, Elisabeth; Croner, Roland S.; Merkel, Susanne; Dimmler, Arno; Tripal, Philipp; Amann, Kerstin Ute; Kremmer, Elisabeth; Brueckl, Wolfgang M.; Papadopoulos, Thomas; Hohenadl, Christine; Hohenberger, Werner; Stürzl, Michael (International Journal of Cancer, 2008)
Angiogenesis and inflammation are the 2 major stroma reactions in colorectal carcinoma (CRC). Guanylate binding protein-1 (GBP-1) is a key mediator of angiostatic effects of inflammation. Therefore, we hypothesized that GBP-1 may be a biomarker of intrinsic angiostasis associated with an improved outcome in CRC patients. GBP-1 was strongly expressed in endothelial cells and immune cells in the desmoplastic stroma of 32% of CRC as determined by immunohistochemical investigation of 388 sporadic CRC. Cancer-related 5-year survival was highly significant (p < 0.001) increased (16.2%) in patients with GBP-1-positive CRC. Multivariate analysis showed that GBP-1 is an independent prognostic factor indicating a reduction of the relative risk of cancer-related death by the half (p = 0.032). A comparative transcriptome analysis (22,215 probe sets) of GBP-1-positive (n = 12) and -negative (n = 12) tumors showed that particularly IFN-γ-induced genes including the major antiangiogenic chemokines CXCL9, CXCL10 and CXCL11 were coexpressed with GBP-1. Altogether our findings indicated that GBP-1 may be a novel biomarker and an active component of a Th-1-like angiostatic immune reaction in CRC. This reaction may affect patient's response to antiangiogenic therapy and the identification of such tumors may provide a novel criterion for patient selection. Moreover, the induction of a Th-1-like angiostatic immune reaction may be a promising approach for the clinical treatment of CRC. © 2008 Wiley-Liss, Inc.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Colorectal carcinoma; Guanylate binding protein-1; Inflammation; Interferon-γ

Angiotensin II type 1a receptor-deficient mice develop angiotensin II-induced oxidative stress and DNA damage without blood pressure increase - Zimnol, Anna; Amann, Kerstin Ute; Mandel, Philipp; Hartmann, Christina; Schupp, Nicole (American Journal of Physiology-Renal Physiology, 2017)
Hypertensive patients have an increased risk to develop kidney cancer. We have shown in vivo, that besides elevating blood pressure, angiotensin II causes DNA damage dose-dependently. Here, the role of blood pressure in the formation of DNA damage is studied. Mice lacking one of the two murine angiotensin II type 1 receptor (AT1R) subtypes, AT1aR, were equipped with osmotic minipumps, delivering angiotensin II during 28 days. Parameters of oxidative stress and DNA damage of kidneys and hearts of AT1aR-knockout mice were compared to wildtype (C57BL/6) mice receiving angiotensin II, and additionally, to wildtype (WT) mice treated with candesartan, an antagonist of both AT1R-subtypes. In WT mice, angiotensin II induced hypertension, reduced kidney function and led to a significant formation of reactive oxygen species (ROS). Furthermore, genomic damage was markedly increased in this group. All these responses to angiotensin II could be attenuated by concurrent administration of candesartan. In AT1aR-deficient mice treated with angiotensin II, systolic pressure was not increased, and renal function was not affected. However, angiotensin II still led to an increase of ROS in kidneys and hearts of these animals. Additionally, genomic damage in the form of double-strand breaks, was significantly induced in kidneys of AT1aR-deficient mice. Our results show that angiotensin II induced ROS production and DNA damage even without the presence of AT1aR and independently of blood pressure changes.
EVALuna2:25539

An investigation of the diagnostic, predictive, and prognostic impacts of three colonic biopsy grading systems for acute graft versus host disease - Kreft, Andreas; Hippe, Katrin; Wagner-Drouet, Eva Maria; Ries, Isabelle; Kandulski, Arne; Büttner-Herold, Maike; Neumann, Helmut; Weber, Daniela; Holler, Ernst; Schindeldecker, Mario (PLoS ONE, 2021)
Acute graft versus host disease (aGvHD) is an important, life-threatening complication after allogeneic hematopoietic stem cell transplantation (alloHSCT). To investigate the value of multiple simultaneous colon biopsies in improving diagnostic accuracy in patients with aGvHD, we retrospectively analyzed 157 patients after alloHSCT. The biopsies were evaluated individually using three established histological grading systems (Lerner, Sale, and Melson). The maximum, minimum, median, and mean histological aGvHD grades were calculated for each patient, and the results were correlated with the Glucksberg grade of clinical manifestation of GvHD, steroid therapy status, and outcome. We found that multiple colon biopsies enhanced diagnostic sensitivity. Moreover, higher histological grades correlated with steroid therapy initiation and refractoriness; the latter particularly occurred when advanced damage was present in all samples and healthy colon mucosa was reduced or absent. On multivariate analysis, the minimal Lerner and Glucksberg grades for intestinal aGvHD were significantly associated with steroid treatment failure. Ninety-nine patients died. The median survival was 285 days after the biopsies were taken. Fifteen patients died from relapse of their underling disorder and 84 from other causes, mostly infection (53 patients) and GvHD (14 patients). Multivariate analysis revealed a significant association between none-relapse mortality and the mean Lerner grade, minimum Melson grade, Glucksberg organ stage, and platelet counts. Thus, we found the Lerner system to be superior to the other grading methods in most instances and histologic evaluation of multiple simultaneously obtained biopsies from the colon to result in a higher diagnostic yield, which helps plan systemic steroid treatment while predicting treatment response and outcome.
CRIS-Team Scopus Importer:2021-09-10

A noninvasive diagnostic approach to retrospective donor HLA typing in kidney transplant patients using urine - Bach, Christian; Knaup, Karl; Herrmann, Markus; Krumbiegel, Mandy; Pfister, Frederick; Büttner-Herold, Maike; Steffen, Martin; Zecher, Daniel; Lopau, Kai; Schneider, Karen; Dieterle, Anne; Amann, Kerstin Ute; et al. (Transplant International, 2021)
Antibody-mediated rejection (AMR) is a major obstacle to long-term kidney transplantation. AMR is mostly caused by donor specific HLA antibodies, which can arise before or any time after transplantation. Incomplete donor HLA typing and unavailability of donor DNA regularly preclude the assessment of donor-specificity of circulating anti-HLA antibodies. In our centre, this problem arises in approximately 20% of all post-transplant HLA-antibody assessments. We demonstrate that this diagnostic challenge can be resolved by establishing donor renal tubular cell cultures from recipient´s urine as a source of high-quality donor DNA. DNA was then verified for genetic origin and purity by fluorescence in situ hybridization and short tandem repeat analysis. Two representative cases highlight the diagnostic value of this approach which is corroborated by analysis of ten additional patients. The latter were randomly sampled from routine clinical care patients with available donor DNA as controls. In all 12 cases, we were able to perform full HLA typing of the respective donors confirmed by cross-comparison to results from the stored 10 donor DNAs. We propose that this noninvasive diagnostic approach for HLA typing in kidney transplant patients is valuable to determine donor specificity of HLA antibodies, which is important in clinical assessment of suspected AMR.
CRIS-Team Scopus Importer:2021-06-25
Keywords: antibody-mediated rejection; HLA typing; HLA-antibody post-transplantation; rejection

A novel urinary proteomics classifier for non-invasive evaluation of interstitial fibrosis and tubular atrophy in chronic kidney disease - Catanese, Lorenzo; Siwy, Justyna; Mavrogeorgis, Emmanouil; Amann, Kerstin Ute; Mischak, Harald; Beige, Joachim; Rupprecht, Harald (Proteomes, 2021)
Non-invasive urinary peptide biomarkers are able to detect and predict chronic kidney disease (CKD). Moreover, specific urinary peptides enable discrimination of different CKD etiologies and offer an interesting alternative to invasive kidney biopsy, which cannot always be performed. The aim of this study was to define a urinary peptide classifier using mass spectrometry technology to predict the degree of renal interstitial fibrosis and tubular atrophy (IFTA) in CKD patients. The urinary peptide profiles of 435 patients enrolled in this study were analyzed using capillary electrophoresis coupled with mass spectrometry (CE-MS). Urine samples were collected on the day of the diagnostic kidney biopsy. The proteomics data were divided into a training (n = 200) and a test (n = 235) cohort. The fibrosis group was defined as IFTA ≥ 15% and no fibrosis as IFTA < 10%. Statistical comparison of the mass spectrometry data enabled identification of 29 urinary peptides with differential occurrence in samples with and without fibrosis. Several collagen fragments and peptide fragments of fetuinA and others were combined into a peptidomic classifier. The classifier separated fibrosis from non-fibrosis patients in an independent test set (n = 186) with area under the curve (AUC) of 0.84 (95% CI: 0.779 to 0.889). A significant correlation of IFTA and FPP_BH29 scores could be observed Rho = 0.5, p < 0.0001. We identified a peptidomic classifier for renal fibrosis containing 29 peptide fragments corresponding to 13 different proteins. Urinary proteomics analysis can serve as a noninvasive tool to evaluate the degree of renal fibrosis, in contrast to kidney biopsy, which allows repeated measurements during the disease course.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Biomarkers; Fibrosis; IFTA; Peptides; Urine

Anti-BAFF treatment interferes with humoral responses in a model of renal transplantation in rats - Steines, Louisa; Poth, Helen; Schuster, Antonia; Geissler, Edward K.; Amann, Kerstin Ute; Banas, Bernhard; Bergler, Tobias (Transplantation, 2019)
BACKGROUND: B cell activating factor (BAFF) is associated with donor-specific antibodies (DSA) and poorer outcomes after renal transplantation (RTx). We examined the effects of anti-BAFF treatment on B cells, expression of costimulatory molecules and cytokines, germinal centers (GCs) and DSA formation in a RTx model in rats. METHODS: Anti-BAFF antibody was injected on days 3, 17, 31 and 45 after allogeneic RTx. Rats received reduced dose cyclosporine A (CsA) for 28 or 56 days to allow chronic rejection and DSA formation. Leukocytes, B cell subsets and DSA were measured using flow cytometry; expression of cytokines and costimulatory molecules was measured by qRT-PCR, and GCs and T follicular helper (TfH) were assessed using immunohistochemistry. Rejection was evaluated by a nephropathologist. RESULTS: Anti-BAFF treatment reduced the frequency of B cells in allografts and spleen. Naïve B cells were strongly reduced by anti-BAFF treatment in all compartments. mRNA expression of IL-6 and the costimulatory molecules CD40 and ICOS ligand was significantly reduced in anti-BAFF-treated rats. GCs were smaller and plasmablast/plasma cell numbers lower in anti-BAFF-treated rats, which was reflected by less DSA in certain IgG subclasses. CONCLUSIONS: Anti-BAFF treatment interferes with humoral responses at multiple levels in this model of allogeneic RTx.
EVALuna2:205573

A preliminary analysis of renal infiltrating cells in acute tubular injury induced by water treated with high fluoride and high hardness in rat model - Perera, Thanusha; Ranasinghe, Shirani; Alles, Neil; Daniel, Christoph; Waduge, Roshitha (Research Journal of Biotechnology, 2021)
The impact of water containing high fluoride and high hardness on kidneys of rats was investigated. Control and test water sample with high fluoride and hardness were collected from Kandy and Mihinthale regions respectively. Twelve rats were divided into 2 control and 2 test groups. One set of control and test group received normal and test water for 60 days and the other set of control and test group received same water treatment for 90 days. Rats treated with test water for 60 days were observed loss of brush border in less than 25% of tubular cells and in 90 days associated with loss of brush border in more than 25% of tubule cells resulting in acute tubular injury compared to control group. Immunohistochemical staining revealed the strong infiltration of CD3 T-cells and CD68 macrophages in test group for 90 days.
CRIS-Team WoS Importer:2021-04-02

Aprotinin prevents proteolytic epithelial sodium channel (ENaC) activation and volume retention in nephrotic syndrome - Bohnert, Bernhard N.; Menacher, Martina; Janessa, Andrea; Woern, Matthias; Schork, Anja; Daiminger, Sophie; Kalbacher, Hubert; Haering, Hans-Ulrich; Daniel, Christoph; Amann, Kerstin Ute; Sure, Florian; Bertog, Marko; et al. (Kidney International, 2018)
Volume retention in nephrotic syndrome has been linked to activation of the epithelial sodium channel (ENaC) by proteolysis of its ?-subunit following urinary excretion of serine proteases such as plasmin. Here we tested whether pharmacological inhibition of urinary serine protease activity might protect from ENaC activation and volume retention in nephrotic syndrome. Urine from both nephrotic mice (induced by doxorubicin injection) and nephrotic patients exhibited high aprotinin-sensitive serine protease activity. Treatment of nephrotic mice with the serine protease inhibitor aprotinin by means of subcutaneous sustained-release pellets normalized urinary serine protease activity and prevented sodium retention, as did treatment with the ENaC inhibitor amiloride. In the kidney cortex from nephrotic mice, immunofluorescence revealed increased apical ?-ENaC staining, normalized by aprotinin treatment. In Xenopus laevis oocytes heterologously expressing murine ENaC, aprotinin had no direct inhibitory effect on channel activity but prevented proteolytic channel activation. Thus, our study shows that volume retention in experimental nephrotic syndrome is related to proteolytic ENaC activation by proteasuria and can be prevented by treatment with aprotinin. Hence, inhibition of urinary serine protease activity might become a therapeutic approach to treat patients with nephrotic-range proteinuri
EVALuna2:25560

Arginase expression impedes the resolution of intestinal inflammation by altering the fecal microbiome and the metabolome - Baier, Julia; Gänsbauer, Maximilian; Giessler, Claudia; Arnold, Harald; Muske, Mercedes; Schleicher, Ulrike; Lukassen, Sören; Ekici, Arif Bülent; Rauh, Manfred; Daniel, Christoph; Hartmann, Arndt; Schmid, Benjamin; et al. (Journal of Clinical Investigation, 2020)
Arginase 1 (Arg1), which converts L-arginine into ornithine and urea, exerts pleiotropic immunoregulatory effects. However, the function of Arg1 in inflammatory bowel disease (IBD) remains poorly characterized. Here, we found that Arg1 expression correlated with the degree of inflammation in intestinal tissues from IBD patients. In mice, Arg1 was upregulated in an IL-4-/IL-13- and intestinal microbiota-dependent manner. Tie2-Cre+/-Arg1fl/fl mice lacking Arg1 in hematopoietic and endothelial cells recovered faster from experimental colitis than Arg1-expressing littermates. This correlated with decreased vessel density, compositional changes in intestinal microbiota, diminished infiltration by myeloid cells and an accumulation of intraluminal polyamines that promote epithelial healing. The pro-resolving effect of Arg1-deletion was reduced by an L-arginine-free diet, but rescued by simultaneous deletion of other L-arginine-metabolizing enzymes such as Arg2 or Nos2, demonstrating that protection from colitis requires L-arginine. Fecal microbiota transfers from Tie2-Cre+/-Arg1fl/fl mice into wild-type recipients ameliorated intestinal inflammation while transfers from wild-type littermates into Arg1-deficient mice prevented an advanced recovery from colitis. Thus, an increased availability of L-arginine as well as altered intestinal microbiota and metabolic products account for the accelerated resolution from colitis in the absence of Arg1. Consequently, the metabolism of L-arginine may serve as target for clinical intervention in IBD patients.<br

Artificial intelligence in kidney transplant pathology Künstliche Intelligenz in der Nierentransplantationspathologie - Bülow, Roman David; Lan, Yu Chia; Amann, Kerstin Ute; Boor, Peter (Die Pathologie, 2024)
Background: Artificial intelligence (AI) systems have showed promising results in digital pathology, including digital nephropathology and specifically also kidney transplant pathology. Aim: Summarize the current state of research and limitations in the field of AI in kidney transplant pathology diagnostics and provide a future outlook. Materials and methods: Literature search in PubMed and Web of Science using the search terms “deep learning”, “transplant”, and “kidney”. Based on these results and studies cited in the identified literature, a selection was made of studies that have a histopathological focus and use AI to improve kidney transplant diagnostics. Results and Conclusion: Many studies have already made important contributions, particularly to the automation of the quantification of some histopathological lesions in nephropathology. This likely can be extended to automatically quantify all relevant lesions for a kidney transplant, such as Banff lesions. Important limitations and challenges exist in the collection of representative data sets and the updates of Banff classification, making large-scale studies challenging. The already positive study results make future AI support in kidney transplant pathology appear likely.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Computer assistance; Datenintegration; Deep learning; Histomorphometry; Kidney transplantation

Assessment and Risk Prediction of Chronic Kidney Disease and Kidney Fibrosis Using Non-Invasive Biomarkers. - Rupprecht, Harald; Catanese, Lorenzo; Amann, Kerstin Ute; Hengel, Felicitas E.; Huber, Tobias B.; Latosinska, Agnieszka; Lindenmeyer, Maja T.; Mischak, Harald; Siwy, Justyna; Wendt, Ralph; Beige, Joachim (International Journal of Molecular Sciences, 2024)
Effective management of chronic kidney disease (CKD), a major health problem worldwide, requires accurate and timely diagnosis, prognosis of progression, assessment of therapeutic efficacy, and, ideally, prediction of drug response. Multiple biomarkers and algorithms for evaluating specific aspects of CKD have been proposed in the literature, many of which are based on a small number of samples. Based on the evidence presented in relevant studies, a comprehensive overview of the different biomarkers applicable for clinical implementation is lacking. This review aims to compile information on the non-invasive diagnostic, prognostic, and predictive biomarkers currently available for the management of CKD and provide guidance on the application of these biomarkers. We specifically focus on biomarkers that have demonstrated added value in prospective studies or those based on prospectively collected samples including at least 100 subjects. Published data demonstrate that several valid non-invasive biomarkers of potential value in the management of CKD are currently available.
EVALuna2:566232

Assessment of myocardial fibrosis in patients with systemic sclerosis using [Ga-68]Ga-FAPI-04-PET-CT - Treutlein, Christoph; Distler, Jörg; Tascilar, Koray; Chenguiti Fakhouri, Sara; Györfi, Andrea-Hermina; Atzinger, Armin; Matei, Alexandru-Emil; Dees, Clara; Büttner-Herold, Maike; Kuwert, Torsten; Prante, Olaf; Bäuerle, Tobias; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2022)
Purpose Myocardial fibrosis (MF) is a factor of poor prognosis in systemic sclerosis (SSc). Direct in-vivo visualization of fibroblast activation as early readout of MF has not been feasible to date. Here, we characterize (68)Gallium-labeled-Fibroblast-Activation-Inhibitor-04 ([Ga-68]Ga-FAPI-04)-PET-CT as a diagnostic tool in SSc-related MF.Methods In this proof-of-concept trial, six SSc patients with and eight without MF of the EUSTAR cohort Erlangen underwent [Ga-68]Ga-FAPI-04-PET-CT and cardiac MRI (cMRI) and clinical and serologic investigations just before baseline and during follow-up between January 2020 and December 2020. Myocardial biopsy was performed as clinically indicated.Results [Ga-68]Ga-FAPI-04 tracer uptake was increased in SSc-related MF with higher uptake in SSc patients with arrhythmias, elevated serum-NT-pro-BNP, and increased late gadolinium enhancement (LGE) in cMRI. Histologically, myocardial biopsies from cMRI- and [Ga-68]Ga-FAPI-04-positive regions confirmed the accumulation of FAP(+) fibroblasts surrounded by collagen deposits. We observed similar but not equal spatial distributions of [Ga-68]Ga-FAPI-04 uptake and quantitative cMRI-based techniques. Using sequential [Ga-68]Ga-FAPI-04-PET-CTs, we observed dynamic changes of [Ga-68]Ga-FAPI-04 uptake associated with changes in the activity of SSc-related MF, while cMRI parameters remained stable after regression of molecular activity and rather indicated tissue damage.Conclusions We present first in-human evidence that [Ga-68]Ga-FAPI-04 uptake visualizes fibroblast activation in SSc-related MF and may be a diagnostic option to monitor cardiac fibroblast activity in situ.
CRIS-Team WoS Importer:2023-02-10

Association of Blood Donor-derived Cell-free DNA Levels with Banff Scores and Histopathological Lesions in Kidney Allograft Biopsies: Results from an Observational Study - Akifova, Aylin; Budde, Klemens; Choi, Mira; Amann, Kerstin Ute; Büttner-Herold, Maike; Oellerich, Michael; Beck, Julia; Bornemann-Kolatzki, Kirsten; Schütz, Ekkehard; Bachmann, Friederike; Halleck, Fabian; Schrezenmeier, Eva V.; et al. (Transplantation Direct, 2025)
Background. Donor-derived cell-free DNA (dd-cfDNA) is an emerging biomarker of kidney allograft injury, mainly investigated in the context of rejection. However, the dd-cfDNA dynamics in other graft pathologies merit further investigation. Methods. In this single-center observational study, we prospectively collected dd-cfDNA at indication biopsies. To evaluate the association between dd-cfDNA and different histological patterns, we correlated absolute and relative dd-cfDNA (thresholds of 50 copies/mL and 0.5%, respectively) with the Banff 2022 lesion scores and the assigned diagnoses. Results. We examined 151 dd-cfDNA paired biopsies in 131 kidney transplant recipients and found significantly higher absolute dd-cfDNA levels in antibody-mediated rejection (n, median, IQR: 45, 63 copies/mL, 42-89), microvascular inflammation (MVI) without donor-specific antibodies or C4d-deposition (6, 102 copies/mL, 61-134), mixed rejection (8, 140 copies/mL, 77-171), and BK virus-Associated nephropathy (6, 213 copies/mL, 83-298) compared with glomerulonephritis (20, 12 copies/mL, 8-18), calcineurin toxicity (19, 10 copies/mL, 7-16), interstitial fibrosis/tubular atrophy (12, 10 copies/mL, 9-16) and normal histology (6, 9 copies/mL, 7-16). In the multivariable analysis, absolute and relative dd-cfDNA correlated with the peritubular capillaritis (ptc), glomerulitis (g), and tubulitis (t) scores. In the receiver operating characteristic analysis, absolute dd-cfDNA showed best discrimination for MVI of any cause (area under the curve [AUC] 0.88, sensitivity 0.71, specificity 0.86, positive predictive value [PPV] 0.76, negative predictive value [NPV] 0.82), followed by antibody-mediated rejection including mixed rejection (AUC 0.85, sensitivity 0.72, specificity 0.83, PPV 0.69, NPV 0.84), and overall rejection (AUC 0.83, sensitivity 0.66, specificity 0.85, PPV 0.76, NPV 0.77). T cell-mediated rejection was only detectable by dd-cfDNA when associated with vascular lesions. Conclusions. Altogether, we conclude that dd-cfDNA-release is not limited to rejection-related injury phenotypes and is mainly driven by MVI in kidney allografts.
CRIS-Team Scopus Importer:2025-05-02

Association of donor hypertension and recipient renal function in living donor kidney transplantation: A single-center retrospective study - Dienemann, Thomas; Schellenberg, Jana; Heller, Katharina; Daniel, Christoph; Amann, Kerstin Ute; Hilgers, Karl Friedrich; Schiffer, Mario; Weidemann, Alexander (Clinical Transplantation, 2019)
Transplant centers now accept living donors with well-controlled hypertension. Little is known whether hypertension in living donors affects recipient's kidney function. We aimed to examine potential differences in kidneys from hypertensive donors compared to normotensive donors with respect to renal function over 36 months and histologic findings at transplantation (T0) and 12 months after transplantation (T1). Retrospective single-center analysis of 174 living donor-recipient pairs (age > 18; transplantation date 1/2008-3/2016). Hypertension in donors was defined as being on antihypertensive medication. All biopsies were assessed by the same blinded, experienced renal pathologist. Biopsies were scored for glomerulosclerosis, IFTA, and arteriosclerosis. Regression models were used to examine the relationship of donor hypertension with renal function and histologic changes. Hypertensive donors were significantly older than normotensive donors. Chronic changes such as tubular atrophy and atherosclerosis were more evident in kidneys from hypertensive donors at T0 as well as T1. Donor hypertension was independently associated with histologic changes at T0 and T1 but not with renal function over the follow period. Despite more pronounced histologic changes in kidneys from hypertensive living donors, these grafts exhibited a similar functional outcome. However, they subsequently might be at a greater risk and warrant thorough follow-up care.
CRIS-Team WoS Importer:2019-09-27

Associations of TACSTD2/TROP2 and NECTIN-4/NECTIN-4 with molecular subtypes, PD-L1 expression, and FGFR3 mutational status in two advanced urothelial bladder cancer cohorts - Bahlinger, Veronika; Branz, Annalena; Strissel, Pamela; Strick, Reiner; Lange, Fabienne; Geppert, Carol-Immanuel; Klümper, Niklas; Hölzel, Michael; Wach, Sven; Taubert, Helge; Sikic, Danijel; Wullich, Bernd; et al. (Histopathology, 2024)
Aims: Treatment options for advanced urothelial carcinoma (aUC) rapidly evolved: besides immunomodulative therapeutic options and inhibitors targeting Fibroblast growth factor receptor (FGFR) alterations, two new antibody-drug conjugates (ADC), sacituzumab govitecan (SG) and enfortumab vedotin (EV), have been approved. However, little is known about the associations of specific aUC properties and the surface target expression of TROP2 and NECTIN-4. Our aim was to characterize associations of TACSTD2/TROP2 and NECTIN-4/NECTIN-4 protein and gene expression with morphomolecular and clinicopathological characteristics of aUC in two large independent cohorts. Methods and results: The TCGA BLCA (n = 405) and the CCC-EMN (n = 247) cohorts were retrospectively analysed. TROP2/TACSTD2 and NECTIN-4/NECTIN-4 are highly expressed at the protein and transcript level in aUC, and their expression status did not correlate with patient survival in both cohorts. NECTIN-4/NECTIN-4 expression was higher in luminal tumours and reduced in squamous aUCs. NECTIN-4 was negative in 10.6% of samples, and 18.4% of samples had low expression (H-score <15). The TROP2 negativity rate amounted to 6.5%. TACSTD2 and NECTIN-4 expression was reduced in neuroendocrine-like and/or protein-based double-negative tumours. TROP2- and NECTIN-4-negative tumours included one sarcomatoid and four neuroendocrine aUC. FGFR3 alterations and PD-L1 expression on tumour and immune cells did not associate with TROP2 or NECTIN-4 expression. Conclusions: TACSTD2/TROP2 and NECTIN-4/NECTIN-4 are widely expressed in aUC, independent of FGFR3 alterations or PD-L1 expression, thus representing a suitable target for ADC treatment in the majority of aUC. The expression loss was associated with aggressive morphomolecular aUC subtypes, i.e. neuroendocrine(-like) and sarcomatoid aUC.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Advanced urothelial carcinoma; membranous expression; NECTIN-4/NECTIN-4; TACSTD2/TROP2; treatment options

ATF2 loss promotes tumor invasion in colorectal cancer cells via upregulation of cancer driver TROP2 - Hübner, Kerstin; Erlenbach-Wünsch, Katharina; Prochazka, Jan; Sheraj, Ilir; Hampel, Chuanpit; Mrazkova, Blanka; Michalcikova, Tereza; Tureckova, Jolana; Iatsiuk, Veronika; Weissmann, Anne; Ferrazzi, Fulvia; Kunze, Philipp; et al. (Cellular and Molecular Life Sciences, 2022)
In cancer, the activating transcription factor 2 (ATF2) has pleiotropic functions in cellular responses to growth stimuli, damage, or inflammation. Due to only limited studies, the significance of ATF2 in colorectal cancer (CRC) is not well understood. We report that low ATF2 levels correlated with worse prognosis and tumor aggressiveness in CRC patients. NanoString gene expression and ChIP analysis confirmed trophoblast cell surface antigen 2 (TROP2) as a novel inhibitory ATF2 target gene. This inverse correlation was further observed in primary human tumor tissues. Immunostainings revealed that high intratumoral heterogeneity for ATF2 and TROP2 expression was sustained also in liver metastasis. Mechanistically, our in vitro data of CRISPR/Cas9-generated ATF2 knockout (KO) clones revealed that high TROP2 levels were critical for cell de-adhesion and increased cell migration without triggering EMT. TROP2 was enriched in filopodia and displaced Paxillin from adherens junctions. In vivo imaging, micro-computer tomography, and immunostainings verified that an ATF2(KO)/TROP2(high) status triggered tumor invasiveness in in vivo mouse and chicken xenograft models. In silico analysis provided direct support that ATF2(low)/TROP2(high) expression status defined high-risk CRC patients. Finally, our data demonstrate that ATF2 acts as a tumor suppressor by inhibiting the cancer driver TROP2. Therapeutic TROP2 targeting might prevent particularly the first steps in metastasis, i.e., the de-adhesion and invasion of colon cancer cells.
CRIS-Team WoS Importer:2022-07-29

AT II Receptor Blockade and Renal Denervation: Different Interventions with Comparable Renal Effects? - Rodionova, Kristina; Hindermann, Martin; Hilgers, Karl Friedrich; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Ditting, Tilmann (Kidney & Blood Pressure Research, 2021)
Background: Angiotensin II (Ang II) and the renal sympathetic nervous system exert a strong influence on renal sodium and water excretion. We tested the hypothesis that already low doses of an Ang II inhibitor (candesartan) will result in similar effects on tubular sodium and water reabsorption in congestive heart failure (CHF) as seen after renal denervation (DNX). Methods: Measurement of arterial blood pressure, heart rate (HR), renal sympathetic nerve activity (RSNA), glomerular filtration rate (GFR), renal plasma flow (RPF), urine volume, and urinary sodium. To assess neural control of volume homeostasis, 21 days after the induction of CHF via myocardial infarction rats underwent volume expansion (0.9% NaCL; 10% body weight) to decrease RSNA. CHF rat and controls with or without DNX or pretreated with the Ang II type-1 receptor antagonist candesartan (0.5 ug i.v.) were studied. Results: CHF rats excreted only 68 + 10.2% of the volume load (10% body weight) in 90 min. CHF rats pretreated with candesartan or after DNX excreted from 92 to 103% like controls. Decreases of RSNA induced by volume expansion were impaired in CHF rats but unaffected by candesartan pointing to an intrarenal drug effect. GFR and RPF were not significantly different in controls or CHF. Conclusion: The prominent function of increased RSNA - retaining salt and water - could no longer be observed after renal Ang II receptor blockade in CHF rats.
CRIS-Team WoS Importer:2021-06-11
Keywords: Renal sympathetic innervation; Angiotensin II; Congestive heart failure; Renal nerve ablation; Renal function

A TNFR2-Specific TNF Fusion Protein With Improved In Vivo Activity - Vargas, Juan Gamboa; Wagner, Jennifer; Shaikh, Haroon; Lang, Isabell; Medler, Juliane; Anany, Mohamed; Steinfatt, Tim; Mosca, Josefina Pena; Haack, Stephanie; Dahlhoff, Julia; Büttner-Herold, Maike; Graf, Carolin; et al. (Frontiers in Immunology, 2022)
Tumor necrosis factor (TNF) receptor-2 (TNFR2) has attracted considerable interest as a target for immunotherapy. Indeed, using oligomeric fusion proteins of single chain-encoded TNFR2-specific TNF mutants (scTNF80), expansion of regulatory T cells and therapeutic activity could be demonstrated in various autoinflammatory diseases, including graft-versus-host disease (GvHD), experimental autoimmune encephalomyelitis (EAE) and collagen-induced arthritis (CIA). With the aim to improve the in vivo availability of TNFR2-specific TNF fusion proteins, we used here the neonatal Fc receptor (FcRn)-interacting IgG1 molecule as an oligomerizing building block and generated a new TNFR2 agonist with improved serum retention and superior in vivo activity. MethodsSingle-chain encoded murine TNF80 trimers (sc(mu)TNF80) were fused to the C-terminus of an in mice irrelevant IgG1 molecule carrying the N297A mutation which avoids/minimizes interaction with Fc gamma-receptors (Fc gamma Rs). The fusion protein obtained (irrIgG1(N297A)-sc(mu)TNF80), termed NewSTAR2 (New selective TNF-based agonist of TNF receptor 2), was analyzed with respect to activity, productivity, serum retention and in vitro and in vivo activity. STAR2 (TNC-sc(mu)TNF80 or selective TNF-based agonist of TNF receptor 2), a well-established highly active nonameric TNFR2-specific variant, served as benchmark. NewSTAR2 was assessed in various in vitro and in vivo systems. ResultsSTAR2 (TNC-sc(mu)TNF80) and NewSTAR2 (irrIgG1(N297A)-sc(mu)TNF80) revealed comparable in vitro activity. The novel domain architecture of NewSTAR2 significantly improved serum retention compared to STAR2, which correlated with efficient binding to FcRn. A single injection of NewSTAR2 enhanced regulatory T cell (Treg) suppressive activity and increased Treg numbers by > 300% in vivo 5 days after treatment. Treg numbers remained as high as 200% for about 10 days. Furthermore, a single in vivo treatment with NewSTAR2 upregulated the adenosine-regulating ectoenzyme CD39 and other activation markers on Tregs. TNFR2-stimulated Tregs proved to be more suppressive than unstimulated Tregs, reducing conventional T cell (Tcon) proliferation and expression of activation markers in vitro. Finally, singular preemptive NewSTAR2 administration five days before allogeneic hematopoietic cell transplantation (allo-HCT) protected mice from acute GvHD. ConclusionsNewSTAR2 represents a next generation ligand-based TNFR2 agonist, which is efficiently produced, exhibits improved pharmacokinetic properties and high serum retention with superior in vivo activity exerting powerful protective effects against acute GvHD.
CRIS-Team WoS Importer:2022-07-08

Author Correction: Non-professional phagocytosis: a general feature of normal tissue cells (Scientific Reports, (2019), 9, 1, (11875), 10.1038/s41598-019-48370-3) - Seeberg, Jacob; Loibl, Monika; Moser, Fabian; Schwegler, Manuela; Büttner-Herold, Maike; Daniel, Christoph; Engel, Felix; Hartmann, Arndt; Schlötzer-Schrehardt, Ursula; Goppelt-Strübe, Margarete; Schellerer, Vera; Naschberger, Elisabeth; et al. (Scientific Reports, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.
CRIS-Team Scopus Importer:2020-06-16

Author Correction: Novel diagnostic and therapeutic techniques reveal changed metabolic profiles in recurrent focal segmental glomerulosclerosis (Scientific Reports, (2021), 11, 1, (4577), 10.1038/s41598-021-83883-w) - Müller-Deile, Janina; Sarau, George; Kotb, Ahmed M.; Jaremenko, Christian; Rolle-Kampczyk, Ulrike E.; Daniel, Christoph; Kalkhof, Stefan; Christiansen, Silke H.; Schiffer, Mario (Scientific Reports, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.
CRIS-Team Scopus Importer:2021-06-04

A VERSATILE MODEL OF CARDIAC TISSUE FROM HIPSC-DERIVED CARDIOMYOCYTES WITHIN PERICARDIAL MATRIX HYDROGELS DOPED WITH HYDRAZIDE FUNCTIONALIZED MWCNTS FOR PHARMACEUTICAL SCREENING AND TISSUE ENGINEERING APPLICATIONS - Roshanbinfar, Kaveh; Oommen, Oommen Podiyan; Hilborn, Jons; Engel, Felix (TISSUE ENGINEERING PART A, 2022)
CRIS-Team WoS Importer:2022-08-12

Banff 2022 pancreas transplantation multidisciplinary report: Refinement of guidelines for T cell–mediated rejection, antibody-mediated rejection and islet pathology. Assessment of duodenal cuff biopsies and noninvasive diagnostic methods - Drachenberg, Cinthia B.; Büttner-Herold, Maike; Aguiar, Pedro Ventura; Horsfield, Catherine; Mikhailov, Alexei V.; Papadimitriou, John C.; Seshan, Surya V.; Perosa, Marcelo; Boggi, Ugo; Uva, Pablo; Rickels, Michael; Grzyb, Krzyztof; et al. (American Journal of Transplantation, 2024)
The Banff pancreas working schema for diagnosis and grading of rejection is widely used for treatment guidance and risk stratification in centers that perform pancreas allograft biopsies. Since the last update, various studies have provided additional insight regarding the application of the schema and enhanced our understanding of additional clinicopathologic entities. This update aims to clarify terminology and lesion description for T cell–mediated and antibody-mediated allograft rejections, in both active and chronic forms. In addition, morphologic and immunohistochemical tools are described to help distinguish rejection from nonrejection pathologies. For the first time, a clinicopathologic approach to islet pathology in the early and late posttransplant periods is discussed. This update also includes a discussion and recommendations on the utilization of endoscopic duodenal donor cuff biopsies as surrogates for pancreas biopsies in various clinical settings. Finally, an analysis and recommendations on the use of donor-derived cell-free DNA for monitoring pancreas graft recipients are provided. This multidisciplinary effort assesses the current role of pancreas allograft biopsies and offers practical guidelines that can be helpful to pancreas transplant practitioners as well as experienced pathologists and pathologists in training.
CRIS-Team Scopus Importer:2024-03-15
Keywords: acute T cell–mediated rejection; antibody-mediated rejection; donor-specific antibody; mixed rejection; pancreas after kidney transplant; percutaneous pancreas biopsy; simultaneous pancreas kidney transplant; solitary pancreas transplant; whole pancreas transplantation

Basic nephropathology for pathologists—part 1: Kidney biopsy—inflammation and immune complexes Grundlagen der Nierenpathologie für Pathologen – Teil 1: Nierenbiopsie – Inflammation und Immunkomplexe - Büttner-Herold, Maike; Gaspert, Ariana; Amann, Kerstin Ute (Pathologe, 2022)
The assessment of kidney biopsies is mainly confined to specialized centres. However, sometimes a kidney biopsy is submitted to a general pathologist, and in addition peritumorous renal parenchyma in tumour nephrectomies can have concomitant non-neoplastic renal disease. Here we present a survey of inflammatory and immunologic changes in all renal compartments, which may in part indicate the need of prompt therapeutic intervention such as in vasculitis, glomerulonephritis and interstitial nephritis. It is important to take into account that renal involvement of vasculitis is mainly centred in glomeruli and only to a much lesser extent in arteries, and that the frequently observed interstitial inflammation very often is an epiphenomenon of another primary kidney disease and not an independent disease process. Typical renal patterns of injury are emphasised.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Biopsy; Differential diagnosis; Immune complexes; Inflammation; Microscopy

Batf-dependent Th17 cells critically regulate IL-23 driven colitis-associated colon cancer - Punkenburg, Elise; Vogler, Tina; Büttner, Maike; Amann, Kerstin Ute; Waldner, Maximilian; Atreya, Raja; Abendroth, Benjamin; Mudter, Jonas; Merkel, Susanne; Gallmeier, Eike; Rose-John, Stefan; Neurath, Markus; et al. (Gut, 2016)
IBDs have an increased risk for development of colorectal cancer (CRC). Here, we aimed at the characterisation of the functional role of Th17-associated transcription factors in sporadic and colitis-associated colon cancer in vivo.We used mice deficient or transgenic for the activating protein 1 family member basic leucine zipper transcription factor ATF-like (Batf) to evaluate the role of Th17 cells during sporadic and inflammation-induced colon carcinogenesis. We also studied the expression of Batf and ROR?t in patients with IBD and CRC.Batf but not retinoic acid-related orphan receptor ?t(ROR?t) expression was significantly increased together with interleukin (IL) 23 expression in UC but not in Crohn's disease (CD) tissue samples. In CRC also Batf but not ROR?t expression was increased and its expression correlated with the IL-23 and IL-23 receptor (IL-23R) expression. Finally, Batf but not ROR?t was coexpressed with IL-17a, IL-23R and IL-6 within CRC-infiltrating CD4(+) T cells. Functional studies in mice revealed that Batf-dependent T cells are crucial regulators of sporadic and inflammation-induced CRC. Colitis-associated Batf(-/-) tumours lacked IL-17a(+)IL-23R(+)IL-6(+)CD4(+) T cells, hence displaying characteristics reminiscent of human CRC-infiltrating CD4(+) T cells. Strikingly, Batf(-/-) tumours contained low IL-23 but high IL-17a expression levels. Tumour formation and intratumoral IL-23 expression could be restored by administration of Hyper-IL-6 consisting of IL-6 and soluble IL-6 receptor.Batf-dependent IL-23R(+)IL-6(+)CD4(+) Th17 cells critically control IL-23 driven colitis-associated tumour formation and the progression of sporadic colon tumours. Batf-dependent IL-23R(+) T cells represent a potential future therapeutic target limiting CRC progression.
EVALuna2:2026

BDNF: mRNA expression in urine cells of patients with chronic kidney disease and its role in kidney function - Endlich, Nicole; Lange, Tim; Kuhn, Jana; Klemm, Paul; Kotb, Ahmed M.; Siegerist, Florian; Kindt, Frances; Lindenmeyer, Maja T.; Cohen, Clemens D.; Kuss, Andreas W.; Nath, Neetika; Rettig, Rainer; et al. (Journal of Cellular and Molecular Medicine, 2018)
Podocyte loss and changes to the complex morphology are major causes of chronic kidney disease (CKD). As the incidence is continuously increasing over the last decades without sufficient treatment, it is important to find predicting biomarkers. Therefore, we measured urinary mRNA levels of podocyte genes NPHS1, NPHS2, PODXL and BDNF, KIM-1, CTSL by qRT-PCR of 120 CKD patients. We showed a strong correlation between BDNF and the kidney injury marker KIM-1, which were also correlated with NPHS1, suggesting podocytes as a contributing source. In human biopsies, BDNF was localized in the cell body and major processes of podocytes. In glomeruli of diabetic nephropathy patients, we found a strong BDNF signal in the remaining podocytes. An inhibition of the BDNF receptor TrkB resulted in enhanced podocyte dedifferentiation. The knockdown of the orthologue resulted in pericardial oedema formation and lowered viability of zebrafish larvae. We found an enlarged Bowman's space, dilated glomerular capillaries, podocyte loss and an impaired glomerular filtration. We demonstrated that BDNF is essential for glomerular development, morphology and function and the expression of BDNF and KIM-1 is highly correlated in urine cells of CKD patients. Therefore, BDNF mRNA in urine cells could serve as a potential CKD biomarker.
EVALuna2:156717

beta(2)-m - a Trigger for NLRP3 Inflammasome Activation within Macrophages Promoting Multiple Myeloma Cell Proliferation - Hofbauer, Daniel; Mougiakakos, Dimitrios; Büttner-Herold, Maike; Neumann, Frank; Nolting, Jens; Bisht, Savita; Zeiser, Robert; Hamarsheh, Shaima'A; Ricagno, Stefano; Zaiss, Mario; Eberhardt, Martin; Böttcher, Martin; et al. (BLOOD, 2019)
CRIS-Team WoS Importer:2021-10-18

Biallelic ANKS6 mutations cause late-onset ciliopathy with chronic kidney disease through YAP dysregulation - Schwarz, Hannah; Popp, Bernt; Airik, Rannar; Torabi Sarijalo, Nasrin; Knaup, Karl; Stoeckert, Johanna; Wiech, Thorsten; Amann, Kerstin Ute; Wiesmann da Silva Reis, André; Schiffer, Mario; Schueler, Markus; Wiesener, Michael (Human Molecular Genetics, 2022)
Nephronophthisis-related ciliopathies (NPHP-RC) comprises a group of inherited kidney diseases, caused by mutations in genes encoding proteins localizing to primary cilia. NPHP-RC represents one of the most frequent monogenic causes of renal failure within the first three decades of life, but its molecular disease mechanisms remain unclear. Here, we identified biallelic ANKS6 mutations in two affected siblings with late-onset chronic kidney disease by whole-exome sequencing. We employed patient-derived fibroblasts generating an in vitro model to study the precise biological impact of distinct human ANKS6 mutations, completed by immunohistochemistry studies on renal biopsy samples. Functional studies using patient-derived cells showed an impaired integrity of the ciliary inversin compartment with reduced cilia length. Further analyses demonstrated that ANKS6 deficiency leads to a dysregulation of Hippo-signaling through nuclear yes-associated protein (YAP) imbalance and disrupted ciliary localization of YAP. In addition, an altered transcriptional activity of canonical Wnt target genes and altered expression of non-phosphorylated (active) beta-catenin and phosphorylated glycogen synthase kinase 3 beta were observed. Upon ciliation, ANKS6 deficiency revealed a deranged subcellular localization and expression of components of the endocytic recycling compartment. Our results demonstrate that ANKS6 plays a key role in regulating the Hippo pathway, and ANKS6 deficiency is linked to dysregulation of signaling pathways. Our study provides molecular clues in understanding pathophysiological mechanisms of NPHP-RC and may offer new therapeutic targets.
CRIS-Team WoS Importer:2022-05-13

Biallelic Expression of Mucin-1 in Autosomal Dominant Tubulointerstitial Kidney Disease: Implications for Nongenetic Disease Recognition - Knaup, Karl; Hackenbeck, Thomas; Popp, Bernt; Stoeckert, Johanna; Wenzel, Andrea; Büttner-Herold, Maike; Pfister, Frederick; Schüler, Markus; Seven, Didem; May, Annette M.; Halbritter, Jan; Gröne, Hermann Josef; et al. (Journal of the American Society of Nephrology, 2018)
BACKGROUND: Providing the correct diagnosis for patients with tubulointerstitial kidney disease and secondary degenerative disorders, such as hypertension, remains a challenge. The autosomal dominant tubulointerstitial kidney disease (ADTKD) subtype caused by MUC1 mutations (ADTKD-MUC1) is particularly difficult to diagnose, because the mutational hotspot is a complex repeat domain, inaccessible with routine sequencing techniques. Here, we further evaluated SNaPshot minisequencing as a technique for diagnosing ADTKD-MUC1 and assessed immunodetection of the disease-associated mucin 1 frameshift protein (MUC1-fs) as a nongenetic technique. METHODS: We re-evaluated detection of MUC1 mutations by targeted repeat enrichment and SNaPshot minisequencing by haplotype reconstruction via microsatellite analysis in three independent ADTKD-MUC1 families. Additionally, we generated rabbit polyclonal antibodies against MUC1-fs and evaluated immunodetection of wild-type and mutated allele products in human kidney biopsy specimens. RESULTS: The detection of MUC1 mutations by SNaPshot minisequencing was robust. Immunostaining with our MUC1-fs antibodies and an MUC1 antibody showed that both proteins are readily detectable in human ADTKD-MUC1 kidneys, with mucin 1 localized to the apical membrane and MUC1-fs abundantly distributed throughout the cytoplasm. Notably, immunohistochemical analysis of MUC1-fs expression in clinical kidney samples facilitated reliable prediction of the disease status of individual patients. CONCLUSIONS: Diagnosing ADTKD-MUC1 by molecular genetics is possible, but it is technically demanding and labor intensive. However, immunohistochemistry on kidney biopsy specimens is feasible for nongenetic diagnosis of ADTKD-MUC1 and therefore, a valid method to select families for further diagnostics. Our data are compatible with the hypothesis that specific molecular effects of MUC1-fs underlie the pathogenesis of this disease.
EVALuna2:34428

Bi-nucleation of podocytes is uniformly accompanied by foot processes widening in renal disease - Muehldorfer, Johanna; Pfister, Eva; Buettner-Herold, Maike; Klewer, Monika; Amann, Kerstin Ute; Daniel, Christoph (Nephrology Dialysis Transplantation, 2017)
Podocytes are terminally differentiated glomerular cells expressing a highly complex architecture and lacking the ability to proliferate. However, during renal injury or stress these cells can re-enter into the cell cycle but fail to divide. As a consequence, bi- and multi-nucleated podocytes can be identified in renal biopsies from patients with various kidney diseases. It is still unclear whether the occurrence of such cells is dependent on or correlates with renal damage and if bi- or multi-nucleation results in ultrastructural alterations such as e.g. foot process effacement. Therefore, we investigated the frequency, correlation with clinical parameters and morphological consequences of podocyte bi- or multi-nucleation in a cohort of 377 patients suffering from different renal diseases.Renal biopsies from patients with minimal change disease (MCD; n = 93), IgA-glomerulonephritis (IgA-GN, n = 95), lupus nephritis (LN; n = 90) and diabetic nephropathy (DN; n = 99) were investigated for the occurrence of bi-nucleated or multi-nucleated podocytes using semi-thin sections and light-microscopy at 1000× magnification. The frequency of bi-nucleation and multi-nucleation in podocytes was correlated with clinical parameters and markers of renal injury. In addition, ultrastructural morphological features associated with podocyte bi- or multi-nucleation were analysed by scanning transmission electron microscopy at various magnifications.Ultrastructural analysis of podocyte nuclear morphology revealed a broad spectrum of nuclear appearances. Therefore, podocytes were classified in cells with mono-nucleated, lobulated, potential bi-nucleated, symmetrically bi-nucleated, asymmetrically bi-nucleated and multi-nucleated nuclear morphology. In 65-80% of all investigated glomeruli only mono-nuclear podocytes were identified. The highest frequency of bi-nucleated podocytes was found in patients with IgA-GN (18.6%) and the lowest in patients with DN (5.6%). The proportion of bi-nucleated podocytes with asymmetric nuclear morphology was about 50% of all bi-nucleated podocytes and independent of the underlying renal disease. In addition, ultrastructural analysis by electron microscopy showed significant widening of foot processes in bi-nucleated compared with mono-nucleated podocytes. Interestingly, foot process width of podocytes with lobulated nuclei was also significantly increased compared with podocytes with normal mono-nuclear morphology. Furthermore, podocyte density per glomerular area was significantly lower in glomeruli with bi-nucleated podocytes. Due to the relatively low frequency of bi- and multi-nucleated podocytes, correlations with clinical parameters were weak and dependent on renal disease.The frequency of bi-nucleated podocytes was highest in IgA-GN but can also be observed in all investigated renal diseases. In podocytes with altered nuclear morphology particularly in bi- and multi-nucleated podocytes ultrastructural analysis of podocytes revealed significant widening of foot processes as a potential maladaptive structural consequence.
EVALuna2:25559

BIOHYBRID HYDROGEL WITH ENHANCED ELECTROCONDUCTIVITY ADVANCES MATURATION OF HIPSC-DERIVED CARDIOMYOCYTES - Roshanbinfar, Kaveh; Engel, Felix (TISSUE ENGINEERING PART A, 2022)
CRIS-Team WoS Importer:2022-08-12

Biomimetic Organic-Inorganic Nanocomposite Scaffolds to Regenerate Cranial Bone Defects in a Rat Animal Model - Moosavifar, Mirjavad; Parsaei, Houman; Hosseini, Seyedjamal; Mirmontazeri, Seyed Mohammad; Ahadi, Reza; Ahadian, Samad; Engel, Felix; Roshanbinfar, Kaveh (ACS Biomaterials Science and Engineering, 2022)
While bone regenerates itself after an injury, a critical bone defect requires external interventions. Engineering approaches to restore bone provide a temporary scaffold to support the damage and provide beneficial biological cues for bone repair. Biomimetically generated scaffolds replicate the naturally occurring phenomena in bone regeneration. In this study, a gelatin-calcium phosphate nanocomposite was synthesized by an efficient and cost-effective double-diffusion biomimetic approach. Calcium and phosphate ions are impregnated in the gelatin, mimicking the natural bone mineralization process. Glutaraldehyde from 0.5 to 2 w/v% was used for gelatin cross-linking and mechanical properties of the scaffold, and its biological support for rat bone marrow mesenchymal stromal cells was analyzed. Analysis of scanning electron microscopy images of the nanocomposite scaffolds and Fourier transform infrared (FTIR) and X-ray diffraction (XRD) characterizations of these scaffolds confirmed precipitation of calcium phosphates in the gelatin. Moreover, lysozyme degradation assay showed that scaffold degradation reversely correlates with the concentration of the cross-linking agent. Increased glutaraldehyde concentrations enhanced the mechanical properties of the scaffolds, bringing them closer to those of cancellous bone. Rat bone marrow mesenchymal stromal cells maintained their viability on these scaffolds compared to standard cell culture plates. In addition, these cells showed differentiation into bone lineage as evaluated from alkaline phosphatase activity up to 21 days and Alizarin red staining of the cells over 28 days. Eventually, scaffolds were implanted in a cranial defect in a rat animal model with a 5 mm diameter. Bone regeneration was studied over 90 days. Analysis of histological sections of the injury and computer tomography images revealed that nanocomposite scaffolds cross-linked with 1% w/v glutaraldehyde provide the maximum bone regeneration after 90 days. Collectively, our data show that nanocomposite scaffolds developed here provide effective regeneration for extensive bone defects in vivo.
CRIS-Team Scopus Importer:2022-04-15
Keywords: biomimetic scaffold; bone tissue engineering; gelatin-calcium phosphate; nanocomposite graft

BKPYV-SPECIFIC T CELLS REDUCE VIRAL LOAD IN A PRIMARY TUBULAR CELL MODEL - Wasielewski, E.; Lippler, Susanne; Knaup, Karl; Gary, Regina; Aigner, Michael; Kremer, Anna-Lena; Pfister, Felix; Amann, Kerstin Ute; Schiffer, Mario; Mackensen, Andreas; Wiesener, Michael (TRANSPLANT INTERNATIONAL, 2021)
CRIS-Team WoS Importer:2021-10-15

Blockade of the CD47/SIRPα checkpoint axis potentiates the macrophage-mediated antitumor efficacy of tafasitamab. - Biedermann, Alexander; Patra-Kneuer, Maria; Mougiakakos, Dimitrios; Büttner-Herold, Maike; Mangelberger-Eberl, Doris; Berges, Johannes; Kellner, Christian; Altmeyer, Sarah; Bittenbring, Jörg Thomas; Augsberger, Christian; Ilieva-Babinsky, Kristina; Haskamp, Stefan; et al. (Haematologica, 2024)
Macrophages are one of the key mediators of the therapeutic effects exerted by monoclonal antibodies, such as the anti-CD19 antibody tafasitamab, approved in combination with lenalidomide for the treatment of relapsed or refractory diffuse large B-cell lymphoma (DLBCL). However, antibody-dependent cellular phagocytosis (ADCP) in the tumor microenvironment can be counteracted by increased expression of the inhibitory receptor SIRPα on macrophages and its ligand, the immune checkpoint molecule CD47, on tumor cells. The aim of this study was to investigate the impact of the CD47-SIRPα axis on tafasitamab- mediated phagocytosis and explore the potential of anti-CD47 blockade to enhance its antitumor activity. Elevated expression of both SIRPα and CD47 was observed in DLBCL patient-derived lymph node biopsies compared to healthy control lymph nodes. CRISPR-mediated CD47 overexpression affected tafasitamab-mediated ADCP in vitro and increased expression of SIRPα on macrophages correlated with decreased ADCP activity of tafasitamab against DLBCL cell lines. A combination of tafasitamab and an anti-CD47 blocking antibody enhanced ADCP activity of in vitro-generated macrophages. Importantly, tafasitamab-mediated phagocytosis was elevated in combination with CD47 blockade using primary DLBCL cells and patient-derived lymphoma-associated macrophages in an autologous setting. Furthermore, lymphoma cells with low CD19 expression were efficiently eliminated by the combination treatment. Finally, combined treatment of tafasitamab and an anti-CD47 antibody resulted in enhanced tumor volume reduction and survival benefit in lymphoma xenograft mouse models. These findings provide evidence that CD47 blockade can enhance the phagocytic potential of tumor-targeting immunotherapies such as tafasitamab and suggest that there is value in exploring the combination in the clinic.
EVALuna2:569373

Blocking of angiotensin II is more than blocking of transforming growth factor-β - Daniel, Christoph (Kidney International, 2008)
Fibrosis is a common feature of chronic kidney diseases that is mediated by matrix-producing myofibroblasts. One potential origin of myofibroblasts is epithelial-mesenchymal transition (EMT) of tubuloepithelial cells. Transforming growth factor-β (TGF-β) is a key factor inducing EMT. Carvajal et al. demonstrate that angiotensin II induces EMT by classical stimulation of TGF-β and also by a TGF-β-independent pathway, both signaling via Smad molecules. Therefore, blockade of angiotensin II is more than lowering of blood pressure and inhibition of TGF-β stimulation.
Created from Fastlane, Scopus look-up

Blocking the CD47-Sirpa Axis Enhances Tafasitamab-Mediated Phagocytosis - Biedermann, Alexander; Mangelberger-Eberl, Doris; Mougiakakos, Dimitrios; Büttner-Herold, Maike; Flamann, Cindy; Kellner, Christian; Altmeyer, Sarah; Bittenbring, Joerg; Augsberger, Christian; Patra-Kneuer, Maria; Landgraf, Karin; Ilieva-Babinsky, Kristina; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-17

Blood group-specific apheresis in combination with daratumumab as a rescue therapy of acute antibody-mediated rejection in a case of ABO- and human leukocyte antigen-incompatible kidney transplantation - Süsal, Can C.; Kraft, Leonie; Ender, Andrea; Süsal, Caner; Schwenger, Amelie; Amann, Kerstin Ute; Böhmig, Georg A.; Schwenger, Vedat (SAGE Open Medical Case Reports, 2023)
We report a case of antibody-mediated rejection treated with the human CD38 monoclonal antibody daratumumab in a 58-year-old female patient with end-stage kidney disease due to autosomal dominant polycystic kidney disease who received an ABO- and human leukocyte antigen antibody-incompatible living donor kidney transplant. The patient experienced an episode of severe antibody-mediated rejection within the first week of transplantation. Blood-group-antibody selective immunoadsorption in combination with administration of four doses of daratumumab (each 1800 mg s.c.) led to a persistent decrease of ABO- and more interestingly donor-specific human leukocyte antigen antibody reactivity and resulted in clinical and histopathological remission with full recovery of graft function, which has remained stable until post-transplant day 212. This case illustrates the potential of targeting CD38 in antibody-mediated rejection.
CRIS-Team Scopus Importer:2023-11-24
Keywords: antibody-mediated rejection; blood-group incompatibility; Case report; daratumumab; HLA incompatibility; kidney transplantation; living-donor transplantation; rejection therapy

Blunted transcriptional response to skeletal muscle ischemia in rats with chronic kidney disease: potential role for impaired ischemia-induced angiogenesis - Heiß, Rafael; Fahlbusch, Fabian B.; Jacobi, Johannes; Daniel, Christoph; Ekici, Arif Bülent; Cordasic, Nada; Amann, Kerstin Ute; Hilgers, Karl Friedrich; Hartner, Andrea (Physiological Genomics, 2017)
Chronic kidney disease (CKD) is associated with increased cardiovascular morbidity and mortality. Previous studies indicated an impairment of ischemia-induced angiogenesis in skeletal muscle of rats with CKD. We performed a systematic comparison of early gene expression in response to ischemia in rats with or without CKD to identify potential molecular mechanisms underlying impaired angiogenesis in CKD. CKD was induced in male rats by 5/6 nephrectomy (SNX); control rats were sham operated (sham). Eight weeks later, ischemia of the right limb was induced by ligation and resection of the femoral artery. Rats were sacrificed 24 hours after the onset of ischemia, and RNA was extracted from the musculus soleus of the ischemic and the nonischemic hindlimb. To identify differentially expressed transcripts, RNA was analyzed employing Affymetrix GeneChip Rat Genome 230 2.0 Arrays. RT-PCR analysis of selected genes was performed to validate observed changes. Hindlimb ischemia up-regulated 239 genes in CKD and 299 genes in control rats (66% overlap) whereas only a few genes were down-regulated (14 in CKD and 34 in controls), compared with the non-ischemic limb of the same animals. Comparison between the ischemic limbs of CKD and controls revealed down-regulation of 65 genes in CKD; 37 of these genes were also among the ischemia-induced genes in controls. Analysis of functional groups (other than angiogenesis) pointed to genes involved in leukocyte recruitment and fatty acid metabolism. Transcript expression profiling points to a relatively small number of differentially expressed genes which may underlie the impaired post-ischemic angiogenesis in CKD.
EVALuna2:3946

BRONJ-related jaw bone is associated with increased Dlx-5 and suppressed osteopontin-implication in the site-specific alteration of angiogenesis and bone turnover by bisphosphonates - Wehrhan, Falk; Amann, Kerstin Ute; Moebius, Patrick; Weber, Manuel; Preidl, Raimund; Ries, Jutta; Stockmann, Philipp (Clinical Oral Investigations, 2015)
Site-specific suppression of bone remodelling has been implicated in bisphosphonate-(BP)-related osteonecrosis of the jaws (BRONJ). Due to the origin of jaw bone from cranial neural crest, osseous differentiation is regulated specifically by the antagonizing BMP-2-downstream-transcription factors Msx-1 and Dlx-5. Osteopontin has been implicated in bone remodelling and angiogenesis. The osteoblast and osteoclast progenitor proliferation mediating Msx-1 has been demonstrated to be suppressed in BRONJ. In vitro BPs were shown to increase Dlx-5 and to suppress osteopontin expression. This study targeted Dlx-5 and osteopontin in BRONJ-related and BP-exposed jaw bone compared with healthy jaw bone samples at protein- and messenger RNA (mRNA) level, since increased Dlx-5 and suppressed osteopontin might account for impaired bone turnover in BRONJ.Fifteen BRONJ-exposed, 15 BP-exposed and 20 healthy jaw bone samples were processed for real-time reverse transcription polymerase chain reaction (RT-PCR) and for immunohistochemistry. Targeting Dlx-5, osteopontin and glyceraldehyde 3-phosphate dehydrogenase mRNA was extracted, quantified by the LabChip-method, followed by quantitative RT-PCR. For immunohistochemistry, an autostaining-based alkaline phosphatase antialkaline phosphatase (APAPP) staining kit was used. Semiquantitative assessment was performed measuring the ratio of stained cells/total number of cells (labelling index, Bonferroni adjustment).The labelling index was significant decreased for osteopontin (p < 0.017) and significantly increased for Dlx-5 (p < 0.021) in BRONJ samples. In BRONJ specimens, a significant fivefold decrease in gene expression for osteopontin (p < 0.015) and a significant eightfold increase in Dlx-5 expression (p < 0.012) were found.BRONJ-related suppression of bone turnover is consistent with increased Dlx-5 expression and with suppression of osteopontin. The BP-related impaired BMP-2-Msx-1-Dlx-5 axis might explain the jaw bone specific alteration by BP.The findings of this study help to explain the restriction of RONJ to craniofacial bones. BRONJ might serve as a model of disease elucidating the specific signal transduction of neural crest cell-derived bone structures in health and disease.
EVALuna2:24383

Bruton’s tyrosine kinase inhibition attenuates disease progression by reducing renal immune cell invasion in mice with hemolytic-uremic syndrome - Kroeller, Sarah; Wissuwa, Bianka; Dennhardt, Sophie; Krieg, Nadine; Thiemermann, Christoph; Daniel, Christoph; Amann, Kerstin Ute; Gunzer, Florian; Coldewey, Sina M. (Frontiers in Immunology, 2023)
Hemolytic-uremic syndrome (HUS) can occur as a complication of an infection with Shiga-toxin (Stx)-producing Escherichia coli. Patients typically present with acute kidney injury, microangiopathic hemolytic anemia and thrombocytopenia. There is evidence that Stx-induced renal damage propagates a pro-inflammatory response. To date, therapy is limited to organ-supportive strategies. Bruton’s tyrosine kinase (BTK) plays a pivotal role in recruitment and function of immune cells and its inhibition was recently shown to improve renal function in experimental sepsis and lupus nephritis. We hypothesized that attenuating the evoked immune response by BTK-inhibitors (BTKi) ameliorates outcome in HUS. We investigated the effect of daily oral administration of the BTKi ibrutinib (30 mg/kg) and acalabrutinib (3 mg/kg) in mice with Stx-induced HUS at day 7. After BTKi administration, we observed attenuated disease progression in mice with HUS. These findings were associated with less BTK and downstream phospholipase-C-gamma-2 activation in the spleen and, subsequently, a reduced renal invasion of BTK-positive cells including neutrophils. Only ibrutinib treatment diminished renal invasion of macrophages, improved acute kidney injury and dysfunction (plasma levels of NGAL and urea) and reduced hemolysis (plasma levels of bilirubin and LDH activity). In conclusion, we report here for the first time that BTK inhibition attenuates the course of disease in murine HUS. We suggest that the observed reduction of renal immune cell invasion contributes – at least in part – to this effect. Further translational studies are needed to evaluate BTK as a potential target for HUS therapy to overcome currently limited treatment options.
CRIS-Team Scopus Importer:2023-03-24
Keywords: acalabrutinib; acute kidney injury; animal model; Bruton’s tyrosine kinase; hemolytic-uremic syndrome; ibrutinib; inflammation

Calcium supplementation of bioinks reduces shear stress-induced cell damage during bioprinting - Fischer, Lena; Nosratlo, Mojtaba; Hast, Katharina; Karakaya, Emine; Ströhlein, Nadi; Esser, Tilman; Gerum, Richard; Richter, Sebastian; Engel, Felix; Detsch, Rainer; Fabry, Ben; Thievessen, Ingo (Biofabrication, 2022)
During bioprinting, cells are suspended in a viscous bioink and extruded under pressure through small diameter printing needles. The combination of high pressure and small needle diameter exposes cells to considerable shear stress, which can lead to cell damage and death. Approaches to monitor and control shear stress-induced cell damage are currently not well established. To visualize the effects of printing-induced shear stress on plasma membrane integrity, we add FM 1-43 to the bioink, a styryl dye that becomes fluorescent when bound to lipid membranes, such as the cellular plasma membrane. Upon plasma membrane disruption, the dye enters the cell and also stains intracellular membranes. Extrusion of alginate-suspended NIH/3T3 cells through a 200 mu m printing needle led to an increased FM 1-43 incorporation at high pressure, demonstrating that typical shear stresses during bioprinting can transiently damage the plasma membrane. Cell imaging in a microfluidic channel confirmed that FM 1-43 incorporation is caused by cell strain. Notably, high printing pressure also impaired cell survival in bioprinting experiments. Using cell types of different stiffnesses, we find that shear stress-induced cell strain, FM 1-43 incorporation and cell death were reduced in stiffer compared to softer cell types and demonstrate that cell damage and death correlate with shear stress-induced cell deformation. Importantly, supplementation of the suspension medium with physiological concentrations of CaCl2 greatly reduced shear stress-induced cell damage and death but not cell deformation. As the sudden influx of calcium ions is known to induce rapid cellular vesicle exocytosis and subsequent actin polymerization in the cell cortex, we hypothesize that calcium supplementation facilitates the rapid resealing of plasma membrane damage sites. We recommend that bioinks should be routinely supplemented with physiological concentrations of calcium ions to reduce shear stress-induced cell damage and death during extrusion bioprinting.
CRIS-Team WoS Importer:2022-08-26

Can Gene Expression Analysis in Zero-Time Biopsies Predict Kidney Transplant Rejection? - Vonbrunn, Eva; Angeloni, Miriam; Büttner-Herold, Maike; Müller-Deile, Janina; Heller, Katharina M.; Bleich, Erik; Söllner, Stefan; Amann, Kerstin Ute; Ferrazzi, Fulvia; Daniel, Christoph (Frontiers in Medicine, 2022)
Zero-time biopsies are taken to determine the quality of the donor organ at the time of transplantation. Histological analyses alone have so far not been able to identify parameters that allow the prediction of subsequent rejection episodes or graft survival. This study investigated whether gene expression analyses of zero-time biopsies might support this prediction. Using a well-characterized cohort of 26 zero-time biopsies from renal transplant patients that include 4 living donor (LD) and 22 deceased donor (DD) biopsies that later developed no rejection (Ctrl, n = 7), delayed graft function (DGF, n = 4), cellular (T-cell mediated rejection; TCMR, n = 8), or antibody-mediated rejection (ABMR, n = 7), we analyzed gene expression profiles for different types of subsequent renal transplant complication. To this end, RNA was isolated from formalin-fixed, paraffin-embedded (FFPE) sections and gene expression profiles were quantified. Results were correlated with transplant data and B-cell, and plasma cell infiltration was assessed by immunofluorescence microscopy. Both principal component analysis and clustering analysis of gene expression data revealed marked separation between LDs and DDs. Differential expression analysis identified 185 significant differentially expressed genes (adjusted p < 0.05). The expression of 68% of these genes significantly correlated with cold ischemia time (CIT). Furthermore, immunoglobulins were differentially expressed in zero-time biopsies from transplants later developing rejection (TCMR + ABMR) compared to non-rejected (Ctrl + DGF) transplants. In addition, immunoglobulin expression did not correlate with CIT but was increased in transplants with previous acute renal failure (ARF). In conclusion, gene expression profiles in zero-time biopsies derived from LDs are markedly different from those of DDs. Pre-transplant ARF increased immunoglobulin expression, which might be involved in triggering later rejection events. However, these findings must be confirmed in larger cohorts and the role of early immunoglobulin upregulation in zero-biopsies needs further clarification.
CRIS-Team Scopus Importer:2022-04-29
Keywords: inflammation; kidney transplantation; mRNA expression; outcome; zero-time biopsy

Carbon nanotube doped pericardial matrix derived electroconductive biohybrid hydrogel for cardiac tissue engineering - Roshanbinfar, Kaveh; Mohammadi, Zahra; Sheikh-Mahdi Mesgar, Abdorreza; Dehghan, Mohammad Mehdi; Oommen, Oommen P.; Hilborn, Jöns; Engel, Felix (Biomaterials Science, 2019)
Cardiovascular diseases represent a major socio-economic burden. In recent years, considerable effort has been invested in optimizing cell delivery strategies to advance cell transplantation therapies to restore heart function for example after an infarct. A particular issue is that the implantation of cells using a non-electroconductive matrix potentially causes arrhythmia. Here, we demonstrate that our hydrazide-functionalized nanotubes-pericardial matrix-derived electroconductive biohybrid hydrogel provides a suitable environment for maturation of human-induced pluripotent stem cell (hiPSC)-derived cardiomyocytes. hiPSC-derived cardiomyocytes exhibited an improved contraction amplitude (>500%) on conductive hydrogels compared to cells cultured on Matrigel®. This was accompanied by increased cellular alignment, enhanced connexin 43 expression, and improved sarcomere organization suggesting maturation of the hiPSC-derived cardiomyocytes. Sarcomeric length of these cells increased from 1.3 to 1.7 μm. Moreover, 3D cell-laden engineered tissues exhibited enhanced calcium handling as well as positive response to external electrical and pharmaceutical stimulation. Collectively, our data indicate that our biohybrid hydrogels consisting of solubilized nanostructured pericardial matrix and electroconductive positively charged hydrazide-conjugated carbon nanotubes provide a promising material for stem cell-based cardiac tissue engineering.
CRIS-Team Scopus Importer:2019-09-03

Cardiac injury of the newborn mammalian heart accelerates cardiomyocyte terminal differentiation - Zebrowski, David; Jensen, Charlotte H.; Becker, Robert; Ferrazzi, Fulvia; Baun, Christina; Hvidsten, Svend; Sheikh, Soren P.; Polizzotti, Brian D.; Andersen, Ditte C.; Engel, Felix (Scientific Reports, 2017)
After birth cardiomyocytes undergo terminal differentiation, characterized by binucleation and centrosome disassembly, rendering the heart unable to regenerate. Yet, it has been suggested that newborn mammals regenerate their hearts after apical resection by cardiomyocyte proliferation. Thus, we tested the hypothesis that apical resection either inhibits, delays, or reverses cardiomyocyte centrosome disassembly and binucleation. Our data show that apical resection rather transiently accelerates centrosome disassembly as well as the rate of binucleation. Consistent with the nearly 2-fold increased rate of binucleation there was a nearly 2-fold increase in the number of cardiomyocytes in mitosis indicating that the majority of injury-induced cardiomyocyte cell cycle activity results in binucleation, not proliferation. Concurrently, cardiomyocytes undergoing cytokinesis from embryonic hearts exhibited midbody formation consistent with successful abscission, whereas those from 3 day-old cardiomyocytes after apical resection exhibited midbody formation consistent with abscission failure. Lastly, injured hearts failed to fully regenerate as evidenced by persistent scarring and reduced wall motion. Collectively, these data suggest that should a regenerative program exist in the newborn mammalian heart, it is quickly curtailed by developmental mechanisms that render cardiomyocytes post-mitotic.
EVALuna2:9380

Cardiomyocyte binucleation is associated with aberrant mitotic microtubule distribution, mislocalization of RhoA and IQGAP3, as well as defective actomyosin ring anchorage and cleavage furrow ingression - Leone, Marina; Musa, Gentian; Engel, Felix (Cardiovascular Research, 2018)
Aims After birth mammalian cardiomyocytes initiate a last cell cycle which results in binucleation due to cytokinesis failure. Despite its importance for cardiac regenerative therapies, this process is poorly understood. Here, we aimed at a better understanding of the difference between cardiomyocyte proliferation and binucleation and providing a new tool to distinguish these two processes.Methods and results Monitoring of cell division by time-lapse imaging revealed that rat cardiomyocyte binucleation stems from a failure to properly ingress the cleavage furrow. Astral microtubule required for actomyosin ring anchorage and thus furrow ingression were not symmetrically distributed at the periphery of the equatorial region during anaphase in binucleating cardiomyocytes. Consequently, RhoA, the master regulator of actomyosin ring formation and constriction, non-muscle myosin IIB, a central component of the actomyosin ring, as well as IQGAP3 were abnormally localized during cytokinesis. In agreement with improper furrow ingression, binucleation in vitro and in vivo was associated with a failure of RhoA and IQGAP3 to localize to the stembody of the midbody.Conclusion Taken together, these results indicate that naturally occurring cytokinesis failure in primary cardiomyocytes is due to an aberrant mitotic microtubule apparatus resulting in inefficient anchorage of the actomyosin ring to the plasma cell membrane. Thus, cardiomyocyte binucleation and division can be discriminated by the analysis of RhoA as well as IQGAP3 localization.
Keywords: IQGAP3; RhoA; Actomyosin ring; Cardiomyocytes; Microtubules

Cardiomyocyte Cell-Cycle Activity during Preadolescence - Soonpaa, Mark H.; Zebrowski, David; Platt, Colin; Rosenzweig, Anthony; Engel, Felix; Field, Loren J. (Cell, 2015)
EVALuna2:25501

Cardiomyocyte proliferation in cardiac development and regeneration: a guide to methodologies and interpretations - Leone, Marina; Magadum, Ajit; Engel, Felix (American Journal of Physiology-Heart and Circulatory Physiology, 2015)
The newt and the zebrafish have the ability to regenerate many of their tissues and organs including the heart. Thus, a major goal in experimental medicine is to elucidate the molecular mechanisms underlying the regenerative capacity of these species. A wide variety of experiments have demonstrated that naturally occurring heart regeneration relies on cardiomyocyte proliferation. Thus, major efforts have been invested to induce proliferation of mammalian cardiomyocytes in order to improve cardiac function after injury or to protect the heart from further functional deterioration. In this review, we describe and analyze methods currently used to evaluate cardiomyocyte proliferation. In addition, we summarize the literature on naturally occurring heart regeneration. Our analysis highlights that newt and zebrafish heart regeneration relies on factors that are also utilized in cardiomyocyte proliferation during mammalian fetal development. Most of these factors have, however, failed to induce adult mammalian cardiomyocyte proliferation. Finally, our analysis of mammalian neonatal heart regeneration indicates experiments that could resolve conflicting results in the literature, such as binucleation assays and clonal analysis. Collectively, cardiac regeneration based on cardiomyocyte proliferation is a promising approach for improving adult human cardiac function after injury, but it is important to elucidate the mechanisms arresting mammalian cardiomyocyte proliferation after birth and to utilize better assays to determine formation of new muscle mass.
EVALuna2:25502

Cardiovascular changes in the NZB/W F1 mouse model of lupus nephritis - Böhme, Romy; Daniel, Christoph; Ferrazzi, Fulvia; Angeloni, Miriam; Ekici, Arif Bülent; Winkler, Thomas; Hilgers, Karl Friedrich; Wellmann, Ute; Voll, Reinhard E.; Amann, Kerstin Ute (Frontiers in Cardiovascular Medicine, 2023)
Background: Patients with systemic lupus erythematosus (SLE), an autoimmune disease, have a higher risk of cardiovascular (CV) disease and death. In addition, up to 40%–50% of SLE patients develop lupus nephritis (LN) and chronic kidney disease, which is an additional CV risk factor. Thus, the individual contributions of LN and other SLE-specific factors to CV events are unclear. Methods: In this study, we investigated the effect of LN on the development of CV changes using the female NZBxNZW F1 (NZB/W) mouse model of lupus-like disease, with female NZW mice as controls. Standard serologic, morphologic, immunohistologic, and molecular analyses were performed. In a separate group of NZB/W mice, systolic blood pressure (BP) was measured during the course of the disease using tail plethysmography. Results: Our data show marked CV changes in NZB/W mice, i.e., increased heart weight, hypertrophy of the left ventricle (LV) and septum, and increased wall thickness of the intramyocardial arteries and the aorta, which correlated with the progression of renal damage, but not with the age of the mice. In addition, systolic BP was increased in NZB/W mice only when kidney damage progressed and proteinuria was present. Pathway analysis based on gene expression data revealed a significant upregulation of the response to interferon beta in NZB/W mice with moderate kidney injury compared with NZB mice. Furthermore, IFI202b and IL-6 mRNA expression is correlated with CV changes. Multiple linear regression analysis demonstrated serum urea as a surrogate marker of kidney function and IFI202b expression as an independent predictor for LV wall thickness. In addition, deposition of complement factors CFD and C3c in hearts from NZB/W mice was seen, which correlated with the severity of kidney disease. Conclusions: Thus, we postulate that the pathogenesis of CV disease in SLE is affected by renal impairment, i.e., LN, but it can also be partly influenced by lupus-specific cardiac expression of pro-inflammatory factors and complement deposition.
CRIS-Team Scopus Importer:2023-08-18
Keywords: autoimmune disease; cardiovascular disease; IL-15; interferon-related; renal disease; systemic lupus erythematosus

Case Report: Pediatric Renal Sarcoidosis and Prognostic Factors in Reviewed Cases - Klaus, Richard; Jansson, Annette Friederike; Griese, Matthias; Seeman, Tomas; Amann, Kerstin Ute; Lange-Sperandio, Bärbel (Frontiers in Pediatrics, 2021)
Background: Pediatric sarcoidosis is a complex inflammatory disorder with multisystemic manifestations. Kidney involvement in children is rare, and prognostic factors are unknown. Case Report and Methods: We report the case of a 16-year-old girl with multiorgan sarcoidosis and renal involvement. The patient presented with tubulointerstitial nephritis, acute kidney injury (AKI), chest CT disseminated noduli, granulomatous iridocyclitis, giant-cell sialadenitis, and arthralgia. The kidney biopsy revealed non-granulomatous interstitial nephritis. Treatment consisted of initial high-dose methylprednisolone pulse followed by oral prednisolone and methotrexate. Full remission was achieved. In addition, we performed a literature review using PubMed and analyzed data on pediatric renal sarcoidosis cases. Results: We identified 36 cases of pediatric sarcoidosis with renal involvement on presentation and data on the end-of-follow-up glomerular filtration rate (GFR). The data from the literature review showed that renal involvement was slightly more prevalent in males (60%). AKI was present in most of the described patients (84%). Oral prednisolone was used in 35 of 36 cases; in more severe cases, other immunosuppressants were used. We newly identified renal concentration impairment and granulomatous interstitial nephritis as factors with a clear trend toward GFR loss at the end of follow-up, emphasizing the importance of kidney biopsy in symptomatic patients. In contrast, higher GFR at presentation and hypercalcemia were rather favorable factors. According to the identified predictive factors, our patient has a good prognosis and is in remission. Conclusion: The factors indicating a trend toward an unfavorable renal outcome in pediatric sarcoidosis are renal concentration impairment and granulomatous interstitial nephritis at presentation, while a higher GFR is beneficial.
CRIS-Team Scopus Importer:2021-10-08
Keywords: acute kidney injury; case report; prognostic factor analysis; sarcoidosis; tubulointerstitial nephritis

Caspase-8 regulates TNF-α-induced epithelial necroptosis and terminal ileitis - Günther, Claudia; Martini, Eva; Amann, Kerstin Ute; Weigmann, Benno; Neumann, Helmut; Waldner, Maximilian; Tenzer, Stefan; Neurath, Markus; Becker, Christoph; et al. (Nature, 2011)
Dysfunction of the intestinal epithelium is believed to result in the excessive translocation of commensal bacteria into the bowel wall that drives chronic mucosal inflammation in Crohn's disease, an incurable inflammatory bowel disease in humans characterized by inflammation of the terminal ileum. In healthy individuals, the intestinal epithelium maintains a physical barrier, established by the tight contact of cells. Moreover, specialized epithelial cells such as Paneth cells and goblet cells provide innate immune defence functions by secreting mucus and antimicrobial peptides, which hamper access and survival of bacteria adjacent to the epithelium. Epithelial cell death is a hallmark of intestinal inflammation and has been discussed as a possible pathogenic mechanism driving Crohn's disease in humans. However, the regulation of epithelial cell death and its role in intestinal homeostasis remain poorly understood. Here we demonstrate a critical role for caspase-8 in regulating necroptosis of intestinal epithelial cells (IECs) and terminal ileitis. Mice with a conditional deletion of caspase-8 in the intestinal epithelium (Casp8(ΔIEC)) spontaneously developed inflammatory lesions in the terminal ileum and were highly susceptible to colitis. Casp8(ΔIEC) mice lacked Paneth cells and showed reduced numbers of goblet cells, indicating dysregulated antimicrobial immune cell functions of the intestinal epithelium. Casp8(ΔIEC) mice showed increased cell death in the Paneth cell area of small intestinal crypts. Epithelial cell death was induced by tumour necrosis factor (TNF)-α, was associated with increased expression of receptor-interacting protein 3 (Rip3; also known as Ripk3) and could be inhibited on blockade of necroptosis. Lastly, we identified high levels of RIP3 in human Paneth cells and increased necroptosis in the terminal ileum of patients with Crohn's disease, suggesting a potential role of necroptosis in the pathogenesis of this disease. Together, our data demonstrate a critical function of caspase-8 in regulating intestinal homeostasis and in protecting IECs from TNF-α-induced necroptotic cell death.

CD101 inhibits the expansion of colitogenic T cells - Schey, Regina; Dornhoff, H.; Baier, J. L. C.; Purtak, M.; Opoka, R.; Koller, A. K.; Atreya, Raja; Rau, Tilman; Daniel, Christoph; Amann, Kerstin Ute; Bogdan, Christian; Mattner, Jochen (Mucosal Immunology, 2016)
CD101 exerts negative-costimulatory effects in vitro, but its function in vivo remains poorly defined. CD101 is abundantly expressed on lymphoid and myeloid cells in intestinal tissues, but absent from naïve splenic T cells. Here, we assessed the impact of CD101 on the course of inflammatory bowel disease (IBD). Using a T-cell transfer model of chronic colitis, we found that in recipients of naïve T cells from CD101(+/+) donors up to 30% of the recovered lymphocytes expressed CD101, correlating with an increased interleukin (IL)-2-mediated FoxP3 expression. Transfer of CD101(-/-) T cells caused more severe colitis and was associated with an expansion of IL-17-producing T cells and an enhanced expression of IL-2R?/? independently of FoxP3. The co-transfer of naïve and regulatory T cells (Treg) protected most effectively from colitis, when both donor and recipient mice expressed CD101. Although the expression of CD101 on T cells was sufficient for Treg-function and the inhibition of T-cell proliferation, sustained IL-10 production required additional CD101 expression by myeloid cells. Finally, in patients with IBD a reduced CD101 expression on peripheral and intestinal monocytes and CD4(+) T cells correlated with enhanced IL-17 production and disease activity. Thus, CD101 deficiency is a novel marker for progressive colitis and potential target for therapeutic intervention.
EVALuna2:2051

CD107a+ (LAMP-1) Cytotoxic CD8+ T-Cells in Lupus Nephritis Patients - Wiechmann, Anika; Wilde, Benjamin; Tyczynski, Bartosz; Amann, Kerstin Ute; Abdulahad, Wayel H.; Kribben, Andreas; Lang, Karl Sebastian; Witzke, Oliver; Dolff, Sebastian (Frontiers in Medicine, 2021)
Cytotoxic CD8+ T-cells play a pivotal role in the pathogenesis of systemic lupus erythematosus (SLE). The aim of this study was to investigate the role of CD107a (LAMP-1) on cytotoxic CD8+ T-cells in SLE-patients in particular with lupus nephritis. Peripheral blood of SLE-patients (n = 31) and healthy controls (n = 21) was analyzed for the expression of CD314 and CD107a by flow cytometry. Kidney biopsies of lupus nephritis patients were investigated for the presence of CD8+ and C107a+ cells by immunohistochemistry and immunofluorescence staining. The percentages of CD107a+ on CD8+ T-cells were significantly decreased in SLE-patients as compared to healthy controls (40.2 ± 18.5% vs. 47.9 ± 15.0%, p = 0.02). This was even more significant in SLE-patients with inactive disease. There was a significant correlation between the percentages of CD107a+CD8+ T-cells and SLEDAI. The evaluation of lupus nephritis biopsies showed a significant number of CD107a+CD8+ T-cells mainly located in the peritubular infiltrates. The intrarenal expression of CD107a+ was significantly correlated with proteinuria. These results demonstrate that CD8+ T-cells of patients with systemic lupus erythematosus have an altered expression of CD107a which seems to be associated with disease activity. The proof of intrarenal CD107a+CD8+ suggests a role in the pathogenesis of lupus nephritis.
CRIS-Team Scopus Importer:2021-04-16
Keywords: CD107a; cytotoxic T-cells; LAMP-1; lupus nephritis; SLE

CD161a-positive natural killer (NK) cells and α-smooth muscle actin-positive myofibroblasts were upregulated by extrarenal DPP4 in a rat model of acute renal rejection - Schmid, Franziska; Mayer, Carolin; Büttner-Herold, Maike; von Hörsten, Stephan; Amann, Kerstin Ute; Daniel, Christoph (Diabetes Research and Clinical Practice, 2021)
Aims: Systemic inhibition of dipeptidyl peptidase 4 (DPP4) showed a protective effect in several transplant models. Here we assessed the specific role of extrarenal DPP4 in renal transplant rejection. Methods: Kidneys from wildtype (wt) F344 rats were either transplanted in wt Dark Agouti or congenic rats not expressing DPP4. The remaining, not transplanted donor kidney served as healthy controls. To investigate early inflammatory events rats were sacrificed 3 days after transplantation and kidneys were evaluated for inflammatory cells, capillary rarefaction, proliferation, apoptosis and myofibroblasts by immunohistochemistry. Results: Capillary ERG-1-positive endothelial cells were significantly more abundant in renal cortex when transplanted into DPP4 deficient compared to wt recipients. In contrast, TGF-ß and myofibroblasts were reduced by more than 25% in kidneys transplanted into DPP4 deficient compared to wt recipients. Numbers of CD161a-positive NK-cells were significantly lower in allografts in DPP4 deficient compared to wt recipients. Numbers of all other investigated immune cells were not affected by the lack of extrarenal DPP4. Conclusion: In early transplant rejection extrarenal DPP4 is involved in the recruitment of NK-cells and early fibrosis. Beneficial effects were less pronounced than reported for systemic DPP4 inhibition, indicating that renal DPP4 is an important player in transplantation-mediated injury.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Extrarenal DPP4; Fibrosis; Inflammation; Renal transplantation

CD163+ M2c-like macrophages predominate in renal biopsies from patients with lupus nephritis - Olmes, Gregor; Buettner-Herold, Maike; Ferrazzi, Fulvia; Distel, Luitpold; Amann, Kerstin Ute; Daniel, Christoph (Arthritis Research & Therapy, 2015)
The role of macrophages in the pathogenesis of lupus nephritis, in particular their differentiation to a certain subtype (e.g., M1- or M2-like) modulating the inflammatory reaction, is unknown. Here we investigated whether the differentiation in M1- or M2-like macrophages depends on the stage of lupus nephritis and whether this correlates with clinical parameters.Using immunohistochemical analysis we analyzed renal biopsies from 68 patients with lupus nephritis (ISN/RPS classes II-V) for infiltration with M1-like (iNOS+/CD68+), M2a-like (CD206+/CD68+), M2c-like macrophages (CD163+/CD68+), and FoxP3+ regulatory T-cells. In addition, clinical parameters at the time of renal biopsy, i.e., blood pressure, proteinuria and serum urea were correlated with the macrophage infiltration using the Spearman test.The mean number of CD68+ macrophages was related to the diagnosed ISN/RPS class, showing the highest macrophage infiltration in biopsies with diffuse class IV and the lowest number in ISN/RPS class V. In all ISN/RPS classes we detected more M2c-like CD163+/CD68+ than M2a-like CD206+/CD68+ cells, while M1-macrophages played only a minor role. Cluster analysis using macrophage subtype numbers in different renal compartments revealed three main clusters showing cluster 1 dominated by class V. Clusters 2 and 3 were dominated by lupus class IV indicating that this class can be further differentiated by its macrophage population. The number of tubulointerstitial FoxP3+ cells correlated with all investigated macrophage subtypes showing the strongest association to numbers of M2a-like macrophages. Kidney function, as assessed by serum creatinine and serum urea, correlated positively with the number of total CD68+, M2a-like and M2c-like macrophages in the tubulointerstitium. In addition, total CD68+ and M2c-like macrophage numbers highly correlated with Austin activity score. Interestingly, in hypertensive lupus patients only the number of M2a-like macrophages was significantly increased compared to biopsies from normotensive lupus patients.M2-like macrophages are the dominant subpopulation in human lupus nephritis and particularly, M2a subpopulations were associated with disease progression, but their role in disease progression remains unclear.
EVALuna2:9308

CD19-CAR T-cell therapy induces deep tissue depletion of B cells - Tur, Carlo; Eckstein, Markus; Velden, Joachim; Rauber, Simon; Bergmann, Christina; Auth, Janina; Bucci, Laura; Corte, Giulia; Hagen, Melanie; Wirsching, Andreas; Grieshaber Bouyer, Ricardo; Reis, Petra; et al. (Annals of the Rheumatic Diseases, 2024)
Objectives CD19-targeting chimeric antigen receptor (CAR) T-cell therapy can induce long-term drug-free remission in patients with autoimmune diseases (AIDs). The efficacy of CD19-CAR T-cell therapy is presumably based on deep tissue depletion of B cells; however, such effect has not been proven in humans in vivo. Methods Sequential ultrasound-guided inguinal lymph node biopsies were performed at baseline and after CD19-CAR T-cell therapy in patients with AIDs. Results were compared with lymph node biopsies from rituximab (RTX)-treated AID patients with absence of peripheral B cells. Conventional and immunohistochemistry staining were performed on lymph node tissue to assess architecture as well the number of B cells, follicular dendritic cells (FDCs), plasma cells, T cells and macrophages. Results Sequential lymph node biopsies were analysed from five patients with AID before and after CD19-CAR T-cell therapy and from five patients with AID after RTX treatment. In addition, non-lymphoid organ biopsies (colon, kidney and gallbladder) from three additional patients with AID after CD19-CAR T-cell therapy were analysed. CD19+ and CD20+ B cells were completely depleted in the lymph nodes after CD19-CAR T-cell therapy, but not after RTX treatment. Plasma cells, T cells and macrophages in the lymph nodes remained unchanged. Follicular structures were disrupted and FDCs were depleted in the lymph nodes after CD19-CAR T-cell therapy, but not after RTX. Non-lymphoid organs were completely depleted of B cells. Discussion This study demonstrates complete B-cell depletion in secondary lymphoid tissues of patients with AIDs following CD19-CAR T-cell therapy combined with standard lymphodepleting therapy.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Autoimmune Diseases; B-Lymphocytes; Rituximab; Ultrasonography

CD22 x Siglec-G Double-Deficient Mice Have Massively Increased B1 Cell Numbers and Develop Systemic Autoimmunity - Jellusova, Julia; Wellmann, Ute; Amann, Kerstin Ute; Winkler, Thomas; Nitschke, Lars (Journal of Immunology, 2010)
CD22 and Siglec-G are inhibitory coreceptors for BCR-mediated signaling. Although CD22-deficient mice show increased calcium signaling in their conventional B2 cells and a quite normal B cell maturation, Siglec-G-deficient mice have increased calcium mobilization just in B1 cells and show a large expansion of the 131 cell population. Neither CD22-deficient, nor Siglec-G-deficient mice on a pure C57BL/6 or BALB/c background, respectively, develop autoimmunity. Using Siglec-G X CD22 double-deficient mice, we addressed whether Siglec-G and CD22 have redundant functions. Siglec-G X CD22 double-deficient mice show elevated calcium responses in both B1 cells and B2 cells, increased serum IgM levels and an enlarged population of B1 cells. The enlargement of 131 cell numbers is even higher than in Siglecg(-/-) mice. This expansion seems to happen at the expense of B2 cells, which are reduced in absolute cell numbers, but show an activated phenotype. Furthermore, Siglec-G X CD22 double-deficient mice show a diminished immune response to both thymus-dependent and thymus-independent type 11 Ags. In contrast, B cells from Siglec-G X CD22 double-deficient mice exhibit a hyperproliferative response to stimulation with several TLR ligands. Aged Siglec-G X CD22 double-deficient mice spontaneously develop anti-DNA and antinuclear autoantibodies. These resulted in a moderate form of immune complex glomerulonephritis. These results show that Siglec-G and CD22 have partly compensatory functions and together are crucial in maintaining the B cell tolerance. The Journal of Immunology, 2010, 184: 3618-3627.

Cell cycle re-entry sensitizes podocytes to injury induced death - Hagen, Manuel; Pfister, Eva; Kosel, Andrea; Shankland, Stuart; Pippin, Jeffrey; Amann, Kerstin Ute; Daniel, Christoph (Cell Cycle, 2016)
Podocytes are terminally differentiated renal cells, lacking the ability to regenerate by proliferation. However, during renal injury, podocytes re-enter into the cell cycle but fail to divide. Earlier studies suggested that re-entry into cell cycle results in loss of podocytes, but a direct evidence for this is lacking. Therefore, we established an in vitro model to test the consequences of re-entry into the cell cycle on podocyte survival. A mouse immortalized podocyte cell line was differentiated to non-permissive podocytes and stimulated with e.g. growth factors. Stimulated cells were analyzed for mRNA-expression or stained for cell cycle analysis using flow cytometry and immunocytofluorescence microscopy. After stimulation to re-entry into cell cycle, podocytes were stressed with puromycin aminonucleoside (PAN) and analyzed for survival. During permissive stage more than 40% of immortalized podocytes were in the S-phase. In contrast, S-phase in non-permissive differentiated podocytes was reduced to 5%. Treatment with b-FGF dose dependently induced re-entry into cell cycle increasing the number of podocytes in the S-phase to 10.7% at an optimal bFGF dosage of 10 ng/ml. Forty eight hours after stimulation with bFGF the number of bi-nucleated podocytes significantly increased. A secondary injury stimulus significantly reduced podocyte survival preferentially in bi-nucleated podocytes In conclusion, stimulation of podocytes using bFGF was able to induce re-entry of podocytes into the cell cycle and to sensitize the cells for cell death by secondary injuries. Therefore, this model is appropriate for testing new podocyte protective substances that can be used for therapy.
EVALuna:32169

Cell-in-cell phenomenon: leukocyte engulfment by non-tumorigenic cells and cancer cell lines - Bauer, Mareike; Hader, Michael; Hecht, Markus; Büttner-Herold, Maike; Fietkau, Rainer; Distel, Luitpold (BMC Molecular and Cell Biology, 2021)
Background Research on cell-in-cell (CIC) phenomena, including entosis, emperipolesis and cannibalism, and their biological implications has increased in recent years. Homotypic and heterotypic engulfment of various target cells by numerous types of host cells has been studied in vitro and in tissue sections. This work has identified proteins involved in the mechanism and uncovered evidence for CIC as a potential histopathologic predictive and prognostic marker in cancer. Our experimental study focused on non-professional phagocytosis of leukocytes. Results We studied the engulfment of peripheral blood mononuclear cells isolated from healthy donors by counting CIC structures. Two non-tumorigenic cell lines (BEAS-2B, SBLF-9) and two tumour cell lines (BxPC3, ICNI) served as host cells. Immune cells were live-stained and either directly co-incubated or treated with irradiation or with conventional or microwave hyperthermia. Prior to co-incubation, we determined leukocyte viability for each batch via Annexin V-FITC/propidium iodide staining. All host cells engulfed their targets, with uptake rates ranging from 1.0% +/- 0.5% in BxPC3 to 8.1% +/- 5.0% in BEAS-2B. Engulfment rates of the cancer cell lines BxPC3 and ICNI (1.6% +/- 0.2%) were similar to those of the primary fibroblasts SBLF-9 (1.4% +/- 0.2%). We found a significant negative correlation between leukocyte viability and cell-in-cell formation rates. The engulfment rate rose when we increased the dose of radiotherapy and prolonged the impact time. Further, microwave hyperthermia induced higher leukocyte uptake than conventional hyperthermia. Using fluorescent immunocytochemistry to descriptively study the proteins involved, we detected ring-like formations of diverse proteins around the leukocytes, consisting, among others, of alpha-tubulin, integrin, myosin, F-actin, and vinculin. These results suggest the involvement of actomyosin contraction, cell-cell adhesion, and the alpha-tubulin cytoskeleton in the engulfment process. Conclusions Both non-tumorigenic and cancer cells can form heterotypic CIC structures by engulfing leukocytes. Decreased viability and changes caused by microwave and X-ray irradiation trigger non-professional phagocytosis.
CRIS-Team WoS Importer:2021-08-13

Cell-In-Cell Structures in Early Breast Cancer Are Prognostically Valuable - Bauer, Mareike; Hildebrand, Laura; Rosahl, Marie-Charlotte; Erber, Ramona; Schnellhardt, Sören; Büttner-Herold, Maike; Putz, Florian; Ott, Oliver; Hack, Carolin; Fietkau, Rainer; Distel, Luitpold (Cells, 2023)
Cell-in-cell (CIC) structures in breast cancer have so far been studied in a small inhomogeneous patient population, suggesting the prognostic importance of CIC. In the present study, we focused on CIC in early hormone-sensitive breast cancer. With in vitro co-culture experiments, we compared the homotypic phagocytic capacity of two breast cancer cell lines to that of primary human fibroblasts. Afterward, we studied 601 tissue specimens from 147 patients participating in an institutional accelerated partial breast irradiation (APBI) phase II trial. Both breast cancer cell lines performed non-professional phagocytosis at a higher rate than primary human fibroblasts. In this study cohort, 93.2% of the patients had T1 tumours, and 6.8% had T2 tumours. CIC was found in 61.2% of the patients, with a CIC rate ranging from <1/mm2 to 556.5/mm2 with a mean of 30.9/mm2 ± 68.4/mm2. CIC structures were prognostically favourable for local recurrence-free survival and disease-free survival. Regarding metastasis-free survival, CIC-positive patients had an unfavourable prognosis. Subgroup analysis indicated a correlation between a high proliferation index and high CIC rates. CIC had the highest prognostic value in young breast cancer patients (p = 0.004). With this study, we provide further evidence of CIC as a prognostic marker in breast cancer.
CRIS-Team Scopus Importer:2023-01-20
Keywords: accelerated partial breast irradiation; breast cancer; cell-in-cell; ionizing radiation; non-professional phagocytosis; radiotherapy

Cell type-specific modulation of metabolic, immune-regulatory, and anti-microbial pathways by CD101 - Wrage, Marius; Holland, Tim; Nüse, Björn; Kaltwasser, Johanna; Fröhlich, Jessica; Arnold, Harald; Gießler, Claudia; Flamann, Cindy; Bruns, Heiko; Berges, Johannes; Daniel, Christoph; Hoffmann, Markus; et al. (Mucosal Immunology, 2024)
T lymphocytes and myeloid cells express the immunoglobulin-like glycoprotein cluster of differentiation (CD)101, notably in the gut. Here, we investigated the cell-specific functions of CD101 during dextran sulfate sodium (DSS)-induced colitis and Salmonella enterica Typhimurium infection. Similar to conventional CD101−/− mice, animals with a regulatory T cell-specific Cd101 deletion developed more severe intestinal pathology than littermate controls in both models. While the accumulation of T helper 1 cytokines in a CD101-deficient environment entertained DSS-induced colitis, it impeded the replication of Salmonella as revealed by studying CD101−/− x interferon-g−/− mice. Moreover, CD101-expressing neutrophils were capable to restrain Salmonella infection in vitro and in vivo. Both cell-intrinsic and -extrinsic mechanisms of CD101 contributed to the control of bacterial growth and spreading. The CD101-dependent containment of Salmonella infection required the expression of Irg-1 and Nox2 and the production of itaconate and reactive oxygen species. The level of intestinal microbial antigens in the sera of inflammatory bowel disease patients correlated inversely with the expression of CD101 on myeloid cells, which is in line with the suppression of CD101 seen in mice following DSS application or Salmonella infection. Thus, depending on the experimental or clinical setting, CD101 helps to limit inflammatory insults or bacterial infections due to cell type-specific modulation of metabolic, immune-regulatory, and anti-microbial pathways.
CRIS-Team Scopus Importer:2024-07-19

Cellular FLICE-like inhibitory protein secures intestinal epithelial cell survival and immune homeostasis by regulating caspase-8. - Günther, Claudia; Martini, Eva; He, Guiwei; Amann, Kerstin Ute; He, You-Wen; Neurath, Markus; Becker, Christoph; et al. (Gastroenterology, 2013)
The intestinal epithelium generates a barrier that protects mammals from potentially harmful intestinal contents, such as pathogenic bacteria. Dysregulation of epithelial cell death has been implicated in barrier dysfunction and in the pathogenesis of intestinal inflammation. We investigated mechanisms of cell-death regulation in the intestinal epithelium of mice. Conditional knockout mice (either inducible or permanent) with deletion of cellular FLICE-inhibitory protein (cFlip) or caspase-8 in the intestinal epithelium were analyzed by histology and high-resolution endoscopy. We assessed the effects of cFlip or caspase-8 deficiency on intestinal homeostasis. Expression of cFlip in the intestinal epithelium was required for constitutive activation of caspase-8 under steady-state conditions. Intestinal expression of cFlip was required for development; disruption of the gene encoding cFlip from the intestinal epithelium (cFlip(fl/fl) VillinCre(+) mice) resulted in embryonic lethality. When cFlip was deleted from the intestinal epithelium of adult mice (cFlip(iΔIEC) mice), the animals died within a few days from severe tissue destruction, epithelial cell death, and intestinal inflammation. Death of cFlip-depleted intestinal epithelial cells was regulated extrinsically and required the presence of death receptor ligands, such as tumor necrosis factor-α and CD95 ligand, but was independent of receptor-interacting protein 3. cFlip deficiency was associated with strong up-regulation of caspase-8 and caspase-3 activity and excessive apoptosis in intestinal crypts. cFlip is required for intestinal tissue homeostasis in mice. It controls the level of activation of caspase-8 to promote survival of intestinal epithelial cells. BACKGROUND & AIMS METHODS RESULTS CONCLUSIONS
Keywords: CASP8; CFLAR; Fadd; Fadd-Like Apoptosis Regulator; Fas-associated protein with death domain; IEC; NEMO; NF-κB essential modulator; Rip; TNF; TUNEL; cFLIP; cellular FLICE-like inhibitory protein; intestinal epithelial cell; receptor interacting protein; terminal deoxynucleotidyl transferase–mediated deoxyuridine triphosphate nick-end labeling; tumor necrosis factor

Cellular stress induces erythrocyte assembly on intravascular von Willebrand factor strings and promotes microangiopathy - Nicolay, Jan P.; Thorn, Verena; Daniel, Christoph; Amann, Kerstin Ute; Siraskar, Balasaheb; Lang, Florian; Hillgruber, Carina; Goerge, Tobias; Hoffmann, Stefan; Gorzelanny, Christian; Huck, Volker; Mess, Christian; et al. (Scientific Reports, 2018)
Microangiopathy with subsequent organ damage represents a major complication in several diseases. The mechanisms leading to microvascular occlusion include von Willebrand factor (VWF), notably the formation of ultra-large von Willebrand factor fibers (ULVWFs) and platelet aggregation. To date, the contribution of erythrocytes to vascular occlusion is incompletely clarified. We investigated the platelet-independent interaction between stressed erythrocytes and ULVWFs and its consequences for microcirculation and organ function under dynamic conditions. In response to shear stress, erythrocytes interacted strongly with VWF to initiate the formation of ULVWF/erythrocyte aggregates via the binding of Annexin V to the VWF A1 domain. VWF-erythrocyte adhesion was attenuated by heparin and the VWF-specific protease ADAMTS13. In an in vivo model of renal ischemia/reperfusion injury, erythrocytes adhered to capillaries of wild-type but not VWF-deficient mice and later resulted in less renal damage. In vivo imaging in mice confirmed the adhesion of stressed erythrocytes to the vessel wall. Moreover, enhanced eryptosis rates and increased VWF binding were detected in blood samples from patients with chronic renal failure. Our study demonstrates that stressed erythrocytes have a pronounced binding affinity to ULVWFs. The discovered mechanisms suggest that erythrocytes are essential for the pathogenesis of microangiopathies and renal damage by actively binding to ULVWFs.
EVALuna:34419

Changes in glomerular parietal epithelial cells in mouse kidneys with advanced age - Roeder, Sebastian S.; Stefanska, Ania; Eng, Diana G.; Kaverina, Natalya; Sunseri, Maria W.; Mcnicholas, Bairbre A.; Rabinovitch, Peter; Engel, Felix; Daniel, Christoph; Amann, Kerstin Ute; Lichtnekert, Julia; Pippin, Jeffrey W.; et al. (American Journal of Physiology-Renal Physiology, 2015)
Kidney aging is accompanied by characteristic changes in the glomerulus, but little is known about the effect of aging on glomerular parietal epithelial cells (PECs), nor if the characteristic glomerular changes in humans and rats also occur in very old mice. Accordingly, a descriptive analysis was undertaken in 27-mo-old C57B6 mice, considered advanced age. PEC density was significantly lower in older mice compared with young mice (aged 3 mo), and the decrease was more pronounced in juxtamedullary glomeruli compared with outer cortical glomeruli. In addition to segmental and global glomerulosclerosis in older mice, staining for matrix proteins collagen type IV and heparan sulfate proteoglycan were markedly increased in Bowman's capsules of older mouse glomeruli, consistent with increased extracellular matrix production by PECs. De novo staining for CD44, a marker of activated and profibrotic PECs, was significantly increased in aged glomeruli. CD44 staining was more pronounced in the juxtamedullary region and colocalized with phosphorylated ERK. Additionally, a subset of aged PECs de novo expressed the epithelial-to-mesenchymal transition markers ?-smooth muscle and vimentin, with no changes in epithelial-to-mesenchymal transition markers E-cadherin and ?-catenin. The mural cell markers neural/glial antigen 2, PDGF receptor-?, and CD146 as well as Notch 3 were also substantially increased in aged PECs. These data show that mice can be used to better understand the aging kidney and that PECs undergo substantial changes, especially in juxtamedullary glomeruli, that may participate in the overall decline in glomerular structure and function with advancing age.
EVALuna2:25490

Characteristic morphological changes in anti-VEGF therapy induced glomerular microangiopathy - Pfister, Frederick; Amann, Kerstin Ute; Daniel, Christoph; Klewer, Monika; Büttner, Anke; Büttner-Herold, Maike (Histopathology, 2018)
BACKGROUND: Thrombotic microangiopathy (TMA) is a microvascular pathology caused by several drugs used in cancer therapy. Agents targeting vascular endothelial growth factor (VEGF) have increasingly been used in therapy of advanced malignancies and have been found to induce renal TMA and proteinuria. However, histomorphological changes in human biopsies in this setting and the underlying mechanism are not yet fully understood. METHODS: Renal biopsies of 15 patients with anti-VEGF therapy (aVEGF) evaluated between 2013 and 2017 at a single centre were morphologically characterized using light microscopy, electron microscopy and immunohistochemistry (IgA, IgG, IgM, C1q, C3) and compared to cases with acute TMA caused by atypical haemolytic uramic syndrome or hypertension. Morphological overlap with immune-complex and cryoglobulinemic membranoproliferative glomerulonephritis, diabetic glomerulopathy and pre-emclapsia induced glomerulopathy were discussed. RESULTS: Segmental glomerular capillary microaneurysms and segmental hyalinosis were typical morphological features of aVEGF therapy induced glomerular microangiopathy, whereas fibrin or platelet thrombi or fragmented erythrocytes were rarely found or absent. aVEGF therapy associated microangiopathy was diffusely distributed in the glomeruli, spared pre-glomerular vessels, and showed morphological characteristics of chronic TMA. In individual cases, aVEGF therapy induced glomerular microangiopathy was accompanied by immune-complex glomerulonephritis. CONCLUSION: aVEGF therapy induced glomerular microangiopathy has a characteristic morphology and clinical presentation that helps to differentiate it from other causes of TMA. Awareness of these light microscopic findings allows identification of aVEGF therapy as a trigger of renal disease in critically ill cancer patients and therefore might help in deciding on further therapy. This article is protected by copyright. All rights reserved.
EVALuna2:34420

Characterization of Glomerular Sox9+ Cells in Anti-Glomerular Basement Membrane Nephritis in the Rat - Prochnicki, Ania; Amann, Kerstin Ute; Wegner, Michael; Sock, Elisabeth; Pfister, Eva; Shankland, Stuart; Pippin, Jeffrey; Daniel, Christoph (American Journal of Pathology, 2018)
Mechanisms of glomerular crescent formation and podocyte repair processes are still unclear. Therefore, we investigated the expression of the transcription factor Sox9 as a potential marker of a subpopulation of parietal epithelial cells (PECs) with potential regenerative properties. Glomerular Sox9 expression was characterized in detail in a rat anti-glomerular basement membrane (GBM) nephritis model using immunofluorescence and confocal laser scanning microscopy. In healthy kidneys Sox9 is expressed in a subpopulation of PECs restricted to approximately 20% to 50% of PEC nuclei and was highly conserved in all investigated species. During rat anti-GBM nephritis the number of glomerular Sox9+ cells increased and was associated with proliferation activity. In nephritic glomeruli Sox9 expression was not restricted to Bowman's capsule lining but was also found on cells of the glomerular tuft. Nearly all Sox9+ cells also expressed the PEC marker Pax8, whereas endothelial cells, mesangial cells, macrophages, and T lymphocytes lacked Sox9 expression. At the margins of crescents Sox9+/Pax8+ cells additionally expressed podocyte markers. In contrast, in sclerotic lesions a minority of Sox9+/Pax8+ cells expressed the myofibroblast marker α-smooth muscle actin. In glomerular Sox9+ cells Jagged 1 was up-regulated. During anti-GBM nephritis Sox9+ PECs proliferate and migrate onto the glomerular tuft. Future studies are needed to confirm the origin of Sox9+ cells from PECs and differentiation in both podocytes and/or myofibroblasts.
EVALuna2:35393

Characterization of Proenkephalin-A as a potential biomarker for kidney damage in the murine and human kidney - Fuchs, M. A. A.; Schrankl, J.; Wagner, C.; Daniel, Christoph; Kurtz, A.; Broeker, K. A. -E. (ACTA PHYSIOLOGICA, 2022)
CRIS-Team WoS Importer:2022-10-07

Checkpoint kinase Chk2 controls renal Cyp27b1 expression, calcitriol formation, and calcium-phosphate metabolism - Fahkri, Hajar; Zhang, Bingbing; Fajol, Abul; Hernando, Nati; Elvira, Bernat; Mannheim, Julia G.; Pichler, Bernd J.; Daniel, Christoph; Amann, Kerstin Ute; Hirao, Atsushi; Haight, Jillian; Mak, Tak W.; et al. (Pflügers Archiv: European Journal of Physiology, 2015)
Checkpoint kinase 2 (Chk2) is the main effector kinase of ataxia telangiectasia mutated (ATM) and responsible for cell cycle regulation. ATM signaling has been shown to upregulate interferon-regulating factor-1 (IRF-1), a transcription factor also expressed in the kidney. Calcitriol (1,25 (OH)2D3), a major regulator of mineral metabolism, is generated by 25-hydroxyvitamin D 1?-hydroxylase in the kidney. Since 25-hydroxyvitamin D 1?-hydroxylase expression is enhanced by IRF-1, the present study explored the role of Chk2 for calcitriol formation and mineral metabolism. Chk2-deficient mice (chk2 (-/-)) were compared to wild-type mice (chk2 (+/+)). Transcript levels of renal 25-hydroxyvitamin D 1?-hydroxylase, Chk2, and IRF-1 were determined by RT-PCR; Klotho expression by Western blotting; bone density by ?CT analysis; serum or plasma 1,25 (OH)2D3, PTH, and C-terminal FGF23 concentrations by immunoassays; and serum, fecal, and urinary calcium and phosphate concentrations by photometry. The renal expression of IRF-1 and 25-hydroxyvitamin D 1?-hydroxylase as well as serum 1,25 (OH)2D3 and FGF23 levels were significantly lower in chk2 (-/-) mice compared to chk2 (+/+) mice. Plasma PTH was not different between the genotypes. Renal calcium and phosphate excretion were significantly higher in chk2 (-/-) mice than in chk2 (+/+) mice despite hypophosphatemia and normocalcemia. Bone density was not different between the genotypes. We conclude that Chk2 regulates renal 25-hydroxyvitamin D 1?-hydroxylase expression thereby impacting on calcium and phosphate metabolism.
EVALuna2:25469

CHIR99021 Promotes hiPSC-Derived Cardiomyocyte Proliferation in Engineered 3D Microtissues - Hesselbarth, Ramona; Esser, Tilman; Roshanbinfar, Kaveh; Schrüfer, Stefan; Schubert, Dirk W.; Engel, Felix (Advanced Healthcare Materials, 2021)
Cardiac tissue engineering is a promising strategy to generate human cardiac tissues for modeling cardiac diseases, screening for therapeutic drugs, and repairing the injured heart. Yet, several issues remain to be resolved including the generation of tissues with high cardiomyocyte density. Here, it is shown that the integration of the glycogen synthase kinase-3β inhibitor CHIR99021 in collagen I hydrogels promotes proliferation of human-induced pluripotent stem cell-derived (hiPSC) cardiomyocytes post-fabrication improving contractility of and calcium flow in engineered 3D cardiac microtissues. CHIR99021 has no effect on the gelation kinetics or the mechanical properties of collagen I hydrogels. Analysis of cell density and proliferation based on Ki-67 staining indicates that integration of CHIR99021 together with external CHIR99021 stimulation increases hiPSC-cardiomyocyte number by ≈2-fold within 7 d post-fabrication. Analysis of the contractility of engineered cardiac tissues after another 3 d in the absence of external CHIR99021 shows that CHIR99021-induced hiPSC-cardiomyocyte proliferation results in synchronized calcium flow, rhythmic beating, increased speed of contraction and contraction amplitude, and reduced peak-to-peak time. The CHIR99021-stimulated engineered cardiac microtissues exhibit spontaneous rhythmic contractions for at least 35 d. Collectively, the data demonstrate the potential of induced cardiomyocyte proliferation to enhance engineered cardiac microtissues by increasing cardiomyocyte density.
CRIS-Team Scopus Importer:2021-09-17
Keywords: cardiomyocytes; CHIR99021; heart; hiPSC; proliferation; tissue engineering

Chronic Kidney Disease and Coronary Artery Disease: JACC State-of-the-Art Review - Sarnak, Mark J.; Amann, Kerstin Ute; Bangalore, Sripal; Cavalcante, João L.; Charytan, David M.; Craig, Jonathan C.; Gill, John S.; Hlatky, Mark A.; Jardine, Alan G.; Landmesser, Ulf; Newby, L. Kristin; Herzog, Charles A.; et al. (Journal of the American College of Cardiology, 2019)
Chronic kidney disease (CKD) is a major risk factor for coronary artery disease (CAD). As well as their high prevalence of traditional CAD risk factors, such as diabetes and hypertension, persons with CKD are also exposed to other nontraditional, uremia-related cardiovascular disease risk factors, including inflammation, oxidative stress, and abnormal calcium-phosphorus metabolism. CKD and end-stage kidney disease not only increase the risk of CAD, but they also modify its clinical presentation and cardinal symptoms. Management of CAD is complicated in CKD patients, due to their likelihood of comorbid conditions and potential for side effects during interventions. This summary of the Kidney Disease: Improving Global Outcomes (KDIGO) Controversies Conference on CAD and CKD (including end-stage kidney disease and transplant recipients) seeks to improve understanding of the epidemiology, pathophysiology, diagnosis, and treatment of CAD in CKD and to identify knowledge gaps, areas of controversy, and priorities for research.
CRIS-Team Scopus Importer:2019-10-01
Keywords: acute coronary syndromes; calcification; chronic kidney disease; coronary artery disease; revascularization

Chronic kidney disease and valvular heart disease: conclusions from a Kidney Disease: Improving Global Outcomes (KDIGO) Controversies Conference - Marwick, Thomas H.; Amann, Kerstin Ute; Bangalore, Sripal; Cavalcante, João L.; Charytan, David M.; Craig, Jonathan C.; Gill, John S.; Hlatky, Mark A.; Jardine, Alan G.; Landmesser, Ulf; Newby, L. Kristin; Herzog, Charles A.; et al. (Kidney International, 2019)
Chronic kidney disease (CKD) is a major risk factor for valvular heart disease (VHD). Mitral annular and aortic valve calcifications are highly prevalent in CKD patients and commonly lead to valvular stenosis and regurgitation, as well as complications including conduction system abnormalities and endocarditis. VHD, especially mitral regurgitation and aortic stenosis, is associated with significantly reduced survival among CKD patients. Knowledge related to VHD in the general population is not always applicable to CKD patients because the pathophysiology may be different, and CKD patients have a high prevalence of comorbid conditions and elevated risk for periprocedural complications and mortality. This Kidney Disease: Improving Global Outcomes (KDIGO) review of CKD and VHD seeks to improve understanding of the epidemiology, pathophysiology, diagnosis, and treatment of VHD in CKD by summarizing knowledge gaps, areas of controversy, and priorities for research.
CRIS-Team Scopus Importer:2019-09-24
Keywords: aortic stenosis; chronic kidney disease; end-stage kidney disease; mitral annular calcification; valvular heart disease

CIDP, myasthenia gravis, and membranous glomerulonephritis - three autoimmune disorders in one patient: a case report - Bolz, Saskia; Totzeck, Andreas; Amann, Kerstin Ute; Stettner, Mark; Kleinschnitz, Christoph; Hagenacker, Tim (BMC Neurology, 2018)
BACKGROUND: We present a patient fulfilling the electrophysiological criteria for definite chronic inflammatory demyelinating polyneuropathy (CIDP), antibody-positive myasthenia gravis (MG), and membranous glomerulonephritis (MGN) confirmed by biopsy. To our knowledge, this is the first case of the concomitant appearance of these three autoimmune diseases in a single patient. CASE REPRESENTATION: A 42-year-old Caucasian male presented with rapidly progressive gait disturbance, distal weakness of the lower extremities, ascending hypoesthesia, impaired fine motor skills, and beginning cranial nerve palsy showing dysarthrophonia, facial paralysis, and eye movement abnormalities and was diagnosed as rapid onset (atypical) CIDP. After 3 months, the patient complained of increasing physical exhaustion, reduction of his walking distance, worsening of the residual dysphagia, and dysarthria with an inability to swallow. AChR antibodies (17.0 nmol/L, RF < 0.4) and titin antibodies were positive and repetitive nerve stimulation showed an abnormal decrement matching the criteria of myasthenia gravis. Over time the patient developed severe acute-on-chronic renal failure with high-grade proteinuria resulting in generalized edema followed by secondary hyperparathyroidism and dialysis-dependent renal failure. Renal biopsy confirmed beginning anti-phospholipase A2 receptor antibody membranous nephropathy. CONCLUSION: All three diseases are of autoimmune origin with distinctive immunopathogenetic mechanisms. The present case of CIDP, MG, and MGN occurring in one patient indicates a common underlying immune mechanism in these distinct conditions, including the involvement of autoantibodies and T cells.
EVALuna2:205570

Clinical Course of an Early Childhood-Onset Granulomatosis with Polyangiitis - Krasselt, Marco; Pierer, Matthias; Amann, Kerstin Ute; Bachmann, Anette; Lindner, Tom H. (Deutsche Medizinische Wochenschrift, 2017)
History A 26-year-old male patient presented with an eight-week history of unspecific symptoms such as weight loss and fever. Besides, he also suffered from haemoptysis, cough, and arthralgia. Since the age of twelve years, the patient has been treated for Wegner's granulomatosis. At the age of 20 years he received a kidney transplant which failed only four years later. Investigations The relapse we clinically suspected was confirmed by CT scan showing bilateral pulmonary manifestations. Moreover, we found highly positive antibodies against proteinase 3. Treatment and course After an induction therapy using Glucocorticoids and Rituximab, accompanied by plasmapheresis, the patient's clinical condition showed a marked improvement. We were able to discharge him continuing the treatment in an outpatient setting. Conclusion Childhood-onset GPA is a life-threatening disease and often characterized by recurring relapses as well as a significantly reduced quality of life for the patient.
EVALuna2:25540

Coding practice in national and regional kidney biopsy registries - Dendooven, Amélie; Peetermans, Han; Helbert, Mark; Nguyen, Tri Q.; Marcussen, Niels; Nagata, Michio; Gesualdo, Loreto; Perkowska-Ptasinska, Agnieszka; Capusa, Cristina; López-Gómez, Juan M.; Geddes, Colin; Abdul-Hamid, Myrurgia A.; et al. (BMC Nephrology, 2021)
Background: Kidney biopsy registries all over the world benefit research, teaching and health policy. Comparison, aggregation and exchange of data is however greatly dependent on how registration and coding of kidney biopsy diagnoses are performed. This paper gives an overview over kidney biopsy registries, explores how these registries code kidney disease and identifies needs for improvement of coding practice. Methods: A literature search was undertaken to identify biopsy registries for medical kidney diseases. These data were supplemented with information from personal contacts and from registry websites. A questionnaire was sent to all identified registries, investigating age of registries, scope, method of coding, possible mapping to international terminologies as well as self-reported problems and suggestions for improvement. Results: Sixteen regional or national kidney biopsy registries were identified, of which 11 were older than 10 years. Most registries were located either in Europe (10/16) or in Asia (4/16). Registries most often use a proprietary coding system (12/16). Only a few of these coding systems were mapped to SNOMED CT (1), older SNOMED versions (2) or ERA-EDTA PRD (3). Lack of maintenance and updates of the coding system was the most commonly reported problem. Conclusions: There were large gaps in the global coverage of kidney biopsy registries. Limited use of international coding systems among existing registries hampers interoperability and exchange of data. The study underlines that the use of a common and uniform coding system is necessary to fully realize the potential of kidney biopsy registries.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Coding; Kidney biopsy registry; Nephropathology; Renal pathology; Systematic review

COL4A5-p.Gly624Asp is the Predominant Variant in Europe Associated With a Mild Alport Syndrome Phenotype - Krüger, Bastian M.; Jens, Annika; Neuhaus, Anna; Ćomić, Jasmina; Berutti, Riccardo; de Fallois, Jonathan; Petzold, Friederike; Münch, Johannes; Kowald, Jan; Lindner, Tom H.; Budde, Klemens; Brüning, Klara K.; et al. (Kidney International Reports, 2025)
Introduction: Pathogenic variants in COL4A3–5 are common causes of inherited kidney disease. The clinical presentation extends from classical Alport syndrome (AS) to focal segmental glomerulosclerosis (FSGS) without extrarenal manifestation. In this study, we aimed to assess the genetic and phenotypic spectrum, along with the associated natural histories, in a cohort of patients with AS from 3 tertiary centers in Central Europe. Methods: A total of 210 patients with disease causing variants in one of the COL4A3–5 genes were characterized and evaluated for genotype-phenotype correlations. In addition, 48 COL4A5-p.Gly624Asp carriers were analyzed for replication and pooled analysis. Results: COL4A5-p.Gly624Asp was by far the most common variant, accounting for 16% of all genetic diagnoses. These patients presented with overall milder renal phenotypes than patients with other COL4A5 missense variants and COL4A5 glycine-missense variants after age- and sex-matching. In patients lacking a wild-type allele (X-Linked AS [XLAS] males and autosomal recessive AS [ARAS]), histological AS was most frequently observed in kidney biopsies, and truncating variants were associated with increased disease severity. Conversely, in patients with a wild-type allele present (XLAS females and autosomal dominant AS [ADAS]), FSGS was more frequently observed. Predicted protein truncation was not inferior to missense alterations in terms of renal survival. Conclusion: The predominance of the European COL4A5 founder variant p.Gly624Asp allowed for the creation of the largest cohort of patients with an identical Alport variant to date, confirming the more favorable renal prognosis specific to this amino acid change. Allelic and gene dosage effects drive phenotypic differences and should be incorporated into future risk models.
CRIS-Team Scopus Importer:2025-04-01
Keywords: alport syndrome; chronic kidney disease; COL4A3; COL4A4; COL4A5; collagen type IV

Collagen Hydrogel Containing Polyethylenimine-Gold Nanoparticles for Drug Release and Enhanced Beating Properties of Engineered Cardiac Tissues - Roshanbinfar, Kaveh; Kolesnik-Gray, Maria; Angeloni, Miriam; Schrüfer, Stefan; Fiedler, Maren; Schubert, Dirk W.; Ferrazzi, Fulvia; Krstic, Vojislav; Engel, Felix (Advanced Healthcare Materials, 2023)
Cardiac tissue engineering is a promising strategy to prevent heart failure. However, several issues remain unsolved, including efficient electrical coupling and incorporating factors to enhance tissue maturation and vascularization. Herein, a biohybrid hydrogel that enhances beating properties of engineered cardiac tissues and allows drug release concurrently is developed. Gold nanoparticles (AuNPs) with different sizes (18–241 nm) and surface charges (33.9–55.4 mV) are synthesized by reducing gold (III) chloride trihydrate using branched polyethyleneimine (bPEI). These nanoparticles increase gel stiffness from ≈91 to ≈146 kPa, enhance electrical conductivity of collagen hydrogels from ≈40 to 49–68 mS cm−1, and allow slow and steady release of loaded drugs. Engineered cardiac tissues based on bPEI-AuNP-collagen hydrogels and either primary or human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes show enhanced beating properties. hiPSC-derived cardiomyocytes exhibit more aligned and wider sarcomeres in bPEI-AuNP-collagen hydrogels compared to collagen hydrogels. Furthermore, the presence of bPEI-AuNPs result in advanced electrical coupling evidenced by synchronous and homogenous calcium flux throughout the tissue. RNA-seq analyses are in agreement with these observations. Collectively, this data demonstrate the potential of bPEI-AuNP-collagen hydrogels to improve tissue engineering approaches to prevent heart failure and possibly treat diseases of other electrically sensitive tissues.
CRIS-Team Scopus Importer:2023-04-21
Keywords: collagen; gold nanoparticles; heart; tissue engineering

Colony-stimulating factor-1: a potential biomarker for lupus nephritis - Menke, Julia; Amann, Kerstin Ute; Cavagna, Lorenzo; Blettner, Maria; Weinmann, Arndt; Schwarting, Andreas; Kelley, Vicki R. (Journal of the American Society of Nephrology, 2015)
A noninvasive means to predict the onset and recurrence of lupus nephritis (LN) before overt renal injury is needed to optimize and individualize treatment. Colony-stimulating factor-1 (CSF-1) is expressed by kidney tubules at the onset of LN, increases with disease progression, and spills into the circulation in lupus-prone mice. We tested the hypothesis that amplified expression of CSF-1 detected in the serum or urine correlates with intrarenal CSF-1 expression and histopathology (increased macrophage accumulation, activity indices) and clinical kidney disease activity and predicts the onset and recurrence of nephritis in patients with systemic lupus erythematosus (SLE). We found increased serum or urine CSF-1 levels in patients with cutaneous, serositis, and musculoskeletal disease; however, the increase in CSF-1 levels was far greater in LN. Moreover, an elevation in serum or urine CSF-1 levels correlated with increasing intrarenal CSF-1 expression and histopathology. By longitudinally tracking patients, we found that elevated serum CSF-1 heralded the initial onset of disease, and a rise in serum or urine CSF-1 predicted recurrences of LN before clinical evidence of glomerular dysfunction and conventional serologic measures, even in patients with other manifestations of SLE. These findings indicate that serial monitoring for a rise in serum or urine CSF-1 levels in patients with SLE reflects kidney histopathology and may predict renal disease activity and the onset and recurrence of LN more accurately than conventional laboratory measures.
EVALuna2:25483

Comparison of different normalization strategies for the analysis of glomerular microRNAs in IgA nephropathy - Bockmeyer, Clemens L.; Saeuberlich, Karen; Wittig, Juliane; Esser, Marc; Röder, Sebastian; Vester, Udo; Hoyer, Peter F.; Agustian, Putri A.; Zeuschner, Philip; Amann, Kerstin Ute; Daniel, Christoph; Becker, Jan U. (Scientific Reports, 2016)
Small nucleolar RNAs (snoRNAs) have been used for normalization in glomerular microRNA (miRNA) quantification without confirmation of validity. Our aim was to identify glomerular reference miRNAs in IgA nephropathy. We compared miRNAs in human paraffin-embedded renal biopsies from patients with cellular-crescentic IgA-GN (n = 5; crescentic IgA-GN) and non-crescentic IgA-GN (n = 5; IgA-GN) to mild interstitial nephritis without glomerular abnormalities (controls, n = 5). Laser-microdissected glomeruli were used for expression profiling of 762 miRNAs by low-density TaqMan arrays (cards A and B). The comparison of different normalization methods (GeNormPlus, NormFinder, global mean and snoRNAs) in crescentic IgA-GN, IgA-GN and controls yielded similar results. However, levels of significance and the range of relative expression differed. In median, two normalization methods demonstrated similar results. GeNormPlus and NormFinder gave different top ranked reference miRNAs. Stability ranking for snoRNAs varied between cards A and B. In conclusion, we suggest the geometric mean of the most stable reference miRNAs found in GeNormPlus (miR-26b-5p), NormFinder (miR-28-5p) and snoRNAs (RNU44) as reference. It should be considered that significant differences could be missed using one particular normalization method. As a starting point for glomerular miRNA studies in IgA nephropathy we provide a library of miRNAs.
EVALuna2:25525

Complement 9 in amyloid deposits - Lux, Annelie; Gottwald, Juliane; Behrens, Hans-Michael; Daniel, Christoph; Amann, Kerstin Ute; Roecken, Christoph (Amyloid-Journal of Protein Folding Disorders, 2021)
Amyloidosis is a disease group caused by pathological aggregation and deposition of peptides in diverse tissue sites. Apart from the fibril protein, amyloid deposits frequently enclose non-fibrillar constituents. In routine diagnostics, we noticed the presence of complement 9 (C9) in amyloid. Based on this observation, we systematically explored the occurrence of C9 in amyloid. Apolipoprotein E (apoE), caspase 3 and complement 3 (C3) served as controls. From the Amyloid Registry Kiel, we retrieved 118 formalin-fixed and paraffin-embedded tissue samples, including eight different amyloid- and 18 different tissue types. The expression patterns were assessed immunohistochemically in relation to amyloid deposits. A literature search on proteomic data was performed. Amyloid deposits stained for C9 and apoE in 117 (99.2%) and 112 of 118 (94.9%) cases, respectively. A homogeneous immunostaining of the entire amyloid deposits was found in 75.4% (C9) and 61.9% (apoE) of the cases. Caspase 3 and C3 were present only in 22 (19.3%) of 114 and 20 (36%) of 55 assessable cases, respectively. Caspase 3 and C3 immunostaining rarely covered substantial areas of the amyloid deposits. The literature search on proteomic data confirmed the frequent detection of apoE and the occurrence of C9 and C3 in amyloid deposits. No data were found regarding caspase 3. Our findings demonstrate the ubiquitous, spatial and specific enrichment of C9 in amyloid deposits irrespective of amyloid-, organ- or tissue type. Our findings lend support to the hypothesis that amyloidosis might activate the complement cascade, which could lead to the formation of the membrane attack complex and cell death.
CRIS-Team WoS Importer:2021-06-11

Complement Activation in Kidneys of Patients With COVID-19 - Pfister, Frederick; Vonbrunn, Eva; Ries, Tajana; Jäck, Hans-Martin; Überla, Klaus; Lochnit, Günter; Sheriff, Ahmed; Herrmann, Martin; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Frontiers in Immunology, 2021)
Most patients who became critically ill following infection with COVID-19 develop severe acute respiratory syndrome (SARS) attributed to a maladaptive or inadequate immune response. The complement system is an important component of the innate immune system that is involved in the opsonization of viruses but also in triggering further immune cell responses. Complement activation was seen in plasma adsorber material that clogged during the treatment of critically ill patients with COVID-19. Apart from the lung, the kidney is the second most common organ affected by COVID-19. Using immunohistochemistry for complement factors C1q, MASP-2, C3c, C3d, C4d, and C5b-9 we investigated the involvement of the complement system in six kidney biopsies with acute kidney failure in different clinical settings and three kidneys from autopsy material of patients with COVID-19. Renal tissue was analyzed for signs of renal injury by detection of thrombus formation using CD61, endothelial cell rarefaction using the marker E-26 transformation specific-related gene (ERG-) and proliferation using proliferating cell nuclear antigen (PCNA)-staining. SARS-CoV-2 was detected by in situ hybridization and immunohistochemistry. Biopsies from patients with hemolytic uremic syndrome (HUS, n = 5), severe acute tubular injury (ATI, n = 7), zero biopsies with disseminated intravascular coagulation (DIC, n = 7) and 1 year protocol biopsies from renal transplants (Ctrl, n = 7) served as controls. In the material clogging plasma adsorbers used for extracorporeal therapy of patients with COVID-19 C3 was the dominant protein but collectin 11 and MASP-2 were also identified. SARS-CoV-2 was sporadically present in varying numbers in some biopsies from patients with COVID-19. The highest frequency of CD61-positive platelets was found in peritubular capillaries and arteries of COVID-19 infected renal specimens as compared to all controls. Apart from COVID-19 specimens, MASP-2 was detected in glomeruli with DIC and ATI. In contrast, the classical pathway (i.e. C1q) was hardly seen in COVID-19 biopsies. Both C3 cleavage products C3c and C3d were strongly detected in renal arteries but also occurs in glomerular capillaries of COVID-19 biopsies, while tubular C3d was stronger than C3c in biopsies from COVID-19 patients. The membrane attack complex C5b-9, demonstrating terminal pathway activation, was predominantly deposited in COVID-19 biopsies in peritubular capillaries, renal arterioles, and tubular basement membrane with similar or even higher frequency compared to controls. In conclusion, various complement pathways were activated in COVID-19 kidneys, the lectin pathway mainly in peritubular capillaries and in part the classical pathway in renal arteries whereas the alternative pathway seem to be crucial for tubular complement activation. Therefore, activation of the complement system might be involved in the worsening of renal injury. Complement inhibition might thus be a promising treatment option to prevent deregulated activation and subsequent collateral tissue injury.
CRIS-Team Scopus Importer:2021-03-05
Keywords: complement—immunological term; COVID-19; endothelial injury; kidney; lectin pathway activation

Complement Activation via the Lectin and Alternative Pathway in Patients With Severe COVID-19 - Niederreiter, Janina; Eck, Christine; Ries, Tajana; Hartmann, Arndt; Märkl, Bruno; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Frontiers in Immunology, 2022)
Complement plays an important role in the direct defense to pathogens, but can also activate immune cells and the release of pro-inflammatory cytokines. However, in critically ill patients with COVID-19 the immune system is inadequately activated leading to severe acute respiratory syndrome (SARS) and acute kidney injury, which is associated with higher mortality. Therefore, we characterized local complement deposition as a sign of activation in both lungs and kidneys from patients with severe COVID-19. Using immunohistochemistry we investigated deposition of complement factors C1q, MASP-2, factor D (CFD), C3c, C3d and C5b-9 as well as myeloperoxidase (MPO) positive neutrophils and SARS-CoV-2 virus particles in lungs and kidneys from 38 patients who died from COVID-19. In addition, tissue damage was analyzed using semi-quantitative scores followed by correlation with complement deposition. Autopsy material from non-COVID patients who died from cardiovascular causes, cerebral hemorrhage and pulmonary embolism served as control (n=8). Lung injury in samples from COVID-19 patients was significantly more pronounced compared to controls with formation of hyaline membranes, thrombi and edema. In addition, in the kidney tubular injury was higher in these patients and correlated with lung injury (r=0.361*). In autopsy samples SARS-CoV-2 spike protein was detected in 22% of the lungs of COVID-19 patients but was lacking in kidneys. Complement activation was significantly stronger in lung samples from patients with COVID-19 via the lectin and alternative pathway as indicated by deposition of MASP-2, CFD, C3d and C5b9. Deposits in the lung were predominantly detected along the alveolar septa, the hyaline membranes and in the alveolar lumina. In the kidney, complement was significantly more deposited in patients with COVID-19 in peritubular capillaries and tubular basement membranes. Renal COVID-19-induced complement activation occurred via the lectin pathway, while activation of the alternative pathway was similar in both groups. Furthermore, MPO-positive neutrophils were found in significantly higher numbers in lungs and kidneys of COVID-19 patients and correlated with local MASP-2 deposition. In conclusion, in patients who died from SARS-CoV-2 infection complement was activated in both lungs and kidneys indicating that complement might be involved in systemic worsening of the inflammatory response. Complement inhibition might thus be a promising treatment option to prevent deregulated activation and subsequent collateral tissue injury in COVID-19.
CRIS-Team Scopus Importer:2022-03-11
Keywords: autopsy; complement deposition; COVID-19; kidney; lectin pathway; lung

Complement Factor H-Related 5-Hybrid Proteins Anchor Properdin and Activate Complement at Self-Surfaces - Chen, Qian; Manzke, Melanie; Hartmann, Andrea; Büttner, Maike; Amann, Kerstin Ute; Pauly, Diana; Wiesener, Michael; Skerka, Christine; Zipfel, Peter F. (Journal of the American Society of Nephrology, 2016)
C3 glomerulopathy (C3G) is a severe kidney disease for which no specific therapy exists. The causes of C3G are heterogeneous, and defective complement regulation is often linked to C3G pathogenesis. Copy number variations in the complement factor H-related (CFHR) gene cluster on chromosome 1q32 and CFHR5 mutant proteins associate with this disease. Here, we identified CFHR5 as a pattern recognition protein that binds to damaged human endothelial cell surfaces and to properdin, the human complement activator. We found the two N-terminal short consensus repeat domains of CFHR5 contact properdin and mediate dimer formation. These properdin-binding segments are duplicated in two mutant CFHR5 proteins, CFHR2-CFHR5Hyb from German patients with C3G and CFHR5Dup from Cypriot patients with C3G. Each of these mutated proteins assembled into large multimeric complexes and, compared to CFHR5, bound damaged human cell surfaces and properdin with greater intensity and exacerbated local complement activation. This enhanced surface binding and properdin recruitment was further evidenced in the mesangia of a transplanted and explanted kidney from a German patient with a CFHR2-CFHR5Hyb protein. Enhanced properdin staining correlated with local complement activation with C3b and C5b-9 deposition on the mesangial cell surface in vitro This gain of function in complement activation for two disease-associated CFHR5 mutants describes a new disease mechanism of C3G, which is relevant for defining appropriate treatment options for this disorder.
EVALuna2:3837

Complement factor H-related hybrid protein deregulates complement in dense deposit disease - Chen, Qian; Wiesener, Michael; Eberhardt, Hannes U.; Hartmann, Andrea; Uzonyi, Barbara; Kirschfink, Michael; Amann, Kerstin Ute; Büttner, Maike; Goodship, Tim; Hugo, Christian; Skerka, Christine; Zipfel, Peter F. (Journal of Clinical Investigation, 2014)
The renal disorder C3 glomerulopathy with dense deposit disease (C3G-DDD) pattern results from complement dysfunction and primarily affects children and young adults. There is no effective treatment, and patients often progress to end-stage renal failure. A small fraction of C3G-DDD cases linked to factor H or C3 gene mutations as well as autoantibodies have been reported. Here, we examined an index family with 2 patients with C3G-DDD and identified a chromosomal deletion in the complement factor H-related (CFHR) gene cluster. This deletion resulted in expression of a hybrid CFHR2-CFHR5 plasma protein. The recombinant hybrid protein stabilized the C3 convertase and reduced factor H-mediated convertase decay. One patient was refractory to plasma replacement and exchange therapy, as evidenced by the hybrid protein quickly returning to pretreatment plasma levels. Subsequently, complement inhibitors were tested on serum from the patient for their ability to block activity of CFHR2-CFHR5. Soluble CR1 restored defective C3 convertase regulation; however, neither eculizumab nor tagged compstatin had any effect. Our findings provide insight into the importance of CFHR proteins for C3 convertase regulation and identify a genetic variation in the CFHR gene cluster that promotes C3G-DDD. Monitoring copy number and sequence variations in the CFHR gene cluster in C3G-DDD and kidney patients with C3G-DDD variations will help guide treatment strategies.
EVALuna2:3659

Complement Inhibition in Kidney Transplantation: Where Are We Now? - Vonbrunn, Eva; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Biodrugs, 2022)
Kidney transplantation is a life-saving strategy for patients with end-stage renal disease. Although progress has been made in the field of transplantation medicine in recent decades in terms of surgical techniques and immunosuppression, long-term organ survival remains a challenge. Also, for reasons of organ shortage, there is an unmet need for new therapeutic approaches to improve the long-term survival of transplants. There is increasing evidence that the complement system plays a crucial role in various pathological events after transplantation, including ischemia/reperfusion injury as well as rejection episodes. The complement system is part of the innate immune system and plays a crucial role in the defense against pathogens but is also involved in tissue homeostasis. However, the tightly regulated complement system can become dysregulated or activated by non-infectious stimuli, then targeting the organism’s own cells and leading to inflammatory tissue damage that exacerbates injury. In this review, we will highlight the role of the complement system after transplantation and discuss ongoing and potential therapeutic approaches.
CRIS-Team Scopus Importer:2022-12-23

Complement in Renal Disease as a Potential Contributor to Arterial Hypertension - Fischer, Lisa-Maren; Fichte, Laura A.; Büttner-Herold, Maike; Ferrazzi, Fulvia; Amann, Kerstin Ute; Benz, Kerstin; Daniel, Christoph (Kidney & Blood Pressure Research, 2021)
Objective: Complement deposition is prevalent in kidney biopsies of patients with arterial hypertension and hypertensive nephropathy, but an association of hypertension and complement deposition or involvement of complement in the pathogenesis of hypertensive nephropathy has not been shown to date. Methods: In this study, we analyzed complement C1q and C3c deposition in a rat model of overload and hypertension by subtotal nephrectomy (SNX) and in archival human renal biopsies from 217 patients with known hypertension and 91 control patients with no history of hypertension using semiquantitative scoring of C1q and C3c immunohistochemistry and correlation with parameters of renal function. To address whether complement was only passively deposited or actively expressed by renal cells, C1q and C3 mRNA expression were additionally analyzed. Results: Glomerular C1q and C3c complement deposition were significantly higher in kidneys of hypertensive SNX rats and hypertensive compared to nonhypertensive patients. Mean arterial blood pressure (BP) in SNX rats correlated well with the amount of glomerular C1q and C3c deposition and with left ventricular weight, as an indirect parameter of high BP. Quantitative mRNA analysis showed that C3 was not only deposited but also actively produced by glomerular cells of hypertensive SNX rats and in human renal biopsies. Of note, in patients CKD-stage correlated significantly with the intensity of glomerular C3c staining, but not with that of C1q. Conclusion: Renal complement deposition correlated with experimental hypertension as well as the presence of hypertension in a variety of renal diseases. To answer the question, if and how exactly renal complement is causative for the pathogenesis of arterial hypertension in men, further studies are needed.
CRIS-Team WoS Importer:2021-06-11
Keywords: Kidney; Complement deposition; Hypertension; Renal disease

Complex reinnervation pattern after unilateral renal denervation in rats - Rodionova, Kristina; Fiedler, Christian; Günther, Franziska; Grouzmann, Eric; Neuhuber, Winfried; Fischer, Michael; Ott, Christian; Linz, Peter; Freisinger, Wolfgang; Heinlein, Sonja; Schmidt, Stefan; Schmieder, Roland; et al. (American Journal of Physiology-Regulatory Integrative and Comparative Physiology, 2016)
Renal denervation (DNX) is a treatment for resistant arterial hypertension. Efferent sympathetic nerves regrow, but reinnervation by renal afferent nerves has only recently been shown in the renal pelvis of rats after unilateral DNX. We examined intrarenal perivascular afferent and sympathetic efferent nerves after unilateral surgical DNX. Tyrosine hydroxylase (TH), CGRP, and smooth muscle actin were identified in kidney sections from 12 Sprague-Dawley rats, to distinguish afferents, efferents, and vasculature. DNX kidneys and nondenervated kidneys were examined 1, 4, and 12 wk after DNX. Tissue levels of CGRP and norepinephrine (NE) were measured with ELISA and mass spectrometry, respectively. DNX decreased TH and CGRP labeling by 90% and 95%, respectively (P < 0.05) within 1 wk. After 12 wk TH and CGRP labeling returned to baseline with a shift toward afferent innervation (P < 0.05). Nondenervated kidneys showed a doubling of both labels within 12 wk (P < 0.05). CGRP content decreased by 72% [3.2 ± 0.3 vs. 0.9 ± 0.2 ng/gkidney; P < 0.05] and NA by 78% [1.1 ± 0.1 vs. 0.2 ± 0.1 pmol/mgkidney; P < 0.05] 1 wk after DNX. After 12 wk, CGRP, but not NE, content in DNX kidneys was fully recovered, with no changes in the nondenervated kidneys. The use of phenol in the DNX procedure did not influence this result. We found morphological reinnervation and transmitter recovery of afferents within 12 wk after DNX. Despite morphological evidence of sympathetic regrowth, NE content did not fully recover. These results suggest a long-term net surplus of afferent influence on the DNX kidney may be contributing to the blood pressure lowering effect of DNX.
EVALuna2:3840

Consensus definitions for glomerular lesions by light and electron microscopy: recommendations from a working group of the Renal Pathology Society - Haas, Mark; Seshan, Surya V.; Barisoni, Laura; Amann, Kerstin Ute; Bajema, Ingeborg M.; Becker, Jan Ulrich; Joh, Kensuke; Ljubanovic, Danica; Roberts, Ian S.D.; Roelofs, Joris J.; Sethi, Sanjeev; Zeng, Caihong; et al. (Kidney International, 2020)
Over the past 2 decades, scoring systems for multiple glomerular diseases have emerged, as have consortia of pathologists and nephrologists for the study of glomerular diseases, including correlation of pathologic findings with clinical features and outcomes. However, one important limitation faced by members of these consortia and other renal pathologists and nephrologists in both investigative work and routine practice remains a lack of uniformity and precision in clearly defining the morphologic lesions on which the scoring systems are based. In response to this issue, the Renal Pathology Society organized a working group to identify the most frequently identified glomerular lesions observed by light microscopy and electron microscopy, review the literature to capture the published definitions most often used for each, and determine consensus terms and definitions for each lesion in a series of online and in-person meetings. The defined lesions or abnormal findings are not specific for any individual disease or subset of diseases, but rather can be applied across the full spectrum of glomerular diseases and within the context of the different scoring systems used for evaluating and reporting these diseases. In addition to facilitating glomerular disease research, standardized terms and definitions should help harmonize reporting of medical kidney diseases worldwide and lead to more-precise diagnoses and improved patient care.
CRIS-Team Scopus Importer:2020-11-06
Keywords: electron microscopy; glomerulonephritis; glomerulus; kidney biopsy; renal pathology

Control of PD-L1 expression in CLL-cells by stromal triggering of the Notch-c-Myc-EZH2 oncogenic signaling axis - Böttcher, Martin; Bruns, Heiko; Lu, Junyan; Chartomatsidou, E.; Papakonstantinou, N.; Mentz, K.; Büttner-Herold, Maike; Zenz, Thorsten; Herling, M.; Huber, Wolfgang; Ghia, P.; Stamatopoulos, Kostas; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Correction to: Long-term endothelial dysfunction in irradiated vessels: an immunohistochemical analysis (Strahlentherapie und Onkologie, (2019), 195, 1, (52-61), 10.1007/s00066-018-1382-3) - Preidl, Raimund; Möbius, Patrick; Weber, Manuel; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Kesting, Marco Rainer; Geppert, Carol-Immanuel; Wehrhan, Falk (Strahlentherapie und Onkologie, 2020)
The original version of this article unfortunately contained a mistake. The correct version of the Acknowledgements is given below: Acknowledgements This study was supported by the ELAN-Fond (University of Erlangen-Nürnberg). The authors thank Carsten Kronauer and Florian Obstmeier for conducting the immunohistochemical staining and detecting the expression of mediators.
CRIS-Team Scopus Importer:2020-01-21

Correlation of enhanced thrombospondin-1 expression, TGF-β signalling and proteinuria in human type-2 diabetic nephropathy - Hohenstein, Bernd; Daniel, Christoph; Hausknecht, Birgit; Boehmer, Kirsten; Riess, Regine; Amann, Kerstin Ute; Hugo, Christian (Nephrology Dialysis Transplantation, 2008)
Background. Activation of the thrombospondin-1 (TSP-1)-TGF-β pathway by glucose and the relevance of TSP-1-dependent activation of TGF-β for renal matrix expansion, renal fibrosis and sclerosis have previously been demonstrated by our group in in vivo and in vitro studies. Design and methods. We investigated renal biopsies (n = 40) and clinical data (n = 30) of patients with diabetic nephropathy. Ten kidneys without evidence of renal disease served as controls. Glomerular and cortical expression of TSP-1, p-smad2/3, fibrosis and glomerular sclerosis (PAS) were assessed by immunhistochemical staining and related with clinical data. Results. Glomerular (g) and cortical (c) TSP-1 were increased during diabetic nephropathy (g: 2.62 ± 2.65; c: 4.5 ± 4.2) compared to controls (g: 0.67 ± 0.7; c: 1.5 ± 1.2). P-smad2/3 was significantly increased (g: 16.7 ± 12.9; c: 148.7 ± 92.8) compared to controls (g: 7.1 ± 3.6; c: 55 ± 25; P < 0.05). TSP-1 was coexpressed with p-smad2/3 as an indicator of TGF-β activation. TSP-1 correlated with enhanced tubulointerstitial p-smad2/3 positivity (r = 0.39 and r = 0.4, P < 0.05) and glomerular p-smad2/3 correlated with proteinuria (r = 0.35, P < 0.05). Conclusions. In summary, the present study suggests a functional activity of the TSP-1/TGF-β axis, especially in the tubulointerstitium of patients with diabetic nephropathy. The positive correlation of glomerular p-smad2/3 positivity with proteinuria further supports the importance of the TSP-1/TGF-β system as a relevant mechanism for progression of human type-2 diabetic nephropathy. © The Author [2008].
Created from Fastlane, Scopus look-up
Keywords: Diabetic nephropathy; Proteinuria; TGF-β; TSP-1; Tubulointerstitium

Correlation of Hif1a expression of primary oral squamous cell carcinomas with histomorphologic parameters and macrophage polarization - Wehrhan, Falk; Möbius, Patrick; Amann, Kerstin Ute; Geppert, Carol-Immanuel; Preidl, Raimund; Ries, Jutta; Neukam, Friedrich Wilhelm; Weber, Manuel (2018)
EVALuna2:34066

Correlations Between Interleukin-11 Expression and Hypertensive Kidney Injury in a Rat Model of Renovascular Hypertension - Menendez-Castro, Carlos; Cordasic, Nada; Dambietz, Thomas; Veelken, Roland; Amann, Kerstin Ute; Hartner, Andrea; Hilgers, Karl Friedrich (American Journal of Hypertension, 2020)
BACKGROUND: Interleukin-11 (IL-11) is a pleiotropic cytokine of the interleukin-6 family. Recent studies revealed its crucial role in the development of cardiovascular fibrosis. In this study we examined IL-11 expression levels in the heart and the kidney exposed to high blood pressure in renovascular hypertensive rats and their correlations to fibrotic markers and kidney injury. METHODS: Two-kidney, one-clip renovascular hypertension (2K1C) was induced in rats. IL-11 expression was measured by real-time polymerase chain reaction in the left ventricle and the right kidney. The correlation of cardiac IL-11 expression with biomarkers of renal fibrosis was assessed. We further investigated IL-11 expression in 2K1C rats grouped into rats with malignant vs. nonmalignant hypertension (distinguishing criteria: weight loss, number of fibrinoid necrosis, and onion skin lesions). RESULTS: Thirty-five days after clipping, mean arterial pressure was significantly increased in 2K1C. Renal IL-11 expression was elevated in 2K1C. In the heart there was only a trend toward higher IL-11 expression in 2K1C. IL-11 in the kidney in 2K1C correlated with the expression of transforming growth factor (TGF)-β1/2, collagens, fibronectin, osteopontin, as well as tissue inhibitors of metalloprotease 1/2. There were also correlations of IL-11 with tissue collagen expansion, number of activated fibroblasts and serum creatinine, but no correlation with mean arterial pressure. Renal expression of IL-11 was highest in rats with malignant hypertension. CONCLUSIONS: Renal IL-11 expression of renovascular hypertensive rats is markedly increased and correlates with profibrotic markers and loss of function and might therefore serve as a biomarker for the severity of hypertensive nephrosclerosis.
CRIS-Team Scopus Importer:2020-04-14
Keywords: blood pressure; hypertension; interleukin-11 (IL-11); malignant hypertension; renal fibrosis; two-kidney one-clip renovascular hypertension (2K1C)

Corrigendum: A TNFR2-specific TNF fusion protein with improved in vivo activity. - Gamboa Vargas, Juan; Wagner, Jennifer; Shaikh, Haroon; Lang, Isabell; Medler, Juliane; Anany, Mohamed; Steinfatt, Tim; Peña Mosca, Josefina; Haack, Stephanie; Dahlhoff, Julia; Büttner-Herold, Maike; Graf, Carolin; et al. (Frontiers in Immunology, 2023)
[This corrects the article DOI: 10.3389/fimmu.2022.888274.].
EVALuna2:547440

Corrigendum: Complement activation via the lectin and alternative pathway in patients with severe COVID-19(Front. Immunol., (2022), 13, (835156), 10.3389/fimmu.2022.835156) - Niederreiter, Janina; Eck, Christine; Ries, Tajana; Hartmann, Arndt; Märkl, Bruno; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Frontiers in Immunology, 2023)
In the published article, information in the Acknowledgments was mistakenly not included in the publication. A correction has been made to Acknowledgments:
CRIS-Team Scopus Importer:2023-10-20
Keywords: autopsy; complement deposition; COVID-19; kidney; lectin pathway; lung

COVID-19 effects on the kidney. - Amann, Kerstin Ute; Boor, P.; Wiech, T.; Singh, Jeeshan; Vonbrunn, Eva; Knöll, Antje; Hermann, Maike; Büttner-Herold, Maike; Daniel, Christoph; Hartmann, Arndt (Pathologe, 2021)
Apart from pulmonary disease, acute kidney injury (AKI) is one of the most frequent and most severe organ complications in severe coronavirus disease 2019 (COVID-19). The SARS-CoV‑2 virus has been detected in renal tissue. Patients with chronic kidney disease (CKD) before and on dialysis and specifically renal transplant patients represent a particularly vulnerable population. The increasing number of COVID-19 infected patients with renal involvement led to an evolving interest in the analysis of its pathophysiology, morphology and modes of virus detection in the kidney. Meanwhile, there are ample data from several autopsy and kidney biopsy studies that differ in the quantity of cases as well as in their quality. While the detection of SARS-CoV‑2 RNA in the kidney leads to reproducible results, the use of electron microscopy for visualisation of the virus is difficult and currently critically discussed due to various artefacts. The exact contribution of indirect or direct effects on the kidney in COVID-19 are not yet known and are currently the focus of intensive research.
EVALuna2:421391

COVID-19 effects on the kidney - Amann, Kerstin Ute; Boor, P.; Wiech, T.; Singh, Jeeshan; Vonbrunn, Eva; Knöll, Antje; Hermann, Maike; Büttner-Herold, Maike; Daniel, Christoph; Hartmann, Arndt (Pathologe, 2021)
Apart from pulmonary disease, acute kidney injury (AKI) is one of the most frequent and most severe organ complications in severe coronavirus disease 2019 (COVID-19). The SARS-CoV-2 virus has been detected in renal tissue. Patients with chronic kidney disease (CKD) before and on dialysis and specifically renal transplant patients represent a particularly vulnerable population. The increasing number of COVID-19 infected patients with renal involvement led to an evolving interest in the analysis of its pathophysiology, morphology and modes of virus detection in the kidney. Meanwhile, there are ample data from several autopsy and kidney biopsy studies that differ in the quantity of cases as well as in their quality. While the detection of SARS-CoV-2 RNA in the kidney leads to reproducible results, the use of electron microscopy for visualisation of the virus is difficult and currently critically discussed due to various artefacts. The exact contribution of indirect or direct effects on the kidney in COVID-19 are not yet known and are currently the focus of intensive research.
CRIS-Team WoS Importer:2021-02-19

COVID-19 und Nierenbefall - Amann, Kerstin Ute; Boor, P.; Wiech, T. (Nephrologe, 2020)
Apart from the pulmonary disease, acute kidney injury is one of the most frequent and most severe organ complications in severe coronavirus disease 2019 (COVID-19). Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) could also be detected in renal tissue. Patients with chronic kidney disease and on dialysis as well as kidney transplantation patients represent a particularly vulnerable population. The increasing number of patients infected with SARS-CoV‑2 has aroused increased interest in the exact pathophysiology and morphology of kidney damage as well as the direct detection of the virus in the kidneys, which in contrast to the lungs is overall more difficult to perform. Meanwhile, data from several large autopsy and kidney biopsy studies are now available. While the detection of SARS-CoV‑2 RNA in tissue leads to consistently reproducible results, the use of electron microscopy for visualization of the virus is critically discussed due to various artefacts. The exact and direct effects of SARS-CoV‑2 on the kidneys are not yet known in detail and are currently the focus of intensive research.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Acute renal insufficiency; Acute tubular injury; Chronic kidney disease; Coronavirus; Virus detection

CRISPR-mediated fluorescent tagging of endogenous PCM1 enables live cell imaging of non-centrosomal MTOC formation in muscle cells - Becker, Robert; Engel, Felix (2018)
EVALuna2:34442

Critical size defect regeneration using PEG-mediated BMP-2 gene delivery and the use of cell occlusive barrier membranes - the osteopromotive principle revisited - Wehrhan, Falk; Amann, Kerstin Ute; Molenberg, Aart; Lutz, Rainer; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas (Clinical Oral Implants Research, 2013)
Objective: The objective of this study was to investigate if osseous regeneration can be accelerated by involvement of periosteal tissue. Bone defect regeneration could be accelerated by the involvement of periosteal tissue if osteogenic cell signalling is maintained within the defect. It was questioned if local cell-mediated BMP-2 gene delivery makes a cell occlusive membrane dispensable during bone critical size defect regeneration. Methods: PEG matrix (degradation time 10 days) and PEG membrane (degradation time 120 days) were used in the pig calvarial model. Cylindrical (1 × 1 cm) critical size defects (CSD) (9 per animal; 20 animals) were filled with: (i) particulated autologous bone, covered with PEG membrane (group 1); (ii) HA/TCP, covered with PEG membrane (group 2); (iii) HA/TCP, mixed with PEG matrix (group 3); and (iv) HA/TCP mixed with BMP-2-transfected osteoblasts and PEG matrix (group 4). BMP-2/4 gene transfer: liposomal in vitro transfection of BMP-2/V5-tag fusion-protein. Quantitative histomorphometry (toluidine blue staining) after 2, 4 and 12 weeks assessed bone formation. Semiquantitative immunohistochemistry estimated the expression of BMP-2, V5-tag, Runx-2 and Sox9. Results: PEG matrix embedded BMP-2 expressing cells presented higher bone formation (P < 0.05) than HA/TCP + PEG matrix defect filling or PEG membrane covering (HA/TCP filling) after 12 weeks. Highest expression of BMP-2, Runx-2 and lowest expression of fibrous tissue marker Sox9 was seen in the BMP-2 group. Conclusion: PEG matrix embedded BMP-2 expressing cells are capable to maintain osteogenic signalling and to accelerate osseous defect regeneration in absence of a cell occlusive membrane. © 2012 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2024-05-13
Keywords: BMP; Bone regeneration; Gene transfer; Hydrogel; Immunohistochemistry; Osteogenesis

CSF2-dependent monocyte education in the pathogenesis of ANCA-induced glomerulonephritis - Rousselle, Anthony; Sonnemann, Janis; Amann, Kerstin Ute; Mildner, Alexander; Lodka, Dorte; Kling, Lovis; Bieringer, Markus; Schneider, Udo; Leutz, Achim; Enghard, Philipp; Kettritz, Ralph; Schreiber, Adrian (Annals of the Rheumatic Diseases, 2022)
Objectives Myeloid cell activation by antineutrophil cytoplasmic antibody (ANCA) is pivotal for necrotising vasculitis, including necrotising crescentic glomerulonephritis (NCGN). In contrast to neutrophils, the contribution of classical monocyte (CM) and non-classical monocyte (NCM) remains poorly defined. We tested the hypothesis that CMs contribute to antineutrophil cytoplasmic antibody-associated vasculitis (AAV) and that colony-stimulating factor-2 (CSF2, granulocyte-macrophage colony-stimulating factor (GM-CSF)) is an important monocyte-directed disease modifier. Methods Myeloperoxidase (MPO)-immunised MPO-/- mice were transplanted with haematopoietic cells from wild-type (WT) mice, C-C chemokine receptor 2 (CCR2)(-/-) mice to abrogate CM, or transcription factor CCAAT-enhancer-binding protein beta (C/EBP beta)(-/-) mice to reduce NCM, respectively. Monocytes were stimulated with CSF2, and CSF2 receptor subunit beta (CSF2rb)-deficient mice were used. Urinary monocytes and CSF2 were quantified and kidney Csf2 expression was analysed. CSF2-blocking antibody was used in the nephrotoxic nephritis (NTN) model. Results Compared with WT mice, CCR2(-/-) chimeric mice showed reduced circulating CM and were protected from NCGN. C/EBP beta(-/-) chimeric mice lacked NCM but developed NCGN similar to WT chimeric mice. Kidney and urinary CSF2 were upregulated in AAV mice. CSF2 increased the ability of ANCA-stimulated monocytes to generate interleukin-1 beta and to promote T(H)17 effector cell polarisation. CSF2rb(-/-) chimeric mice harboured reduced numbers of kidney T(H)17 cells and were protected from NCGN. CSF2 neutralisation reduced renal damage in the NTN model. Finally, patients with active AAV displayed increased urinary CM numbers, CSF2 levels and expression of GM-CSF in infiltrating renal cells. Conclusions CMs but not NCMs are important for inducing kidney damage in AAV. CSF2 is a crucial pathological factor by modulating monocyte proinflammatory functions and thereby T(H)17 cell polarisation.
CRIS-Team WoS Importer:2022-04-29

Cutting-edge microangio-CT: new dimensions in vascular imaging and kidney morphometry - Hlushchuk, Ruslan; Zubler, Cédric; Barré, Sébastien; Shokiche, Carlos Correa; Schaad, Laura; Röthlisberger, Raphael; Wnuk, Monika; Daniel, Christoph; Khoma, Oleksiy; Tschanz, Stefan A.; Reyes, Mauricio; Djonov, Valentin (American Journal of Physiology-Renal Physiology, 2017)
In the last decades the contrast-enhanced microCT-imaging of whole animal kidney became increasingly important. The visualization was mainly limited to middle-sized vessels. Since modern desktop microCT-scanners provide the necessary detail resolution, we developed an approach for rapid visualization and consistent assessment of kidney vasculature and glomeruli number. This method is based on ?Angiofil®, a new polymerizing contrast agent with homogenous X-ray absorption, which provides continuous filling of the complete vasculature and enables correlative imaging approaches. For rapid and reliable kidney morphometry the microangioCT-datasets from GDNF+/- mice and their wildtype littermates were used. The results were obtained much faster compared to the current gold standard, histology-based stereology, and without processing artefacts. The histology-based morphometry was afterwards done on the same kidneys. Both approaches revealed that the GDNF+/- male mice had more than 30% fewer glomeruli. Futhermore, our approach allows defining sites of interest for further histological investigation, i.e., correlative morphology. The polymerized ?Angiofil stays in perfused vessels and is auto-fluorescent what greatly facilitates matching of histological sections with microangioCT-data. The presented approach is time-efficient and reliable qualitative and quantitative methodology. Besides glomerular morphometry the microangioCT-data can be used for qualitative and quantitative analysis of the kidney vasculature and correlative morphology.
EVALuna2:25561

CXCL5 drives neutrophil recruitment in TH17-mediated GN - Disteldorf, Erik M.; Krebs, Christian F.; Paust, Hans-Joachim; Turner, Jan-Eric; Nouailles, Geraldine; Tittel, Andre; Meyer-Schwesinger, Catherine; Stege, Gesa; Brix, Silke; Velden, Joachim; Wiech, Thorsten; Helmchen, Udo; et al. (Journal of the American Society of Nephrology, 2015)
Neutrophil trafficking to sites of inflammation is essential for the defense against bacterial and fungal infections, but also contributes to tissue damage in TH17-mediated autoimmunity. This process is regulated by chemokines, which often show an overlapping expression pattern and function in pathogen- and autoimmune-induced inflammatory reactions. Using a murine model of crescentic GN, we show that the pathogenic TH17/IL-17 immune response induces chemokine (C-X-C motif) ligand 5 (CXCL5) expression in kidney tubular cells, which recruits destructive neutrophils that contribute to renal tissue injury. By contrast, CXCL5 was dispensable for neutrophil recruitment and effective bacterial clearance in a murine model of acute bacterial pyelonephritis. In line with these findings, CXCL5 expression was highly upregulated in the kidneys of patients with ANCA-associated crescentic GN as opposed to patients with acute bacterial pyelonephritis. Our data therefore identify CXCL5 as a potential therapeutic target for the restriction of pathogenic neutrophil infiltration in TH17-mediated autoimmune diseases while leaving intact the neutrophil function in protective immunity against invading pathogens.
EVALuna2:25509

Cyclosporine A responsive congenital nephrotic syndrome with single heterozygous variants in NPHS1, NPHS2, and PLCE1 - Eichinger, Anna; Ponsel, Sabine; Bergmann, Carsten; Guenthner, Roman; Hoefele, Julia; Amann, Kerstin Ute; Lange-Sperandio, Baerbel (Pediatric Nephrology, 2018)
BACKGROUND: Congenital nephrotic syndrome (CNS) is primarily a monogenetic disease, with the majority of cases due to changes in five different genes: the nephrin (NPHS1), podocin (NPHS2), Wilms tumor 1 (WT1), laminin ß2 (LAMB2), and phospholipase C epsilon 1 (PLCE1, NPHS3) gene. Usually CNS is not responsive to immunosuppressive therapy, but treatment with ACE inhibitors, AT1 receptor blockade and/or indomethacin can reduce proteinuria. If the disease progresses to end-stage renal disease, kidney transplantation is the therapy of choice. CASE-DIAGNOSIS: Here, we present the case of a 4-month-old girl with congenital nephrotic syndrome. Upon admission, the patient presented with life-threatening anasarca, hypoalbuminemia, proteinuria, and impaired growth. There was no evidence of an infectious or immunological etiology. The genetic evaluation revealed a heterozygous variant in NPHS1 (p.Arg207Trp), in NPHS2 (p.Ser95Phe) as well as in PLCE1 (p.Ala1045Ser) and did not explain CNS. In addition to daily parenteral albumin infusions plus furosemide, a pharmacological antiproteinuric therapy was started to reduce protein excretion. Based on the genetic results, immunosuppressive therapy with prednisolone was initiated, but without response. However, following cyclosporine A treatment, the patient achieved complete remission and now has good renal function, growth, and development. CONCLUSIONS: A profound search for the cause of CNS is necessary but has its limitations. The therapeutic strategy should be adapted when the etiology remains unclear.
EVALuna2:34430

Daratumumab for the treatment of refractory ANCA-associated vasculitis - Ostendorf, Lennard; Burns, Marie; Wagner, Dimitrios Laurin; Enghard, Philipp; Amann, Kerstin Ute; Mei, Henrik; Eckardt, Kai-Uwe; Seelow, Evelyn; Schreiber, Adrian (RMD Open, 2023)
Objective Treatment-refractory antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a life-threatening condition without evidence-based treatment options. One emerging treatment option for several antibody-mediated autoimmune diseases is the anti-CD38 antibody daratumumab, which depletes autoantibody-secreting plasma cells.Methods We treated two patients with severe life-threatening AAV with renal and pulmonary manifestation despite induction therapy with rituximab and cyclophosphamide with four to eight doses of 1800 mg daratumumab. We followed clinical and immunological responses.Results The first patient with myeloperoxidase-ANCA-positive microscopic polyangiitis had resolution of pneumonitis and pleuritis and stabilisation of kidney function after daratumumab. The second patient with proteinase 3-ANCA-positive granulomatosis with polyangiitis, diffuse alveolar haemorrhage necessitating extracorporeal membrane oxygenation (ECMO) and acute kidney failure, requiring kidney replacement therapy, was weaned off ECMO, mechanical ventilation and dialysis and discharged home after daratumumab. Clinical improvement was paralleled by a strong reduction in serum ANCA levels as well as total IgG, indicating depletion of plasma cells. Apart from the depletion of CD38+ natural killer cells, blood leucocyte levels were not notably influenced by daratumumab. Only mild adverse events, such as hypogammaglobulinaemia and an upper respiratory tract infection occurred.Conclusion Daratumumab was safe and effective in inducing remission in two patients with severe treatment-refractory AAV, warranting prospective clinical trials to establish safety and efficacy.
CRIS-Team Scopus Importer:2023-01-20
Keywords: Autoimmune Diseases; Systemic vasculitis; Treatment

Darbepoetin alpha reduces oxidative stress and chronic inflammation in atherosclerotic lesions of apo e deficient mice in experimental renal failure - Arend, Nicole; Hilgers, Karl Friedrich; Campean, Valentina; Karpe, Britta; Cordasic, Nada; Klanke, Bernd; Amann, Kerstin Ute (PLoS ONE, 2014)
Cardiovascular morbidity and mortality is very important in patients with chronic renal failure. This occurs even in mild impairment of renal function and may be related to oxidative stress and chronic inflammation. The nephrectomized apo E knockout mouse is an accepted model for evaluating atherosclerosis in renal dysfunction. Erythropoietin derivates showed anti-oxidative and anti-inflammatory effects. Therefore, this study evaluates the effects of Darbepoetin on markers of oxidative stress and chronic inflammation in atherosclerotic lesions in apo E knockout mice with renal dysfunction.Apo E knockout mice underwent unilateral (Unx, n = 20) or subtotal (Snx, n = 26) nephrectomy or sham operation (Sham, n = 16). Mice of each group were either treated with Darbepoetin or saline solution, a part of Snx mice received a tenfold higher dose of Darbepoetin. The aortic plaques were measured and morphologically characterized. Additional immunhistochemical analyses were performed on tissue samples taken from the heart and the aorta.Both Unx and Snx mice showed increased expression of markers of oxidative stress and chronic inflammation. While aortic plaque size was not different, Snx mice showed advanced plaque stages when compared to Unx mice. Darbepoetin treatment elevated hematocrit and lowered Nitrotyrosin as one marker of oxidative stress, inflammation in heart and aorta, plaque stage and in the high dose even plaque cholesterol content. In contrast, there was no influence of Darbepoetin on aortic plaque size; high dose Darbepoetin treatment resulted in elevated renal serum parameters.Darbepoetin showed some protective cardiovascular effects irrespective of renal function, i.e. it improved plaque structure and reduced some signs of oxidative stress and chronic inflammation without affecting plaque size. Nevertheless, the dose dependent adverse effects must be considered as high Darbepoetin treatment elevated serum urea. Elevation of hematocrit might be a favorable effect in anemic Snx animals but a thrombogenic risk in Sham animals.
EVALuna2:3673

Deceased Donor Kidney Transplantation in the Eurotransplant Senior Program (ESP): A Single-Center Experience from 2008 to 2013 - Jacobi, Johannes; Beckmann, Sophie; Heller, Katharina; Hilgers, Karl Friedrich; Apel, Hendrik; Spriewald, Bernd; Eckardt, Kai-Uwe; Amann, Kerstin Ute (Annals of Transplantation, 2016)
BACKGROUND The aim of this study was to evaluate the outcome after transplantation of deceased allografts in donor/recipient pairs aged >=65 years enrolled in the Eurotransplant Senior Program (ESP). MATERIAL AND METHODS In this retrospective cohort study we evaluated data from 89 patients transplanted under the ESP protocol from 2008 to 2013. Outcome parameters included graft and patient survival, rate of biopsy-proven acute rejections (BPAR), peri- and post-operative complications, tumor development, development of donor-specific antibodies (DSA), and the prognostic role of preimplantation biopsies. RESULTS One-year patient and allograft survival rates were 92.1% and 84.3%, respectively. During follow-up, 23 (26%) patients died; the major cause of death was sepsis, followed by cardiovascular events and malignancies. BPAR episodes were frequent within the first year ( 33%) and overall were less common in patients treated with tacrolimus. Post-transplant malignancies were seen in 15 (17%) patients. During follow-up, 16 (18%) patients developed DSA; patients with delayed graft function (DGF) were more likely to develop DSA (p=0.029). A higher preimplantation biopsy score was associated with DGF but did not predict later graft outcome. CONCLUSIONS The results highlight increased risks in ESP transplant candidates and the importance of careful surveillance of this patient group.
EVALuna2:3834

Deceased donor urinary Dickkopf-3 associates with future allograft function following kidney transplantation - Fallois, Jonathan de; Günzel, Anna; Daniel, Christoph; Stumpf, Julian; Busch, Martin; Pein, Ulrich; Paliege, Alexander; Amann, Kerstin Ute; Wiech, Thorsten; Hantmann, Elena; Wolf, Gunter; Pfeifer, Felix; et al. (American Journal of Transplantation, 2024)
Predicting future kidney allograft function is challenging. Novel biomarkers, such as urinary Dickkopf-3 (uDKK3), may help guide donor selection and improve allograft outcomes. In this prospective multicenter pilot trial, we investigated whether donor uDKK3 reflects organ quality and is associated with future allograft function. We measured uDKK3/crea ratios (uDKK3/crea) from 95 deceased and 46 living kidney donors. Prenephrectomy uDKK3/crea levels were 100× higher in deceased than in living donors (9888 pg/mg vs 113 pg/mg; P < .001). Among deceased donor transplantations, recipients were stratified by their corresponding uDKK3/crea donor levels ranging below (group A, n = 68) or above (group B, n = 65) median. The primary end point of best estimated glomerular filtration rate (eGFR) within the first 3 months after kidney transplantation was superior in group A (56.3 mL/min/1.73 m2) than that in group B (44.2 mL/min/1.73 m2; P = .0139). Second, the composite clinical end point consisting of death, allograft failure or eGFR decline >50% occurred less frequent in group A. By mixed linear regression modeling, donor uDKK3/crea remained an independent predictor of eGFR after transplantation, with a slope of −4.282 mL/min/1.73 m2 per logarithmic increase in donor uDKK3/crea. In summary, uDKK3 may serve as a noninvasive, donor-dependent biomarker for assessing organ quality and future allograft function.
CRIS-Team Scopus Importer:2024-10-18
Keywords: biomarker; DKK3; donor; kidney transplantation; recipient

Deficiency of the Interleukin 17/23 Axis Accelerates Renal Injury in Mice With Deoxycorticosterone Acetate+Angiotensin II-Induced Hypertension - Krebs, Christian F.; Lange, Sascha; Niemann, Gianina; Rosendahl, Alva; Lehners, Alexander; Meyer-Schwesinger, Catherine; Stahl, Rolf A. K.; Benndorf, Ralf A.; Velden, Joachim; Paust, Hans-Joachim; Panzer, Ulf; Ehmke, Heimo; et al. (Hypertension, 2014)
T cells participate in angiotensin II (Ang II)-induced hypertension. However, the specific subsets of T cells that are important in the end-organ damage are unknown. T-helper 17 cells are a recently identified subset that produces interleukin 17 (IL-17) and requires interleukin 23 (IL-23) for expansion. To evaluate the role of the T-helper 17 immune response in hypertensive renal and cardiac end-organ damage, hypertension was induced with deoxycorticosterone acetate (DOCA)+Ang II in wild-type (n=39) and IL-17-deficient (n=31) mice. The injury was evaluated at day 4 and day 14. To inactivate the IL-17/IL-23 axis at a different point, DOCA+Ang II hypertension was also induced in IL-23p19-deficient mice. Renal infiltration by T-helper 17 cells was increased in hypertensive wild-type mice. Systolic blood pressure did not differ between hypertensive IL-17-deficient and wild-type mice. Three days after induction of hypertension, a significantly higher albuminuria was found in IL-17-deficient than in wild-type mice (196±64 versus 58±16 mg/mg albumin/creatinine). Histology revealed significantly more glomerular injury (1.04±0.06 versus 0.67±0.05) and renal infiltration of ?? T cells in IL-17-deficient than in wild-type mice after 14 days. Similarly, significantly higher albuminuria, glomerular injury, and ?? T cell infiltration were found in IL-23p19-deficient mice with DOCA+Ang II-induced hypertension. DOCA+Ang II also induced cardiac damage as assessed by heart weight, cardiac fibrosis, as well as expression of fetal genes and matrix components, but no significant differences were found among IL-17(-/-), IL-23p19(-/-), and wild-type mice. IL-17/IL-23 deficiency accelerates DOCA+Ang II-induced albuminuria and hypertensive renal but not cardiac end-organ damage.
EVALuna2:25454

Deletion of Gas2l3 in mice leads to specific defects in cardiomyocyte cytokinesis during development - Stopp, Sabine; Gruendl, Marco; Fackler, Marc; Malkmus, Jonas; Leone, Marina; Naumann, Ronald; Frantz, Stefan; Wolf, Elmar; Von Eyss, Bjoern; Engel, Felix; Gaubatz, Stefan (Proceedings of the National Academy of Sciences of the United States of America, 2017)
GAS2L3 is a recently identified cytoskeleton-associated protein that interacts with actin filaments and tubulin. The in vivo function of GAS2L3 in mammals remains unknown. Here, we show that mice deficient in GAS2L3 die shortly after birth because of heart failure. Mammalian cardiomyocytes lose the ability to proliferate shortly after birth, and further increase in cardiac mass is achieved by hypertrophy. The proliferation arrest of cardiomyocytes is accompanied by binucleation through incomplete cytokinesis. We observed that GAS2L3 deficiency leads to inhibition of cardiomyocyte proliferation and to cardiomyocyte hypertrophy during embryonic development. Cardiomyocyte-specific deletion of GAS2L3 confirmed that the phenotype results from the loss of GAS2L3 in cardiomyocytes. Cardiomyocytes from Gas2l3-deficient mice exhibit increased expression of a p53-transcriptional program including the cell cycle inhibitor p21. Furthermore, loss of GAS2L3 results in premature binucleation of cardiomyocytes accompanied by unresolved midbody structures. Together these results suggest that GAS2L3 plays a specific role in cardiomyocyte cytokinesis and proliferation during heart development.
EVALuna2:25556

Designing of spider silk proteins for human induced pluripotent stem cell-based cardiac tissue engineering - Esser, Tilman; Trossmann, Vanessa T.; Lentz, Sarah; Engel, Felix; Scheibel, T (Materials Today Bio, 2021)
Materials made of recombinant spider silk proteins are promising candidates for cardiac tissue engineering, and their suitability has so far been investigated utilizing primary rat cardiomyocytes. Herein, we expanded the tool box of available spider silk variants and demonstrated for the first time that human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes attach, contract, and respond to pharmacological treatment using phenylephrine and verapamil on explicit spider silk films. The hiPSC-cardiomyocytes contracted for at least 14 days on films made of positively charged engineered Araneus diadematus fibroin 4 (eADF4(κ16)) and three different arginyl-glycyl-aspartic acid (RGD)-tagged spider silk variants (positively or negatively charged and uncharged). Notably, hiPSC-cardiomyocytes exhibited different morphologies depending on the spider silk variant used, with less spreading and being smaller on films made of eADF4(κ16) than on RGD-tagged spider silk films. These results indicate that spider silk engineering is a powerful tool to provide new materials suitable for hiPSC-based cardiac tissue engineering.
CRIS-Team Scopus Importer:2021-06-25

Development and Evaluation of a Semi-automated Segmentation Tool and a Modified Ellipsoid Formula for Volumetric Analysis of the Kidney in Non-contrast T2-Weighted MR Images - Seuß, Hannes; Janka, Rolf Matthias; Pruemmer, Marcus; Hammon, Rebecca; Theis, Ragnar; Sandmair, Martin; Amann, Kerstin Ute; Bäuerle, Tobias; Uder, Michael; Hammon, Matthias; Cavallaro, Alexander Josef (Journal of Digital Imaging, 2017)
Volumetric analysis of the kidney parenchyma provides additional information for the detection and monitoring of various renal diseases. Therefore the purposes of the study were to develop and evaluate a semi-automated segmentation tool and a modified ellipsoid formula for volumetric analysis of the kidney in non-contrast T2-weighted magnetic resonance (MR)-images. Three readers performed semi-automated segmentation of the total kidney volume (TKV) in axial, non-contrast-enhanced T2-weighted MR-images of 24 healthy volunteers (48 kidneys) twice. A semi-automated threshold-based segmentation tool was developed to segment the kidney parenchyma. Furthermore, the three readers measured renal dimensions (length, width, depth) and applied different formulas to calculate the TKV. Manual segmentation served as a reference volume. Volumes of the different methods were compared and time required was recorded. There was no significant difference between the semi-automatically and manually segmented TKV (p = 0.31). The difference in mean volumes was 0.3 ml (95% confidence interval (CI), -10.1 to 10.7 ml). Semi-automated segmentation was significantly faster than manual segmentation, with a mean difference = 188 s (220 vs. 408 s); p < 0.05. Volumes did not differ significantly comparing the results of different readers. Calculation of TKV with a modified ellipsoid formula (ellipsoid volume × 0.85) did not differ significantly from the reference volume; however, the mean error was three times higher (difference of mean volumes -0.1 ml; CI -31.1 to 30.9 ml; p = 0.95). Applying the modified ellipsoid formula was the fastest way to get an estimation of the renal volume (41 s). Semi-automated segmentation and volumetric analysis of the kidney in native T2-weighted MR data delivers accurate and reproducible results and was significantly faster than manual segmentation. Applying a modified ellipsoid formula quickly provides an accurate kidney volume.
EVALuna2:14622

DEVELOPMENT OF APPROACHES FOR A TWO-LAYER PATCH COMBINING ELECTROSPINNING AND 3D PRINTING WITH IMPROVED ELECTRICAL STIMULUS TRANSMISSION AND SELF-REGULATING VISCOELASTIC PROPERTIES FOR APPLICATION IN CARDIAC TISSUE ENGINEERING - Boccaccini, Aldo R.; Vogt, Lena; Ruther, Florian; Roshanbinfar, Kaveh; Engel, Felix (TISSUE ENGINEERING PART A, 2022)
CRIS-Team WoS Importer:2022-08-12

Diabetes mellitus negatively affects peri-implant bone formation in the diabetic domestic pig - von Wilmowsky, Cornelius; Stockmann, Philipp; Harsch, Igor; Amann, Kerstin Ute; Metzler, Philipp; Lutz, Rainer; Möst, Tobias; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas (Journal of Clinical Periodontology, 2011)
Aim: Diabetes mellitus is classified as a relative contraindication for implant treatment, and higher failure rates have been seen in diabetic patients. The aim of the present study was to investigate the effect of diabetes on peri-implant bone formation in an animal model of human bone repair. Materials and Methods: Diabetes was induced by an intra-venous application of streptozotocin (90 mg/kg) in 15 domestic pigs. Implants were placed after significant histopathological changes in the hard and soft tissues were verified. The bone-implant contact (BIC), peri-implant bone mineral density (BMD), and expression of collagen type-I and osteocalcin proteins were qualitatively evaluated 4 and 12 weeks after implantation. Fifteen animals served as healthy controls. Results: Diabetes caused pathological changes in the soft and hard tissues. The BIC and BMD were significantly reduced in the diabetic group after 4 and 12 weeks. Collagen type-I was increased in the diabetic group at both time points, whereas osteocalcin was reduced in the diabetic group. Conclusions: Poorly controlled diabetes negatively affects peri-implant bone formation and bone mineralization. These findings have to be taken into consideration for diabetic patients with an indication for implant therapy. © 2011 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2024-05-13
Keywords: bone; diabetes; implants; osseointegration; pig

Diagnostic impact of percutaneous renal biopsy - Kitterer, Daniel; Guerzing, Katharina; Segerer, Stephan; Alscher, M. Dominik; Amann, Kerstin Ute; Braun, Niko; Latus, Joerg (Clinical Nephrology, 2015)
Ultrasound-guided percutaneous renal biopsy (PRB) is an important diagnostic tool for nephrologists. Athough widely used and without question of pivotal importance for the diagnosis of renal diseases, little systematic data regarding standardized indications, outcomes, or consequences for this procedure are available. The aim of this study was to compare the clinically suspected diagnosis with the morphological results and the potential impact of PRB on the treatment of the patient.205 patients who underwent PRB of the native kidney within a 4-year period were included in this retrospective analysis. The biopsy results (BR), discharge diagnosis (DD), and the suspected diagnoses (SD) of the attending nephrologists prior to biopsy were documented.Mean age of the patients was 58 (range 44 - 77) years. The majority of patients (61%) received PRB during an acute disease phase, whereas 39% had elective PRB. Percutaneous biopsy of the native kidney led to a discharge diagnosis in 92% of the patients, with low complication rates (with 3 out of 205 patients had major bleeding complications). In 2/3, the nephrologists were correct with the suspected diagnosis prior to the biopsy. In 74% of the biopsies, a disease was identified that was potentially responsive to treatment modification.In summary, PRB was found to be a safe procedure that confirmed the suspected clinical diagnosis in two thirds of patients. As one third of the histopathological analyses demonstrated a non-suspected disease, the biopsies were of major importance for the correct treatment of the patients.
EVALuna2:25522

Dichloroacetate prevents restenosis in preclinical animal models of vessel injury - Deuse, Tobias; Hua, Xiaoqin; Wang, Dong; Maegdefessel, Lars; Heeren, Joerg; Scheja, Ludger; Bolanos, Juan P.; Rakovic, Aleksandar; Spin, Joshua M.; Stubbendorff, Mandy; Ikeno, Fumiaki; Laenger, Florian; et al. (Nature, 2014)
Despite the introduction of antiproliferative drug-eluting stents, coronary heart disease remains the leading cause of death in the United States. In-stent restenosis and bypass graft failure are characterized by excessive smooth muscle cell (SMC) proliferation and concomitant myointima formation with luminal obliteration. Here we show that during the development of myointimal hyperplasia in human arteries, SMCs show hyperpolarization of their mitochondrial membrane potential (??m) and acquire a temporary state with a high proliferative rate and resistance to apoptosis. Pyruvate dehydrogenase kinase isoform 2 (PDK2) was identified as a key regulatory protein, and its activation proved necessary for relevant myointima formation. Pharmacologic PDK2 blockade with dichloroacetate or lentiviral PDK2 knockdown prevented ??m hyperpolarization, facilitated apoptosis and reduced myointima formation in injured human mammary and coronary arteries, rat aortas, rabbit iliac arteries and swine (pig) coronary arteries. In contrast to several commonly used antiproliferative drugs, dichloroacetate did not prevent vessel re-endothelialization. Targeting myointimal ??m and alleviating apoptosis resistance is a novel strategy for the prevention of proliferative vascular diseases.
EVALuna2:25471

Die Komplementkaskade in der Nierenpathologie - Vonbrunn, Eva; Daniel, Christoph (Die Pathologie, 2024)
The complement cascade comprises a variety of soluble and cell surface proteins and is an important component of the innate immune system. When the cascade is triggered by any of the three activation pathways, the complement system rapidly produces large amounts of protein fragments that are potent mediators of inflammatory, vasoactive, and metabolic responses. All activation pathways lead to the terminal complement cascade with the formation of the membrane attack complex, which lyses cells by forming membrane pores. Although the complement system is essential for pathogen defense and homeostasis, excessive or uncontrolled activation can lead to tissue damage. Recent research shows that the complement system is activated in almost all kidney diseases, even those not traditionally considered immune-mediated. In directly complement-mediated kidney diseases, complement factors or regulators are defective, afunctional or inactivated by antibodies. In many other renal diseases, the complement system is activated secondarily as a result of renal damage and is therefore involved in the pathogenesis of the disease, but is not the trigger. The detection of complement deposits is also used to diagnose kidney disease. This review describes the structure of the complement system and the effects of its dysregulation as a cause and modulator of renal disease.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Antibodies; C3G; Immune system; Lectin; Microangiopathy

Differences in Inflammation and Bone Resorption between Apical Granulomas, Radicular Cysts, and Dentigerous Cysts - Weber, Manuel; Ries, Jutta; Büttner-Herold, Maike; Geppert, Carol-Immanuel; Kesting, Marco Rainer; Wehrhan, Falk (Journal of Endodontics, 2019)
Introduction: Dental cysts can be of inflammatory (radicular cysts) or noninflammatory (dentigerous cysts) origin. Apical periodontitis is a necrosis of the pulp and infection of the root canal causing the development of apical granulomas or radicular cysts. The immunology of granuloma and cyst formation is important because modern root filling materials are immunologically active and can contribute to the resolution of apical granulomas. In contrast, radicular cysts often require apicectomy. A better understanding of the pathophysiology of inflammation and bone resorption in apical periodontitis could be the basis for developing new root filling materials with superior immunomodulatory properties. Methods: Forty-one apical granulomas, 23 radicular cysts, and 23 dentigerous cysts were analyzed in this study. A tissue microarray of the 87 consecutive specimens was created, and human leukocyte antigen–DR isotype (HLA-DR)-, CD83-, receptor activator of nuclear factor kappa B ligand–, macrophage colony-stimulating factor (MCSF)-, galectin-3 (Gal3)-, CD4-, and CD8-positive cells were detected by immunohistochemistry. Tissue microarrays were digitized, and the expression of markers was quantitatively assessed. Results: HLA-DR, CD83, MCSF, and Gal3 expression was significantly (P < .05) higher in radicular cysts compared with apical granulomas. HLA-DR, CD83, MCSF, receptor activator of nuclear factor kappa B ligand, and Gal3 expression in dentigerous cysts was significantly (P < .05) lower than in both periapical lesions (apical granulomas and radicular cysts). CD4 and CD8 infiltration was not statistically different between apical granulomas and radicular cysts. Dentigerous cysts showed a significantly (P < .05) lower T-cell infiltration than apical periodontitis. The CD4/CD8 ratio was not significantly different between the analyzed groups. Conclusions: The development of radicular cysts in apical periodontitis is associated with an increased expression of myeloid inflammatory markers and bone resorption parameters. Antigen-presenting cells and myeloid cells might be more relevant for the pathogenesis of apical periodontitis than T cells. Increased inflammation might promote the formation of radicular cysts and more pronounced bone resorption.
CRIS-Team Scopus Importer:2019-09-27
Keywords: Apical granuloma; apical periodontitis; bone resorption; follicular cyst; periapical lesion; radicular cysts

Differences in kidney-specific DPP-4 inhibition by linagliptin and sitagliptin - Luippold, Gerd; Mark, Michael; Klein, Thomas; Amann, Kerstin Ute; Daniel, Christoph (Diabetes Research and Clinical Practice, 2018)
The two dipeptidyl peptidase (DPP)-4 inhibitors, linagliptin and sitagliptin, were shown to exert different binding kinetics in vitro. Twenty-four hours after oral dosing particularly in vivo inhibition of renal-specific DPP-4 activity was more sustained in Sprague Dawley rats after exposure to linagliptin than it was after sitagliptin.
EVALuna2:34421

DIFFERENT FORMS OF AFFERENT NERVE INPUT IN CARDIAC AND RENAL DISEASE IN RATS? - Rodionova, Kristina; Ditting, Tilmann; Pickny, Lisa; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Differential Diagnosis of Interstitial Allograft Rejection and BKV Nephropathy by T-cell Receptor Sequencing - Stervbo, Ulrik; Nienen, Mikalai; Hecht, Jochen; Viebahn, Richard; Amann, Kerstin Ute; Westhoff, Timm H.; Babel, Nina (Transplantation, 2020)
CRIS-Team Scopus Importer:2020-04-10

Differentiating primary and secondary FSGS using non-invasive urine biomarkers. - Catanese, Lorenzo; Siwy, Justyna; Wendt, Ralph; Amann, Kerstin Ute; Beige, Joachim; Hendry, Bruce; Mischak, Harald; Mullen, William; Paterson, Ian; Schiffer, Mario; Wolf, Michael; Rupprecht, Harald (Clinical Kidney Journal, 2024)
BACKGROUND: Focal segmental glomerulosclerosis (FSGS) is divided into genetic, primary (p), uncertain cause, and secondary (s) forms. The subclasses differ in management and prognosis with differentiation often being challenging. We aimed to identify specific urine proteins/peptides discriminating between clinical and biopsy-proven pFSGS and sFSGS. METHODS: Sixty-three urine samples were collected in two different centers (19 pFSGS and 44 sFSGS) prior to biopsy. Samples were analysed using capillary electrophoresis-coupled mass spectrometry. For biomarker definition, datasets of age-/sex-matched normal controls (NC, n = 98) and patients with other chronic kidney diseases (CKDs, n = 100) were extracted from the urinary proteome database. Independent specificity assessment was performed in additional data of NC (n = 110) and CKD (n = 170). RESULTS: Proteomics data from patients with pFSGS were first compared to NC (n = 98). This resulted in 1179 biomarker (P < 0.05) candidates. Then, the pFSGS group was compared to sFSGS, and in a third step, pFSGS data were compared to data from different CKD etiologies (n = 100). Finally, 93 biomarkers were identified and combined in a classifier, pFSGS93. Total cross-validation of this classifier resulted in an area under the receiving operating curve of 0.95. The specificity investigated in an independent set of NC and CKD of other etiologies was 99.1% for NC and 94.7% for CKD, respectively. The defined biomarkers are largely fragments of different collagens (49%). CONCLUSION: A urine peptide-based classifier that selectively detects pFSGS could be developed. Specificity of 95%-99% could be assessed in independent samples. Sensitivity must be confirmed in independent cohorts before routine clinical application.
EVALuna2:552743

Digital odyssey: lessons learnt from a reverse transition from a digital to a manual pathology workflow - Caputo, Alessandro; Angeloni, Miriam; Merolla, Francesco; Vatrano, Simona; Ferrazzi, Fulvia; Fraggetta, Filippo (Journal of Clinical Pathology, 2024)
In the fully digital Caltagirone pathology laboratory, a reverse shift from a digital to a manual workflow occurred due to a server outage in September 2023. Here, insights gained from this unplanned transition are explored. Surveying the affected pathologists and technicians revealed unanimous preferences for the time-saving and error-reducing capabilities of the digital methodology. Conversely, the return to manual methods highlighted increased dissatisfaction and reduced efficiency, emphasising the superiority of digital workflows. This case study underscores that transition challenges are not inherent to digital workflows but to transitioning itself, advocating for the adoption of digital technologies in all pathology practices.
CRIS-Team Scopus Importer:2024-02-09
Keywords: Laboratory Personnel; Process Assessment; Health Care; TELEPATHOLOGY

Direct 3D‐Bioprinting of hiPSC‐derived Cardiomyocytes to Generate Functional Cardiac Tissues - Esser, Tilman; Anspach, Annalise; Muenzebrock, Katrin; Kah, Delf-Thorge Eric; Schrüfer, Stefan; Schenk, Joachim; Heinze, Katrin G.; Schubert, Dirk W.; Fabry, Ben; Engel, Felix (Advanced Materials, 2023)
3D-bioprinting is a promising technology to produce human tissues as drug screening tool or for organ repair. However, direct printing of living cells has proven difficult. Here, we present a method to directly 3D-bioprint human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes embedded in a collagen-hyaluronic acid ink generating centimeter-sized functional ring- and ventricle-shaped cardiac tissues in an accurate and reproducible manner. The printed tissues contained hiPSC-derived cardiomyocytes with well-organized sarcomeres and exhibited spontaneous and regular contractions, which persisted for several months and were able to contract against passive resistance. Importantly, beating frequencies of the printed cardiac tissues could be modulated by pharmacological stimulation. This approach opens up new possibilities for generating complex functional cardiac tissues as models for advanced drug screening or as tissue grafts for organ repair or replacement.<br

Direct 3D printing of hiPSC-cardiomyocytes in collagen-based bioinks - Esser, Tilman; Engel, Felix (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

DISRUPTION OF TFH:B CELL CROSSTALK PREVENTS ANTIBODY-MEDIATED REJECTION IN AN EXPERIMENTAL KIDNEY TRANSPLANT MODEL - Steines, L.; Poth, H.; Schuster, A.; Amann, Kerstin Ute; Banas, B.; Bergler, T. (TRANSPLANT INTERNATIONAL, 2020)
CRIS-Team WoS Importer:2020-11-06

Disruption of Tfh:B Cell Interactions Prevents Antibody-Mediated Rejection in a Kidney Transplant Model in Rats: Impact of Calcineurin Inhibitor Dose - Steines, Louisa; Poth, Helen; Schuster, Antonia; Amann, Kerstin Ute; Banas, Bernhard; Bergler, Tobias (Frontiers in Immunology, 2021)
We aimed to investigate the mechanisms of humoral immune activation in ABMR using a MHC-mismatched rat kidney transplant model. We applied low dose cyclosporine A (loCNI) to allow donor-specific antibody (DSA) formation and rejection and high dose cyclosporine A (hiCNI) for non-rejection. DSA and leukocyte subsets were measured by flow cytometry. Germinal centers (GC), T follicular helper cells (Tfh), plasma cells and interleukin-21 (IL-21) expression were analyzed by immunofluorescence microscopy. Expression of important costimulatory molecules and cytokines was measured by qRT-PCR. Allograft rejection was evaluated by a nephropathologist. We found that DSA formation correlated with GC frequency and expansion, and that GC size was linked to the number of activated Tfh. In hiCNI, GC and activated Tfh were virtually absent, resulting in fewer plasma cells and no DSA or ABMR. Expression of B cell activating T cell cytokine IL-21 was substantially inhibited in hiCNI, but not in loCNI. In addition, hiCNI showed lower expression of ICOS ligand and IL-6, which stimulate Tfh differentiation and maintenance. Overall, Tfh:B cell crosstalk was controlled only by hiCNI treatment, preventing the development of DSA and ABMR. Additional strategies targeting Tfh:B cell interactions are needed for preventing alloantibody formation and ABMR.
CRIS-Team Scopus Importer:2021-06-25
Keywords: antibody-mediated rejection; B cell activation; calcineurin inhibitor; donor-specific antibodies; kidney transplantation; T follicular helper cells

Distinct increased outliers among 136 rectal cancer patients assessed by ?H2AX - Kroeber, Jana; Wenger, Barbara; Schwegler, Manuela; Daniel, Christoph; Schmidt, Manfred; Djuzenova, Cholpon S.; Polat, Buelent; Flentje, Michael; Fietkau, Rainer; Distel, Luitpold (Radiation Oncology, 2015)
In recent years attention has focused on ?H2AX as a very sensitive double strand break indicator. It has been suggested that ?H2AX might be able to predict individual radiosensitivity. Our aim was to study the induction and repair of DNA double strand breaks labelled by ?H2AX in a large cohort.In a prospective study lymphocytes of 136 rectal cancer (RC) patients and 59 healthy individuals were ex vivo irradiated (IR) and initial DNA damage was compared to remaining DNA damage after 2 Gy and 24 hours repair time and preexisting DNA damage in unirradiated lymphocytes. Lymphocytes were immunostained with anti-?H2AX antibodies and microscopic images with an extended depth of field were acquired. ?H2AX foci counting was performed using a semi-automatic image analysis software.Distinct increased values of preexisting and remaining ?H2AX foci in the group of RC patients were found compared to the healthy individuals. Additionally there are clear differences within the groups and there are outliers in about 12% of the RC patients after ex vivo IR.The ?H2AX assay has the capability to identify a group of outliers which are most probably patients with increased radiosensitivity having the highest risk of suffering radiotherapy-related late sequelae.
EVALuna2:18245

Divergent roles of haptoglobin and hemopexin deficiency for disease progression of Shiga-toxin-induced hemolytic-uremic syndrome in mice - Pirschel, Wiebke; Mestekemper, Antonio N.; Wissuwa, Bianka; Krieg, Nadine; Kröller, Sarah; Daniel, Christoph; Gunzer, Florian; Tolosano, Emanuela; Bauer, Michael; Amann, Kerstin Ute; Heinemann, Stefan H.; Coldewey, Sina M. (Kidney International, 2022)
Thrombotic microangiopathy, hemolysis and acute kidney injury are typical clinical characteristics of hemolytic-uremic syndrome (HUS), which is predominantly caused by Shiga-toxin–producing Escherichia coli. Free heme aggravates organ damage in life-threatening infections, even with a low degree of systemic hemolysis. Therefore, we hypothesized that the presence of the hemoglobin- and the heme-scavenging proteins, haptoglobin and hemopexin, respectively impacts outcome and kidney pathology in HUS. Here, we investigated the effect of haptoglobin and hemopexin deficiency (haptoglobin-/-, hemopexin-/-) and haptoglobin treatment in a murine model of HUS-like disease. Seven-day survival was decreased in haptoglobin-/- (25%) compared to wild type mice (71.4%), whereas all hemopexin-/- mice survived. Shiga-toxin–challenged hemopexin-/- mice showed decreased kidney inflammation and attenuated thrombotic microangiopathy, indicated by reduced neutrophil recruitment and platelet deposition. These observations were associated with supranormal haptoglobin plasma levels in hemopexin-/- mice. Low dose haptoglobin administration to Shiga-toxin–challenged wild type mice attenuated kidney platelet deposition and neutrophil recruitment, suggesting that haptoglobin at least partially contributes to the beneficial effects. Surrogate parameters of hemolysis were elevated in Shiga-toxin–challenged wild type and haptoglobin-/- mice, while signs for hepatic hemoglobin degradation like heme oxygenase-1, ferritin and CD163 expression were only increased in Shiga-toxin–challenged wild type mice. In line with this observation, haptoglobin-/- mice displayed tubular iron deposition as an indicator for kidney hemoglobin degradation. Thus, haptoglobin and hemopexin deficiency plays divergent roles in Shiga-toxin–mediated HUS, suggesting haptoglobin is involved and hemopexin is redundant for the resolution of HUS pathology.
CRIS-Team Scopus Importer:2022-03-25
Keywords: acute kidney injury; haptoglobin; hemolysis; hemolytic-uremic syndrome; hemopexin; iron homeostasis; Shiga toxin

Diverse molecular causes of unsolved autosomal dominant tubulointerstitial kidney diseases - Wopperer, Florian; Knaup, Karl; Stanzick, Kira J.; Schneider, Karen; Jobst-Schwan, Tilman; Ekici, Arif Bülent; Uebe, Steffen; Wenzel, Andrea; Schliep, Stefan; Schürfeld, Carsten; Seitz, Randolf; Bernhardt, Wanja; et al. (Kidney International, 2022)
Autosomal Dominant Tubulointerstitial Kidney Disease (ADTKD) is caused by mutations in one of at least five genes and leads to kidney failure usually in mid adulthood. Throughout the literature, variable numbers of families have been reported, where no mutation can be found and therefore termed ADTKD-not otherwise specified. Here, we aim to clarify the genetic cause of their diseases in our ADTKD registry. Sequencing for all known ADTKD genes was performed, followed by SNaPshot minisequencing for the dupC (an additional cytosine within a stretch of seven cytosines) mutation of MUC1. A virtual panel containing 560 genes reported in the context of kidney disease (nephrome) and exome sequencing were then analyzed sequentially. Variants were validated and tested for segregation. In 29 of the 45 registry families, mutations in known ADTKD genes were found, mostly in MUC1. Sixteen families could then be termed ADTKD-not otherwise specified, of which nine showed diagnostic variants in the nephrome (four in COL4A5, two in INF2 and one each in COL4A4, PAX2, SALL1 and PKD2). In the other seven families, exome sequencing analysis yielded potential disease associated variants in novel candidate genes for ADTKD; evaluated by database analyses and genome-wide association studies. For the great majority of our ADTKD registry we were able to reach a molecular genetic diagnosis. However, a small number of families are indeed affected by diseases classically described as a glomerular entity. Thus, incomplete clinical phenotyping and atypical clinical presentation may have led to the classification of ADTKD. The identified novel candidate genes by exome sequencing will require further functional validation.
CRIS-Team Scopus Importer:2022-07-15
Keywords: ADTKD; Alport syndrome; exome; MITKD; MUC1; UMOD

Do ANCAs make the difference in lupus nephritis? - Amann, Kerstin Ute (Kidney International, 2017)
There has been much debate as to whether the distinction between lupus nephritis class IV-S and class IV-G is clinically relevant and whether antineutrophil cytoplasmic antibodies are pathomechanistically involved because they have been associated with the more necrotic and pauci-inflammatory phenotype of lupus nephritis that is more often seen in class IV-S. Recent data show that antineutrophil cytoplasmic antibody positivity indeed influences the histological pattern of lupus nephritis and is associated with worse baseline renal function and more active lupus serology.
EVALuna2:25558

Donor acute kidney injury and short-term graft outcome in renal transplantation - Jacobi, Johannes; Rebhan, Dirk; Heller, Katharina; Velden, Joachim; Hilgers, Karl Friedrich; Wullich, Bernd; Eckardt, Kai-Uwe; Amann, Kerstin Ute (Clinical Transplantation, 2014)
With increased waiting times for kidney transplantation, marginal organs from expanded criteria donors (ECD) are increasingly offered for allocation. In addition to ECD status, donors may have suffered from acute kidney injury (AKI) prior to organ procurement.In this retrospective cohort study, we studied short-term allograft function in 517 kidney transplants performed between the years 2008-2014. Recipients of allografts from deceased organ donors were categorized as standard criteria donors (SCD) or ECD with or without AKI defined by RIFLE criteria.Of 382 deceased donations, 174 (45.5%) were classified as ECD and 63 (16.5%) fulfilled AKI criteria. Donor creatinine on hospital admission was similar, whereas creatinine before organ procurement differed (p < 0.001). Despite these differences, serum creatinine and eGFR at discharge and after one yr showed only minor differences between kidneys with or without AKI. In multivariate linear regression analyses, donor AKI was not a predictor of one-yr allograft function.Given the poor prognosis of dialysis patients and the increase in waiting time, kidneys from SCD and ECD donors with AKI should be allocated for transplantation. In case of ECD donors with AKI, recipients should be informed about the possibility of permanent non-function or early graft loss.
EVALuna2:3714

Donor-Derived Cell-Free DNA as a Companion Biomarker for AMR Treatment With Daratumumab: Case Series - Osmanodja, Bilgin; Akifova, Aylin; Budde, Klemens; Oellerich, Michael; Beck, Julia; Bornemann-Kolatzki, Kirsten; Schütz, Ekkehard; Velden, Joachim; Lehmann, Claudia; Krüger, Bastian Malte; Bachmann, Anette; Kowald, Jan (Transplant International, 2024)
Antibody-mediated rejection (AMR) is among the most frequent causes for graft loss after kidney transplantation. While there are no approved therapies, several case reports with daratumumab and the very recent phase 2 trial of felzartamab in AMR have indicated the potential efficacy of therapeutic interventions targeting CD38. Donor-derived cell-free DNA (dd-cfDNA) is an emerging biomarker with injury-specific release and a short half-life, which could facilitate early diagnosis of AMR and monitoring of treatment response. We describe two cases of patients with chronic active AMR, who were treated with monthly daratumumab infusions, and in whom donor-derived cell-free DNA (dd-cfDNA) was measured longitudinally to monitor treatment response. In both patients, daratumumab treatment led to stabilization of kidney function parameters, a strong decline of dd-cfDNA below the previously established threshold for rejection, and partial or complete histologic resolution of AMR activity. Our case series suggests that dd-cfDNA may be a useful companion biomarker for longitudinal monitoring of anti-CD38 treatment in patients with AMR.
CRIS-Team Scopus Importer:2024-08-30
Keywords: antibody-mediated rejection; biomarker; daratumumab; donor-derived cell-free DNA; kidney transplantation

Double-Sided Graphene-Enhanced Raman Scattering and Fluorescence Quenching in Hybrid Biological Structures - Sarau, George; Daniel, Christoph; Heilmann, Martin; Leuchs, Gerd; Amann, Kerstin Ute; Christiansen, Silke H. (Advanced Materials Technologies, 2021)
Due to their large contact and loading surfaces as well as high sensitivities to chemical changes, graphene-based materials (GBMs) are increasingly being employed into novel nanomedicine technologies. Here biomolecule-monolayer graphene-kidney tissue hybrid structures are studied using mapping micro-Raman and fluorescence spectroscopies. Because in this configuration graphene interacts with molecules on both sides, a double-sided graphene-enhanced Raman scattering (GERS) effect up to approximate to 10.1 is found for biomolecules adsorbed on graphene and amino acids in the kidney tissue below graphene. Moreover, graphene causes an efficient autofluorescence quenching (FLQ) up to approximate to 20% emitted by the kidney tissue. Despite the complexity of such layered materials, the intriguing simultaneous occurrence of double-sided GERS (a new development of GERS) and FLQ phenomena can be well explained by suitable molecular structure and energy level alignment between molecules and graphene. These result in effective charge transfer mediated by non-covalent interactions as indicated by correlative strain, doping, and defect analyses in graphene based on the Raman data and energy level calculations. Last, the advantages of using graphene over standard photobleaching are demonstrated. This work can be extended to other macromolecular entities toward integrating GBMs in versatile drug delivery, imaging, and sensing devices.
CRIS-Team WoS Importer:2021-08-13

DPP4-INHIBITOR LINAGLIPTIN ACCELERATES RESOLUTION OF CRESCENT FORMATION IN A RAT MODEL OF ANTI-GBM GLOMERULONEPHRITIS - Mayer, Anna-Lena; Ebert, Nadja; Klein, Thomas; Amann, Kerstin Ute; Daniel, Christoph (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2020)
CRIS-Team WoS Importer:2020-08-21

Dysfunction of the key ferroptosis-surveilling systems hypersensitizes mice to tubular necrosis during acute kidney injury - Tonnus, Wulf; Meyer, Claudia; Steinebach, Christian; Belavgeni, Alexia; von Mässenhausen, Anne; Gonzalez, Nadia Zamora; Maremonti, Francesca; Gembardt, Florian; Himmerkus, Nina; Latk, Markus; Locke, Sophie; Marschner, Julian; et al. (Nature Communications, 2021)
Acute kidney injury (AKI) is morphologically characterized by a synchronized plasma membrane rupture of cells in a specific section of a nephron, referred to as acute tubular necrosis (ATN). Whereas the involvement of necroptosis is well characterized, genetic evidence supporting the contribution of ferroptosis is lacking. Here, we demonstrate that the loss of ferroptosis suppressor protein 1 (Fsp1) or the targeted manipulation of the active center of the selenoprotein glutathione peroxidase 4 (Gpx4cys/-) sensitize kidneys to tubular ferroptosis, resulting in a unique morphological pattern of tubular necrosis. Given the unmet medical need to clinically inhibit AKI, we generated a combined small molecule inhibitor (Nec-1f) that simultaneously targets receptor interacting protein kinase 1 (RIPK1) and ferroptosis in cell lines, in freshly isolated primary kidney tubules and in mouse models of cardiac transplantation and of AKI and improved survival in models of ischemia-reperfusion injury. Based on genetic and pharmacological evidence, we conclude that GPX4 dysfunction hypersensitizes mice to ATN during AKI. Additionally, we introduce Nec-1f, a solid inhibitor of RIPK1 and weak inhibitor of ferroptosis.
CRIS-Team Scopus Importer:2021-08-06

Early Ultrastructural Changes in Biopsies From Patients With Symptomatic CKD of Uncertain Etiology - Daniel, Christoph; Enghard, Philipp; Ratnatunga, Neelakanthi; Wijetunge, Sulochana; Wazil, A. W.M.; Zwiener, Christian; Barth, Johannes; Chandrajith, Rohana; Klewer, Monika; Eckardt, Kai-Uwe; Amann, Kerstin Ute; Freund, Paul; et al. (Kidney International Reports, 2023)
Introduction: Although the investigation of chronic kidney disease of uncertain etiology (CKDu) has identified many possible influencing factors in recent years, the exact pathomechanism of this disease remains unclear. Methods: In this study, we collected 13 renal biopsies from patients with symptomatic CKDu (Sym-CKDu) from Sri Lanka with well-documented clinical and socioeconomic factors. We performed light microscopy and electron microscopic evaluation for ultrastructural analysis, which was compared with 100 biopsies from German patients with 20 different kidney diseases. Results: Of the 13 Sri Lankan patients, 12 were men (92.3%), frequently employed in agriculture (50%), and experienced symptoms such as feeling feverish (83.3%), dysuria (83.3%), and arthralgia (66.6%). Light microscopic evaluation using activity and chronicity score revealed that cases represented early stages of CKDu except for 2 biopsies, which showed additional signs of diabetes. Most glomeruli showed only mild changes, such as podocyte foot process effacement on electron microscopy. We found a spectrum of early tubulointerstitial changes including partial loss of brush border in proximal tubules, detachment of tubular cells, enlarged vacuoles, and mitochondrial swelling associated with loss of cristae and dysmorphic lysosomes with electron-dense aggregates. None of these changes occurred exclusively in Sym-CKDu; however, they were significantly more frequent in these cases than in the control cohort. Conclusion: In conclusion, our findings confirm the predominant and early alterations of tubular structure in CKDu that can occur without significant glomerular changes. The ultrastructural changes do not provide concrete evidence of the cause of CKDu but were significantly more frequent in Sym-CKDu than in the controls.
CRIS-Team Scopus Importer:2023-03-17
Keywords: chronic kidney disease of uncertain etiology (CKDu); lysosomal alteration; mitochondrial swelling; renal biopsy; transmission electron microscopy; tubular injury

Eculizumab in Pediatric Dense Deposit Disease - Oosterveld, Michiel J. S.; Garrelfs, Mark R.; Hoppe, Bernd; Florquin, Sandrine; Roelofs, Joris J. T. H.; Van Den Heuvel, L. P.; Amann, Kerstin Ute; Davin, Jean-Claude; Bouts, Antonia H. M.; Schriemer, Pietrik J.; Groothoff, Jaap W. (Clinical Journal of the American Society of Nephrology, 2015)
Dense deposit disease (DDD), a subtype of C3 glomerulopathy, is a rare disease affecting mostly children. Treatment options are limited. Debate exists whether eculizumab, a monoclonal antibody against complement factor C5, is effective in DDD. Reported data are scarce, especially in children.The authors analyzed clinical and histologic data of five pediatric patients with a native kidney biopsy diagnosis of DDD. Patients received eculizumab as therapy of last resort for severe nephritic or nephrotic syndrome with alternative pathway complement activation; this therapy was given only when the patients had not or only marginally responded to immunosuppressive therapy. Outcome measures were kidney function, proteinuria, and urine analysis.In all, seven disease episodes were treated with eculizumab (six episodes of severe nephritic syndrome [two of which required dialysis] and one nephrotic syndrome episode). Median age at treatment start was 8.4 (range, 5.9-13) years. For three treatment episodes, eculizumab was the sole immunosuppressive treatment. In all patients, both proteinuria and renal function improved significantly within 12 weeks of treatment (median urinary protein-to-creatinine ratio of 8.5 [range, 2.2-17] versus 1.1 [range, 0.2-2.0] g/g, P<0.005, and eGFR of 58 [range, 17-114] versus 77 [range, 50-129] ml/min per 1.73 m(2), P<0.01). A striking finding was the disappearance of leukocyturia within 1 week after the first eculizumab dose in all five episodes with leukocyturia at treatment initiation.In this case series of pediatric patients with DDD, eculizumab treatment was associated with reduction in proteinuria and increase in eGFR. Leukocyturia resolved within 1 week of initiation of eculizumab treatment. These results underscore the need for a randomized trial of eculizumab in DDD.
EVALuna2:25493

Editorial: Methods in cardiovascular biologics and regenerative medicine - Gurusamy, Narasimman; Bergmann, Olaf; Castaldo, Clotilde; Huang, Ngan F.; Lien, Ching Ling; Tan, Jun Jie; Engel, Felix (Frontiers in Cardiovascular Medicine, 2024)
CRIS-Team Scopus Importer:2024-10-04
Keywords: 3D-bioprinting; cardiac remuscularization; methods in cardiovascular biologics; mitochondrial function; pericytes; regenerative medicine; tissue engineering; vascular grafts

Effects of a high-caloric diet and physical exercise on brain metabolite levels: a combined proton MRS and histologic study - Auer, Matthias K.; Sack, Markus; Lenz, Jenny N.; Jakovcevski, Mira; Biedermann, Sarah V.; Falfan-Melgoza, Claudia; Deussing, Jan; Steinle, Joerg; Bielohuby, Maximilian; Bidlingmaier, Martin; Pfister, Frederik; Stalla, Guenter K.; et al. (Journal of Cerebral Blood Flow and Metabolism, 2015)
Excessive intake of high-caloric diets as well as subsequent development of obesity and diabetes mellitus may exert a wide range of unfavorable effects on the central nervous system (CNS). It has been suggested that one mechanism in this context is the promotion of neuroinflammation. The potentially harmful effects of such diets were suggested to be mitigated by physical exercise. Here, we conducted a study investigating the effects of physical exercise in a cafeteria-diet mouse model on CNS metabolites by means of in vivo proton magnetic resonance spectroscopy ((1)HMRS). In addition postmortem histologic and real-time (RT)-PCR analyses for inflammatory markers were performed. Cafeteria diet induced obesity and hyperglycemia, which was only partially moderated by exercise. It also induced several changes in CNS metabolites such as reduced hippocampal glutamate (Glu), choline-containing compounds (tCho) and N-acetylaspartate (NAA)+N-acetyl-aspartyl-glutamic acid (NAAG) (tNAA) levels, whereas opposite effects were seen for running. No association of these effects with markers of central inflammation could be observed. These findings suggest that while voluntary wheel running alone is insufficient to prevent the unfavorable peripheral sequelae of the diet, it counteracted many changes in brain metabolites. The observed effects seem to be independent of neuroinflammation.
EVALuna2:25504

EFFECTS OF NEUROGENIC CGRP ON RENAL AFFERENT PEPTIDERGIC NEURONS - Veelken, Roland; Raschke, Giulia; Ditting, Tilmann; Ott, Christian; Schmieder, Roland; Amann, Kerstin Ute; Rodionova, Kristina (2018)
EVALuna2:204843

Effects of the Non-Neutralizing Humanized Monoclonal Anti-Adrenomedullin Antibody Adrecizumab on Hemodynamic and Renal Injury in a Porcine Two-Hit Model - Thiele, Christoph; Simon, Tim Philipp; Szymanski, Jeanine; Daniel, Christoph; Golias, Christos; Hartmann, Oliver; Struck, Joachim; Martin, Lukas; Marx, Gernot; Schuerholz, Tobias (Shock, 2020)
Adrenomedullin is a vasoactive peptide that improves endothelial barrier function in sepsis, but may also cause hypotension and organ failure. Treatment with a non-neutralizing monoclonal anti-adrenomedullin antibody showed improvement in murine sepsis models. We tested the effects of the humanized monoclonal anti-adrenomedullin antibody Adrecizumab in a porcine two hit model of hemorrhagic and septic shock.In this randomized, blinded study 12 German Landrace pigs were bled to half of baseline mean arterial pressure for 45 minutes. Sepsis was induced using an E.coli clot placed into the abdominal cavity 6 hours after hemorrhagic shock. Animals received either 2 mg/kg BW anti-adrenomedullin antibody or vehicle solution immediately after sepsis induction. After 4 hours, resuscitation was initiated using balanced crystalloids and noradrenalin to maintain a CVP of 8-12 mmHg, a MAP ≥ 65mmHg and a ScvO2 ≥70% for another 8 hours. Hemodynamic parameters, laboratory parameters and kidney histology were assessed.The amount of volume resuscitation was significantly lower and significantly less animals developed a septic shock in the antibody-treated group, compared to the vehicle group. Kidney histology showed significantly lower granulocytes in both cortex and medulla in antibody-treated animals, while the remaining four kidney measures (serum creatinine and urine output and cortical and medullary injury in histopathology) did not reach the significance levels. After induction of sepsis, plasma adrenomedullin increased immediately in both groups, but increased quicker and more pronounced in the antibody group.In this two hit shock model, treatment with an anti-adrenomedullin antibody significantly increased plasma adrenomedullin levels, while significantly less animals developed septic shock and renal granulocyte extravasation was significantly reduced. Thus, therapy with Adrecizumab may provide benefit in sepsis, and clinical investigation of this drug candidate is warranted.
CRIS-Team Scopus Importer:2020-06-30

Eine übermäßige Phagozytose von Myelomzellen induziert Pyroptose in Myelom-assoziierten Makrophagen und beeinträchtigt die Wirksamkeit therapeutischer Antikörper - Flamann, Cindy; Biedermann, Alexander; Mougiakakos, D.; Bitterer, Katrin; Karg, K.; Bittenbring, J.; Büttner-Herold, Maike; Liebisch, G.; Leffler, M.; Lischer, Christopher; Eberhardt, Martin; Vera-Gonzales, J.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Einfluss des Klimawandels auf Infektionskrankheiten in der Nephrologie - Kraft, Leonie; Schmidt-Chanasit, Jonas; Paul, Gregor; Amann, Kerstin Ute; Latus, Jörg (Die Nephrologie, 2023)
Climate change is one of the most important challenges of our time. While at first sight the danger seems to emanate from extreme weather situations and natural disasters, the risk of a possible increase or change in the pathogen spectrum of infectious diseases should not be ignored. We do not yet know much about the spread of infectious diseases due to global warming. Most scenarios are derived from statistical climate models and what the future will look like is difficult to estimate. In addition, the lack of epidemiological data and different mandatory reporting of infectious diseases make the risk assessment more difficult. Furthermore, the spread of infectious diseases is not only dependent on higher temperatures. Changes in the use of agricultural land, socioeconomic factors with population growth and migration, access to clean drinking water, and innovations in the healthcare and reporting systems will continue to change the pattern of infectious diseases. Infectious diseases will affect the nephrology community in different ways in the coming years and decades. Some, such as hantavirus infections, are obvious as acute kidney injury is characteristic for this disease. Others have an indirect effect, through septic or prerenal kidney injury or because most of the patients belong to vulnerable groups and are particularly in need of protection. In the case of febrile illnesses, many of the diseases mentioned should be considered as differential diagnoses in the future, even without a suitable travel history.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Arbovirus infections; Global warming; Kidney injury; Metazoonoses; Vector-borne pathogens

Einführung in die Nierenpathologie - Büttner-Herold, Maike; Amann, Kerstin Ute (Die Pathologie, 2024)
In recent decades, nephropathology has developed worldwide as a subspeciality of pathology, which requires special methodological and technical equipment to process the material and specific clinical and pathological expertise to interpret the findings. These special requirements mean that nephropathology is not available at all pathology institutes, but is carried out on a large scale in a few highly specialised centres. The history of nephropathology, or in a narrower sense the specialised histopathological examination of kidney biopsies, began in 1958 with the first use or performance of a kidney biopsy [1]. It thus replaced the practice of urinalysis, which had been common since the Middle Ages, as a diagnostic tool for kidney diseases. Specialised techniques such as immunofluorescence or immunohistology but also electron microscopy are required to assess specific renal changes, for which the examination of renal biopsies is one of the few remaining routine applications today. In Germany and German-speaking countries, the discipline developed thanks to the work of outstanding people in the field of pathology who were primarily involved in this discipline and had the necessary technical and human resources in their laboratories to ensure that these biopsies could be analysed.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Electron microscopy; Immunohistology; Light microscopy; Renal biopsy; Renal specimens

Elastin imaging enables noninvasive staging and treatment monitoring of kidney fibrosis - Sun, Qinxue; Baues, Maike; Klinkhammer, Barbara M.; Ehling, Josef; Djudjaj, Sonja; Drude, Natascha; Daniel, Christoph; Amann, Kerstin Ute; Kramann, Rafael; Kim, Hyojin; Saez-Rodriguez, Julio; Weiskirchen, Ralf; et al. (Science Translational Medicine, 2019)
Fibrosis is the common endpoint and currently the best predictor of progression of chronic kidney diseases (CKDs). Despite several drawbacks, biopsies remain the only available means to specifically assess the extent of renal fibrosis. Here, we show that molecular imaging of the extracellular matrix protein elastin allows for noninvasive staging and longitudinal monitoring of renal fibrosis. Elastin was hardly expressed in healthy mouse, rat, and human kidneys, whereas it was highly up-regulated in cortical, medullar, and perivascular regions in progressive CKD. Compared to a clinically relevant control contrast agent, the elastin-specific magnetic resonance imaging agent ESMA specifically detected elastin expression in multiple mouse models of renal fibrosis and also in fibrotic human kidneys. Elastin imaging allowed for repetitive and reproducible assessment of renal fibrosis, and it enabled longitudinal monitoring of therapeutic interventions, accurately capturing anti-fibrotic therapy effects. Last, in a model of reversible renal injury, elastin imaging detected ensuing fibrosis not identifiable via routine assessment of kidney function. Elastin imaging thus has the potential to become a noninvasive, specific imaging method to assess renal fibrosis.
CRIS-Team WoS Importer:2019-04-16

Electrically Conductive Collagen-PEDOT:PSS Hydrogel Prevents Post-Infarct Cardiac Arrhythmia and Supports hiPSC-Cardiomyocyte Function - Roshanbinfar, Kaveh; Schiffer, Miriam; Carls, Esther; Angeloni, Miriam; Kolesnik-Gray, Maria; Schrüfer, Stefan; Schubert, Dirk W.; Ferrazzi, Fulvia; Krstic, Vojislav; Fleischmann, Bernd K.; Roell, Wilhelm; Engel, Felix (Advanced Materials, 2024)
Myocardial infarction (MI) causes cell death, disrupts electrical activity, triggers arrhythmia, and results in heart failure, whereby 50–60% of MI-associated deaths manifest as sudden cardiac deaths (SCD). The most effective therapy for SCD prevention is implantable cardioverter defibrillators (ICDs). However, ICDs contribute to adverse remodeling and disease progression and do not prevent arrhythmia. This work develops an injectable collagen-PEDOT:PSS (poly(3,4-ethylenedioxythiophene) polystyrene sulfonate) hydrogel that protects infarcted hearts against ventricular tachycardia (VT) and can be combined with human induced pluripotent stem cell (hiPSC)-cardiomyocytes to promote partial cardiac remuscularization. PEDOT:PSS improves collagen gel formation, micromorphology, and conductivity. hiPSC-cardiomyocytes in collagen-PEDOT:PSS hydrogels exhibit near-adult sarcomeric length, improved contractility, enhanced calcium handling, and conduction velocity. RNA-sequencing data indicate enhanced maturation and improved cell-matrix interactions. Injecting collagen-PEDOT:PSS hydrogels in infarcted mouse hearts decreases VT to the levels of healthy hearts. Collectively, collagen-PEDOT:PSS hydrogels offer a versatile platform for treating cardiac injuries.
CRIS-Team Scopus Importer:2024-05-10
Keywords: arrhythmia; cardiac tissue engineering; collagen; electrically conductive; PEDOT:PSS

Electroconductive Biohybrid Hydrogel for Enhanced Maturation and Beating Properties of Engineered Cardiac Tissues - Roshanbinfar, Kaveh; Vogt, Lena; Greber, Boris; Diecke, Sebastian; Boccaccini, Aldo R.; Scheibel, Thomas; Engel, Felix (Advanced Functional Materials, 2018)
Keywords: electroconductive hydrogels; maturation; tissue engineering; heart; hiPSC

Elevated n-3/n-6 PUFA ratio in early life diet reverses adverse intrauterine kidney programming in female rats - Voggel, Jenny; Fink, Gregor; Zelck, Magdalena; Wohlfarth, Maria; Post, Julia M.; Bindila, Laura; Rauh, Manfred; Amann, Kerstin Ute; Alcazar, Miguel A. Alejandre; Doetsch, Joerg; Nuesken, Kai-Dietrich; Nuesken, Eva (Journal of Lipid Research, 2022)
Intrauterine growth restriction (IUGR) predisposes to chronic kidney disease via activation of proinflammatory pathways, and omega-3 PUFAs (n-3 PUFAs) have anti-inflammatory properties. In female rats, we investigated 1) how an elevated di-etary n-3/n-6 PUFA ratio (1:1) during postnatal kidney development modifies kidney phospholipid (PL) and arachidonic acid (AA) metabolite content and 2) whether the diet counteracts adverse molecular pro-tein signatures expected in IUGR kidneys. IUGR was induced by bilateral uterine vessel ligation or intra-uterine stress through sham operation 3.5 days before term. Control (C) offspring were born after uncom-promised pregnancy. On postnatal (P) days P2-P39, rats were fed control (n-3/n-6 PUFA ratio 1:20) or n-3 PUFA intervention diet (N3PUFA; ratio 1:1). Plasma parameters (P33), kidney cortex lipidomics and pro-teomics, as well as histology (P39) were studied. We found that the intervention diet tripled PL-DHA content (PC 40:6; P < 0.01) and lowered both PL-AA content (PC 38:4 and lyso-phosphatidylcholine 20:4; P < 0.05) and AA metabolites (HETEs, dihydrox-yeicosatrienoic acids, and epoxyeicosatrienoic acids) to 25% in all offspring groups. After ligation, our network analysis of differentially expressed proteins identified an adverse molecular signature indicating inflammation and hypercoagulability. N3PUFA diet reversed 61 protein alterations (P < 0.05), thus miti-gating adverse IUGR signatures. In conclusion, an elevated n-3/n-6 PUFA ratio in early diet strongly reduces proinflammatory PLs and mediators while increasing DHA-containing PLs regardless of prior intrauterine conditions. Counteracting a proin-flammatory hypercoagulable protein signature in young adult IUGR individuals through early diet intervention may be a feasible strategy to prevent developmentally programmed kidney damage in later life.
CRIS-Team WoS Importer:2022-12-02

End-stage renal disease after sarcoma therapy - case 3/2014 - Baumann, D.; Amann, Kerstin Ute; Schlatter, E.; Ciarimboli, G.; Kopp, H. G.; Müller, M.; Kluba, T.; Bakos, G.; Steinke, I.; Bunz, H.; Weyrich, P.; Artunc, F. (Deutsche Medizinische Wochenschrift, 2014)
A 67-year-old male patient developed progressive renal failure following successful treatment of a soft tissue sarcoma that comprised surgical resection after neoadjuvant radiochemotherapy with the application of doxorubicin (cumulative dose 180 mg/m²) and ifosfamide (cumulative dose 33 g/m²).Plasma creatinine concentration was elevated to 4.5 mg/dl. Upon detection of glucosuria and ?1-microglobulinuria renal biopsy was performed.Histologic analysis revealed massively injured tubules that could be explained by a toxic effect of ifosfamide. Glomeruli were not affected and appeared normal. After two months of conservative therapy, the patient developed an uremic syndrome requiring hemodialysis. Ever since kidney function did not recover albeit preserved diuresis.Ifosfamide can cause end-stage renal disease by a tubulotoxic effect that may be the result of a selective intracellular uptake into the proximal tubule via the human organic cation transporter 2 (OCT2).
EVALuna2:25473

Engineering of vascularized transplantable bone tissues: induction of axial vascularization in an osteoconductive matrix using an arteriovenous loop. - Kneser, Ulrich; Polykandriotis, Elias; Ohnolz, Jan; Heidner, Kristina; Grabinger, Lucia; Euler, Simon; Amann, Kerstin Ute; Heß, Andreas; Brune, Kay; Greil, Peter; Stürzl, Michael; Horch, Raymund E. (Tissue Engineering -Larchmont, 2006)
This study demonstrates for the first time successful vascularization of solid porous matrices by means of an AV loop. Injection of osteogenic cells into axially prevascularized matrices may eventually create functional bioartificial bone tissues for reconstruction of large defects. Vascularization remains an obstacle to engineering of larger volume bone tissues. Our aim was to induce axial vascularization in a processed bovine cancellous bone (PBCB) matrix using an arteriovenous (AV) loop (artery, vein graft, and vein). Custom-made PBCB discs (9 x 5 mm) were implanted into rats. In group A (n = 19), the matrices were inserted into microsurgically constructed AV loops between the femoral vessels using a vein graft from the contralateral side. In group B (n = 19), there was no vascular carrier. The matrices were encased in isolation chambers. After 2, 4, and 8 weeks, the animals were perfused with India ink via the abdominal aorta. Matrices were explanted and subjected to histological and morphometric analysis. Results were compared with intravital dynamic micro & magnetic resonance imaging and scanning electron microscopy images of vascular corrosion replicas. In group A, significant vascularization of the matrix had occurred by the 8th week. At this time, vascular remodeling with organization into vessels of different sizes was evident. Blood vessels originated from all 3 zones of the AV loop. Group A was significantly superior to group B in terms of vascular density and vascularization kinetics. DISCUSSION INTRODUCTION METHODS RESULTS

Enhancement of engineered cardiac tissues by promotion of hiPSC-cardiomyocyte proliferation - Hesselbarth, Ramona; Esser, Tilman; Roshanbinfar, Kaveh; Schrüfer, Stefan; Schubert, Dirk W.; Engel, Felix (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Enhancing biofabrication: Shrink-resistant collagen-hyaluronan composite hydrogel for tissue engineering and 3D bioprinting applications - Roshanbinfar, Kaveh; Evans, Austin Donnelly; Samanta, Sumanta; Kolesnik-Gray, Maria; Fiedler, Maren; Krstic, Vojislav; Engel, Felix; Oommen, Oommen P. (Biomaterials, 2025)
Biofabrication represents a promising technique for creating tissues for regeneration or as models for drug testing. Collagen-based hydrogels are widely used as suitable matrix owing to their biocompatibility and tunable mechanical properties. However, one major challenge is that the encapsulated cells interact with the collagen matrix causing construct shrinkage. Here, we present a hydrogel with high shape fidelity, mimicking the major components of the extracellular matrix. We engineered a composite hydrogel comprising gallic acid (GA)-functionalized hyaluronic acid (HA), collagen I, and HA-coated multiwall carbon nanotubes (MWCNT). This hydrogel supports cell encapsulation, exhibits shear-thinning properties enhancing injectability and printability, and importantly significantly mitigates shrinkage when loaded with human fibroblasts compared to collagen I hydrogels (∼20 % vs. > 90 %). 3D-bioprinted rings utilizing human fibroblast-loaded inks maintain their shape over 7 days in culture. Furthermore, inclusion of HAGA into collagen I hydrogels increases mechanical stiffness, radical scavenging capability, and tissue adhesiveness. Notably, the here developed hydrogel is also suitable for human induced pluripotent stem cell-derived cardiomyocytes and allows printing of functional heart ventricles responsive to pharmacological treatment. Cardiomyocytes behave similar in the newly developed hydrogels compared to collagen I, based on survival, sarcomere appearance, and calcium handling. Collectively, we developed a novel material to overcome the challenge of post-fabrication matrix shrinkage conferring high shape fidelity.
CRIS-Team Scopus Importer:2025-02-21
Keywords: 3D bioprinting; Cardiac; Hydrogel; Shrink-resistant; Shrinkage; Tissue engineering

Enhancing Form Stability: Shrink-Resistant Hydrogels Made of Interpenetrating Networks of Recombinant Spider Silk and Collagen-I - Ng, Xuen J.; Esser, Tilman; Trossmann, Vanessa T.; Rudisch, Christoph; Fiedler, Maren; Roshanbinfar, Kaveh; Lamberger, Zan; Stahlhut, Philipp; Lang, Gregor; Scheibel, Thomas; Engel, Felix (Advanced Healthcare Materials, 2025)
Tissue engineering enables the production of tissues and organ-like structures as models for drug testing and mechanistical studies or functional replacements for injured tissues. Available cytocompatible materials are limited in number, suffer from insufficient mechanical properties, and cells interacting with them often cause construct shrinkage. As shape is important for function, identifying cytocompatible, shrink-resistant materials are a major aim. Here, it is shown that hydrogels made of interpenetrating networks of collagen-I and recombinant spider silk protein eADF4(C16)-RGD nanofibrils exhibit synergistic and tunable mechanical properties. Composite hydrogels allow cell adhesion and spreading and are resistant to shrinkage mediated by fibroblasts, C2C12 myoblasts, and human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes. Myoblasts differentiate and fuse into myotubes, and hiPSC-cardiomyocytes can be cultured long-term, show spontaneous contractions, and remain drug responsive. Collectively, a novel composite material is developed to overcome the challenge of post-fabrication matrix shrinkage conferring high shape fidelity suitable for tissue engineering.
CRIS-Team Scopus Importer:2025-04-11
Keywords: biopolymer; cardiac tissue engineering; compaction; heart; shrinkage

Epidemiology, molecular, and genetic methodologies to evaluate causes of CKDu around the world: report of the Working Group from the ISN International Consortium of Collaborators on CKDu - Anand, Shuchi; Caplin, Ben; Gonzalez-Quiroz, Marvin; Schensul, Stephen L.; Bhalla, Vivek; Parada, Xavier; Nanayakkara, Nishantha; Fire, Andrew; Levin, Adeera; Friedman, David J.; Aguilar-Gonzalez, Angie; Abbot, Kevin; et al. (Kidney International, 2019)
CRIS-Team WoS Importer:2019-12-06

Epigenomic and transcriptomic approaches in the post-genomic era: path to novel targets for diagnosis and therapy of the ischaemic heart? Position Paper of the European Society of Cardiology Working Group on Cellular Biology of the Heart - Perrino, Cinzia; Barabasi, Albert-Laszlo; Condorelli, Gianluigi; Davidson, Sean Michael; De Windt, Leon; Dimmeler, Stefanie; Engel, Felix; Hausenloy, Derek John; Hill, Joseph Addison; Van Laake, Linda Wilhelmina; Lecour, Sandrine; Leor, Jonathan; et al. (Cardiovascular Research, 2017)
Despite advances in myocardial reperfusion therapies, acute myocardial ischaemia/reperfusion injury and consequent ischaemic heart failure represent the number one cause of morbidity and mortality in industrialized societies. Although different therapeutic interventions have been shown beneficial in preclinical settings, an effective cardioprotective or regenerative therapy has yet to be successfully introduced in the clinical arena. Given the complex pathophysiology of the ischaemic heart, large scale, unbiased, global approaches capable of identifying multiple branches of the signalling networks activated in the ischaemic/reperfused heart might be more successful in the search for novel diagnostic or therapeutic targets. High-throughput techniques allow high-resolution, genome-wide investigation of genetic variants, epigenetic modifications, and associated gene expression profiles. Platforms such as proteomics and metabolomics (not described here in detail) also offer simultaneous readouts of hundreds of proteins and metabolites. Isolated omics analyses usually provide Big Data requiring large data storage, advanced computational resources and complex bioinformatics tools. The possibility of integrating different omics approaches gives new hope to better understand the molecular circuitry activated by myocardial ischaemia, putting it in the context of the human 'diseasome'. Since modifications of cardiac gene expression have been consistently linked to pathophysiology of the ischaemic heart, the integration of epigenomic and transcriptomic data seems a promising approach to identify crucial disease networks. Thus, the scope of this Position Paper will be to highlight potentials and limitations of these approaches, and to provide recommendations to optimize the search for novel diagnostic or therapeutic targets for acute ischaemia/reperfusion injury and ischaemic heart failure in the post-genomic era.
EVALuna2:25534

Epistatic effects of Siglec-G and DNase1 or DNase1l3 deficiencies in the development of systemic lupus erythematosus - Korn, Marina; Steffensen, Marie; Brandl, Carolin; Royzman, Dmytro; Daniel, Christoph; Winkler, Thomas; Nitschke, Lars (Frontiers in Immunology, 2023)
Systemic lupus erythematosus (SLE) is a severe autoimmune disease that displays considerable heterogeneity not only in its symptoms, but also in its environmental and genetic causes. Studies in SLE patients have revealed that many genetic variants contribute to disease development. However, often its etiology remains unknown. Existing efforts to determine this etiology have focused on SLE in mouse models revealing not only that mutations in specific genes lead to SLE development, but also that epistatic effects of several gene mutations significantly amplify disease manifestation. Genome-wide association studies for SLE have identified loci involved in the two biological processes of immune complex clearance and lymphocyte signaling. Deficiency in an inhibitory receptor expressed on B lymphocytes, Siglec-G, has been shown to trigger SLE development in aging mice, as have mutations in DNA degrading DNase1 and DNase1l3, that are involved in clearance of DNA-containing immune complexes. Here, we analyze the development of SLE-like symptoms in mice deficient in either Siglecg and DNase1 or Siglecg and DNase1l3 to evaluate potential epistatic effects of these genes. We found that germinal center B cells and follicular helper T cells were increased in aging Siglecg-/- x Dnase1-/- mice. In contrast, anti-dsDNA antibodies and anti-nuclear antibodies were strongly increased in aging Siglecg-/- x Dnase1l3-/- mice, when compared to single-deficient mice. Histological analysis of the kidneys revealed glomerulonephritis in both Siglecg-/- x Dnase1-/- and Siglecg-/- x Dnase1l3-/- mice, but with a stronger glomerular damage in the latter. Collectively, these findings underscore the impact of the epistatic effects of Siglecg with DNase1 and Dnase1l3 on disease manifestation and highlight the potential combinatory effects of other gene mutations in SLE.
CRIS-Team Scopus Importer:2023-03-31
Keywords: autoimmunity; B cell signaling; inhibitory receptors; lymphocytes; mouse models

Epithelial RAC1-dependent cytoskeleton dynamics controls cell mechanics, cell shedding and barrier integrity in intestinal inflammation - Martínez Sánchez, Luz del Carmen; Phuong Anh Ngo,; Pradhan, Rashmita; Becker, Lukas S; Böhringer, David; Soteriou, Despina; Kubankova, Marketa; Schweitzer, Christine; Koch, Tatyana; Thonn, Veronika; Erkert, Lena; Stolzer, Iris; et al. (Gut, 2022)
Objective Increased apoptotic shedding has been linked to intestinal barrier dysfunction and development of inflammatory bowel diseases (IBD). In contrast, physiological cell shedding allows the renewal of the epithelial monolayer without compromising the barrier function. Here, we investigated the role of live cell extrusion in epithelial barrier alterations in IBD. Design Taking advantage of conditional GGTase and RAC1 knockout mice in intestinal epithelial cells (Pggt1b (i Delta IEC) and Rac1 (i Delta IEC) mice), intravital microscopy, immunostaining, mechanobiology, organoid techniques and RNA sequencing, we analysed cell shedding alterations within the intestinal epithelium. Moreover, we examined human gut tissue and intestinal organoids from patients with IBD for cell shedding alterations and RAC1 function. Results Epithelial Pggt1b deletion led to cytoskeleton rearrangement and tight junction redistribution, causing cell overcrowding due to arresting of cell shedding that finally resulted in epithelial leakage and spontaneous mucosal inflammation in the small and to a lesser extent in the large intestine. Both in vivo and in vitro studies (knockout mice, organoids) identified RAC1 as a GGTase target critically involved in prenylation-dependent cytoskeleton dynamics, cell mechanics and epithelial cell shedding. Moreover, inflamed areas of gut tissue from patients with IBD exhibited funnel-like structures, signs of arrested cell shedding and impaired RAC1 function. RAC1 inhibition in human intestinal organoids caused actin alterations compatible with arresting of cell shedding. Conclusion Impaired epithelial RAC1 function causes cell overcrowding and epithelial leakage thus inducing chronic intestinal inflammation. Epithelial RAC1 emerges as key regulator of cytoskeletal dynamics, cell mechanics and intestinal cell shedding. Modulation of RAC1 might be exploited for restoration of epithelial integrity in the gut of patients with IBD.
CRIS-Team WoS Importer:2022-03-25

Erratum to: ‘Inhibition of the renal apical sodium dependent bile acid transporter prevents cholemic nephropathy in mice with obstructive cholestasis’ [J Hepatol (2024) 80:268-281, (S0168827823052352), (10.1016/j.jhep.2023.10.035)] - Ghallab, Ahmed; González, Daniela; Strängberg, Ellen; Hofmann, Ute; Myllys, Maiju; Hassan, Reham; Hobloss, Zaynab; Brackhagen, Lisa; Begher-Tibbe, Brigitte; Duda, Julia C.; Drenda, Carolin; Kappenberg, Franziska; et al. (Journal of Hepatology, 2025)
In this article, owing to a typesetter error, the supplementary video files were incorrectly named. This has now been updated online. The publisher apologises for any inconvenience caused.
CRIS-Team Scopus Importer:2025-04-01

ESC Working Group Cellular Biology of the Heart: Position Paper: improving the preclinical assessment of novel cardioprotective therapies - Lecour, Sandrine; Botker, Hans E.; Condorelli, Gianluigi; Davidson, Sean M.; Garcia-Dorado, David; Engel, Felix; Ferdinandy, Peter; Heusch, Gerd; Madonna, Rosalinda; Ovize, Michel; Ruiz-Meana, Marisol; Schulz, Rainer; et al. (Cardiovascular Research, 2014)
Ischaemic heart disease (IHD) remains the leading cause of death and disability worldwide. As a result, novel therapies are still needed to protect the heart from the detrimental effects of acute ischaemia-reperfusion injury, in order to improve clinical outcomes in IHD patients. In this regard, although a large number of novel cardioprotective therapies discovered in the research laboratory have been investigated in the clinical setting, only a few of these have been demonstrated to improve clinical outcomes. One potential reason for this lack of success may have been the failure to thoroughly assess the cardioprotective efficacy of these novel therapies in suitably designed preclinical experimental animal models. Therefore, the aim of this Position Paper by the European Society of Cardiology Working Group Cellular Biology of the Heart is to provide recommendations for improving the preclinical assessment of novel cardioprotective therapies discovered in the research laboratory, with the aim of increasing the likelihood of success in translating these new treatments into improved clinical outcomes.
EVALuna2:25478

ESC Working Group on Cellular Biology of the Heart: Tissue Engineering and Cell-Based Therapies for Cardiac Repair in Ischemic Heart Disease and Heart Failure - Madonna, Rosalinda; Van Laake, Linda W.; Botker, Hans Erik; Davidson, Sean M.; De Caterina, Raffaele; Engel, Felix; Eschenhagen, Thomas; Fernandez-Aviles, Francesco; Hausenloy, Derek J.; Hulot, Jean Sebastien; Lecour, Sandrine; Leor, Jonathan; et al. (Cardiovascular Research, 2019)
Morbidity and mortality from ischemic heart disease (IHD) and heart failure (HF) remain significant in Europe and are increasing worldwide. Patients with IHD or HF might benefit from novel therapeutic strategies, such as cell-based therapies. We recently discussed the therapeutic potential of cell-based therapies and provided recommendations on how to improve the therapeutic translation of these novel strategies for effective cardiac regeneration and repair. Despite major advances in optimizing these strategies with respect to cell source and delivery method, the clinical outcome of cell-based therapy remains unsatisfactory. Major obstacles are the low engraftment and survival rate of transplanted cells in the harmful microenvironment of the host tissue, and the paucity or even lack of endogenous cells with repair capacity. Therefore, new ways of delivering cells and their derivatives are required in order to empower cell-based cardiac repair and regeneration in patients with IHD or HF. Strategies using tissue engineering (TE) combine cells with matrix materials to enhance cell retention or cell delivery in the transplanted area, and have recently received much attention for this purpose. Here, we summarize knowledge on novel approaches emerging from the TE scenario. In particular, we will discuss how combinations of cell/bio-materials (e.g., hydrogels, cell sheets, prefabricated matrices, microspheres, and injectable matrices) combinations might enhance cell retention or cell delivery in the transplantation areas and thereby increase the success rate of cell therapies for IHD and HF. We will not focus on the use of classical engineering approaches, employing fully synthetic materials, because of their unsatisfactory material properties which render them not clinically applicable. The overall aim of this Position Paper from the ESC Working Group Cellular Biology of the Heart is to provide recommendations on how to proceed in research with these novel tissue engineering strategies combined with cell-based therapies to boost cardiac repair in the clinical settings of IHD and HF.
EVALuna2:35428

Essential role of DNA-PKcs and plasminogen for the development of doxorubicin-induced glomerular injury in mice - Bohnert, Bernhard N.; Gonzalez-Menendez, Irene; Dörffel, Thomas; Schneider, Jonas C.; Xiao, Mengyun; Janessa, Andrea; Kalo, M. Zaher; Fehrenbacher, Birgit; Schaller, Martin; Casadei, Nicolas; Amann, Kerstin Ute; Daniel, Christoph; et al. (Disease Models & Mechanisms, 2021)
Susceptibility to doxorubicin-induced nephropathy (DIN), a toxic model for the induction of proteinuria in mice, is related to the single-nucleotide polymorphism (SNP) C6418T of the Prkdc gene encoding for the DNA-repair enzyme DNA-PKcs. In addition, plasminogen (Plg) has been reported to play a role in glomerular damage. Here, we investigated the interdependence of both factors for the development of DIN. Genotyping confirmed the SNP of the Prkdc gene in C57BL/6 (PrkdcC6418/C6418) and 129S1/SvImJ (PrkdcT6418/T6418) mice. Intercross of heterozygous 129SB6F1 mice led to 129SB6F2 hybrids with Mendelian inheritance of the SNP. After doxorubicin injection, only homozygous F2 mice with PrkdcT6418/T6418 developed proteinuria. Genetic deficiency of Plg (Plg-/-) in otherwise susceptible 129S1/SvImJ mice led to resistance to DIN. Immunohistochemistry revealed glomerular binding of Plg in Plg+/+ mice after doxorubicin injection involving histone H2B as Plg receptor. In doxorubicin-resistant C57BL/6 mice, Plg binding was absent. In conclusion, susceptibility to DIN in 129S1/SvImJ mice is determined by a hierarchical two-hit process requiring the C6418T SNP in the Prkdc gene and subsequent glomerular binding of Plg.
CRIS-Team Scopus Importer:2021-10-15
Keywords: DNA-pkcs; Doxorubicin; Nephropathy; Plasminogen; Prkdc

Ethylene glycol poisoning - Garibashvili, Tamara; Roeder, Maximilian; Pfluegler, Carolin; Breckner, Martin; Amann, Kerstin Ute; Heckmann, Josef G. (Practical Neurology, 2022)
CRIS-Team WoS Importer:2022-10-21

Europe-side external quality assessment (EQA) of RNA based testing of ER, PR, HER2 and Ki67 in invasive breast cancer - Erber, Ramona; Hartmann, Arndt; Fasching, Peter; Stöhr, Robert; Beckmann, Matthias; Zentgraf, M.; Rübner, Matthias; Hübner, Hanna; Fischer, J.; Guerini Rocco, E.; Viale, G.; Cayre, A.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-06-26

Experimental renal transplantation in rats improves cardiac dysfunction caused by chronic kidney disease while LVH persists - Hagmayer, Linda; Mayer, Christina; Ebert, Nadja; Amann, Kerstin Ute; Daniel, Christoph (Frontiers in Cardiovascular Medicine, 2023)
Background: Chronic kidney disease (CKD) causes congestive heart failure (CHF) with systolic dysfunction and left ventricular hypertrophy (LVH), which is a major contributor to increased mortality in CKD patients. It remains unclear whether cardiovascular changes that occur during the course of CKD can be reversed when renal function is restored by transplantation. Methods: To investigate this, chronic kidney disease was established in F344 rats by subtotal nephrectomy (SNx) for 8 weeks, followed by transplantation of a functional kidney from an isogenic F344 donor. SNx rats without transplantation and sham-operated animals served as controls. Renal function was assessed before and throughout the experiment. In addition, cardiac ultrasound was performed at weeks 0, 8, 12 and 16. At the end of the experiment, intra-arterial blood pressure was measured and kidneys and hearts were histologically and molecularly examined. Results: Eight weeks after SNx, rats developed marked renal dysfunction associated with significant glomerulosclerosis and tubulointerstitial fibrosis, but also an increase in left ventricular mass. After transplantation, renal function normalized but relative heart weight and ventricular mass as assessed by ultrasound scans showed no reduction compared with SNx controls. However, left ventricular wall thickness, fractional shortening and ejection fraction was normalized by renal transplantation. At 8 weeks after kidney transplantation, cardiac expression of BNP and FGF23 was also at levels comparable to healthy controls, whereas these factors were significantly increased in SNx rats. Cardiac fibrosis, as measured by fibronectin mRNA expression, was completely normalized, whereas cardiac fibronectin protein was still slightly but not significantly increased in transplanted animals compared to controls. In addition, the myofibroblast marker collagen 1, as assessed by immunohistochemistry, was significantly increased in SNx rats and also normalized by renal transplantation. Interestingly, CD68+ macrophages were significantly reduced in the hearts of SNx rats and in transplanted animals at slightly higher levels compared to controls. Conclusion: Restoration of renal function by kidney transplantation normalized early cardiac changes at most functional and molecular levels, but did not completely reverse LVH. However, further studies are needed to determine whether restoration of renal function can also reverse LVH at a later time point.
CRIS-Team Scopus Importer:2023-08-11
Keywords: cardiac hypertrophy; chronic kidney disease; FGF23; fibrosis; renal tranplantation

Expression of Immune Phenotypes in Rectal Cancer after neoadjuvant Chemoradiotherapy - Schnellhardt, Sören; Hirneth, Johannes; Büttner-Herold, Maike; Daniel, Christoph; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Expression of the Alpha8 Integrin Chain Facilitates Phagocytosis by Renal Mesangial Cells - Marek, Ines; Becker, Robert; Fahlbusch, Fabian B.; Menendez-Castro, Carlos; Rascher, Wolfgang; Daniel, Christoph; Volkert, Gudrun; Hartner, Andrea (Cellular Physiology and Biochemistry, 2018)
BACKGROUND/AIMS: Healing of mesangioproliferative glomerulonephritis involves degradation of excess extracellular matrix, resolution of hypercellularity by apoptosis and phagocytosis of apoptotic cells. Integrin receptors participate in the regulation of phagocytosis. In mice deficient for alpha8 integrin (Itga8-/-) healing of glomerulonephritis is delayed. As Itga8 is abundant in mesangial cells (MC) which are non-professional phagocytes, we hypothesized that Itga8 facilitates phagocytosis of apoptotic cells and matrix components by MC. METHODS: MC were isolated from wild type (WT) and Itga8-/- mice. Latex beads were coated with matrix components. Apoptosis was induced by cisplatin in macrophages and in DiI-stained MC. After coincubation of latex beads or apoptotic cells with MC, the phagocytosis rate was detected in WT and Itga8-/- MC via fluorescence microscopy and FACS analysis. RESULTS: Itga8-/- MC showed reduced phagocytosis of matrix-coated beads and apoptotic cells compared to WT MC. Reduction of stress fibers was observed in Itga8-/- compared to WT MC. Inhibition of cytoskeletal reorganization by inhibition of Rac1 or ROCK during phagocytosis significantly decreased the rate of phagocytosis by WT MC but not by Itga8-/- MC. CONCLUSION: The expression of Itga8 facilitates phagocytosis in MC, likely mediated by Itga8-cytoskeleton interactions. An impairment of MC phagocytosis might thus contribute to a delayed glomerular regeneration in Itga8-/- mice.
EVALuna2:34300

Expression of transforming growth factor beta 1-related signaling proteins in irradiated vessels - Preidl, Raimund; Moebius, Patrick; Weber, Manuel; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Schlegel, Andreas; Wehrhan, Falk (Strahlentherapie und Onkologie, 2015)
Microvascular free tissue transfer is a standard method in head and neck reconstructive surgery. However, previous radiotherapy of the operative region is associated with an increased incidence in postoperative flap-related complications and complete flap loss. As transforming growth factor beta (TGF-?) 1 and galectin-3 are well known markers in the context of fibrosis and lectin-like oxidized low-density lipoprotein 1 (LOX-1) supports vascular atherosclerosis, the aim of this study was to evaluate the expression of TGF-?1 and related markers as well as LOX-1 in irradiated vessels.To evaluate the expression of galectin-3, Smad 2/3, TGF-?1, and LOX-1, 20 irradiated and 20 nonirradiated arterial vessels were used for immunohistochemical staining. We semiquantitatively assessed the ratio of stained cells/total number of cells (labeling index).Expression of galectin-3, Smad 2/3, and TGF-?1 was significantly increased in previously irradiated vessels compared with nonirradiated controls. Furthermore, LOX-1 was expressed significantly higher in irradiated compared with nonirradiated vessels.Fibrosis-related proteins like galectin-3, Smad 2/3, and TGF-?1 are upregulated after radiotherapy and support histopathological changes leading to vasculopathy of the irradiated vessels. Furthermore, postoperative complications in irradiated patients can be explained by increased endothelial dysfunction caused by LOX-1 in previously irradiated patients. Consequently, not only TGF-?1 but also galectin-3inhibitors may decrease complications after microsurgical tissue transfer.
EVALuna2:24387

Extracellular DNA traps in inflammation, injury and healing - Daniel, Christoph; Leppkes, Moritz; Munoz, Luis Enrique; Muñoz, Luis E.; Schley, Gunnar; Schett, Georg; Herrmann, Martin (Nature Reviews Nephrology, 2019)
Following strong activation signals, several types of immune cells reportedly release chromatin and granular proteins into the extracellular space, forming DNA traps. This process is especially prominent in neutrophils but also occurs in other innate immune cells such as macrophages, eosinophils, basophils and mast cells. Initial reports demonstrated that extracellular traps belong to the bactericidal and anti-fungal armamentarium of leukocytes, but subsequent studies also linked trap formation to a variety of human diseases. These pathological roles of extracellular DNA traps are now the focus of intensive biomedical research. The type of pathology associated with the release of extracellular DNA traps is mainly determined by the site of trap formation and the way in which these traps are further processed. Targeting the formation of aberrant extracellular DNA traps or promoting their efficient clearance are attractive goals for future therapeutic interventions, but the manifold actions of extracellular DNA traps complicate these approaches.
CRIS-Team Scopus Importer:2019-07-09

Extracellular vesicles in diagnostics and therapy of the ischaemic heart: Position Paper from the Working Group on Cellular Biology of the Heart of the European Society of Cardiology - Sluijter, Joost Petrus Gerardus; Davidson, Sean Michael; Boulanger, Chantal M.; Buzas, Edit Iren; De Kleijn, Dominique Paschalis Victor; Engel, Felix; Giricz, Zoltan; Hausenloy, Derek J.; Kishore, Raj; Lecour, Sandrine; Leor, Jonathan; Madonna, Rosalinda; et al. (Cardiovascular Research, 2018)
Extracellular vesicles (EVs)-particularly exosomes and microvesicles (MVs)-are attracting considerable interest in the cardiovascular field as the wide range of their functions is recognized. These capabilities include transporting regulatory molecules including different RNA species, lipids, and proteins through the extracellular space including blood and delivering these cargos to recipient cells to modify cellular activity. EVs powerfully stimulate angiogenesis, and can protect the heart against myocardial infarction. They also appear to mediate some of the paracrine effects of cells, and have therefore been proposed as a potential alternative to cell-based regenerative therapies. Moreover, EVs of different sources may be useful biomarkers of cardiovascular disease identities. However, the methods used for the detection and isolation of EVs have several limitations and vary widely between studies, leading to uncertainties regarding the exact population of EVs studied and how to interpret the data. The number of publications in the exosome and MV field has been increasing exponentially in recent years and, therefore, in this ESC Working Group Position Paper, the overall objective is to provide a set of recommendations for the analysis and translational application of EVs focussing on the diagnosis and therapy of the ischaemic heart. This should help to ensure that the data from emerging studies are robust and repeatable, and optimize the pathway towards the diagnostic and therapeutic use of EVs in clinical studies for patient benefit.
EVALuna2:25557

Factor inhibiting HIF limits the expression of hypoxia-inducible genes in podocytes and distal tubular cells - Schödel, Johannes; Bohr, Daniela; Klanke, Bernd; Schley, Gunnar; Schlötzer-Schrehardt, Ursula; Warnecke, Christina; Kurtz, Armin; Amann, Kerstin Ute; Eckardt, Kai-Uwe; Willam, Carsten (Kidney International, 2010)
The two hypoxia-inducible factors (HIF-1α and HIF-2α) are transcription factors that regulate the response to hypoxia. Recently, the factor inhibiting HIF (FIH1) was identified as a molecular oxygen-dependent dioxygenase that blunts the transcriptional activity of HIF and has also been implicated in HIF-dependent and-independent hypoxia responses. Interestingly, HIF accumulation in the kidney has been shown to confer renal protection and to also cause glomerular injury or enhance renal fibrosis. In order to better understand the regulation of hypoxia-inducible genes, we determined the expression of FIH1 in the kidney and its functional role in isolated renal cells. FIH1 was expressed only in distal tubules and in podocytes, thus showing a very distinct expression pattern, partially overlapping with sites of HIF-1α expression. In tubular cells, RNA silencing of FIH1 caused transcriptional activation of HIF target genes during hypoxia. In contrast, FIH1 silencing in podocytes enhanced transcription of hypoxia-inducible genes in an HIF-independent manner. Using the anti-Thy.1 rat model of glomerulonephritis, we found a gradual decrease of glomerular FIH1 expression during disease progression paralleled by an increase in hypoxia-inducible genes including CXCR4, a mediator of glomerular inflammation. Thus, FIH1 appears to be a suppressor of oxygen-dependent genes in the kidney, operating through HIF-dependent and-independent mechanisms. © 2010 International Society of Nephrology.
CRIS-Team Scopus Importer:2024-05-13
Keywords: cell biology and structure; hypoxia; immunohistochemistry; podocyte; tubule cells

Fatal Puumala Hantavirus Infection in a Patient with Common Variable Immunodeficiency (CVID) - Steininger, Philipp; Herbst, Larissa; Bihlmaier, Karl; Willam, Carsten; Koerper, Sixten; Schrezenmeier, Hubert; Klueter, Harald; Pfister, Frederick; Amann, Kerstin Ute; Weiss, Sabrina; Krueger, Detlev H.; Zimmermann, Robert; et al. (Microorganisms, 2023)
Puumala hantavirus (PUUV) infections usually show a mild or moderate clinical course, but may sometimes also lead to life-threatening disease. Here, we report on a 60-year-old female patient with common variable immunodeficiency (CVID) who developed a fatal PUUV infection with persistent renal failure, thrombocytopenia, and CNS infection with impaired consciousness and tetraparesis. Hantavirus-specific antibodies could not be detected due to the humoral immunodeficiency. Diagnosis and virological monitoring were based on the quantitative detection of PUUV RNA in blood, cerebrospinal fluid, bronchial lavage, and urine, where viral RNA was found over an unusually extended period of one month. Due to clinical deterioration and virus persistence, treatment with ribavirin was initiated. Additionally, fresh frozen plasma (FFP) from convalescent donors with a history of PUUV infection was administered. Despite viral clearance, the clinical condition of the patient did not improve and the patient died on day 81 of hospitalization. This case underlines the importance of the humoral immune response for the course of PUUV disease and illustrates the need for PCR-based virus diagnostics in those patients. Due to its potential antiviral activity, convalescent plasma should be considered in the therapy of severe hantavirus diseases.
CRIS-Team Scopus Importer:2023-03-10
Keywords: common variable immunodeficiency; convalescent plasma; encephalitis; Puumala hantavirus; ribavirin

FGF1-mediated cardiomyocyte cell cycle reentry depends on the interaction of FGFR-1 and Fn14 - Novoyatleva, Tatyana; Sajjad, Amna; Pogoryelov, Denys; Patra, Chinmoy; Schermuly, Ralph T.; Engel, Felix (The FASEB Journal, 2014)
Fibroblast growth factors (FGFs) signal through FGF receptors (FGFRs) mediating a broad range of cellular functions during embryonic development, as well as disease and regeneration during adulthood. Thus, it is important to understand the underlying molecular mechanisms that modulate this system. Here, we show that FGFR-1 can interact with the TNF receptor superfamily member fibroblast growth factor-inducible molecule 14 (Fn14) resulting in cardiomyocyte cell cycle reentry. FGF1-induced cell cycle reentry in neonatal cardiomyocytes could be blocked by Fn14 inhibition, while TWEAK-induced cell cycle activation was inhibited by blocking FGFR-1 signaling. In addition, costimulation experiments revealed a synergistic effect of FGF1 and TWEAK in regard to cardiomyocyte cell cycle induction via PI3K/Akt signaling. Overexpression of Fn14 with either FGFR-1 long [FGFR-1(L)] or FGFR-1 short [FGFR-1(S)] isoforms resulted after FGF1/TWEAK stimulation in cell cycle reentry of >40% adult cardiomyocytes. Finally, coimmunoprecipitation and proximity ligation assays indicated that endogenous FGFR-1 and Fn14 interact with each other in cardiomyocytes. This interaction was strongly enhanced in the presence of their corresponding ligands, FGF1 and TWEAK. Taken together, our data suggest that FGFR-1/Fn14 interaction may represent a novel endogenous mechanism to modulate the action of these receptors and their ligands and to control cardiomyocyte cell cycle reentry.
EVALuna2:25462

Fibroblastic reticular cells mitigate acute GvHD via MHCII-dependent maintenance of regulatory T cells - Shaikh, Haroon; Pezoldt, Joern; Mokhtari, Zeinab; Vargas, Juan Gamboa; Le, Duc Dung; Mosca, Josefina Peña; Viera, Estibaliz Arellano; Kern, Michael A.G.; Graf, Caroline; Beyersdorf, Niklas; Lutz, Manfred B.; Riedel, Angela; et al. (JCI Insight, 2022)
Acute graft versus host disease (aGvHD) is a life-threatening complication of allogeneic hematopoietic cell transplantation (allo-HCT) inflicted by alloreactive T cells primed in secondary lymphoid organs (SLOs) and subsequent damage to aGvHD target tissues. In recent years, Treg transfer and/or expansion has emerged as a promising therapy to modulate aGvHD. However, cellular niches essential for fostering Tregs to prevent aGvHD have not been explored. Here, we tested whether and to what extent MHC class II (MHCII) expressed on Ccl19+ fibroblastic reticular cells (FRCs) shape the donor CD4+ T cell response during aGvHD. Animals lacking MHCII expression on Ccl19-Cre-expressing FRCs (MHCIIΔCcl19) showed aberrant CD4+ T cell activation in the effector phase, resulting in exacerbated aGvHD that was associated with significantly reduced expansion of Foxp3+ Tregs and invariant NK T (iNKT) cells. Skewed Treg maintenance in MHCIIΔCcl19 mice resulted in loss of protection from aGvHD provided by adoptively transferred donor Tregs. In contrast, although FRCs upregulated costimulatory surface receptors, and although they degraded and processed exogenous antigens after myeloablative irradiation, FRCs were dispensable to activate alloreactive CD4+ T cells in 2 mouse models of aGvHD. In summary, these data reveal an immunoprotective, MHCII-mediated function of FRC niches in secondary lymphoid organs (SLOs) after allo-HCT and highlight a framework of cellular and molecular interactions that regulate CD4+ T cell alloimmunity.
CRIS-Team Scopus Importer:2022-12-16

Fibronectin is up-regulated in podocytes by mechanical stress - Kliewe, Felix; Kaling, Sören; Lötzsch, Henriette; Artelt, Nadine; Schindler, Maximilian; Rogge, Henrik; Schröder, Sindy; Scharf, Christian; Amann, Kerstin Ute; Daniel, Christoph; Lindenmeyer, Maja T.; Cohen, Clemens D.; et al. (The FASEB Journal, 2019)
Hypertension is one of the central causes of kidney damage. In the past it was shown that glomerular hypertension leads to morphologic changes of podocytes and effacement and is responsible for detachment of these postmitotic cells. Because we have shown that podocytes are mechanosensitive and respond to mechanical stress by reorganization of the actin cytoskeleton in vitro, we look for mechanotransducers in podocytes. In this study, we demonstrate that the extracellular matrix protein fibronectin (Fn1) might be a potential candidate. The present study shows that Fn1 is essential for the attachment of podocytes during mechanical stress. By real-time quantitative PCR as well as by liquid chromatography-mass spectrometry, we found a significant up-regulation of Fn1 caused by mechanical stretch (3 d, 0.5 Hz, and 5% extension). To study the role of Fn1 in cultured podocytes under mechanical stress, Fn1 was knocked down (Fn1 KD) by a specific small interfering RNA. Additionally, we established a Fn1 knockout (KO) podocyte cell line (Fn1 KO) by clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9). During mechanical stress, a significant loss of podocytes (>80%) was observed in Fn1 KD as well as Fn1 KO podocytes compared with control cells. Furthermore, Fn1 KO podocytes showed a significant down-regulation of the focal adhesion proteins talin, vinculin, and paxillin and a reduced cell spreading, indicating an important role of Fn1 in adhesion. Analyses of kidney sections from patients with diabetic nephropathy have shown a significant up-regulation of FN1 in contrast to control biopsies. In summary, we show that Fn1 plays an important role in the adaptation of podocytes to mechanical stress.-Kliewe, F., Kaling, S., Lötzsch, H., Artelt, N., Schindler, M., Rogge, H., Schröder, S., Scharf, C., Amann, K., Daniel, C., Lindenmeyer, M. T., Cohen, C. D., Endlich, K., Endlich, N. Fibronectin is up-regulated in podocytes by mechanical stress.
EVALuna2:204845
Keywords: Fn1; extracellular matrix; hypertension; mechanical load; diabetic nephropathy

Fine particulate matter (PM2.5) induces microRNA-192–5p causing glomerular damage - Yarbakht, Melina; Sarau, George; Xu, Yanyi; Fang, Xinyi; Mirzaei, Zeynab; Krüger, René; Xiao, Yalan; Usman, Arslan; Daniel, Christoph; Schiffer, Mario; Christiansen, Silke; Müller-Deile, Janina (Ecotoxicology and Environmental Safety, 2025)
An association between air pollution and the incidence of membranous glomerulonephritis (MGN) has been shown in epidemiological studies. However, the causality of this relationship and data on potential pathomechanisms are still missing. Anti-phospholipase A2 receptor (PLA2R1) antibodies, upregulation of microRNA-192–5p, and decreased expression of its podocyte target nephronectin (NPNT) in patients with MGN have been shown, but the trigger for these regulations remained unknown. The current study aimed to assay the possible role of PM2.5 in the pathogenesis of MGN. In this study, we characterized particulate matter (PM2.5) collected on air filters in Shanghai by scanning electron microscopy, energy dispersive X-ray spectroscopy, X-ray fluorescence, microwave plasma atomic emission spectroscopy, nanoparticle tracking analysis, and Raman spectroscopy. Cultured human podocytes, zebrafish, and mice were exposed to PM2.5 to assess possible effects on glomerular function and ultrastructure. PM2.5 caused a reduction of podocyte-specific markers and upregulation of microRNA-192–5p. Moreover, NPNT/npnt/Npnt were downregulated, while PLA2R1/pla2r1/Pla2r1 were upregulated. PM2.5 was able to cause edema, proteinuria, and glomerular damage with loosening of the glomerular basement membrane and partial podocyte effacement in zebrafish larvae. BulkRNA seq analysis and qPCR of zebrafish larvae showed an increase in inflammatory response and oxidative stress due to the exposure to PM2.5. Long-term exposure of mice to ambient PM2.5 induced glomerular damage, albuminuria, and upregulation of pulmonary microRNA-192–5p. Therefore, air pollution might be involved in developing MGN through inflammatory pathways and the induction of microRNA-192–5p, which targets gene expression important for glomerular cell function.
CRIS-Team Scopus Importer:2025-05-23
Keywords: Air pollution; glomerulus; membranous glomerulonephritis; PM; podocytes; proteinuria; zebrafish model

First report from the German COVID-19 autopsy registry - von Stillfried, Saskia; Bülow, Roman David; Röhrig, Rainer; Boor, Peter; Böcker, Jana; Schmidt, Jens; Tholen, Pauline; Majeed, Raphael; Wienströer, Jan; Weis, Joachim; Bremer, Juliane; Knüchel, Ruth; et al. (The Lancet Regional Health - Europe, 2022)
Background: Autopsies are an important tool in medicine, dissecting disease pathophysiology and causes of death. In COVID-19, autopsies revealed e.g., the effects on pulmonary (micro)vasculature or the nervous system, systemic viral spread, or the interplay with the immune system. To facilitate multicentre autopsy-based studies and provide a central hub supporting autopsy centres, researchers, and data analyses and reporting, in April 2020 the German COVID-19 Autopsy Registry (DeRegCOVID) was launched. Methods: The electronic registry uses a web-based electronic case report form. Participation is voluntary and biomaterial remains at the respective site (decentralized biobanking). As of October 2021, the registry included N=1129 autopsy cases, with 69271 single data points including information on 18674 available biospecimens gathered from 29 German sites. Findings: In the N=1095 eligible records, the male-to-female ratio was 1·8:1, with peaks at 65-69 and 80-84 years in males and >85 years in females. The analysis of the chain of events directly leading to death revealed COVID-19 as the underlying cause of death in 86% of the autopsy cases, whereas in 14% COVID-19 was a concomitant disease. The most common immediate cause of death was diffuse alveolar damage, followed by multi-organ failure. The registry supports several scientific projects, public outreach and provides reports to the federal health authorities, leading to legislative adaptation of the German Infection Protection Act, facilitating the performance of autopsies during pandemics. Interpretation: A national autopsy registry can provide multicentre quantitative information on COVID-19 deaths on a national level, supporting medical research, political decision-making and public discussion. Funding: German Federal Ministries of Education and Research and Health. Hintergrund: Obduktionen sind ein wichtiges Instrument in der Medizin, um die Pathophysiologie von Krankheiten und Todesursachen zu untersuchen. Im Rahmen von COVID-19 wurden durch Obduktionen z.B. die Auswirkungen auf die pulmonale Mikrovaskulatur, das Nervensystem, die systemische Virusausbreitung, und das Zusammenspiel mit dem Immunsystem untersucht. Um multizentrische, auf Obduktionen basierende Studien zu erleichtern und eine zentrale Anlaufstelle zu schaffen, die Obduktionszentren, Forscher sowie Datenanalysen und -berichte unterstützt, wurde im April 2020 das deutsche COVID-19-Autopsieregister (DeRegCOVID) ins Leben gerufen. Methoden: Das elektronische Register verwendet ein webbasiertes elektronisches Fallberichtsformular. Die Teilnahme ist freiwillig und das Biomaterial verbleibt am jeweiligen Standort (dezentrales Biobanking). Im Oktober 2021 umfasste das Register N=1129 Obduktionsfälle mit 69271 einzelnen Datenpunkten, die Informationen über 18674 verfügbare Bioproben enthielten, die von 29 deutschen Standorten gesammelt wurden. Ergebnisse: In den N=1095 ausgewerteten Datensätzen betrug das Verhältnis von Männern zu Frauen 1,8:1 mit Spitzenwerten bei 65-69 und 80-84 Jahren bei Männern und >85 Jahren bei Frauen. Die Analyse der Sequenz der unmittelbar zum Tod führenden Ereignisse ergab, dass in 86 % der Obduktionsfälle COVID-19 die zugrunde liegende Todesursache war, während in 14 % der Fälle COVID-19 eine Begleiterkrankung war. Die häufigste unmittelbare Todesursache war der diffuse Alveolarschaden, gefolgt von Multiorganversagen. Das Register unterstützt mehrere wissenschaftliche Projekte, die Öffentlichkeitsarbeit und liefert Berichte an die Bundesgesundheitsbehörden, was zu einer Anpassung des deutschen Infektionsschutzgesetzes führte und die Durchführung von Obduktionen in Pandemien erleichtert. Interpretation: Ein nationales Obduktionsregister kann multizentrische quantitative Informationen über COVID-19-Todesfälle auf nationaler Ebene liefern und damit die medizinische Forschung, die politische Entscheidungsfindung und die öffentliche Diskussion unterstützen. Finanzierung: Bundesministerien für Bildung und Forschung und für Gesundheit.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Autopsy; Cause of Death; COVID-19; Registry; SARS-CoV-2

First Treatment of Relapsing Rapidly Progressive IgA Nephropathy With Eculizumab After Living Kidney Donation: A Case Report - Herzog, A. L.; Wanner, C.; Amann, Kerstin Ute; Lopau, K. (Transplantation Proceedings, 2017)
IgA nephropathy (IGAN) rarely can present as a crescent and progressive form leading to end-stage renal disease (ESRD) in a short period of time. Recurrence of IGAN after kidney transplantation is frequent, and complement components such as C3, C4d, and C5 seem to be involved. We present a case of a young male patient with ESRD caused by rapidly progressive IGAN and who demonstrated rapid recurrence of crescentic IGAN after kidney donation.In September 2014, a 28-year-old male patient was hospitalized due to IGAN with 60% of crescents. Cyclophosphamide, steroids, and plasmapheresis did not prevent ESRD. After 8 months of peritoneal dialysis, the patient received a blood group-compatible living donor kidney from his 57-year-old mother. Immunosuppression consisted of tacrolimus, mycophenolic acid, and steroids without induction therapy. Acute graft failure occurred 2 months later, and graft biopsy results revealed recurrence of crescentic IGAN. Cyclophosphamide was added to tacrolimus and steroid treatment, but graft function could not be restored despite viable kidney tissue in repeated biopsy specimens. Rescue therapy with 4 single doses of eculizumab was introduced while hemodialysis had already been initiated. After a cumulative dose of 1800 mg of eculizumab, kidney function did not recover.In this case, eculizumab was not effective in treating IGAN recurrence after transplantation. Therapy was started late when hemodialysis had already been initiated; an earlier start of therapy might be more effective.
EVALuna2:25549

Four subunits (αβγδ) of the epithelial sodium channel (ENaC) are expressed in the human eye in various locations - Krüger, Bettina; Schlötzer-Schrehardt, Ursula; Härteis, Silke; Zenkel, Matthias; Chankiewitz, Verena E.; Amann, Kerstin Ute; Kruse, Friedrich; Korbmacher, Christoph (Investigative Ophthalmology & Visual Science, 2012)
The epithelial sodium channel (ENaC) is typically expressed in sodium-absorbing epithelia. Several reports suggest that ENaC is also expressed in ocular tissues and may play a role in aqueous humor secretion and glaucoma. However, the precise localization of ENaC in the human eye is still unclear. Here, the authors studied ENaC expression in 12 normal human donor eyes and in six eyes of patients with glaucoma.Quantitative real-time PCR was used to investigate the expression of ?-, ?-, ?-, and ?-ENaC transcripts in ocular tissues. In addition, the authors performed immunohistochemical studies using recently generated antibodies against human ?- and ?-ENaC.At the mRNA level, all four ENaC subunits were found to be expressed in a wide range of ocular tissues from normal and glaucomatous human eyes, with the cornea, ciliary body, iris, and retina showing the highest expression levels. At the protein level, ?- and ?-ENaC subunits showed distinct distribution patterns and could be immunolocalized primarily to the cell membranes of epithelial cells of the cornea and to the conjunctiva, iris, ciliary body, lens, and retinal pigment epithelium but also to vascular endothelial cells, smooth muscle cells, stromal cells, and retinal neurons. The authors found no altered mRNA level of any subunit in glaucomatous eyes.All four ENaC subunits (????) are expressed in the normal human eye, with distinct localization of subunits possibly reflecting different functional states of the channel. The (patho-)physiological roles of ENaC in the various localizations in the eye remain to be determined.
EVALuna2:4482

From basic mechanisms to clinical applications in heart protection, new players in cardiovascular diseases and cardiac theranostics: meeting report from the third international symposium on "New frontiers in cardiovascular research" - Cabrera-Fuentes, Hector A.; Aragones, Julian; Bernhagen, Juergen; Boening, Andreas; Boisvert, William A.; Botker, Hans E.; Bulluck, Heerajnarain; Cook, Stuart; Di Lisa, Fabio; Engel, Felix; Engelmann, Bernd; Ferrazzi, Fulvia; et al. (Basic Research in Cardiology, 2016)
In this meeting report, particularly addressing the topic of protection of the cardiovascular system from ischemia/reperfusion injury, highlights are presented that relate to conditioning strategies of the heart with respect to molecular mechanisms and outcome in patients' cohorts, the influence of co-morbidities and medications, as well as the contribution of innate immune reactions in cardioprotection. Moreover, developmental or systems biology approaches bear great potential in systematically uncovering unexpected components involved in ischemia-reperfusion injury or heart regeneration. Based on the characterization of particular platelet integrins, mitochondrial redox-linked proteins, or lipid-diol compounds in cardiovascular diseases, their targeting by newly developed theranostics and technologies opens new avenues for diagnosis and therapy of myocardial infarction to improve the patients' outcome.
EVALuna2:9341

Functional genomics meta-analysis to identify gene set enrichment networks in cardiac hypertrophy - Angeloni, Miriam; Thievessen, Ingo; Engel, Felix; Magni, Paolo; Ferrazzi, Fulvia (Biological Chemistry, 2021)
In order to take advantage of the continuously increasing number of transcriptome studies, it is important to develop strategies that integrate multiple expression datasets addressing the same biological question to allow a robust analysis. Here, we propose a meta-analysis framework that integrates enriched pathways identified through the Gene Set Enrichment Analysis (GSEA) approach and calculates for each meta-pathway an empirical p-value. Validation of our approach on benchmark datasets showed comparable or even better performance than existing methods and an increase in robustness with increasing number of integrated datasets. We then applied the meta-analysis framework to 15 functional genomics datasets of physiological and pathological cardiac hypertrophy. Within these datasets we grouped expression sets measured at time points that represent the same hallmarks of heart tissue remodeling ('aggregated time points') and performed meta-analysis on the expression sets assigned to each aggregated time point. To facilitate biological interpretation, results were visualized as gene set enrichment networks. Here, our meta-analysis framework identified well-known biological mechanisms associated with pathological cardiac hypertrophy (e.g., cardiomyocyte apoptosis, cardiac contractile dysfunction, and alteration in energy metabolism). In addition, results highlighted novel, potentially cardioprotective mechanisms in physiological cardiac hypertrophy involving the down-regulation of immune cell response, which are worth further investigation.
CRIS-Team Scopus Importer:2021-06-11
Keywords: cardiac hypertrophy; pathological hypertrophy; pathway network; physiological hypertrophy; transcriptome meta-analysis

Galectin 3 expression in primary oral squamous cell carcinomas - Weber, Manuel; Buettner-Herold, Maike; Distel, Luitpold; Ries, Jutta; Möbius, Patrick; Preidl, Raimund; Geppert, Carol-Immanuel; Neukam, Friedrich Wilhelm; Wehrhan, Falk (BMC Cancer, 2017)
Immunologic factors can promote the progression of oral squamous cell carcinomas (oscc). The phylogenetic highly conserved protein Galectin 3 (Gal3) contributes to cell differentiation and immune homeostasis. There is evidence that Gal3 is involved in the progression of oscc and influences the regulation of macrophage polarization. Macrophage polarization (M1 vs. M2) in solid malignancies like oscc contributes to tumor immune-escape. However, the relationship between macrophage polarization and Gal3 expression in oscc is not yet understood. The current study analyzes the association between histomorphologic parameters (T-, N-, L- Pn-status, grading) and Gal3 expression resp. the ratio between Gal3 expressing cells and CD68 positive macrophages in oscc specimens.Preoperative diagnostic biopsies (n = 26) and tumor resection specimens (n = 34) of T1/T2 oscc patients were immunohistochemically analyzed for Gal3 and CD68 expression. The number of Gal3 expressing cells and the ratio between CD68 and Gal3 expressing cells was quantitatively assessed.In biopsy and tumor resection specimens, the number of Gal3 positive cells as well as the Gal3/CD68 ratio were significantly (p < 0.05) higher in T2 oscc compared to T1 cases. In biopsy specimens, a significantly (p < 0.05) increased Gal3 expression and Gal3/CD68 ratio was associated with the progression marker lymph vessel infiltration (L1). Tumor resection specimens of cases with lymph node metastases (N+) had a significantly (p < 0.05) increased Gal3 expression. Additionally, a high Gal3/CD68 ratio correlated significantly (p < 0.05) with higher grading (G3) in tumor resection specimens.High Gal3 expression in oscc is associated with tumor size (T-status) and parameters of malignancy (N-, L-status, grading). Gal3 might contribute to M2 macrophage mediated local immune tolerance. Gal3 expression shows association with prognosis in oscc and represent a potential therapeutic target.
EVALuna2:24446

GAS2L3: Coordinator of cardiomyocyte cytokinesis? - Gruendl, Marco; Engel, Felix; Gaubatz, Stefan (Cell Cycle, 2017)
EVALuna2:25554

Gastrointestinal involvement in granulomatosis with polyangiitis and microscopic polyangiitis: histological features and outcome - Latus, Joerg; Koetter, Ina; Fritz, Peter; Kimmel, Martin; Biegger, Dagmar; Ott, German; Stange, Eduard F.; Amann, Kerstin Ute; Alscher, Dominik M.; Braun, Niko (International Journal of Rheumatic Diseases, 2014)
Gastrointestinal (GI) involvement in patients with granulomatosis with polyangiitis (GPA) or microscopic polyangiitis (MPA) is rare.Medical charts of seven patients with GPA and MPA and GI involvement were reviewed regarding clinical presentation, outcome, diagnostic tools and therapy. Second, the cellular composition of the inflammatory infiltrate associated with the vascular lesions in histological samples (ileum, colon, rectum, duodenum) were investigated to identify possible treatment targets. Immunohistochemistry was done with antibodies against CD20, CD3 and CD34. Samples from a healthy control group (n = 15) were used for comparison.Mean age at onset of the first symptoms of vasculitis was 48 ± 21.3 years. At time of diagnosis GI symptoms were present in five out of seven patients (71%) and occurred during relapse of the vasculitis in two patients (29%). All patients had abdominal pain, four of seven (57%) had an acute kidney injury and three patients required renal replacement therapy. At the time of diagnosis five of seven patients (71%) required surgery and mean Birmingham Vasculitis Activity Score (BVAS) on admission was high (26.3 ± 7.7). Regarding outcome, one patient died due to gastrointestinal bleeding. Histological analysis showed significantly higher expression of CD3 in this patient compared to the control group (P = 0.02). Analysis of expression of CD20 and CD34 showed no statistically significant differences between patients with GPA and MPA with GI involvement compared to the control group.GI involvement in GPA and MPA is rare. Therapy directed at T cells might be an alternative treatment option.
EVALuna2:25467

Gelatin methacryloyl is a slow degrading material allowing vascularization and long-term use in vivo - Heltmann-Meyer, Stefanie; Steiner, Dominik; Mueller, Claudia; Schneidereit, Dominik; Friedrich, Oliver; Salehi, Sahar; Engel, Felix; Arkudas, Andreas; Horch, Raymund E. (Biomedical Materials, 2021)
In situ tissue engineering is an emerging field aiming at the generation of ready-to-use three-dimensional tissues. One solution to supply a proper vascularization of larger tissues to provide oxygen and nutrients is the arteriovenous loop (AVL) model. However, for this model, suitable scaffold materials are needed that are biocompatible/non-immunogenic, slowly degradable, and allow vascularization. Here, we investigate the suitability of the known gelatin methacryloyl (GelMA)-based hydrogel for in-situ tissue engineering utilizing the AVL model. Rat AVLs are embedded by two layers of GelMA hydrogel in an inert PTFE chamber and implanted in the groin. Constructs were explanted after 2 or 4 weeks and analyzed. For this purpose, gross morphological, histological, and multiphoton microscopic analysis were performed. Immune response was analyzed based on anti-CD68 and anti-CD163 staining of immune cells. The occurrence of matrix degradation was assayed by anti-MMP3 staining. Vascularization was analyzed by anti-alpha-smooth muscle actin staining, multiphoton microscopy, as well as expression analysis of 53 angiogenesis-related proteins utilizing a proteome profiler angiogenesis array kit. Here we show that GelMA hydrogels are stable for at least 4 weeks in the rat AVL model. Furthermore, our data indicate that GelMA hydrogels are biocompatible. Finally, we provide evidence that GelMA hydrogels in the AVL model allow connective tissue formation, as well as vascularization, introducing multiphoton microscopy as a new methodology to visualize neovessel formation originating from the AVL. GelMA is a suitable material for in situ and in vivo TE in the AVL model.
CRIS-Team WoS Importer:2021-09-17

Gene network analysis: from heart development to cardiac therapy - Ferrazzi, Fulvia; Bellazzi, Riccardo; Engel, Felix (Thrombosis and Haemostasis, 2015)
Networks offer a flexible framework to represent and analyse the complex interactions between components of cellular systems. In particular gene networks inferred from expression data can support the identification of novel hypotheses on regulatory processes. In this review we focus on the use of gene network analysis in the study of heart development. Understanding heart development will promote the elucidation of the aetiology of congenital heart disease and thus possibly improve diagnostics. Moreover, it will help to establish cardiac therapies. For example, understanding cardiac differentiation during development will help to guide stem cell differentiation required for cardiac tissue engineering or to enhance endogenous repair mechanisms. We introduce different methodological frameworks to infer networks from expression data such as Boolean and Bayesian networks. Then we present currently available temporal expression data in heart development and discuss the use of network-based approaches in published studies. Collectively, our literature-based analysis indicates that gene network analysis constitutes a promising opportunity to infer therapy-relevant regulatory processes in heart development. However, the use of network-based approaches has so far been limited by the small amount of samples in available datasets. Thus, we propose to acquire high-resolution temporal expression data to improve the mathematical descriptions of regulatory processes obtained with gene network inference methodologies. Especially probabilistic methods that accommodate the intrinsic variability of biological systems have the potential to contribute to a deeper understanding of heart development.
EVALuna2:9255

Gene variants of unknown significance in Fabry disease: Clinical characteristics of c.376A>G (p.Ser126Gly) - Lau, Kolja; Ueceyler, Nurcan; Cairns, Tereza; Lorenz, Lora; Sommer, Claudia; Schindehuette, Magnus; Amann, Kerstin Ute; Wanner, Christoph; Nordbeck, Peter (Molecular Genetics and Genomic Medicine, 2022)
Background: Anderson-Fabry disease (FD) is an X-linked lysosomal storage disorder with varying organ involvement and symptoms, depending on the underlying mutation in the alpha-galactosidase A gene (HGNC: GLA). With genetic testing becoming more readily available, it is crucial to precisely evaluate pathogenicity of each genetic variant, in order to determine whether there is or might be not a need for FD-specific therapy in affected patients and relatives at the time point of presentation or in the future.
CRIS-Team WoS Importer:2022-03-11

Geochemical Characteristics of Groundwater Consumed by Patients with Chronic Kidney Disease with Unknown Aetiology in the Crystalline Dry Zone Terrain of Sri Lanka - Chandrajith, Rohana; Nanayakkara, Nishantha; Zwiener, Christian; Daniel, Christoph; Amann, Kerstin Ute; Barth, Johannes (Exposure and Health, 2023)
Quality of drinking water has become a significant concern with chronic kidney disease of uncertain aetiology (CKDu), particularly in the dry zone regions of Sri Lanka. In this study, groundwaters consumed by biopsy-proven CKDu patients were assessed for identifying possible hydrogeochemical risk factors because histopathological observations are still considered the best method for identifying CKDu cases. Major anions, cations, and 22 trace elements in groundwater were measured in addition to dissolved organic carbon (DOC) and its isotope ratios (expressed as δ13CDOC). Variations of groundwater quality were monitored monthly in five selected wells. The data were compared with a non-endemic region with a similar climatic and socio-economic background. Groundwater used by CKDu cases is predominantly of the Ca–Mg–HCO3 type. Over 88% of the samples showed excess hardness, while 44% showed high fluoride (F−) contents (> 0.60 mg/L). These two parameters are noticeably different compared to groundwater from non-endemic regions with similar geoenvironmental backgrounds. The dissolved organic carbon (DOC) content varied from 0.06 to 0.30 mmol/L with a mean value of 0.15 mmol/L in CKDu wells. In most cases, known nephrotoxic trace elements such as As, Pb, Cd, and U were found to be lower than 0.01 µg/L. Seasonally, F− and Si4+ (as H4SiO4) content fluctuated, even though monsoon rain inputs did not seem to alter the geochemical composition. Principal component analysis (PCA) indicated that the dissolution of aquifer minerals and ion exchange processes are most likely responsible for the groundwater geochemistry in the study terrain. This study highlights the importance of F−, hardness (Ca2+ + Mg2+), and Si4+ in groundwaters of CKDu-related tropical terrains. The synergetic impact of these parameters needs further systematic studies, ideally combined with animal models, to unravel the aetiological mechanisms of CKDu.
CRIS-Team Scopus Importer:2023-04-14
Keywords: CKDu; Dissolved organic carbon; Environmental-nephrotoxin; Fluoride; Silica; Water hardness; Water isotopes

Germline C1GALT1C1 mutation causes a multisystem chaperonopathy - Erger, Florian; Aryal, Rajindra P.; Reusch, Björn; Matsumoto, Yasuyuki; Meyer, Robert; Zeng, Junwei; Knopp, Cordula; Noel, Maxence; Muerner, Lukas; Wenzel, Andrea; Kohl, Stefan; Tschernoster, Nikolai; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Mutations in genes encoding molecular chaperones can lead to chaperonopathies, but none have so far been identified causing congenital disorders of glycosylation. Here we identified two maternal half-brothers with a novel chaperonopathy, causing impaired protein O-glycosylation. The patients have a decreased activity of T-synthase (C1GALT1), an enzyme that exclusively synthesizes the T-antigen, a ubiquitous O-glycan core structure and precursor for all extended O-glycans. The T-synthase function is dependent on its specific molecular chaperone Cosmc, which is encoded by X-chromosomal C1GALT1C1. Both patients carry the hemizygous variant c.59C>A (p.Ala20Asp; A20D-Cosmc) in C1GALT1C1. They exhibit developmental delay, immunodeficiency, short stature, thrombocytopenia, and acute kidney injury (AKI) resembling atypical hemolytic uremic syndrome. Their heterozygous mother and maternal grandmother show an attenuated phenotype with skewed X-inactivation in blood. AKI in the male patients proved fully responsive to treatment with the complement inhibitor Eculizumab. This germline variant occurs within the transmembrane domain of Cosmc, resulting in dramatically reduced expression of the Cosmc protein. Although A20D-Cosmc is functional, its decreased expression, though in a cell or tissue-specific manner, causes a large reduction of T-synthase protein and activity, which accordingly leads to expression of varied amounts of pathological Tn-antigen (GalNAcα1-O-Ser/Thr/Tyr) on multiple glycoproteins. Transient transfection of patient lymphoblastoid cells with wild-type C1GALT1C1 partially rescued the T-synthase and glycosylation defect. Interestingly, all four affected individuals have high levels of galactose-deficient IgA1 in sera. These results demonstrate that the A20D-Cosmc mutation defines a novel O-glycan chaperonopathy and causes the altered O-glycosylation status in these patients.
CRIS-Team Scopus Importer:2023-06-02
Keywords: C1GALT1C1; Cosmc; COSMC-CDG; O-glycosylation; Tn-antigen

Glomerular Endothelial Cell-Derived microRNA-192 Regulates Nephronectin Expression in Idiopathic Membranous Glomerulonephritis. - Müller-Deile, Janina; Sopel, Nina; Ohs, Alexandra; Rose, Victoria; Gröner, Marwin; Wrede, Christoph; Hegermann, Jan; Daniel, Christoph; Amann, Kerstin Ute; Zahner, Gunther; Schiffer, Mario (Journal of the American Society of Nephrology, 2021)
BACKGROUND: Autoantibodies binding to podocyte antigens cause idiopathic membranous glomerulonephritis (iMGN). However, it remains elusive how autoantibodies reach the subepithelial space because the glomerular filtration barrier (GFB) is size selective and almost impermeable for antibodies. METHODS: Kidney biopsies from patients with iMGN, cell culture, zebrafish, and mouse models were used to investigate the role of nephronectin (NPNT) regulating microRNAs (miRs) for the GFB. RESULTS: Glomerular endothelial cell (GEC)-derived miR-192-5p and podocyte-derived miR-378a-3p are upregulated in urine and glomeruli of patients with iMGN, whereas glomerular NPNT is reduced. Overexpression of miR-192-5p and morpholino-mediated npnt knockdown induced edema, proteinuria, and podocyte effacement similar to podocyte-derived miR-378a-3p in zebrafish. Structural changes of the glomerular basement membrane (GBM) with increased lucidity, splitting, and lamellation, especially of the lamina rara interna, similar to ultrastructural findings seen in advanced stages of iMGN, were found. IgG-size nanoparticles accumulated in lucidity areas of the lamina rara interna and lamina densa of the GBM in npnt-knockdown zebrafish models. Loss of slit diaphragm proteins and severe structural impairment of the GBM were further confirmed in podocyte-specific Npnt knockout mice. GECs downregulate podocyte NPNT by transfer of miR-192-5p-containing exosomes in a paracrine manner. CONCLUSIONS: Podocyte NPNT is important for proper glomerular filter function and GBM structure and is regulated by GEC-derived miR-192-5p and podocyte-derived miR-378a-3p. We hypothesize that loss of NPNT in the GBM is an important part of the initial pathophysiology of iMGN and enables autoantigenicity of podocyte antigens and subepithelial immune complex deposition in iMGN.
EVALuna2:483425

Glomerulocapillary miRNA response to HLA-class I antibody in vitro and in vivo - Heinemann, Falko M.; Jindra, Peter T.; Bockmeyer, Clemens L.; Zeuschner, Philip; Wittig, Juliane; Hoeflich, Heike; Esser, Marc; Abbas, Mahmoud; Dieplinger, Georg; Stolle, Katharina; Vester, Udo; Hoyer, Peter F.; et al. (Scientific Reports, 2017)
Changes in miRNA expression glomerular of capillaries during antibody-mediated rejection (ABMR) are poorly understood and could contribute to the deleterious inflammation and fibrosis of ABMR via suppression of target genes. A better understanding could lead to novel diagnostic tools and reveal novel therapeutic targets. We explored deregulated miRNAs in an glomeruloendothelial in vitro model of ABMR due to class I human leukocyte antigen (HLA) with and without complement activation. We studied a set of 16 promising candidate miRNAs in microdissected glomeruli a confirmation set of 20 human transplant biopsies (DSA+) compared to 10 matched controls without evidence for ABMR. Twelve out of these 16 glomerulocapillary miRNAs could successfully be confirmed as dysregulated in vivo with 10 upregulated (let-7c-5p, miR-28-3p, miR-30d-5p, miR-99b-5p, miR-125a-5p, miR-195-5p, miR-374b-3p, miR-484, miR-501-3p, miR-520e) and 2 downregulated (miR29b-3p, miR-885-5p) in DSA+ vs.A random forest analysis based on glomerular miRNAs identified 18/20 DSA+ and 8/10 controls correctly. This glomerulocapillary miRNA signature associated with HLA class I-DSA could improve our understanding of ABMR and be useful for diagnostic or therapeutic purposes.
EVALuna2:25564

GOLD, SILVER, AND BRONZE WITH HIS FATHERS KIDNEY: A LIVING-DONOR KIDNEY TRANSPLANT IN A FAMILY WITH AUTOSOMAL ALPORT SYNDROME - Petzold, Friederike; Bachmann, Anette; Amann, Kerstin Ute; Lindner, Tom H.; Helmchen, Udo; Bergmann, Carsten; Halbritter, Jan (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2019)
CRIS-Team WoS Importer:2019-11-26

Gpr126 (Adgrg6) is expressed in cell types known to be exposed to mechanical stimuli - Musa, Gentian; Cazorla-Vázquez, Salvador; van Amerongen, Machteld J.; Stemmler, Marc; Eckstein, Markus; Hartmann, Arndt; Braun, Thomas; Brabletz, Thomas; Engel, Felix (Annals of the New York Academy of Sciences, 2019)
GPR126 (ADGRG6) is an adhesion G protein–coupled receptor that plays an important role in a variety of tissues/organs, such as heart, sciatic nerve, cartilage, and ear. Moreover, GPR126 (ADGRG6) mutations are associated with human diseases, like adolescent idiopathic scoliosis, lung disease, bladder cancer, and intellectual disability. Despite its clinical importance, it remains elusive how GPR126 is activated and mediates signal transduction and what cellular processes depend on GPR126 signaling. Here, we generated a lacZ reporter mouse line to determine endogenous Gpr126 (Adgrg6) expression in a cell type-specific manner during embryonic development, at postnatal day 5 and in adult animals. Our results confirm Gpr126 expression data previously obtained utilizing antibodies and in situ hybridization in embryonic heart and sciatic nerve. In addition, we provide data with cellular resolution for previously described RT-PCR–based data, including lung and bladder. Moreover, new Gpr126-expressing tissues and cell types were identified, such as ureter and acinar secretory cells. Collectively, our data demonstrate that the newly generated lacZ reporter mouse is a suitable model to study Gpr126 expression during development and adulthood, provide detailed insight into Gpr126 expression at the cellular level, and reveal that all identified Gpr126-expressing cells are known to be exposed to mechanical stimuli.
CRIS-Team Scopus Importer:2019-06-28
Keywords: ADGRG6; chondrocytes; endothelium; epithelium

Gpr126 domains control different cellular mechanisms of ventricular chamber development - Srivastava, Swati; Gunanwan, F.; Guenther, S.; Ferrazzi, Fulvia; Gentile, A.; Monk, K. M.; Stainier, D. Y. R.; Engel, Felix (EUROPEAN HEART JOURNAL, 2021)
Trabeculation is a crucial process during ventricular chamber development which describes the protrusion of cardiomyocytes into the lumen of the ventricular chamber to form complex muscular structures called trabeculae. Defects in this process results in various human diseases such as left ventricular non compaction cardiomyopathies and other congenital heart defects. Several cellular mechanisms have been identified underlying trabeculation including tension heterogeneity induced cardiomyocyte selection, depolarization and delamination. However, the molecular mechanisms governing trabeculation are still poorly understood.<br
CRIS-Team WoS Importer:2021-12-10

G Protein-coupled Estrogen Receptor Protects from Atherosclerosis - Meyer, Matthias R.; Fredette, Natalie C.; Howard, Tamara A.; Hu, Chelin; Ramesh, Chinnasamy; Daniel, Christoph; Amann, Kerstin Ute; Arterburn, Jeffrey B.; Barton, Matthias; Prossnitz, Eric R. (Scientific Reports, 2014)
Coronary atherosclerosis and myocardial infarction in postmenopausal women have been linked to inflammation and reduced nitric oxide (NO) formation. Natural estrogen exerts protective effects on both processes, yet also displays uterotrophic activity. Here, we used genetic and pharmacologic approaches to investigate the role of the G protein-coupled estrogen receptor (GPER) in atherosclerosis. In ovary-intact mice, deletion of gper increased atherosclerosis progression, total and LDL cholesterol levels and inflammation while reducing vascular NO bioactivity, effects that were in some cases aggravated by surgical menopause. In human endothelial cells, GPER was expressed on intracellular membranes and mediated eNOS activation and NO formation, partially accounting for estrogen-mediated effects. Chronic treatment with G-1, a synthetic, highly selective small molecule agonist of GPER, reduced postmenopausal atherosclerosis and inflammation without uterotrophic effects. In summary, this study reveals an atheroprotective function of GPER and introduces selective GPER activation as a novel therapeutic approach to inhibit postmenopausal atherosclerosis and inflammation in the absence of uterotrophic activity.
EVALuna2:25485

Grundlagen der Nierenpathologie für Pathologen – Teil 2, Nichtentzündliche Veränderungen - Gaspert, Ariana; Büttner-Herold, Maike; Amann, Kerstin Ute (Die Pathologie, 2023)
The evaluation of kidney biopsies for specific renal diseases or kidney transplant biopsies is mainly restricted to specialized centers. Lesions in nonneoplastic renal tissue in partial nephrectomies or nephrectomies due to renal tumors, especially noninflammatory, ischemic, vascular changes or diabetic nephropathy can be of greater prognostic significance than the tumor itself in patients with a localized tumor and good tumor-associated survival. In this part of basic nephropathology for pathologists, the most common noninflammatory lesions of the vascular, glomerular and tubulo-interstitial compartment are discussed.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Diabetic nephropathy; Differential diagnosis; Hypertension; Nephropathy; Thrombotic microangiopathy

GSK3ss-Dependent Dysregulation of Neurodevelopment in SPG11-Patient Induced Pluripotent Stem Cell Model - Mishra, Himanshu Kumar; Prots, Iryna; Havlicek, Steven; Kohl, Zacharias; Pérez-Brangulí, Francesc; Börstler, Tom; Anneser, Lukas; Minakaki, Georgia; Wend, Holger; Hampl, Martin; Leone, Marina; Brückner, Martina; et al. (Annals of Neurology, 2016)
Objective: Mutations in the spastic paraplegia gene 11 (SPG11), encoding spatacsin, cause the most frequent form of autosomal-recessive complex hereditary spastic paraplegia (HSP) and juvenile-onset amyotrophic lateral sclerosis (ALS5). When SPG11 is mutated, patients frequently present with spastic paraparesis, a thin corpus callosum, and cognitive impairment. We previously delineated a neurodegenerative phenotype in neurons of these patients. In the current study, we recapitulated early developmental phenotypes of SPG11 and outlined their cellular and molecular mechanisms in patient-specific induced pluripotent stem cell (iPSC)-derived cortical neural progenitor cells (NPCs).Methods: We generated and characterized iPSC-derived NPCs and neurons from 3 SPG11 patients and 2 age-matched controls.Results: Gene expression profiling of SPG11-NPCs revealed widespread transcriptional alterations in neurodevelopmental pathways. These include changes in cell-cycle, neurogenesis, cortical development pathways, in addition to autophagic deficits. More important, the GSK3ss-signaling pathway was found to be dysregulated in SPG11-NPCs. Impaired proliferation of SPG11-NPCs resulted in a significant diminution in the number of neural cells. The decrease in mitotically active SPG11-NPCs was rescued by GSK3 modulation.Interpretation: This iPSC-derived NPC model provides the first evidence for an early neurodevelopmental phenotype in SPG11, with GSK3ss as a potential novel target to reverse the disease phenotype.

Guanylate-binding protein 1 expression from embryonal endothelial progenitor cells reduces blood vessel density and cellular apoptosis in an axially vascularised tissue-engineered construct - Bleiziffer, Oliver; Hammon, Matthias; Arkudas, Andreas; Taeger, Christian; Beier, Justus; Amann, Kerstin Ute; Naschberger, Elisabeth; Stürzl, Michael; Horch, Raymund E.; Kneser, Ulrich (BMC Biotechnology, 2012)
Background: Guanylate binding protein-1 (GBP-1) is a large GTPase which is actively secreted by endothelial cells. It is a marker and intracellular inhibitor of endothelial cell proliferation, migration, and invasion. We previously demonstrated that stable expression of GBP-1 in murine endothelial progenitor cells (EPC) induces their premature differentiation and decreases their migration capacity in vitro and in vivo. The goal of the present study was to assess the antiangiogenic capacity of EPC expressing GBP-1 (GBP-1-EPC) and their impact on blood vessel formation in an axially vascularized 3-D bioartificial construct in vivo.Results: Functional in vitro testing demonstrated a significant increase in VEGF secretion by GBP-1-EPC after induction of cell differentiation. Undifferentiated GBP-1-EPC, however, did not secrete increased levels of VEGF compared to undifferentiated control EPC expressing an empty vector (EV-EPC). In our In vivo experiments, we generated axially vascularized tissue-engineered 3-D constructs. The new vascular network arises from an arterio-venous loop (AVL) embedded in a fibrin matrix inside a separation chamber. Total surface area of the construct as calculated from cross sections was larger after transplantation of GBP-1-EPC compared to control EV-EPC. This indicated reduced formation of fibrovascular tissue and less resorption of fibrin matrix compared to constructs containing EV-EPC. Most notably, the ratio of blood vessel surface area over total construct surface area in construct cross sections was significantly reduced in the presence of GBP-1-EPC. This indicates a significant reduction of blood vessel density and thereby inhibition of blood vessel formation from the AVL constructs caused by GBP-1. In addition, GBP-1 expressed from EPC significantly reduced cell apoptosis compared to GBP-1-negative controls.Conclusion: Transgenic EPC expressing the proinflammatory antiangiogenic GTPase GBP-1 can reduce blood vessel density and inhibit apoptosis in a developing bioartificial vascular network and may become a new powerful tool to manipulate angiogenetic processes in tissue engineering and other pathological conditions such as tumour angiogenesis. © 2012 Bleiziffer et al.; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Endothelial progenitor cells; Guanylate-binding protein 1; In vivo tissue engineering

Harnessing the Expression of TNFR2 on Tregs to Prevent Agvhd - Vargas, Juan Gamboa; Kanzler, Carla; Scheller, Lukas; Kreckel, Jennifer; Shaikh, Haroon; Lang, Isabell; Medler, Juliane; Anany, Mohamed; Steinfatt, Tim; Hartweg, Julia; Haack, Stefanie; Holler, Ernst; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Heart Development, Angiogenesis, and Blood-Brain Barrier Function Is Modulated by Adhesion GPCRs - Musa, Gentian; Engel, Felix; Niaudet, Colin (Handbook of experimental pharmacology, 2016)
The cardiovascular system in adult organisms forms a network of interconnected endothelial cells, supported by mural cells and displaying a high degree of hierarchy: arteries emerging from the heart ramify into arterioles and then capillaries, which return to the venous systems through venules and veins. The cardiovascular system allows blood circulation, which in turn is essential for hemostasis through gas diffusion, nutrient distribution, and cell trafficking. In this chapter, we have summarized the current knowledge on how adhesion GPCRs (aGPCRs) impact heart development, followed by their role in modulating vascular angiogenesis.
EVALuna2:25530

Hemophagocytic lymphohistiocytosis and thrombotic microangiopathy after parvovirus B19 infection and renal transplantation: a case report - Steffen, C. J.; Koch, N.; Eckardt, K. U.; Amann, Kerstin Ute; Seelow, E.; Schreiber, A. (BMC Nephrology, 2021)
Background: Hemophagocytic lymphohistiocytosis (HLH) is a rare and life-threatening disease characterized by hyperactivation of the immune system that causes hypercytokinemia and potentially multi organ failure. HLH can occur in patients with underlying rheumatic or autoinflammatory disorders. Additionally, HLH can develop in patients during infections or malignancies without a known genetic predisposition. Case presentation: We herein report a patient, who presented with fever, both acute kidney and liver injury, anemia, thrombocytopenia and HSV stomatitis. HLH was diagnosed based on clinical criteria and qPCR revealed an acute parvovirus B19 infection as potential underlying infectious trigger. Treatment was started with both IVIG and dexamethasone. Subsequently, kidney biopsy demonstrated TMA. Conclusions: In rare cases both HLH and aHUS can occur simultaneously in a patient as a consequence of viral infections. Insights from this unusual case might help physicians understand this complex symptom constellation.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Atypical hemorrhagic uremic syndrome (aHUS); Case report; Hemophagocytic Lymphohistiocytosis (HLH); Parvovirus B19

Hepatocyte differentiation markers in adenocarcinoma of the prostate: hepatocyte paraffin 1 but not arginase-1 is specifically expressed in a subset of prostatic adenocarcinoma - Giedl, Josef; Buettner-Herold, Maike; Wach, Sven; Wullich, Bernd; Hartmann, Arndt; Agaimy, Abbas (Human Pathology, 2016)
Prostate adenocarcinoma and hepatocellular carcinoma (HCC) are common cancer types. Both may present with bone metastases, and both are known to be CK7/CK20 negative. Thus, diagnosis of less well-differentiated tumors at metastatic sites essentially relies on immunohistochemical confirmation. However, insufficient data exist on the expression status of the main 2 hepatocyte markers hepatocyte paraffin 1 (HepPar-1) and arginase-1 (Arg-1) in prostatic adenocarcinoma. We screened 557 prostate carcinoma cases for expression of these 2 markers using tissue microarrays. Sixty-four of 557 (11.5%) cases showed highly variable expression of HepPar-1 in 1% to 75% of tumor cells with a characteristically strong granular "mitochondrial" pattern. Only 13 cases (2.3%) expressed HepPar-1 in greater than 10% of the tumor cells. No correlation was seen with Gleason grade. On the other hand, 19 (3.4%) of 557 cases showed variable nonspecific cytoplasmic expression of Arg-1 distinct from the specific combined nucleocytoplasmic staining seen in normal liver and in HCC. Specifically, this Arg-1 pattern was seen only using one antibody lot and not another suggesting cross-reactivity. Only a single case showed specific nucleocytoplasmic expression of Arg-1 in the tumor cells. In conclusion, specific granular cytoplasmic staining for HepPar-1 is frequent in prostatic adenocarcinomas (11.5%) but usually focal and limited to less than 5% of tumor cells. This should not be misinterpreted as evidence of HCC, particularly in solid-pattern neoplasms. On the other hand, specific Arg-1 expression is very rare (0.18%), highlighting the value of Arg-1 in distinguishing HepPar-1-positive prostatic carcinoma from HCC at metastatic sites or in cases of liver metastasis from prostate carcinoma.
EVALuna2:6774

Heterozygosity of mitogen-activated protein kinase organizer 1 ameliorates diabetic nephropathy and suppresses epithelial-to-mesenchymal transition-like changes in db/db mice - Loeffler, Ivonne; Liebisch, Marita; Daniel, Christoph; Amann, Kerstin Ute; Wolf, Gunter (Nephrology Dialysis Transplantation, 2017)
Progressive diabetic nephropathy (DN) is characterized by tubulointerstitial fibrosis that is caused by accumulation of extracellular matrix. Induced by several factors, matrix-producing myofibroblasts may to some extent originate from tubular cells by epithelial-to-mesenchymal transition (EMT). Although previous data document that activation of hypoxia-inducible factor (HIF) signalling can be renoprotective in acute kidney disease, this issue remains controversial in chronic kidney injury. Here, we studied whether DN and EMT-like changes are ameliorated in a mouse model of type 2 diabetes mellitus with increased stability and activity of the HIF.We used db/db mice that were crossed with transgenic mice expressing reduced levels of mitogen-activated protein kinase organizer 1 (MORG1), a scaffold protein interacting with prolyl hydroxylase domain 3 (PHD3), because of deletion of one MORG1 allele.We found significantly reduced nephropathy in diabetic MORG1 +/- heterozygous mice compared with the diabetic wild-types ( db/db XMORG1 +/+ ). Furthermore, we demonstrated that EMT-like changes in the tubulointerstitium of diabetic wild-type MORG1 +/+ mice are present, whereas diabetic mice with reduced expression of MORG1 showed significantly fewer EMT-like changes.These findings reveal that a deletion of one MORG1 allele inhibits the development of DN in db/db mice. The data suggest that the diminished interstitial fibrosis in these mice is a likely consequence of suppressed EMT-like changes.
EVALuna2:25538

HIF activation protects from acute kidney injury - Weidemann, Alexander; Bernhardt, Wanja M.; Klanke, Bernd; Daniel, Christoph; Buchholz, Björn; Campean, Valentina; Amann, Kerstin Ute; Warnecke, Christina; Wiesener, Michael Sean; Eckardt, Kai-Uwe; Willam, Carsten (Journal of the American Society of Nephrology, 2008)
The contribution of hypoxia to cisplatin-induced renal tubular injury is controversial. Because the hypoxia-inducible factor (HIF) pathway is a master regulator of adaptation to hypoxia, we measured the effects of cisplatin on HIF accumulation in vitro and in vivo, and tested whether hypoxic preconditioning is protective against cisplatin-induced injury. We found that cisplatin did not stabilize HIF-1 alpha protein in vitro or in vivo under normoxic conditions. However, hypoxic preconditioning of cisplatin-treated proximal tubular cells in culture reduced apoptosis in an HIF-1 alpha-dependent fashion and increased cell proliferation as measured by BrdU incorporation. In vivo, rats preconditioned with carbon monoxide before cisplatin administration had significantly better renal function than rats kept in normoxic conditions throughout. Moreover, the histomorphological extent of renal damage and tubular apoptosis was reduced by the preconditional treatment. Therefore, development of pharmacologic agents to induce renal HIF might provide a new approach to ameliorate cisplatin-induced nephrotoxicity.

High frequency of autoantibody-secreting cells and long-lived plasma cells within inflamed kidneys of NZB/W F1 lupus mice - Starke, Charlotte; Frey, Silke; Wellmann, Ute; Urbonaviciute, Vilma; Herrmann, Martin; Amann, Kerstin Ute; Schett, Georg; Winkler, Thomas; Voll, Reinhard E. (European Journal of Immunology, 2011)
Autoantibodies to double-stranded (ds) DNA represent a serological hallmark of systemic lupus erythematosus (SLE) and may critically contribute to the pathogenesis of lupus nephritis. Self-reactive antibodies might be partially produced by long-lived plasma cells (PCs), which mainly reside within the bone marrow and spleen. In contrast to short-lived PCs, long-lived PCs are extremely resistant to therapy and may sustain refractory disease courses. Recently, antibody-secreting cells were found within the inflamed kidneys of New Zealand black/white (NZB/W) F1 lupus mice as well as of patients with SLE. To analyze the longevity of the IgG-producing cells present in nephritic kidneys of NZB/W F1 mice we performed in vivo BrdU-labeling. We identified a higher frequency of long-lived than short-lived renal PCs, indicating that survival niches for long-lived PCs also exist within inflamed kidneys. Using ELISPOT assays, we found that on average 31% of renal IgG-producing cells reacted with dsDNA and 24% with nucleolin. Moreover, the frequencies of IgG-secreting cells specific for the autoantigens dsDNA and nucleolin were higher in the kidneys compared with those in the spleen and bone marrow.
Keywords: Autoantibody-secreting cells; Autoimmunity; Long-lived plasma cells; Lupus nephritis

High RIPK3 expression is associated with a higher risk of early kidney transplant failure - Wahida, Adam; Schmaderer, Christoph; Büttner-Herold, Maike; Branca, Caterina; Donakonda, Sainitin; Haberfellner, Flora; Torrez, Carlos; Schmitz, Jessica; Schulze, Tobias; Seibt, Tobias; Öllinger, Rupert; Engleitner, Thomas; et al. (iScience, 2023)
Renal ischemia-reperfusion injury (IRI) is associated with reduced allograft survival, and each additional hour of cold ischemia time increases the risk of graft failure and mortality following renal transplantation. Receptor-interacting protein kinase 3 (RIPK3) is a key effector of necroptosis, a regulated form of cell death. Here, we evaluate the first-in-human RIPK3 expression dataset following IRI in kidney transplantation. The primary analysis included 374 baseline biopsy samples obtained from renal allografts 10 minutes after onset of reperfusion. RIPK3 was primarily detected in proximal tubular cells and distal tubular cells, both of which are affected by IRI. Time-to-event analysis revealed that high RIPK3 expression is associated with a significantly higher risk of one-year transplant failure and prognostic for one-year (death-censored) transplant failure independent of donor and recipient associated risk factors in multivariable analyses. The RIPK3 score also correlated with deceased donation, cold ischemia time and the extent of tubular injury.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Molecular biology; Nephrology

HIGH RIPK3 EXPRESSION IS ASSOCIATED WITH HIGHER RISK FOR EARLY KIDNEY TRANSPLANT FAILURE - Kemmner, S.; Schmaderer, C.; Büttner-Herold, Maike; Steiger, K.; Haller, B.; Yabal, M.; Renders, L.; Assfalg, V.; Matevossian, E.; Thorban, S.; Heemann, U.; Wahida, A. (TRANSPLANT INTERNATIONAL, 2021)
CRIS-Team WoS Importer:2021-10-15

High Sodium Diet - Role in Renal Sympathodepression - Rodionova, Kristina; Ditting, Tilmann; Fahrmeier, Franziska; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland (FASEB JOURNAL, 2020)
CRIS-Team WoS Importer:2020-10-16

High stroma T-cell infiltration is associated with better survival in stage pT1 bladder cancer - Hülsen, Sabine; Lippolis, Eleonora; Ferrazzi, Fulvia; Otto, Wolfgang; Distel, Luitpold; Fietkau, Rainer; Denzinger, Stefan; Breyer, Johannes; Burger, Maximilian; Bertz, Simone; Eckstein, Markus; Ebner, Annette; et al. (International Journal of Molecular Sciences, 2020)
Stage pT1 bladder cancer (BC) shows highly diverse outcomes. Predictive markers are required to stratify patients for personalized treatment. The present study aimed to validate immune response quantification as a prognostic marker. Patients with pT1 BC (n = 167) treated by transurethral resection of the bladder (TURB) were enrolled. Formaldehyde-fixed paraffin-embedded material was stained for CD3 and CD8. Corresponding T cells were counted in three regions with the highest immune response. Numbers of tertiary lymphoid structures (TLS) and lymphocyte aggregates (LA) were quantified. High CD3+ stroma T-cell infiltration was associated with improved survival (p = 0.045), especially in the G3 subgroup (p = 0.01). Cluster with higher immune response showed less recurrence (p = 0.034) and favorable overall survival (OS) (p = 0.019). In contrast, higher CD3+ and CD8+ tumor T-cell infiltration seemed to have a negative impact on prognosis. TLS and LA were more frequently observed in G3 tumors, indicating an increased antitumoral immune response. We proved the role of immune cell infiltration and showed that higher infiltration numbers of CD3+ (not CD8+) lymphocytes in the stroma are associated with favorable outcome. Immune cell quantification could be used as a marker to help stratify patients’ risk and therefore, to optimize patients’ management and follow-up examination as well as possible therapies.
CRIS-Team Scopus Importer:2020-11-20
Keywords: CD8; Immunoscore; Progression; PT1 bladder cancer; Survival; Tumor-infiltrating lymphocytes (TILs); CD3

Histomorphology and pathogenesis of diabetic nephropathy Histomorphologie und Pathogenese der diabetischen Nephropathie - Amann, Kerstin Ute; Daniel, Christoph (Nephrologe, 2020)
Diabetes mellitus and organ involvement or associated diseases are a medical problem worldwide with an ever increasing incidence and prevalence, not only in western countries. Diabetes mellitus must be taken seriously particularly because the incidence in children and young adults is increasing in a threatening way. It is estimated that in the USA by 2025 every third individual born in 2000 will suffer from diabetes, which in the long term will drastically reduce the life expectation of the population. In addition to cardiovascular diseases, such as high blood pressure, coronary heart disease and stroke, the renal involvement in diabetes mellitus, the so-called diabetic nephropathy (DN) in particular represents an increasing and serious problem. In Germany DN now represents with approximately 35% the leading single course by far of end-stage renal disease. This article deals with the pathogenesis and morphology of DN with a special emphasis on new treatment principles.
CRIS-Team Scopus Importer:2020-02-07
Keywords: Diabetes mellitus; DPP‑4; Kidney; Pathogenesis; SGLT1

HLA-DO: a possible switch between GvHD and GvL effect - Zeun, J.; Neubeck, S.; Lang, Vanessa; Flamann, Cindy; Nagel, L.; Kunert, Timo; Vogler, T.; Brey, Stefanie; Hildner, Kai; Bäuerle, Tobias; Büttner-Herold, Maike; Winkler, Thomas; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Human cytomegaloviral multifunctional protein kinase pUL97 impairs zebrafish embryonic development and increases mortality - Cazorla-Vázquez, Salvador; Steingruber, Mirjam; Marschall, Manfred; Engel, Felix (Scientific Reports, 2019)
Cytomegalovirus is a worldwide-distributed human pathogen, which is the leading cause of congenital virus infection, affecting 0.5 to 2% of live births. To date, it is largely unclear which molecular mechanisms underlie the symptomatic outcomes. This is mainly due to species specificity and limited homology among cytomegalovirus genomes. As it is not possible to infect model organisms with human cytomegalovirus, the aim of this study was to develop a heterologous system allowing in the future the elucidation of the pathological role of individual viral proteins. As a model organism the zebrafish has been chosen due to its ease of manipulation and characterization as well as its large offspring. As cytomegalovirus model protein, pUL97 was characterized because it is multiply involved in virus-host interaction. Here, we show in zebrafish embryos, that (i) pUL97 can be expressed in zebrafish, (ii) increasing pUL97 expression levels quantitatively correlate with both minor and major pathological defects, (iii) pUL97 expression impairs cell cycle progression and induces cell death, (iv) active pUL97, but not an inactive mutant, induces excess mortality, and (v) co-administration of a pUL97 inhibitor reduces embryonic pathology. Collectively, these data indicate the suitability of zebrafish to elucidate the pathological role of human cytomegaloviral proteins.
CRIS-Team Scopus Importer:2019-05-24

Hypoxia inducible factor stabilization improves defective ischemia-induced angiogenesis in a rodent model of chronic kidney disease - Schellinger, Isabel Nahal; Cordasic, Nada; Panesar, Julian; Buchholz, Björn; Jacobi, Johannes; Hartner, Andrea; Klanke, Bernd; Jakubiczka-Smorag, Joanna; Burzlaff, Nicolai; Heinze, Eva; Warnecke, Christina; Raaz, Uwe; et al. (Kidney International, 2017)
Chronic kidney disease (CKD) is associated with increased risk and worse prognosis of cardiovascular disease, including peripheral artery disease. An impaired angiogenic response to ischemia may contribute to poor outcomes of peripheral artery disease in patients with CKD. Hypoxia inducible factors (HIF) are master regulators of angiogenesis and therefore represent a promising target for therapeutic intervention. To test this we induced hind-limb ischemia in rats with CKD caused by 5/6 nephrectomy and administered two different treatments known to stabilize HIF protein in vivo: carbon monoxide and a pharmacological inhibitor of prolyl hydroxylation 2-(1-chloro-4- hydroxyisoquinoline-3-carboxamido) acetate (ICA). Expression levels of pro-angiogenic HIF target genes (Vegf, Vegf-r1, Vegf-r2, Ho-1) were measured by qRT-PCR. Capillary density was measured by CD31 immunofluorescence staining and HIF expression was evaluated by immunohistochemistry. Capillary density in ischemic skeletal muscle was significantly lower in CKD animals compared to sham controls. Rats with CKD showed significantly lower expression of HIF and all measured pro-angiogenic HIF target genes, including VEGF. Both HIF stabilizing treatments rescued HIF target gene expression in animals with CKD and led to significantly higher ischemia-induced capillary sprouting compared to untreated controls. ICA was effective regardless of whether it was administered before or after induction of ischemia and led to a HIF expression in skeletal muscle. Thus, impaired ischemia-induced angiogenesis in rats with CKD can be improved by HIF stabilization, even if started after onset of ischemia.
EVALuna2:3925
Keywords: cardiovascular disease; chronic kidney disease; hypoxia

Hypoxia-inducible protein 2 is a novel lipid droplet protein and a specific target gene of hypoxia-inducible factor-1 - Gimm, Tina; Wiese, Melanie; Teschemacher, Barbara; Deggerich, Anke; Schödel, Johannes; Knaup, Karl; Hackenbeck, Thomas; Hellerbrand, Claus; Amann, Kerstin Ute; Wiesener, Michael; Höning, Stefan; Eckardt, Kai-Uwe; et al. (The FASEB Journal, 2010)
Hypoxia-inducible protein 2 (HIG2) has been implicated in canonical Wnt signaling, both as target and activator. The potential link between hypoxia and an oncogenic signaling pathway might play a pivotal role in renal clear-cell carcinoma characterized by constitutive activation of hypoxia-inducible factors (HIFs), and hence prompted us to analyze HIG2 regulation and function in detail. HIG2 was up-regulated by hypoxia and HIF inducers in all cell types and mouse organs investigated and abundantly expressed in renal clear-cell carcinomas. Promoter analyses, gel shifts, and siRNA studies revealed that HIG2 is a direct and specific target of HIF-1, but not responsive to HIF-2. Surprisingly, HIG2 was not secreted, and HIG2 overexpression neither stimulated proliferation nor activated Wnt signaling. Instead, we show that HIG2 decorates the hemimembrane of lipid droplets, whose number and size increase on hypoxic inhibition of fatty acid β-oxidation, and colocalizes with the lipid droplet proteins adipophilin and TIP47. Normoxic overexpression of HIG2 was sufficient to increase neutral lipid deposition in HeLa cells and stimulated cytokine expression. HIG2 could be detected in atherosclerotic arteries and fatty liver disease, suggesting that this ubiquitously inducible HIF-1 target gene may play an important functional role in diseases associated with pathological lipid accumulation. © FASEB.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Gene expression; Lipid metabolism; Promoter; Renal clear-cell carcinoma

Hypoxia-inducible transcription factors stabilization in the thick ascending limb protects against ischemic acute kidney injury - Schley, Gunnar; Klanke, Bernd; Schödel, Johannes; Forstreuter, Frauke; Shukla, Deepa; Kurtz, Armin; Amann, Kerstin Ute; Wiesener, Michael; Rosen, Seymour; Eckardt, Kai-Uwe; Maxwell, Patrick H.; Willam, Carsten (Journal of the American Society of Nephrology, 2011)
Hypoxia-inducible transcription factors (HIF) protect cells against oxygen deprivation, and HIF stabilization before ischemia mitigates tissue injury. Because ischemic acute kidney injury (AKI) often involves the thick ascending limb (TAL), modulation of HIF in this segment may be protective. Here, we generated mice with targeted TAL deletion of the von Hippel-Lindau protein (Vhl), which mediates HIF degradation under normoxia, using Tamm-Horsfall protein (Thp)-driven Cre expression. These mice showed strong expression of HIF-1α in TALs but no changes in kidney morphology or function under control conditions. Deficiency of Vhl in the TAL markedly attenuated proximal tubular injury and preserved TAL function following ischemia-reperfusion, which may be partially a result of enhanced expression of glycolytic enzymes and lactate metabolism. These results highlight the importance of the thick ascending limb in the pathogenesis of AKI and suggest that pharmacologically targeting the HIF system may have potential to prevent and mitigate AKI. Copyright © 2011 by the American Society of Nephrology.
CRIS-Team Scopus Importer:2024-05-13

Hypoxia regulates the sperm associated antigen 4 (SPAG4) via HIF, which is expressed in renal clear cell carcinoma and promotes migration and invasion in vitro - Knaup, Karl; Monti, Juliana; Hackenbeck, Thomas; Jobst-Schwan, Tilman; Klanke, Bernd; Schietke, Ruth Elisabeth; Wacker, Ingrid; Behrens, Jürgen; Amann, Kerstin Ute; Eckardt, Kai-Uwe; Warnecke, Christina; Wiesener, Michael (Molecular Carcinogenesis, 2014)
Hypoxia leads to the upregulation of a variety of genes mediated largely via the hypoxia inducible transcription factor (HIF). Prominent HIF-regulated target genes such as the vascular endothelial growth factor (VEGF), the glucose transporter 1 (Glut-1), or erythropoietin (EPO) help to assure survival of cells and organisms in a low oxygenated environment. Here, we are the first to report the hypoxic regulation of the sperm associated antigen 4 (SPAG4). SPAG4 is a member of the cancer testis (CT) gene family and to date little is known about its physiological function or its involvement in tumor biology. A number of CT family candidate genes are therefore currently being investigated as potential cancer markers, due to their predominant testicular expression pattern. We analyzed RNA and protein expression by RNAse protection assay, immunoflurescent as well as immunohistological stainings. To evaluate the influence of SPAG4 on migration and invasion capabilities, siRNA knockdown as well as transient overexpression was performed prior to scratch or invasion assay analysis. The hypoxic regulation of SPAG4 is clearly mediated in a HIF-1 and VHL dependent manner. We furthermore show upregulation of SPAG4 expression in human renal clear cell carcinoma (RCC) and co-localization within the nucleolus in physiological human testis tissue. SPAG4 knockdown reduces the invasion capability of RCC cells in vitro and overexpression leads to enhancement of tumor cell migration. Together, SPAG4 could possibly play a role in the invasion capability and growth of renal tumors and could represent an interesting target for clinical intervention. © 2013 Wiley Periodicals, In
EVALuna2:3620

Identification of isoaspartate-modified transthyretin as potential target for selective immunotherapy of transthyretin amyloidosis - Köppen, Janett; Kleinschmidt, Martin; Morawski, Markus; Rahfeld, Jens Ulrich; Wermann, Michael; Cynis, Holger; Hegenbart, Ute; Daniel, Christoph; Roβner, Steffen; Schilling, Stephan; Schulze, Anja (Amyloid-Journal of Protein Folding Disorders, 2024)
Background: Numerous studies suggest a progressive accumulation of post-translationally modified peptides within amyloid fibrils, including isoaspartate (isoD) modifications. Here, we generated and characterised novel monoclonal antibodies targeting isoD-modified transthyretin (TTR). The antibodies were used to investigate the presence of isoD-modified TTR in deposits from transthyretin amyloidosis patients and to mediate antibody-dependent phagocytosis of TTR fibrils. Methods: Monoclonal antibodies were generated by immunisation of mice using an isoD-modified peptide and subsequent hybridoma generation. The antibodies were characterised in terms of affinity and specificity to isoD-modified TTR using surface plasmon resonance, transmission electron microscopy and immunohistochemical staining of human cardiac tissue. The potential to elicit antibody-dependent phagocytosis of TTR fibrils was assessed using THP-1 cells. Results: We developed two mouse monoclonal antibodies, 2F2 and 4D4, with high nanomolar affinity for isoD-modified TTR and strong selectivity over the unmodified epitope. Both antibodies show presence of isoD-modified TTR in human cardiac tissue, but not in freshly purified recombinant TTR, suggesting isoD modification only present in aged fibrillar deposits. Likewise, the antibodies only facilitated phagocytosis of TTR fibrils and not TTR monomers by THP-1 cells. Conclusions: These antibodies label aged, non-native TTR deposits, leaving native TTR unattended and thereby potentially enabling new therapeutic approaches.
CRIS-Team Scopus Importer:2024-06-07
Keywords: Fibrils; immunotherapy; isoaspartate; monoclonal antibody; transthyretin amyloidosis

Idiopathic granulomatous interstitial nephritis and isolated renal sarcoidosis: Two diagnoses of exclusion - Janssen, Ulf; Naderi, Shirin; Amann, Kerstin Ute (SAGE Open Medicine, 2021)
Granulomatous interstitial nephritis is a rare finding in renal biopsy caused by drugs, infections, and inflammatory or autoimmune diseases. Idiopathic cases account for 18% of granulomatous interstitial nephritis in native kidneys. Sarcoidosis and drugs are the most common causes of granulomatous interstitial nephritis in Western countries, while in India tuberculosis prevails. Few cases of renal sarcoidosis without extrarenal involvement, that is, isolated renal sarcoidosis, have been reported. The diagnostic criteria of isolated renal sarcoidosis remain, however, unclear. Extrarenal sarcoidosis and other etiologies of granulomatous interstitial nephritis, in particular drug-related, have to be excluded. Some of these patients may develop extrarenal manifestations during follow-up. Changes in calcium and vitamin D metabolism are frequently observed in renal sarcoidosis and support its diagnosis. While non-necrotizing granulomas are a feature of sarcoidosis and drug-induced granulomatous interstitial nephritis, they also prevail in tuberculosis-associated granulomatous interstitial nephritis. Granulomatous interstitial nephritis caused by sarcoidosis and drugs usually responds to steroid therapy. A poor response to steroids may indicate an infectious etiology such as tuberculosis and should lead to a review of the initial diagnosis. This article gives an overview of the various etiologies of granulomatous interstitial nephritis, their frequency and histopathological characteristics, as well as potential biomarkers associated with renal sarcoidosis.
CRIS-Team WoS Importer:2021-09-17

IFN-γ-response mediator GBP-1 represses human cell proliferation by inhibiting the Hippo signaling transcription factor TEAD - Unterer, Bea; Wiesmann, Veit; Gunasekaran, Mekala; Sticht, Heinrich; Tenkerian, Clara; Behrens, Jürgen; Leone, Marina; Engel, Felix; Britzen-Laurent, Nathalie; Naschberger, Elisabeth; Wittenberg, Thomas; Stürzl, Michael (Biochemical Journal, 2018)
Interferon-gamma (IFN-γ) is a pleiotropic cytokine that exerts important functions in inflammation, infectious diseases, and cancer. The large GTPase human guanylate-binding protein 1 (GBP-1) is among the most strongly IFN-γ-induced cellular proteins. Previously, it has been shown that GBP-1 mediates manifold cellular responses to IFN-γ including the inhibition of proliferation, spreading, migration, and invasion and through this exerts anti-tumorigenic activity. However, the mechanisms of GBP-1 anti-tumorigenic activities remain poorly understood. Here, we elucidated the molecular mechanism of the human GBP-1-mediated suppression of proliferation by demonstrating for the first time a cross-talk between the anti-tumorigenic IFN-γ and Hippo pathways. The α9-helix of GBP-1 was found to be sufficient to inhibit proliferation. Protein-binding and molecular modeling studies revealed that the α9-helix binds to the DNA-binding domain of the Hippo signaling transcription factor TEA domain protein (TEAD) mediated by the 376VDHLFQK382 sequence at the N-terminus of the GBP-1-α9-helix. Mutation of this sequence resulted in abrogation of both TEAD interaction and suppression of proliferation. Further on, the interaction caused inhibition of TEAD transcriptional activity associated with the down-regulation of TEAD-target genes. In agreement with these results, IFN-γ treatment of the cells also impaired TEAD activity, and this effect was abrogated by siRNA-mediated inhibition of GBP-1 expression. Altogether, this demonstrated that the α9-helix is the proliferation inhibitory domain of GBP-1, which acts independent of the GTPase activity through the inhibition of the Hippo transcription factor TEAD in mediating the anti-proliferative cell response to IFN-γ.
EVALuna2:34818

Imaging mass spectrometry analysis of renal amyloidosis biopsies reveals protein co-localization with amyloid deposits - Casadonte, Rita; Kriegsmann, Mark; Deininger, Soeren-Oliver; Amann, Kerstin Ute; Paape, Rainer; Belau, Eckhard; Suckau, Detlev; Fuchser, Jens; Beckmann, Janine; Becker, Michael; Kriegsmann, Joerg (Analytical and Bioanalytical Chemistry, 2015)
Amyloidosis is a heterogeneous group of protein misfolding diseases characterized by deposition of amyloid proteins. The kidney is frequently affected, especially by immunoglobulin light chain (AL) and serum amyloid A (SAA) amyloidosis as the most common subgroups. Current diagnosis relies on histopathological examination, Congo red staining, or electron microscopy. Subtyping is done by immunohistochemistry; however, commercially available antibodies lack specificity. The purpose of this study was to identify and map amyloid proteins in formalin-fixed paraffin-embedded tissue sections using matrix-assisted laser desorption/ionization imaging mass spectrometry (MALDI IMS) coupled with liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis in an integrated workflow. Renal amyloidosis and non-amyloidosis biopsies were processed for histological and MS analysis. Mass spectra corresponding to the congophilic areas were directly linked to the histological and MS images for correlation studies. Peptides for SAA and AL were detected by MALDI IMS associated to Congo red-positive areas. Sequence determination of amyloid peptides by LC-MS/MS analysis provided protein distribution and identification. Serum amyloid P component, apolipoprotein E, and vitronectin proteins were identified in both AA and AL amyloidosis, showing a strong correlation with Congo red-positive regions. Our findings highlight the utility of MALDI IMS as a new method to type amyloidosis in histopathological routine material and characterize amyloid-associated proteins that may provide insights into the pathogenetic process of amyloid formation.
EVALuna2:25521

Immune cell regulation by vitamin D-3 during allogeneic hematopoietic stem cell transplantation (HSCT) - Flamann, Cindy; Zeun, J.; Kremer, Andreas; Peter, K.; Kreutz, M.; Büttner-Herold, Maike; Kellner, C.; Saul, Domenica; Mougiakakos, Dimitrios; Mackensen, Andreas; Bruns, Heiko; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Immune Complex-Type Deposits in the Fischer-344 to Lewis Rat Model of Renal Transplantation and a Subset of Human Transplant Glomerulopathy - Grau, Veronika; Zeuschner, Philip; Immenschuh, Stephan; Bockmeyer, Clemens Luitpold; Zell, Stefanie; Wittig, Juliane; Saeuberlich, Karen; Abbas, Mahmoud; Padberg, Winfried; Meyer-Schwesinger, Catherine; Von Brandenstein, Melanie; Schlosser, Monika; et al. (Transplantation, 2016)
Antibody-mediated rejection is a leading cause for renal transplant loss. Rodent models are useful to dissect pathomechanisms and to develop treatment strategies. Although used for decades as a model, glomerular histopathological findings of Fischer-344 kidneys transplanted into Lewis rats have never been comprehensively described.Kidneys from Fischer-344 rats were transplanted into Lewis rats as life-sustaining allografts without immunosuppression. Lewis isografts and normal Fischer-344 kidneys served as controls. Grafts were harvested at 9 days, 6 and 26 weeks. Histopathological examination included light microscopy, immunohistochemistry, and morphometry. Findings were compared with 51 human biopsies with transplant glomerulopathy.Most glomerular findings in rat allografts resembled human acute and chronic antibody-mediated rejection with glomerulitis, microthrombosis, microaneurysms, glomerular hypertrophy, podocyte loss, glomerular basement membrane splitting, and secondary focal and segmental glomerulosclerosis. In line with previous reports on nonendothelial antigens, glomerular immunoglobulin and C4d deposition was mostly nonendothelial. Only in 26-week allografts, we found mesangial and subendothelial immune complex-type electron-dense deposits. Similar deposits were found in 8 of 51 human biopsies with transplant glomerulopathy after rigorous exclusion of immune complexes of other cause, particularly recurrent glomerulonephritis and hepatitis C.Thus, our model closely reflects the glomerular changes of acute antibody-mediated rejection in humans and of a special subset of human transplant glomerulopathy. The significance of alloimmune immune complex-type deposits in human transplants deserves further investigation.
EVALuna2:25520

Immune monitoring facilitates the clinical decision in multifocal COVID-19 of a pancreas-kidney transplant patient - Babel, Nina; Anft, Moritz; Blazquez-Navarro, Arturo; Doevelaar, Adrian A.N.; Seibert, Felix S.; Bauer, Frederic; Rohn, Benjamin J.; Hoelzer, Bodo; Thieme, Constantin J.; Roch, Toralf; Meister, Toni L.; Pfaender, Stephanie; et al. (American Journal of Transplantation, 2020)
The optimal management in transplant recipients with coronavirus disease 2019 (COVID-19) remains uncertain. The main concern is the ability of immunosuppressed patients to generate sufficient immunity for antiviral protection. Here, we report on immune monitoring facilitating a successful outcome of severe severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-associated pneumonia, meningoencephalitis, gastroenteritis, and acute kidney and pancreas graft failure in a pancreas-kidney transplant recipient. Despite the very low numbers of circulating B, NK, and T cells identified in follow-up, a strong SARS-CoV-2 reactive T cell response was observed. Importantly, we detected T cells reactive to Spike, Membrane, and Nucleocapsid proteins of SARS-CoV-2 with majority of T cells showing polyfunctional proinflammatory Th1 phenotype at all analyzed time points. Antibodies against Spike protein were also detected with increasing titers in follow-up. Neutralization tests confirmed their antiviral protection. A correlation between cellular and humoral immunity was observed underscoring the specificity of demonstrated data. We conclude that analyzing the kinetics of nonspecific and SARS-CoV-2-reactive cellular and humoral immunity can facilitate the clinical decision on immunosuppression adjustment and allow successful outcome as demonstrated in the current clinical case. Although the antiviral protection of the detected SARS-CoV-2-reactive T cells requires further evaluation, our data prove an ability mounting a strong SARS-CoV-2-reactive T cell response with functional capacity in immunosuppressed patients.
CRIS-Team Scopus Importer:2020-09-18

(Immuno‑)Pathology of drug side effects in the kidney - Pfister, F.; Büttner-Herold, Maike; Amann, Kerstin Ute (Pathologe, 2018)
Nephrotoxicity or renal side effects of drugs are frequent and may vary in their clinical presentation. Various types of acute and chronic kidney disease are known to develop as a consequence or side effect of a long list of drugs with nephrotoxicity most commonly being associated with injury in the tubulointerstitial compartment. In addition, drug-induced glomerular and vascular disease have also been reported, either as the result of direct cellular injury or immune-mediated injury to glomerular or endothelial cells. From a clinical point of view it is important to recognize such drug-induced nephropathies early in order to prevent or adequately treat them to favour kidney recovery and to avoid long-lasting negative consequences for kidney function.This article will focus on the typical morphology and pathogenesis of some frequent drug-induced renal diseases.
EVALuna2:204840

Immunosuppression with cyclosporine versus tacrolimus shows distinctive nephrotoxicity profiles within renal compartments - Demirci, Hasan; Popovic, Suncica; Dittmayer, Carsten; Yilmaz, Duygu Elif; El-Shimy, Ismail Amr; Mülleder, Michael; Hinze, Christian; Su, Mingzhen; Mertins, Philipp; Kirchner, Marieluise; Osmanodja, Bilgin; Paliege, Alexander; et al. (Acta Physiologica, 2024)
Aim: Calcineurin inhibitors (CNIs) are the backbone for immunosuppression after solid organ transplantation. Although successful in preventing kidney transplant rejection, their nephrotoxic side effects contribute to allograft injury. Renal parenchymal lesions occur for cyclosporine A (CsA) as well as for the currently favored tacrolimus (Tac). We aimed to study whether chronic CsA and Tac exposures, before reaching irreversible nephrotoxic damage, affect renal compartments differentially and whether related pathogenic mechanisms can be identified. Methods: CsA and Tac were administered chronically in wild type Wistar rats using osmotic minipumps over 4 weeks. Functional parameters were controlled. Electron microscopy, confocal, and 3D-structured illumination microscopy were used for histopathology. Clinical translatability was tested in human renal biopsies. Standard biochemical, RNA-seq, and proteomic technologies were applied to identify implicated molecular pathways. Results: Both drugs caused significant albeit differential damage in vasculature and nephron. The glomerular filtration barrier was more affected by Tac than by CsA, showing prominent deteriorations in endothelium and podocytes along with impaired VEGF/VEGFR2 signaling and podocyte-specific gene expression. By contrast, proximal tubule epithelia were more severely affected by CsA than by Tac, revealing lysosomal dysfunction, enhanced apoptosis, impaired proteostasis and oxidative stress. Lesion characteristics were confirmed in human renal biopsies. Conclusion: We conclude that pathogenetic alterations in the renal compartments are specific for either treatment. Considering translation to the clinical setting, CNI choice should reflect individual risk factors for renal vasculature and tubular epithelia. As a step in this direction, we share protein signatures identified from multiomics with potential pathognomonic relevance.
CRIS-Team Scopus Importer:2024-06-28
Keywords: calcineurin inhibitor nephropathy; multiomics; pore endothelium; proximal tubule; unfolded protein response; VEGF

Impact of Consensus Definitions on Identification of Glomerular Lesions by Light and Electron Microscopy - Haas, Mark; Mirocha, James; Amann, Kerstin Ute; Bajema, Ingeborg M.; Barisoni, Laura; Becker, Jan Ulrich; Jennette, J. Charles; Joh, Kenuske; Ljubanovic, Danica Galesic; Roberts, Ian S.D.; Roelofs, Joris J.; Sethi, Sanjeev; et al. (Kidney International Reports, 2021)
Introduction: In 2020, a working group of 13 renal pathologists published consensus definitions for 47 individual glomerular lesions found on light microscopy (LM) and 47 glomerular lesions and 9 normal structures found on electron microscopy (EM). Methods: To test the impact of these definitions on identification of these lesions and structures, 2 surveys were circulated to all members of the Renal Pathology Society (RPS), each having 32 images (19 LM, 13 EM) and accompanying questions with 5 multiple-choice answers, one being the consensus choice of the working group. The first survey (survey 1 [S1]), answered by 297 RPS members, was sent in September 2020, before publication of the consensus definitions. The second (survey 2 [S2]), with images of the same lesions and structures (but not the same images) and the same questions and multiple choices in different order, was sent in April 2020, 5 months after the publication of the definitions. Results: S2 was taken by 181 RPS members; 64% also took S1 and 61% reported having read the definitions paper (def. paper). Mean agreement with the consensus answers increased modestly between the 2 surveys (65.2% vs. 72.0%, P = 0.097); the increase was greater and significant when only respondents to S2 who read the def. paper were considered (65.2% vs. 74.8%, P = 0.026). Furthermore, in S2 agreement with consensus answers was greater among respondents who read this paper versus those who did not (66.9% vs. 74.8%, P < 0.0001). Conclusions: Publication of the consensus definitions modestly improved interobserver agreement in identification of glomerular lesions.
CRIS-Team Scopus Importer:2021-11-26
Keywords: electron microscopy; glomerulonephritis; glomerulus; kidney biopsy; renal pathology

IMPACT OF DONOR HYPERTENSION AND HISTOLOGIC CHANGES IN LIVING DONOR KIDNEY TRANSPLANTATION: A SINGLE CENTER RETROSPECTIVE STUDY - Dienemann, Thomas; Schellenberg, J.; Heller, K.; Daniel, Christoph; Amann, Kerstin Ute; Weidemann, A. (2018)
EVALuna2:204841

Impact of phosphorus restriction and vitamin D-substitution on secondary hyperparathyroidism in a proteinuric mouse model - Bohnert, Bernhard N.; Daniel, Christoph; Amann, Kerstin Ute; Voelkl, Jakob; Alesutan, Ioana; Lang, Florian; Heyne, Nils; Haering, Hans-Ulrich; Artunc, Ferruh (Kidney & Blood Pressure Research, 2015)
Since the discovery of FGF23, secondary hyperparathyroidism (SHPT) in renal disease has been considered to result primarily from phosphorus retention rather than vitamin D deficiency. However, the impact of phosphorus restriction and vitamin D supplementation on SHPT is still ill defined.We investigated the development of SHPT in a doxorubicin-induced proteinuric mouse model and tested different treatment strategies including a low phosphorus diet and substitution with native or active vitamin D in 129 S1/SvImJ wild-type mice.Development of SHPT at day 30 was strongly related to the magnitude of induced proteinuria. In mice with a proteinuria <100 mg/mg creatinine, SHPT was mild (PTH increase 2.4-fold), and serum levels of FGF23, phosphate and urea remained almost stable, whereas mice with heavy proteinuria (>100 mg/mg creatinine) developed marked SHPT (PTH increase 10.1-fold) accompanied by massive increase in FGF23 (27.0-fold increase), hyperphosphatemia (1.8-fold increase), renal failure (7.3-fold urea increase) and depletion of both 25-OH vitamin D and 1,25-OH vitamin D. Substitution with native or active vitamin D was unable to suppress SHPT, whereas a low-phosphorus diet (Pi content 0.013%) completely suppressed SHPT in mice with both mild and heavy proteinuria.The development of SHPT resulted from phosphate retention in this proteinuric model and could completely be suppressed with a low-phosphorus diet.
EVALuna2:25491

IMPACT OF SAMPLING SIDE OF PERITONEAL BIOPSIES ON PERITONEAL THICKNESS AND HISTOPATHOLOGICAL DIAGNOSIS - A QUANTITATIVE HISTOLOGICAL STUDY IN BODY DONORS - Eden, Gabriele; Pfister, Frederick; Kielstein, Heike; Amann, Kerstin Ute; Kielstein, Jan T. (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2019)
CRIS-Team WoS Importer:2019-11-26

Impaired Neovascularization and Reduced Capillary Supply in the Malignant vs. Non-malignant Course of Experimental Renovascular Hypertension - Jagusch, Lisa Gudrun; Cordasic, Nada; Amann, Kerstin Ute; Veelken, Roland; Jacobi, Johannes; Hilgers, Karl Friedrich; Hartner, Andrea (Frontiers in Physiology, 2016)
Malignant hypertension develops in some cases of hypertension but not in others. We hypothesized that an impaired neovascularization and a reduced capillary supply characterizes the malignant course of experimental hypertension. Two-kidney, one-clip renovascular hypertension was induced in rats; controls (sham) were sham operated. To distinguish malignant hypertension from non-malignant hypertension, we considered two factors: weight loss, and the number of typical vascular lesions (onion skin lesions and fibrinoid necroses) per kidney section of the nonclipped kidney. Animals in the upper half for both criteria were defined as malignant hypertensives. After 5 weeks, mean arterial blood pressure was elevated to the same degree in malignant hypertension and non-malignant hypertension whereas plasma renin and aldosterone were significantly higher in malignant hypertensives. The expression of plasminogen activator inhibitor-1 was elevated (up to 14-fold) in non-malignant but significantly more increased (up to 36-fold) in malignant hypertensive rats, compared to sham. As a bioassay for neovascularization, the area of granulation tissue ingrowth in polyvinyl discs (implanted subcutaneously) was reduced in malignant hypertension compared to non-malignant hypertension and sham, while there was no difference between non-malignant hypertension and sham. The number of renal and left ventricular capillaries was significantly lower in malignant hypertension compared to non-malignant hypertension, as was the number of proliferating endothelial cells. We conclude that an impaired neovascularization and capillarization occurs in malignant renovascular hypertension but not in the non-malignant course of the disease despite comparable blood pressure levels. This might contribute to the unique vascular lesions and progressive target organ damage observed in malignant hypertension.
EVALuna2:3914

Importance of the PD-1/PD-L1 Axis for Malignant Transformation and Risk Assessment of Oral Leukoplakia - Ries, Jutta; Agaimy, Abbas; Wehrhan, Falk; Baran, Christoph; Bolze, Stella; Danzer, Eva; Frey, Silke; Jantsch, Jonathan; Möst, Tobias; Büttner-Herold, Maike; Wickenhauser, Claudia; Kesting, Marco Rainer; et al. (Biomedicines, 2021)
Background: The programmed cell death ligand 1/programmed cell death receptor 1 (PD-L1/PD-1) Immune Checkpoint is an important modulator of the immune response. Overexpression of the receptor and its ligands is involved in immunosuppression and the failure of an immune response against tumor cells. PD-1/PD-L1 overexpression in oral squamous cell carcinoma (OSCC) compared to healthy oral mucosa (NOM) has already been demonstrated. However, little is known about its expression in oral precancerous lesions like oral leukoplakia (OLP). The aim of the study was to investigate whether an increased expression of PD-1/PD-L1 already exists in OLP and whether it is associated with malignant transformation. Material and Methods: PD-1 and PD-L1 expression was immunohistologically analyzed separately in the epithelium (E) and the subepithelium (S) of OLP that had undergone malignant transformation within 5 years (T-OLP), in OLP without malignant transformation (N-OLP), in corresponding OSCC and in NOM. Additionally, RT-qPCR analysis for PD-L1 expression was done in the entire tissues. Additionally, the association between overexpression and malignant transformation, dysplasia and inflammation were examined. Results: Compared to N-OLP, there were increased levels of PD-1 protein in the epithelial and subepithelial layers of T-OLP (PE = 0.001; PS = 0.005). There was no significant difference in PD-L1 mRNA expression between T-OLP and N-OLP (p = 0.128), but the fold-change increase between these groups was significant (Relative Quantification (RQ) = 3.1). In contrast to N-OLP, the PD-L1 protein levels were significantly increased in the epithelial layers of T-OLP (p = 0.007), but not in its subepithelial layers (p = 0.25). Importantly, increased PD-L1 levels were significantly associated to malignant transformation within 5 years. Conclusion: Increased levels of PD-1 and PD-L1 are related to malignant transformation in OLP and may represent a promising prognostic indicator to determine the risk of malignant progression of OLP. Increased PD-L1 levels might establish an immunosuppressive microenvironment, which could favor immune escape and thereby contribute to malignant transformation. Hence, checkpoint inhibitors could counteract tumor development in OLP and may serve as efficient therapeutic strategy in patients with high-risk precancerous lesions.
CRIS-Team WoS Importer:2021-03-19

Improved Bladder Tumor RNA Isolation from Archived Tissues Using Methylene Blue for Normalization, Multiplex RNA Hybridization, Sequencing and Subtyping - Köhler, Stefanie; Brandl, Lisa; Strissel, Pamela; Glossner, Laura; Ekici, Arif Bülent; Angeloni, Miriam; Ferrazzi, Fulvia; Bahlinger, Veronika; Hartmann, Arndt; Beckmann, Matthias; Eckstein, Markus; Strick, Reiner (International Journal of Molecular Sciences, 2022)
Methylene blue (MB) is a dye used for histology with clinical importance and intercalates into nucleic acids. After MB staining of formalin fixed paraffin embedded (FFPE) muscle invasive bladder cancer (MIBC) and normal urothelium, specific regions could be microdissected. It is not known if MB influences RNA used for gene expression studies. Therefore, we analyzed MIBC using five different RNA isolation methods comparing patient matched FFPE and fresh frozen (FF) tissues pre-stained with or without MB. We demonstrate a positive impact of MB on RNA integrity with FF tissues using real time PCR with no interference of its chemical properties. FFPE tissues showed no improvement of RNA integrity, which we propose is due to formalin induced nucleotide crosslinks. Using direct multiplex RNA hybridization the best genes for normalization of MIBC and control tissues were identified from 34 reference genes. In addition, 5SrRNA and 5.8SrRNA were distinctive reference genes detecting <200 bp fragments important for mRNA analyses. Using these normalized RNAs from MB stained MIBC and applying multiplex RNA hybridization and mRNA sequencing, a minimal gene expression panel precisely identified luminal and basal MIBC tumor subtypes, important for diagnosis, prognosis and chemotherapy response.
CRIS-Team WoS Importer:2022-09-30

Improvement of the Layer Adhesion of Composite Cardiac Patches - Ruther, Florian; Zimmermann, Andrea; Engel, Felix; Boccaccini, Aldo R. (Advanced Engineering Materials, 2019)
The major purpose of cardiac patches is to deliver healthy cells to infarcted tissues. Such cardiac patches must fulfill specific mechanical as well as chemical requirements. Herein, bi-component cardiac patches are investigated with regard to their layer adhesion. Combinations of salt-leached porous poly (glycerol sebacate) (PGS) films with a layer of electrospun-gelatin fibers are produced. Gelatin fibers are fabricated by solution electrospinning using 20 wt% gelatin in 98 v% formic acid. Fibers are attached to PGS films either via direct electrospinning on top of the film or via combining as spun fiber mats with PGS using gelatin as glue. Scanning electron microscopy (SEM) images show that fiber mats adapt to the rough surface of the porous PGS film. In contrast, fibers spun directly onto films show poor adhesion and only a few fibers are attached to the PGS substrate. Fourier transform infrared (FTIR) analysis, contact-angle measurements, and pull-off adhesion tests of the bi-component patches confirm these results. Modified pull-off adhesion tests of the two layers show that combining as spun gelatin fiber mats with porous PGS substrates by gluing leads to excellent material adhesion before and after incubation for up to 14 days.
CRIS-Team Scopus Importer:2019-11-19
Keywords: bi-layer adhesions; cardiac patches; electrospinning; gelatin; porous poly (glycerol sebacate)

Improving translational research in sex-specific effects of comorbidities and risk factors in ischaemic heart disease and cardioprotection: position paper and recommendations of the ESC Working Group on Cellular Biology of the Heart - Perrino, Cinzia; Ferdinandy, Péter; Bøtker, Hans E.; Brundel, Bianca J.J.M.; Collins, Peter; Davidson, Sean M.; den Ruijter, Hester M.; Engel, Felix; Gerdts, Eva; Girao, Henrique; Gyöngyösi, Mariann; Hausenloy, Derek J.; et al. (Cardiovascular Research, 2021)
Ischaemic heart disease (IHD) is a complex disorder and a leading cause of death and morbidity in both men and women. Sex, however, affects several aspects of IHD, including pathophysiology, incidence, clinical presentation, diagnosis as well as treatment and outcome. Several diseases or risk factors frequently associated with IHD can modify cellular signalling cascades, thus affecting ischaemia/reperfusion injury as well as responses to cardioprotective interventions. Importantly, the prevalence and impact of risk factors and several comorbidities differ between males and females, and their effects on IHD development and prognosis might differ according to sex. The cellular and molecular mechanisms underlying these differences are still poorly understood, and their identification might have important translational implications in the prediction or prevention of risk of IHD in men and women. Despite this, most experimental studies on IHD are still undertaken in animal models in the absence of risk factors and comorbidities, and assessment of potential sex-specific differences are largely missing. This ESC WG Position Paper will discuss: (i) the importance of sex as a biological variable in cardiovascular research, (ii) major biological mechanisms underlying sex-related differences relevant to IHD risk factors and comorbidities, (iii) prospects and pitfalls of preclinical models to investigate these associations, and finally (iv) will provide recommendations to guide future research. Although gender differences also affect IHD risk in the clinical setting, they will not be discussed in detail here.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Cardioprotection Sex differences Ischaemic heart disease Ischaemia and reperfusion Translational research Comorbidities

Incorporation of montmorillonite into microfluidics-generated chitosan microfibers enhances neuron-like PC12 cells for application in neural tissue engineering - Katoli, Zahra; Navaei-Nigjeh, Mona; Mirzababaei, Soheyl; Sabahi, Hossein; Baeeri, Maryam; Akrami, Mohammad; Roshanbinfar, Kaveh; Engel, Felix; Abdollahi, Mohammad (Carbohydrate Polymers, 2024)
The complexity in structure and function of the nervous system, as well as its slow rate of regeneration, makes it more difficult to treat it compared to other tissues. Neural tissue engineering aims to create an appropriate environment for nerve cell proliferation and differentiation. Fibrous scaffolds with suitable morphology and topography and better mimicry of the extracellular matrix have been promising for the alignment and migration of neural cells. On this premise, to improve the properties of the scaffold, we combined montmorillonite (MMT) with chitosan (CS) polymer and created microfibers with variable diameters and varied concentrations of MMT using microfluidic technology and tested its suitability for the rat pheochromocytoma cell line (PC12). According to the findings, CS/MMT 0.1 % compared to CS/MMT 0 % microfibers showed a 201 MPa increase in Young's modulus, a 68 mS/m increase in conductivity, and a 1.4-fold increase in output voltage. Analysis of cell mitochondrial activity verified the non-toxicity, resulting in good cell morphology with orientation along the microfiber. Overall, the results of this project showed that with a low concentration of MMT, the properties of microfibers can be significantly improved and a suitable scaffold can be designed for neural tissue engineering.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Chitosan; Microfiber; Microfluidic technology; Montmorillonite; Neural tissue engineering

Increased CD47 expression inhibits phagocytosis of alloreactive donor T cells after allo-HSCT - Flamann, Cindy; Matos, C.; Kreutz, M.; Shaikh, H.; Beilhack, A.; Büttner-Herold, Maike; Lischer, Christopher; Völkl, Simon; Kellner, C.; Zeun, J.; Kremer, Andreas; Bitterer, Katrin; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Increased Levels of sCD30 Have No Impact on the Incidence of Early ABMR and Long-Term Outcome in Intermediate-Risk Renal Transplant Patients With Preformed DSA - Drasch, Thomas; Bach, Christian; Luber, Markus; Spriewald, Bernd; Utpatel, Kirsten; Büttner-Herold, Maike; Banas, Bernhard; Zecher, Daniel (Frontiers in Medicine, 2021)
Background: It is still incompletely understood why some patients with preformed donor-specific anti-HLA antibodies (DSA) have reduced kidney allograft survival secondary to antibody-mediated rejection (ABMR), whereas many DSA-positive patients have favorable long-term outcomes. Elevated levels of soluble CD30 (sCD30) have emerged as a promising biomarker indicating deleterious T-cell help in conjunction with DSA in immunologically high-risk patients. We hypothesized that this would also be true in intermediate-risk patients. Methods: We retrospectively analyzed pre-transplant sera from 287 CDC-crossmatch negative patients treated with basiliximab induction and tacrolimus-based maintenance therapy for the presence of DSA and sCD30. The incidence of ABMR according to the Banff 2019 classification and death-censored allograft survival were determined. Results: During a median follow-up of 7.4 years, allograft survival was significantly lower in DSA-positive as compared to DSA-negative patients (p < 0.001). In DSA-positive patients, most pronounced in those with strong DSA (MFI > 5,000), increased levels of sCD30 were associated with accelerated graft loss compared to patients with low sCD30 (3-year allograft survival 75 vs. 95%). Long-term survival, however, was comparable in DSA-positive patients irrespective of sCD30 status. Likewise, the incidence of early ABMR and lesion score characteristics were comparable between sCD30-positive and sCD30-negative patients with DSA. Finally, increased sCD30 levels were not predictive for early persistence of DSA. Conclusion: Preformed DSA are associated with an increased risk for ABMR and long-term graft loss independent of sCD30 levels in intermediate-risk kidney transplant patients.
CRIS-Team Scopus Importer:2021-12-03
Keywords: ABMR; antibody-mediated rejection; donor-specific anti HLA antibodies; kidney transplantation; risk stratification; sCD30

Increased malignancy of oral squamous cell carcinomas (oscc) is associated with macrophage polarization in regional lymph nodes - an immunohistochemical study - Wehrhan, Falk; Buettner-Herold, Maike; Hyckel, Peter; Moebius, Patrick; Preidl, Raimund; Distel, Luitpold; Ries, Jutta; Amann, Kerstin Ute; Schmitt, Christian; Neukam, Friedrich Wilhelm; Weber, Manuel (BMC Cancer, 2014)
It is largely accepted that specific immunological parameters in solid malignancies are associated with patient's prognosis. Recently a correlation of macrophage polarization with histomorphological parameters could also be shown in oral squamous cell carcinoma (oscc). The observed tumor derived peripheral immune tolerance could be associated with the macrophage polarization in regional tumor draining lymph nodes.So far there are no studies analyzing the macrophage polarization in cervical lymph nodes of oscc patients. In the present study we aimed to correlate macrophage polarization in different anatomical lymph node compartments of patients diagnosed with oscc with histopathologic parameters of the primary tumor (T-, N-, L-, V-, Pn-status, grading).Tumor free (n = 37) and metastatic (n = 17) lymph nodes of T1 and T2 oscc patients were processed for immunohistochemistry to detect CD68, CD11c, CD163 and MRC1 positive cells. Samples were digitized using whole slide imaging and the number of cells expressing the aforementioned markers in the region of interest quantitatively analyzed.The malignancy of the primary tumor (defined by T-, L-, Pn-status, grading) correlated with the lymph node macrophage polarization. L1 and Pn1 tumor cases displayed a significantly (p < 0.05) decreased M1 and increased M2 polarization in the sinus of the lymph nodes. G3 cases presented a significantly (p < 0.05) increased M2 polarization in the sinus compared to G2 cases. T2 tumors had significantly (p < 0.05) increased M2 polarization in the interfollicular zone of regional lymph nodes compared to T1 tumors. Metastatic and non-metastatic lymph nodes did not differ regarding their macrophage polarization.The current study revealed for the first time an influence of oscc on the macrophage polarization in regional lymph nodes. Markers of malignant behavior in the primary tumor were associated with a shift of macrophage polarization in lymph nodes from the anti-tumoral M1 type to the tumor-promoting M2 type. As tumor free and metastatic lymph nodes did not differ in terms of their macrophage polarization pattern, there must be other factors influencing the location for lymph node metastasis formation.
EVALuna2:18175

Increase in non-professional phagocytosis during the progression of cell cycle - Hofmann, Alexander; Putz, Florian; Büttner-Herold, Maike; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (PLoS ONE, 2021)
Homotypic or heterotypic internalization of another, either living or necrotic cell is currently in the center of research interest. The active invasion of a living cell called entosis and cannibalism of cells by rapidly proliferating cancers are prominent examples. Additionally, normal healthy tissue cells are capable of non-professional phagocytosis. This project studied the relationship between non-professional phagocytosis, individual proliferation and cell cycle progression. Three mesenchymal and two epithelial normal tissue cell lines were studied for homotypic non-professional phagocytosis. Homotypic dead cells were co-incubated with adherent growing living cell layers. Living cells were synchronized by mitotic shake-off as well as Aphidicolin-treatment and phagocytotic activity was analyzed by immunostaining. Cell cycle phases were evaluated by flow cytometry. Mesenchymal and epithelial normal tissue cells were capable of internalizing dead cells. Epithelial cells had much higher non-professional phagocytotic rates than mesenchymal cells. Cells throughout the entire cell cycle were able to phagocytose. The phagocytotic rate significantly increased with progressing cell cycle phases. Mitotic cells regularly phagocytosed dead cells, this was verified by Nocodazole and Colcemid treatment. Taken together, our findings indicate the ability of human tissue cells to phagocytose necrotic neighboring cells in confluent cell layers. The origin of the cell line influences the rate of cell-in-cell structure formation. The higher cell-in-cell structure rates during cell cycle progression might be influenced by cytoskeletal reorganization during this period or indicate an evolutionary anchorage of the process. Recycling of nutrients during cell growth might also be an explanation. ?2021 Hofmann et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.
CRIS-Team Scopus Importer:2021-02-19

In Deutschland erworbene West-Nil-Virusinfektion bei einem nierentransplantierten Patienten - Karrasch, Matthias; Pein, Ulrich; Fritz, Annekathrin; Lange, Danica; Moritz, Stefan; Amann, Kerstin Ute; Schmidt-Chanasit, Jonas; Cadar, Daniel; Tappe, Dennis; Gabriel, Martin (Deutsche Medizinische Wochenschrift, 2021)
Background West-Nile-Virus (WNV) is a widely distributed flavivirus that is mainly transmitted between birds through different mosquito species (e.g. Culex, Aedes), but may also be transmitted to mammals including humans. WNV causes a spectrum of disease, ranging from asymptomatic infection to encephalitis in a minority of cases. Risk factors for severe disease are older age, cardiovascular disease and an immunocompromised state. Medical History and Clinical Examination Here we report about a 60-year-old male patient who was referred to the University Hospital of Halle (Saale) with severe fever two years after kidney transplantation due to hypertensive nephropathy. No infection focus could be found and by day 6 in the course of his illness the patient developed neurologic symptoms and viral encephalitis was suspected. Treatment and course The patient was initially treated with aciclovir. After initial reduction of immunosuppression, coincident graft dysfunction was treated with methylprednisolon. WNV-infection was suspected due to recent emerging human cases in the nearby area of the city of Leipzig. WNV lineage 2 was detected in the patient's urine by RT-PCR and seroconversion with presence of anti WNV IgM and IgG could be demonstrated. Consecutively, aciclovir treatment was stopped. The patient fully recovered and the transplanted kidney regained adequate function. Kidney biopsy did not reveal gross rejection of the transplant. Conclusion This case highlights the need to consider rarer causes of illness like WNV-infection particularly in risk groups for more severe outcomes of infectious disease. WNV may be detected by PCR in the blood and cerebrospinal fluid early in the course of infection but it is also excreted for a prolonged period of time in the urine. Seroconversion to anti WNV IgG and IgM may be shown but serologic cross-reactivity among members of the flaviviridae family must be considered.
CRIS-Team Scopus Importer:2021-04-16
Keywords: encephalitis; kidney; menigoencephalitis; transplantation; west nile virus

Influence of AAV vector tropism on long-term expression and Fc-γ receptor binding of an antibody targeting SARS-CoV-2 - Wagner, Jannik; Müller-Schmucker, Sandra; Wang, Wenjun; Arnold, Philipp; Uhlig, Nadja; Issmail, Leila; Eberlein, Valentina; Damm, Dominik; Roshanbinfar, Kaveh; Enßer, Armin; Oltmanns, Friederike; Peter, Antonia Sophia; et al. (Communications Biology, 2024)
Long-acting passive immunization strategies are needed to protect immunosuppressed vulnerable groups from infectious diseases. To further explore this concept for COVID-19, we constructed Adeno-associated viral (AAV) vectors encoding the human variable regions of the SARS-CoV-2 neutralizing antibody, TRES6, fused to murine constant regions. An optimized vector construct was packaged in hepatotropic (AAV8) or myotropic (AAVMYO) AAV capsids and injected intravenously into syngeneic TRIANNI-mice. The highest TRES6 serum concentrations (511 µg/ml) were detected 24 weeks after injection of the myotropic vector particles and mean TRES6 serum concentrations remained above 100 µg/ml for at least one year. Anti-drug antibodies or TRES6-specific T cells were not detectable. After injection of the AAV8 particles, vector mRNA was detected in the liver, while the AAVMYO particles led to high vector mRNA levels in the heart and skeletal muscle. The analysis of the Fc-glycosylation pattern of the TRES6 serum antibodies revealed critical differences between the capsids that coincided with different binding activities to murine Fc-γ-receptors. Concomitantly, the vector-based immune prophylaxis led to protection against SARS-CoV-2 infection in K18-hACE2 mice. High and long-lasting expression levels, absence of anti-drug antibodies and favourable Fc-γ-receptor binding activities warrant further exploration of myotropic AAV vector-based delivery of antibodies and other biologicals.
CRIS-Team Scopus Importer:2024-07-26

Inhibition of the renal apical sodium dependent bile acid transporter prevents cholemic nephropathy in mice with obstructive cholestasis - Ghallab, Ahmed; González, Daniela; Strängberg, Ellen; Hofmann, Ute; Myllys, Maiju; Hassan, Reham; Hobloss, Zaynab; Brackhagen, Lisa; Begher-Tibbe, Brigitte; Duda, Julia C.; Drenda, Carolin; Kappenberg, Franziska; et al. (Journal of Hepatology, 2024)
Background & Aims: Cholemic nephropathy (CN) is a severe complication of cholestatic liver diseases for which there is no specific treatment. We revisited its pathophysiology with the aim of identifying novel therapeutic strategies. Methods: Cholestasis was induced by bile duct ligation (BDL) in mice. Bile flux in kidneys and livers was visualized by intravital imaging, supported by MALDI mass spectrometry imaging and liquid chromatography-tandem mass spectrometry. The effect of AS0369, a systemically bioavailable apical sodium-dependent bile acid transporter (ASBT) inhibitor, was evaluated by intravital imaging, RNA-sequencing, histological, blood, and urine analyses. Translational relevance was assessed in kidney biopsies from patients with CN, mice with a humanized bile acid (BA) spectrum, and via analysis of serum BAs and KIM-1 (kidney injury molecule 1) in patients with liver disease and hyperbilirubinemia. Results: Proximal tubular epithelial cells (TECs) reabsorbed and enriched BAs, leading to oxidative stress and death of proximal TECs, casts in distal tubules and collecting ducts, peritubular capillary leakiness, and glomerular cysts. Renal ASBT inhibition by AS0369 blocked BA uptake into TECs and prevented kidney injury up to 6 weeks after BDL. Similar results were obtained in mice with humanized BA composition. In patients with advanced liver disease, serum BAs were the main determinant of KIM-1 levels. ASBT expression in TECs was preserved in biopsies from patients with CN, further highlighting the translational potential of targeting ASBT to treat CN. Conclusions: BA enrichment in proximal TECs followed by oxidative stress and cell death is a key early event in CN. Inhibiting renal ASBT and consequently BA enrichment in TECs prevents CN and systemically decreases BA concentrations. Impact and implications: Cholemic nephropathy (CN) is a severe complication of cholestasis and an unmet clinical need. We demonstrate that CN is triggered by the renal accumulation of bile acids (BAs) that are considerably increased in the systemic blood. Specifically, the proximal tubular epithelial cells of the kidney take up BAs via the apical sodium-dependent bile acid transporter (ASBT). We developed a therapeutic compound that blocks ASBT in the kidneys, prevents BA overload in tubular epithelial cells, and almost completely abolished all disease hallmarks in a CN mouse model. Renal ASBT inhibition represents a potential therapeutic strategy for patients with CN.
CRIS-Team Scopus Importer:2024-02-02
Keywords: bile cast nephropathy; bile duct ligation; Cholestasis; intravital imaging; kidney injury

In-situ analysis of mast cells and dendritic cells in coronary atherosclerosis in chronic kidney disease (CKD) - Wachter, David; Neureiter, D.; Campean, Valentina; Hilgers, Karl Friedrich; Buettner-Herold, M.; Daniel, Christoph; Benz, Kerstin; Amann, Kerstin Ute (Histology and Histopathology, 2018)
AIMS: Mast cells (MC) and dendritic cells (DC) have immune modulatory function and can influence T-cell activity. Both cell types have been found in atherosclerotic plaques and are thought to play an important role for plaque stability. Compared to matched segments of the non-renal population, patients with chronic kidney disease (CKD) show a more pronounced and more aggressive course of atherosclerosis with higher plaque calcification and significantly higher complications rates. It was the aim of this study to analyze the number and localization of MCs and DCs, macrophages, T- and B-cells as well as the expression of markers of inflammation such as CRP and NFκB in calcified and non-calcified atherosclerotic plaques of patients with CKD and control patients. METHODS: Fifty coronary atherosclerotic plaques from patients with endstage CKD (CKD, n=25) and control (n=25) patients were categorized according to the Stary classification and investigated using immunohistochemistry (markers for MC, DC, T, B, macrophage and NFκB). Expression was analyzed separately for the complete plaque area as well as for the different plaque subregions and correlations were analyzed. RESULTS: We found only very few DCs and MCs per lesion area with slightly increased numbers in calcified plaques. MCs per plaque area were significantly more frequent in CKD than in control patients and this was independent of plaque calcification. MCs were most frequently found in the shoulder and basis of the plaque. DCs per plaque area were significantly less in calcified plaques of CKD compared to control patients. In control, but not in CKD patients, DCs were significantly more frequent in calcified than in non-calcified plaques. Within the plaques DCs were similarly distributed between all 4 subregions. CONCLUSIONS: Coronary atherosclerotic plaques of CKD patients showed a significantly higher number of MCs whereas DCs were less frequent compared to control patients particularly if plaques were calcified. These findings might indicate a potential proinflammatory role of MCs, but not of DCs in atherosclerotic lesions of CKD patients, adding another characteristic of advanced atherosclerosis in these patients.
EVALuna2:34422

INTERLEUKIN-21-A NEW PLAYER IN ALLOGRAFT REJECTION? - Steines, L.; Friedmann, J.; Schuster, A.; Poth, H.; Amann, Kerstin Ute; Banas, B.; Bergler, T. (TRANSPLANT INTERNATIONAL, 2020)
CRIS-Team WoS Importer:2020-11-06

International Union of Basic and Clinical Pharmacology. XCIV. Adhesion G protein-coupled receptors - Hamann, Joerg; Aust, Gabriela; Arac, Demet; Engel, Felix; Formstone, Caroline; Fredriksson, Robert; Hall, Randy A.; Harty, Breanne L.; Kirchhoff, Christiane; Knapp, Barbara; Krishnan, Arunkumar; Liebscher, Ines; et al. (Pharmacological Reviews, 2015)
The Adhesion family forms a large branch of the pharmacologically important superfamily of G protein-coupled receptors (GPCRs). As Adhesion GPCRs increasingly receive attention from a wide spectrum of biomedical fields, the Adhesion GPCR Consortium, together with the International Union of Basic and Clinical Pharmacology Committee on Receptor Nomenclature and Drug Classification, proposes a unified nomenclature for Adhesion GPCRs. The new names have ADGR as common dominator followed by a letter and a number to denote each subfamily and subtype, respectively. The new names, with old and alternative names within parentheses, are: ADGRA1 (GPR123), ADGRA2 (GPR124), ADGRA3 (GPR125), ADGRB1 (BAI1), ADGRB2 (BAI2), ADGRB3 (BAI3), ADGRC1 (CELSR1), ADGRC2 (CELSR2), ADGRC3 (CELSR3), ADGRD1 (GPR133), ADGRD2 (GPR144), ADGRE1 (EMR1, F4/80), ADGRE2 (EMR2), ADGRE3 (EMR3), ADGRE4 (EMR4), ADGRE5 (CD97), ADGRF1 (GPR110), ADGRF2 (GPR111), ADGRF3 (GPR113), ADGRF4 (GPR115), ADGRF5 (GPR116, Ig-Hepta), ADGRG1 (GPR56), ADGRG2 (GPR64, HE6), ADGRG3 (GPR97), ADGRG4 (GPR112), ADGRG5 (GPR114), ADGRG6 (GPR126), ADGRG7 (GPR128), ADGRL1 (latrophilin-1, CIRL-1, CL1), ADGRL2 (latrophilin-2, CIRL-2, CL2), ADGRL3 (latrophilin-3, CIRL-3, CL3), ADGRL4 (ELTD1, ETL), and ADGRV1 (VLGR1, GPR98). This review covers all major biologic aspects of Adhesion GPCRs, including evolutionary origins, interaction partners, signaling, expression, physiologic functions, and therapeutic potential.
EVALuna2:25498

Intestinal graft-versus-host disease is driven by BATF-dependent IL-7R(hi)GM-CSF+ T cells - Ullrich, Evelyn; Abendroth, Benjamin; Rothamer, Johanna; Huber, Carina; Buettner-Herold, Maike; Kitowski, Vera; Vogler, Tina; Longerich, Thomas; Zundler, Sebastian; Völkl, Simon; Beilhack, Andreas; Rose-John, Stefan; et al. (2018)
EVALuna2:207769

Intracranial hemorrhage in COVID-19 patients during extracorporeal membrane oxygenation for acute respiratory failure: a nationwide register study report - von Stillfried, Saskia; Bülow, Roman David; Röhrig, Rainer; Meybohm, Patrick; Boor, Peter; Böcker, Jana; Schmidt, Jens; Tholen, Pauline; Majeed, Raphael; Wienströer, Jan; Weis, Joachim; Bremer, Juliane; et al. (Critical Care, 2022)
Background: In severe cases, SARS-CoV-2 infection leads to acute respiratory distress syndrome (ARDS), often treated by extracorporeal membrane oxygenation (ECMO). During ECMO therapy, anticoagulation is crucial to prevent device-associated thrombosis and device failure, however, it is associated with bleeding complications. In COVID-19, additional pathologies, such as endotheliitis, may further increase the risk of bleeding complications. To assess the frequency of bleeding events, we analyzed data from the German COVID-19 autopsy registry (DeRegCOVID). Methods: The electronic registry uses a web-based electronic case report form. In November 2021, the registry included N = 1129 confirmed COVID-19 autopsy cases, with data on 63 ECMO autopsy cases and 1066 non-ECMO autopsy cases, contributed from 29 German sites. Findings: The registry data showed that ECMO was used in younger male patients and bleeding events occurred much more frequently in ECMO cases compared to non-ECMO cases (56% and 9%, respectively). Similarly, intracranial bleeding (ICB) was documented in 21% of ECMO cases and 3% of non-ECMO cases and was classified as the immediate or underlying cause of death in 78% of ECMO cases and 37% of non-ECMO cases. In ECMO cases, the three most common immediate causes of death were multi-organ failure, ARDS and ICB, and in non-ECMO cases ARDS, multi-organ failure and pulmonary bacterial ± fungal superinfection, ordered by descending frequency. Interpretation: Our study suggests the potential value of autopsies and a joint interdisciplinary multicenter (national) approach in addressing fatal complications in COVID-19.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Autopsy; Bleeding events; COVID-19; ECMO; Intracranial bleeding; Registry

Intralesional TLR4 agonist treatment strengthens the organ defense against colonizing cancer cells in the brain - Blazquez, Raquel; Chuang, Han-Ning; Wenske, Britta; Trigueros, Laura; Wlochowitz, Darius; Liguori, Renato; Ferrazzi, Fulvia; Regen, Tommy; Proescholdt, Martin A.; Rohde, Veit; Riemenschneider, Markus J.; Stadelmann, Christine; et al. (Oncogene, 2022)
Brain metastasis in breast cancer remains difficult to treat and its incidence is increasing. Therefore, the development of new therapies is of utmost clinical relevance. Recently, toll-like receptor (TLR) 4 was correlated with IL6 expression and poor prognosis in 1 215 breast cancer primaries. In contrast, we demonstrated that TLR4 stimulation reduces microglia-assisted breast cancer cell invasion. However, the expression, prognostic value, or therapeutic potential of TLR signaling in breast cancer brain metastasis have not been investigated. We thus tested the prognostic value of various TLRs in two brain-metastasis gene sets. Furthermore, we investigated different TLR agonists, as well as MyD88 and TRIF-deficient microenvironments in organotypic brain-slice ex vivo co-cultures and in vivo colonization experiments. These experiments underline the ambiguous roles of TLR4, its adapter MyD88, and the target nitric oxide (NO) during brain colonization. Moreover, analysis of the gene expression datasets of breast cancer brain metastasis patients revealed associations of TLR1 and IL6 with poor overall survival. Finally, our finding that a single LPS application at the onset of colonization shapes the later microglia/macrophage reaction at the macro-metastasis brain-parenchyma interface (MMPI) and reduces metastatic infiltration into the brain parenchyma may prove useful in immunotherapeutic considerations.
CRIS-Team Scopus Importer:2022-10-21

INTRARENAL HIGH SALT ADMINISTRATION CAUSES TONIC INHIBITION OF RENAL SYMPATHETIC NERVE ACTIVITY (RSNA) - Hindermann, Martin; Rodionova, Kristina; Dietz, Amelie; Ditting, Tilmann; Ott, Christian; Schmieder, Roland; Amann, Kerstin Ute; Veelken, Roland (2018)
EVALuna2:204842

Intravital imaging reveals glomerular capillary distension and endothelial and immune cell activation early in Alport syndrome - Gyarmati, Georgina; Shroff, Urvi Nikhil; Izuhara, Audrey; Hou, Xiaogang; Da Sacco, Stefano; Sedrakyan, Sargis; Lemley, Kevin V.; Amann, Kerstin Ute; Perin, Laura; Peti-Peterdi, Janos (JCI Insight, 2022)
Alport syndrome (AS) is a genetic disorder caused by mutations in type IV collagen that lead to defective glomerular basement membrane, glomerular filtration barrier (GFB) damage, and progressive chronic kidney disease. While the genetic basis of AS is well known, the molecular and cellular mechanistic details of disease pathogenesis have been elusive, hindering the development of mechanism-based therapies. Here, we performed intravital multiphoton imaging of the local kidney tissue microenvironment in a X-linked AS mouse model to directly visualize the major drivers of AS pathology. Severely distended glomerular capillaries and aneurysms were found accompanied by numerous microthrombi, increased glomerular endothelial surface layer (glycocalyx) and immune cell homing, GFB albumin leakage, glomerulosclerosis, and interstitial fibrosis by 5 months of age, with an intermediate phenotype at 2 months. Renal histology in mouse or patient tissues largely failed to detect capillary aberrations. Treatment of AS mice with hyaluronidase or the ACE inhibitor enalapril reduced the excess glomerular endothelial glycocalyx and blocked immune cell homing and GFB albumin leakage. This study identified central roles of glomerular mechanical forces and endothelial and immune cell activation early in AS, which could be therapeutically targeted to reduce mechanical strain and local tissue inflammation and improve kidney function.
CRIS-Team Scopus Importer:2022-01-28

IQGAP3, a YAP target, is required for proper cell-cycle progression and genome stability - Leone, Marina; Cazorla-Vazquez, Salvador; Ferrazzi, Fulvia; Wiederstein, Janica L.; Grundl, Marco; Weinstock, Grit; Vergarajauregui, Silvia; Eckstein, Markus; Kruger, Marcus; Gaubatz, Stefan; Engel, Felix (Molecular Cancer Research, 2021)
Controlling cell proliferation is critical for organism development, tissue homeostasis, disease, and regeneration. IQGAP3 has been shown to be required for proper cell proliferation and migration, and is associated to a number of cancers. Moreover, its expression is inversely correlated with the overall survival rate in the majority of cancers. Here, we show that IQGAP3 expression is elevated in cervical cancer and that in these cancers IQGAP3 high expression is correlated with an increased lethality. Furthermore, we demonstrate that IQGAP3 is a target of YAP, a regulator of cell cycle gene expression. IQGAP3 knockdown resulted in an increased percentage of HeLa cells in S phase, delayed progression through mitosis, and caused multipolar spindle formation and consequentially aneuploidy. Protein–protein interaction studies revealed that IQGAP3 interacts with MMS19, which is known in Drosophila to permit, by competitive binding to Xpd, Cdk7 to be fully active as a Cdk-activating kinase (CAK). Notably, IQGAP3 knockdown caused decreased MMS19 protein levels and XPD knockdown partially rescued the reduced proliferation rate upon IQGAP3 knockdown. This suggests that IQGAP3 modulates the cell cycle via the MMS19/XPD/CAK axis. Thus, in addition to governing proliferation and migration, IQGAP3 is a critical regulator of mitotic progression and genome stability. Implications: Our data indicate that, while IQGAP3 inhibition might be initially effective in decreasing cancer cell proliferation, this approach harbors the risk to promote aneuploidy and, therefore, the formation of more aggressive cancers.
CRIS-Team Scopus Importer:2021-11-05

Is Early Complement Activation in Renal Transplantation Associated with Later Graft Outcome? - Bobka, Steffen; Ebert, Nadja; Koertvely, Eloed; Jacobi, Johannes; Wiesener, Michael; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Kidney & Blood Pressure Research, 2018)
BACKGROUND/AIMS: Complement activation is important in post-transplantation renal injury, but data on its role as predictor of transplant outcome/complications when assessed in donor kidneys are lacking. METHODS: In human renal transplant biopsies with delayed graft function (DGF, n=12), antibody mediated rejection (ABMR, n=8), T-cell mediated rejection (TCMR, n=11), 1 year protocol biopsies (control, n=10) and corresponding zero-biopsies we performed immunohistochemical analyses of 6 complement factors using FFPE sections and correlated the findings with kidney function, as assessed by serum creatinine, and morphological changes including interstitial fibrosis and tubular atrophy (IF/TA). RESULTS: In DGF, TCMR and ABMR significant complement deposition was observed, which was less pronounced in corresponding zero-biopsies. Zero-biopsies with subsequent ABMR showed glomerular complement factor D and C3c expression. Moreover, glomerular C3c and C9 and tubular MASP-2 and Collectin-11 expression in zero-biopsies significantly correlated with serum creatinine at diagnosis of DGF, TCMR or ABMR. Glomerular C1q was significantly increased in ABMR, but not in DGF and TCMR. In contrast, peritubular C1q was significantly enhanced in DGF and TCMR compared to zero-biopsies. Using C3d as a surrogate marker for complement activity we could confirm that stained complement factors are frequently associated with complement activity. CONCLUSION: Complement deposition strongly correlated with histopathological changes observed in renal transplants. All 3 complement pathways were operational in biopsies with DGF, TCMR and ABMR albeit with differential abundance and localization. Since complement deposition in zero-biopsies correlated with graft function and morphological changes, early specific complement inhibition in renal transplantation may be a new therapeutic option to prevent graft loss.
EVALuna2:35394

Isolated thrombotic microangiopathy of the small intestine in a patient with atypical hemolytic uremic syndrome - a case report - Nunius, Christoph; Büttner-Herold, Maike; Bertz, Simone; Schiffer, Mario; Buchholz, Björn (BMC Nephrology, 2020)
Background: Atypical hemolytic uremic syndrome (aHUS) is a rare disease characterized by systemic thrombotic microangiopathy (TMA) reflected by hemolysis, anemia, thrombocytopenia and systemic organ injury. The optimal management of aHUS-patients when undergoing kidney transplantation to prevent recurrence in the allograft is eculizumab, an approved recombinant antibody targeting human complement component C5. Case presentation: A 39 year-old woman presented with severe abdominal pain, diarrhea and emesis for 3 days. In her past medical history she had experienced an episode of aHUS leading to end stage renal disease (ESRD) in 2007 and a genetic workup revealed a heterozygous mutation in the membrane cofactor protein gene. In 2014 she underwent cadaveric kidney transplantation. Four years later she had to go back on hemodialysis due to allograft failure following a severe systemic cytomegalovirus infection resulting in transplant failure. At presentation she still received calcineurin-inhibitor therapy and reported subfebrile temperatures and pain projecting over the transplant prior to the current symptoms. A contrast enhanced CT-scan of the abdomen revealed inflammatory wall thickening of the small intestine. Diagnostic endoscopy discovered fresh blood in the small intestine without a clear source of bleeding. Histopathology of the small intestine biopsies showed severe thrombotic microangiopathy. Of note, the patient persistently had no signs of systemic hemolysis. Since the TMA of the small intestine was most likely due to aHUS, eculizumab treatment was initiated which abolished the symptoms. Conclusion: Here we report a patient with thrombotic microangiopathy with predominant manifestation in a single organ, the small intestine, due to aHUS with absence of systemic signs and symptoms. aHUS patients usually require a secondary trigger for the disease to manifest. In this case, the trigger may be attributed to the dysfunctional renal transplant, which was subsequently explanted. Histology of the explanted kidney showed severe inflammation due to purulent nephritis and signs of cellular rejection. After nephrectomy, we continued eculizumab therapy until the patient completely recovered. No signs of TMA recurred after discontinuation of eculizumab, further supporting the concept of the renal transplant as the main trigger of TMA of the small intestine in our patient.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Atypical hemolytic uremic syndrome; Case report; Renal transplant; Small intestine; Thrombotic microangiopathy

Isolation, Culture, and Live-Cell Imaging of Primary Rat Cardiomyocytes - Leone, Marina; Engel, Felix (Methods in Molecular Biology, 2021)
The heart is a complex organ consisting of a variety of different cardiomyocytes (ventricular vs. atrial, left vs. right ventricular, working vs. nodal) as well as other cell types, including endothelial cells and vascular smooth muscle cells. Pericytes, neurons, and immune cells are less abundant, yet still important. Whereas cardiomyocytes account for around 75% of the heart volume, 50-70% of the cells in the heart are non-myocytes. This complexity of the heart underlines the difficulties in interpreting data obtained in vivo. In the field of cardiac regeneration, it remains unclear whether it is possible to induce a significant number of cardiomyocytes to proliferate and whether the often-observed improvement in cardiac function after experimental therapies is due to the induction of cardiomyocyte proliferation. Therefore, the reductionist approach inherent to cultures of isolated cells continues to be of great importance, even though it is important to study heart disease in vivo due to interactions of the different cell types. Cultured cardiomyocytes allow for easy manipulation of cell behavior (e.g., cell division) and its analysis (e.g., live-cell imaging). In addition, isolated cells in culture are a valuable tool for pharmacological and toxicological studies. This chapter offers a practical guide to isolate and culture primary neonatal and adult rat cardiomyocytes and a detailed protocol for live-cell imaging of embryonic and neonatal cardiomyocytes.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Adult; Cardiomyocytes; Langendorff-perfusion; Live-cell imaging; MACS; Neonatal; Rat; SADO Mix

Isolation of Human Endothelial Cells from Normal Colon and Colorectal Carcinoma - An Improved Protocol - Naschberger, Elisabeth; Regensburger, Daniela; Tenkerian, Clara; Langheinrich, Melanie; Engel, Felix; Geppert, Carol-Immanuel; Hartmann, Arndt; Grützmann, Robert; Schellerer, Vera; Stürzl, Michael (Journal of Visualized Experiments, 2018)
Primary cells isolated from human carcinomas are valuable tools to identify pathogenic mechanisms contributing to disease development and progression. In particular, endothelial cells (EC) constituting the inner surface of vessels, directly participate in oxygen delivery, nutrient supply, and removal of waste products to and from tumors, and are thereby prominently involved in the constitution of the tumor microenvironment (TME). Tumor endothelial cells (TECs) can be used as cellular biosensors of the intratumoral microenvironment established by communication between tumor and stromal cells. TECs also serve as targets of therapy. Accordingly, in culture these cells allow studies on mechanisms of response or resistance to anti-angiogenic treatment. Recently, it was found that TECs isolated from human colorectal carcinoma (CRC) exhibit memory-like effects based on the specific TME they were derived from. Moreover, these TECs actively contribute to the establishment of a specific TME by the secretion of different factors. For example, TECs in a prognostically favorable Th1-TME secrete the anti-angiogenic tumor-suppressive factor secreted protein, acidic and rich in cysteine-like 1 (SPARCL1). SPARCL1 regulates vessel homeostasis and inhibits tumor cell proliferation and migration. Hence, cultures of pure, viable TECs isolated from human solid tumors are a valuable tool for functional studies on the role of the vascular system in tumorigenesis. Here, a new up-to-date protocol for the isolation of primary EC from the normal colon as well as CRC is described. The technique is based on mechanical and enzymatic tissue digestion, immunolabeling, and fluorescence activated cell sorting (FACS)-sorting of triple-positive cells (CD31, VE-cadherin, CD105). With this protocol, viable TEC or normal endothelial cell (NEC) cultures could be isolated from colon tissues with a success rate of 62.12% when subjected to FACS-sorting (41 pure EC cultures from 66 tissue samples). Accordingly, this protocol provides a robust approach to isolate human EC cultures from normal colon and CRC.
EVALuna2:34267

Janus kinase 3 regulates renal 25-hydroxyvitamin D 1?-hydroxylase expression, calcitriol formation, and phosphate metabolism - Umbach, Anja T.; Zhang, Bingbing; Daniel, Christoph; Fajol, Abul; Velic, Ana; Hosseinzadeh, Zohreh; Bhavsar, Shefalee K.; Bock, C-Thomas; Kandolf, Reinhard; Pichler, Bernd J.; Amann, Kerstin Ute; Foeller, Michael; et al. (Kidney International, 2015)
Calcitriol, a powerful regulator of phosphate metabolism and immune response, is generated by 25-hydroxyvitamin D 1?-hydroxylase in the kidney and macrophages. Renal 1?-hydroxylase expression is suppressed by Klotho and FGF23, the expression of which is stimulated by calcitriol. Interferon ? (INF?) regulates 1?-hydroxylase expression in macrophages through transcription factor interferon regulatory factor-1. INF?-signaling includes Janus kinase 3 (JAK3) but a role of JAK3 in the regulation of 1?-hydroxylase expression and mineral metabolism has not been shown. Thus, the impact of JAK3 deficiency on calcitriol formation and phosphate metabolism was measured. Renal interferon regulatory factor-1 and 1?-hydroxylase transcript levels, serum calcitriol and FGF23 levels, intestinal phosphate absorption as well as absolute and fractional renal phosphate excretion were significantly higher in jak3 knockout than in wild-type mice. Coexpression of JAK3 increased the phosphate-induced current in renal sodium-phosphate cotransporter-expressing Xenopus oocytes. Thus, JAK3 is a powerful regulator of 1?-hydroxylase expression and phosphate transport. Its deficiency leads to marked derangement of phosphate metabolism.
EVALuna2:25470

Key role of renal biopsy in management of progressive chronic kidney disease in liver graft recipients - Welker, Martin-Walter; Weiler, Nina; Bechstein, Wolf Otto; Herrmann, Eva; Betz, Christoph; Schoeffauer, Mark; Zeuzem, Stefan; Sarrazin, Christoph; Amann, Kerstin Ute; Jung, Oliver (Journal of Nephrology, 2018)
AIMS: Chronic kidney disease (CKD) is a common complication after liver transplantation (LT). The etiology of CKD is broad and may only be assessed accurately by renal histology. The current study aimed to analyze the safety of renal biopsy in daily clinical practice as well as its usefulness regarding management of CKD after LT. METHODS: We performed a retrospective analysis of clinical data and renal biopsies obtained from patients with severe renal impairment (overt proteinuria, progressive deterioration of renal function) after LT with respect to safety, etiology of renal disease, and therapeutic consequences. RESULTS: Renal biopsies were obtained from 14 patients at median (minimum-maximum) 3 (0.2-12) years after LT. No major complications associated with renal biopsy were observed. Histomorphological alterations were varied (nephrosclerosis, n = 5; IgA-glomerulonephritis, n = 4; tenofovir-associated nephropathy, membranoproliferative glomerulonephritis type 1, membranous glomerulonephritis, amyloid A amyloidosis, and calcineurin inhibitor nephropathy, n = 1, respectively). The diagnosis of specific renal diseases other than calcineurin-inhibitor nephrotoxicity facilitated specific treaments and avoided unnecessary modification of immunosuppression in the majority of patients. CONCLUSIONS: Renal biopsy in patients with CKD after LT seems safe and may offer specific therapeutic options. Furthermore, unnecessary changes of immunosuppression can be avoided in a considerable number of patients.
EVALuna2:34431

Key role of renal biopsy in management of progressive chronic kidney disease in liver graft recipients - Welker, Martin-Walter; Weiler, Nina; Bechstein, Wolf Otto; Herrmann, Eva; Betz, Christoph; Schoeffauer, Mark; Zeuzem, Stefan; Sarrazin, Christoph; Amann, Kerstin Ute; Jung, Oliver (Journal of Nephrology, 2019)
Aims Chronic kidney disease (CKD) is a common complication after liver transplantation (LT). The etiology of CKD is broad and may only be assessed accurately by renal histology. The current study aimed to analyze the safety of renal biopsy in daily clinical practice as well as its usefulness regarding management of CKD after LT.
CRIS-Team WoS Importer:2019-02-27

Kidney injury is independent of endothelial HIF-1? - Kalucka, Joanna; Schley, Gunnar; Georgescu, Adela; Klanke, Bernd; Roessler, Susanne; Baumgartl, Jasmin; Velden, Joachim; Amann, Kerstin Ute; Willam, Carsten; Johnson, Randall S.; Eckardt, Kai-Uwe; Weidemann, Alexander (Journal of Molecular Medicine, 2015)
Hypoxia-inducible transcription factors (HIFs) control cellular adaptation to low oxygen. In the kidney, activation of HIF is beneficial during injury; however, the specific contribution of HIF-1? in renal endothelial cells (EC) remains elusive. Since EC display tissue-specific heterogeneity, we investigated how HIF-1? affects key functions of glomerular EC in vitro and its contribution to renal development and pathophysiological adaptation to acute or chronic renal injury in vivo. Loss of HIF-1? in glomerular EC induces hypoxic cell death and reduces hypoxic adhesion of macrophages in vitro. In vivo, HIF-1? expression in EC in mouse kidneys is detectable but limited. Accordingly, EC-specific ablation of HIF-1? does not lead to developmental or phenotypical abnormalities in the kidney. Renal function and expression of adhesion molecules during acute ischemic kidney injury is independent of HIF-1? in EC. Likewise, inflammation and development of fibrosis after unilateral ureteric obstruction is not influenced by endothelial HIF-1?. Taken together, although HIF-1? exerts effects on glomerular EC in vitro, endothelial HIF-1? does not influence renal development and pathophysiological adaptation to kidney injury in vivo. This implies a profound difference of the hypoxic response of the renal vascular bed compared to other organs, such as the heart. This has implications for the development of pharmacological strategies targeting the endothelial hypoxic response pathways.HIF-1? controls hypoxic survival and adhesion on endothelial cells (EC) in vitro. In vivo, HIF-1? expression in renal EC is low. Deletion of HIF-1? in EC does not affect kidney development and function in mice. Renal function after acute and chronic kidney injury is independent of HIF-1? in EC. Data suggest organ-specific regulation of HIF-1? function in EC.
EVALuna2:3772

Kidney transplantation after rescue allocation-meticulous selection yields the chance for excellent outcome - Assfalg, Volker; Misselwitz, Svea; Renders, Lutz; Hüser, Norbert; Novotny, Alexander; Jäger, Carsten; Büttner-Herold, Maike; Amann, Kerstin Ute; Schmaderer, Christoph; Heemann, Uwe; Wen, Ming; Haberfellner, Flora; et al. (Nephrology Dialysis Transplantation, 2021)
BACKGROUND: The small number of organ donors forces transplant centres to consider potentially suboptimal kidneys for transplantation. Eurotransplant established an algorithm for rescue allocation (RA) of kidneys repeatedly declined or not allocated within 5 h after procurement. Data on the outcomes and benefits of RA are scarce to date. METHODS: We conducted a retrospective 8-year analysis of transplant outcomes of RA offers based on our in-house criteria catalogue for acceptance and decline of organs and potential recipients. RESULTS: RA donors and recipients were both older compared with standard allocation (SA). RA donors more frequently had a history of hypertension, diabetes or fulfilled expanded criteria donor key parameters. RA recipients had poorer human leucocyte antigen (HLA) matches and longer cold ischaemia times (CITs). However, waiting time was shorter and delayed graft function, primary non-function and biopsy-proven rejections were comparable to SA. Five-year graft and patient survival after RA were similar to SA. In multivariate models accounting for confounding factors, graft survival and mortality after RA and SA were comparable as well. CONCLUSIONS: Facing relevant comorbidities and rapid deterioration with the risk of being removed from the waiting list, kidney transplantation after RA was identified to allow for earlier transplantation with excellent outcome. Data from this survey propose not to reject categorically organs from multimorbid donors with older age and a history of hypertension or diabetes to aim for the best possible HLA matching and to carefully calculate overall expected CIT.
CRIS-Team Scopus Importer:2021-03-19
Keywords: allocation; kidney; outcome; rescue; transplantation

Knockdown of ApoL1 in Zebrafish Larvae Affects the Glomerular Filtration Barrier and the Expression of Nephrin - Kotb, Ahmed M.; Simon, Ole; Blumenthal, Antje; Vogelgesang, Silke; Dombrowski, Frank; Amann, Kerstin Ute; Zimmermann, Uwe; Endlich, Karlhans; Endlich, Nicole (PLoS ONE, 2016)
APOL1, a secreted high-density lipoprotein, is expressed in different human tissues. Genetic variants of APOL1 are described to be associated with the development of end stage renal diseases in African Americans. In human kidney, APOL1 is mainly expressed in podocytes that are responsible for proper blood filtration. Since mice do not express ApoL1, the zebrafish is an ideal model to study the role of ApoL1. Injection of morpholinos against zApoL1 into zebrafish eggs and larvae, respectively, induces severe edema indicating a leakage of the filtration barrier. This was demonstrated in zApoL1 knockdown larvae by intravascular injection of fluorescently-labeled 10- and 500-kDa dextrans and by clearance of the vitamin D-binding protein from the circulation. Immunohistochemistry and RT-PCR revealed the reduction of nephrin, a podocyte-specific protein essential for blood filtration. Coinjection of human nephrin mRNA rescued the zApoL1 knockdown induced phenotype. Reduced APOL1 and nephrin levels were also found in biopsies of patients suffering from end stage renal diseases. Our results demonstrate that zApoL1 is essential for proper blood filtration in the zebrafish glomerulus and that zApoL1 affects the expression of nephrin.
EVALuna2:25517

Lack of intestinal epithelial atg7 affects paneth cell granule formation but does not compromise immune homeostasis in the gut. - Günther, Claudia; Martini, Eva; Waldner, Maximilian; Amann, Kerstin Ute; Neurath, Markus; Becker, Christoph; et al. (Clinical & Developmental Immunology, 2012)
Genetic polymorphisms of autophagy-related genes have been associated with an increased risk to develop inflammatory bowel disease (IBD). Autophagy is an elementary process participating in several cellular events such as cellular clearance and nonapoptotic programmed cell death. Furthermore, autophagy may be involved in intestinal immune homeostasis due to its participation in the digestion of intracellular pathogens and in antigen presentation. In the present study, the role of autophagy in the intestinal epithelial layer was investigated. The intestinal epithelium is essential to maintain gut homeostasis, and defects within this barrier have been associated with the pathogenesis of IBD. Therefore, mice with intestinal epithelial deletion of Atg7 were generated and investigated in different mouse models. Knockout mice showed reduced size of granules and decreased levels of lysozyme in Paneth cells. However, this was dispensable for gut immune homeostasis and had no effect on susceptibility in mouse models of experimentally induced colitis.

Large-scale microRNA functional high-throughput screening identifies miR-515-3p and miR-519e-3p as inducers of human cardiomyocyte proliferation - Renikunta, Harsha V.; Lazarow, Katina; Gong, Yiqi; Shukla, Praphulla Chandra; Nageswaran, Vanasa; Giral, Hector; Kratzer, Adelheid; Opitz, Lennart; Engel, Felix; Haghikia, Arash; Costantino, Sarah; Paneni, Francesco; et al. (iScience, 2023)
Ischemic cardiomyopathy, driven by loss of cardiomyocytes and inadequate proliferative response, persists to be a major global health problem. Using a functional high-throughput screening, we assessed differential proliferative potential of 2019 miRNAs after transient hypoxia by transfecting both miR-inhibitor and miR-mimic libraries in human iPSC-CM. Whereas miR-inhibitors failed to enhance EdU uptake, overexpression of 28 miRNAs substantially induced proliferative activity in hiPSC-CM, with an overrepresentation of miRNAs belonging to the primate-specific C19MC-cluster. Two of these miRNAs, miR-515-3p and miR-519e-3p, increased markers of early and late mitosis, indicative of cell division, and substantially alter signaling pathways relevant for cardiomyocyte proliferation in hiPSC-CM.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Cardiovascular medicine; Genetics; Molecular biology

Lenalidomide enhances MOR202-dependent macrophage-mediated effector functions via the vitamin D pathway - Busch, Leonhard; Mougiakakos, Dimitrios; Büttner-Herold, Maike; Müller, Miriam J.; Volmer, Dietrich A.; Bach, Christian; Fabri, Mario; Bittenbring, Jörg T.; Neumann, Frank; Boxhammer, Rainer; Nolting, Jens; Bisht, Savita; et al. (Leukemia, 2018)
Macrophages are key mediators of the therapeutic effects exerted by monoclonal antibodies, such as the anti-CD38 antibody MOR202, currently introduced in multiple myeloma (MM) therapy. Therefore, it is important to understand how antibody-mediated effector functions of myeloma-associated macrophages (MAMs) are regulated. Here, we focused on the effects of vitamin D, a known regulator of macrophage effector functions. Consequently, it was the aim of this study to assess whether modulation of the vitamin D pathway alters the tumoricidal activity of MAMs. Here, we demonstrate that MAMs display a defective vitamin D pathway with reduced expression level of CYP27B1 and limited tumoricidal activity which can be restored by the IMiD lenalidomide in vitro. Furthermore, our data indicate that the vitamin D pathway of MAMs from MM patients does recover during an IMiD-containing therapy shown by an improved MOR202-mediated cytotoxic activity of these MAMs against primary MM cells ex vivo. Here, the ex vivo cytotoxic activity could be further enhanced by vitamin D supplementation. These data suggest that vitamin D holds a key role for the effector functions of MAMs and that vitamin D supplementation in IMiD combination trials could further increase the therapeutic efficacy of anti-CD38 antibodies such as MOR202, which remains to be investigated in clinical studies.
EVALuna2:34165

Lessons for the clinical nephrologist: recurrence of nephrotic syndrome induced by SARS-CoV-2 - Doevelaar, Adrian A.N.; Hölzer, Bodo; Seibert, Felix S.; Bauer, Frederic; Stervbo, Ulrik; Rohn, Benjamin J.; Zgoura, Panagiota; Schenker, Peter; Vonbrunn, Eva; Amann, Kerstin Ute; Viebahn, Richard; Babel, Nina; et al. (Journal of Nephrology, 2020)
SARS-CoV-2 is characterized by a multiorgan tropism including the kidneys. Recent autopsy series indicated that SARS-CoV-2 can infect both tubular and glomerular cells. Whereas tubular cell infiltration may contribute to acute kidney injury, data on a potential clinical correlative to glomerular affection is rare. We describe the first case of nephrotic syndrome in the context of COVID-19 in a renal transplant recipient. A 35 year old male patient received a kidney allograft for primary focal segmental glomerulosclerosis (FSGS). Three months posttransplant a recurrence of podocytopathy was successfully managed by plasma exchange, ivIG, and a conversion from tacrolimus to belatacept (initial proteinuria > 6 g/l decreased to 169 mg/l). Six weeks later he was tested positive for SARS-CoV-2 and developed a second increase of proteinuria (5.6 g/l). Renal allograft biopsy revealed diffuse podocyte effacement and was positive for SARS-CoV-2 in RNA in-situ hybridation indicating a SARS-CoV-2 associated recurrence of podocytopathy. Noteworthy, nephrotic proteinuria resolved spontaneously after recovering from COVID-19. The present case expands the spectrum of renal involvement in COVID-19 from acute tubular injury to podocytopathy in renal transplant recipients. Thus, it may be wise to test for SARS-CoV-2 prior to initiation of immunosuppression in new onset glomerulopathy during the pandemic.
CRIS-Team Scopus Importer:2020-09-18
Keywords: COVID-19; Podocytopathy; SARS-CoV-2

Light chain proximal tubulopathy in the spectrumof B-cell dyscrasia induced renal disease - Buettner-Herold, M.; Chuva, T.; Minuth, Kaija; Pfister, F.; Daniel, C.; Klewer, M.; Buttner, A.; Ferrazzi, F.; Bertz, S.; Amann, Kerstin Ute (2018)
EVALuna2:34617

Light Chain Restriction in Proximal Tubules—Implications for Light Chain Proximal Tubulopathy - Büttner-Herold, Maike; Krieglstein, Nathalie; Chuva, Teresa; Minuth, Kaija; Pfister, Frederick; Daniel, Christoph; Klewer, Monika; Büttner, Anke; Ferrazzi, Fulvia; Bertz, Simone; Amann, Kerstin Ute (Frontiers in Medicine, 2022)
Monoclonal gammopathy (MG) causes various nephropathies, which may suffice for cytoreductive therapy even in the absence of diagnostic criteria for multiple myeloma or B-cell non-Hodgkin lymphoma. The aim of this study was to better understand the significance of light chain (LC) restriction or crystals (LC-R/C) in proximal tubules in the spectrum of LC-induced nephropathies. A consecutive cohort of 320 renal specimens with a history of B-cell dyscrasia was characterized. Special attention was paid to immunohistochemical LC restriction in proximal tubules, tubular crystals or constipation, and ultrastructural findings. Complementary cell culture experiments were performed to assess the role of LC concentrations in generating LC restriction. Light chain restriction or crystals in proximal tubules was found in a quarter of analyzed cases (81/316) and was associated with another LC-induced disease in 70.4% (57/81), especially LC cast-nephropathy (cast-NP) and interstitial myeloma infiltration. LC restriction without significant signs of acute tubular injury was observed in 11.1% (9/81). LC-R/C was not associated with inferior renal function compared to the remainder of cases, when cases with accompanying cast-NP were excluded. Besides crystals, cloudy lysosomes were significantly associated with LC-R/C on an ultrastructural level. In summary, LC-R/C is frequent and strongly associated with cast-NP, possibly indicating that a high load of clonal LC is responsible for this phenomenon, supported by the observation that LC restriction can artificially be generated in cell culture. This and the lack of significant tubular injury in a subgroup imply that in part LC-R/C is a tubular trafficking phenomenon rather than an independent disease process.
CRIS-Team Scopus Importer:2022-04-29
Keywords: cast nephropathy; light chain restriction; monoclonal gammopathies of renal significance; renal tubule; tubular crystals

Lineage-associated connexin 43 expression in bisphosphonate-exposed rat bones - Preidl, Raimund; Amann, Kerstin Ute; Weber, Manuel; Schiller, Martin; Ringler, Manuela; Ries, Jutta; Neukam, Friedrich Wilhelm; Kesting, Marco Rainer; Geppert, Carol-Immanuel; Wehrhan, Falk (Journal of Cranio-Maxillofacial Surgery, 2021)
Expression of signaling proteins in bone cells depends on their embryological mesoderm-derived (e.g. tibia) or cranial neural crest (CNC)-derived (e.g. jaw) origin. Connexin 43 (Cx43) is a gap junction protein that plays an essential role in the mode of action of bisphosphonates (BP). This study aimed to investigate Cx43 expression and the influence of BP application on mesoderm- and CNC-derived bone. Using a rat model, molar extraction and tibia osteotomy with (Group 4) or without (Group 3) previous BP application was performed. Untreated (Group 1) and animals selectively treated with BPs (Group 2) served as controls. Cx43 expression was immunohistochemically determined 12 and 16 weeks postoperatively via a labeling index. Cx43 expression in CNC-derived bone was significantly higher compared with mesodermal bone. BP application decreased Cx43 expression; however, detected expression levels were still higher in jawbone (Group 2 tibia vs jaw: 5.83 ± 5.06 vs 23.52 ± 6.42; p = 0.007). During bone healing after surgical intervention (Group 3) there were no expression differences between tibia and jawbone. BP treatment prior to surgery resulted in significantly lower Cx43 expression in CNC-derived compared with tibia bone (Group 4 tibia vs jaw: 56.84 ± 15.57 vs 16.40 ± 5.66; p < 0.01). Increased Cx43 expression in jaw compared with tibia bone is in line with their embryological origins. A significant Cx43 suppression in jawbone after BP application and surgery might contribute to the selectively altered osseous turnover and development of MRONJ in CNC-derived bone.
CRIS-Team Scopus Importer:2021-03-12
Keywords: Bisphosphonate; Jawbone; Medication-related osteonecrosis of the jaw (MRONJ)

Lipomatous Solitary Fibrous Tumors Harbor Rare NAB2-STAT6 Fusion Variants and Show Up-Regulation of the Gene PPARG, Encoding for a Regulator of Adipocyte Differentiation - Haller, Florian; Schlieben, Lea D.; Ferrazzi, Fulvia; Michal, Michael; Stöhr, Robert; Moskalev, Evgeny; Bieg, Matthias; Bovée, Judith V.M.G.; Ströbel, Philip; Ishaque, Naveed; Grützmann, Robert; Meidenbauer, Norbert; et al. (American Journal of Pathology, 2021)
Solitary fibrous tumors (SFTs) harbor activating NAB2-STAT6 gene fusions. Different variants of the NAB2-STAT6 gene fusion have been associated with distinct clinicopathologic features. Lipomatous SFTs are a morphologic variant of SFTs, characterized by a fat-forming tumor component. Our aim was to evaluate NAB2-STAT6 fusion variants and to further study the molecular genetic features in a cohort of lipomatous SFTs. A hybrid-capture–based next-generation sequencing panel was employed to detect NAB2-STAT6 gene fusions at the RNA level. In addition, the RNA expression levels of 507 genes were evaluated using this panel, and were compared with a control cohort of nonlipomatous SFTs. Notably, 5 of 11 (45%) of lipomatous SFTs in the current series harbored the uncommon NAB2 exon 4–STAT6 exon 4 gene fusion variant, which is observed in only 0.9% to 1.4% of nonlipomatous SFTs. Furthermore, lipomatous SFTs displayed significant differences in gene expression compared with their nonlipomatous counterparts, including up-regulation of the gene peroxisome proliferator activated receptor-γ (PPARG). Peroxisome proliferator activated receptor-γ is a nuclear receptor regulating adipocyte differentiation, providing a possible explanation for the fat-forming component in lipomatous SFTs. In summary, the current study provides a possible molecular genetic basis for the distinct morphologic features of lipomatous SFTs.
CRIS-Team Scopus Importer:2021-06-04

Live cell screening identifies glycosides as enhancers of cardiomyocyte cell cycle activity - Magadum, Ajit; Renikunta, Harsha V.; Singh, Neha; Estaras, Conchi; Kishore, Raj; Engel, Felix (Frontiers in Cardiovascular Medicine, 2022)
Promoting cardiomyocyte proliferation is a promising strategy to regenerate the heart. Yet, so far, it is poorly understood how cardiomyocyte proliferation is regulated, and no factor identified to promote mammalian cardiomyocyte proliferation has been translated into medical practice. Therefore, finding a novel factor will be vital. Here, we established a live cell screening based on mouse embryonic stem cell-derived cardiomyocytes expressing a non-functional human geminin deletion mutant fused to Azami Green (CM7/1-hgem-derived cardiomyocytes). We screened for a subset of compounds of the small molecule library Spectrum Collection and identified 19 potential inducers of stem cell-derived cardiomyocyte proliferation. Furthermore, the pro-proliferative potential of identified candidate compounds was validated in neonatal and adult rat cardiomyocytes as well as human induced pluripotent stem cell-derived cardiomyocytes. 18 of these compounds promoted mitosis and cytokinesis in neonatal rat cardiomyocytes. Among the top four candidates were two cardiac glycosides, peruvoside and convallatoxin, the flavonoid osajin, and the selective α-adrenoceptor antagonist and imidazoline I1 receptor ligand efaroxan hydrochloride. Inhibition of PTEN and GSK-3β enhanced cell cycle re-entry and progression upon stimulation with cardiac glycosides and osajin, while inhibition of IP3 receptors inhibited the cell cycle-promoting effect of cardiac glycosides. Collectively, we established a screening system and identified potential compounds to promote cardiomyocyte proliferation. Our data suggest that modulation of calcium handling and metabolism promotes cardiomyocyte proliferation, and cardiac glycosides might, besides increasing myocardial contraction force, contribute to cardiac repair by inducing cardiomyocyte proliferation.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Azami Green; calcium handling; cardiac glycosides; cardiomyocyte proliferation; cell cycle; live cell screening platform AG; small molecules; stem cell

Live cell screening platform identifies PPAR? as a regulator of cardiomyocyte proliferation and cardiac repair - Magadum, Ajit; Ding, Yishu; He, Lan; Kim, Teayoun; Vasudevarao, Mohankrishna Dalvoy; Long, Qinqiang; Yang, Kevin; Wickramasinghe, Nadeera; Renikunta, Harsha V.; Dubois, Nicole; Weidinger, Gilbert; Yang, Qinglin; et al. (Cell Research, 2017)
Zebrafish can efficiently regenerate their heart through cardiomyocyte proliferation. In contrast, mammalian cardiomyocytes stop proliferating shortly after birth, limiting the regenerative capacity of the postnatal mammalian heart. Therefore, if the endogenous potential of postnatal cardiomyocyte proliferation could be enhanced, it could offer a promising future therapy for heart failure patients. Here, we set out to systematically identify small molecules triggering postnatal cardiomyocyte proliferation. By screening chemical compound libraries utilizing a Fucci-based system for assessing cell cycle stages, we identified carbacyclin as an inducer of postnatal cardiomyocyte proliferation. In vitro, carbacyclin induced proliferation of neonatal and adult mononuclear rat cardiomyocytes via a peroxisome proliferator-activated receptor ? (PPAR?)/PDK1/p308Akt/GSK3?/?-catenin pathway. Inhibition of PPAR? reduced cardiomyocyte proliferation during zebrafish heart regeneration. Notably, inducible cardiomyocyte-specific overexpression of constitutively active PPAR? as well as treatment with PPAR? agonist after myocardial infarction in mice induced cell cycle progression in cardiomyocytes, reduced scarring, and improved cardiac function. Collectively, we established a cardiomyocyte proliferation screening system and present a new drugable target with promise for the treatment of cardiac pathologies caused by cardiomyocyte loss.
EVALuna2:25555
Keywords: cardiac repair; cardiomyocyte proliferation; screening; carbacyclin; PPAR delta; GSK3 beta; Tbx20

Localization and characterization of proenkephalin-A as a potential biomarker for kidney disease in murine and human kidneys - Fuchs, Michaela Alexandra Anna; Schrankl, Julia; Wagner, Charlotte; Daniel, Christoph; Kurtz, Armin; Broeker, Katharina Anna Elisabeth (Biomarkers, 2022)
Introduction: Exact measurement of renal function is essential for the treatment of patients. Elevated serum-creatinine levels, while established, are influenced by other parameters and show a significant time-lag. This drives the search for novel biomarkers of renal function and injury. Beside Lipocalin-2 and kidney-injury-molecule-1 (KIM-1), the endogenous opioid precursor proenkephalin-A (Penk) has recently emerged as a promising marker for renal function. But the cellular origin and regulation of Penk outside the brain has not yet been investigated in depth. Materials and methods: This study characterizes the cellular origin of Penk expression with high-resolution in situ hybridization in two models of renal fibrosis in mice and human tissue. Results: Interstitial cells are the main expression site for renal Penk. This classifies Penk as biomarker for interstitial damage as opposed to tubular damage markers like Lipocalin-2 and KIM-1. Furthermore, our data indicate that renal Penk expression is not regulated by classical profibrotic pathways. Discussion: This study characterizes changing Penk expression in the kidneys. The similarity of Penk expression across species gives rise to further investigations into the function of Penk in healthy and injured kidneys. Conclusion: Penk is a promising biomarker for interstitial renal damage that warrants further studies to utilize its predictive potential.Clinical significance Knowledge of real-time renal function is essential for proper treatment of critically ill patients and in early diagnosis of acute kidney injury (AKI). Proenkephalin-A has been measured in a number of patient cohorts as a highly accurate and predictive biomarker of renal damage. The present study identifies Penk as a biomarker for interstitial damage in contrast to the tubular biomarkers such as Lipocalin-2 or KIM-1. Our data show that Penk is regulated independently of classical profibrotic or proinflammatory pathways, indicating it might be more robust against extra-renal influences. Data presented in this study provide fundamental information about cell type-specific localization and regulation of the potential new biomarker Penk across species as foundation for further research.
CRIS-Team Scopus Importer:2022-12-02
Keywords: chronic kidney disease; interstitial fibrosis; kidney damage; Proenkephalin-A; renal function

Localization of angiotensin II type 1 receptor gene expression in rodent and human kidneys - Schrankl, Julia; Fuchs, Michaela; Broeker, Katharina; Daniel, Christoph; Kurtz, Armin; Wagner, Charlotte (American Journal of Physiology-Renal Physiology, 2021)
The kidneys are an important target for angiotensin II (ANG II). In adult kidneys, the effects of ANG II are mediated mainly by ANG II type 1 (AT1) receptors. AT1 receptor expression has been reported for a variety of different cell types within the kidneys, suggesting a broad spectrum of actions for ANG II. Since there have been heterogeneous results in the literature regarding the intrarenal distribution of AT1 receptors, this study aimed to obtain a comprehensive overview about the localization of AT1 receptor expression in mouse, rat, and human kidneys. Using the cell-specific and high-resolution RNAscope technique, we performed colocalization experiments with various cell markers to specifically discriminate between different segments of the tubular and vascular system. Overall, we found a similar pattern of AT1 mRNA expression in mouse, rat, and human kidneys. AT1 receptors were detected in mesangial cells and renin-producing cells. In addition, AT1 mRNA was found in interstitial cells of the cortex and outer medulla. In rodents, late afferent and early efferent arterioles expressed AT1 receptor mRNA, but larger vessels of the investigated species showed no AT1 expression. Tubular expression of AT1 mRNA was species dependent with a strong expression in proximal tubules of mice, whereas expression was undetectable in human tubular cells. These findings suggest that the (juxta)glomerular area and tubulointerstitium are conserved expression sites for AT1 receptors across species and might present the main target sites for ANG II in adult human and rodent kidneys.NEW & NOTEWORTHY Angiotensin II (ANG II) type 1 (AT1) receptors are essential for mediating the effects of ANG II in the kidneys. This study aimed to obtain a comprehensive overview about the cell-specific localization of AT1 receptor expression in rodent and human kidneys using the novel RNAscope technique. We found that the conserved AT1 receptor mRNA expression sites across species are the (juxta)glomerular areas and tubulointerstitium, which might present main target sites for ANG II in adult human and rodent kidneys.
CRIS-Team Scopus Importer:2021-04-23
Keywords: angiotensin II; angiotensin II type 1 receptors; kidney; renin-angiotensin-aldosterone system; RNAscope

LONGITUDINAL INTRAINDIVIDUAL CHANGES OF PERITONEAL HISTOLOGY OVER TIME IN 37 PERITONEAL DIALYSIS PATIENTS - Aziz, Alan; Kielstein, Jan T.; Pfister, Frederick; Amann, Kerstin Ute; Eden, Gabriele (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2022)
CRIS-Team WoS Importer:2022-07-22

Long-term endothelial dysfunction in irradiated vessels: an immunohistochemical analysis - Preidl, Raimund; Möbius, Patrick; Weber, Manuel; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Kesting, Marco Rainer; Geppert, Carol-Immanuel; Wehrhan, Falk (Strahlentherapie und Onkologie, 2019)
BACKGROUND: Microvascular free flap reconstruction has become a standard technique in head and neck reconstructive surgery. Pre-operative radiotherapy is associated with a higher incidence of free flap malperfusion and the need for operative revision. Irradiated vessels present characteristic histomorphological and structural changes. Alterations in endothelial cells of irradiated arteries remain incompletely investigated especially with regard to long-term changes in endothelial dysfunction supporting an intraluminal pro-thrombotic and pro-inflammatory milieu. METHODS: Endothelial expression of intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), E‑ and P‑selectin, endothelial NO-synthase (eNOS), thrombomodulin and plasminogen activator inhibitor-1 (PAI-1) in irradiated and non-irradiated arteries was analysed using immunohistochemistry and Remmele scale grading. The average radiation dose was 58.7 ± 7.0 Gy; the time interval between end of radiation and tissue sampling was 106.0 ± 86.8 months. RESULTS: Endothelial expression of ICAM-1, VCAM-1, E‑ and P‑selectin as well as PAI-1 was significantly increased in previously irradiated arteries compared with non-irradiated controls, whereas thrombomodulin and eNOS expression did not show any differences. However, when comparing non-irradiated free flap arteries with irradiated arteries from the head and neck area in respective individuals, eNOS expression was significantly lower in irradiated vessels whereas ICAM-1, VCAM-1, E‑/p-Selectin and PAI-1 showed significantly higher expression levels. CONCLUSION: There is ongoing endothelial dysfunction in terms of increased expression of pro-thrombotic and pro-inflammatory markers in irradiated arteries even years after radiotherapy. Treating this endothelial dysfunction might reduce the complication rates associated with microvascular free flap reconstructions in irradiated patients.
EVALuna2:35426

Long-term endothelial dysfunction in irradiated vessels: an immunohistochemical analysis Langzeit-Endothelfunktionsstörung in bestrahlten Gefäßen: immunhistochemische Analyse - Preidl, Raimund; Möbius, Patrick; Weber, Manuel; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Kesting, Marco Rainer; Geppert, Carol-Immanuel; Wehrhan, Falk (Strahlentherapie und Onkologie, 2019)
Background: Microvascular free flap reconstruction has become a standard technique in head and neck reconstructive surgery. Pre-operative radiotherapy is associated with a higher incidence of free flap malperfusion and the need for operative revision. Irradiated vessels present characteristic histomorphological and structural changes. Alterations in endothelial cells of irradiated arteries remain incompletely investigated especially with regard to long-term changes in endothelial dysfunction supporting an intraluminal pro-thrombotic and pro-inflammatory milieu. Methods: Endothelial expression of intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), E‑ and P‑selectin, endothelial NO-synthase (eNOS), thrombomodulin and plasminogen activator inhibitor-1 (PAI-1) in irradiated and non-irradiated arteries was analysed using immunohistochemistry and Remmele scale grading. The average radiation dose was 58.7 ± 7.0 Gy; the time interval between end of radiation and tissue sampling was 106.0 ± 86.8 months. Results: Endothelial expression of ICAM-1, VCAM-1, E‑ and P‑selectin as well as PAI-1 was significantly increased in previously irradiated arteries compared with non-irradiated controls, whereas thrombomodulin and eNOS expression did not show any differences. However, when comparing non-irradiated free flap arteries with irradiated arteries from the head and neck area in respective individuals, eNOS expression was significantly lower in irradiated vessels whereas ICAM-1, VCAM-1, E‑/p-Selectin and PAI-1 showed significantly higher expression levels. Conclusion: There is ongoing endothelial dysfunction in terms of increased expression of pro-thrombotic and pro-inflammatory markers in irradiated arteries even years after radiotherapy. Treating this endothelial dysfunction might reduce the complication rates associated with microvascular free flap reconstructions in irradiated patients.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Endothelial dysfunction; Free tissue flaps; Radiation dosage; Radiotherapy; Reconstructive surgery

Loss of Survivin in Intestinal Epithelial Progenitor Cells Leads to Mitotic Catastrophe and Breakdown of Gut Immune Homeostasis - Martini, Eva; Wittkopf, Nadine; Günther, Claudia; Leppkes, Moritz; Okada, Hitoshi; Watson, Alastair J.; Podstawa, Eva; Backert, Ingo; Amann, Kerstin Ute; Neurath, Markus; Becker, Christoph (Cell Reports, 2016)
A tightly regulated balance of proliferation and cell death of intestinal epithelial cells (IECs) is essential for maintenance of gut homeostasis. Survivin is highly expressed during embryogenesis and in several cancer types, but little is known about its role in adult gut tissue. Here, we show that Survivin is specifically expressed in transit-amplifying cells and Lgr5(+) stem cells. Genetic loss of Survivin in IECs resulted in destruction of intestinal integrity, mucosal inflammation, and death of the animals. Survivin deletion was associated with decreased epithelial proliferation due to defective chromosomal segregation. Moreover, Survivin-deficient animals showed induced phosphorylation of p53 and H2AX and increased levels of cell-intrinsic apoptosis in IECs. Consequently, induced deletion of Survivin in Lgr5(+) stem cells led to cell death. In summary, Survivin is a key regulator of gut tissue integrity by regulating epithelial homeostasis in the stem cell niche.
EVALuna2:2058

Loss of the collagen IV modifier prolyl 3-hydroxylase 2 causes thin basement membrane nephropathy - Aypek, Hande; Krisp, Christoph; Lu, Shun; Liu, Shuya; Kylies, Dominik; Kretz, Oliver; Wu, Guochao; Moritz, Manuela; Amann, Kerstin Ute; Benz, Kerstin; Tong, Ping; Hu, Zheng Mao; et al. (Journal of Clinical Investigation, 2022)
The glomerular filtration barrier (GFB) produces primary urine and is composed of a fenestrated endothelium, a glomerular basement membrane (GBM), podocytes, and a slit diaphragm. Impairment of the GFB leads to albuminuria and microhematuria. The GBM is generated via secreted proteins from both endothelial cells and podocytes and is supposed to majorly contribute to filtration selectivity. While genetic mutations or variations of GBM components have been recently proposed to be a common cause of glomerular diseases, pathways modifying and stabilizing the GBM remain incompletely understood. Here, we identified prolyl 3-hydroxylase 2 (P3H2) as a regulator of the GBM in an a cohort of patients with albuminuria. P3H2 hydroxylates the 3′ of prolines in collagen IV subchains in the endoplasmic reticulum. Characterization of a P3h2ΔPod mouse line revealed that the absence of P3H2 protein in podocytes induced a thin basement membrane nephropathy (TBMN) phenotype with a thinner GBM than that in WT mice and the development of microhematuria and microalbuminuria over time. Mechanistically, differential quantitative proteomics of the GBM identified a significant decrease in the abundance of collagen IV subchains and their interaction partners in P3h2ΔPod mice. To our knowledge, P3H2 protein is the first identified GBM modifier, and loss or mutation of P3H2 causes TBMN and focal segmental glomerulosclerosis in mice and humans.
CRIS-Team Scopus Importer:2022-05-20

Low Dietary Fiber Intake Links Development of Obesity and Lupus Pathogenesis - Schaefer, Anna-Lena; Eichhorst, Alexandra; Hentze, Carolin; Kraemer, Antoine N. N.; Amend, Anais; Sprenger, Dalina T. L.; Fluhr, Cara; Finzel, Stephanie; Daniel, Christoph; Salzer, Ulrich; Rizzi, Marta; Voll, Reinhard E.; et al. (Frontiers in Immunology, 2021)
Changed dietary habits in Western countries such as reduced fiber intake represent an important lifestyle factor contributing to the increase in inflammatory immune-mediated diseases. The mode of action of beneficial fiber effects is not fully elucidated, but short-chain fatty acids (SCFA) and gut microbiota have been implicated. The aim of this study was to explore the impact of dietary fiber on lupus pathology and to understand underlying mechanisms. Here, we show that in lupus-prone NZB/WF1 mice low fiber intake deteriorates disease progression reflected in accelerated mortality, autoantibody production and immune dysregulation. In contrast to our original assumption, microbiota suppression by antibiotics or direct SCFA feeding did not influence the course of lupus-like disease. Mechanistically, our data rather indicate that in low fiber-fed mice, an increase in white adipose tissue mass, fat-inflammation and a disrupted intestinal homeostasis go along with systemic, low-grade inflammation driving autoimmunity. The links between obesity, intestinal leakage and low-grade inflammation were confirmed in human samples, while adaptive immune activation predominantly correlated with lupus activity. We further propose that an accelerated gastro-intestinal passage along with energy dilution underlies fiber-mediated weight regulation. Thus, our data highlight the often-overlooked effects of dietary fiber on energy homeostasis and obesity prevention. Further, they provide insight into how intricately the pathologies of inflammatory immune-mediated conditions, such as obesity and autoimmunity, might be interlinked, possibly sharing common pathways.
CRIS-Team WoS Importer:2021-08-13

Low dietary fiber intake links development of obesity and lupus pathogenesis - Schaefer, A. L.; Eichhorst, A.; Hentze, C.; Kraemer, A. N.; Amend, A.; Sprenger, D. T. L.; Fluhr, C.; Finzel, S.; Daniel, Christoph; Salzer, U.; Rizzi, M.; Voll, R. E.; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-02-17

L Particles Transmit Viral Proteins from Herpes Simplex Virus 1-Infected Mature Dendritic Cells to Uninfected Bystander Cells, Inducing CD83 Downmodulation - Heilingloh, Christiane; Kummer, Mirko; Muehl-Zuerbes, Petra; Drassner, Christina; Daniel, Christoph; Klewer, Monika; Steinkasserer, Alexander (Journal of Virology, 2015)
Mature dendritic cells (mDCs) are known as the most potent antigen-presenting cells (APCs) since they are also able to prime/induce naive T cells. Thus, mDCs play a pivotal role during the induction of antiviral immune responses. Remarkably, the cell surface molecule CD83, which was shown to have costimulatory properties, is targeted by herpes simplex virus 1 (HSV-1) for viral immune escape. Infection of mDCs with HSV-1 results in downmodulation of CD83, resulting in reduced T cell stimulation. In this study, we report that not only infected mDCs but also uninfected bystander cells in an infected culture show a significant CD83 reduction. We demonstrate that this effect is independent of phagocytosis and transmissible from infected to uninfected mDCs. The presence of specific viral proteins found in these uninfected bystander cells led to the hypothesis that viral proteins are transferred from infected to uninfected cells via L particles. These L particles are generated during lytic replication in parallel with full virions, called H particles. L particles contain viral proteins but lack the viral capsid and DNA. Therefore, these particles are not infectious but are able to transfer several viral proteins. Incubation of mDCs with L particles indeed reduced CD83 expression on uninfected bystander DCs, providing for the first time evidence that functional viral proteins are transmitted via L particles from infected mDCs to uninfected bystander cells, thereby inducing CD83 downmodulation.HSV-1 has evolved a number of strategies to evade the host's immune system. Among others, HSV-1 infection of mDCs results in an inhibited T cell activation caused by degradation of CD83. Interestingly, CD83 is lost not only from HSV-1-infected mDCs but also from uninfected bystander cells. The release of so-called L particles, which contain several viral proteins but lack capsid and DNA, during infection is a common phenomenon observed among several viruses, such as human cytomegalovirus (HCMV), Epstein-Barr virus, and HSV-1. However, the detailed function of these particles is poorly understood. Here, we provide for the first time evidence that functional viral proteins can be transferred to uninfected bystander mDCs via L particles, revealing important biological functions of these particles during lytic replication. Therefore, the transfer of viral proteins by L particles to modulate uninfected bystander cells may represent an additional strategy for viral immune escape.
EVALuna2:19522

Lysine methyltransferase Smyd2 suppresses p53-dependent cardiomyocyte apoptosis - Sajjad, Amna; Novoyatleva, Tatyana; Vergarajauregui, Silvia; Troidl, Christian; Schermuly, Ralph T.; Tucker, Haley O.; Engel, Felix (Biochimica Et Biophysica Acta-Molecular Cell Research, 2014)
Apoptosis, or programmed cell death, is an essential physiological process for proper embryogenesis as well as for homeostasis during aging. In addition, apoptosis is one of the major mechanisms causing cell loss in pathophysiological conditions such as heart failure. Thus, inhibition of apoptosis is an important approach for preventive and therapeutic strategies. Here we show that the histone 3 lysine 4- and lysine 36-specific methyltransferase Smyd2 acts as an endogenous antagonistic player of p53-dependent cardiomyocyte apoptosis. Smyd2 protein levels were significantly decreased in cardiomyocytes upon cobalt chloride-induced apoptosis or myocardial infarction, while p53 expression was enhanced. siRNA-mediated knockdown of Smyd2 in cultured cardiomyocytes further enhanced cobalt chloride-induced cardiomyocyte apoptosis. In contrast, Smyd2 overexpression resulted in marked methylation of p53 and prevented its accumulation as well as apoptotic cell death in an Hsp90-independent manner. Moreover, overexpression, of Smyd2, but not Smyd2Y240F lacking a methyl transferase activity, significantly rescued CoCl2-induced apoptosis in H9c2 cardioblasts. Finally, Smyd2 cardiomyocyte-specific deletion in vivo promoted apoptotic cell death upon myocardial infarction, which correlated with enhanced expression of p53 and pro-apoptotic Bax. Collectively, our data indicate Smyd2 as a cardioprotective protein by methylating p53.
EVALuna2:25466

Machine Learning-Supported Diagnosis of Small Blue Round Cell Sarcomas Using Targeted RNA Sequencing. - Schlieben, Lea D.; Carta, Maria Giulia; Moskalev, Evgeny; Stöhr, Robert; Metzler, Markus; Besendörfer, Manuel; Meidenbauer, Norbert; Semrau, Sabine; Janka, Rolf Matthias; Grützmann, Robert; Wiemann, Stefan; Hartmann, Arndt; et al. (Journal of Molecular Diagnostics, 2024)
Small blue round cell sarcomas (SBRCSs) are a heterogeneous group of tumors with overlapping morphologic features but markedly varying prognosis. They are characterized by distinct chromosomal alterations, particularly rearrangements leading to gene fusions, whose detection currently represents the most reliable diagnostic marker. Ewing sarcomas are the most common SBRCSs, defined by gene fusions involving EWSR1 and transcription factors of the ETS family, and the most frequent non-EWSR1-rearranged SBRCSs harbor a CIC rearrangement. Unfortunately, currently the identification of CIC::DUX4 translocation events, the most common CIC rearrangement, is challenging. Here, we present a machine-learning approach to support SBRCS diagnosis that relies on gene expression profiles measured via targeted sequencing. The analyses on a curated cohort of 69 soft-tissue tumors showed markedly distinct expression patterns for SBRCS subgroups. A random forest classifier trained on Ewing sarcoma and CIC-rearranged cases predicted probabilities of being CIC-rearranged >0.9 for CIC-rearranged-like sarcomas and <0.6 for other SBRCSs. Testing on a retrospective cohort of 1335 routine diagnostic cases identified 15 candidate CIC-rearranged tumors with a probability >0.75, all of which were supported by expert histopathologic reassessment. Furthermore, the multigene random forest classifier appeared advantageous over using high ETV4 expression alone, previously proposed as a surrogate to identify CIC rearrangement. Taken together, the expression-based classifier can offer valuable support for SBRCS pathologic diagnosis.
EVALuna2:565265

Macrophage and osteoclast polarization in bisphosphonate associated necrosis and osteoradionecrosis - Wehrhan, Falk; Möbius, Patrick; Amann, Kerstin Ute; Ries, Jutta; Preidl, Raimund; Neukam, Friedrich Wilhelm; Weber, Manuel (Journal of Cranio-Maxillofacial Surgery, 2017)
Bisphosphonate-related osteonecrosis of the jaw (BRONJ) is a complication of antiresorptive therapy with nitrogen-containing bisphosphonates (BP). With various suggestions as to pathogenesis, the etiology of BRONJ is not sufficiently understood. Osteoclasts and their precursors, that is, macrophages, are the main target cells of BP. BP can repolarize regeneration- and healing-associated M2 macrophages towards the tissue destructive M1-type. The current study aims to elucidate differences in macrophage and osteoclast polarization in BRONJ, osteoradionecrosis (ORN) and healthy control specimens.A total of 39 jaw bone samples (18 BRONJ, 8 ORN and 13 healthy controls) were processed for immunohistochemistry to detect CD68-, CD11c- and CD163-positive cells. Macrophages and osteoclasts were distinguished on the basis of morphological differences. Samples were digitized, and the macrophage and osteoclast cell counts were quantitatively analyzed.In jaw bone affected by BRONJ, a significantly increased macrophage infiltration and M1 polarization of macrophages can be seen. The density of CD68-expressing osteoclasts is significantly increased in BRONJ specimens compared to ORN and to healthy controls.A bisphosphonate-derived shift of macrophage polarization towards M1-polarized macrophages might impair bone tissue homeostasis and thus contribute to the pathogenesis of BRONJ. The observed increase in osteoclast density might be caused by BP-induced prolonged osteoclast survival.
EVALuna2:24431

Macrophage-Induced Pro-Fibrotic Gene Expression in Tubular Cells after Ischemia/Reperfusion Is Paralleled but Not Directly Mediated by C5a/C5aR1 Signaling - Bleich, Erik; Vonbrunn, Eva; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Life, 2024)
Ischemia/reperfusion (I/R) is inevitable during kidney transplantation and causes acute kidney injury (AKI), which affects immediate outcome and leads to chronic changes such as fibrotic remodeling of the graft. We investigated pro-fibrotic signaling after I/R, focusing on the complement component and receptor C5a/C5aR1 and macrophage/tubule crosstalk. Male Dark Agouti rats were subjected to I/R and their kidneys were harvested 10 min, 6 h, 24 h, 3 days, 5 days and 8 weeks after reperfusion. The development of renal fibrosis was assessed by the detection of Vimentin (VIM), α-smooth muscle actin (α-SMA) and collagen by immunohistochemistry and Sirius Red staining, respectively. The characterization of C5a/C5aR1 activity and C5aR1+ cells was performed by multiplex mRNA analysis, ELISA, immunofluorescence flow cytometry and in situ hybridization in animal models and cell culture analyses. In the cell culture experiments, we focused on macrophage/tubule cell crosstalk in co-culture experiments and mimicked in vivo conditions by hypoxia/reoxygenation and supplementation with C5a. Already 6–24 h after the induction of I/R in the rat model, C5a concentration in the plasma was significantly increased compared to the control. The matrix components VIM and α-SMA peaked on day 5 and declined after 8 weeks, when an increase in collagen was detected using Sirius Red. In contrast to early I/R-induced C5a activation, renal C5ar1 expression was maximal at day 5 and C5 expression increased until week 8, indicating that the renal upregulation of expression is not required for early complement activation. C5aR1 mRNA was detected in neutrophils and macrophages, but not in proximal tubular cells in the injured kidneys. The macrophage/tubular cell co-culture experiments showed that macrophages were mainly responsible for the increased expression of fibrosis-associated genes in tubule cells (ACTA2, VIM, SNAI1, TGFB1 and FGF-2), and hypoxia/reoxygenation had a partially enhancing effect. A direct pro-fibrotic effect of C5a was not observed. Increased TGF-ß levels were dependent on the differentiation of macrophages to the M2 subtype. In conclusion, the early activation of mesenchymal markers in tubular epithelial cells leads to long-term fibrotic remodeling characterized by VIM expression and driven by TGF-ß-dependent macrophage/tubular crosstalk. The chemoattractive properties of complement C5a may contribute to the recruitment of pro-fibrotic macrophages.
CRIS-Team Scopus Importer:2024-09-06
Keywords: complement C5a; fibrosis; ischemia/reperfusion; macrophage/tubular crosstalk

Macrophage polarisation changes within the time between diagnostic biopsy and tumour resection in oral squamous cell carcinomas-an immunohistochemical study - Weber, Manuel; Moebius, P.; Büttner-Herold, M.; Amann, Kerstin Ute; Preidl, Raimund; Neukam, Friedrich Wilhelm; Wehrhan, Falk (British Journal of Cancer, 2015)
The prognosis of solid malignancies has been shown to depend on immunological parameters, such as macrophage polarisation (M1/M2). Recently, it was reported that preoperative oral surgery leads to a worsening of oral squamous cell carcinomas (OSCC) prognosis. Diagnostic incision biopsies are oral surgery procedures that might lead to healing-associated M2 macrophage polarisation with a potential negative influence on tumour biology. No studies have compared macrophage polarisation in OSCC biopsies and tumour specimens.Preoperative diagnostic incision biopsies (n=25) and tumour resection specimens (n=34) of T1/T2 OSCC were processed for immunohistochemistry to detect CD68-, CD11c-, CD163- and MRC1-positive cells. Samples were digitised using whole-slide imaging, and the expression of macrophage markers was quantitatively analysed.Carcinoma tissues obtained during OSCC tumour resections showed a significantly (P<0.05) increased CD163 cell count (M2 macrophages) compared with tissues obtained during preoperative incision biopsies. Additionally, the CD163/CD68 ratio (an indicator of M2 polarisation) was significantly (P<0.05) higher in tumour resection specimens than in biopsies.This study revealed for the first time an increase in M2 polarisation in samples obtained during OSCC tumour resection surgery compared with preoperative incision biopsies. The biopsy-induced tissue trauma might explain the observed shift in macrophage polarisation towards the tumour-promoting M2 type and could lead to accelerated tumour progression.
EVALuna2:24401

Macrophages and dendritic cells as actors in the immune reaction of classical hodgkin lymphoma - Tudor, Christiane; Bruns, Heiko; Daniel, Christoph; Distel, Luitpold; Hartmann, Arndt; Gerbitz, Armin; Büttner, Maike (PLoS ONE, 2014)
The inflammatory infiltrate plays a pivotal role in classical Hodgkin lymphoma (cHL). Here, we focussed on the role of macrophages (M?) and dendritic cells (DC).M? and DC infiltration was investigated in 106 cHL specimens using immunohistochemistry and cytokine expression was analyzed in a subset by real-time PCR. Human peripheral blood-derived monocytes, DC, M? stimulated with GM-CSF (M?GM-CSF, pro-inflammatory M?-1-model) or M-CSF (M?M-CSF, immunomodulatory M?-2-model) were incubated with cHL cell line (L1236, HDLM2) supernatants (SN). DC maturation or M? polarization were investigated by flow cytometry. Furthermore, the impact of DC or M? on cHL cell proliferation was analyzed by BrdU/CFSE assay.In cHL tissues mature myeloid (m)DC and M? predominated. High numbers of CD83+ mDC and low numbers of CD163+ M? were associated with improved disease specific survival. In numerous cHL specimens increased levels of both pro- and anti-inflammatory cytokines and of IL13 and GM-CSF were observed compared to reactive lymphadenopathies. Maturation of DC and induction and maintenance of an immunomodulatory M? phenotype were promoted by SN derived from cHL cell lines. TNF? neutralization in SN resulted in a significant inhibition of mDC maturation. DC and pro-inflammatory M? inhibited the proliferation of cHL cells.Adopting an immunomodulatory phenotype is a potential mechanism for how M? promote immune evasion in cHL. Mature DC, in contrast, might participate in antitumoral immunit
EVALuna2:6630

Macrophages inhibit Coxiella burnetii by the ACOD1-itaconate pathway for containment of Q fever - Kohl, Lisa; Siddique, Md Nur A Alam; Bodendorfer, Barbara; Berger, Raffaela; Preikschat, Annica; Daniel, Christoph; Ölke, Martha; Liebler-Tenorio, Elisabeth; Schulze-Lührmann, Jan; Mauermeir, Michael; Yang, Kai-Ting; Hayek, Inaya; et al. (Embo Molecular Medicine, 2022)
Infection with the intracellular bacterium Coxiella (C.) burnetii can cause chronic Q fever with severe complications and limited treatment options. Here, we identify the enzyme cis-aconitate decarboxylase 1 (ACOD1 or IRG1) and its product itaconate as protective host immune pathway in Q fever. Infection of mice with C. burnetii induced expression of several anti-microbial candidate genes, including Acod1. In macrophages, Acod1 was essential for restricting C. burnetii replication, while other antimicrobial pathways were dispensable. Intratracheal or intraperitoneal infection of Acod1−/− mice caused increased C. burnetii burden, weight loss and stronger inflammatory gene expression. Exogenously added itaconate restored pathogen control in Acod1−/− mouse macrophages and blocked replication in human macrophages. In axenic cultures, itaconate directly inhibited growth of C. burnetii. Finally, treatment of infected Acod1−/− mice with itaconate efficiently reduced the tissue pathogen load. Thus, ACOD1-derived itaconate is a key factor in the macrophage-mediated defense against C. burnetii and may be exploited for novel therapeutic approaches in chronic Q fever.
CRIS-Team Scopus Importer:2022-12-16
Keywords: Cis-aconitate decarboxylase 1; Coxiella burnetii; Immune responsive gene 1; immunometabolism; itaconate

Macrophage subpopulations in pediatric patients with lupus nephritis and other inflammatory diseases affecting the kidney. - Sandersfeld, Mira; Büttner-Herold, Maike; Ferrazzi, Fulvia; Amann, Kerstin Ute; Benz, Kerstin; Daniel, Christoph (Arthritis Research & Therapy, 2024)
BACKGROUND: Macrophages play an important role in the pathogenesis of lupus nephritis (LN), but less is known about macrophage subtypes in pediatric LN. Here we compared renal inflammation in LN with other inflammatory pediatric kidney diseases and assessed whether inflammation correlates with clinical parameters. METHODS: Using immunofluorescence microscopy, we analyzed renal biopsies from 20 pediatric patients with lupus nephritis (ISN/RPS classes II-V) and pediatric controls with other inflammatory kidney diseases for infiltration with M1-like (CD68 + /CD206 - , CD68 + /CD163 -), M2a-like (CD206 + /CD68 +), and M2c-like macrophages (CD163 + /CD68 +) as well as CD3 + T-cells, CD20 + B-cells, and MPO + neutrophilic granulocytes. In addition, the correlation of macrophage infiltration with clinical parameters at the time of renal biopsy, e.g., eGFR and serum urea, was investigated. Macrophage subpopulations were compared with data from a former study of adult LN patients. RESULTS: The frequency of different macrophage subtypes in biopsies of pediatric LN was dependent on ISN/RPS class and showed the most pronounced M1-like macrophage infiltration in patients with LN class IV, whereas M2c-like macrophages were most abundant in class III and IV. Interestingly, on average, only half as many macrophages were found in renal biopsies of pediatric LN compared to adult patients with LN. The distribution of frequencies of macrophage subpopulations, however, was different for CD68 + CD206 + (M2a-like) but comparable for CD68 + CD163 - (M1-like) CD68 + CD163 + (M2c-like) cells in pediatric and adult patients. Compared to other inflammatory kidney diseases in children, fewer macrophages and other inflammatory cells were found in kidney biopsies of LN. Depending on the disease, the frequency of individual immune cell types varied, but we were unable to confirm disease-specific inflammatory signatures in our study due to the small number of pediatric cases. Worsened renal function, measured as elevated serum urea and decreased eGFR, correlated particularly strongly with the number of CD68 + /CD163 - M1-like macrophages and CD20 + B cells in pediatric inflammatory kidney disease. CONCLUSION: Although M1-like macrophages play a greater role in pediatric LN patients than in adult LN patients, M2-like macrophages appear to be key players and are more abundant in other pediatric inflammatory kidney diseases compared to LN.
EVALuna2:552742

Management of spontaneous enophthalmos due to silent sinus syndrome: a case report - Nkenke, Emeka; Alexiou, Christoph; Iro, Heinrich; Amann, Kerstin Ute; Kirchner, Thomas; Häusler, Gerd; Neukam, Friedrich Wilhelm; Holbach, Benedict (International Journal of Oral and Maxillofacial Surgery, 2005)
UnivIS-Import:2015-04-14:Pub.2005.nat.dphy.optik.1optik.manage

Marine alkaloid Monanchocidin a overcomes drug resistance by induction of autophagy and lysosomal membrane permeabilization - Dyshlovoy, Sergey A.; Hauschild, Jessica; Amann, Kerstin Ute; Tabakmakher, Ksenia M.; Venz, Simone; Walther, Reinhard; Guzii, Alla G.; Makarieva, Tatiana N.; Shubina, Larisa K.; Fedorov, Sergey N.; Stonik, Valentin A.; Bokemeyer, Carsten; et al. (Oncotarget, 2015)
Monanchocidin A (MonA) is a novel alkaloid recently isolated from the marine sponge Monanchora pulchra. The compound reveals cytotoxic activity in genitourinary cancers including cisplatin-sensitive and -resistant germ cell tumor (GCT) cell lines, hormone-sensitive and castration-resistant prostate carcinoma cell lines and different bladder carcinoma cell lines. In contrast, non-malignant cells were significantly less sensitive. MonA is highly synergistic with cisplatin in GCT cells. Induction of autophagy at lower and lysosomal membrane permeabilization (LMP) at higher concentrations were identified as the dominating modes of action. Cytotoxicity and protein degradation could be inhibited by 3-methyladenine, an inhibitor of autophagy. LMP was confirmed by loss of acridine orange staining of lysosoms and by release of cathepsin B. In conclusion, MonA exerts cytotoxic activity by mechanisms different from "classical" apoptosis, and could be a promising new compound to overcome resistance to standard therapies in genitourinary malignancies.
EVALuna2:25492

Marine compound rhizochalinin shows high in vitro and in vivo efficacy in castration resistant prostate cancer - Dyshlovoy, Sergey A.; Otte, Katharina; Alsdorf, Winfried H.; Hauschild, Jessica; Lange, Tobias; Venz, Simone; Bauer, Christiane K.; Baehring, Robert; Amann, Kerstin Ute; Mandanchi, Ramin; Schumacher, Udo; Schroeder-Schwarz, Jennifer; et al. (Oncotarget, 2016)
Development of drug resistance is an inevitable phenomenon in castration-resistant prostate cancer (CRPC) cells requiring novel therapeutic approaches. In this study, efficacy and toxicity of Rhizochalinin (Rhiz) - a novel sphingolipid-like marine compound - was evaluated in prostate cancer models, resistant to currently approved standard therapies. In vitro activity and mechanism of action of Rhiz were examined in the human prostate cancer cell lines PC-3, DU145, LNCaP, 22Rv1, and VCaP. Rhiz significantly reduced cell viability at low micromolar concentrations showing most pronounced effects in enzalutamide and abiraterone resistant AR-V7 positive cells. Caspase-dependent apoptosis, inhibition of pro-survival autophagy, downregulation of AR-V7, PSA and IGF-1 expression as well as inhibition of voltage-gated potassium channels were identified as mechanisms of action. Remarkably, Rhiz re-sensitized AR-V7 positive cells to enzalutamide and increased efficacy of taxanes.In vivo activity and toxicity were evaluated in PC-3 and 22Rv1 NOD SCID mouse xenograft models using i.p. administration. Rhiz significantly reduced growth of PC-3 and 22Rv1 tumor xenografts by 27.0% (p = 0.0156) and 46.8% (p = 0.047) compared with controls with an increased fraction of tumor cells showing apoptosis secondary to Rhiz exposure. In line with the in vitro data, Rhiz was most active in AR-V7 positive xenografts in vivo. In animals, no severe side effects were observed.In conclusion, Rhiz is a promising novel marine-derived compound characterized by a unique combination of anticancer properties. Its further clinical development is of high impact for patients suffering from drug resistant prostate cancer especially those harboring AR-V7 mediated resistance to enzalutamide and abiraterone.
EVALuna2:25524

Mechanisms of everolimus‐induced glomerulosclerosis after glomerular injury in the rat - Daniel, Christoph; Renders, L.; Amann, Kerstin Ute; Schulze-Lohoff, Eckhard; Hauser, Ingeborg A.; Hugo, Christian (American Journal of Transplantation, 2005)
Despite the lack of nephrotoxicity, adverse effects of the new antiproliferative immunosuppressant everolimus have been reported. By varying time point and dose of everolimus treatment as well as the degree of glomerular injury, the specific conditions and potential mechanisms leading to adverse actions in the anti-Thy1 model have been determined. Only the combination of early and high-dose everolimus treatment (1-3 mg/kg bw) with a severe glomerular lesion ('full-dose' anti-Thy1 model) caused adverse effects with a high mortality rate, progressive apoptosis, crescent formation and glomerulosclerosis. In contrast, either later start or low-dose (0.3 mg/kg bw) therapy or treatment of a less severe lesion ('reduced dose' anti-Thy1 model) appeared to be relatively safe for the glomerular architecture. The adverse effects of everolimus were linked to its marked inhibition of endothelial cell, but not necessarily mesangial cell proliferation. In addition, everolimus markedly inhibited the angiogenic cytokine vascular endothelial growth factor in nephritic glomeruli in vivo. These experimental results suggest special caution regarding the use of everolimus in all situations of severe glomerular cell injury requiring extensive capillary repair, where at least adaption to a low dose needs to be considered. Copyright © Blackwell Munksgaard 2005.
Created from Fastlane, Scopus look-up
Keywords: Anti-Thy1 model; Glomerular endothelial cell proliferation; Glomerular regeneration; Rapamycin derivative everolimus; Renal microvascular injury

Mechanisms of pathogenicity and the quest for genetic modifiers of kidney disease in branchiootorenal syndrome - Sewerin, Sebastian; Aurnhammer, Charlotte; Skubic, Cene; Cokan, Kaja Blagotinšek; Jeruc, Jera; Rozman, Damjana; Pfister, Frederick; Dittrich, Katalin; Mayer, Brigitte; Schönauer, Ria; Petzold, Friederike; Halbritter, Jan (Clinical Kidney Journal, 2024)
Backgound. Branchiootorenal (BOR) syndrome is an autosomal dominant disorder caused by pathogenic EYA1 variants and clinically characterized by auricular malformations with hearing loss, branchial arch anomalies, and congenital anomalies of the kidney and urinary tract. BOR phenotypes are highly variable and heterogenous. While random monoallelic expression is assumed to explain this phenotypic heterogeneity, the potential role of modifier genes has not yet been explored. Methods. Through thorough phenotyping and exome sequencing, we studied one family with disease presentation in at least four generations in both clinical and genetic terms. Functional investigation of the single associated EYA1 variant c.1698+1G>A included splice site analysis and assessment of EYA1 distribution in patient-derived fibroblasts. The candidate modifier gene CYP51A1 was evaluated by histopathological analysis of murine Cyp51+/− and Cyp51−/− kidneys. As the gene encodes the enzyme lanosterol 14α-demethylase, we assessed sterol intermediates in patient blood samples as well. Results. The EYA1 variant c.1698+1G>A resulted in functional deletion of the EYA domain by exon skipping. The EYA domain mediates protein-protein interactions between EYA1 and co-regulators of transcription. EYA1 abundance was reduced in the nuclear compartment of patient-derived fibroblasts, suggesting impaired nuclear translocation of these protein complexes. Within the affected family, renal phenotypes spanned from normal kidney function in adulthood to chronic kidney failure in infancy. By analyzing exome sequencing data for variants that potentially play roles as genetic modifiers, we identified a canonical splice site alteration in CYP51A1 as the strongest candidate variant. Conclusion. In this study, we demonstrate pathogenicity of EYA1 c.1698+1G>A, propose a mechanism for dysfunction of mutant EYA1, and conjecture CYP51A1 as a potential genetic modifier of renal involvement in BOR syndrome.
CRIS-Team Scopus Importer:2024-01-26
Keywords: branchiootorenal syndrome; chronic kidney disease; modifier genes; patient-derived fibroblasts; phenotypic heterogeneity

Melatonin as a cardioprotective therapy following ST-segment elevation myocardial infarction: is it really promising? Reply - Hausenloy, Derek J.; Garcia-Dorado, David; Botker, Hans Erik; Davidson, Sean M.; Downey, James; Engel, Felix; Jennings, Robert; Lecour, Sandrine; Leor, Jonathan; Madonna, Rosalinda; Ovize, Michel; Perrino, Cinzia; et al. (Cardiovascular Research, 2017)
EVALuna2:25553

Membranoproliferative glomerulonephritis and C3 glomerulopathy - Hohenstein, B.; Amann, Kerstin Ute; Menne, J. (Internist, 2019)
Based on an increasingly better pathophysiological understanding over the last 10 years, in 2010 a new classification of glomerulonephritis with dominant or codominant C3 deposits was introduced and the predominant subgoup was termed C3 glomerulopathy (C3G). In the current classification, immune complex mediated membranoproliferative glomerulonephritis (IC-MPGN) and C3 glomerulopathy (C3G) form a disease spectrum which is very heterogeneous in terms of pathophysiology and the clinical course. Recent evidence suggests that IC-MPGN and C3G share more pathophysiological aspects with respect to secondary causes, autoantibodies and genetic aspects than had been suggested with the creation of the new classification. Knowledge of the underlying pathophysiology is important for guiding the diagnostic steps for clarification of secondary causes. Comprehensive complement analysis, accompanied by antibody screening and genetic analysis, should be consistently carried out. Although not systematically validated in clinical trials, the published evidence provides a robust foundation for the use of available treatment approaches for these diseases that are often rapidly progressive and often return after renal transplantation.
EVALuna2:102223

Mesenteric Lymph Node Transplantation in Mice to Study Immune Responses of the Gastrointestinal Tract - Shaikh, Haroon; Vargas, Juan Gamboa; Mokhtari, Zeinab; Jarick, Katja J.; Ulbrich, Maria; Mosca, Josefina Pena; Viera, Estibaliz Arellano; Graf, Caroline; Le, Duc-Dung; Heinze, Katrin G.; Büttner-Herold, Maike; Rosenwald, Andreas; et al. (Frontiers in Immunology, 2021)
Mesenteric lymph nodes (mLNs) are sentinel sites of enteral immunosurveillance and immune homeostasis. Immune cells from the gastrointestinal tract (GIT) are constantly recruited to the mLNs in steady-state and under inflammatory conditions resulting in the induction of tolerance and immune cells activation, respectively. Surgical dissection and transplantation of lymph nodes (LN) is a technique that has supported seminal work to study LN function and is useful to investigate resident stromal and endothelial cell biology and their cellular interactions in experimental disease models. Here, we provide a detailed protocol of syngeneic mLN transplantation and report assays to analyze effective mLN engraftment in congenic recipients. Transplanted mLNs allow to study T cell activation and proliferation in preclinical mouse models. Donor mLNs proved viable and functional after surgical transplantation and regenerated blood and lymphatic vessels. Immune cells from the host completely colonized the transplanted mLNs within 7-8 weeks after the surgical intervention. After allogeneic hematopoietic cell transplantation (allo-HCT), adoptively transferred allogeneic CD4+ T cells from FVB/N (H-2q) mice homed to the transplanted mLNs in C57BL/6 (H-2b) recipients during the initiation phase of acute graft-versus-host disease (aGvHD). These CD4+ T cells retained full proliferative capacity and upregulated effector and gut homing molecules comparable to those in mLNs from unmanipulated wild-type recipients. Wild type mLNs transplanted into MHCII deficient syngeneic hosts sufficed to activate alloreactive T cells upon allogeneic hematopoietic cell transplantation, even in the absence of MHCII+ CD11c+ myeloid cells. These data support that orthotopically transplanted mLNs maintain physiological functions after transplantation. The technique of LN transplantation can be applied to study migratory and resident cell compartment interactions in mLNs as well as immune reactions from and to the gut under inflammatory and non-inflammatory conditions.
CRIS-Team Scopus Importer:2021-08-20
Keywords: acute graft-versus host disease; alloreactive T cells; lymph node stromal cells; lymph node transplantation; mesenteric lymph node; mouse models

Microfluidically fabricated fibers containing pancreatic islets and mesenchymal stromal cells improve longevity and sustained normoglycemia in diabetic rats - Navaei-Nigjeh, Mona; Mirzababaei, Soheyl; Ghiass, Mohammad Adel; Roshanbinfar, Kaveh; Gholami, Mahdi; Abdollahi, Mohammad (Biofabrication, 2022)
Type 1 diabetes mellitus is an autoimmune disease characterized by the loss of pancreatic isletβcells. Insulin injections and pancreas transplants are currently available therapies. The former requires daily insulin injections, while the latter is constrained by donor organ availability. Islet transplantation is a promising alternative treatment for type 1 diabetes mellitus that may overcome the limitations of previous techniques. Two challenges, however, must be addressed: limited cell retention as a result of the immune response and limited function of the transplanted cells that survive. To address these problems, we developed a microfluidic technology for a one-step generation of islet-laden fibers to protect them from the immune response. This approach enables continuous generation of microfibers with a diameter suitable for islet encapsulation (275µm). We, then, transplanted islet-laden fibers into diabetic Wistar rats. While islet-laden fibers alone were unable to restore normoglycemia in diabetic rats, adding mesenchymal stromal cells (MSCs) restored normoglycemia for an extended time. It increased the animals' lifespan by up to 75 d. Additionally, it improved the glucose-stimulated response of islets to the point where there was no significant difference between the treatment group and the healthy animals. Additionally, the presence of MSCs suppressed the immune response, as seen by decreased levels of pro-inflammatory cytokines such as tumor necrosis factor-α. Taken together, these fibers including islet and MSCs provide a versatile platform for concurrently improving cell preservation and functioning followingin vivotransplantation.
CRIS-Team Scopus Importer:2022-12-16
Keywords: cell encapsulation; cell-laden fiber; diabetes; mesenchymal stromal cells; microfiber; microfluidics; pancreatic islet transplantation

Microtubule Organization in Striated Muscle Cells - Becker, Robert; Leone, Marina; Engel, Felix (Cells, 2020)
Distinctly organized microtubule networks contribute to the function of differentiated cell types such as neurons, epithelial cells, skeletal myotubes, and cardiomyocytes. In striated (i.e. skeletal and cardiac) muscle cells, the nuclear envelope acts as the dominant microtubule-organizing center (MTOC) and the function of the centrosome-the canonical MTOC of mammalian cells-is attenuated, a common feature of differentiated cell types. We summarize the mechanisms known to underlie MTOC formation at the nuclear envelope, discuss the significance of the nuclear envelope MTOC for muscle function and cell cycle progression, and outline potential mechanisms of centrosome attenuation.
CRIS-Team Scopus Importer:2020-06-16
Keywords: cardiomyocytes; cell cycle; centrosome; microtubules; MTOC; non-centrosomal MTOC; skeletal muscle

Mild Salt-Sensitive Hypertension in Genetically Determined Low Nephron Number is Associated with Chloride but Not Sodium Retention - Benz, Kerstin; Schlote, Julia; Daniel, Christoph; Kopp, Christoph; Dahlmann, Anke; Schröder, Agnes; Cordasic, Nada; Klanke, Bernd; Hilgers, Karl Friedrich; Titze, Jens; Amann, Kerstin Ute (Kidney & Blood Pressure Research, 2018)
BACKGROUND/AIMS: One potential pathomechanism how low nephron number leads to hypertension in later life is altered salt handling. We therefore evaluated changes in electrolyte and water content in wildtype (wt) and GDNF+/- mice with a 30% reduction of nephron number. METHODS: 32 GDNF+/- and 36 wt mice were fed with low salt (LSD, 0.03%, normal drinking water) or high salt (HSD, 4%, 0.9% drinking water) diet for 4 weeks. Blood pressure was continuously measured by telemetry in a subgroup. At the end of the experiment and after standardized ashing processes electrolyte- and water contents of the skin and the total body were determined. RESULTS: We found higher blood pressure in high salt treated GDNF+/-compared to wt mice. Of interest, we could not confirm an increase in total-body sodium as predicted by prevailing explanations, but found increased total body and skin chloride that interestingly correlated with relative kidney weight. CONCLUSION: We hereby firstly report significant total body and skin chloride retention in salt sensitive hypertension of GDNF+/-mice with genetically determined lower nephron number. Thus, in contrast to the prevailing opinion our data argue for the involvement of non-volume related mechanisms.
EVALuna2:34423

miR-27a/b is a posttranscriptional regulator of Gpr126 (Adgrg6) - Musa, Gentian; Srivastava, Swati; Petzold, Jana; Cazorla-Vazquez, Salvador; Engel, Felix (Annals of the New York Academy of Sciences, 2019)
Gpr126 (Adgrg6), a member of the adhesion G protein-coupled receptor family, has been associated with a variety of human diseases. Yet, despite its clinical importance, the mechanisms regulating Gpr126 expression are poorly understood. Here, we aimed at identifying upstream regulatory mechanisms of Gpr126 expression utilizing the heart as model organ in which Gpr126 regulates trabeculation. Here, we focused on possible regulation of Gpr126 regulation by microRNAs, which have emerged as key players in regulating development, have a critical role in disease progression, and might serve as putative therapeutic targets. In silico analyses identified one conserved binding site in the 3 ' UTR of Gpr126 for microRNA 27a and 27b (miR-27a/b). In addition, miR-27a/b and Gpr126 expression were differentially expressed during rat heart development. A regulatory role of miR-27a/b in controlling Gpr126 expression was substantiated by reduced Gpr126 mRNA levels upon ectopic expression of miR-27a/b in HEK293T cells and miR-27b in zebrafish embryos. Regulation of Gpr126 expression by direct binding of miR-27a/b to the 3 ' UTR of Gpr126 was verified by luciferase reporter assays in HEK293T cells. Finally, the modulation of gpr126 expression in zebrafish by injection of either miR-27b or miR-27b inhibitor in single cell-stage embryos resulted in hypo- or hypertrabeculation, respectively. Collectively, the data indicate that Gpr126 expression is regulated by miR-27a/b.
CRIS-Team WoS Importer:2019-10-22

Modeling Hemolytic-Uremic Syndrome: In-Depth Characterization of Distinct Murine Models Reflecting Different Features of Human Disease - Dennhardt, Sophie; Pirschel, Wiebke; Wissuwa, Bianka; Daniel, Christoph; Gunzer, Florian; Lindig, Sandro; Medyukhina, Anna; Kiehntopf, Michael; Rudolph, Wolfram W.; Zipfel, Peter F.; Gunzer, Matthias; Figge, Marc Thilo; et al. (Frontiers in Immunology, 2018)
Diarrhea-positive hemolytic-uremic syndrome (HUS) is a renal disorder that results from infections with Shiga-toxin (Stx)-producing Escherichia coli. The aim of this study was to establish well-defined refined murine models of HUS that can serve as preclinical tools to elucidate molecular mechanisms of disease development. C57BL/6J mice were subjected to different doses of Stx2 purified from an E. coli O157:H7 patient isolate. Animals received 300 ng/kg Stx2 and were sacrificed on day 3 to establish an acute model with fast disease progression. Alternatively, mice received 25 ng/kg Stx2 on days 0, 3, and 6, and were sacrificed on day 7 to establish a subacute model with moderate disease progression. Indicated by a rise in hematocrit, we observed dehydration despite volume substitution in both models, which was less pronounced in mice that underwent the 7-day regime. Compared with sham-treated animals, mice subjected to Stx2 developed profound weight loss, kidney dysfunction (elevation of plasma urea, creatinine, and neutrophil gelatinase-associated lipocalin), kidney injury (tubular injury and loss of endothelial cells), thrombotic microangiopathy (arteriolar microthrombi), and hemolysis (elevation of plasma bilirubin, lactate dehydrogenase, and free hemoglobin). The degree of complement activation (C3c deposition), immune cell invasion (macrophages and T lymphocytes), apoptosis, and proliferation were significantly increased in kidneys of mice subjected to the 7-day but not in kidneys of mice subjected to the 3-day regime. However, glomerular and kidney volume remained mainly unchanged, as assessed by 3D analysis of whole mount kidneys using CD31 staining with light sheet fluorescence microscopy. Gene expression analysis of kidneys revealed a total of only 91 overlapping genes altered in both Stx2 models. In conclusion, we have developed two refined mouse models with different disease progression, both leading to hemolysis, thrombotic microangiopathy, and acute kidney dysfunction and damage as key clinical features of human HUS. While intrarenal changes (apoptosis, proliferation, complement deposition, and immune cell invasion) mainly contribute to the pathophysiology of the subacute model, prerenal pathomechanisms (hypovolemia) play a predominant role in the acute model. Both models allow the further study of the pathomechanisms of most aspects of human HUS and the testing of distinct novel treatment strategies.
EVALuna2:34424

Molecular diagnosis of kidney transplant failure based on urine - Wiesener, Antje; Knaup, Karl; Büttner-Herold, Maike; Dieterle, Anne; Stoeckert, Johanna; Riedl, Bernhard; Morath, Christian; Wald, Alexandra; Vondran, Florian; Braun, Felix; Schödel, Johannes; Schüler, Markus; et al. (American Journal of Transplantation, 2020)
In light of the organ shortage, there is a great responsibility to assess postmortal organs for which procurement has been consented and to increase the life span of transplanted organs. The former responsibility has moved many centers to accept extended criteria organs. The latter responsibility requires an exact diagnosis and, if possible, omission of the harmful influence on the transplant. We report the course of a kidney transplant that showed a steady decline of function over a decade, displaying numerous cysts of different sizes. Clinical workup excluded the most frequent causes of chronic transplant failure. The filed allocation documents mentioned the donor's disease of oral-facial-digital syndrome, a rare ciliopathy, which can also affect the kidney. Molecular diagnosis was performed by culturing donor tubular cells from the recipient ' s urine more than 10 years after transplantation. Next-generation panel sequencing with DNA from tubular urinary cells revealed a novel truncating mutation in OFD1, which sufficiently explains the features of the kidney transplants, also found in the second kidney allograft. Despite this severe donor disease, lifesaving transplantation with good long-term outcome was enabled for 5 recipients.
CRIS-Team WoS Importer:2020-01-31

MOLECULAR DIAGNOSIS OF KIDNEY TRANSPLANT FAILURE BY THE URINE - Knaup, Karl; Wiesener, A.; Buettner-Herold, M.; Dieterle, A.; Morath, C.; Vondran, F. W. R.; Wald, A.; Braun, F.; Schüler, Markus; Schödel, Johannes; Schiffer, Mario; Reis, André; et al. (TRANSPLANT INTERNATIONAL, 2019)
CRIS-Team WoS Importer:2019-10-29

Molecular Subtyping of Invasive Breast Cancer Using a PAM50-Based Multigene Expression Test-Comparison with Molecular-Like Subtyping by Tumor Grade/Immunohistochemistry and Influence on Oncologist's Decision on Systemic Therapy in a Real-World Setting - Erber, Ramona; Angeloni, Miriam; Stöhr, Robert; Lux, Michael P.; Ulbrich-Gebauer, Daniel; Pelz, Enrico; Bankfalvi, Agnes; Schmid, Kurt W.; Walter, Robert F. H.; Vetter, Martina; Thomssen, Christoph; Mayr, Doris; et al. (International Journal of Molecular Sciences, 2022)
In intermediate risk hormone receptor (HR) positive, HER2 negative breast cancer (BC), the decision regarding adjuvant chemotherapy might be facilitated by multigene expression tests. In all, 142 intermediate risk BCs were investigated using the PAM50-based multigene expression test Prosigna (R) in a prospective multicentric study. In 119/142 cases, Prosigna (R) molecular subtyping was compared with local and two central (C1 and C6) molecular-like subtypes relying on both immunohistochemistry (IHC; HRs, HER2, Ki-67) and IHC + tumor grade (IHC+G) subtyping. According to local IHC, 35.4% were Luminal A-like and 64.6% Luminal B-like subtypes (local IHC+G subtype: 31.9% Luminal A-like; 68.1% Luminal B-like). In contrast to local and C1 subtyping, C6 classified >2/3 of cases as Luminal A-like. Pairwise agreement between Prosigna (R) subtyping and molecular-like subtypes was fair to moderate depending on molecular-like subtyping method and center. The best agreement was observed between Prosigna (R) (53.8% Luminal A; 44.5% Luminal B) and C1 surrogate subtyping (Cohen's kappa = 0.455). Adjuvant chemotherapy was suggested to 44.2% and 88.6% of Prosigna (R) Luminal A and Luminal B cases, respectively. Out of all Luminal A-like cases (locally IHC/IHC+G subtyping), adjuvant chemotherapy was recommended if Prosigna (R) testing classified as Prosigna (R) Luminal A at high / intermediate risk or upgraded to Prosigna (R) Luminal B.
CRIS-Team WoS Importer:2022-08-26

Molecular weight and molar substitution are more important in HES-induced renal impairment than concentration after hemorrhagic and septic shock - Simon, T P; Thiele, C; Schuerholz, T; Fries, M; Stadermann, F; Haase, G; Amann, Kerstin Ute; Marx, G (Minerva Anestesiologica, 2015)
Clinical studies have raised concerns about the safety of 6% hydroxyethylstarch (HES) 130/0.42, but the pathomechanisms of this renal impairment remain unknown. To evaluate the effects of different HES concentrations, molar substitutions and molecular weights in HES-induced renal impairment, we used a porcine two-hit model that combined haemorrhagic and septic shock.We conducted a prospective, randomised, double-blinded, controlled study in a university animal laboratory. Thirty anaesthetised and ventilated pigs were randomised to receive volume replacement therapy using 6% HES130/0.42, 6% HES200/0.5, 10% HES130/0.42 or 10% HES200/0.5, all dissolved in 0.9% NaCl rather than 0.9% NaCl alone. First, we bled the animals until they reached half of their baseline mean arterial pressure (MAP) for 45 minutes followed by fluid resuscitation. As a second hit, sepsis was induced using an Escherichia coli-laden clot 6 hours after haemorrhagic shock. Volume resuscitation started with a delay of two hours and a central venous pressure goal of 12 mmHg.At the end of the study, the groups showed no difference in cardiac output or MAP, but the volume balance (mL/kg BW) was significantly higher in the 0.9% NaCl group (346±90; P<=0.05) than in the other groups (6% HES130, 125±26; 6% HES200, 105±15; 10% HES130, 114±17; 10% HES200, 96±23). Creatinine clearance (mL/min) was significantly lower in the 6% HES200 (26±33) and 10% HES200 (15±18) groups compared to the 0.9% NaCl group (104±46; P<=0.05) but not in the HES 130 formulations (6% HES130: 64±51; 10% HES130: 58±38) at the end of the study.In this porcine two-hit shock model, treatment with 0.9% NaCl, HES 130/0.42 or HES 200/0.5 led to a similar maintenance of haemodynamic values. Despite this similar maintenance of the haemodynamic values, volume replacement with 6% and 10% HES 200/0.5 led to an accumulation of HES, higher colloid osmotic pressure and significantly reduced renal function after haemorrhagic and septic shock. These facts support the presumption that not the concentration but the degree of substitution and the molecular weight play a decisive role in HES-induced renal impairment.
EVALuna2:25475

MONITORING OF GENERAL IMMUNE STATUS AND SARS-COV-2 REACTIVE T-CELL AND HUMORAL IMMUNITY FACILITATES THE CLINICAL DECISION IN A SEVERE SARS-COV-2-ASSOCIATED PNEUMONIA, MENINGOENCEPHALITIS AND GASTROENTERITIS IN A PANCREAS-KIDNEY TRANSPLANT PATIENT - Babel, N.; Stervbo, U.; Seibert, F.; Bauer, F.; Anft, M.; Rohn, B.; Winnekendonk, G.; Dittmer, U.; Schenker, P.; Amann, Kerstin Ute; Viebahn, R.; Westhoff, T. (TRANSPLANT INTERNATIONAL, 2020)
CRIS-Team WoS Importer:2020-11-06

Mononuclear phagocytes orchestrate prolyl hydroxylase inhibition-mediated renoprotection in chronic tubulointerstitial nephritis - Schley, Gunnar; Klanke, Bernd; Kalucka, Joanna; Schatz, Valentin; Daniel, Christoph; Mayer, Marleen; Goppelt-Strübe, Margarete; Herrmann, Martin; Thorsteinsdottir, Margret; Palsson, Runolfur; Beneke, Angelika; Katschinski, Dörthe M.; et al. (Kidney International, 2019)
Prolyl hydroxylase domain enzyme inhibitors (PHDIs) stabilize hypoxia-inducible factors (HIFs), and are protective in models of acute ischemic and inflammatory kidney disease. Whether PHDIs also confer protection in chronic inflammatory kidney disease models remains unknown. Here we investigated long-term effects of PHDI treatment in adenine-induced nephropathy as a model for chronic tubulointerstitial nephritis. After three weeks, renal dysfunction and tubulointerstitial damage, including proximal and distal tubular injury, tubular dilation and renal crystal deposition were significantly attenuated in PHDI-treated (the isoquinoline derivative ICA and Roxadustat) compared to vehicle-treated mice with adenine-induced nephropathy. Crystal-induced renal fibrosis was only partially diminished by treatment with ICA. Renoprotective effects of ICA treatment could not be attributed to changes in adenine metabolism or urinary excretion of the metabolite 2,8-dihydroxyadenine. ICA treatment reduced inflammatory infiltrates of F4/80+ mononuclear phagocytes in the kidneys and supported a regulatory, anti-inflammatory immune response. Furthermore, interstitial deposition of complement C1q was decreased in ICA-treated mice fed an adenine-enriched diet. Tubular cell-specific HIF-1α and myeloid cell-specific HIF-1α and HIF-2α expression were not required for the renoprotective effects of ICA. In contrast, depletion of mononuclear phagocytes with clodronate largely abolished the nephroprotective effects of PHD inhibition. Thus, our findings indicate novel and potent systemic anti-inflammatory properties of PHDIs that confer preservation of kidney function and structure in chronic tubulointerstitial inflammation and might counteract kidney disease progression.
CRIS-Team Scopus Importer:2019-06-04
Keywords: adenine; chronic inflammation; chronic kidney disease; hypoxia-inducible factor; mononuclear phagocyte; PHD inhibitor

Morphological subtypes of colorectal low-grade intraepithelial neoplasia: Diagnostic reproducibility, frequency and clinical impact - Lang-Schwarz, Corinna; Büttner-Herold, Maike; Burian, Stephan; Erber, Ramona; Hartmann, Arndt; Jesinghaus, Moritz; Kamarádová, Kateina; Rubio, Carlos A.; Seitz, Gerhard; Sterlacci, William; Vieth, Michael; Bertz, Simone (Journal of Clinical Pathology, 2023)
Aims: Special histomorphological subtypes of colorectal low-grade intraepithelial neoplasia (LGIN) with variable prognostic impact were recently described in patients with inflammatory bowel disease (IBD) referred to as non-conventional dysplasia. However, they can also be found in patients without IBD. We aimed to analyse the reproducibility, frequency and prognostic impact of non-conventional colorectal LGIN in patients with and without IBD. Methods: Six pathologists evaluated 500 specimens of five different LGIN-cohorts from patients with and without IBD. Non-conventional LGIN included hypermucinous, goblet cell-deficient, Paneth cell-rich and crypt cell dysplasia. A goblet cell-rich type and non-conventional LGIN, not otherwise specified were added. Results were compared with the original expert-consented diagnosis from archived pathology records. Results: Four or more pathologists agreed in 86.0% of all cases. Non-conventional LGIN was seen in 44.4%, more frequently in patients with IBD (52%; non-IBD: 39.3%, p=0.005). In patients with IBD non-conventional LGIN associated with more frequent and earlier LGIN relapse (p=0.006, p=0.025), high-grade intraepithelial neoplasia (p=0.003), larger lesion size (p=0.001), non-polypoid lesions (p=0.019) and additional risk factors (p=0.034). Results were highly comparable with expert-consented diagnoses. In patients without IBD, non-conventional LGIN may indicate a higher risk for concurrent or subsequent colorectal carcinoma (CRC, p=0.056 and p=0.061, respectively). Frequencies and association with high-grade intraepithelial neoplasia or CRC varied between the different LGIN subtypes. Conclusions: Non-conventional histomorphology in colorectal LGIN is frequent and highly reproducible. Our results indicate an increased risk for CRC in patients with non-conventional LGIN, probably independent of IBD. We recommend reporting non-conventional LGIN in routine pathology reports.
CRIS-Team Scopus Importer:2023-12-29
Keywords: Histology; Inflammatory Bowel Diseases; Intestine; Large; NEOPLASMS

Multiplex gene analysis reveals T-cell and antibody-mediated rejection-specific upregulation of complement in renal transplants - Vonbrunn, Eva; Ries, Tajana; Söllner, Stefan; Müller-Deile, Janina; Büttner, Maike; Amann, Kerstin Ute; Daniel, Christoph (Scientific Reports, 2021)
In renal transplantation, complement is involved in ischemia reperfusion injury, graft rejection and dysfunction. However, it is still unclear how induction of complement and its activation are initiated. Using allograft biopsies of a well-characterized cohort of 28 renal transplant patients with no rejection (Ctrl), delayed graft function (DGF), acute T-cell-mediated (TCMR) or antibody-mediated rejection (ABMR) we analyzed differences in complement reaction. For that mRNA was isolated from FFPE sections, quantified with a multiplex gene expression panel and correlated with transplant conditions and follow-up of patients. Additionally, inflammatory cells were quantified by multiplex immunohistochemistry. In allograft biopsies with TCMR and ABMR gene expression of C1QB was 2-4 fold elevated compared to Ctrl. In TCMR biopsies, mRNA counts of several complement-related genes including C1S, C3, CFB and complement regulators CFH, CR1 and SERPING1 were significantly increased compared to Ctrl. Interestingly, expression levels of about 75% of the analyzed complement related genes correlated with cold ischemia time (CIT) and markers of inflammation. In conclusion, this study suggest an important role of complement in transplant pathology which seems to be at least in part triggered by CIT. Multiplex mRNA analysis might be a useful method to refine diagnosis and explore new pathways involved in rejection.
CRIS-Team Scopus Importer:2021-08-13

Murine cytomegalovirus reactivation concomitant with acute graft-versus-host disease is controlled by antibodies. - Seefried, Martina; Hundhausen, Nadine; Kroeger, Irena; Büttner-Herold, Maike; Hoffmann, Petra; Edinger, Matthias; Ullrich, Evelyn; Berberich-Siebelt, Friederike; Britt, William J.; Mach, Michael; Winkler, Thomas (JCI Insight, 2023)
Reactivation of human cytomegalovirus (HCMV) from latency is a frequent complication following hematopoietic stem cell transplantation (HSCT). The development of acute graft-versus-host disease (GVHD) is a significant risk factor for HCMV disease. Using a murine GVHD model in animals latently infected with murine CMV (MCMV), we studied preventive and therapeutic interventions in this high-risk scenario of HSCT. Mice latently infected with MCMV experienced reactivated MCMV and developed disseminated MCMV infection concomitant with the manifestations of GVHD. Dissemination was accompanied by accelerated mortality. We demonstrate that MCMV reactivation and dissemination was modulated by MCMV-specific antibodies, thus demonstrating in vivo protective activity of antiviral antibodies. However, the efficacy of serum therapy required repetitive doses of high-titer immune serum secondary to the shortened serum half-life of IgG in animals with GVHD. In a complementary approach, treatment of GVHD by adoptive transfer of donor-derived Tregs facilitated production of MCMV-specific antibodies from newly developing donor-derived B cells. Together, our findings strongly suggest that antibodies play a major role in controlling recurrent MCMV infection that follows GVHD, and they argue for reassessing the potential of antibody treatments as well as therapeutic strategies that enhance de novo antibody development against HCMV.
EVALuna2:527934

Mutations in the BAF-Complex Subunit DPF2 Are Associated with Coffin-Siris Syndrome - Vasileiou, Georgia; Vergarajauregui, Silvia; Endele, Sabine; Popp, Bernt; Büttner, Christian; Ekici, Arif Bülent; Gerard, Marion; Bramswig, Nuria C.; Albrecht, Beate; Clayton-Smith, Jill; Morton, Jenny; Tomkins, Susan; et al. (American Journal of Human Genetics, 2018)
Variants affecting the function of different subunits of the BAF chromatin-remodelling complex lead to various neurodevelopmental syndromes, including Coffin-Siris syndrome. Furthermore, variants in proteins containing PHD fingers, motifs recognizing specific histone tail modifications, have been associated with several neurological and developmental-delay disorders. Here, we report eight heterozygous de novo variants (one frameshift, two splice site, and five missense) in the gene encoding the BAF complex subunit double plant homeodomain finger 2 (DPF2). Affected individuals share common clinical features described in individuals with Coffin-Siris syndrome, including coarse facial features, global developmental delay, intellectual disability, speech impairment, and hypoplasia of fingernails and toenails. All variants occur within the highly conserved PHD1 and PHD2 motifs. Moreover, missense variants are situated close to zinc binding sites and are predicted to disrupt these sites. Pull-down assays of recombinant proteins and histone peptides revealed that a subset of the identified missense variants abolish or impaire DPF2 binding to unmodified and modified H3 histone tails. These results suggest an impairment of PHD finger structural integrity and cohesion and most likely an aberrant recognition of histone modifications. Furthermore, the overexpression of these variants in HEK293 and COS7 cell lines was associated with the formation of nuclear aggregates and the recruitment of both wild-type DPF2 and BRG1 to these aggregates. Expression analysis of truncating variants found in the affected individuals indicated that the aberrant transcripts escape nonsense-mediated decay. Altogether, we provide compelling evidence that de novo variants in DPF2 cause Coffin-Siris syndrome and propose a dominant-negative mechanism of pathogenicity.

Mutations in the BAF-complex subunit DPF2 are associated with Coffin-Siris syndrome - Vasileiou, G.; Vergarajauregui, S.; Endele, Sabine; Popp, Bernt; Büttner, Christian; Ekici, Arif Bülent; Gerard, M.; Bramswig, N. C.; Albrecht, B.; Clayton-Smith, J.; Morton, J.; Tomkins, S.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Mutations in the leukemia inhibitory factor receptor (LIFR) gene and Lifr deficiency cause urinary tract malformations - Kosfeld, Anne; Brand, Frank; Weiss, Anna-Carina; Kreuzer, Martin; Goerk, Michaela; Martens, Helge; Schubert, Stephanie; Schaefer, Anne-Kathrin; Riehmer, Vera; Hennies, Imke; Braesen, Jan Hinrich; Pape, Lars; et al. (Human Molecular Genetics, 2017)
Congenital anomalies of the kidneys and urinary tract (CAKUT) are the most common cause of chronic kidney disease in children. As CAKUT is a genetically heterogeneous disorder and most cases are genetically unexplained, we aimed to identify new CAKUT causing genes. Using whole-exome sequencing and trio-based de novo analysis, we identified a novel heterozygous de novo frameshift variant in the leukemia inhibitory factor receptor (LIFR) gene causing instability of the mRNA in a patient presenting with bilateral CAKUT and requiring kidney transplantation at one year of age. LIFR encodes a transmembrane receptor utilized by IL-6 family cytokines, mainly by the leukemia inhibitory factor (LIF). Mutational analysis of 121 further patients with severe CAKUT yielded two rare heterozygous LIFR missense variants predicted to be pathogenic in three unrelated patients. LIFR mutants showed decreased half-life and cell membrane localization resulting in reduced LIF-stimulated STAT3 phosphorylation. LIFR showed high expression in human fetal kidney and the human ureter, and was also expressed in the developing murine urogenital system. Lifr knockout mice displayed urinary tract malformations including hydronephrosis, hydroureter, ureter ectopia, and, consistently, reduced ureteral lumen and muscular hypertrophy, similar to the phenotypes observed in patients carrying LIFR variants. Additionally, a form of cryptorchidism was detected in all Lifr-/- mice and the patient carrying the LIFR frameshift mutation. Altogether, we demonstrate heterozygous novel or rare LIFR mutations in 3.3% of CAKUT patients, and provide evidence that Lifr deficiency and deactivating LIFR mutations cause highly similar anomalies of the urogenital tract in mice and humans.
EVALuna2:25536

Mutations in WDR19 encoding the intraflagellar transport component IFT144 cause a broad spectrum of ciliopathies - Fehrenbach, Henry; Decker, Christian; Eisenberger, Tobias; Frank, Valeska; Hampel, Tobias; Walden, Ulrike; Amann, Kerstin Ute; Krueger-Stollfuss, Ingrid; Bolz, Hanno J.; Haeffner, Karsten; Pohl, Martin; Bergmann, Carsten (Pediatric Nephrology, 2014)
An emerging number of clinically and genetically heterogeneous diseases now collectively termed ciliopathies have been connected to the dysfunction of primary cilia. We describe an 8-year-old girl with a complex phenotype that did not clearly match any familiar syndrome.Hypotonia, facial dysmorphism and retardation were noted shortly after birth. Other features included short stature, mild skeletal anomalies, strabism, deafness, subdural hygroma, hepatosplenomegaly and end-stage renal failure. Renal biopsy revealed tubular atrophy, interstitial fibrosis and segmental glomerulosclerosis. After exclusion of a chromosomal abnormality by array-comparative genomic hybridization (CGH), we performed next-generation sequencing (NGS) using a customized panel that targeted 131 genes known or hypothesized to cause ciliopathies. We identified the novel homozygous WDR19 mutation c.1483G > C (p.Gly495Arg) that affects an evolutionarily highly conserved residue in the intraflagellar transport protein IFT144, is absent from databases and is predicted to be pathogenic by all bioinformatic sources used.Mutations in WDR19 encoding the intraflagellar transport component IFT144 have recently been described in single families with the clinically overlapping skeletal ciliopathies Jeune and Sensenbrenner syndromes, combined or isolated nephronophthisis (NPHP) and retinitis pigmentosa (RP) (Senior-Loken syndrome). Our patient emphasizes the usefulness and efficiency of a comprehensive NGS panel approach in patients with unclassified ciliopathies. It further suggests that WDR19 mutations can cause a broad spectrum of ciliopathies that extends to Jeune and Sensenbrenner syndromes, RP and renal NPHP-like phenotypes.
EVALuna2:25461

MyD88 Is Required for Efficient Control of Coxiella burnetii Infection and Dissemination - Kohl, Lisa; Hayek, Inaya; Daniel, Christoph; Schulze-Luehrmann, Jan; Bodendorfer, Barbara; Lührmann, Anja; Lang, Roland (Frontiers in Immunology, 2019)
The intracellular pathogen Coxiella (C.) burnetii causes Q fever, a usually self-limiting respiratory infection that becomes chronic and severe in some patients. Innate immune recognition of C. burnetii and its role in the decision between resolution and chronicity is not understood well. However, TLR2 is important for the response to C. burnetii in mice, and genetic polymorphisms in Myd88 have been associated with chronic Q fever in humans. Here, we have employed MyD88-deficient mice in infection models with the attenuated C. burnetii Nine Mile phase II strain (NMII). Myd88(-/-) macrophages failed to restrict the growth of NMII in vitro, and to upregulate production of the cytokines TNF, IL-6, and IL-10. Following intraperitoneal infection, NMII bacterial burden was significantly higher on day 5 and 20 in organs of Myd88(-/-) mice. After infection via the natural route by intratracheal injection, a higher bacterial load in the lung and increased dissemination of NMII to other organs was observed in MyD88-deficient mice. While wild-type mice essentially cleared NMII on day 27 after intratracheal infection, it was still readily detectable on day 42 in multiple organs in the absence of MyD88. Despite the elevated bacterial load, Myd88(-/-) mice had less granulomatous inflammation and expressed significantly lower levels of chemoattractants, inflammatory cytokines, and of several IFN gamma-induced genes relevant for control of intracellular pathogens. Together, our results show that MyD88-dependent signaling is essential for early control of C. burnetii replication and to prevent systemic spreading. The continued presence of NMII in the organs of Myd88(-/-) mice constitutes a new mouse model to study determinants of chronicity and resolution in Q fever.
CRIS-Team WoS Importer:2019-02-21

Myocardial infarction with a preserved ejection fraction—the impaired function of the cardio-renal baroreflex - Pickny, Lisa; Hindermann, Martin; Ditting, Tilmann; Hilgers, Karl Friedrich; Linz, Peter; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Rodionova, Kristina (Frontiers in Physiology, 2023)
Introduction: In experimental myocardial infarction with reduced ejection fraction causing overt congestive heart failure, the control of renal sympathetic nerve activity (RSNA) by the cardio-renal baroreflex was impaired. The afferent vagal nerve activity under these experimental conditions had a lower frequency at saturation than that in controls. Hence, by investigating respective first neurons in the nodose ganglion (NG), we wanted to test the hypothesis that after myocardial infarction with still-preserved ejection fraction, the cardiac afferent nerve pathway is also already impaired. Material and methods: A myocardial infarction was induced by coronary artery ligature. After 21 days, nodose ganglion neurons with cardiac afferents from rats with myocardial infarction were cultured. A current clamp was used to characterize neurons as “tonic,” i.e., sustained action potential (AP) firing, or “phasic,” i.e., <5 APs upon current injection. Cardiac ejection fraction was measured using echocardiography; RSNA was recorded to evaluate the sensitivity of the cardiopulmonary baroreflex. Renal and cardiac histology was studied for inflammation and fibrosis markers. Results: A total of 192 neurons were investigated. In rats, after myocardial infarction, the number of neurons with a tonic response pattern increased compared to that in the controls (infarction vs. control: 78.6% vs. 48.5%; z-test, *p < 0.05), with augmented production of APs (23.7 ± 2.86 vs. 15.5 ± 1.86 APs/600 ms; mean ± SEM, t-test, *p < 0.05). The baseline activity of RSNA was subtly increased, and its control by the cardiopulmonary baroreflex was impaired following myocardial infarction: the fibrosis marker collagen I augmented in the renal interstitium. Discussion: After myocardial infarction with still-preserved ejection fraction, a complex impairment of the afferent limb of the cardio-renal baroreflex caused dysregulation of renal sympathetic nerve activity with signs of renal fibrosis.
CRIS-Team Scopus Importer:2023-05-05
Keywords: cardiac afferent neurons after myocardial infarction cardiac afferent innervation; congestive heart failure; myocardial infarction; neuronal cell culture; preserved ejection fraction; renal innervation

Myogenin controls via AKAP6 non-centrosomal microtubule-organizing center formation at the nuclear envelope - Becker, Robert; Vergarajauregui, Silvia; Billing, Florian; Sharkova, Maria; Lippolis, Eleonora; Mamchaoui, Kamel; Ferrazzi, Fulvia; Engel, Felix (eLife, 2021)
Non-centrosomal microtubule-organizing centers (MTOCs) are pivotal for the function of multiple cell types, but the processes initiating their formation are unknown. Here, we find that the transcription factor myogenin is required in murine myoblasts for the localization of MTOC proteins to the nuclear envelope. Moreover, myogenin is sufficient in fibroblasts for nuclear envelope MTOC (NE-MTOC) formation and centrosome attenuation. Bioinformatics combined with loss- and gain-of-function experiments identified induction of AKAP6 expression as one central mechanism for myogenin-mediated NE-MTOC formation. Promoter studies indicate that myogenin preferentially induces the transcription of muscle- and NE-MTOC-specific isoforms of Akap6 and Syne1, which encodes nesprin-1 alpha, the NE-MTOC anchor protein in muscle cells. Overexpression of AKAP6 beta and nesprin-1 alpha was sufficient to recruit endogenous MTOC proteins to the nuclear envelope of myoblasts in the absence of myogenin. Taken together, our results illuminate how mammals transcriptionally control the switch from a centrosomal MTOC to an NE-MTOC and identify AKAP6 as a novel NE-MTOC component in muscle cells.
CRIS-Team WoS Importer:2021-11-05

Nanofibrous Composite with Tailorable Electrical and Mechanical Properties for Cardiac Tissue Engineering - Roshanbinfar, Kaveh; Vogt, Lena; Ruther, Florian; Roether, Judith; Boccaccini, Aldo R.; Engel, Felix (Advanced Functional Materials, 2019)
Cardiac tissue engineering is a promising strategy to prevent functional deterioration or even to enhance cardiac function upon myocardial infarction. Here, electrospun fiber mats containing different combinations of electrically conductive polyaniline, collagen, and/or hyaluronic acid are assessed regarding material properties and compatibility with cardiomyocyte attachment and function. Microstructure analysis reveals that collagen fiber mats contain a wide range of fiber diameters after crosslinking (from ≈300 nm to ≈5 µm); all other fiber mats contain fibers in the range of ≈120 to ≈300 nm. Fiber mats exhibit comparable electrical conductivity to and greater mechanical properties than the native human myocardium, which is considered beneficial. Cell–matrix interaction analysis utilizing postnatal rat cardiomyocytes reveals that the fiber mats are non-cytotoxic and permit cell attachment and contraction. Fiber mats containing collagen (9.89%), hyaluronic acid (1.1%), and polyaniline (PANi, 1.34%) exhibit the most favorable properties with longer contraction time, higher contractile amplitude, and lower beating rates. Improved contraction is accompanied by increased connexin 43 expression. Importantly, this fiber mat is a suitable material for human-induced pluripotent stem cell–derived cardiomyocytes regarding cytotoxicity, cell attachment, and function. Collectively, these data demonstrate that fiber mats made of collagen, hyaluronic acid, and polyaniline are promising materials for cardiac tissue engineering.
CRIS-Team Scopus Importer:2019-12-31
Keywords: collagen; electroconductive; electrospinning; heart; hyaluronic acid; polyaniline; tissue engineering

Nebenwirkungen neuer onkologischer Immuntherapien - Braun, G. S.; Kirschner, M.; Ruebben, A.; Wahl, R. U.; Amann, Kerstin Ute; Benesova, K.; Leipe, J. (Nephrologe, 2020)
Systemic treatment with immune checkpoint inhibitors (ICI) has revolutionized the treatment of hematological and oncological diseases in recent years. The mechanism of action hinges on enhancing the natural ability of the immune system to eliminate malignant cells. The most important substances in this arena include inhibitors of PD-1, PD-L1 and CTLA-4. As a consequence, the spectrum of treatment-associated adverse reactions is shifting away from classical cytotoxic effects (e.g. pancytopenia and polyneuropathy) towards novel entities of immune-mediated complex diseases. These so-called immune-related adverse events (irAEs) can involve any organ system and mimic known classical autoimmune conditions. Timely recognition of irAEs is the key for rapid initiation of a suitable treatment and is especially challenging in the clinical routine as it requires an intensive interdisciplinary management. Nephrologists are particularly confronted with this kind of problem due to the highly interdisciplinary nature of their work. This article summarizes the broad spectrum of currently known renal and more frequently occuring non-renal forms of irAEs and aims to prime the reader on diagnostic and therapeutic options.
CRIS-Team WoS Importer:2020-05-15

Nephronectin Is Required for Vascularization in Zebrafish and Sufficient to Promote Mammalian Vessel-Like Structures in Hydrogels for Tissue Engineering. - Patra, Chinmoy; Rayrikar, Amey; Wagh, Ganesh; Kleefeldt, Florian; Roshanbinfar, Kaveh; Cop, Florian; Nikolic, Iva; Schmidt, Mirko H.H.; Acker-Palmer, Amparo; Ergün, Süleyman; Engel, Felix (Journal of the American Heart Association, 2025)
BACKGROUND: Organs and tissues need to be vascularized during development. Similarly, vascularization is required to engineer thick tissues. How vessels are formed during organogenesis is not fully understood, and vascularization of engineered tissues remains a significant challenge. METHODS AND RESULTS: Here, we show that the extracellular matrix protein nephronectin is required for vascularization during zebrafish development as well as adult fin regeneration and is sufficient to promote mammalian vessel formation and maturation. Nephronectin a morphants and mutants exhibit diminished axial vein sprouting and posterior intersegmental vessel growth. Notably, the angiogenesis-associated integrins itgav and itgb3.1 are coexpressed with nephronectin a in the region of the caudal vein plexus and posterior somites; nephronectin binds to integrin alpha-V/integrin beta-3.1 (ITGAV/ITGB3.1), and itgav morphants phenocopy nephronectin a mutants. In addition, nephronectin a mutants showed decreased vessel maturation compared with wild-type siblings during caudal fin regeneration in adult zebrafish. Moreover, nephronectin promotes mammalian endothelial cell migration and tube formation in 2D and 3-dimensional in vitro tissue culture. Further, nephronectin enhances vascular endothelial growth factor-induced periaortic vascular capillary interconnectivity, vessel diameter, and vessel stability. CONCLUSIONS: Collectively, our results identify nephronectin as a proangiogenic factor during embryonic development, which can be used to improve the vascularization of engineered tissues.
EVALuna2:583978

Nephron-specific knockout of TMEM16A leads to reduced number of glomeruli and albuminuria - Schenk, Laura K.; Buchholz, Björn; Henke, Sebastian F.; Michgehl, Ulf; Daniel, Christoph; Amann, Kerstin Ute; Kunzelmann, Karl; Pavenstaedt, Hermann (American Journal of Physiology-Renal Physiology, 2018)
TMEM16A is a transmembrane protein from a conserved family of calcium activated proteins, which is highly expressed in the kidney. TMEM16A confers calcium-activated chloride channel activity which is of importance for various cellular functions in secretory epithelia and involved in secretion-dependent renal cyst growth. However, its specific function in renal physiology has remained elusive so far. Therefore we generated conditional nephron specific TMEM16A knockout mice and found that these animals suffered from albuminuria. Kidney histology demonstrated an intact corticomedullary differentiation and absence of cysts. Electron microscopy showed a normal slit diaphragm. However, the total number of glomeruli and total nephron count was decreased in TMEM16A knockout animals. At the same time, glomerular diameter was increased, presumably as a result of the hyperfiltration in the remaining glomeruli. TUNEL and PCNA stainings showed increased cell death and increased proliferation. Proximal tubular cilia were intact in young animals but the number of properly ciliated cells was decreased in older, albuminuric animals. Taken together, our data suggests that TMEM16A may be involved in ureteric bud branching and proper nephron endowment. Loss of TMEM16A resulted in reduced nephron number and, subsequently, albuminuria and tubular damage.
EVALuna2:35395
Keywords: albuminuria; Ano1; kidney; nephron number; TMEM16A

Nephropathologie - Amann, Kerstin Ute; Wolf, G. (Nephrologe, 2019)
CRIS-Team Scopus Importer:2019-05-03

Nephropathologie infektiöser Erkrankungen - Büttner-Herold, Maike; Amann, Kerstin Ute; Velden, Joachim (Die Pathologie, 2024)
Infections can affect the kidney via different pathways. Urinary tract infections can directly involve the renal tissue by spreading along pre-existing canalicular structures. Such an ascending infection can manifest as a highly active and purulent or even abscessing interstitial nephritis or as a chronic-fibrosing process in recurrent pyelonephritis. Viral infections can also use the canalicular route as in polyomavirus nephropathy or spread via the blood stream in a hematogenous manner as in the case of cytomegalovirus or hantavirus infections. Likewise, bacterial infections can reach the kidney via the blood in the case of systemic infection. Another large group of nephropathies taking place as a sequel of infections includes infection-related glomerulonephritides (IRGN), which are mediated by a series of immunological mechanisms. These IRGN can be subdivided according to their temporal association with the infectious process, occurring either after the infection has healed (postinfectious) or accompanying the ongoing infectious process (parainfectious). The latter, in particular, is of increasing importance in the daily practice of nephropathologists, especially in older patients. A number of other glomerulonephritis forms, i.e., membranous or membranoproliferative forms, can occur as a consequence of infection. In addition, infections can trigger nephropathies, such as thrombotic microangiopathy. The present article gives an overview of morphologic changes in renal parenchyma that take place as a consequence of infectious processes, with particular focus on IRGN.
CRIS-Team Scopus Importer:2024-05-17
Keywords: Immune complex; Infection-related glomerulonephritis; Path of infection; Pathogen spectrum; Urinary tract infection

Nephropathology Nephropathologie - Wolf, Gunter; Amann, Kerstin Ute (Die Nephrologie, 2022)
CRIS-Team Scopus Importer:2024-12-16

Nephropathy in illicit drug abusers: a postmortem analysis - Büttner, Maike; Toennes, Stefan W.; Buettner, Stefan; Bickel, Markus; Allwinn, Regina; Geiger, Helmut; Bratzke, Hansjuergen; Amann, Kerstin Ute; Jung, Oliver (American Journal of Kidney Diseases, 2014)
Illicit drug abuse is an independent risk factor for chronic kidney disease, but the pathogenic consequences of long-term exposure to illicit drugs and contaminants under unsterile conditions remains unclear.Case series.All deceased persons (n 5 129) who underwent forensic autopsy because of suspected connection with illicit drug abuse between January 1, 2009, and April 30, 2011, in Frankfurt/Main, Germany.Clinical characteristics and patterns of drug abuse.Histopathologic alterations of the kidney.Hematoxylin and eosin, periodic acid-Schiff, Sirius, and Congo Red stainings and immunoglobulin A immunohistochemistry of all cases; additional histochemical stainings or immunohistochemistry and electron microscopy in selected cases.Individuals were mostly white (99.2%), were male (82.2%), and had intravenous drug use (IVDU) (81.4%). Median age at death was 39 years and duration of drug abuse was 17 years. The majority (79.1%) took various drugs in parallel as assessed by toxicologic analysis. Despite a young age, the deceased had a high burden of comorbid conditions, especially cardiovascular disease, liver cirrhosis, and infections. Evaluation of the kidneys demonstrated a broad spectrum of pathologic alterations predominated by arteriosclerotic and ischemic damage, mild interstitial inflammation, calcification of renal parenchyma, and interstitial fibrosis and tubular atrophy, with hypertensive-ischemic nephropathy as the most common cause of nephropathy. Interstitial inflammation (OR, 16.59; 95% CI, 3.91-70.39) and renal calcification (OR, 2.43; 95% CI, 1.03- 5.75) were associated with severe IVDU, whereas hypertensive and ischemic damage were associated with cocaine abuse (OR, 6.00; 95% CI, 1.27-28.44). Neither specific glomerular damage indicative for heroin and hepatitis C virus-related disease nor signs of analgesic nephropathy were found.White population, lack of a comparable control group, incomplete clinical data, and absence of routine immunohistochemistry and electron microscopy.Illicit drug abuse is associated with a broad but unspecific spectrum of pathologic alterations of the kidneys. Cocaine abuse has a deleterious role in this setting by promoting hypertensive and ischemic damage.
EVALuna2:25464

Nephrotic syndrome and thrombotic microangiopathy caused by cobalamin C deficiency - Koenig, Jens C.; Rutsch, Frank; Bockmeyer, Clemens; Baumgartner, Matthias; Beck, Bodo B.; Kranz, Brigitta; Konrad, Martin (Pediatric Nephrology, 2015)
Cobalamin C (CblC) defects are inherited autosomal recessive disorders of vitamin B12 metabolism due to mutations in the MMACHC gene. Renal manifestations include thrombotic microangiopathy (TMA), acute or chronic renal failure, tubulointerstitial nephritis, and proximal renal tubular acidosis. However, reports about glomerular pathologies are scarce.A 4-year-old boy presented with nephrotic syndrome, arterial hypertension, and chronic anemia but no signs of hemolysis. Renal biopsy showed TMA with ischemic glomerular collapse, foot process effacement, and tubulointerstitial fibrosis. Elevated serum levels of homocysteine suggested a cobalamin C disorder. This was confirmed by the identification of compound heterozygous mutations in the MMACHC gene. Initial therapy consisted of antihypertensive treatment including angiotensin converting enzyme inhibitor (ACEi) leading to blood pressure control and a significant reduction of proteinuria. After a definite diagnosis of CblC deficiency, hydroxocobalamin was introduced. Thereafter, homocysteine levels decreased, anemia resolved, and a further decline of proteinuria with normalization of serum protein levels was noted. Renal function remained stable.Although uncommon, the clinical picture of CblC defects may be ruled by nephrotic syndrome mimicking glomerulonephritis, minimal change disease, or primary focal and segmental glomerulosclerosis. Key to a correct diagnosis is elevated serum levels of homocysteine, and a definite diagnosis can be confirmed by genetic testing.
EVALuna2:25496

Nephrotic syndrome in antibody deficiency syndrome in CLL - Strutz, Frank; Amann, Kerstin Ute; Wittmann, Gertraud; Beck, Joachim (Die Nephrologie, 2022)
CRIS-Team WoS Importer:2022-12-16

Nephrotisches Syndrom nach COVID-19-Impfung: Drei neue Fälle aus Deutschland - Dormann, Harald; Knüppel-Ruppert, Anja; Amann, Kerstin Ute; Erley, Christiane (Deutsches Ärzteblatt international, 2021)
CRIS-Team Scopus Importer:2021-10-29

Nestin expression in repopulating mesangial cells promotes their proliferation - Daniel, Christoph; Albrecht, Heinz; Lüdke, Andrea; Hugo, Christian (Laboratory Investigation, 2008)
We investigated whether the intermediate filament protein and neural stem cell marker nestin characterizes the glomerular progenitor/reserve cell population immigrating the glomerulus after mesangial cell (MC) injury in the rat (anti-Thy1 nephritis). Nestin expression was investigated by immunohistochemistry and real-time PCR during anti-Thy1 nephritis. Migration and proliferation assays were used to characterize the function of nestin in isolated MCs after nestin knockdown by siRNA. After MC injury during anti-Thy1 nephritis, glomerular nestin was transiently increased during the repopulation phase. At the peak of mesangial proliferation and expansion (day 5) most OX-7-positive MCs expressed nestin largely colocalizing with the activation marker α-smooth muscle actin and the proliferation marker PCNA. In contrast to a healthy, non-injured mesangium in vivo, MCs in culture are considered to be in an 'activated, injured state' and express nestin in a generalized distribution with condensed localization around the nucleus as well as intensive staining of cell protrusions such as filopodia. During cell cycle, the percentage of MCs with high nestin levels was increased during S- aupnd G2-phase. Blocking of nestin using specific siRNA resulted in inhibition of cell proliferation but not cell migration. In conclusion, nestin is constitutively expressed in podocytes, but is a marker for repopulating MCs after experimental MC injury in vivo. Nestin promotes MC proliferation in vitro, suggesting a supporting role for nestin during repair reaction. © 2008 USCAP, Inc All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Nestin; Podocytes; Proliferation; Repopulation; Stem cells

Neurogenic substance P-influences on action potential production in afferent neurons of the kidney? - Rodionova, Kristina; Hilgers, Karl Friedrich; Linz, Peter; Schaetzl, Johannes; Raschke, Giulia; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Ditting, Tilmann (Pflügers Archiv: European Journal of Physiology, 2021)
We recently showed that a substance P (SP)-dependent sympatho-inhibitory mechanism via afferent renal nerves is impaired in mesangioproliferative nephritis. Therefore, we tested the hypothesis that SP released from renal afferents inhibits the action potential (AP) production in their dorsal root ganglion (DRG) neurons. Cultured DRG neurons (Th11-L2) were investigated in current clamp mode to assess AP generation during both TRPV1 stimulation by protons (pH 6) and current injections with and without exposure to SP (0.5 mu mol) or CGRP (0.5 mu mol). Neurons were classified as tonic (sustained AP generation) or phasic (<= 4 APs) upon current injection; voltage clamp experiments were performed for the investigation of TRPV1-mediated inward currents due to proton stimulation. Superfusion of renal neurons with protons and SP increased the number of action potentials in tonic neurons (9.6 +/- 5 APs/10 s vs. 16.9 +/- 6.1 APs/10 s, P < 0.05, mean +/- SD, n = 7), while current injections with SP decreased it (15.2 +/- 6 APs/600 ms vs. 10.2 +/- 8 APs/600 ms, P < 0.05, mean +/- SD, n = 29). Addition of SP significantly reduced acid-induced TRPV1-mediated currents in renal tonic neurons (- 518 +/- 743 pA due to pH 6 superfusion vs. - 82 +/- 50 pA due to pH 6 with SP superfusion). In conclusion, SP increased action potential production via a TRPV1-dependent mechanism in acid-sensitive renal neurons. On the other hand, current injection in the presence of SP led to decreased action potential production. Thus, the peptide SP modulates signaling pathways in renal neurons in an unexpected manner leading to both stimulation and inhibition of renal neuronal activity in different (e.g., acidic) environmental contexts.
CRIS-Team WoS Importer:2021-04-16

Neurogenic tachykinin mechanisms in experimental nephritis of rats - Rodionova, Kristina; Hilgers, Karl Friedrich; Paulus, Eva-Maria; Tiegs, Gisa; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Ditting, Tilmann (Pflügers Archiv: European Journal of Physiology, 2020)
We demonstrated earlier that renal afferent pathways combine very likely "classical" neural signal transduction to the central nervous system and a substance P (SP)-dependent mechanism to control sympathetic activity. SP content of afferent sensory neurons is known to mediate neurogenic inflammation upon release. We tested the hypothesis that alterations in SP-dependent mechanisms of renal innervation contribute to experimental nephritis. Nephritis was induced by OX-7 antibodies in rats, 6 days later instrumented for recording of blood pressure (BP), heart rate (HR), drug administration, and intrarenal administration (IRA) of the TRPV1 agonist capsaicin to stimulate afferent renal nerve pathways containing SP and electrodes for renal sympathetic nerve activity (RSNA). The presence of the SP receptor NK-1 on renal immune cells was assessed by FACS. IRA capsaicin decreased RSNA from 62.4 +/- 5.1 to 21.6 +/- 1.5 mV s (*p < 0.05) in controls, a response impaired in nephritis. Suppressed RSNA transiently but completely recovered after systemic administration of a neurokinin 1 (NK1-R) blocker. NK-1 receptors occurred mainly on CD11(+)dendritic cells (DCs). An enhanced frequency of CD11c(+)NK1R(+)cell, NK-1 receptor(+)macrophages, and DCs was assessed in nephritis. Administration of the NK-1R antagonist aprepitant during nephritis reduced CD11c(+)NK1R(+)cells, macrophage infiltration, renal expression of chemokines, and markers of sclerosis. Hence, SP promoted renal inflammation by weakening sympathoinhibitory mechanisms, while at the same time, substance SP released intrarenally from afferent nerve fibers aggravated immunological processes i.e. by the recruitment of DCs.
CRIS-Team WoS Importer:2020-11-06

Neutrophils in HNSCC Can Be Associated with Both a Worse or Favorable Prognosis - Brunkhorst, Hendrik; Schnellhardt, Sören; Büttner-Herold, Maike; Daniel, Christoph; Fietkau, Rainer; Distel, Luitpold (Biomolecules, 2024)
The prognostic significance of tumor-infiltrating neutrophils in head and neck squamous cell carcinoma (HNSCC) is poorly understood. It is unclear how the presence of neutrophils affects prognosis due to their polarization into cytotoxic N1 or immunosuppressive N2. Therefore, we determined the number of CD66b+ neutrophil granulocytes separately in the stromal and epithelial compartments in cancer tissues from 397 patients with HNSCC. Tumor samples from six historical patient groups were processed into tissue microarrays and stained immunohistochemically. In total, 21.9% were HPV positive (p16+). Neutrophil counts were much lower in the stromal compartment (372 ± 812) than in the epithelial cancer compartment (1040 ± 1477) (p < 0.001), with large differences between groups. In three groups with high neutrophil infiltration, high rates were associated with a favorable prognosis, whereas in two groups, high rates were a negative prognostic factor. In p16- oropharyngeal and hypopharyngeal cancer high infiltration was associated with a favorable prognosis. Cancers with an exclusion of neutrophils in the epithelial compartment were associated with improved prognosis. In oropharyngeal and hypopharyngeal HPV-negative cancer high neutrophil infiltration rates were clearly associated with prolonged survival. Neutrophil granulocytes in HNSCC may contribute to a favorable or unfavorable prognosis.
CRIS-Team Scopus Importer:2024-03-08
Keywords: CD66b+; head and neck cancer; HNSCC; hypopharynx; larynx; neutrophils; oral cavity; oropharynx; prognosis; tumor-associated neutrophils

New functions and signaling mechanisms for the class of adhesion G protein-coupled receptors - Liebscher, Ines; Ackley, Brian; Arac, Demet; Ariestanti, Donna M.; Aust, Gabriela; Bae, Byoung-Il; Bista, Bigyan R.; Bridges, James P.; Duman, Joseph G.; Engel, Felix; Giera, Stefanie; Goffinet, Andre M.; et al. (Annals of the New York Academy of Sciences, 2014)
The class of adhesion G protein-coupled receptors (aGPCRs), with 33 human homologs, is the second largest family of GPCRs. In addition to a seven-transmembrane ?-helix-a structural feature of all GPCRs-the class of aGPCRs is characterized by the presence of a large N-terminal extracellular region. In addition, all aGPCRs but one (GPR123) contain a GPCR autoproteolysis-inducing (GAIN) domain that mediates autoproteolytic cleavage at the GPCR autoproteolysis site motif to generate N- and a C-terminal fragments (NTF and CTF, respectively) during protein maturation. Subsequently, the NTF and CTF are associated noncovalently as a heterodimer at the plasma membrane. While the biological function of the GAIN domain-mediated autocleavage is not fully understood, mounting evidence suggests that the NTF and CTF possess distinct biological activities in addition to their function as a receptor unit. We discuss recent advances in understanding the biological functions, signaling mechanisms, and disease associations of the aGPCRs.
EVALuna2:25477

Next generation sequencing and functional analysis of patient urine renal progenitor-derived podocytes to unravel the diagnosis underlying refractory lupus nephritis - Romagnani, Paola; Giglio, Sabrina; Angelotti, Maria Lucia; Provenzano, Aldesia; Becherucci, Francesca; Mazzinghi, Benedetta; Mueller, Susanna; Amann, Kerstin Ute; Weidenbusch, Marc; Romoli, Simone; Lazzeri, Elena; Anders, Hans-Joachim (Nephrology Dialysis Transplantation, 2016)
Often the cause of refractory lupus nephritis (RLN) remains unclear. We performed next-generation sequencing for podocyte genes in an RLN patient and identified compound heterozygosity for APOL1 risk alleles G1 and G2 and a novel homozygous c.[1049C>T]+[1049C>T] NPHS1 gene variant of unknown significance. To test for causality renal progenitor cells isolated from urine of this patient were differentiated into podocytes in vitro. Podocytes revealed aberrant nephrin trafficking, cytoskeletal structure and lysosomal leakage, and increased detachment as compared with podocytes isolated from controls. Thus, lupus podocytopathy can be confirmed as a cause of RLN by functional genetics on patient-derived podocytes.
EVALuna2:25516

Nierenbeteiligung bei Kollagenosen - Teil 1: Lupus-Nephritis - Oelzner, Peter; Amann, Kerstin Ute; Wolf, Gunter (Aktuelle Rheumatologie, 2020)
Lupus nephritis (LN) occurs dependent on ethnicity and gender in up to 50% of patients with systemic lupus erythematosus (SLE) and represents the prognostic most important organ manifestation in SLE. Pathogenetic important aspects of SLE are a multifactorial caused disturbance of the clearance of autoantigen released in the context of apoptosis and NETosis resulting in the development of autoimmune reaction, an amplification of the pathologic immune reaction by hyperactivation of type I-interferon signaling and cytokine imbalance. The pathogenetic process in the kidney results in immune complex glomerulonephritis. Early diagnosis and initiation of therapy are of critical importance for the prognosis of LN. The selection of therapy is based principally on the findings in renal biopsy. In the case of proliferative LN (class III or IV, also in combination with membranous LN) a remission induction with low-dose cyclophosphamide (CYC)-pulse therapy (6 x 500 mg) or with mycophenolatofetil (MMF) in combination with initial high dose glucocorticoids (GC) is followed by a maintenance therapy with azathioprine or MMF. In refractory situations a switch from CYC to MMF or conversely is indicated. Alternatively rituximab or calcineurin inhibitors can also be used. In other forms of LN the therapeutic procedure is essentially determinated by the course of renal function and the extent of proteinuria. In addition supportive procedures such as the general use of hydroxychloroquine, ACE inhibitors or angiotensin rezeptor blockers in dependence of the extent of proteinuria and of blood pressure and prophylactic measures to prevent thromboembolism, osteoporosis and infections come into use. Aims of therapy are a preferably complete renal remission, prevention of chronic damage and an effective reduction of GC dose. A complete remission which is defined by the preservation of normal renal function and a substantial reduction of proteinuria is achieved in approximately 50-60%. This underlines the effectiveness of the curent therapy on one hand but illuminates the need of new therapeutic strategies on the other, especially in view of the high rate of damage. New therapeutic approaches such multitarget therapy, new protocolls of B cell depletion and B cell neutralization and GC free treatment principles aim at a more effective and side effect poor therapy of LN.
CRIS-Team Scopus Importer:2020-04-21
Keywords: Lupus nephritis; pathogenesis; therapy

Nierenbeteiligung bei Kollagenosen – Teil 2: Antiphospholipid-Syndrom, primäres Sjögren-Syndrom, systemische Sklerose - Oelzner, Peter; Amann, Kerstin Ute; Wolf, Gunter (Aktuelle Rheumatologie, 2020)
Renal manifestations in antiphospholipid syndrome (APS), primary Sjögren?s syndrome (pSS) and systemic sclerosis (SSc) differ from each other substantially with respect to pathogenesis, histology, clinical picture, prognosis and therapeutic consequences. The frequency of APS-associated renal affections ranges from 10 to 40%. APS can affect the kidney in the form of renal hypertension, thrombosis or stenosis of the renal artery, renal infarction, thrombosis of the renal vein and intrarenal vasculopathy (APS nephropathy). Especially in the case of secondary APS, the differential diagnosis of lupus nephritis by renal biopsy is important because APS requires anticoagulation, but generally no immunosuppression. In pSS, too, renal affections are relatively common (20-40%). The characteristic and most frequent manifestation is interstitial nephritis with distal tubular acidosis type 1. Distal tubular acidosis is often asymptomatic, but can result in hypokalaemia and osteomalacia. Whereas interstitial nephritis and the less frequent glomerulonephritis generally respond well to immunosuppression, the response of distal tubular acidosis to immunosuppression is insufficient. Decrease of renal function and proteinuria as a sign of renal affection are observed in up to 36% of patients with SSc. This type of nephropathy, often multifactorial in origin, is characterised by sclerosed glomeruli, tubular atrophy and interstitial fibrosis, and has a good prognosis with respect to renal function. Scleroderma renal crisis, which is characterised by obstructive vasculopathy, accelerated arterial hypertension and progressive renal failure, is substantially less frequent (4-11%). Risk factors for renal crisis in SSc involve the presence of diffuse cutaneous SSc, older age, male gender, glucocorticoid use, pericardial effusion and the presence of anti-RNA polymerase III antibodies. Therapy of hypertensive renal crisis aims to reduce the systolic blood pressure by 10% per day to the normal range, preferably with ACE inhibitors, while avoiding prolonged periods of hypotension. In the case of insufficient reduction of blood pressure despite ACE inhibitor therapy, alpha-blockers, calcium channel blockers and/or minoxidil are used in addition. Intravenous administration of prostacycline to improve renal perfusion and the use of the endothelin receptor antagonist bosentan are also useful. The availability of ACE inhibitors has resulted in a significant reduction of mortality due to renal crisis; however, a progression to end-stage renal disease is to be expected in 40-50%.
CRIS-Team Scopus Importer:2020-04-24
Keywords: connective tissue diseases; pathogenesis; renal involvement; therapy

Nierenerkrankungen bei HIV‑Infektion - Bestandsaufnahme nach fast 40 Jahren Erfahrung mit HIV - Rieke, A.; Amann, Kerstin Ute; Lutz, J. (Nephrologe, 2020)
Human immunodeficiency virus (HIV) infections are nowadays a treatable chronic disease with a nearly normal life expectation. Kidney diseases play an increasingly important role in these patients due to the direct and indirect effects of HIV on the kidneys in the form of HIV-associated nephropathy (HIVAN), secondary glomerulonephritis, chronic inflammation and the increasing age with corresponding comorbidities. In patients with HIVAN and secondary glomerulonephritis an antiretroviral therapy (ART) should be quickly initiated; however, ART requires a continuous surveillance of the renal function as some medications can accumulate with decreasing renal function and can even have nephrotoxic effects themselves.
CRIS-Team Scopus Importer:2020-06-16
Keywords: AIDS-associated nephropathy; Antiretroviral therapy; Fanconi syndrome; Tubular transporters; Tubulopathy

No benefit of HIF prolyl hydroxylase inhibition for hypertensive renal damage in renovascular hypertensive rats - Hartner, Andrea; Dambietz, Thomas; Cordasic, Nada; Willam, Carsten; Burzlaff, Nicolai; Brötsch, Martin; Daniel, Christoph; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Schley, Gunnar; Hilgers, Karl Friedrich (Frontiers in Physiology, 2023)
Introduction: We previously reported that malignant hypertension is associated with impaired capillary density of target organs. Here, we tested the hypothesis that stabilization of hypoxia-inducible factor (HIF) in a modified “preconditioning” approach prevents the development of malignant hypertension. To stabilize HIF, we employed pharmacological inhibition of HIF prolyl hydroxylases (PHD), that profoundly affect HIF metabolism. Methods: Two-kidney, one-clip renovascular hypertension (2K1C) was induced in rats; controls were sham operated. 2K1C rats received either intermittent injections of the PHD inhibitor ICA (2-(1-chloro-4-hydroxyisoquinoline-3-carboxamido) acetate) or placebo. Thirty-five days after clipping, the frequency of malignant hypertension was assessed (based on weight loss and the occurrence of characteristic vascular lesions). In addition, kidney injury was compared between all ICA treated versus all placebo treated 2K1C, regardless of the occurrence of malignant hypertension. HIF stabilization was evaluated by immunohistochemistry, and HIF target gene expression by RT-PCR. Results: Blood pressure was elevated to the same degree in ICA- and placebo-treated 2K1C compared to control rats. ICA treatment did not affect the frequency of malignant hypertension or the extent of kidney tissue fibrosis, inflammation, or capillary density. There was a trend towards higher mortality and worse kidney function in ICA-treated 2K1C rats. ICA increased the number of HIF-1α-positive renal tubular cell nuclei and induced several HIF-1 target genes. In contrast, expression of HIF-2α protein as well as HIF-2 target genes were markedly enhanced by 2K1C hypertension, irrespective of ICA treatment. Discussion: We conclude that intermittent PHD inhibition did not ameliorate severe renovascular hypertension in rats. We speculate that the unexpected strong renal accumulation of HIF-2α in renovascular hypertension, which could not be further augmented by ICA, may contribute to the lack of a benefit from PHD inhibition.
CRIS-Team Scopus Importer:2023-07-21
Keywords: capillarization; HIF stabilization; malignant hypertension; renovascular; vascular lesions

No evidence of pathogenic involvement of cathelicidins in patient cohorts and mouse models of lupus and arthritis - Kienhofer, D.; Hahn, Jonas; Schubert, I.; Reinwald, Christiane; Ipseiz, N.; Lang, Sabine; Borras, E. Bosch; Amann, Kerstin Ute; Sjowall, C.; Barron, A. E.; Hueber, Axel; Agerberth, B.; et al. (PLoS ONE, 2014)
Apart from their role in the immune defence against pathogens evidence of a role of antimicrobial peptides (AMPs) in autoimmune diseases has accumulated in the past years. The aim of this project was to examine the functional impact of the human cathelicidin LL-37 and the mouse cathelicidin-related AMP (CRAMP) on the pathogenesis of lupus and arthritis. Serum LL-37 and anti-LL-37 levels were measured by ELISA in healthy donors and patients with Systemic Lupus Erythematosus (SLE) and Rheumatoid arthritis (RA). Pristane-induced lupus was induced in female wild type (WT) and cathelicidin-deficient (CRAMP-/-) mice. Serum levels of anti-Sm/RNP, anti-dsDNA, and anti-histone were determined via ELISA, cytokines in sera and peritoneal lavages were measured via Multiplex. Expression of Interferon I stimulated genes (ISG) was determined by real-time PCR. Collagen-induced arthritis (CIA) was induced in male WT and CRAMP-/- mice and arthritis severity was visually scored and analysed histomorphometrically by OsteoMeasure software. Serum levels of anti-LL-37 were higher in SLE-patients compared to healthy donors or patients with RA. However, no correlation to markers of disease activity or organ involvement was observed. No significant differences of autoantibody or cytokine/chemokine levels, or of expression of ISGs were observed between WT and CRAMP-/- mice after pristane-injection. Furthermore, lung and kidney pathology did not differ in the absence of CRAMP. Incidence and severity of CIA and histological parameters (inflammation, cartilage degradation, and bone erosion) were not different in WT and CRAMP-/- mice. Although cathelicidins are upregulated in mouse models of lupus and arthritis, cathelicidin-deficiency did not persistently affect the diseases. Also in patients with SLE, autoantibodies against cathelicidins did not correlate with disease manifestation. Reactivity against cathelicidins in lupus and arthritis could thus be an epiphenomenon caused by extensive overexpression in blood and affected tissues. In addition, other cationic AMPs could functionally compensate for the deficiency of cathelicidins.
EVALuna2:12499

No juvenile arterial hypertension in sheep multiples despite reduced nephron numbers - Muehle, Anja; Mühle, Christiane; Amann, Kerstin Ute; Dötsch, Jörg; Nuesken, Kai-Dietrich; Boltze, Johannes; Schneider, Holm (Pediatric Nephrology, 2010)
Low birth weight is associated with an increased risk of metabolic dysfunction and arterial hypertension in later life. Because of their reduced birth weight twins have been used repeatedly as a natural model to investigate prenatal programming of hypertension. To reveal an early impact of lower nephron endowment on blood pressure, we performed a longitudinal study on lambs from single, twin and triplet pregnancies. The lambs were studied from birth until adulthood, including regular blood analyses, measurements of body weight and blood pressure and post-mortem estimation of glomerular numbers. Relative weight differences between multiples and singletons at birth were -28% for twins and -44% for triplets, respectively. Some lambs showed rapid catch-up growth. Total nephron number of twins and triplets was reduced by 21 and 37% with respect to that of singletons (p∈<∈0.01). However, multiples did not show increased blood pressure within the time frame of this study. No gender-specific effect was observed. Plasma concentrations of creatinine, urea, electrolytes or osmolality also did not differ. Our data indicate that the previously reported postnatal blood pressure differences between sheep multiples and singletons are a time-limited phenomenon. During infancy and adolescence, a reduced nephron number in sheep multiples is neither associated with increased blood pressure nor reflected by plasma parameters. © 2010 IPNA.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Blood pressure; Nephron number; Prenatal programming

Non-Invasive Biomarkers for Diagnosis, Risk Prediction, and Therapy Guidance of Glomerular Kidney Diseases: A Comprehensive Review - Catanese, Lorenzo; Rupprecht, Harald; Huber, Tobias B.; Lindenmeyer, Maja T.; Hengel, Felicitas E.; Amann, Kerstin Ute; Wendt, Ralph; Siwy, Justyna; Mischak, Harald; Beige, Joachim (International Journal of Molecular Sciences, 2024)
Effective management of glomerular kidney disease, one of the main categories of chronic kidney disease (CKD), requires accurate diagnosis, prognosis of progression, assessment of therapeutic efficacy, and, ideally, prediction of drug response. Multiple biomarkers and algorithms for the assessment of specific aspects of glomerular diseases have been reported in the literature. Though, the vast majority of these have not been implemented in clinical practice or are not available on a global scale due to limited access, missing medical infrastructure, or economical as well as political reasons. The aim of this review is to compile all currently available information on the diagnostic, prognostic, and predictive biomarkers currently available for the management of glomerular diseases, and provide guidance on the application of these biomarkers. As a result of the compiled evidence for the different biomarkers available, we present a decision tree for a non-invasive, biomarker-guided diagnostic path. The data currently available demonstrate that for the large majority of patients with glomerular diseases, valid biomarkers are available. However, despite the obvious disadvantages of kidney biopsy, being invasive and not applicable for monitoring, especially in the context of rare CKD etiologies, kidney biopsy still cannot be replaced by non-invasive strategies.
CRIS-Team Scopus Importer:2024-04-05
Keywords: biomarker; CKD; diagnosis; glomerular diseases; kidney disease; prognosis; risk prediction

Non-professional phagocytosis: a general feature of normal tissue cells - Seeberg, Jacob; Loibl, Monika; Moser, Fabian; Schwegler, Manuela; Büttner-Herold, Maike; Daniel, Christoph; Engel, Felix; Hartmann, Arndt; Schlötzer-Schrehardt, Ursula; Goppelt-Strübe, Margarete; Schellerer, Vera; Naschberger, Elisabeth; et al. (Scientific Reports, 2019)
Non-professional phagocytosis by cancer cells has been described for decades. Recently, non-professional phagocytosis by normal tissue cells has been reported, which prompted us to take a closer look at this phenomenon. Non-professional phagocytosis was studied by staining cultured cells with live-cell staining dyes or by staining paraffin-embedded tissues by immunohistochemistry. Here, we report that each of 21 normal tissue cell lines from seven different organs was capable of phagocytosis, including ex vivo cell cultures examined before the 3rd passage as well as the primary and virus-transformed cell lines. We extended our analysis to an in vivo setting, and we found the occurrence of non-professional phagocytosis in healthy skin biopsies immediately after resection. Using dystrophin immunohistochemistry for membrane staining, human post-infarction myocardial tissue was assessed. We found prominent signs of non-professional phagocytosis at the transition zone of healthy and infarcted myocardia. Taken together, our findings suggest that non-professional phagocytosis is a general feature of normal tissue cells.
CRIS-Team Scopus Importer:2019-08-27

Non-Professional Phagocytosis Increases in Melanoma Cells and Tissues with Increasing E-Cadherin Expression. - Unseld, Luzie Helene; Hildebrand, Laura; Putz, Florian; Büttner-Herold, Maike; Daniel, Christoph; Fietkau, Rainer; Distel, Luitpold (Current Oncology, 2023)
Non-professional phagocytosis in cancer has been increasingly studied in recent decades. In malignant melanoma metastasis, cell-in-cell structures have been described as a sign of cell cannibalism. To date, only low rates of cell-in-cell structures have been described in patients with malignant melanoma. To investigate these findings further, we examined twelve primary melanoma cell lines in both adherent and suspended co-incubation for evidence of engulfment. In addition, 88 malignant melanoma biopsies and 16 healthy tissue samples were evaluated. E-cadherin levels were determined in the cell lines and tissues. All primary melanoma cell lines were capable of phagocytosis, and phagocytosis increased when cells were in suspension during co-incubation. Cell-in-cell structures were also detected in most of the tissue samples. Early T stages and increasingly advanced N and M stages have correspondingly lower rates of cell-in-cell structures. Non-professional phagocytosis was also present in normal skin tissue. Non-professional phagocytosis appears to be a ubiquitous mechanism in malignant melanoma. The absence of phagocytosis in metastases may be one reason for the high rate of metastasis in malignant melanoma.
EVALuna2:539840

Novel diagnostic and therapeutic techniques reveal changed metabolic profiles in recurrent focal segmental glomerulosclerosis - Müller-Deile, Janina; Sarau, George; Kotb, Ahmed M.; Jaremenko, Christian; Rolle-Kampczyk, Ulrike E.; Daniel, Christoph; Kalkhof, Stefan; Christiansen, Silke H.; Schiffer, Mario (Scientific Reports, 2021)
Idiopathic forms of Focal Segmental Glomerulosclerosis (FSGS) are caused by circulating permeability factors, which can lead to early recurrence of FSGS and kidney failure after kidney transplantation. In the past three decades, many research endeavors were undertaken to identify these unknown factors. Even though some potential candidates have been recently discussed in the literature, “the” actual factor remains elusive. Therefore, there is an increased demand in FSGS research for the use of novel technologies that allow us to study FSGS from a yet unexplored angle. Here, we report the successful treatment of recurrent FSGS in a patient after living-related kidney transplantation by removal of circulating factors with CytoSorb apheresis. Interestingly, the classical published circulating factors were all in normal range in this patient but early disease recurrence in the transplant kidney and immediate response to CytoSorb apheresis were still suggestive for pathogenic circulating factors. To proof the functional effects of the patient’s serum on podocytes and the glomerular filtration barrier we used a podocyte cell culture model and a proteinuria model in zebrafish to detect pathogenic effects on the podocytes actin cytoskeleton inducing a functional phenotype and podocyte effacement. We then performed Raman spectroscopy in the < 50 kDa serum fraction, on cultured podocytes treated with the FSGS serum and in kidney biopsies of the same patient at the time of transplantation and at the time of disease recurrence. The analysis revealed changes in podocyte metabolome induced by the FSGS serum as well as in focal glomerular and parietal epithelial cell regions in the FSGS biopsy. Several altered Raman spectra were identified in the fractionated serum and metabolome analysis by mass spectrometry detected lipid profiles in the FSGS serum, which were supported by disturbances in the Raman spectra. Our novel innovative analysis reveals changed lipid metabolome profiles associated with idiopathic FSGS that might reflect a new subtype of the disease.
CRIS-Team Scopus Importer:2021-03-19

Novel Heritable Human COSMC Mutation Results in a Multisystemic Chaperonopathy - Aryal, Rajindra P.; Erger, Florian; Reusch, Bjoern; Matsumoto, Yasuyuki; Meyer, Robert; Zeng, Junwei; Knopp, Cordula; Noel, Maxence; Wenzel, Andrea; Kohl, Stefan; Tschernoster, Nikolai; Rappl, Gunter; et al. (GLYCOBIOLOGY, 2022)
CRIS-Team WoS Importer:2022-12-02

Novel PGS/PCL electrospun fiber mats with patterned topographical features for cardiac patch applications - Tallawi, Marwa; Dippold, Dirk; Rai, Ranjana; D'Atri, D.; Roether, Judith; Schubert, Dirk W.; Rosellini, E.; Engel, Felix; Boccaccini, Aldo R. (Materials Science and Engineering C, 2016)
Nano- and micro-scale topographical features play a critical role in the induction and maintenance of various cellular properties and functions, including morphology, adhesion, gene regulation, and cell-to-cell communication. In addition, recent studies have indicated that the structure and function of heart tissue are also sensitive to mechanical cues at the nano- and micro-scale. Although fabrication methods exist for generating topographical features on polymeric scaffolds for cell culture, current techniques, especially those with nano-scale resolution, are typically complex, prohibitively expensive and not accessible to most biology laboratories. Here, we present a simple and tunable fabrication method for the production of patterned electrospun fibers that simulate the complex anisotropic and multi-scale architecture of cardiac tissue, to promote cardiac cell alignment. This method is based on the combination of electrospinning and soft lithography techniques, in which electrospun fibers, based on a blend of poly(glycerol sebacate) and poly(caprolactone), were collected on a patterned Teflon-coated silicon wafer with imprinted topographical features. Different surface topographies were investigated, such as squares and grooves, with constant or different interspatial distances. In vitro cell culture studies successfully demonstrated the alignment of both C2C12 myoblasts and neonatal rat cardiomyocytes on fabricated electrospun patterned surfaces. C2C12 cells were cultured over a period of 72h to study the effect of topographical cues on cell morphology. Cells attached within the first 8h after seeding and after 24h most of the cells started to align responding to the topographical cues. Similarly, cardiomyocytes responded to the topographical features by aligning themselves and by expressing Connexin 43 along cellular junctions. Summarizing, we have developed a new method with the potential to significantly promote cardiac tissue engineering by fabricating electrospun fibers with defined topographical features to guide and instruct donor and/or host cells.
EVALuna:34665

Novel targets and future strategies for acute cardioprotection: Position Paper of the European Society of Cardiology Working Group on Cellular Biology of the Heart - Hausenloy, Derek J.; Garcia-Dorado, David; Botker, Hans Erik; Davidson, Sean M.; Downey, James; Engel, Felix; Jennings, Robert; Lecour, Sandrine; Leor, Jonathan; Madonna, Rosalinda; Ovize, Michel; Perrino, Cinzia; et al. (Cardiovascular Research, 2017)
Ischaemic heart disease and the heart failure that often results, remain the leading causes of death and disability in Europe and worldwide. As such, in order to prevent heart failure and improve clinical outcomes in patients presenting with an acute ST-segment elevation myocardial infarction and patients undergoing coronary artery bypass graft surgery, novel therapies are required to protect the heart against the detrimental effects of acute ischaemia/reperfusion injury (IRI). During the last three decades, a wide variety of ischaemic conditioning strategies and pharmacological treatments have been tested in the clinic-however, their translation from experimental to clinical studies for improving patient outcomes has been both challenging and disappointing. Therefore, in this Position Paper of the European Society of Cardiology Working Group on Cellular Biology of the Heart, we critically analyse the current state of ischaemic conditioning in both the experimental and clinical settings, provide recommendations for improving its translation into the clinical setting, and highlight novel therapeutic targets and new treatment strategies for reducing acute myocardial IRI.
EVALuna2:25533

Novel T cell/organoid culture system allows ex vivo modeling of intestinal graft-versus-host disease - Matthe, Diana; Dinkel, Martin; Schmid, Benjamin; Vogler, Tina; Neurath, Markus; Poeck, Hendrik; Neufert, Clemens; Büttner-Herold, Maike; Hildner, Kai (Frontiers in Immunology, 2023)
Acute graft-versus-host disease (GvHD) remains the biggest clinical challenge and prognosis-determining complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Donor T cells are acceptedly key mediators of alloreactivity against host tissues and here especially the gut. In support of previous studies, we found that the intestinal intra-epithelial lymphocyte (IEL) compartment was dynamically regulated in the course of MHC class I full mismatch allo-HSCT. However, while intestinal epithelial cell (IEC) damage endangers the integrity of the intestinal barrier and is a core signature of intestinal GvHD, the question whether and to what degree IELs are contributing to IEC dysregulation is poorly understood. To study lymphoepithelial interaction, we employed a novel ex vivo T cell/organoid co-culture model system. Here, allogeneic intra-epithelial T cells were superior in inducing IEC death compared to syngeneic IEL and allogeneic non-IEL T cells. The ability to induce IEC death was predominately confined to TCRβ+ T cells and was executed in a largely IFNγ-dependent manner. Alloreactivity required a diverse T cell receptor (TCR) repertoire since IELs genetically modified to express a TCR restricted to a single, non-endogenous antigen failed to mediate IEC pathology. Interestingly, minor histocompatibility antigen (miHA) mismatch was sufficient to elicit IEL-driven IEC damage. Finally, advanced live cell imaging analyses uncovered that alloreactive IELs patrolled smaller areas within intestinal organoids compared to syngeneic controls, indicating their unique migratory properties within allogeneic IECs. Together, we provide here experimental evidence for the utility of a co-culture system to model the cellular and molecular characteristics of the crosstalk between IELs and IEC in an allogeneic setting ex vivo. In the light of the emerging concept of dysregulated immune-epithelial homeostasis as a core aspect of intestinal GvHD, this approach represents a novel experimental system to e.g. screen therapeutic strategies for their potential to normalize T cell/IEC- interaction. Hence, analyses in pre-clinical in vivo allo-HSCT model systems may be restricted to hereby positively selected, promising approaches.
CRIS-Team Scopus Importer:2023-09-22
Keywords: allogeneic hematopoietic stem cell transplantation; alloreactive T cell; epithelial cell death; ex vivo model; graft-versus-host disease; GvHD; intestinal organoids; intraepithelial lymphocytes

Novel therapeutic strategies for cardioprotection - Sluijter, Joost P. G.; Condorelli, Gianluigi; Davidson, Sean M.; Engel, Felix; Ferdinandy, Peter; Hausenloy, Derek J.; Lecour, Sandrine; Madonna, Rosalinda; Ovize, Michel; Ruiz-Meana, Marisol; Schulz, Rainer; Van Laake, Linda W. (Pharmacology & Therapeutics, 2014)
The morbidity and mortality from ischemic heart disease (IHD) remain significant worldwide. The treatment for acute myocardial infarction has improved over the past decades, including early reperfusion of occluded coronary arteries. Although it is essential to re-open the artery as soon as possible, paradoxically this leads to additional myocardial injury, called acute ischemia-reperfusion injury (IRI), for which currently no effective therapy is available. Therefore, novel therapeutic strategies are required to protect the heart from acute IRI in order to reduce myocardial infarction size, preserve cardiac function and improve clinical outcomes in patients with IHD. In this review article, we will first outline the pathophysiology of acute IRI and review promising therapeutic strategies for cardioprotection. These include novel aspects of mitochondrial function, epigenetics, circadian clocks, the immune system, microvesicles, growth factors, stem cell therapy and gene therapy. We discuss the therapeutic potential of these novel cardioprotective strategies in terms of pharmacological targeting and clinical application.
EVALuna2:25465

Oat1/3 restoration protects against renal damage after ischemic AKI - Schneider, R.; Meusel, M.; Betz, B.; Held, C.; Moeller-Ehrlich, K.; Buettner-Herold, M.; Wanner, C.; Gekle, M.; Sauvant, C. (American Journal of Physiology-Renal Physiology, 2015)
Expression of proximal tubular organic anion transporters Oat1 and Oat3 is reduced by PGE2 after renal ischemia and reperfusion (I/R) injury. We hypothesized that impaired expression of Oat1/3 is decisively involved in the deterioration of renal function after I/R injury. Therefore, we administered probenecid, which blocks proximal tubular indomethacin uptake, to abolish the indomethacin-mediated restoration of Oat1/3 regulation and its effect on renal functional and morphological outcome. Ischemic acute kidney injury (iAKI) was induced in rats by bilateral clamping of renal arteries for 45 min with 24-h follow-up. Low-dose indomethacin (1 mg/kg) was given intraperitoneally (ip) at the end of ischemia. Probenecid (50 mg/kg) was administered ip 20 min later. Indomethacin restored the expression of Oat1/3, PAH net secretion, and PGE2 clearance. Additionally, indomethacin improved kidney function as measured by glomerular filtration rate (GFR), renal perfusion as determined by corrected PAH clearance, and morphology, whereas it reduced renal cortical apoptosis and nitric oxide production. Notably, indomethacin did not affect inflammation parameters in the kidneys (e.g., monocyte chemoattractant protein-1, ED1+ cells). On the other hand, probenecid blocked the indomethacin-induced restoration of Oat1/3 and moreover abrogated all beneficial effects. Our study indicates that the beneficial effect of low-dose indomethacin in iAKI is not due to its anti-inflammatory potency, but in contrast to its restoration of Oat1/3 expression and/or general renal function. Inhibition of proximal tubular indomethacin uptake abrogates the beneficial effect of indomethacin by resetting the PGE2-mediated Oat1/3 impairment, thus reestablishing renal damage. This provides evidence for a mechanistic effect of Oat1/3 in a new model of the induction of renal damage after iAKI.
EVALuna2:25476

Obligatory role for GPER in cardiovascular aging and disease - Meyer, Matthias R.; Fredette, Natalie C.; Daniel, Christoph; Sharma, Geetanjali; Amann, Kerstin Ute; Arterburn, Jeffrey B.; Barton, Matthias; Prossnitz, Eric R. (Science Signaling, 2016)
Pharmacological activation of the heptahelical G protein-coupled estrogen receptor (GPER) by selective ligands counteracts multiple aspects of cardiovascular disease. We thus expected that genetic deletion or pharmacological inhibition of GPER would further aggravate such disease states, particularly with age. To the contrary, we found that genetic ablation of Gper in mice prevented cardiovascular pathologies associated with aging by reducing superoxide (?O2(-)) formation by NADPH oxidase (Nox) specifically through reducing the expression of the Nox isoform Nox1 Blocking GPER activity pharmacologically with G36, a synthetic, small-molecule, GPER-selective blocker (GRB), decreased Nox1 abundance and ?O2(-) production to basal amounts in cells exposed to angiotensin II and in mice chronically infused with angiotensin II, reducing arterial hypertension. Thus, this study revealed a role for GPER activity in regulating Nox1 abundance and associated ?O2(-)-mediated structural and functional damage that contributes to disease pathology. Our results indicated that GRBs represent a new class of drugs that can reduce Nox abundance and activity and could be used for the treatment of chronic disease processes involving excessive ?O2(-) formation, including arterial hypertension and heart failure.
EVALuna2:25526

Only IF/TA in the Histological Evaluation of Post-Reperfusion Baseline Biopsies Correlates With Kidney Transplant Outcome. - Bachmann, Quirin; Torrez, Carlos; Büttner-Herold, Maike; Haller, Bernhard; Haberfellner, Flora; Hausinger, Renate; Assfalg, Volker; Renders, Lutz; Amann, Kerstin Ute; Heemann, Uwe; Schmaderer, Christoph; Kemmner, Stephan (Transplant International, 2025)
Here, we retrospectively evaluated the informational yield of 338 post-reperfusion kidney transplant biopsies (including 95 living donations) assessed according to BANFF for the histological characteristics interstitial fibrosis and tubular atrophy (IF/TA), glomerulosclerosis, arteriosclerosis, and acute tubular injury (ATI). Associations with delayed graft function (DGF) and death-censored graft survival were explored through Cox-regression analyses. The maximum follow-up time was 11.4 years, with DGF observed in 108 (32%) cases. After deceased donation there was no association between DGF and histologic parameters. Univariable Cox-regression unveiled an association of IF/TA and glomerulosclerosis with long-term death-censored graft survival (HR per 10% increase: IF/TA 1.63; 95% CI 1.17-2.28; p = 0.003; glomerulosclerosis 1.19; 95% CI 1.01-1.39; p = 0.031). In multivariable Cox regression analyses, adjusted for recognized clinical risk variables like expanded criteria donor-status, donor age, history of diabetes, and HLA-mismatches, only IF/TA maintained association over the total observation period in deceased donations and in the total cohort. Arteriosclerosis and ATI were not associated with clinical outcome after deceased donation. Especially ATI did not affect delayed graft function if only deceased donations were considered. Our data underlines the role of organ quality for transplant outcome prior to acute lesions such as ATI during the transplantation process.
EVALuna2:583979

On the representation of cells in bone marrow pathology by a scalar field: propagation through serial sections, co-localization and spatial interaction analysis - Weis, Cleo-Aron; Griessmann, Benedict Walter; Scharff, Christoph; Detzner, Caecilia; Pfister, Eva; Marx, Alexander; Zoellner, Frank Gerrit (Diagnostic Pathology, 2015)
Immunohistochemical analysis of cellular interactions in the bone marrow in situ is demanding, due to its heterogeneous cellular composition, the poor delineation and overlap of functional compartments and highly complex immunophenotypes of several cell populations (e.g. regulatory T-cells) that require immunohistochemical marker sets for unambiguous characterization. To overcome these difficulties, we herein present an approach to describe objects (e.g. cells, bone trabeculae) by a scalar field that can be propagated through registered images of serial histological sections.The transformation of objects within images (e.g. cells) to a scalar field was performed by convolution of the object's centroids with differently formed radial basis function (e.g. for direct or indirect spatial interaction). On the basis of such a scalar field, a summation field described distributed objects within an image.After image registration i) colocalization analysis could be performed on basis scalar field, which is propagated through registered images, and - due to the shape of the field - were barely prone to matching errors and morphological changes by different cutting levels; ii) furthermore, depending on the field shape the colocalization measurements could also quantify spatial interaction (e.g. direct or paracrine cellular contact); ii) the field-overlap, which represents the spatial distance, of different objects (e.g. two cells) could be calculated by the histogram intersection.The description of objects (e.g. cells, cell clusters, bone trabeculae etc.) as a field offers several possibilities: First, co-localization of different markers (e.g. by immunohistochemical staining) in serial sections can be performed in an automatic, objective and quantifiable way. In contrast to multicolour staining (e.g. 10-colour immunofluorescence) the financial and technical requirements are fairly minor. Second, the approach allows searching for different types of spatial interactions (e.g. direct and indirect cellular interaction) between objects by taking field shape into account (e.g. thin vs. broad). Third, by describing spatially distributed groups of objects as summation field, it gives cluster definition that relies rather on the bare object distance than on the modelled spatial cellular interaction.
EVALuna2:25518

Organ manifestations of COVID-19: what have we learned so far (not only) from autopsies? - Jonigk, Danny; Werlein, Christopher; Acker, Till; Aepfelbacher, Martin; Amann, Kerstin Ute; Baretton, Gustavo; Barth, Peter; Bohle, Rainer M.; Buettner, Andreas; Buettner, Reinhard; Dettmeyer, Reinhard; Eichhorn, Philip; et al. (Virchows Archiv, 2022)
The use of autopsies in medicine has been declining. The COVID-19 pandemic has documented and rejuvenated the importance of autopsies as a tool of modern medicine. In this review, we discuss the various autopsy techniques, the applicability of modern analytical methods to understand the pathophysiology of COVID-19, the major pathological organ findings, limitations or current studies, and open questions. This article summarizes published literature and the consented experience of the nationwide network of clinical, neuro-, and forensic pathologists from 27 German autopsy centers with more than 1200 COVID-19 autopsies. The autopsy tissues revealed that SARS-CoV-2 can be found in virtually all human organs and tissues, and the majority of cells. Autopsies have revealed the organ and tissue tropism of SARS-CoV-2, and the morphological features of COVID-19. This is characterized by diffuse alveolar damage, combined with angiocentric disease, which in turn is characterized by endothelial dysfunction, vascular inflammation, (micro-) thrombosis, vasoconstriction, and intussusceptive angiogenesis. These findings explained the increased pulmonary resistance in COVID-19 and supported the recommendations for antithrombotic treatment in COVID-19. In contrast, in extra-respiratory organs, pathological changes are often nonspecific and unclear to which extent these changes are due to direct infection vs. indirect/secondary mechanisms of organ injury, or a combination thereof. Ongoing research using autopsies aims at answering questions on disease mechanisms, e.g., focusing on variants of concern, and future challenges, such as post-COVID conditions. Autopsies are an invaluable tool in medicine and national and international interdisciplinary collaborative autopsy-based research initiatives are essential.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Acute kidney damage; Diffuse alveolar damage; Immune response; SARS-CoV-2

Osteoclastic expression of higher-level regulators NFATc1 and BCL6 in medication-related osteonecrosis of the jaw secondary to bisphosphonate therapy: a comparison with osteoradionecrosis and osteomyelitis - Wehrhan, Falk; Gross, Christian; Creutzburg, Kay; Amann, Kerstin Ute; Ries, Jutta; Kesting, Marco Rainer; Geppert, Carol-Immanuel; Weber, Manuel (Journal of Translational Medicine, 2019)
BackgroundWith an increasing indication spectrum of antiresorptive drugs, the medication-related osteonecrosis of the jaw secondary to bisphosphonate therapy [MRONJ (BP)] is continuously gaining clinical relevance. Impaired osteoclast function, accompanied by altered cell morphology and expression of osteoclastic effector proteins, contributes to the pathogenesis of MRONJ (BP). However, the underlying regulatory mechanisms at a transcriptional level are unaddressed so far. These mechanisms are crucial to the development of disease-characteristic osteoclastic anomalies, that contribute to the pathogenesis of MRONJ (BP). NFATc1 is considered a master upstream osteoclastic activator, whereas BCL6 acts as osteoclastic suppressor. The present study aimed to elucidate the NFATc1 and BCL6 mediated osteoclastic regulation and activity in MRONJ (BP) compared to osteoradionecrosis (ORN) and osteomyelitis (OM) and normal jaw bone.MethodsFormalin-fixed jaw bone specimens from 70 patients [MRONJ (BP) n=30; OM: n=15, ORN: n=15, control: n=10] were analyzed retrospectively for osteoclast expression of NFATc1 and BCL6. The specimens were processed for H&E staining and immunohistochemistry. The histological sections were digitalized and analyzed by virtual microscopy.ResultsOsteoclastic expression of NFATc1 and BCL6 was significantly higher in MRONJ (BP) specimens compared to OM and control specimens. NFATc1 and BCL6 labeling indices revealed no significant differences between MRONJ (BP) and ORN. The ratio of nuclear BCL6+ osteoclasts to cytoplasmic BCL6+ osteoclasts revealed significantly higher values for MRONJ (BP) specimens compared to OM and controls.ConclusionThis study displays that osteoclasts in MRONJ (BP) tissues feature increased expression of the higher-level regulators, paradoxically of both NFATc1 and BCL6. These observations can help to explain the genesis of morphologically altered and resorptive inactive osteoclasts in MRONJ (BP) tissues by outlining the transcriptional regulation of the pathomechanically relevant osteoclastic effector proteins. Furthermore, they strengthen the etiological delineation of MRONJ (BP) from OM and extend the osteoclast profiles of MRONJ (BP), OM and ORN and thus could lead to a better histopathological differentiation that can improve treatment decision and motivate new therapeutic concepts.
CRIS-Team WoS Importer:2019-03-20

Osteoclast profile of medication-related osteonecrosis of the jaw secondary to bisphosphonate therapy: a comparison with osteoradionecrosis and osteomyelitis - Gross, Christian; Weber, Manuel; Creutzburg, Kay; Moebius, Patrick; Preidl, Raimund; Amann, Kerstin Ute; Wehrhan, Falk (Journal of Translational Medicine, 2017)
The medication-related osteonecrosis of the jaw secondary to bisphosphonate therapy [MRONJ (BP)] is characterized by non-healing exposed bone in the maxillofacial region. The pathogenesis of MRONJ (BP) is not fully understood. Giant, hypernucleated, inactive osteoclasts were found in MRONJ (BP) tissues, which indicated that accelerated cell-cell fusion might play a role. Dendritic cell-specific transmembrane protein (DC-STAMP) is associated with the cell-cell fusion of osteoclasts and precursor cells. Tartrate-resistant acid phosphatase (TRAP) is essential for osteoclastic bone resorption. The cell-cell fusion, as part of the osteoclastogenesis, and the resorptive activity can determine the morphology of osteoclasts. This study analyzed jaw bone from patients with MRONJ (BP), osteomyelitis (OM) and osteoradionecrosis (ORN) because a comparison with the osteoclast profiles of OM and ORN is essential for characterizing the osteoclast profile of MRONJ (BP).Formalin-fixed routine jaw bone specimens from 70 patients [MRONJ (BP) n = 30; OM: n = 15, ORN: n = 15, control: n = 10] were analyzed retrospectively for osteoclast quantity, morphology and the expression of TRAP and DC-STAMP. The specimens were processed for hematoxylin and eosin staining (H&E), histochemistry (TRAP) and immunohistochemistry (anti-DC-STAMP) and were analyzed via virtual microscopy.The quantity, diameter and nuclearity of osteoclasts were significantly higher in MRONJ (BP) specimens than in OM, ORN and control specimens. Giant, hypernucleated osteoclasts were detected in MRONJ (BP) specimens only. Osteoclastic TRAP expression was lower in MRONJ (BP) and ORN specimens than in OM and control specimens. The DC-STAMP expression of osteoclasts and mononuclear cells was significantly higher in MRONJ (BP) and ORN specimens than in OM and control specimens.This study indicates that the osteoclast profile of MRONJ (BP) is characterized by osteoclast inactivation and a high cell-cell fusion rate; however, the presence of giant, hypernucleated osteoclasts cannot be attributed to increased DC-STAMP-triggered cell-cell fusion alone. The incidental characterization of the osteoclast profiles of OM and ORN revealed differences that might facilitate the histopathological differentiation of these diseases from MRONJ (BP), which is essential because their therapies are somewhat different.
EVALuna2:24432

Osteo-radio-necrosis (ORN) and bisphosphonate-related osteonecrosis of the jaws (BRONJ): the histopathological differences under the clinical similarities - Mitsimponas, Konstantinos; Moebius, Patrick; Amann, Kerstin Ute; Stockmann, Philipp; Schlegel, Karl-Andreas; Neukam, Friedrich Wilhelm; Wehrhan, Falk (International Journal of Clinical and Experimental Pathology, 2014)
Both Osteoradionecrosis (ORN) and Bisphosphonate associated osteonecrosis of the jaws (BRONJ) present clinically as regions of exposed necrotic bone. The study aimed to demonstrate the histopathological differences behind the observed clinical similarities.Ten ORN specimens and ten BRONJ specimens were used, as well as ten samples of normal mandibular bone as control. Two bone-specific stainings were used, i.e. Sirius Red for the study of the relative presence of collagen types I and III and toluidine blue for the study the osteon density.The Red Green Blue (RGB)-analysis of the specimens stained with Sirius Red identified significant differences between the chromatic patterns observed in bone preparations of patients suffering from ORN when compared to both BRONJ and control samples. Moreover, the osteon density of the BRONJ samples was significantly lower when compared to ORN and normal bone samples.The demonstrated differences in the bone architecture and in the bone collagen content between the two pathological conditions most likely reflect underlying pathophysiological differences.
EVALuna2:24379

Oxalate-induced chronic kidney disease with its uremic and cardiovascular complications in C57BL/6 mice - Mulay, Shrikant R.; Eberhard, Jonathan N.; Pfann, Victoria; Marschner, Julian A.; Darisipudi, Murthy N.; Daniel, Christoph; Romoli, Simone; Desai, Jyaysi; Grigorescu, Melissa; Kumar, Santhosh V.; Rathkolb, Birgit; Wolf, Eckhard; et al. (American Journal of Physiology-Renal Physiology, 2016)
Chronic kidney disease (CKD) research is limited by the lack of convenient inducible models mimicking human CKD and its complications in experimental animals. We demonstrate that a soluble oxalate-rich diet induces stable stages of CKD in male and female C57BL/6 mice. Renal histology is characterized by tubular damage, remnant atubular glomeruli, interstitial inflammation, and fibrosis, with the extent of tissue involvement depending on the duration of oxalate feeding. Expression profiling of markers and magnetic resonance imaging findings established to reflect inflammation and fibrosis parallel the histological changes. Within 3 wk, the mice reproducibly develop normochromic anemia, metabolic acidosis, hyperkalemia, FGF23 activation, hyperphosphatemia, and hyperparathyroidism. In addition, the model is characterized by profound arterial hypertension as well as cardiac fibrosis that persist following the switch to a control diet. Together, this new model of inducible CKD overcomes a number of previous experimental limitations and should serve useful in research related to CKD and its complications.
EVALuna2:3844

Oxidative DNA Damage in Kidneys and Heart of Hypertensive Mice Is Prevented by Blocking Angiotensin II and Aldosterone Receptors - Brand, Susanne; Amann, Kerstin Ute; Mandel, Philipp; Zimnol, Anna; Schupp, Nicole (PLoS ONE, 2014)
Recently, we could show that angiotensin II, the reactive peptide of the blood pressure-regulating renin-angiotensin-aldosterone-system, causes the formation of reactive oxygen species and DNA damage in kidneys and hearts of hypertensive mice. To further investigate on the one hand the mechanism of DNA damage caused by angiotensin II, and on the other hand possible intervention strategies against end-organ damage, the effects of substances interfering with the renin-angiotensin-aldosterone-system on angiotensin II-induced genomic damage were studied.In C57BL/6-mice, hypertension was induced by infusion of 600 ng/kg o min angiotensin II. The animals were additionally treated with the angiotensin II type 1 receptor blocker candesartan, the mineralocorticoid receptor blocker eplerenone and the antioxidant tempol. DNA damage and the activation of transcription factors were studied by immunohistochemistry and protein expression analysis.Administration of angiotensin II led to a significant increase of blood pressure, decreased only by candesartan. In kidneys and hearts of angiotensin II-treated animals, significant oxidative stress could be detected (1.5-fold over control). The redox-sensitive transcription factors Nrf2 and NF-?B were activated in the kidney by angiotensin II-treatment (4- and 3-fold over control, respectively) and reduced by all interventions. In kidneys and hearts an increase of DNA damage (3- and 2-fold over control, respectively) and of DNA repair (3-fold over control) was found. These effects were ameliorated by all interventions in both organs. Consistently, candesartan and tempol were more effective than eplerenone.Angiotensin II-induced DNA damage is caused by angiotensin II type 1 receptor-mediated formation of oxidative stress in vivo. The angiotensin II-mediated physiological increase of aldosterone adds to the DNA-damaging effects. Blocking angiotensin II and mineralocorticoid receptors therefore has beneficial effects on end-organ damage independent of blood pressure normalization.
EVALuna2:25417

P2Y1 gene deficiency protects from renal disease progression and capillary rarefaction during passive crescentic glomerulonephritis - Hohenstein, Bernd; Renk, Sindy; Lang, Kathrin; Daniel, Christoph; Freund, Monique; Léon, Catherine; Amann, Kerstin Ute; Gachet, Christian; Hugo, Christian (Journal of the American Society of Nephrology, 2007)
The metabotropic receptor P2Y1 is necessary for full ADP-induced platelet activation and is localized on various intrinsic renal cells, including mesangial cells, podocytes, and endothelial cells. To date, nothing is known about the role of the P2Y1 receptor during inflammatory renal disease. The role of the P2Y1 receptor was investigated using 22 P2Y1 gene-deficient (-/-) and 27 wild-type (wt) mice during the time course of passive crescentic nephrotoxic glomerulonephritis. Six P2Y1 -/- and six wt mice served as undiseased controls. Renal tissues were harvested on days 1, 10, and 28 after disease induction. No renal phenotype was found in P2Y1 -/- versus wt mice. In contrast, during crescentic glomerulonephritis, approximately 50% of all wt mice died, whereas all P2Y1 -/- mice survived. Renal function as assessed by creatinine clearance measurements, glomerulosclerosis, and tubulointerstitial injury indices as well as glomerular and interstitial matrix expansion were improved significantly in P2Y1 -/- compared with wt mice. These changes were preceded by reduced glomerular and peritubular capillary rarefaction indices in P2Y1 -/- compared with wt mice. The alteration of the rates of both peritubular apoptosis and endothelial cell proliferation suggests improved capillary preservation in P2Y1 -/- mice early in disease (day 10) and an additional enhanced repair reaction in P2Y1 -/- mice at the late time point (day 28), whereas injury on day 1 seemed to be equivalent in both groups. It is concluded that loss of P2Y1 receptor function safeguards against capillary loss, fibrosis, and death by renal failure during experimental crescentic glomerulonephritis. Copyright © 2007 by the American Society of Nephrology.
Created from Fastlane, Scopus look-up

P2Y2R and Cyst Growth in Polycystic Kidney Disease. - Kraus, Andre; Skoczynski, Kathrin; Brötsch, Martin; Burzlaff, Nicolai; Leipziger, Jens; Schiffer, Mario; Büttner-Herold, Maike; Buchholz, Björn (Journal of the American Society of Nephrology, 2024)
EVALuna2:569374

Pals1 Haploinsufficiency Results in Proteinuria and Cyst Formation - Weide, Thomas; Vollenbroeker, Beate; Schulze, Ulf; Djuric, Ivona; Edeling, Maria; Bonse, Jakob; Hochapfel, Florian; Panichkina, Olga; Wennmann, Dirk-Oliver; George, Britta; Kim, Seonhee; Daniel, Christoph; et al. (Journal of the American Society of Nephrology, 2017)
The nephron is the basic physiologic subunit of the mammalian kidney and is made up of several apicobasally polarized epithelial cell types. The process of apicobasal polarization in animal cells is controlled by the evolutionarily conserved Crumbs (CRB), Partitioning-defective, and Scribble protein complexes. Here, we investigated the role of protein associated with LIN-7 1 (Pals1, also known as Mpp5), a core component of the apical membrane-determining CRB complex in the nephron. Pals1 interacting proteins, including Crb3 and Wwtr1/Taz, have been linked to renal cyst formation in mice before. Immunohistologic analysis revealed Pals1 expression in renal tubular cells and podocytes of human kidneys. Mice lacking one Pals1 allele (functionally haploid for Pals1) in nephrons developed a fully penetrant phenotype, characterized by cyst formation and severe defects in renal barrier function, which led to death within 6-8 weeks. In Drosophila nephrocytes, deficiency of the Pals1 ortholog caused alterations in slit-diaphragm-like structures. Additional studies in epithelial cell culture models revealed that Pals1 functions as a dose-dependent upstream regulator of the crosstalk between Hippo- and TGF-?-mediated signaling. Furthermore, Pals1 haploinsufficiency in mouse kidneys associated with the upregulation of Hippo pathway target genes and marker genes of TGF-? signaling, including biomarkers of renal diseases. These findings support a link between apical polarity proteins and renal diseases, especially renal cyst diseases. Further investigation of the Pals1-linked networks is required to decipher the mechanisms underlying the pathogenesis of these diseases.
EVALuna2:25537

Pancreas transplantation—clinic, technique, and histological assessment Pankreastransplantation – Klinik, Technik und histologische Beurteilung - Büttner-Herold, Maike; Amann, Kerstin Ute; Pfister, Frederick; Tannapfel, Andrea; Maslova, Marina; Wunsch, Andreas; Pillokeit, Nina; Viebahn, Richard; Schenker, Peter (Pathologe, 2021)
Background: In Germany pancreas transplants are performed in only a few selected and specialized centres, usually combined with a kidney transplant. Knowlegde of the indications for and techniques of transplantation as well as of the histopathological assessment for rejection in pancreas and duodenal biopsies is not very widespread. Aim: To give an overview of the development and status quo in pancreas-kidney-transplantation in Germany summarizing the experience of the largest German pancreas transplant centre and to give a résumé of the results of histological diagnoses of biopsy specimens submitted between 06/2017 and 12/2020. Moreover, a detailed description and illustration of histological findings is included. Material and Methods: A thorough literature search for aspects of the history, technique and indication for pancreas transplantation was performed and discussed in the context of the local experience and technical particularities specific for the transplant centre in Bochum. The occurrence of complications was compared with international reports. Results of pancreas and duodenal biopsies submitted to Erlangen between 06/2017 and 12/2020 for histological evaluation, which were evaluated according to the Banff classification, were summarized. For a better understanding key histological findings of pancreas rejection and differential diagnoses were illustrated and discussed. Results: A total of 93 pancreas transplant specimens and 3 duodenal biopsies were included. 34.4% of pancreas specimens did not contain representative material for a diagnosis. In the remaining 61 biopsies 24.6% showed no rejection, 62.3% were diagnosed with acute T-cell mediated rejection (TCMR) and 8.2% with signs suspicious of antibody-mediated rejection (ABMR). Acute acinary epithelial injury was seen in 59%, pancreatitis in 8.2% and allograft fibrosis was reported in as many as 54.1%. Calcineurin-inhibitor toxicity was discussed in only 4.9%. Conclusion: Pancreas-kidney-transplantation and standardized histological assessment of the transplanted pancreas or rarely duodenum with reporting according to the updated Banff classification of pancreas transplants or previous reports of duodenal rejection are important mainstays in the management of patients with diabetes.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Biopsy; Diabetes mellitus; Duodenum; Histology; Kidney transplantation

Paraproteinemia and renal involvement - Rupprecht, Harald; Amann, Kerstin Ute (Die Nephrologie, 2022)
Renal manifestations in patients with monoclonal paraproteinemia are frequent. Cast nephropathy is a disease that only occurs in manifest multiple myeloma with a high tumor burden. In contrast, monoclonal gammopathy of renal significance (MGRS) is defined as renal involvement due to a nephrotoxic clone that from a hematological standpoint would per se not require treatment. The diagnosis of MGRS can only be made by renal biopsy. Here monotypic immunoglobulin (Ig) deposits can be found in either organized (amyloidosis, fibrillary glomerulonephritis, GN, immunotactoid GN, cryoglobulinemic GN) or nonorganized forms (monoclonal Ig deposition disease, proliferative GN with monoclonal Ig deposits). There are two forms of MGRS that can occur without the deposition of Ig, namely C3 glomerulopathy and thrombotic microangiopathy. For cast nephropathy there is always a fundamental indication for chemotherapy. The data on mechanical elimination of light chains by plasmapheresis or high cut-off dialysis are inconsistent. In patients with MGRS the indications for treatment must be made based on the renal prognosis in a cooperation between nephrologists and hematologists. Only a clone-directed treatment can lead to an improvement of renal function.
CRIS-Team WoS Importer:2022-12-16

Patient-derived zebrafish xenografts of uveal melanoma reveal ferroptosis as a drug target - Groenewoud, Arwin; Yin, Jie; Gelmi, Maria Chiara; Alsafadi, Samar; Nemati, Fariba; Decaudin, Didier; Roman-Roman, Sergio; Kalirai, Helen; Coupland, Sarah E.; Jochemsen, Aart G.; Jager, Martine J.; Engel, Felix; et al. (Cell Death Discovery, 2023)
Uveal melanoma (UM) has a high risk to progress to metastatic disease with a median survival of 3.9 months after metastases detection, as metastatic UM responds poorly to conventional and targeted chemotherapy and is largely refractory to immunotherapy. Here, we present a patient-derived zebrafish UM xenograft model mimicking metastatic UM. Cells isolated from Xmm66 spheroids derived from metastatic UM patient material were injected into 2 days-old zebrafish larvae resulting in micro-metastases in the liver and caudal hematopoietic tissue. Metastasis formation could be reduced by navitoclax and more efficiently by the combinations navitoclax/everolimus and flavopiridol/quisinostat. We obtained spheroid cultures from 14 metastatic and 10 primary UM tissues, which were used for xenografts with a success rate of 100%. Importantly, the ferroptosis-related genes GPX4 and SLC7A11 are negatively correlated with the survival of UM patients (TCGA: n = 80; Leiden University Medical Centre cohort: n = 64), ferroptosis susceptibility is correlated with loss of BAP1, one of the key prognosticators for metastatic UM, and ferroptosis induction greatly reduced metastasis formation in the UM xenograft model. Collectively, we have established a patient-derived animal model for metastatic UM and identified ferroptosis induction as a possible therapeutic strategy for the treatment of UM patients.
CRIS-Team Scopus Importer:2023-06-30

Patients with COVID-19: in the dark-NETs of neutrophils - Ackermann, Maximilian; Anders, Hans-Joachim; Bilyy, Rostyslav; Bowlin, Gary L.; Daniel, Christoph; De Lorenzo, Rebecca; Egeblad, Mikala; Henneck, Timo; Hidalgo, Andres; Hoffmann, Markus; Hohberger, Bettina; Kanthi, Yogendra; et al. (Cell Death and Differentiation, 2021)
SARS-CoV-2 infection poses a major threat to the lungs and multiple other organs, occasionally causing death. Until effective vaccines are developed to curb the pandemic, it is paramount to define the mechanisms and develop protective therapies to prevent organ dysfunction in patients with COVID-19. Individuals that develop severe manifestations have signs of dysregulated innate and adaptive immune responses. Emerging evidence implicates neutrophils and the disbalance between neutrophil extracellular trap (NET) formation and degradation plays a central role in the pathophysiology of inflammation, coagulopathy, organ damage, and immunothrombosis that characterize severe cases of COVID-19. Here, we discuss the evidence supporting a role for NETs in COVID-19 manifestations and present putative mechanisms, by which NETs promote tissue injury and immunothrombosis. We present therapeutic strategies, which have been successful in the treatment of immunο-inflammatory disorders and which target dysregulated NET formation or degradation, as potential approaches that may benefit patients with severe COVID-19.
CRIS-Team Scopus Importer:2021-06-04

PD-1 and PD-L1 expression predict regression and prognosis following neoadjuvant radiochemotherapy of oesophageal adenocarcinoma - Göbel, Holger H.; Distel, Luitpold; Aigner, Thomas; Büttner-Herold, Maike; Grabenbauer, Gerhard G. (Clinical and Translational Radiation Oncology, 2022)
Background and purpose: PD-1 and PD-L1 are involved in anticancer immunosurveillance, and their expression may be predictive for therapeutic effectiveness of specific antibodies. Their influence on response to neoadjuvant radiochemotherapy (RCT) and prognosis in patients with oesophageal adenocarcinoma (OAC) remains to be defined. Materials and methods: Between 10/2004 and 06/2018, complete pre-RCT biopsy-specimens were available from 76 patients with locally advanced, non-metastatic OAC scheduled for trimodality therapy. We evaluated intra- and peritumoural expression of CD8, PD-1 and PD-L1 in pre-treatment specimens to determine their influence on tumour regression grade and survival. PD-1 and PD-L1 expression were considered positive (+) if ≥1% of all cells were stained positive, otherwise negative (-); densities of CD8+ cells were categorized as being high (Hi) or low (Lo) according to the median. Results: A negative PD-L1 expression in peritumoural cells predicted a poor tumour regression (RD 0.24 [95% CI 0.03–0.44], p = 0.023). A positive PD-1 expression in intra- as well as peritumoural cells was identified as an unfavourable prognostic factor (HR 0.52 [95% CI 0.29–0.93], p = 0.028; HR 0.50 [0.25–0.99], p = 0.047, respectively). With respect to CD8+ infiltration, positive PD-1 and PD-L1 expressions attenuated its favourable prognostic effect in intratumoural area (LoCD8/PD1 + vs. HiCD8/PD1-: HR 0.25 [0.09–0.69], p = 0.007; LoCD8/PDL1+ vs. HiCD8/PDL1-: HR 0.32 [0.12–0.89], p = 0.028) and were associated with negative outcome when seen in peritumoural area (HiCD8/PD1+ vs. LoCD8/PD1-: HR 0.29 [0.11–0.74], p = 0.010); HiCD8/PDL1+ vs. LoCD8/PDL1-: HR 0.33 [0.12–0.90], p = 0.031). Conclusions: PD-1 and PD-L1 expression were identified to be of predictive and prognostic value in patients with OAC, particularly when considering CD8+ infiltration. Further validation by a large size dataset is required.
CRIS-Team Scopus Importer:2022-04-15
Keywords: CD8+; Esophageal adenocarcinoma; PD-1; PD-L1; Radiochemotherapy

PD1 expression and correlation with its ligands in oral cancer specimens and peripheral blood - Wehrhan, Falk; Weber, Manuel; Baran, Christoph; Agaimy, Abbas; Büttner-Herold, Maike; Kesting, Marco Rainer; Ries, Jutta (Journal of Cranio-Maxillofacial Surgery, 2021)
Objectives: This study analyzed the expression of the PD1 receptor in tumor tissue and peripheral blood of oral squamous cell carcinoma (OSCC) patients, and correlated it with the PD1 ligands PD-L1 and PD-L2. The currently low response rates of checkpoint inhibitor treatment in OSCC could be increased by a better understanding of immune checkpoint biology. Despite evidence in the literature for upregulation of PD1 checkpoint ligands in OSCC tissue, there has been no correlation analysis of the PD1 receptor with its ligands in tissue specimens and peripheral blood of OSCC patients.
CRIS-Team WoS Importer:2021-03-05

PDE-5 inhibition impedes TSP-1 expression, TGF-β activation and matrix accumulation in experimental glomerulonephritis - Hohenstein, Bernd; Daniel, Christoph; Wittmann, Sabine; Hugo, Christian (Nephrology Dialysis Transplantation, 2008)
Background. Matrix expansion and mesangial proliferation are hallmarks of mesangial proliferative glomerulonephritis. Specific inhibition of PDE-5, an enzyme catalyzing the intracellular degradation of cyclic GMP, can be achieved by the inhibitor vardenafil. In this study, we investigated the effects of PDE-5 inhibition in the anti-Thy1 model in the rat in vivo. Methods. After disease induction, rats received 10 mg/kg bw vardenafil twice a day via gavage. On Days 2 and 6, renal biopsies, as well as glomerular isolates, urine and blood samples were taken to compare vardenafil- and placebo-treated groups during the course of disease. Results. Small amounts of PDE-5 were detected in healthy kidneys, but induced in a typical mesangial pattern during disease (by IHC and WB). Specific PDE-5 inhibition resulted in increased glomerular levels of cGMP. Treated animals demonstrated inhibition of MC proliferation and matrix accumulation while renal function and influx of inflammatory cells were not affected. Due to PDE-5 inhibition, the endogenous TGF-β-activating protein TSP-1 and the TGF-β-signalling protein p-smad-2/3 were decreased suggesting this as an antifibrotic mechanism of action of vardenafil in this model. Conclusion. Considering the availability and safety profile of vardenafil, the beneficial antiproliferative and antifibrotic effect in experimental glomerulonephritis may potentially be applicable to the treatment of mesangial proliferative glomerulonephritis in man. © The Author [2008]. Published by Oxford University Press on behalf of ERA-EDTA. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Anti-Thy1 model; Matrix expansion; PDE-5 inhibition; TGF-β; TSP-1

PD-L1 expression in peripheral blood samples of patients with oral squamous cell carcinomas - Ries, Jutta; Weber, Manuel; Baran, Christoph; Agaimy, Abbas; Buettner-Herold, M.; Preidl, Raimund; Neukam, Friedrich Wilhelm; Wehrhan, Falk (2018)
EVALuna2:34230

PD-L1 is upregulated by radiochemotherapy in rectal adenocarcinoma patients and associated with a favourable prognosis - Hecht, Markus; Buettner-Herold, Maike; Erlenbach-Wuensch, Katharina; Haderlein, Marlen; Croner, Roland; Grützmann, Robert; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (European Journal of Cancer, 2016)
The influence of neoadjuvant radiochemotherapy (RCT) on programmed death-ligand 1 (PD-L1) expression, a predictive marker for programmed cell death protein 1 (PD-1) inhibitor therapy, was studied on tumour and inflammatory cells in rectal adenocarcinoma patients along with its prognostic value.PD-L1 immunohistochemistry was performed on tissue microarrays of 103 pre-RCT biopsies and 159 post-RCT surgical specimens (central tumour, invasive front and normal tissue) of 199 patients. In 63 patients, both samples were available. Proportion and maximum intensity of PD-L1-positive (PD-L1+) cells were evaluated.RCT increased the proportion of PD-L1-expressing cancer cells from 2.1% to 7.8% in the central tumour (p < 0.001) or 9.3% in the invasive front (p < 0.001). Cancer cell PD-L1 on its own could not predict prognosis. High PD-L1 expression on pre-RCT inflammatory cells (maximum intensity: p = 0.048) and post-RCT invasive front inflammatory cells (p = 0.010) correlated with improved no evidence of disease survival. In multivariate analysis, the combination of low PD-L1 in cancer and inflammatory cells was an independent negative prognostic marker for overall survival (OS) pre-RCT (Cox's proportional hazard ratio 0.438, p = 0.045) and in the invasive front post-RCT (Cox's proportional hazard ratio 0.257, p = 0.030).Neoadjuvant RCT is associated with an increased PD-L1 expression in rectal adenocarcinoma patients, which should prompt clinical trials combining radiotherapy and PD-1/PD-L1 pathway blockade. Combined low PD-L1 expression on tumour and inflammatory cells is an independent negative prognostic marker for OS in RCT of rectal adenocarcinoma.
EVALuna2:6814

PEG matrix enables cell-mediated local BMP-2 gene delivery and increased bone formation in a porcine critical size defect model of craniofacial bone regeneration - Wehrhan, Falk; Amann, Kerstin Ute; Molenberg, Aart; Lutz, Rainer; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas (Clinical Oral Implants Research, 2012)
Purpose: This study addressed the suitability of a polyethylene glycol (PEG) matrix as scaffold for cell-mediated local BMP-2 gene transfer in a calvarial critical size defect (CSD) model. Materials and methods: PEG matrix (degradation time 10 days) and PEG membrane (degradation time 120 days) were used in the pig calvarial model. Cylindrical (1 × 1 cm) CSD (9 per animal; 20 animals) were filled with: (i) HA/TCP, covered by PEG membrane (group 1); (ii) HA/TCP, mixed with PEG matrix (group 2); and (iii) HA/TCP mixed with BMP-2 transfected osteoblasts and PEG matrix (group 3). BMP-2/4 gene transfer: liposomal in vitro transfection of BMP-2/V5-tag fusion-protein. Quantitative histomorphometry (toluidine blue staining) after 2, 4 and 12 weeks assessed bone formation. Semiquantitative immunohistochemistry estimated the expression of BMP-2 and V5-tag. Results: Group 3 showed significantly higher new bone formation than groups 1, 2 at 4 (P < 0.05) and 12 (P < 0.02) weeks. BMP-2-V5-tag was detected for 4 weeks. BMP-2 expression in group 3 was higher compared to all other groups after 2 and 4 (P < 0.02) weeks. Conclusions: The PEG matrix serves as scaffold for cell-mediated BMP-2 gene delivery in guided bone regeneration facilitating cell survival and protein synthesis for at least 4 weeks. Local BMP-2 gene delivery by PEG matrix-embedded cells leads to increased bone formation during critical size defect regeneration. © 2011 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2024-05-13
Keywords: BMP-2; Bone regeneration; Critical size defect; Gene transfer; PEG

Persistent scarring and dilated cardiomyopathy suggest incomplete regeneration of the apex resected neonatal mouse myocardium - A 180days follow up study - Andersen, Ditte Caroline; Jensen, Charlotte Harken; Baun, Christina; Hvidsten, Svend; Zebrowski, David; Engel, Felix; Sheikh, Soren Paludan (Journal of Molecular and Cellular Cardiology, 2016)
Heart damage in mammals is generally considered to result in scar formation, whereas zebrafish completely regenerate their hearts following an intermediate and reversible state of fibrosis after apex resection (AR). Recently, using the AR procedure, one-day-old mice were suggested to have full capacity for cardiac regeneration as well. In contrast, using the same mouse model others have shown that the regeneration process is incomplete and that scarring still remains 21days after AR. The present study tested the hypothesis that like in zebrafish, fibrosis in neonatal mammals could be an intermediate response before the onset of complete heart regeneration. Myocardial damage was performed by AR in postnatal day 1 C57BL/6 mice, and myocardial function and scarring assessed at day 180 using F-18-fluorodeoxyglucose positron emission tomography (FDG-PET) and histology, respectively. AR mice exhibited decreased ejection fraction and wall motion with increased end-diastolic and systolic volumes compared to sham-operated mice. Scarring with collagen accumulation was still substantial, with increased heart size, while cardiomyocyte size was unaffected. In conclusion, these data thus show that apex resection in mice results in irreversible fibrosis and dilated cardiomyopathy suggesting that cardiac regeneration is limited in neonatal mammals and thus distinct from the regenerative capacity seen in zebrafish.
EVALuna2:25499

PGAM5-mediated programmed necrosis of hepatocytes drives acute liver injury - He, Gui-Wei; Günther, Claudia; Kremer, Andreas; Thonn, Veronika; Amann, Kerstin Ute; Poremba, Christopher; Neurath, Markus; Wirtz, Stefan; Becker, Christoph (Gut, 2016)
Autoimmune hepatitis (AIH) is a severe necroinflammatory liver disease associated with significant mortality. Although loss of hepatocytes is generally recognised as a key trigger of liver inflammation and liver failure, the regulation of hepatic cell death causing AIH remains poorly understood. The aim of this study was to identify molecular mechanisms that drive hepatocyte cell death in the pathogenesis of acute liver injury.Acute liver injury was modelled in mice by intravenous administration of concanavalin A (ConA). Liver injury was demonstrated by serum transaminases and histological assessment of liver sections. PGAM5-deficient mice (PGAM5-/-) were used to determine its role in experimental hepatitis. Mdivi-1 was used as an inhibitor of dynamin-related protein 1 (Drp1)-mediated mitochondrial fission. Mitochondrial fission and the expression of PGAM5 were compared between liver biopsies derived from patients with AIH and control patients.PGAM5 was highly expressed in hepatocytes of patients with AIH and in mice with ConA-induced experimental hepatitis. Deficiency of PGAM5 protected mice from ConA-induced hepatocellular death and liver injury. PGAM5 regulated ConA-induced mitochondrial fission in hepatocytes. Administration of the Drp1-inhibitor Mdivi-1 blocked mitochondrial fission, diminished hepatocyte cell death and attenuated liver tissue damage induced by ConA.Our data demonstrate for the first time that PGAM5 plays an indispensable role in the pathogenesis of ConA-induced liver injury. Downstream of PGAM5, Drp1-mediated mitochondrial fission is an obligatory step that drives the execution of hepatic necrosis and tissue damage. Our data highlight the PGAM5-Drp1 axis as a potential therapeutic target for acute immune-mediated liver injury.
EVALuna2:2219

[Philipp A. Schnabel : 24 May 1953-13 May 2021]. - Amann, Kerstin Ute (Pathologe, 2021)
EVALuna2:475671

PLA2R-positive (primary) membranous nephropathy in a child with IPEX syndrome - Chuva, Teresa; Pfister, Frederick; Beringer, Ortraud; Felgentreff, Kerstin; Buettner-Herold, Maike; Amann, Kerstin Ute (Pediatric Nephrology, 2017)
Immunodysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome is a rare primary immunodeficiency syndrome characterized by the development of multiple autoimmune disorders in affected individuals. Different forms of renal injury have been reported in IPEX syndrome, and membranous nephropathy (MN) is among the most common glomerulopathies found. However, the exact pathogenesis of MN in this setting has not been elucidated, and it is not clear whether it is part of the clinical spectrum of the disease or secondary to medications, infections or other concomitant insults.We describe a child diagnosed with IPEX syndrome shortly after birth who presented with nephrotic syndrome at the age of 11 weeks. Renal biopsy revealed a MN with enhanced immunohistochemical staining for phospholipase A2 receptor (PLA2R).This is the first report of a PLA2R-positive MN in a patient with IPEX syndrome. We suggest that, in this context, MN results from an autoimmune process against podocytic antigens, namely PLA2R.
EVALuna2:25544

Plasminogen deficiency does not prevent sodium retention in a genetic mouse model of experimental nephrotic syndrome - Xiao, Mengyun; Bohnert, Bernhard N.; Aypek, Hande; Kretz, Oliver; Grahammer, Florian; Aukschun, Ute; Woern, Matthias; Janessa, Andrea; Essigke, Daniel; Daniel, Christoph; Amann, Kerstin Ute; Huber, Tobias B.; et al. (Acta Physiologica, 2020)
Aim: Sodium retention is the hallmark of nephrotic syndrome (NS) and mediated by the proteolytic activation of the epithelial sodium channel (ENaC) by aberrantly filtered serine proteases. Plasmin is highly abundant in nephrotic urine and has been proposed to be the principal serine protease responsible for ENaC activation in NS. However, a proof of the essential role of plasmin in experimental NS is lacking. Methods: We used a genetic mouse model of NS based on an inducible podocin knockout (Bl6-Nphs2tm3.1Antc*Tg(Nphs1-rtTA*3G)8Jhm*Tg(tetO-cre)1Jaw or nphs2Δipod). These mice were crossed with plasminogen deficient mice (Bl6-Plgtm1Jld or plg−/−) to generate double knockout mice (nphs2Δipod*plg−/−). NS was induced after oral doxycycline treatment for 14 days and mice were followed for subsequent 14 days. Results: Uninduced nphs2Δipod*plg−/− mice had normal kidney function and sodium handling. After induction, proteinuria increased similarly in both nphs2Δipod*plg+/+ and nphs2Δipod*plg−/− mice. Western blot revealed the urinary excretion of plasminogen and plasmin in nphs2Δipod*plg+/+ mice which were absent in nphs2Δipod*plg−/− mice. After the onset of proteinuria, amiloride-sensitive natriuresis was increased compared to the uninduced state in both genotypes. Subsequently, urinary sodium excretion dropped in both genotypes leading to an increase in body weight and development of ascites. Treatment with the serine protease inhibitor aprotinin prevented sodium retention in both genotypes. Conclusions: This study shows that mice lacking urinary plasminogen are not protected from ENaC-mediated sodium retention in experimental NS. This points to an essential role of other urinary serine proteases in the absence of plasminogen.
CRIS-Team Scopus Importer:2020-08-07
Keywords: epithelial sodium channel; nephrotic syndrome; plasminogen; proteasuria; sodium retention

PML-nuclear bodies decrease with age and their stress response is impaired in aged individuals - Wenger, Barbara; Schwegler, Manuela; Brunner, Michaela; Daniel, Christoph; Schmidt, Manfred; Fietkau, Rainer; Distel, Luitpold (BMC Geriatrics, 2014)
Promyelocytic leukemia nuclear bodies (PML-NBs) have been depicted as structures which are involved in processing cell damages and DNA double-strand break repairs. The study was designed to evaluate differences in patients' PML-NBs response to stress factors like a cancerous disease and ionizing radiation exposure dependent on age.In order to clarify the role of PML-NBs in the aging process, we examined peripheral blood monocytes of 134 cancer patients and 41 healthy individuals between 22 and 92 years of age, both before and after in vitro irradiation. Additionally, we analyzed the samples of the cancer patients after in vivo irradiation. Cells were immunostained and about 1600 cells per individual were analyzed for the presence of PML- and ?H2AX foci.The number of existing PML-NBs per nucleus declined with age, while the number of ?H2AX foci increased with age. There was a non-significant trend that in vivo irradiation increased the number of PML-NBs in cells of young study participants, while in older individuals PML-NBs tended to decrease. It can be assumed that PML-NBs decrease in number during the process of aging.The findings suggest that there is a dysfunctional PML-NBs stress response in aged cells.
EVALuna2:18179

PODOCYTE AND GLOMERULAR ENDOTHELIAL CELL DERIVED MICRORNAS REGULATE PODOCYTE NEPHRONECTIN IN MEMBRANOUS GLOMERULONEPHRITIS - Müller-Deile, Janina; Sopel, Nina; Ohs, Alexandra; Kotb, Ahmed; Gröner, Marwin; Daniel, Christoph; Amann, Kerstin Ute; Schiffer, Mario (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2021)
CRIS-Team WoS Importer:2021-12-03

Poly(Glycerol Sebacate)/Poly(Butylene Succinate-Butylene Dilinoleate) Fibrous Scaffolds for Cardiac Tissue Engineering - Tallawi, Marwa; Zebrowski, David; Rai, Ranjana; Roether, Judith; Schubert, Dirk W.; El Fray, Miroslawa; Engel, Felix; Aifantis, Katerina E.; Boccaccini, Aldo R. (Tissue Engineering - Part C: Methods, 2015)
The present article investigates the use of a novel electrospun fibrous blend of poly(glycerol sebacate) (PGS) and poly(butylene succinate-butylene dilinoleate) (PBS-DLA) as a candidate for cardiac tissue engineering. Random electrospun fibers with various PGS/PBS-DLA compositions (70/30, 60/40, 50/50, and 0/100) were fabricated. To examine the suitability of these fiber blends for heart patches, their morphology, as well as their physical, chemical, and mechanical properties were measured before examining their biocompatibility through cell adhesion. The fabricated fibers were bead-free and exhibited a relatively narrow diameter distribution. The addition of PBS-DLA to PGS resulted in an increase of the average fiber diameter, whereas increasing the amount of PBS-DLA decreased the hydrophilicity and the water uptake of the nanofibrous scaffolds to values that approached those of neat PBS-DLA nanofibers. Moreover, the addition of PBS-DLA significantly increased the elastic modulus. Initial toxicity studies with C2C12 myoblast cells up to 72 h confirmed nontoxic behavior of the blends. Immunofluorescence analyses and scanning electron microscopy analyses confirmed that C2C12 cells showed better cell attachment and proliferation on electrospun mats with higher PBS-DLA content. However, immunofluorescence analyses of the 3-day-old rat cardiomyocytes cultured for 2 and 5 days demonstrated better attachment on the 70/30 fibers containing well-aligned sarcomeres and expressing high amounts of connexin 43 in cellular junctions indicating efficient cell-to-cell communication. It can be concluded, therefore, that fibrous PGS/PBS-DLA scaffolds exhibit promising characteristics as a biomaterial for cardiac patch applications.

Position Paper of the European Society of Cardiology Working Group Cellular Biology of the Heart: cell-based therapies for myocardial repair and regeneration in ischemic heart disease and heart failure - Madonna, Rosalinda; Van Laake, Lindaw.; Davidson, Sean M.; Engel, Felix; Hausenloy, Derek J.; Lecour, Sandrine; Leor, Jonathan; Perrino, Cinzia; Schulz, Rainer; Ytrehus, Kirsti; Landmesser, Ulf; Mummery, Christine L.; et al. (European Heart Journal, 2016)
Despite improvements in modern cardiovascular therapy, the morbidity and mortality of ischaemic heart disease (IHD) and heart failure (HF) remain significant in Europe and worldwide. Patients with IHD may benefit from therapies that would accelerate natural processes of postnatal collateral vessel formation and/or muscle regeneration. Here, we discuss the use of cells in the context of heart repair, and the most relevant results and current limitations from clinical trials using cell-based therapies to treat IHD and HF. We identify and discuss promising potential new therapeutic strategies that include ex vivo cell-mediated gene therapy, the use of biomaterials and cell-free therapies aimed at increasing the success rates of therapy for IHD and HF. The overall aim of this Position Paper of the ESC Working Group Cellular Biology of the Heart is to provide recommendations on how to improve the therapeutic application of cell-based therapies for cardiac regeneration and repair.
EVALuna2:25529

Possible links between groundwater geochemistry and chronic kidney disease of unknown etiology (CKDu): an investigation from the Ginnoruwa region in Sri Lanka - Balasooriya, Shyamalie; Munasinghe, Harshaka; Herath, A. T.; Diyabalanage, Saranga; Ileperuma, O. A.; Manthrithilake, Herath; Daniel, Christoph; Amann, Kerstin Ute; Zwiener, Christian; Barth, Johannes; Chandrajith, Rohana (Exposure and Health, 2019)
Since at least two decades, Chronic Kidney Disease of Uncertain Etiology (CKDu) has become an increasingly discussed health issue in Sri Lanka and as well as in other tropical regions. Areas that are particularly affected with the disease are mostly located in the dry zone of Sri Lanka. The disease is more prominent among communities that consume groundwater as their main source of drinking water. Hydrogeochemical investigations were carried out in the Ginnoruwa area, a known hotspot of CKDu. It revealed possible links between drinking water chemistry and the spreading of the disease. This work compares hydrogeochemical data of drinking water sources of wells whose consumers are affected by CKDu and other nearby wells whose consumers were not affected by the disease. A total of 63 groundwater samples were collected from selected wells. About one-third of these samples (i.e., 19) were collected from wells used by CKDu patients. Significantly higher values of pH, total hardness, electrical conductivity, Ca2+, Mg2+, F−, Cl−, PO4 3−, and SO4 2− were found in wells that were used by CKDu patients. Mean contents of Na+, Ca2+, and Mg2+ in CKDu affected wells were 33.8 mg/L, 30.1 mg/L, and 14.9 mg/L, respectively, compared to 23.1 mg/L, 26.7 mg/L, and 9.65 mg/L in non-CKDu wells. Differences in major ion geochemistry in groundwaters are possibly governed by variable time periods of water storage in fractured hard rock aquifers in this region. Hydrogeochemical parameters were statistically compared by a Mann–Whitney U test and indicated significant differences in total dissolved solids (TDS) (p = 0.016), SO4 2− (p = 0.005), PO4 3− (p = 0.030), F− (p = 0.048), Na+ (p = 0.008), and Mg2+(p = 0.008) between non-CKDu and CKDu wells at p = 0.050 level. Other suspected solutes such as nephrotoxic trace elements including As, Cd, and Pb were similar in both types of wells. They were also lower than the accepted guideline limits of the World Health Organization (WHO). Results of this study suggest that fluoride in drinking water in combination with water hardness may be one of the responsible factors for kidney damage and progression of the disease. This may be particularly the case when elevated amounts of Mg2+ are present in hard groundwater.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Fluoride; Girandurukotte; Kidney damage; Magnesium; Mann–Whitney U test; Water hardness

Potential and Uncertainties of RejectClass in Acute Kidney Graft Dysfunction: An Independent Validation Study. - Von Samson-Himmelstjerna, Friedrich A.; Kakavand, Nassim; Gleske, Charlotte; Schraml, Florian; Basta, Agathe A.; Braunisch, Matthias C.; Bräsen, Jan H.; Schmitz, Jessica; Kraus, Daniel; Weinmann-Menke, Julia; Zacharias, Helena U.; Vaulet, Thibaut; et al. (Transplantation, 2024)
BACKGROUND: Kidney graft rejections are classified based on the Banff classification. The RejectClass algorithm, initially derived from a cohort comprising mostly protocol biopsies, identifies data-driven phenotypes of acute rejection and chronic pathology using Banff lesion scores. It also provides composite scores for inflammation activity and chronicity. This study independently evaluates the performance of RejectClass in a cohort consisting entirely of indication biopsies. METHODS: We retrospectively applied RejectClass to 441 patients from the German TRABIO (TRAnsplant BIOpsies) cohort who had received indication biopsies. The primary endpoint was death-censored graft failure during 2 y of follow-up. RESULTS: The application of RejectClass to our cohort demonstrated moderately comparable phenotypic features with the derivation cohort, and most clusters indicated an elevated risk of graft loss. However, the reproduction of all phenotypes and the associated risks of graft failure, as depicted in the original studies, was not fully accomplished. In contrast, adjusted Cox proportional hazards analyses substantiated that both the inflammation score and the chronicity score are independently associated with graft loss, exhibiting hazard ratios of 1.7 (95% confidence interval, 1.2-2.3; P = 0.002) and 2.2 (95% confidence interval, 1.8-2.6; P < 0.001), respectively, per 0.25-point increment (scale: 0.0-1.0). CONCLUSIONS: The composite inflammation and chronicity scores may already have direct utility in quantitatively assessing the disease stage. Further refinement and validation of RejectClass clusters are necessary to achieve more reliable and accurate phenotyping of rejection.
EVALuna2:549467

Potential of graphene-based nanomaterials for cardiac tissue engineering - Edrisi, Fatemeh; Baheiraei, Nafiseh; Razavi, Mehdi; Roshanbinfar, Kaveh; Imani, Rana; Jalilinejad, Negin (Journal of Materials Chemistry B, 2023)
Cardiovascular diseases are the primary cause of death worldwide. Despite significant advances in pharmacological treatments and surgical interventions to restore heart function after myocardial infarction, it can progress to heart failure due to the restricted inherent potential of adult cardiomyocytes to self-regenerate. Hence, the evolution of new therapeutic methods is critical. Nowadays, novel approaches in tissue engineering have assisted in restoring biological and physical specifications of the injured myocardium and, hence, cardiac function. The incorporation of a supporting matrix that could mechanically and electronically support the heart tissue and stimulate the cells to proliferate and regenerate will be advantageous. Electroconductive nanomaterials can facilitate intracellular communication and aid synchronous contraction via electroactive substrate creation, preventing the issue of arrhythmia in the heart. Among a wide range of electroconductive materials, graphene-based nanomaterials (GBNs) are promising for cardiac tissue engineering (CTE) due to their outstanding features including high mechanical strength, angiogenesis, antibacterial and antioxidant properties, low cost, and scalable fabrication. In the present review, we discuss the effect of applying GBNs on angiogenesis, proliferation, and differentiation of implanted stem cells, their antibacterial and antioxidant properties, and their role in improving the electrical and mechanical properties of the scaffolds for CTE. Also, we summarize the recent research that has applied GBNs in CTE. Finally, we present a concise discussion on the challenges and prospects.
CRIS-Team Scopus Importer:2023-08-18

PPARβ/δ: Linking Metabolism to Regeneration - Magadum, Ajit; Engel, Felix (International Journal of Molecular Sciences, 2018)
In contrast to the general belief that regeneration is a rare event, mainly occurring in simple organisms, the ability of regeneration is widely distributed in the animal kingdom. Yet, the efficiency and extent of regeneration varies greatly. Humans can recover from blood loss as well as damage to tissues like bone and liver. Yet damage to the heart and brain cannot be reversed, resulting in scaring. Thus, there is a great interest in understanding the molecular mechanisms of naturally occurring regeneration and to apply this knowledge to repair human organs. During regeneration, injury-activated immune cells induce wound healing, extracellular matrix remodeling, migration, dedifferentiation and/or proliferation with subsequent differentiation of somatic or stem cells. An anti-inflammatory response stops the regenerative process, which ends with tissue remodeling to achieve the original functional state. Notably, many of these processes are associated with enhanced glycolysis. Therefore, peroxisome proliferator-activated receptor (PPAR) β/δ—which is known to be involved for example in lipid catabolism, glucose homeostasis, inflammation, survival, proliferation, differentiation, as well as mammalian regeneration of the skin, bone and liver—appears to be a promising target to promote mammalian regeneration. This review summarizes our current knowledge of PPARβ/δ in processes associated with wound healing and regeneration.
EVALuna2:34819
Keywords: PPAR beta/delta; regeneration; proliferation; differentiation; metabolism; Wnt signaling; PDK1; Akt; glycolysis

Preliminary observations on whole-ovary xenotransplantation as an experimental model for fertility preservation - Nichols-Burns, Stephanie M.; Lotz, Laura; Schneider, Heike; Adamek, Edyta; Daniel, Christoph; Stief, Andrea; Grigo, Christina; Klump, Dorothee; Hoffmann, Inge; Beckmann, Matthias; Dittrich, Ralf (Reproductive Biomedicine Online, 2014)
Ovarian tissue preservation and retransplantation is a promising strategy to restore fertility in cancer survivors. Ischaemia accompanying ovarian tissue grafting, however, can lead to significant follicle loss. Transplantation of the whole ovary by vascular anastomosis has been considered as an alternative to prevent widespread ischaemic damage. In this study, the feasibility and function of transplanting whole ovary with intact vasculature were evaluated, with the goal of developing a xenograft model for studies using donated human ovaries. Whole-swine ovaries with vascular pedicles were perfused and transplanted as intact ovaries by anastomosis into irradiated ovariectomized nude rats (n = 10). The observation period was between 1 and 4 weeks. Fresh swine ovaries served as controls (n = 10). Ovarian stroma and follicle populations were assessed through histological examination in both transplanted and control ovaries. Most of the transplanted whole ovaries (n = 6) maintained stromal quality and all preantral follicle classes were represented, although follicle numbers decreased compared with fresh control. Four transplanted ovaries were fibrotic after 1-4 weeks within the nude rat. Our results demonstrate transplantation of whole-pig ovary into nude rats is possible and support development of this xenograft model system for human studies.
EVALuna2:15573

Primary glomerulonephritides - Floege, Juergen; Amann, Kerstin Ute (Lancet, 2016)
Most glomerulonephritides, even the more common types, are rare diseases. They are nevertheless important since they frequently affect young people, often cannot be cured, and can lead to chronic kidney disease, including end-stage renal failure, with associated morbidity and cost. For example, in young adults, IgA nephropathy is the most common cause of end-stage renal disease. In this Seminar, we summarise existing knowledge of clinical signs, pathogenesis, prognosis, and treatment of glomerulonephritides, with a particular focus on data published between 2008 and 2015, and the most common European glomerulonephritis types, namely IgA nephropathy, membranous glomerulonephritis, minimal change disease, focal segmental glomerulosclerosis, membranoproliferative glomerulonephritis, and the rare complement-associated glomerulonephritides such as dense deposit disease and C3 glomerulonephritis.
EVALuna2:25514

Prognostic significance of macrophage polarization in early stage oral squamous cell carcinomas - Weber, Manuel; Iliopoulos, Christos; Moebius, Patrick; Buettner-Herold, Maike; Amann, Kerstin Ute; Ries, Jutta; Preidl, Raimund; Neukam, Friedrich Wilhelm; Wehrhan, Falk (Oral Oncology, 2016)
Polarization of tumor infiltrating macrophages is associated with the prognosis of solid malignancies and correlates with the occurrence of lymph node metastases in oral squamous cell carcinomas (oscc). Early stage (T1/T2, N0) oscc are characterized by a good prognosis and can be cured by surgery. The postoperative regime usually contains no adjuvant radio-/chemotherapy. The current pilot study was conducted to elucidate whether macrophage polarization in tumor resection specimens and diagnostic biopsies of early stage oscc is associated with tumor outcome.Patients with T1/T2, N0, and R0>5mm oscc without adjuvant therapy and 3-year follow-up after tumor resection were retrospectively selected. Tissue microarrays (TMA) containing diagnostic biopsies (n=17) and tumor resection specimens (n=17) were processed for immunohistochemistry in this pilot study to detect CD68-, CD11c-, CD163- and MRC1-positive macrophages. Samples were digitized, and the expression of macrophage markers was quantitatively analyzed.High infiltration of M2 polarized macrophages correlated with poor tumor outcome in early stage (T1/T2, N0) oscc. This correlation was observed in tumor resection specimens, but was also observed in diagnostic biopsies. M2 macrophage polarization in biopsies - but not in tumor resection samples - correlated with high scores in tumor grading.Macrophage polarization in early stage oscc is a potential prognostic marker for tumor outcome. The correlation of M2 polarized macrophages with tumor outcome can already be detected in the initial biopsies. Furthermore, M2 polarization of macrophages in biopsies is associated with an increased dedifferentiation.
EVALuna2:24408

Progressive Kidney Failure by Angiotensinogen Inactivation in the Germline - Wopperer, Florian; Olinger, Eric; Wiesener, Antje; Broeker, Katharina A.E.; Knaup, Karl; Schaefer, Jan Thomas; Galiano, Matthias; Schneider, Karen; Schiffer, Mario; Büttner-Herold, Maike; Reis, André; Schmieder, Roland; et al. (Hypertension, 2024)
BACKGROUND: Autosomal recessive renal tubular dysgenesis is a rare, usually fatal inherited disorder of the REN (renin)angiotensin system. Herein, we report an adolescent individual experiencing an unknown chronic kidney disease and aim to provide novel insights into disease mechanisms. METHODS: Exome sequencing for a gene panel associated with renal disease was performed. The REN-angiotensin system was assessed by comprehensive biochemical analysis in blood. REN expression was determined in primary tubular cells by quantitative polymerase chain reaction and in situ hybridization on kidney biopsy samples. Allele frequencies of heterozygous and biallelic deleterious variants were determined by analysis of the Genomics England 100,000 Genomes Project. RESULTS: The patient was delivered prematurely after oligohydramnios was detected during pregnancy. Postnatally, he recovered from third-degree acute kidney injury but developed chronic kidney disease stage G3b over time. Exome sequencing revealed a previously reported pathogenic homozygous missense variant, p.(Arg375Gln), in the AGT (angiotensinogen) gene. Blood AGT concentrations were low, but plasma REN concentration and gene expression in kidney biopsy, vascular, and tubular cells revealed strong upregulation of REN. Angiotensin II and aldosterone in blood were not abnormally elevated. CONCLUSIONS: Renal tubular dysgenesis may present as chronic kidney disease with a variable phenotype, necessitating broad genetic analysis for diagnosis. Functional analysis of the renin-angiotensin system in a patient with AGT mutation revealed novel insights regarding compensatory upregulation of REN in vascular and tubular cells of the kidney and in plasma in response to depletion of AGT substrate as a source of Ang II (similarly observed with hepatic AGT silencing for the treatment of hypertension).
CRIS-Team Scopus Importer:2024-07-26
Keywords: angiotensinogen; exome; mass spectrometry; mutation; renin-angiotensin system

Pro-inflammatory NK-like T cells are expanded in the blood and inflamed intestine in Crohn's disease - Chiarolla, Cristina M.; Schulz, Axel R.; Meir, Michael; Ferrara, Sebastian; Xiao, Yin; Reu-Hofer, Simone; Romero-Olmedo, Addi J.; Falcone, Valeria; Hoffmann, Katja; Büttner-Herold, Maike; Prelog, Martina; Rosenwald, Andreas; et al. (Mucosal Immunology, 2024)
Altered intestinal immune homeostasis leads to chronic inflammation in Crohn's disease (CD). To address disease- and tissue-specific alterations, we performed a T cell-centric mass cytometry analysis of peripheral and intestinal lymphocytes from patients with CD and healthy donors’ PBMCs. Chronic intestinal inflammation enforced activation, exhaustion, and terminal differentiation of CD4+ and CD8+ T cells and a relative enrichment of CD4+ regulatory T (Treg) cells. Moreover, enigmatic rare Treg subsets appeared upon inflammation, e.g. CD4+FOXP3+HLA-DR+TIGIT– and CD4+FOXP3+CD56+, expressing pro-inflammatory IFN-γ upon in vitro stimulation. Some conventional T (Tcon) cells acquired NK-like features. In CD patients’ blood, not well studied CD16+CCR6+CD127+ T cells appeared, being CD4+ or CD8+, a phenotype inducible on healthy T cells by CD blood plasma. Upon CD16-mediated antibody binding, they could attain effector function. These findings suggest an uncommon pro-inflammatory innate-like differentiation of Treg and Tcon cells with acquisition of non-specific cytotoxicity. Most likely, this is both cause and consequence of intestinal inflammation during CD.
CRIS-Team Scopus Importer:2025-02-04
Keywords: CD16; CD56; Crohn's Disease; CyTOF; TIGIT

Prolonged podocyte depletion in larval zebrafish resembles mammalian focal and segmental glomerulosclerosis - Hansen, Kerrin Ursula Ingeborg; Siegerist, Florian; Daniel, Sophie; Schindler, Maximilian; Iervolino, Anna; Blumenthal, Antje; Daniel, Christoph; Amann, Kerstin Ute; Zhou, Weibin; Endlich, Karlhans; Endlich, Nicole (The FASEB Journal, 2020)
Focal and segmental glomerulosclerosis (FSGS) is a histological pattern frequently found in patients with nephrotic syndrome that often progress to end-stage kidney disease. The initial step in development of this histologically defined entity is injury and ultimately depletion of podocytes, highly arborized interdigitating cells on the glomerular capillaries with important function for the glomerular filtration barrier. Since there are still no causal therapeutic options, animal models are needed to develop new treatment strategies. Here, we present an FSGS-like model in zebrafish larvae, an eligible vertebrate model for kidney research. In a transgenic zebrafish strain, podocytes were depleted, and the glomerular response was investigated by histological and morphometrical analysis combined with immunofluorescence staining and ultrastructural analysis by transmission electron microscopy. By intravenous injection of fluorescent high-molecular weight dextran, we confirmed leakage of the size selective filtration barrier. Additionally, we observed severe podocyte foot process effacement of remaining podocytes, activation of proximal tubule-like parietal epithelial cells identified by ultrastructural cytomorphology, and expression of proximal tubule markers. These activated cells deposited extracellular matrix on the glomerular tuft which are all hallmarks of FSGS. Our findings indicate that glomerular response to podocyte depletion in larval zebrafish resembles human FSGS in several important characteristics. Therefore, this model will help to investigate the disease development and the effects of potential drugs in a living organism.
CRIS-Team Scopus Importer:2020-10-23
Keywords: FSGS; glomerulus; podocyte injury; zebrafish model organism

Promoting vascularization for tissue engineering constructs: current strategies focusing on HIF-regulating scaffolds - Esser, Tilman; Roshanbinfar, Kaveh; Engel, Felix (Expert Opinion on Biological Therapy, 2018)
INTRODUCTION: Vascularization remains one of the greatest yet unmet challenges in tissue engineering. When engineered tissues are scaled up to therapeutically relevant dimensions, their demand of oxygen and nutrients can no longer be met by diffusion. Thus, there is a need for perfusable vascular structures. Hypoxia-inducible factors (HIF) act as transcriptional oxygen sensors and regulate a multitude of genes involved in adaptive processes to hypoxia, including angiogenesis. Thus, targeting HIFs is a promising strategy to induce vascularization of engineered tissues. Areas covered: Here we review current vascularization strategies and summarize the present knowledge regarding activation of HIF signaling by ions, iron chelating agents, α-Ketoglutarate (αKG) analogues, and the lipid-lowering drug simvastatin to induce angiogenesis. Specifically, we focus on the incorporation of HIF-activating agents into biomaterials and scaffolds for controlled release. Expert opinion: Vascularization of tissue constructs through activation of upstream regulators of angiogenesis offers advantages but also suffers from drawbacks. HIFs can induce a complete angiogenic program; however, this program appears to be too slow to vascularize larger constructs before cell death occurs. It is therefore crucial that HIF-activation is combined with cell protective strategies and prevascularization techniques to obtain fully vascularized, vital tissues of therapeutically relevant dimensions.
EVALuna2:102206

Protease-activated receptor 2 deficient mice develop less angiotensin II induced left ventricular hypertrophy but more cardiac fibrosis. - Meyer zu Schwabedissen, Albrecht; Vergarajauregui, Silvia; Bertog, Marko; Amann, Kerstin Ute; Engel, Felix; Daniel, Christoph (PLoS ONE, 2024)
AIMS: Activation of Protease Activated Receptor 2 (PAR2) has been shown to be involved in regulation of injury-related processes including inflammation, fibrosis and hypertrophy. In this study we will investigate the role of PAR2 in cardiac injury in a mouse model of hypertension using continuous infusion with angiotensin II. METHODS: Hypertension was induced in 12 weeks old wildtype (wt, n = 8) and PAR2 deficient mice (n = 9) by continuous infusion with angiotensin II for 4 weeks using osmotic minipumps. At the end, hearts were collected for analysis of left ventricular hypertrophy (LVH), myocardial capillary supply, fibrosis and localization of PAR2 expression using histological, immunohistological and mRNA expression analysis techniques. In addition, rat cardiac fibroblasts were treated with angiotensin II and PAR2 was inhibited by a blocking antibody and the PAR2 inhibitor AZ3451. RESULTS: Cardiac PAR2 mRNA expression was downregulated by 40±20% in wt mice treated with AngII compared to untreated controls. Four weeks after AngII treatment, LVH was significantly increased in AngII-treated wt mice compared to similarly treated PAR2-deficient animals as determined by relative heart weight, left ventricular cross-sectional area, and analysis of ventricular lumen area determined on sections. Treatment of wt mice resulted in an approximately 3-fold increase in cardiac expression of FGF23, which was 50% lower in PAR2-deficient animals compared to wt animals and therefore no longer significantly different from expression levels in untreated control mice. In contrast, cardiac interstitial fibrosis was significantly higher in PAR2-deficient mice compared to similar treated wt controls, as assessed by Sirius Red staining (>3-fold) and collagen IV staining (>2-fold). Additional experiments with isolated cardiac fibroblasts showed induction of pro-fibrotic genes when treated with PAR2 inhibitors. CONCLUSION: In angiotensin II-induced cardiac injury, PAR2 deficiency has an ambivalent effect, enhancing fibrosis on the one hand, but reducing LVH on the other.
EVALuna2:577005

Pseudo-bipolar spindle formation and cell division in postnatal binucleated cardiomyocytes - Leone, Marina; Engel, Felix (Journal of Molecular and Cellular Cardiology, 2019)
Background: The majority of adult human, mouse and rat cardiomyocytes is not diploid mononucleated. Nevertheless, the current literature on heart regeneration based on cardiomyocyte proliferation focuses mainly on the proliferation capacity of diploid mononucleated cardiomyocytes, instead of the more abundant mononucleated polyploid or binucleated cardiomyocytes. Here, we aimed at a better understanding of the process of mitosis and cell division in postnatal binucleated cardiomyocytes. Methods and results: Postnatal rat binucleated cardiomyocytes were stimulated to re-enter the cell cycle either by fetal bovine serum or a combination of fibroblast growth factor 1 and p38 MAP kinase inhibitor. Phase-contrast videos revealed that binucleated cardiomyocytes form one metaphase plate and preferentially undergo afterwards cytokinesis failure. The maximum rate of cell division of video-recorded binucleated cardiomyocytes was around 6%. Immunofluorescence analyses of centriole number in mitotic binucleated cardiomyocytes revealed that these cells contain more than four centrioles, which can be paired as well as unpaired. In agreement with multiple and/or unpaired centrioles, multipolar spindle formation was observed in mitotic binucleated cardiomyocytes using fluorescence live imaging of tubulin-GFP. Multipoles were transient and resolved into pseudo-bipolar spindles both in case of cell division and cytokinesis failure. Notably, centrioles were in most cases unevenly distributed among daughter cells. Conclusions: Our results indicate that postnatal binucleated cardiomyocytes upon stimulation can enter mitosis, cope with their multiple and/or unpaired centrioles by forming pseudo-bipolar spindles, and divide.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Binucleated cardiomyocyte; Cell division; Centriole; Centrosome; Intermediate multipoles; Live cell imaging

PU.1 controls fibroblast polarization and tissue fibrosis - Wohlfahrt, Thomas; Rauber, Simon; Uebe, Steffen; Luber, Markus; Soare, Alina; Ekici, Arif Bülent; Weber, Stefanie; Matei, Alexandru-Emil; Chen, Chih-Wei; Maier, Christiane; Karouzakis, Emmanuel; Kiener, Hans P.; et al. (Nature, 2019)
Fibroblasts are polymorphic cells with pleiotropic roles in organ morphogenesis, tissue homeostasis and immune responses. In fibrotic diseases, fibroblasts synthesize abundant amounts of extracellular matrix, which induces scarring and organ failure. By contrast, a hallmark feature of fibroblasts in arthritis is degradation of the extracellular matrix because of the release of metalloproteinases and degrading enzymes, and subsequent tissue destruction. The mechanisms that drive these functionally opposing pro-fibrotic and pro-inflammatory phenotypes of fibroblasts remain unknown. Here we identify the transcription factor PU.1 as an essential regulator of the pro-fibrotic gene expression program. The interplay between transcriptional and post-transcriptional mechanisms that normally control the expression of PU.1 expression is perturbed in various fibrotic diseases, resulting in the upregulation of PU.1, induction of fibrosis-associated gene sets and a phenotypic switch in extracellular matrix-producing pro-fibrotic fibroblasts. By contrast, pharmacological and genetic inactivation of PU.1 disrupts the fibrotic network and enables reprogramming of fibrotic fibroblasts into resting fibroblasts, leading to regression of fibrosis in several organs.
EVALuna2:35476

Quantitative assessment of microperfusion by indocyanine green angiography in kidney transplantation resembles chronic morphological changes in kidney specimens - Rother, Ulrich; Amann, Kerstin Ute; Adler, Werner; Nawroth, Nina; Karampinis, Ioannis; Keese, Michael; Manap, Serhat; Regus, Susanne; Meyer, Alexander; Porubsky, Stefan; Hilgers, Karl Friedrich; Krämer, Bernhard K.; et al. (Microcirculation, 2019)
OBJECTIVE: Indocyanine green fluorescence angiography enables a quantitative real-time perfusion assessment in kidney transplantation. The results of intraoperative microperfusion of the kidney allograft were compared to the renal chronicity score in pre-transplantation kidney biopsy specimens. The intrarenal resistance index was calculated by duplex sonography as a method of reference. METHODS: Seventy-seven patients with end stage renal disease undergoing kidney transplantation were prospectively included in two centers. Correlation analysis of chronic changes in kidney biopsy specimens and the ingress of ICG fluorescence signal were investigated. RESULTS: The results yielded a significantly negative correlation for the renal chronicity (r= -0.294, p=0.017) as well as the intestinal fibrosis and tubular atrophy score (r=-0.328, p=0.007). There was a significant inverse relationship between the ingress and the mean RI values of the upper pole of the kidney allograft. CONCLUSION: In summary, fluorescence angiography reflects preexisting morphological changes of the renal cortex. ICG angiography may serve as an alternative method for the assessment of microperfusion of the kidney allograft. This article is protected by copyright. All rights reserved.
EVALuna2:35427

Recombinant Adenosine Deaminase Ameliorates Inflammation, Vascular Disease, and Fibrosis in Preclinical Models of Systemic Sclerosis - Zhang, Yun; Zhu, Honglin; Layritz, Florian; Luo, Hui; Wohlfahrt, Thomas; Chen, Chih-Wei; Soare, Alina; Bergmann, Christina; Ramming, Andreas; Groeber, Florian; Reuter, Christian; Fornasini, Gianfranco; et al. (Arthritis and Rheumatology, 2020)
Objective: Systemic sclerosis (SSc) is characterized by fibrosis, vascular disease, and inflammation. Adenosine signaling plays a central role in fibroblast activation. We undertook this study to evaluate the therapeutic effects of adenosine depletion with PEGylated adenosine deaminase (PEG-ADA) in preclinical models of SSc. Methods: The effects of PEG-ADA on inflammation, vascular remodeling, and tissue fibrosis were analyzed in Fra-2 mice and in a B10.D2→BALB/c (H-2d) model of sclerodermatous chronic graft-versus-host disease (GVHD). The effects of PEG-ADA were confirmed in vitro in a human full-thickness skin model. Results: PEG-ADA effectively inhibited myofibroblast differentiation and reduced pulmonary fibrosis by 34.3% (with decreased collagen expression) (P = 0.0079; n = 6), dermal fibrosis by 51.8% (P = 0.0006; n = 6), and intestinal fibrosis by 17.7% (P = 0.0228; n = 6) in Fra-2 mice. Antifibrotic effects of PEG-ADA were also demonstrated in sclerodermatous chronic GVHD (reduced by 38.4%) (P = 0.0063; n = 8), and in a human full-thickness skin model. PEG-ADA treatment decreased inflammation and corrected the M2/Th2/group 2 innate lymphoid cell 2 bias. Moreover, PEG-ADA inhibited proliferation of pulmonary vascular smooth muscle cells (reduced by 40.5%) (P < 0.0001; n = 6), and prevented thickening of the vessel walls (reduced by 39.6%) (P = 0.0028; n = 6) and occlusions of pulmonary arteries (reduced by 63.9%) (P = 0.0147; n = 6). Treatment with PEG-ADA inhibited apoptosis of microvascular endothelial cells (reduced by 65.4%) (P = 0.0001; n = 6) and blunted the capillary rarefication (reduced by 32.5%) (P = 0.0199; n = 6). RNA sequencing demonstrated that treatment with PEG-ADA normalized multiple pathways related to fibrosis, vasculopathy, and inflammation in Fra-2 mice. Conclusion: Treatment with PEG-ADA ameliorates the 3 cardinal features of SSc in pharmacologically relevant and well-tolerated doses. These findings may have direct translational implications, as PEG-ADA has already been approved by the Food and Drug Administration for the treatment of patients with ADA-deficient severe combined immunodeficiency disease.
CRIS-Team Scopus Importer:2020-07-10

Recombinant spider silk protein eADF4(C16)-RGD coatings are suitable for cardiac tissue engineering - Kramer, Johannes P.M.; Aigner, Tamara B.; Petzold, Jana; Roshanbinfar, Kaveh; Scheibel, Thomas; Engel, Felix (Scientific Reports, 2020)
Cardiac tissue engineering is a promising approach to treat cardiovascular diseases, which are a major socio-economic burden worldwide. An optimal material for cardiac tissue engineering, allowing cardiomyocyte attachment and exhibiting proper immunocompatibility, biocompatibility and mechanical characteristics, has not yet emerged. An additional challenge is to develop a fabrication method that enables the generation of proper hierarchical structures and constructs with a high density of cardiomyocytes for optimal contractility. Thus, there is a focus on identifying suitable materials for cardiac tissue engineering. Here, we investigated the interaction of neonatal rat heart cells with engineered spider silk protein (eADF4(C16)) tagged with the tripeptide arginyl-glycyl-aspartic acid cell adhesion motif RGD, which can be used as coating, but can also be 3D printed. Cardiomyocytes, fibroblasts, and endothelial cells attached well to eADF4(C16)-RGD coatings, which did not induce hypertrophy in cardiomyocytes, but allowed response to hypertrophic as well as proliferative stimuli. Furthermore, Kymograph and MUSCLEMOTION analyses showed proper cardiomyocyte beating characteristics on spider silk coatings, and cardiomyocytes formed compact cell aggregates, exhibiting markedly higher speed of contraction than cardiomyocyte mono-layers on fibronectin. The results suggest that eADF4(C16)-RGD is a promising material for cardiac tissue engineering.
CRIS-Team Scopus Importer:2020-06-09

Recommendations for mRNA analysis of micro-dissected glomerular tufts from paraffin-embedded human kidney biopsy samples - Bockmeyer, Clemens L.; Wittig, Juliane; Saeuberlich, Karen; Selhausen, Philipp; Esser, Marc; Zeuschner, Philip; Modde, Friedrich; Amann, Kerstin Ute; Daniel, Christoph (Bmc Molecular Biology, 2018)
BACKGROUND: Glomeruli are excellent pre-determined natural structures for laser micro-dissection. Compartment-specific glomerular gene expression analysis of formalin-fixed paraffin-embedded renal biopsies could improve research applications. The major challenge for such studies is to obtain good-quality RNA from small amounts of starting material, as applicable for the analysis of glomerular compartments. In this work, we provide data and recommendations for an optimized workflow of glomerular mRNA analysis. RESULTS: With a proper resolution of the camera and screen provided by the next generation of micro-dissection systems, we are able to separate parietal epithelial cells from glomerular tufts. Selected compartment-specific transcripts (WT1 and GLEPP1 for glomerular tuft as well as PAX2 for parietal epithelial cells) seem to be reliable discriminators for these micro-dissected glomerular substructures. Using the phenol-chloroform extraction and hemalaun-stained sections (2 µm), high amounts of Bowman's capsule transections (> 300) reveal sufficient RNA concentrations (> 300 ng mRNA) for further analysis. For comparison, in unstained sections from a number of 60 glomerular transections upwards, a minimum amount of 157 ng mRNA with a reasonable mRNA purity [A260/A280 ratio of 1.5 (1.4/1.7) median (25th/75th percentiles)] was reversely transcribed into cDNA. Comparing the effect of input RNA (20, 60, 150 and 300 micro-dissected glomerular transections), transcript expression of POLR2A significantly correlated when 60 and 150 laser micro-dissected glomerular transections were used for analysis. There was a lower inter-assay coefficient of variability for ADAMTS13, when at least 60 glomerular transections were used. According to the algorithms of geNormPlus and NormFinder, PGK1 and PPIA are more stable glomerular reference transcripts compared to GUSB, GAPDH, POLR2A, RPLPO, TBP, B2M, ACTB, 18SrRNA and HMBS. CONCLUSIONS: Our approach implements compartment-specific glomerular mRNA expression analysis into research applications, even regarding glomerular substructures like parietal epithelial cells. We recommend using of at least 60 micro-dissected unstained glomerular or 300 hemalaun-stained Bowman's capsule transections to obtain sufficient input mRNA for reproducible results. Hereby, the range of RNA concentrations in 60 micro-dissected glomeruli is low and appropriate normalization of Cq values using our suggested reference transcripts (PGK1 and PPIA) allows compensation with respect to different amounts of RNA purity and quantity.
EVALuna2:34425

Reconfiguration and loss of peritubular capillaries in chronic kidney disease. - Gaupp, Charlotte; Schmid, Benjamin; Tripal, Philipp; Edwards, Aurélie; Daniel, Christoph; Zimmermann, Stefan; Goppelt-Strübe, Margarete; Willam, Carsten; Rosen, Seymour; Schley, Gunnar (Scientific Reports, 2023)
Functional and structural alterations of peritubular capillaries (PTCs) are a major determinant of chronic kidney disease (CKD). Using a software-based algorithm for semiautomatic segmentation and morphometric quantification, this study analyzes alterations of PTC shape associated with chronic tubulointerstitial injury in three mouse models and in human biopsies. In normal kidney tissue PTC shape was predominantly elongated, whereas the majority of PTCs associated with chronic tubulointerstitial injury had a rounder shape. This was reflected by significantly reduced PTC luminal area, perimeter and diameters as well as by significantly increased circularity and roundness. These morphological alterations were consistent in all mouse models and human kidney biopsies. The mean circularity of PTCs correlated significantly with categorized glomerular filtration rates and the degree of interstitial fibrosis and tubular atrophy (IFTA) and classified the presence of CKD or IFTA. 3D reconstruction of renal capillaries revealed not only a significant reduction, but more importantly a substantial simplification and reconfiguration of the renal microvasculature in mice with chronic tubulointerstitial injury. Computational modelling predicted that round PTCs can deliver oxygen more homogeneously to the surrounding tissue. Our findings indicate that alterations of PTC shape represent a common and uniform reaction to chronic tubulointerstitial injury independent of the underlying kidney disease.
EVALuna2:561937

Reconstitution of EBV-directed T cell immunity by adoptive transfer of peptide-stimulated T cells in a patient after allogeneic stem cell transplantation for AITL - Cobo, María Fernanda Lammoglia; Ritter, Julia; Gary, Regina; Seitz, Volkhard; Mautner, Josef; Aigner, Michael; Völkl, Simon; Schaffer, Stefanie; Moi, Stephanie; Seegebarth, Anke; Bruns, Heiko; Rösler, Wolf; et al. (PLoS Pathogens, 2022)
Reconstitution of the T cell repertoire after allogeneic stem cell transplantation is a long and often incomplete process. As a result, reactivation of Epstein-Barr virus (EBV) is a frequent complication that may be treated by adoptive transfer of donor-derived EBV-specific T cells. We generated donor-derived EBV-specific T cells by stimulation with peptides representing defined epitopes covering multiple HLA restrictions. T cells were adoptively transferred to a patient who had developed persisting high titers of EBV after allogeneic stem cell transplantation for angioimmunoblastic T-cell lymphoma (AITL). T cell receptor beta (TCRβ) deep sequencing showed that the T cell repertoire of the patient early after transplantation (day 60) was strongly reduced and only very low numbers of EBV-specific T cells were detectable. Manufacturing and in vitro expansion of donor-derived EBV-specific T cells resulted in enrichment of EBV epitope-specific, HLA-restricted T cells. Monitoring of T cell clonotypes at a molecular level after adoptive transfer revealed that the dominant TCR sequences from peptide-stimulated T cells persisted long-term and established an EBV-specific TCR clonotype repertoire in the host, with many of the EBV-specific TCRs present in the donor. This reconstituted repertoire was associated with immunological control of EBV and with lack of further AITL relapse.
CRIS-Team Scopus Importer:2022-05-20

Recurrent novel HMGA2-NCOR2 fusions characterize a subset of keratin-positive giant cell-rich soft tissue tumors - Agaimy, Abbas; Michal, Michael; Stoehr, Robert; Ferrazzi, Fulvia; Fabian, Pavel; Michal, Michal; Franchi, Alessandro; Haller, Florian; Folpe, Andrew L.; Kosemehmetoglu, Kemal (Modern Pathology, 2021)
Giant cell tumors of soft tissue (GCT-ST) are rare low-grade neoplasms that were at one time thought to represent the soft tissue counterparts of GCT of bone (GCT-B) but are now known to lack the H3F3 mutations characteristic of osseous GCT. We present six distinctive giant cell-rich soft tissue neoplasms that expressed keratins and carried a recurrent HMGA2-NCOR2 gene fusion. Patients were five females and one male aged 14-60 years (median, 29). All presented with superficial (subcutaneous) masses that were removed by conservative marginal (3) or wide (2) local excision. The tumors originated in the upper extremity (2), lower extremity (2), head/neck (1), and trunk (1). Five patients with follow-up (median, 21 months; range, 14-168) remained disease-free. Grossly, all tumors were well-demarcated but not encapsulated with variable lobulation. Histologically, they were composed of bland plump epithelioid or ovoid to spindled mononuclear cells admixed with evenly distributed multinucleated osteoclast-type giant cells. Foci of stromal hemorrhage and hemosiderin were seen in all cases. The mitotic activity ranged from 2 to 14/10 high power fields (median: 10). Foci of necrosis and vascular invasion were seen in one case each. The mononuclear cells were immunoreactive with the AE1/AE3 keratin cocktail and less frequently/less diffusely for K7 and K19 but lacked expression of other lineage-associated markers. RNA-based next-generation sequencing revealed an HMGA2-NCOR2 fusion in all tumors. None of the keratin-negative conventional GCT-ST showed the HMGA2-NCOR2 fusion (0/7). Metaplastic bone (4/9) and SATB2 expression (3/4) were frequent in keratin-negative conventional GCT-ST but were lacking in keratin-positive HMGA2-NCOR2 fusion-positive tumors. The distinctive immunophenotype and genotype of these tumors strongly suggest that they represent a discrete entity, differing from conventional GCT-ST and other osteoclast-rich morphologic mimics. Their natural history appears favorable, although a study of additional cases and longer follow-up are warranted.
CRIS-Team WoS Importer:2021-03-26

Reduction in Renal Heme Oxygenase-1 Is Associated with an Aggravation of Kidney Injury in Shiga Toxin-Induced Murine Hemolytic-Uremic Syndrome. - Mestekemper, Antonio N.; Pirschel, Wiebke; Krieg, Nadine; Paulmann, Maria K.; Daniel, Christoph; Amann, Kerstin Ute; Coldewey, Sina M. (Toxins, 2024)
Hemolytic-uremic syndrome (HUS) is a systemic complication of an infection with Shiga toxin (Stx)-producing enterohemorrhagic Escherichia coli, primarily leading to acute kidney injury (AKI) and microangiopathic hemolytic anemia. Although free heme has been found to aggravate renal damage in hemolytic diseases, the relevance of the heme-degrading enzyme heme oxygenase-1 (HO-1, encoded by Hmox1) in HUS has not yet been investigated. We hypothesized that HO-1, also important in acute phase responses in damage and inflammation, contributes to renal pathogenesis in HUS. The effect of tamoxifen-induced Hmox1 gene deletion on renal HO-1 expression, disease progression and AKI was investigated in mice 7 days after HUS induction. Renal HO-1 levels were increased in Stx-challenged mice with tamoxifen-induced Hmox1 gene deletion (Hmox1R26Δ/Δ) and control mice (Hmox1lox/lox). This HO-1 induction was significantly lower (-43%) in Hmox1R26Δ/Δ mice compared to Hmox1lox/lox mice with HUS. Notably, the reduced renal HO-1 expression was associated with an exacerbation of kidney injury in mice with HUS as indicated by a 1.7-fold increase (p = 0.02) in plasma neutrophil gelatinase-associated lipocalin (NGAL) and a 1.3-fold increase (p = 0.06) in plasma urea, while other surrogate parameters for AKI (e.g., periodic acid Schiff staining, kidney injury molecule-1, fibrin deposition) and general disease progression (HUS score, weight loss) remained unchanged. These results indicate a potentially protective role of HO-1 in the pathogenesis of Stx-mediated AKI in HUS.
EVALuna2:578194

Re-expression of pro-fibrotic, embryonic preserved mediators in irradiated arterial vessels of the head and neck region - Möbius, Patrick; Preidl, Raimund; Weber, Manuel; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Wehrhan, Falk (Strahlentherapie und Onkologie, 2017)
Surgical treatment of head and neck malignancies frequently includes microvascular free tissue transfer. Preoperative radiotherapy increases postoperative fibrosis-related complications up to transplant loss. Fibrogenesis is associated with re-expression of embryonic preserved tissue developmental mediators: osteopontin (OPN), regulated by sex-determining region Y-box 9 (Sox9), and homeobox A9 (HoxA9) play important roles in pathologic tissue remodeling and are upregulated in atherosclerotic vascular lesions; dickkopf-1 (DKK1) inhibits pro-fibrotic and atherogenic Wnt signaling. We evaluated the influence of irradiation on expression of these mediators in arteries of the head and neck region.DKK1, HoxA9, OPN, and Sox9 expression was examined immunohistochemically in 24 irradiated and 24 nonirradiated arteries of the lower head and neck region. The ratio of positive cells to total cell number (labeling index) in the investigated vessel walls was assessed semiquantitatively.DKK1 expression was significantly decreased, whereas HoxA9, OPN, and Sox9 expression were significantly increased in irradiated compared to nonirradiated arterial vessels.Preoperative radiotherapy induces re-expression of embryonic preserved mediators in arterial vessels and may thus contribute to enhanced activation of pro-fibrotic downstream signaling leading to media hypertrophy and intima degeneration comparable to fibrotic development steps in atherosclerosis. These histopathological changes may be promoted by HoxA9-, OPN-, and Sox9-related inflammation and vascular remodeling, supported by downregulation of anti-fibrotic DKK1. Future pharmaceutical strategies targeting these vessel alterations, e. g., bisphosphonates, might reduce postoperative complications in free tissue transfer.
EVALuna2:24435

Relevance of glomerular c4d deposition in pediatric patients with henoch-schönlein purpura compared to IgA nephritis - Benz, Kerstin; Ferrazzi, Fulvia; Galiano, Matthias; Sauerstein, Katja; Vonbrunn, Eva; Daniel, Christoph; Büttner-Herold, Maike; Amann, Kerstin Ute (Journal of Nephropathology, 2021)
Introduction: IgA nephropathy (IgAN) is the most common primary glomerulonephritis (GN) in western countries and Henoch-Schönlein purpura nephritis (HSPN) is the most common form of vasculitis in childhood. Renal biopsy findings in both nephropathies are often similar and are characterized by mesangioproliferative GN with mesangial or mesangiocapillary IgA and C3c deposits. Objectives: The aim of this study was to investigate the significance of glomerular C4d-deposition as a discriminating factor between pediatric HSPN and IgAN. Patients and Methods: We retrospectively analyzed patient records and renal biopsies from 53 pediatric patients from one single center with a median age of 10.5 years (range 2.3-18 years). Twenty-two patients suffered from IgAN and 31 from HSPN. Work-up of all renal biopsies was performed using standard protocols including immunohistochemistry for C4d. Results: Pediatric IgAN patients presented significantly more often with gross hematuria, higher serum creatinine, lower glomerular filtration rate, lower serum C3 and proteinuria and on histology less endocapillary hypercellularity compared to HSPN patients. However, the rate of glomerular C4d-positivity was not different between IgAN (36%) and HSPN (42%). Comparing all cases with positive versus negative glomerular C4d-staining, pediatric patients with glomerular C4d-positivity showed significantly lesser gross hematuria and received significantly more often cyclophosphamide. This was in line with a tendency towards more proteinuria, hypertension and renal insufficiency at last follow-up in C4d-positive compared to C4d-negative patients. Conclusion: In conclusion, in our monocentric study glomerular C4d does not differ between pediatric HSPN and IgAN, but was associated with a tendency to a more severe course of the disease that needs to be confirmed in larger multicentric studies.
CRIS-Team Scopus Importer:2021-01-22
Keywords: C4d staining; Glomerulonephritis; Henoch-Schönlein purpura; IgA nephritis; IgA vasculitis; Pediatric nephrology

Relevance of receptor for advanced glycation end products (RAGE) in murine antibody-mediated autoimmune diseases - Eichhorst, Alexandra; Daniel, Christoph; Rzepka, Rita; Sehnert, Bettina; Nimmerjahn, Falk; Voll, Reinhard E.; Chevalier, Nina (International Journal of Molecular Sciences, 2019)
It is incompletely understood how self-antigens become targets of humoral immunity in antibody-mediated autoimmune diseases. In this context, alarmins are discussed as an important level of regulation. Alarmins are recognized by various receptors, such as receptor for advanced glycation end products (RAGE). As RAGE is upregulated under inflammatory conditions, strongly binds nucleic acids and mediates pro-inflammatory responses upon alarmin recognition, our aim was to examine its contribution to immune complex-mediated autoimmune diseases. This question was addressed employing RAGE−/− animals in murine models of pristane-induced lupus, collagen-induced, and serum-transfer arthritis. Autoantibodies were assessed by enzyme-linked immunosorbent assay, renal disease by quantification of proteinuria and histology, arthritis by scoring joint inflammation. The associated immune status was determined by flow cytometry. In both disease entities, we detected tendentiously decreased autoantibody levels in RAGE−/− mice, however no differences in clinical outcome. In accordance with autoantibody levels, a subgroup of the RAGE−/− animals showed a decrease in plasma cells, and germinal center B cells and an increase in follicular B cells. Based on our results, we suggest that RAGE deficiency alone does not significantly affect antibody-mediated autoimmunity. RAGE may rather exert its effects along with other receptors linking environmental factors to auto-reactive immune responses.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Arthritis; HMGB1; Lupus; RA; RAGE; SLE

Renal complications of cancer therapies - Schanz, M.; Schricker, S.; Pfister, F.; Alscher, M. D.; Kimmel, M. (Drugs of Today, 2018)
Cancer patients often exhibit preexisting renal impairment and are simultaneously at risk for developing further kidney injury due to direct or indirect complications of oncological therapies. The nature of kidney injury is highly dependent on the therapy regimen used, and the spectrum of possible kidney stressors has widened as a result of the development of new therapeutic modalities such as molecular therapy or immunotherapy. Indirect renal complications are often due to volume depletion or other therapy-related side effects. Direct toxicity from "classic" chemotherapy treatments such as cisplatin usually leads to acute tubular necrosis, whereas treatment with protein kinase inhibitors is more likely to cause disorders such as thrombotic microangiopathy. Immunotherapy often affects kidneys through the development of acute interstitial nephritis. Because of the high risk of nephrological complications in oncological patients, close monitoring of renal function and the early involvement of a nephrologist are strongly recommended.
EVALuna2:34902

Renal disease associated with myeloproliferative neoplasms and myelodysplastic syndrome/myeloproliferative neoplasms - Büttner-Herold, Maike; Sticht, Carsten; Wiech, Thorsten; Porubsky, Stefan (Histopathology, 2020)
Aims: Renal changes in patients with myeloproliferative neoplasms (MPNs) or myelodysplastic syndrome (MDS)/MPNs have been addressed by few, respectively no, reports. The aim of this study was to focus on a systematic evaluation of renal biopsies in patients with MPNs or MDS/MPNs. Methods and results: The cohort comprised 29 patients (23 men) aged 67 ± 11 years (mean ± standard deviation), diagnosed with chronic myeloid leukaemia (n = 5), polycythaemia vera (n = 9), primary myelofibrosis (n = 5), essential thrombocythaemia (n = 2), or chronic myelomonocytic leukaemia (n = 4), as well as MPNs or MDS/MPNs not otherwise specified (n = 4). Patients manifested with proteinuria (93%), partially in the nephrotic range (46%), haematuria (72%), and impaired kidney function (93%). The most prominent histological findings included double-contoured glomerular basement membranes (71%), acute endothelial damage (68%), intracapillary platelet aggregation (62%), mesangiolysis (21%), thrombotic microangiopathy (24%), segmental glomerulosclerosis (66%), mesangial hypercellularity and sclerosis, extramedullary haematopoiesis (17%), and also IgA nephropathy (21%) and glomerulonephritis (GN) with features of infection-related GN (21%). MPN and MDS/MPN patients showed significantly more chronic changes than age-matched and sex-matched controls, including global and segmental glomerulosclerosis, mesangial sclerosis, and hypercellularity, whereas the extent of arteriosclerosis was comparable. Conclusions: MPN and MDS/MPN patients show glomerular scarring that exceeds age-related phenomena. Ongoing endothelial damage, growth factors released by platelets and deposition of immune complexes are probably the causative mechanisms. Early recognition of renal failure heralded by proteinuria and haematuria, and consequent control of risk factors for kidney failure, should be recommended for MPN and MDS/MPN patients.
CRIS-Team Scopus Importer:2020-12-25
Keywords: endothelium; glomerulopathy; myelodysplastic syndrome/myeloproliferative neoplasms; myeloproliferative neoplasms; thrombotic microangiopathy

Renal effects of the serine protease inhibitor aprotinin in healthy conscious mice - Woerner, Stefan; Bohnert, Bernhard N.; Woern, Matthias; Xiao, Mengyun; Janessa, Andrea; Birkenfeld, Andreas L.; Amann, Kerstin Ute; Daniel, Christoph; Artunc, Ferruh (Acta Pharmacologica Sinica, 2021)
Treatment with aprotinin, a broad-spectrum serine protease inhibitor with a molecular weight of 6512 Da, was associated with acute kidney injury, which was one of the reasons for withdrawal from the market in 2007. Inhibition of renal serine proteases regulating the epithelial sodium channel ENaC could be a possible mechanism. Herein, we studied the effect of aprotinin in wild-type 129S1/SvImJ mice on sodium handling, tubular function, and integrity under a control and low-salt diet. Mice were studied in metabolic cages, and aprotinin was delivered by subcutaneously implanted sustained release pellets (2 mg/day over 10 days). Mean urinary aprotinin concentration ranged between 642 ± 135 (day 2) and 127 ± 16 (day 8) µg/mL. Aprotinin caused impaired sodium preservation under a low-salt diet while stimulating excessive hyperaldosteronism and unexpectedly, proteolytic activation of ENaC. Aprotinin inhibited proximal tubular function leading to glucosuria and proteinuria. Plasma urea and cystatin C concentration increased significantly under aprotinin treatment. Kidney tissues from aprotinin-treated mice showed accumulation of intracellular aprotinin and expression of the kidney injury molecule 1 (KIM-1). In electron microscopy, electron-dense deposits were observed. There was no evidence for kidney injury in mice treated with a lower aprotinin dose (0.5 mg/day). In conclusion, high doses of aprotinin exert nephrotoxic effects by accumulation in the tubular system of healthy mice, leading to inhibition of proximal tubular function and counterregulatory stimulation of ENaC-mediated sodium transport.
CRIS-Team Scopus Importer:2021-04-09
Keywords: aprotinin; epithelial sodium channel; renal dysfunction; serine proteases; sodium

Renal fibrosis is the common feature of autosomal dominant tubulointerstitial kidney diseases caused by mutations in mucin 1 or uromodulin - Ekici, Arif Bülent; Hackenbeck, Thomas; Moriniere, Vincent; Panness, Andrea; Büttner, Maike; Uebe, Steffen; Janka, Rolf Matthias; Wiesener, Antje; Hermann, Ingo; Grupp, Sina; Hornberger, Martin; Huber, Tobias B.; et al. (Kidney International, 2014)
For decades, ill-defined autosomal dominant renal diseases have been reported, which originate from tubular cells and lead to tubular atrophy and interstitial fibrosis. These diseases are clinically indistinguishable, but caused by mutations in at least four different genes: UMOD, HNF1B, REN, and, as recently described, MUC1. Affected family members show renal fibrosis in the biopsy and gradually declining renal function, with renal failure usually occurring between the third and sixth decade of life. Here we describe 10 families and define eligibility criteria to consider this type of inherited disease, as well as propose a practicable approach for diagnosis. In contrast to what the frequently used term 'Medullary Cystic Kidney Disease' implies, development of (medullary) cysts is neither an early nor a typical feature, as determined by MRI. In addition to Sanger and gene panel sequencing of the four genes, we established SNaPshot minisequencing for the predescribed cytosine duplication within a distinct repeat region of MUC1 causing a frameshift. A mutation was found in 7 of 9 families (3 in UMOD and 4 in MUC1), with one indeterminate (UMOD p.T62P). On the basis of clinical and pathological characteristics we propose the term 'Autosomal Dominant Tubulointerstitial Kidney Disease' as an improved terminology. This should enhance recognition and correct diagnosis of affected individuals, facilitate genetic counseling, and stimulate research into the underlying pathophysiology.
EVALuna2:3695

Renal Function, Blood Pressure, and Histologic Changes in Living Kidney Transplant Recipients from Hypertensive Donors - Dienemann, T.; Schellenberg, J.; Amann, Kerstin Ute; Heller, K.; Weidemann, Alexander (2018)
EVALuna2:34437

Renal involvement in sarcoidosis: Histologic findings and clinical course - Naderi, Shirin; Amann, Kerstin Ute; Janssen, Ulf (Nephrology @ Point of Care, 2019)
Background: Renal failure in sarcoidosis is rare and data on its long-term outcome are scarce. Aim: To investigate the pattern of renal involvement in sarcoidosis, its clinical course and response to treatment in the long-term. Methods: A single-center retrospective study with review of renal biopsies and medical charts was performed. Results: Between January 2005 and December 2016, seven patients with sarcoidosis underwent a kidney biopsy. This is equivalent to a frequency of 1.6% in a total of 434 biopsies from native kidney performed in our institution. All patients presented with renal failure. Five patients had granulomatous interstitial nephritis (GIN) and one patient each interstitial nephritis without granuloma and nephrocalcinosis. Three patients had concomitant glomerular disease: IgA nephropathy (n = 2), membranous and focal proliferative glomerulonephritis (n = 1). Most patients (n = 5) presented with hypercalcemia. All patients initially received oral prednisolone 1 mg/kg/day (n = 3) or 0.5 mg/kg/day (n = 4), respectively, with subsequent tapering or suspension. One patient was started on azathioprine after 18 months to spare steroids. After a mean follow-up of 59 months mean estimated glomerular filtration rate (eGFR) had improved from 19 +/- 7 at presentation to 49 +/- 16 mL/min. No patient required dialysis. All patients started on prednisolone 1 mg/kg/day developed transient diabetes mellitus while patients on 0.5 mg/kg/day did not. Renal function improvement did not differ between both treatment groups. Conclusion: GIN was the most common diagnosis in sarcoidosis patients with renal failure. Initial hypercalcemia was observed in the majority. Early steroid treatment lead to sustained renal function improvement.
CRIS-Team WoS Importer:2019-04-16

Renal leishmaniasis as unusual cause of nephrotic syndrome in an HIV patient - Amann, Kerstin Ute; Bogdan, Christian; Harrer, Thomas; Rech, Jürgen (Journal of the American Society of Nephrology, 2012)
Renal involvement is a rare complication in HIV-1-infected patients leading to various pathologies and clinical symptoms. In addition to the classic HIV-1-associated nephropathy with collapsing-type focal segmental glomerulosclerosis and characteristic tubulocystic changes, which is more common in Afro-American than in Caucasian HIV-1 patients, immune complex GNs such as membranous GN and membranoproliferative GN are particularly common renal manifestations. Besides HIV-1 itself, a number of opportunistic infections may cause renal disease in HIV-1-infected patients. In this study, we report an unusual case of HIV-1 infection with a severe renal manifestation of systemic leishmaniasis that developed years after repeated visits to Mediterranean countries. The case presents several remarkable clinical, pathologic, and therapeutic aspects that may be important for daily clinical practice. Copyright © 2012 by the American Society of Nephrology.
CRIS-Team Scopus Importer:2021-02-03

Renal pathology Nierenpathologie - Amann, Kerstin Ute (Die Pathologie, 2024)
CRIS-Team Scopus Importer:2024-07-05

Renal replacement therapy-requiring acute kidney injury due to tubulointerstitial nephritis and uveitis syndrome: case report - Marahrens, B.; Amann, Kerstin Ute; Asmus, K.; Erfurt, S.; Patschan, D. (Journal of Medical Case Reports, 2021)
Background: Acute kidney injury is a major challenge for today’s healthcare systems around the globe. Renal replacement therapy has been shown to be beneficial in acute kidney injury, but treatment highly depends on the cause of the acute kidney injury. One less common cause is tubulointerstitial nephritis, which comes in different entities. A very rare type of tubulointerstitial nephritis is tubulointerstitial nephritis and uveitis syndrome, in which the patient presents with additional uveitis. Case presentation: A 19-year-old caucasian male presented with mild dyspnea, lack of appetite, weight loss, and moderate itchiness. Lab results showed an acute kidney injury with marked increase of serum creatinine. The patient was started on prednisolone immediately after admission. As the patient in this case showed symptoms of uremia on admission, we decided to establish renal replacement therapy, which is unusual in tubulointerstitial nephritis and uveitis syndrome. During his course of dialysis, the patient developed symptoms of sepsis probably due to a catheter-related infection requiring intensive care and antibiotic treatment, which had to be terminated early as the patient developed a rash. Intensified immunosuppression, combined with antibiotics, significantly resolved excretory kidney dysfunction. Conclusions: Since both the primary inflammatory process and the secondary infectious complication significantly impaired excretory kidney function, kidney function of younger individuals with new-onset anterior uveitis should be monitored over time and during follow-up.
CRIS-Team Scopus Importer:2021-12-31
Keywords: AKI; Case report; Interstitial nephritis; RRT; TINU syndrome

Renal tubular HIF-2α expression requires VHL inactivation and causes fibrosis and cysts - Schietke, Ruth E.; Hackenbeck, Thomas; Tran, Maxine; Guenther, Regina; Klanke, Bernd; Warnecke, Christina; Knaup, Karl X.; Shukla, Deepa; Rosenberger, Christian; Koesters, Robert; Bachmann, Sebastian; Betz, Peter; et al. (PLoS ONE, 2012)
The Hypoxia-inducible transcription Factor (HIF) represents an important adaptive mechanism under hypoxia, whereas sustained activation may also have deleterious effects. HIF activity is determined by the oxygen regulated α-subunits HIF-1α or HIF-2α. Both are regulated by oxygen dependent degradation, which is controlled by the tumor suppressor "von Hippel-Lindau" (VHL), the gatekeeper of renal tubular growth control. HIF appears to play a particular role for the kidney, where renal EPO production, organ preservation from ischemia-reperfusion injury and renal tumorigenesis are prominent examples. Whereas HIF-1α is inducible in physiological renal mouse, rat and human tubular epithelia, HIF-2α is never detected in these cells, in any species. In contrast, distinct early lesions of biallelic VHL inactivation in kidneys of the hereditary VHL syndrome show strong HIF-2α expression. Furthermore, knockout of VHL in the mouse tubular apparatus enables HIF-2α expression. Continuous transgenic expression of HIF-2α by the Ksp-Cadherin promotor leads to renal fibrosis and insufficiency, next to multiple renal cysts. In conclusion, VHL appears to specifically repress HIF-2α in renal epithelia. Unphysiological expression of HIF-2α in tubular epithelia has deleterious effects. Our data are compatible with dedifferentiation of renal epithelial cells by sustained HIF-2α expression. However, HIF-2α overexpression alone is insufficient to induce tumors. Thus, our data bear implications for renal tumorigenesis, epithelial differentiation and renal repair mechanisms. © 2012 Schietke et al.

Renal uptake of the antiapoptotic protein survivin is mediated by megalin at the apical membrane of the proximal tubule - Jobst-Schwan, Tilman; Knaup, Karl; Nielsen, Rikke; Hackenbeck, Thomas; Büttner-Herold, Maike; Lechler, Philipp; Kroening, Sven; Goppelt-Strübe, Margarete; Schlötzer-Schrehardt, Ursula; Fuernrohr, Barbara G.; Voll, Reinhard E.; Amann, Kerstin Ute; et al. (American Journal of Physiology-Renal Physiology, 2013)
The inhibitor of apoptosis protein survivin is a bifunctional molecule that regulates cellular division and survival. We have previously shown that survivin protein can be found at high concentrations in the adult kidney, particularly in the proximal tubules. Here, survivin is localized primarily at the apical membrane, a pattern that may indicate absorption of the protein. Several proteins in primary urine are internalized by megalin, an endocytosis receptor, which is in principle found in the same localization as survivin. Immunolabeling for survivin in different species confirmed survivin signal localizing to the apical membrane of the proximal tubule. Immunoelectron microscopy also showed apical localization of survivin in human kidneys. Furthermore, in polarized human primary tubular cells endogenous as well as external recombinant survivin is stored in the apical region of the cells. Costaining of survivin and megalin by immunohistochemistry and immunoelectron microscopy confirmed colocalization. Finally, by surface plasmon resonance we were able to demonstrate that survivin binds megalin and cubilin and that megalin knockout mice lose survivin through the urine. Survivin accumulates at the apical membrane of the renal tubule by reuptake, which is achieved by the endocytic receptor megalin, collaborating with cubilin. For this to occur, survivin will have to circulate in the blood and be filtered into the primary urine. It is not known at this stage what the functional role of tubular survivin is. However, a small number of experimental and clinical reports implicate that renal survivin is important for functional integrity of the kidney. © 2013 by the American Physiological Society.
Created from Fastlane, Scopus look-up
Keywords: Acute kidney injury; Apoptosis; Glomerular filtration; Lysosomes; Proteinuria

Reproducibility of mRNA-Based Testing of ESR1, PGR, ERBB2, and MKI67 Expression in Invasive Breast Cancer-A Europe-Wide External Quality Assessment - Erber, Ramona; Hartmann, Arndt; Fasching, Peter; Rübner, Matthias; Stöhr, Robert; Beckmann, Matthias; Zentgraf, Miriam; Popp, Verena; Weidler, Jodi; Simon, Iris; Becker, Steffi; Hübner, Hanna; et al. (Cancers, 2021)
Simple Summary Four biomarkers [estrogen receptor (ER), progesterone receptor (PgR), Ki-67, and HER2], are used to stratify breast cancer (BC) into subtypes predictive of therapy response. In a Europe-wide external quality assessment, we compared performance of an mRNA-based method [Xpert(R) Breast Cancer STRAT4 (CE-IVD)] for determining ESR1, PGR, ERBB2, and MKI67 expression against the gold standard [immunohistochemistry (IHC)/HER2 in situ hybridization (ISH)]. The coordinating center (CC) and five European laboratories tested ten breast cancer samples. STRAT4 binary (positive or negative) results of each marker were compared with the gold standard. ESR1 and ERBB2 mRNA results were concordant with IHC/ISH in all single analyses. In contrast, PGR and MKI67 results were discordant in a few cases, which had STRAT4 expression values close to assay cut-offs and immunohistochemically presented heterogeneous low positive PgR and heterogeneous Ki-67. STRAT4 assay may be a reproducible method. However, cases with expression values close to cut-offs should be carefully reviewed. Estrogen receptor (ER), progesterone receptor (PgR), Ki-67, and HER2 immunohistochemistry (IHC) together with HER2 in situ hybridization (ISH) are utilized to classify invasive breast cancer (IBC) into predictive molecular subtypes. As IHC evaluation may be hampered by analytical errors, gene expression assays could offer a reliable alternative. In this first Europe-wide external quality assessment (EQA) study, we investigated performance of mRNA-based Xpert(R) Breast Cancer STRAT4 (CE-IVD) in five European laboratories. The cohort comprised ten pre-therapy IBC core biopsies diagnosed in the coordinating center (CC). STRAT4 binary (positive or negative) mRNA results of each marker (ESR1, PGR, ERBB2, MKI67) were compared with the gold standard IHC/ISH performed by the CC. Sensitivity, specificity, and accuracy of ESR1 and ERBB2 mRNA were 100% for all samples. In contrast, PGR expression was falsely negative for one case by two sites and MKI67 falsely negative for two cases (respectively by four and one sites). These cases had STRAT4 expression values close to assay cut-offs and immunohistochemically presented heterogeneous low positive PgR and heterogeneous Ki-67. Our EQA shows that STRAT4 mRNA assay may be a reproducible method to evaluate ER, PgR, HER2, and Ki-67 status. However, cases with expression values close to assay cut-offs should be carefully reviewed.
CRIS-Team WoS Importer:2021-10-08

Responsiveness of afferent renal nerve units in renovascular hypertension in rats - Rodionova, Kristina; Hilgers, Karl Friedrich; Rafii-Tabrizi, Salman; Doellner, Johannes; Cordasic, Nada; Linz, Peter; Karl, Annalena; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; et al. (Pflügers Archiv: European Journal of Physiology, 2021)
Previous data suggest that renal afferent nerve activity is increased in hypertension exerting sympathoexcitatory effects. Hence, we wanted to test the hypothesis that in renovascular hypertension, the activity of dorsal root ganglion (DRG) neurons with afferent projections from the kidneys is augmented depending on the degree of intrarenal inflammation. For comparison, a nonhypertensive model of mesangioproliferative nephritis was investigated. Renovascular hypertension (2-kidney, 1-clip [2K1C]) was induced by unilateral clipping of the left renal artery and mesangioproliferative glomerulonephritis (anti-Thy1.1) by IV injection of a 1.75-mg/kg BW OX-7 antibody. Neuronal labeling (dicarbocyanine dye [DiI]) in all rats allowed identification of renal afferent dorsal root ganglion (DRG) neurons. A current clamp was used to characterize neurons as tonic (sustained action potential [AP] firing) or phasic (1-4 AP) upon stimulation by current injection. All kidneys were investigated using standard morphological techniques. DRG neurons exhibited less often tonic response if in vivo axonal input from clipped kidneys was received (30.4% vs. 61.2% control, p < 0.05). However, if the nerves to the left clipped kidneys were cut 7 days prior to investigation, the number of tonic renal neurons completely recovered to well above control levels. Interestingly, electrophysiological properties of neurons that had in vivo axons from the right non-clipped kidneys were not distinguishable from controls. Renal DRG neurons from nephritic rats also showed less often tonic activity upon current injection (43.4% vs. 64.8% control, p < 0.05). Putative sympathoexcitatory and impaired sympathoinhibitory renal afferent nerve fibers probably contribute to increased sympathetic activity in 2K1C hypertension.
CRIS-Team WoS Importer:2021-07-23

Restricted expression of mGCMa in kidney ind thymus - Hashemolhosseini, Said; Hadjihannas, Michel; Haase, Christian; Amann, Kerstin Ute; Wegner, Michael (Mechanisms of Development, 2002)
UnivIS-Import:2015-04-14:Pub.2002.forsch.sonder.sfb423.restri

RNA sequencing reveals induction of specific renal inflammatory pathways in a rat model of malignant hypertension - Menendez-Castro, Carlos; Cordasic, Nada; Fahlbusch, Fabian; Ekici, Arif Bülent; Kirchner, Philipp; Daniel, Christoph; Amann, Kerstin Ute; Velkeen, Roland; Wölfle, Joachim; Schiffer, Mario; Hartner, Andrea; Hilgers, Karl Friedrich (Journal of Molecular Medicine, 2021)
Abstract: In malignant hypertension, far more severe kidney injury occurs than in the “benign” form of the disease. The role of high blood pressure and the renin–angiotensin–aldosterone system is well recognized, but the pathogenesis of the renal injury of malignant hypertension (MH) remains incompletely understood. Using the rat model of two-kidney, one-clip renovascular hypertension in which some but not all animals develop MH, we performed a transcriptomic analysis of gene expression by RNA sequencing to identify transcriptional changes in the kidney cortex specific for MH. Differential gene expression was assessed in three groups: MH, non-malignant hypertension (NMH), and normotensive, sham-operated controls. To distinguish MH from NMH, we considered two factors: weight loss and typical renovascular lesions. Mean blood pressure measured intraarterially was elevated in MH (220 ± 6.5 mmHg) as well as in NMH (192 ± 6.4 mmHg), compared to controls (119 ± 1.7 mmHg, p < 0.05). Eight hundred eighty-six genes were exclusively regulated in MH only. Principal component analysis revealed a separated clustering of the three groups. The data pointed to an upregulation of many inflammatory mechanisms in MH including pathways which previously attracted relatively little attention in the setting of hypertensive kidney injury: Transcripts from all three complement activation pathways were upregulated in MH compared to NMH but not in NMH compared with controls; immunohistochemistry confirmed complement deposition in MH exclusively. The expression of chemokines attracting neutrophil granulocytes (CXCL6) and infiltration of myeloperoxidase-positive cells were increased only in MH rats. The data suggest that these pathways, especially complement deposition, may contribute to kidney injury under MH. Key messages: The most severe hypertension-induced kidney injury occurs in malignant hypertension.In a rat model of malignant hypertension, we assessed transcriptional responses in the kidney exposed to high blood pressure. A broad stimulation of inflammatory mechanisms was observed, but a few specific pathways were activated only in the malignant form of the disease, notably activation of the complement cascades.Complement inhibitors may alleviate the thrombotic microangiopathy of malignant hypertension even in the absence of primary complement abnormalities.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Complement activation; Inflammation; Kidney injury; Malignant hypertension; RNA-Seq; Two-kidney one-clip renovascular hypertension (2K1C)

Role of guanylate binding protein-1 in vascular defects associated with chronic inflammatory diseases - Hammon, Matthias; Herrmann, Martin; Bleiziffer, Oliver; Pryymachuk, Galyna; Andreoli, Laura; Munoz, Luis Enrique; Amann, Kerstin Ute; Mondini, Michele; Gariglio, Marisa; Airo, Paolo; Schellerer, Vera; Hatzopoulos, Antonis K.; et al. (Journal of Cellular and Molecular Medicine, 2011)
Rheumatic autoimmune disorders are characterized by a sustained pro-inflammatory microenvironment associated with impaired function of endothelial progenitor cells (EPC) and concomitant vascular defects. Guanylate binding protein-1 (GBP-1) is a marker and intracellular regulator of the inhibition of proliferation, migration and invasion of endothelial cells induced by several pro-inflammatory cytokines. In addition, GBP-1 is actively secreted by endothelial cells. In this study, significantly increased levels of GBP-1 were detected in the sera of patients with chronic inflammatory disorders. Accordingly we investigated the function of GBP-1 in EPC. Interestingly, stable expression of GBP-1 in T17b EPC induced premature differentiation of these cells, as indicated by a robust up-regulation of both Flk-1 and von Willebrand factor expression. In addition, GBP-1 inhibited the proliferation and migration of EPC in vitro. We confirmed that GBP-1 inhibited vessel-directed migration of EPC at the tissue level using the rat arterio-venous loop model as a novel quantitative in vivo migration assay. Overall, our findings indicate that GBP-1 contributes to vascular dysfunction in chronic inflammatory diseases by inhibiting EPC angiogenic activity via the induction of premature EPC differentiation. © 2011 The Authors Journal of Cellular and Molecular Medicine © 2011 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up
Keywords: Endothelial progenitor cells; Guanylate binding protein-1; Inflammation; Rheumatic autoimmune disorders; Rheumatoid arthritis; Systemic lupus erythematosus; Systemic sclerosis

Role of tumor cell senescence in non-professional phagocytosis and cell-in-cell structure formation - Gottwald, Dorian; Putz, Florian; Hohmann, Nora; Büttner-Herold, Maike; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (BMC Molecular and Cell Biology, 2020)
Background: Non-professional phagocytosis is usually triggered by stimuli such as necrotic cell death. In tumor therapy, the tumors often disappear slowly and only long time after the end of therapy. Here, tumor therapy inactivates the cells by inducing senescence. Therefore, study focused whether senescence is a stimulus for non-professional phagocytosis or whether senescent cells themselves phagocytize non-professionally. Results: Senescence was induced in cell lines by camptothecin and a phagocytosis assay was performed. In tissue of a cohort of 192 rectal cancer patients senescence and non-professional phagocytosis was studied by anti-histone H3K9me3 and anti-E-cadherin staining. Senescent fibroblasts and pancreas carcinoma cells phagocytize necrotic cells but are not phagocytized. In the tissue of rectal carcinoma, senescent cells can phagocytize and can be phagocytized. A high number of senescent cells and, at the same time, high numbers of non-professional phagocytizing cells in the rectal carcinoma tissue lead to an extremely unfavorable prognosis regarding overall survival. Conclusion: Senescent cells can be non-professionally phagocytized and at the same time they can non-professionally phagocytize in vivo. In vitro experiments indicate that it is unlikely that senescence is a strong trigger for non-professional phagocytosis. Combined high rates of non-professional phagocytosis and high rates of senescence are an extremely poor prognostic factor for overall survival.
CRIS-Team Scopus Importer:2020-11-13
Keywords: Camptothecin; Cannibalism; Cell-in-cell; Entosis; Non-professional phagocytosis; Prognostic factor and survival; Rectal cancer; Senescence

Round-Robin test for the histological diagnosis of acute colonic Graft-versus-Host disease validating established histological criteria and grading systems - Hippe, Katrin; Kreft, Andreas; Reu-Hofer, Simone; Rosenwald, Andreas; Ferrazzi, Fulvia; Daniel, Christoph; Amann, Kerstin Ute; Kraus, Sabrina; Holler, Ernst; Kandulski, Arne; Hirsch, Daniela; Buttner, Anke; et al. (Virchows Archiv, 2023)
Histomorpholgy is one of the mainstays of acute Graft-versus-host disease (GvHD) diagnosis. However, concerns about reproducibility and the most appropriate grading system question its usefulness. Our aim was to assess histomorphological parameters and previously reported grading systems for GvHD regarding reproducibility and validity. Moreover, we propose that sum scores, derived by combining separately scored morphological parameters into a total score, might provide a simplified but equally effective means to grade GvHD. A total of 123 colon biopsies were assessed across four pathologists for intestinal GvHD using a Round-Robin test and results were correlated with clinical findings. Interobserver reproducibility was high for histological parameters that were evaluated as indicators of acute GvHD. Published grading systems were moderately reproducible (ICC 0.679–0.769) while simplified sum scores, in comparison, showed better interrater reliability (ICC 0.818–0.896). All grading systems and sum scores were associated with clinical signs of GvHD and in part with therapy response and survival. However, they were not able to stratify patients according to the clinical severity of GvHD. In a hot-spot analysis 1 crypt apoptotic body (CAB) in 10 crypts was a reasonable cut-off value for minimal diagnostic criteria of GvHD. In conclusion, histology can contribute to the diagnosis of GvHD and is reproducible. Published grading systems are able to reflect clinical findings as are simplified sum scores, which showed improved reproducibility and might be easier to handle as they are based on adding up histological parameters rather than transferring histological findings into a separate grading system. Sum scores will have to be further tested in a prospective setting.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Acute Graft-versus-host disease; Colon biopsy; Grading; Interobserver agreement; Round-Robin test

SCNT-derived ESCs with mismatched mitochondria trigger an immune response in allogeneic hosts - Deuse, Tobias; Wang, Dong; Stubbendorff, Mandy; Itagaki, Ryo; Grabosch, Antje; Greaves, Laura C.; Alawi, Malik; Gruenewald, Anne; Hu, Xiaomeng; Hua, Xiaoqin; Velden, Joachim; Reichenspurner, Hermann; et al. (Cell Stem Cell, 2015)
The generation of pluripotent stem cells by somatic cell nuclear transfer (SCNT) has recently been achieved in human cells and sparked new interest in this technology. The authors reporting this methodical breakthrough speculated that SCNT would allow the creation of patient-matched embryonic stem cells, even in patients with hereditary mitochondrial diseases. However, herein we show that mismatched mitochondria in nuclear-transfer-derived embryonic stem cells (NT-ESCs) possess alloantigenicity and are subject to immune rejection. In a murine transplantation setup, we demonstrate that allogeneic mitochondria in NT-ESCs, which are nucleus-identical to the recipient, may trigger an adaptive alloimmune response that impairs the survival of NT-ESC grafts. The immune response is adaptive, directed against mitochondrial content, and amenable for tolerance induction. Mitochondrial alloantigenicity should therefore be considered when developing therapeutic SCNT-based strategies.
EVALuna2:25507

Screening of Micro-organic Compounds in Groundwater from Areas with Chronic Kidney Disease of Unclear Aetiology (CKDu) in the Dry Zone of Sri Lanka - Chandrajith, Rohana; Zwiener, Christian; Daniel, Christoph; Amann, Kerstin Ute; Nanayakkara, Nishantha; Barth, Johannes (Exposure and Health, 2024)
Chronic kidney disease of unknown aetiology (CKDu) occurs in tropical countries, including Latin America, Mexico, Sri Lanka, and India. The disease occurs mainly in men who work in the agricultural sector. Although many studies have been conducted in CKDu areas, hardly any have examined emerging organic contaminants (EOCs) in drinking water. Therefore, this study examined EOCs, including pesticide residues, pharmaceuticals, and personal care products, in 29 shallow groundwater samples collected from wells commonly used by CKDu patients. These patients were identified through renal biopsy examinations from the Girandurukotte and Wilgamuwa regions in the dry zone of Sri Lanka. Of 110 EOCs measured, 40 were found in at least one or more samples. Among the detected EOCs, all groundwater samples examined showed the highest concentrations of caffeine (max: 950 ng/L) and DEET (max: 647 ng/L). In particular, the insect repellents commonly used in the region, such as coils, mats, vaporizers, spray and creams, would be the source of DEET in the environment. Pharmaceuticals and personal care products were the most common EOCs in all groundwater samples, with concentrations ranging from 129 (propylparaben) to 1.26 ng/L (carbamazepine) and 1.25 ng/L (hydrochlorothiazide), respectively, followed by herbicides and fungicides. Sources of such compounds would be insect repellents, antifungal and bactericidal preservatives, and agricultural pesticides. Notably, none of the identified EOCs reached critical values and were often below the values in European drinking water standards. Although primary evidence of EOCs as a cause of the disease does not emerge from the results of this study, regular monitoring of EOCs in groundwater, particularly in the dry zone of Sri Lanka, is essential as the presence of these compounds highlights their vulnerability in shallow groundwater wells.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Emerging contaminants; Personal-care product; Pesticides; Pharmaceuticals; Solid-phase extraction

Selective expression of constitutively activated STAT6 in intestinal epithelial cells promotes differentiation of secretory cells and protection against helminths - Schubart, Christoph; Krljanac, Branislav; Otte, Manuel; Symowski, Cornelia; Martini, Eva; Günther, Claudia; Becker, Christoph; Daniel, Christoph; Vöhringer, David (Mucosal Immunology, 2018)
Intestinal epithelial cells (IECs) constitute an important barrier between host and pathogen. Immune mechanisms that provide protection against gastrointestinal helminths often require IL-4Rα-induced activation of STAT6-regulated genes in IECs. However, it is not known whether STAT6 activation in IECs enhances protective immunity against helminths. Furthermore, the regulation of proliferation and differentiation processes of the intestinal epithelium by IEC-intrinsic STAT6 signaling remains unclear. To address these questions, we generated mice with specific expression of a constitutively active version of STAT6 in IECs. These VillinCre_STAT6vt mice show accumulation of secretory IECs, increased proliferation of IECs and lengthening of the small intestine. They rapidly expelled Nippostrongylus brasiliensis worms even in the absence of T cells. Furthermore, primary infection with Heligmosomoides polygyrus resulted in larval trapping in the submucosa and the fecundity of adult worms was severely impaired. Our results reveal an important IEC-intrinsic role of STAT6-regulated genes for intestinal homeostasis and protective immunity against helminths.
EVALuna2:35396

Selective stabilization of HIF-1α in renal tubular cells by 2-oxoglutarate analogues - Schley, Gunnar; Klanke, Bernd; Schödel, Johannes; Kroening, Sven; Türkoglu, Gazi; Beyer, Andreas; Hagos, Yohannes; Amann, Kerstin Ute; Burckhardt, Birgitta C.; Burzlaff, Nicolai; Eckardt, Kai-Uwe; Willam, Carsten (American Journal of Pathology, 2012)
The role of proximal versus distal tubular injury in the pathogenesis of acute kidney injury (AKI) is debatable. Inhibition of prolyl hydroxylases that regulate the degradation of hypoxia-inducible transcription factors (HIFs) is a promising therapeutic approach to optimize energy preservation under hypoxia and has successfully been applied to protect kidney structure and function in AKI models. Presently used prolyl hydroxylase inhibitors are lipophilic 2-oxoglutarate analogues (2OGAs) that are widely taken up in cells of most organs. Given the selective expression of organic anion transporters (OATs) in renal proximal tubular cells, we hypothesized that hydrophilic 2OGAs can specifically target proximal tubular cells. We found that cellular hydrophilic 2OGAs uptake depended on OATs and largely confined to the kidney, where it resulted in activation of HIF target genes only in proximal tubular cells. When applied in ischemia-reperfusion experiments, systemically active 2OGA preserved kidney structure and function, but OAT1-transported 2OGA was not protective, suggesting that HIF stabilization in distal tubular rather than proximal tubular cells and/or nontubular cells mediates protective effects. This study provides proof of concept for selective drug targeting of proximal tubular cells on the basis of specific transporters, gives insights into the role of different nephron segments in AKI pathophysiology, and may offer options for long-term HIF stabilization in proximal tubules without confounding effects of erythropoietin induction in peritubular cells and unwarranted extrarenal effects. © 2012 American Society for Investigative Pathology.

Serum Uromodulin as early marker for ischemic acute kidney injury and nephron loss: association with kidney tissue distribution pattern - Vonbrunn, Eva; Ebert, Nadja; Cordasic, Nada; Amann, Kerstin Ute; Büttner, Anke; Büttner-Herold, Maike; Scherberich, Jürgen E.; Daniel, Christoph (Journal of Translational Medicine, 2025)
Background: Uromodulin (UMOD) is expressed in kidneys and is mainly excreted in the urine, although a smaller amount is also released into the serum. Here, we investigated UMOD in acute kidney injury (AKI), with particular focus on the utility of serum UMOD as marker for nephron loss. Methods: Blood and kidney samples were collected 6 h, 24 h, 3 days and 8 weeks after ischemia/reperfusion (I/R) in a rat model. To investigate the impact of nephron number on UMOD levels, sera and tissue from healthy, uninephrectomized (Unx) and 5/6-nephrectomized (Snx) rats were analyzed. Histological changes, kidney function and cell damage were evaluated and serum UMOD, Umod mRNA expression and distribution of UMOD protein in the kidney were examined. Results: In AKI, kidney function was markedly impaired 24 h after I/R, while kidney injury and serum UMOD was increased transiently. Simultaneously, the amount of UMOD-positive kidney cells rapidly decreased 24 h after I/R compared to healthy kidneys, and mRNA expression of Umod was lowest on days 1–3 after I/R. Serum UMOD correlated with nephron number showing the highest levels in healthy rats, which were reduced after Unx and further reduced after Snx. Conclusion: In an AKI model with severe tubular damage, a transient increase in UMOD serum levels in parallel with loss of UMOD-positive cells suggests temporary release of UMOD from destroyed tubular cells into the blood. Serum UMOD appears to be not only a marker of chronic renal failure but also of acute loss of functional and cellular integrity of kidney epithelia in AKI.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Acute kidney injury; Ischemia/reperfusion; Nephron loss; Tamm-Horsfall protein; Uromodulin

SGK1 induces vascular smooth muscle cell calcification through NF-κB signaling - Voelkl, Jakob; Luong, Trang T. D.; Tuffaha, Rashad; Musculus, Katharina; Auer, Tilman; Lian, Xiaoming; Daniel, Christoph; Zickler, Daniel; Boehme, Beate; Sacherer, Michael; Metzler, Bernhard; Kuhl, Dietmar; et al. (Journal of Clinical Investigation, 2018)
Medial vascular calcification, associated with enhanced mortality in chronic kidney disease (CKD), is fostered by osteo-/chondrogenic transdifferentiation of vascular smooth muscle cells (VSMCs). Here, we describe that serum- and glucocorticoid-inducible kinase 1 (SGK1) was upregulated in VSMCs under calcifying conditions. In primary human aortic VSMCs, overexpression of constitutively active SGK1S422D, but not inactive SGK1K127N, upregulated osteo-/chondrogenic marker expression and activity, effects pointing to increased osteo-/chondrogenic transdifferentiation. SGK1S422D induced nuclear translocation and increased transcriptional activity of NF-κB. Silencing or pharmacological inhibition of IKK abrogated the osteoinductive effects of SGK1S422D. Genetic deficiency, silencing, and pharmacological inhibition of SGK1 dissipated phosphate-induced calcification and osteo-/chondrogenic transdifferentiation of VSMCs. Aortic calcification, stiffness, and osteo-/chondrogenic transdifferentiation in mice following cholecalciferol overload were strongly reduced by genetic knockout or pharmacological inhibition of Sgk1 by EMD638683. Similarly, Sgk1 deficiency blunted vascular calcification in apolipoprotein E-deficient mice after subtotal nephrectomy. Treatment of human aortic smooth muscle cells with serum from uremic patients induced osteo-/chondrogenic transdifferentiation, effects ameliorated by EMD638683. These observations identified SGK1 as a key regulator of vascular calcification. SGK1 promoted vascular calcification, at least partly, via NF-κB activation. Inhibition of SGK1 may, thus, reduce the burden of vascular calcification in CKD.
EVALuna2:34426

Shifts in Macrophage as a prognostic Biomarker in Patients with luminal Breast Cancer - A Confirmatory Study - Schnellhardt, Sören; Segelhorst, Sarah; Erber, Ramona; Daniel, Christoph; Hartmann, Arndt; Fasching, Peter; Beckmann, Matthias; Fietkau, Rainer; Distel, Luitpold; Rübner, Matthias (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Siglec-G Deficiency Leads to Autoimmunity in Aging C57BL/6 Mice. - Müller, Jennifer; Lunz, Benjamin; Schwab, Inessa; Acs, Andreas; Nimmerjahn, Falk; Daniel, Christoph; Nitschke, Lars (Journal of Immunology, 2015)
Siglec-G, a member of the sialic acid-binding Ig-like lectin (Siglec) family, is expressed on B cell and dendritic cell surfaces. It acts as an inhibitory coreceptor and modulates B cell activation, especially on B1 cells, as Siglec-G-deficient mice show mainly a B1 cell-restricted phenotype resulting in increased B1 cell numbers. Although higher B1 cell numbers are discussed to be associated with autoimmunity, loss of Siglec-G does not result in autoimmune disease in BALB/c mice. However, there is evidence from Siglec-G × CD22 double-deficient mice and Siglec-G(-/-) mice on an autoimmune-prone MRL/lpr background that Siglec-G is important to maintain tolerance in B cells. In this study, we analyzed the role of Siglec-G in induction and maintenance of B cell tolerance on C57BL/6 background and in the FcγRIIb-deficient background. We find that aging Siglec-G-deficient and Siglec-G × FcγRIIb double-deficient mice develop an autoimmune phenotype with elevated autoantibody levels and mild glomerulonephritis. Aging Siglec-G-deficient mice have elevated numbers of plasma cells and germinal center B cells, as well as a higher number of activated CD4 T cells, which likely all contribute to autoantibody production. Additional loss of the inhibitory receptor FcγRIIb in Siglec-G(-/-) mice does not result in exacerbation of disease. These results indicate that Siglec-G is important to maintain tolerance in B cells and prevent autoimmunity.

Siglec-G deficiency leads to more severe collagen-induced arthritis and earlier onset of lupus-like symptoms in MRL/lpr mice - Boekers, Susanne; Urbat, Anne; Daniel, Christoph; Amann, Kerstin Ute; Smith, Kenneth G. C.; Espeli, Marion; Nitschke, Lars (Journal of Immunology, 2014)
Siglec-G is a member of the sialic acid-binding Ig-like lectin (Siglec) family expressed on all B cells. Siglec-G-deficient mice show a large expansion of the B1 cell compartment, demonstrating the crucial role of Siglec-G as an inhibitory receptor on this cellular subset. Although Siglec-G-deficient mice did not develop spontaneous autoimmunity, mice double-deficient for Siglec-G and the related Siglec protein CD22 did show autoimmunity at an older age. In this study, we addressed the question of whether loss of Siglec G on its own affects disease severity in animal models of rheumatoid arthritis and systemic lupus erythematosus. Siglec-G-deficient mice showed moderately increased clinical severity and higher inflammation of the knee joints following collagen-induced arthritis, when compared with control mice. The Siglec-G-deficient mouse was also backcrossed to the autoimmune prone MLR/lpr background. Although both Siglec-G-deficient and control MRL/lpr mice developed a lupus-like disease, Siglec-G-deficient MRL/lpr mice showed an earlier occurrence of autoantibodies; a higher lymphoproliferation of B and T cells; and an earlier onset of disease, as shown by proteinuria and glomerular damage in the kidney. Moreover, Siglec-G-deficient female mice showed a significantly reduced survival compared with female control MRL/lpr mice. Thus, the loss of the inhibitory receptor Siglec-G led to a moderate exacerbation of disease severity and early onset in both collagen-induced arthritis and spontaneous lupus nephritis in MRL/lpr mice.
EVALuna2:25460

Siglec-H protects from virus-triggered severe systemic autoimmunity - Schmitt, Heike; Sell, Sabrina; Koch, Julia; Seefried, Martina; Sonnewald, Sophia; Daniel, Christoph; Winkler, Thomas; Nitschke, Lars (Journal of Experimental Medicine, 2016)
It is controversial whether virus infections can contribute to the development of autoimmune diseases. Type I interferons (IFNs) are critical antiviral cytokines during virus infections and have also been implicated in the pathogenesis of systemic lupus erythematosus. Type I IFN is mainly produced by plasmacytoid dendritic cells (pDCs). The secretion of type I IFN of pDCs is modulated by Siglec-H, a DAP12-associated receptor on pDCs. In this study, we show that Siglec-H-deficient pDCs produce more of the type I IFN, IFN-alpha, in vitro and that Siglec-H knockout (KO) mice produce more IFN-alpha after murine cytomegalovirus (mCMV) infection in vivo. This did not impact control of viral replication. Remarkably, several weeks after a single mCMV infection, Siglec-H KO mice developed a severe form of systemic lupus-like autoimmune disease with strong kidney nephritis. In contrast, uninfected aging Siglec-H KO mice developed a mild form of systemic autoimmunity. The induction of systemic autoimmune disease after virus infection in Siglec-H KO mice was accompanied by a type I IFN signature and fully dependent on type I IFN signaling. These results show that Siglec-H normally serves as a modulator of type I IFN responses after infection with a persistent virus and thereby prevents induction of autoimmune disease.

Signaling pathways involved in vascular smooth muscle cell calcification during hyperphosphatemia - Voelkl, Jakob; Lang, Florian; Eckardt, Kai Uwe; Amann, Kerstin Ute; Kuro-o, Makoto; Pasch, Andreas; Pieske, Burkert; Alesutan, Ioana (Cellular and Molecular Life Sciences, 2019)
Medial vascular calcification has emerged as a putative key factor contributing to the excessive cardiovascular mortality of patients with chronic kidney disease (CKD). Hyperphosphatemia is considered a decisive determinant of vascular calcification in CKD. A critical role in initiation and progression of vascular calcification during elevated phosphate conditions is attributed to vascular smooth muscle cells (VSMCs), which are able to change their phenotype into osteo-/chondroblasts-like cells. These transdifferentiated VSMCs actively promote calcification in the medial layer of the arteries by producing a local pro-calcifying environment as well as nidus sites for precipitation of calcium and phosphate and growth of calcium phosphate crystals. Elevated extracellular phosphate induces osteo-/chondrogenic transdifferentiation of VSMCs through complex intracellular signaling pathways, which are still incompletely understood. The present review addresses critical intracellular pathways controlling osteo-/chondrogenic transdifferentiation of VSMCs and, thus, vascular calcification during hyperphosphatemia. Elucidating these pathways holds a significant promise to open novel therapeutic opportunities counteracting the progression of vascular calcification in CKD.
CRIS-Team Scopus Importer:2019-05-02
Keywords: CKD; Osteogenic signaling; Phosphate; Vascular calcification; Vascular smooth muscle cells

Significance of altered PD-L1 expression in tumor tissue of oral squamous cell carcinomas - Weber, Manuel; Wehrhan, Falk; Baran, Christoph; Agaimy, Abbas; Buettner-Herold, M.; Preidl, Raimund; Neukam, Friedrich Wilhelm; Ries, Jutta (2018)
EVALuna2:34231

Significance of Glomerular Immune Reactivity in Time Zero Biopsies for Allograft Survival Beyond IgA - Vonbrunn, Eva; Serikova, Sofya; Daniel, Christoph; Amann, Kerstin Ute; Schödel, Johannes; Buchholz, Björn; Ferrazzi, Fulvia; Heller, Katharina M.; Apel, Hendrik; Büttner-Herold, Maike (Frontiers in Medicine, 2021)
The quality of a renal transplant can influence the clinical course after transplantation. Glomerular immune reactivity in renal transplants has previously been described, focusing particularly on IgA, and has been shown to disappear in most cases without affecting the outcome. Here, we describe a cohort of time zero biopsies with regard to glomerular immune reactivity and implications for histomorphology and follow-up. 204 Time zero biopsies were analyzed by immunohistochemistry for glomerular immune reactivity. Time zero and 1-year biopsies were evaluated for histomorphological changes, which, together with clinical and follow-up data, were assessed for associations with glomerular immune profiles. Nearly half of the analyzed time zero biopsies showed glomerular immune reactivity with mesangial C3 being the most common (32.9%), followed by IgA (13.7%) and fullhouse patterns (6.9%). Strong C3 deposits (C3high) were only observed in deceased transplants. In the majority of cases immune reactivity was undetectable in follow-up biopsies and had no adverse effect on transplant function in follow-up of 5 years. In kidney pairs transplanted to different recipients a strong concordance of immune profiles in both kidneys was observed. Moreover, an association of male donor sex and deceased donor transplantation with the presence of immune reactivity was observed. In conclusion, glomerular immune reactivity is a very frequent finding in time zero biopsies, which seems to be determined by donor parameters including male sex and deceased donor transplants. It had no adverse impact on transplant function in 5-year follow-up. Glomerular immune reactivity in time zero biopsies, therefore, does not appear to indicate an inferior quality of the transplant.
CRIS-Team WoS Importer:2021-04-30
Keywords: complement; renal tranplantation; time zero biopsy; transplant quality; immune reactivity

Silk for cardiac tissue engineering - Engel, Felix (Silk-Based Biomaterials for Tissue Engineering, Regenerative and Precision Medicine, 2023)
Cardiovascular diseases are among the leading causes of death worldwide. In addition, congenital heart disease is the most common congenital disability, affecting almost 1% of newborns. The primary cause of most heart diseases is the irreversible loss of heart muscle cells, the cardiomyocytes. Thus developing novel strategies to prevent, reduce, or reverse cardiomyocyte loss is critically important. One promising strategy to reverse cardiomyocyte loss is cardiac tissue engineering (CTE). This chapter reviews the advances in CTE, the special requirements for heart repair, and the remaining challenges. Subsequently, the suitability of silk for CTE is discussed.
CRIS-Team Scopus Importer:2024-12-16
Keywords: biofabrication; Cardiac tissue engineering (CTE); heart disease; recombinant silk; silk fibroin; vascularization

Single-cell cardiovascular research - Engelhardt, Stefan; Engel, Felix (Cardiovascular Research, 2020)
CRIS-Team Scopus Importer:2020-07-17

Small oral squamous cell carcinomas with nodal lymphogenic metastasis show increased infiltration of M2 polarized macrophages - An immunohistochemical analysis - Weber, Manuel; Büttner, Maike; Hyckel, Peter; Moebius, Patrick; Distel, Luitpold; Ries, Jutta; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Wehrhan, Falk (Journal of Cranio-Maxillofacial Surgery, 2014)
In solid malignancies the influence of immunological parameters - especially of macrophages - on invasiveness, metastatic potential and prognosis has been shown. There are no studies quantitatively analysing the macrophage polarization in oral squamous cell carcinoma (oscc). The aim of this study was to correlate macrophage polarization in the epithelial and stromal compartment of oscc with histopathologic parameters.T1 and T2 oscc samples (n = 34) were used. Automated immunohistochemical staining detected CD68, CD11c, CD163 and MRC1 positive cells. All samples were completely digitalized using whole slide imaging and the number of stained cells per area was assessed quantitatively.Primary tumours with lymphogenic metastasis (N+) showed a significantly (p < 0.05) increased count of CD68, CD11c, CD163 and MRC1 positive cells in the epithelial fraction compared to N0 tumours. The ratio of CD163 positive cells (M2 macrophages) to CD68 positive cells (M1 and M2 macrophages) was significantly (p < 0.05) increased in N+ tumours.An increased macrophage infiltration and an increased M2 polarization in primary oral squamous cell carcinomas with lymphogenic metastasis was shown. Macrophages that migrated into the epithelial tumour fraction seem to be of special biological importance. The results indicate a central role of macrophages in the progression of oscc.
EVALuna2:18151

Smartwatch, hemorrhagic pericardial effusion and acute kidney injury—all united in one diagnosis Smartwatch, hämorrhagischer Perikarderguss und akute Nierenschädigung – alle vereint eine Diagnose - Neumann, L. M.; Baumgärtel, M. W.; Amann, Kerstin Ute; Friesicke, H. (Die Nephrologie, 2024)
CRIS-Team Scopus Importer:2024-11-22

Soluble DPP4 originates in part from bone marrow cells and not from the kidney - Wang, Zhendi; Grigo, Christina; Steinbeck, Julia; von Hörsten, Stephan; Amann, Kerstin Ute; Daniel, Christoph (Peptides, 2014)
Dipeptidyl peptidase 4 (DPP4) is known to inactivate incretins as well as important chemokines and neuropeptides. DPP4 is expressed as a transmembrane protein but also occurs as a soluble enzyme circulating in the blood. However, the origin of the soluble DPP4 (sDPP4) is still unknown. In this study, DPP4 activity was quantified in plasma and extracted from different rat organs. Then, in order to see if the kidney or the bone marrow was the source of sDPP4, kidney or bone marrow transplantation was performed between wildtype (wt) Dark Agouti (DA) and DPP4 deficient congenic rats (n=6-9). Kidney was verified to have the highest DPP4 activity, followed by spleen and lung. In the following three weeks after successful kidney transplantation only transient trace plasma DPP4 activity was detected in DPP4 deficient rats receiving wt kidneys. In addition, DPP4 activity was not diminished in DA wt rats receiving DPP4 deficient kidneys. Both findings indicated that sDPP4 did not originate from the kidney. In contrast, 43±14% (compared to wt) sDPP4 activity was detected in the plasma of DPP4 deficient DA rats that were reconstituted with wt bone marrow cells. Not only leukocyte but also macrophage subpopulations express DPP4 in bone marrow as well as in blood as assessed by flow cytometry. Thus, bone marrow derived cells but not the kidney represent at least one source of sDPP4. And leukocyte or macrophage subpopulations could be potential candidates.
EVALuna2:3742

Soluble guanylate cyclase stimulator BAY 41-8543 and female sex ameliorate uremic aortic remodeling in a rat model of mild uremia - Stancu, Bianca; Kraemer, Stephanie; Loof, Tanja; Mika, Alice; Amann, Kerstin Ute; Neumayer, Hans-H.; Peters, Harm (Journal of Hypertension, 2015)
Cardiovascular disease is the leading comorbidity in renal patients and has been related to impaired nitric oxide signaling. Estrogens exert protective effects on the vascular system. This study investigates the effects of biological sex and nitric oxide-independent soluble guanylate cyclase (sGC) stimulator BAY 41-8543 on aortic remodeling in experimental mild uremia.Age-matched male and female Wistar rats were assigned for 18 weeks into sham-operated, subtotally nephrectomized (SNX), SNX + BAY 41-8543 and SNX + hydralazine. Analysis involved functional, histological, and molecular kidney and thoracic aorta parameters.SNX significantly increased SBP, which was comparably reduced to control levels by BAY 41-8543 and hydralazine. In SNX males, uremic aortic remodeling was characterized by marked media thickening and increased media-to-lumen ratio (P < 0.01), vascular smooth muscle cell (VSMC) proliferation, macrophage infiltration, extracellular matrix turnover, decreased aortic elastin-to-collagen ratio (P < 0.01) and endothelial nitric oxide-synthase (eNOS) mRNA expression (P < 0.05). No significant alterations of aortic media-to-lumen ratio, VSMC proliferation, macrophage infiltration, matrix metalloproteinase-2, and eNOS mRNA expressions were seen in female uremic animals. BAY 41-8543 significantly ameliorated uremic aortic remodeling and stiffening involving reduced VSMC proliferation, collagen I-deposition, extracellular matrix turnover, and increased elastin content and eNOS mRNA expression. Hydralazine treatment did not substantially alter aortic remodeling.Experimental mild uremia leads to pronounced aortic hypertrophic remodeling and stiffening with sex-dependent alternations, and these are more severe in male rats. BAY 41-8543 ameliorates uremic aortic remodeling in a blood pressure-independent manner. The results suggest that sGC-stimulators may offer a novel treatment mode for pathological arterial wall remodeling in patients with impaired renal function.
EVALuna2:25503

Spatial distribution of FoxP3+ and CD8+ tumour infiltrating T cells reflects their functional activity - Posselt, Rebecca; Erlenbach-Wuensch, Katharina; Haas, Matthias; Jeßberger, Jonas; Buettner-Herold, Maike; Haderlein, Marlen; Hecht, Markus; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Oncotarget, 2016)
Regulatory and cytotoxic T cells are key players in the host's anticancer immune response. We studied the spatial distribution of FoxP+ and CD8+ cells to identify potential interactions.In 202 patients 103 pre-radiochemotherapy biopsies and 153 post-radiochemotherapy tumour specimens of advanced rectal cancer were available and an immunohistochemical double staining of FoxP3+ and CD8+ tumour-infiltrating lymphocytes was performed to investigate cell density and cell-to-cell distances.FoxP3+ cells decreased after radiochemotherapy by a factor of 3 while CD8+ cells remained nearly unchanged. High epithelial (p=0.033) and stromal (p=0.009) FoxP3+ cell density was associated with an improved overall survival. Cell-to-cell distances of randomly distributed cells were simulated and compared to observed cell-to-cell distances. Observed distances shorter than the simulated, random distances were hypothesized to represent FoxP3+ cells actively interacting with CD8+ cells. Epithelial short distances were associated with a favourable prognosis while the opposite was true for the stromal compartment.The analysis of cell-to-cell distances may offer a tool to predict outcome, maybe by identifying functionally active, interacting infiltrating inflammatory cells in different tumour compartments.
EVALuna2:6815

Spatially Resolved Genome-wide Transcriptional Profiling Identifies BMP Signaling as Essential Regulator of Zebrafish Cardiomyocyte Regeneration - Wu, Chi-Chung; Kruse, Fabian; Vasudevarao, Mohankrishna Dalvoy; Junker, Jan Philipp; Zebrowski, David; Fischer, Kristin; Noel, Emily S.; Grun, Dominic; Berezikov, Eugene; Engel, Felix; Van Oudenaarden, Alexander; Weidinger, Gilbert; et al. (Developmental Cell, 2016)
In contrast to mammals, zebrafish regenerate heart injuries via proliferation of cardiomyocytes located near the wound border. To identify regulators of cardiomyocyte proliferation, we used spatially resolved RNA sequencing (tomo-seq) and generated a high-resolution genome-wide atlas of gene expression in the regenerating zebrafish heart. Interestingly, we identified two wound border zones with distinct expression profiles, including the re-expression of embryonic cardiac genes and targets of bone morphogenetic protein (BMP) signaling. Endogenous BMP signaling has been reported to be detrimental to mammalian cardiac repair. In contrast, we find that genetic or chemical inhibition of BMP signaling in zebrafish reduces cardiomyocyte dedifferentiation and proliferation, ultimately compromising myocardial regeneration, while bmp2b overexpression is sufficient to enhance it. Our results provide a resource for further studies on the molecular regulation of cardiac regeneration and reveal intriguing differential cellular responses of cardiomyocytes to a conserved signaling pathway in regenerative versus non-regenerative hearts.
EVALuna2:25511

Stain-Independent Deep Learning-Based Analysis of Digital Kidney Histopathology. - Bouteldja, Nassim; Hölscher, David Laurin; Klinkhammer, Barbara Mara; Buelow, Roman David; Lotz, Johannes; Weiss, Nick; Daniel, Christoph; Amann, Kerstin Ute; Boor, Peter (American Journal of Pathology, 2023)
Convolutional neural network (CNN)-based image analysis applications in digital pathology (eg, tissue segmentation) require a large amount of annotated data and are mostly trained and applicable on a single stain. Here, a novel concept based on stain augmentation is proposed to develop stain-independent CNNs requiring only one annotated stain. In this benchmark study on stain independence in digital pathology, this approach is comprehensively compared with state-of-the-art techniques including image registration and stain translation, and several modifications thereof. A previously developed CNN for segmentation of periodic acid-Schiff-stained kidney histology was used and applied to various immunohistochemical stainings. Stain augmentation showed very high performance in all evaluated stains and outperformed all other techniques in all structures and stains. Without the need for additional annotations, it enabled segmentation on immunohistochemical stainings with performance nearly comparable to that of the annotated periodic acid-Schiff stain and could further uphold performance on several held-out stains not seen during training. Herein, examples of how this framework can be applied for compartment-specific quantification of immunohistochemical stains for inflammation and fibrosis in animal models and patient biopsy specimens are presented. The results show that stain augmentation is a highly effective approach to enable stain-independent applications of deep-learning segmentation algorithms. This opens new possibilities for broad implementation in digital pathology.
EVALuna2:508561

Standardisierte histomorphologische Aufarbeitung von Peritonealbiopsien im Rahmen des Deutschen Peritonealbiopsieregisters (GRIP, German Registry In PD) - Pfister, Frederick; Büttner-Herold, Maike; Kitsche, Benno; Bulian, Dirk R.; Kielstein, Jan; Wanninger, Reinhard; Eden, Gabriele; Alscher, Dominik; Nebel, Michael; Schwenger, Vedat; Amann, Kerstin Ute (Pathologe, 2020)
The peritoneal lining of the abdominal cavity consists of a parietal and visceral sheet. The serosa is an interesting organ, which in medical practice is particularly important in the context of chronic peritoneal dialysis (PD). This method of renal replacement therapy utilizes the semipermeability of the peritoneal surface by applying PD solutions of differing osmolarity to eliminate toxic substances and regulate fluid and electrolyte equilibrium. This method is an ideal approach especially for younger patients and is very effective at least for some time. Pre-existing injury to the peritoneum, for example as a consequence of chronic renal insufficiency or associated comorbidities and inflammatory changes that develop during PD, results in a structural remodelling of the serosa. As a consequence, the filtering function of the serosa is lost and PD has to be replaced by another renal replacement therapy. Thorough knowledge of the morphology of peritoneal changes as well as of the risk factors is of paramount importance for therapeutic management and prognosis of PD patients. In order to take this into account, the German Registry In Peritoneal Dialysis (Deutsches Peritonealbiopsieregister, GRIP) was founded a few years ago, which now includes roughly 1700 biopsies, of which detailed clinical and histomorphological information was systematically acquired and collected.
CRIS-Team Scopus Importer:2020-09-18
Keywords: EPS; Fibrosis; Morphology; Peritoneal dialysis; Peritoneum

Static magnetic field enhances the bone remodelling capacity of human demineralized bone matrix in a rat animal model of cranial bone defects - Hosseini, Seyed Jamal; Parsaei, Houman; Moosavifar, Mir Javad; Tavakoli, Narjes; Ahadi, Reza; Roshanbinfar, Kaveh (Journal of Materials Chemistry B, 2024)
The regeneration of bone defects that exceed 2 cm is a challenge for the human body, necessitating interventional therapies. Demineralized bone matrices (DBM) derived from biological tissues have been employed for bone regeneration and possess notable osteoinductive and osteoconductive characteristics. Nevertheless, their efficiency in regenerating critically sized injuries is limited, and therefore additional signaling cues are required. Thanks to the piezoelectric properties of the bone, external physical stimulation is shown to accelerate tissue healing. We have implanted human DBM in critically sized cranial bone defects in rat animal models and exposed them to an external magnetic field (1 T) to enhance endogenous bone formation. Our in vitro experiments showed the superior cytocompatibility of DBM compared to cell culture plates. Furthermore, alkaline phosphatase activity after 14 days and Alizarin red staining at 28 days demonstrated differentiation of rat bone marrow mesenchymal stem cells into bone lineage on DBM. Computer tomography images together with histological analyses showed that implanting DBM in the injured rats significantly enhanced bone regeneration. Notably, combining DBM transplantation with a 2 h daily exposure to a 1 T magnetic field for 2 weeks (day 7 to 21 post-surgery) significantly improved bone regeneration compared to DBM transplantation alone. This research indicates that utilizing external magnetic stimulation significantly enhances the potential of bone allografts to regenerate critically sized bone defects.
CRIS-Team Scopus Importer:2024-04-26

Stem Cell Aging and Age-Related Cardiovascular Disease: Perspectives of Treatment by Ex-vivo Stem Cell Rejuvenation - Madonna, Rosalinda; Engel, Felix; Davidson, Sean M.; Ferdinandy, Peter; Goerbe, Aniko; Sluijter, Joost P. G.; Van Laake, Linda W. (Current Drug Targets, 2015)
Aging affects endogenous stem cells in terms of functionality and numbers. In particular, during aging, the stemness property can decrease because of enhanced apoptotic cell death and senescence. In addition, aging and aging-related co-morbidities affect the paracrine activity of stem cells and the efficiency of their transplantation. Collectively, this leads to a reduction of the capacity of organs to repair themselves, possibly due to a reduced functional capability of stem cells. Therefore, major efforts have been invested to improve the repair capability of stem cells in aged individuals by overexpressing antisenescence and antiapoptotic genes. In this review, we describe critical genes and signaling pathways in stem cell aging and discuss ex vivo genetic modification approaches aimed at stem cell rejuvenation that are of interest for the cardiovascular system.
EVALuna2:25484

Stem Cells and Their Cardiac Derivatives for Cardiac Tissue Engineering and Regenerative Medicine - Roshanbinfar, Kaveh; Esser, Tilman; Engel, Felix (Antioxidants & Redox Signaling, 2020)
Significance: Heart failure is among the leading causes of morbidity worldwide with a 5-year mortality rate of similar to 50%. Therefore, major efforts are invested to reduce heart damage upon injury or maintain and at best restore heart function.
CRIS-Team WoS Importer:2020-12-04

Strain specific differences in vitamin D3 response: impact on gut homeostasis - Schreiber, Laura; Ghimire, Sakhila; Hiergeist, Andreas; Renner, Kathrin; Althammer, Michael; Babl, Nathalie; Peuker, Alice; Schoenhammer, Gabriele; Hippe, Katrin; Gessner, Andre; Albrecht, Christin; Pielmeier, Fransziska; et al. (Frontiers in Immunology, 2024)
Vitamin D3 regulates a variety of biological processes irrespective of its well-known importance for calcium metabolism. Epidemiological and animal studies indicate a role in immune regulation, intestinal barrier function and microbiome diversity. Here, we analyzed the impact of different vitamin D3- containing diets on C57BL/6 and BALB/c mice, with a particular focus on gut homeostasis and also investigated effects on immune cells in vitro. Weak regulatory effects were detected on murine T cells. By trend, the active vitamin D3 metabolite 1,25-dihydroxyvitamin D3 suppressed IFN, GM-CSF and IL-10 cytokine secretion in T cells of C57BL/6 but not BALB/c mice, respectively. Using different vitamin D3-fortified diets, we found a tissue–specific enrichment of mainly CD11b+ myeloid cells but not T cells in both mouse strains e.g. in spleen and Peyer’s Patches. Mucin Reg3γ and Batf expression, as well as important proteins for gut homeostasis, were significantly suppressed in the small intestine of C57BL76 but not BALB/c mice fed with a high-vitamin D3 containing diet. Differences between both mouse stains were not completely explained by differences in vitamin D3 receptor expression which was strongly expressed in epithelial cells of both strains. Finally, we analyzed gut microbiome and again an impact of vitamin D3 was detected in C57BL76 but not BALB/c. Our data suggest strain-specific differences in vitamin D3 responsiveness under steady state conditions which may have important implications when choosing a murine disease model to study vitamin D3 effects.
CRIS-Team Scopus Importer:2024-03-29
Keywords: BALB/c; barrier function; C57BL/6; intestinal; vitamin D3

Stressed erythrocytes bind intravascular von Willebrand factor and promote microangiopathy - Nicolay, J. P.; Thorn, V.; Daniel, Christoph; Amann, Kerstin Ute; Siraskar, B.; Lang, F.; Hillgruber, C.; Goerge, T.; Gorzelanny, C.; Huck, V.; Obser, T.; Schneppenheim, R.; et al. (2018)
EVALuna2:34440

Structural and geochemical assessment of the coralline alga Tethysphytum antarcticum from Terra Nova Bay, Ross Sea, Antarctica - López Correa, Matthias; Teichert, Sebastian; Ragazzola, Federica; Cazorla Vázquez, Salvador; Engel, Felix; Hurle, Katrin; Mazzoli, Claudio; Kuklinski, Piotr; Raiteri, Giancarlo; Lombardi, Chiara (Minerals, 2023)
Crustose coralline algae (CCA) occur from the tropics to the poles in photic benthic environments. Here, we report on some of the world’s southernmost and coldest CCA sites in Terra Nova, Ross Sea, Antarctica at 74°41′ S. The recently described red alga Tethysphytum antarticum is investigated for its skeletal architecture, its mineralogical and geochemical composition, as well as for its taxonomic classification. A phylogenetic analysis based on molecular genetics and the sequencing of the photosystem II protein D1 (psbA) gave a perfect match with T. antarcticum. Histological sections and micro-CT-scans provide new diagnostic details for the conceptacles (the reproductive organs of the alga). X-ray diffractometry and electron-microprobe measurements yielded a clear high-Mg calcite ( 8 mol%) composition of the skeletal parts. Detailed back-scattered electron imaging of polished petrographic thin sections revealed a two-layered thallus (vegetative plant tissue), comprising an organic-rich irregularly calcified basal layer with rectangular cells, overlain by the main thallus. Elemental maps show relatively increased sulphur in the basal layer, clearly tied to organic cell walls. MgCO3 and SrCO3 were targeted with semiquantitative elemental mappings and in an ontogenetic quantitative spot transect. Compared with temperature (−1.95 °C to +1.08 °C), the MgCO3 (mol%) reflects this world’s coldest CCA site temperature with the lowest MgCO3 content of 7.9 ± 1.6 mol%. The along transect variability, however, shows with 6 mol% a larger MgCO3 variability than expected for the 3 °C intra-annual temperature amplitude in Terra Nova Bay. This implies that in low amplitude settings the biomineralisation control on Mg/Ca ratios can outcompete its temperature sensitivity. Mark-recapture studies, next to the environmental logger station La Zecca are suggested, to perform a detailed growth rate and biomineralisation quantificatio
Keywords: crustose coralline algae; Antarctica; taxonomy; phylogeny; thallus structure; biomineralization; geochemistry; climate change

Structured illumination microscopy and automatized image processing as a rapid diagnostic tool for podocyte effacement - Siegerist, Florian; Ribback, Silvia; Dombrowski, Frank; Amann, Kerstin Ute; Zimmermann, Uwe; Endlich, Karlhans; Endlich, Nicole (Scientific Reports, 2017)
The morphology of podocyte foot processes is obligatory for renal function. Here we describe a method for the superresolution-visualization of podocyte foot processes using structured illumination microscopy of the slit diaphragm, which before has only been achieved by electron microscopy. As a proof of principle, we measured a mean foot process width of 0.249 ± 0.068 µm in healthy kidneys and a significant higher mean foot process width of 0.675 ± 0.256 µm in minimal change disease patients indicating effacement of foot processes. We then hypothesized that the slit length per glomerular capillary surface area (slit diaphragm density) could be used as an equivalent for the diagnosis of effacement. Using custom-made software we measured a mean value of 3.10 ± 0.27 µm(-1) in healthy subjects and 1.83 ± 0.49 µm(-1) in the minimal change disease patients. As foot process width was highly correlated with slit diaphragm density (R(2) = 0.91), we concluded that our approach is a valid method for the diagnosis of foot process effacement. In summary, we present a new technique to quantify podocyte damage, which combines superresolution microscopy with automatized image processing. Due to its diverse advantages, we propose this technique to be included into routine diagnostics of glomerular histopathology.
EVALuna2:25548

Studies on the Role of the Transcription Factor Tcf21 in the Transdifferentiation of Parietal Epithelial Cells into Podocyte-Like Cells. - Kliewe, Felix; Kuss, Andreas W.; Siegerist, Florian; Schröder, Sindy; Schordan, Sandra; Artelt, Nadine; Kindt, Frances; Amann, Kerstin Ute; Lindenmeyer, Maja T.; Endlich, Karlhans; Endlich, Nicole (Cellular Physiology and Biochemistry, 2021)
BACKGROUND/AIMS: Podocyte differentiation is essential for proper blood filtration in the kidney. It is well known that transcription factors play an essential role to maintain the differentiation of podocytes. The present study is focused on the basic helix-loop-helix (bHLH) transcription factor Tcf21 (Pod1) which is essential for the development of podocytes in vivo. Since parietal epithelial cells (PECs) are still under debate to be progenitor cells which can differentiate into podocytes, we wanted to find out whether the expression of Tcf21 induces a transition of PECs into podocytes. METHODS: We transfected PECs with Tcf21-GFP and analyzed the expression of PEC- and podocyte-specific markers. Furthermore, we performed ChIP-Seq analysis to identify new putative interaction partners and target genes of Tcf21. RESULTS: By gene arrays analysis, we found that podocytes express high levels of Tcf21 in vivo in contrast to cultured podocytes and parietal epithelial cells (PECs) in vitro. After the expression of Tcf21 in PECs, we observed a downregulation of specific PEC markers like caveolin‑1, β-catenin and Pax2. Additionally, we found that the upregulation of Tcf21 induced multi-lobulation of cell nuclei, budding and a formation of micronuclei (MBM). Furthermore, a high number of PECs showed a tetraploid set of chromosomes. By qRT-PCR and Western blot analysis, we revealed that the transcription factor YY1 is downregulated by Tcf21. Interestingly, co-expression of YY1 and Tcf21 rescues MBM and reduced tetraploidy. By ChIP-Seq analysis, we identified a genome-wide Tcf21-binding site (CAGCTG), which matched the CANNTG sequence, a common E-box binding motif used by bHLH transcription factors. Using this technique, we identified additional Tcf21 targets genes that are involved in the regulation of the cell cycle (e.g. Mdm2, Cdc45, Cyclin D1, Cyclin D2), on the stability of microtubules (e.g. Mapt) as well as chromosome segregation. CONCLUSION: Taken together, we demonstrate that Tcf21 inhibits the expression of PEC-specific markers and of the transcription factor YY1, induces MBM as well as regulates the cell cycle suggesting that Tcf21 might be important for PEC differentiation into podocyte-like cells.
EVALuna2:466165

Studying the role of fascin-1 in mechanically stressed podocytes - Kliewe, Felix; Scharf, Christian; Rogge, Henrik; Darm, Katrin; Lindenmeyer, Maja T.; Amann, Kerstin Ute; Cohen, Clemens D.; Endlich, Karlhans; Endlich, Nicole (Scientific Reports, 2017)
Glomerular hypertension causes glomerulosclerosis via the loss of podocytes, which are challenged by increased mechanical load. We have demonstrated that podocytes are mechanosensitive. However, the response of podocytes to mechanical stretching remains incompletely understood. Here we demonstrate that the actin-bundling protein fascin-1 plays an important role in podocytes that are exposed to mechanical stress. Immunofluorescence staining revealed colocalization of fascin-1 and nephrin in mouse kidney sections. In cultured mouse podocytes fascin-1 was localized along actin fibers and filopodia in stretched and unstretched podocytes. The mRNA and protein levels of fascin-1 were not affected by mechanical stress. By Western blot and 2D-gelelectrophoresis we observed that phospho-fascin-1 was significantly downregulated after mechanical stretching. It is known that phosphorylation at serine 39 (S39) regulates the bundling activity of fascin-1, e.g. required for filopodia formation. Podocytes expressing wild type GFP-fascin-1 and non-phosphorylatable GFP-fascin-1-S39A showed marked filopodia formation, being absent in podocytes expressing phosphomimetic GFP-fascin-1-S39D. Finally, the immunofluorescence signal of phosphorylated fascin-1 was strongly reduced in glomeruli of patients with diabetic nephropathy compared to healthy controls. In summary, mechanical stress dephosphorylates fascin-1 in podocytes in vitro and in vivo thereby fascin-1 may play an important role in the adaptation of podocytes to mechanical forces.
EVALuna2:25547

Study protocol: the TRAnsplant BIOpsies (TRABIO) study - a prospective, observational, multicentre cohort study to assess the treatment of kidney graft rejections - von Samson-Himmelstjerna, Friedrich Alexander; Esser, Grit; Schulte, Kevin; Kolbrink, Benedikt; Krautter, Markus; Schwenger, Vedat; Weinmann-Menke, Julia; Matschkal, Julia; Schraml, Florian; Pahl, Anne; Braunisch, Matthias; Amann, Kerstin Ute; et al. (BMJ Open, 2022)
INTRODUCTION: Despite continued efforts, long-term outcomes of kidney transplantation remain unsatisfactory. Kidney graft rejections are independent risk factors for graft failure. At the participating centres of the TRAnsplant BIOpsies study group, a common therapeutic standard has previously been defined for the treatment of graft rejections. The outcomes of this strategy will be assessed in a prospective, observational cohort study. METHODS AND ANALYSIS: A total of 800 kidney transplantation patients will be enrolled who undergo a graft biopsy because of deteriorating kidney function. Patients will be stratified according to the Banff classification, and the influence of the treatment strategy on end points will be assessed using regression analysis. Primary end points will be all-cause mortality and graft survival. Secondary end points will be worsening of kidney function (≥30% decline of estimated Glomerular Filtration Rate [eGFR] or new-onset large proteinuria), recurrence of graft rejection and treatment response. Baseline data and detailed histopathology data will be entered into an electronic database on enrolment. During a first follow-up period (within 14 days) and subsequent yearly follow-ups (for 5 years), treatment strategies and clinical course will be recorded. Recruitment at the four participating centres started in September 2016. As of August 2020, 495 patients have been included. ETHICS AND DISSEMINATION: Ethical approval for the study has been obtained from the ethics committee of Kiel (AZ B 278/16) and was confirmed by the committees of Munich, Mainz and Stuttgart. The results will be reported in a peer-reviewed journal, according to the Strengthening the Reporting of Observational Studies in Epidemiology criteria. TRIAL REGISTRATION NUMBER: ISRCTN78772632; Pre-results.
CRIS-Team Scopus Importer:2022-05-06
Keywords: Nephrology; Renal transplantation; TRANSPLANT MEDICINE; Transplant pathology

Successful Desensitization with Imlifidase and Daratumumab in a Highly Immunized, Crossmatch Positive, Blood Group-Incompatible Living-Donor Re-Transplant Recipient with Systemic Lupus Erythematosus and Antiphospholipid Syndrome - Schrezenmeier, Eva; Choi, Mira; Globke, Brigitta; Dörner, Thomas; Leimbach, Alexandra; Osmanodja, Bilgin; Schramm, Alexander; Amann, Kerstin Ute; Eckardt, Kai Uwe; Budde, Klemens; Öllinger, Robert; Lachmann, Nils; et al. (Transfusion Medicine and Hemotherapy, 2024)
Introduction: The transplantation of highly sensitized patients remains a major obstacle. Immunized patients wait longer for a transplant if not prioritized, and if transplanted, their transplant outcome is worse. Case Presentation: We report a successful AB0- and HLA-incompatible living donor kidney transplantation in a 35-year-old female patient with systemic lupus erythematosus (SLE) and antiphospholipid syndrome. The patient had a positive T- and B-cell complement-dependent cytotoxicity (CDC) crossmatch and previous graft loss due to renal vein thrombosis. We treated the patient with intravenous immunoglobulins, rituximab, horse anti-thymocyte globulin, daratumumab, and imlifidase, besides standard immunosuppression. All IgG antibodies were sensitive to imlifidase treatment. Besides donor-specific HLA antibodies, anti-dsDNA antibodies and antiphospholipid antibodies were cleaved. The patient initially had delayed graft function. Two kidney biopsies (day 7 and day 14) revealed acute tubular necrosis without signs of HLA antibody-mediated rejection. On posttransplant day 30, hemodialysis was stopped, and creatinine levels declined over the next weeks to a baseline creatinine of about 1.7 mg/ dL after 12 months. Conclusion: In this case, a novel multimodal treatment strategy including daratumumab and imlifidase enabled successful kidney transplantation for a highly immunized patient with antiphospholipid antibodies.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Daratumumab; Imlifidase; Kidney transplant

Successful long-term management of recurrent focal segmental glomerulosclerosis after kidney transplantation with costimulation blockade - Muehlbacher, Thomas; Amann, Kerstin Ute; Mahling, Moritz; Nadalin, Silvio; Heyne, Nils; Guthoff, Martina (Clinical Kidney Journal, 2021)
Recurrence of primary focal segmental glomerulosclerosis (FSGS) occurs in up to 50% of patients after kidney transplantation and is associated with poor allograft outcome. Novel therapeutic concepts directly target podocyte function via B7-1 with inconsistent response. We present the case of a 19-year-old patient with recurrent primary FSGS early after living donor kidney transplantation. Plasmapheresis and rituximab did not induce remission. Repetitive abatacept administration was able to achieve partial remission. Maintenance immunosuppression was subsequently switched to a belatacept-based calcineurin inhibitor-free immunosuppression, resulting in sustained complete remission with excellent allograft function throughout a follow-up of >56months.
CRIS-Team WoS Importer:2021-10-01

Super-resolved local recruitment of CLDN5 to filtration slits implicates a direct relationship with podocyte foot process effacement - Tesch, Florian; Siegerist, Florian; Hay, Eleonora; Artelt, Nadine; Daniel, Christoph; Amann, Kerstin Ute; Zimmermann, Uwe; Kavvadas, Panagiotis; Grisk, Olaf; Chadjichristos, Christos; Endlich, Karlhans; Chatziantoniou, Christos; et al. (Journal of Cellular and Molecular Medicine, 2021)
Under healthy conditions, foot processes of neighbouring podocytes are interdigitating and connected by an electron-dense slit diaphragm. Besides slit diaphragm proteins, typical adherens junction proteins are also found to be expressed at this cell-cell junction. It is therefore considered as a highly specialized type of adherens junction. During podocyte injury, podocyte foot processes lose their characteristic 3D structure and the filtration slits typical meandering structure gets linearized. It is still under debate how this change of structure leads to the phenomenon of proteinuria. Using super-resolution 3D-structured illumination microscopy, we observed a spatially restricted up-regulation of the tight junction protein claudin-5 (CLDN5) in areas where podocyte processes of patients suffering from minimal change disease (MCD), focal and segmental glomerulosclerosis (FSGS) as well as in murine nephrotoxic serum (NTS) nephritis and uninephrectomy DOCA-salt hypertension models, were locally injured. CLDN5/nephrin ratios in human glomerulopathies and NTS-treated mice were significantly higher compared to controls. In patients, the CLDN5/nephrin ratio is significantly correlated with the filtration slit density as a foot process effacement marker, confirming a direct association of local CLDN5 up-regulation in injured foot processes. Moreover, CLDN5 up-regulation was observed in some areas of high filtration slit density, suggesting that CLND5 up-regulation preceded the changes of foot processes. Therefore, CLDN5 could serve as a biomarker predicting early foot process effacement.
CRIS-Team Scopus Importer:2021-07-02
Keywords: 3D-structured illumination microscopy; Claudin-5; foot process effacement; glomerulosclerosis; podocyte; tight junction proteins

Surface Features of Recombinant Spider Silk Protein eADF4(kappa 16)-Made Materials are Well-Suited for Cardiac Tissue Engineering - Petzold, Jana; Aigner, Tamara B.; Touska, Filip; Zimmermann, Katharina; Scheibel, Thomas; Engel, Felix (Advanced Functional Materials, 2017)
Cardiovascular diseases causing high morbidity and mortality represent a major socioeconomic burden. The primary cause of impaired heart function is often the loss of cardiomyocytes. Thus, novel therapies aim at restoring the lost myocardial tissue. One promising approach is cardiac tissue engineering. Previously, it is shown that Antheraea mylitta silk protein fibroin is a suitable material for cardiac tissue engineering, however, its quality is difficult to control. To overcome this limitation, the interaction of primary rat heart cells with engineered Araneus diadematus fibroin 4 (kappa 16) (eADF4(kappa 16)) is investigated here, which is engineered based on the sequence of ADF4 by replacing the glutamic acid residue in the repetitive unit of its core domain with lysine. The data demonstrate that cardiomyocytes, fibroblasts, endothelial cells, and smooth muscle cells attach well to eADF4(kappa 16) films on glass coverslips which provide an engineered surface with a polycationic character. Moreover, eADF4(kappa 16) films have, in contrast to fibronectin films, no hypertrophic effect but allow the induction of cardiomyocyte hypertrophy. Finally, cardiomyocytes grown on eADF4(kappa 16) films respond to pro-proliferative factors and exhibit proper cell-to-cell communication and electric coupling. Collectively, these data demonstrate that designed recombinant eADF4(kappa 16)-based materials are promising materials for cardiac tissue engineering.
EVALuna2:34287
Keywords: adhesion; cardiac tissue engineering; cell-material interactions; eADF4(kappa 16); engineered spider silk proteins

Synthetic Oligosaccharide-Based Vaccines Protect Mice from Clostridioides difficile Infections - Broecker, Felix; Wegner, Erik; Seco, Bruna M.S.; Kaplonek, Paulina; Bräutigam, Maria; Enßer, Armin; Pfister, Frederick; Daniel, Christoph; Martin, Christopher E.; Mattner, Jochen; Seeberger, Peter H. (ACS Chemical Biology, 2019)
Infections with Clostridioides difficile (formerly Clostridium difficile) have increased in incidence, morbidity, and mortality over the past decade. Preventing infections is becoming increasingly important, as frontline antibiotics become less effective and frequently induce recurrence by disrupting intestinal microbiota. The clinically most advanced vaccine approaches prevent symptoms once C. difficile infection is established by inducing immunity to secreted clostridial cytotoxins. However, they do not inhibit bacterial colonization and thereby favor asymptomatic carriage. Synthetic oligosaccharides resembling the C. difficile surface glycans PS-I, PS-II, and PS-III are immunogenic and serve as basis for colonization-preventing vaccines. Here, we demonstrate that glycoconjugate vaccine candidates based on synthetic oligosaccharides protected mice from infections with two different C. difficile strains. Four synthetic antigens, ranging in size from disaccharides to hexasaccharides, were conjugated to CRM197, which is a carrier protein used in commercial vaccines. The vaccine candidates induced glycan-specific antibodies in mice and substantially limited C. difficile colonization and colitis after experimental infection. The glycoconjugates ameliorated intestinal pathology more substantially than a toxin-targeting vaccine. Colonization of the gut by C. difficile was selectively inhibited while intestinal microbiota remained preserved. Passive transfer experiments with anti-PS-I serum revealed that protection is mediated by specific antiglycan antibodies; however, cell-mediated immunity likely also contributed to protection in vivo. Thus, glycoconjugate vaccines against C. difficile are a complementary approach to toxin-targeting strategies and are advancing through preclinical work.
CRIS-Team Scopus Importer:2019-12-03

Targeting Fibroblast Activation Protein: Radiosynthesis and Preclinical Evaluation of an 18F-Labeled FAP Inhibitor - Toms, Johannes; Kogler, Jürgen; Maschauer, Simone; Daniel, Christoph; Schmidkonz, Christian; Kuwert, Torsten; Prante, Olaf (Journal of Nuclear Medicine, 2020)
Fibroblast activation protein (FAP) has emerged as an interesting molecular target used in the imaging and therapy of various types of cancers. 68Ga-labeled chelator-linked FAP inhibitors (FAPIs) have been successfully applied to PET imaging of various tumor types. To broaden the spectrum of applicable PET tracers for extended imaging studies of FAP-dependent diseases, we herein report the radiosynthesis and preclinical evaluation of an 18F-labeled glycosylated FAPI ([18F]FGlc-FAPI). Methods: An alkyne-bearing precursor was synthesized and subjected to click chemistry-based radiosynthesis of [18F]FGlc-FAPI by 2-step 18F-fluoroglycosylation. FAP-expressing HT1080hFAP cells were used to study competitive binding to FAP, cellular uptake, internalization, and efflux of [18F]FGlc-FAPI in vitro. Biodistribution studies and in vivo small-animal PET studies of [18F]FGlc-FAPI compared with [68Ga]Ga-FAPI-04 were conducted in nude mice bearing HT1080hFAP tumors or U87MG xenografts. Results: [18F]FGlc-FAPI was synthesized with a 15% radioactivity yield and a high radiochemical purity of more than 99%. In HT1080hFAP cells, [18F]FGlc-FAPI showed specific uptake, a high internalized fraction, and low cellular efflux. Compared with FAPI-04 (half maximal inhibitory concentration [IC50] = 32 nM), the glycoconjugate, FGlc-FAPI (IC50 = 167 nM), showed slightly lower affinity for FAP in vitro, whereas plasma protein binding was higher for [18F]FGlc-FAPI. Biodistribution studies revealed significant hepatobiliary excretion of [18F]FGlc-FAPI; however, small-animal PET studies in HT1080hFAP xenografts showed higher specific tumor uptake of [18F]FGlc-FAPI (4.5 percentage injected dose per gram of tissue [%ID/g]) than of [68Ga]Ga-FAPI-04 (2 %ID/g). In U87MG tumor-bearing mice, both tracers showed similar tumor uptake, but [18F]FGlc-FAPI showed a higher tumor retention. Interestingly, [18F]FGlc-FAPI demonstrated high specific uptake in bone structures and joints. Conclusion: [18F]FGlc-FAPI is an interesting candidate for translation to the clinic, taking advantage of the longer half-life and physical imaging properties of 18F. The availability of [18F]FGlc-FAPI may allow extended PET studies of FAP-related diseases, such as cancer, but also arthritis, heart diseases, or pulmonary fibrosis.
CRIS-Team Scopus Importer:2020-12-11
Keywords: 18F; 18F-fluoroglycosylation; cancer-associated fibroblasts; fibroblast activation protein; PET

Targeting Inflammatory T Helper Cells via Retinoic Acid-Related Orphan Receptor Gamma t Is Ineffective to Prevent Allo-Response-Driven Colitis - Buchele, Vera; Abendroth, Benjamin; Buettner-Herold, Maike; Vogler, Tina; Rothamer, Johanna; Ghimire, Sakhila; Ullrich, Evelyn; Holler, Ernst; Neurath, Markus; Hildner, Kai (Frontiers in Immunology, 2018)
Intestinal graft-versus-host disease (GvHD) is a life-threatening, inflammatory donor T cell-mediated complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT). In the light of the reported efficacy of interleukin-23 (IL-23)-blockade to mitigate syngeneic intestinal inflammation in inflammatory bowel disease patients, targeting IL-23 and thereby interleukin-17a (IL-17a) producing T helper (Th17) cells as the T cell subset assumed to be mostly regulated by IL-23, has emerged as a putatively general concept to harness immune-mediated mucosal inflammation irrespective of the underlying trigger. However, the role of Th17 cells during allo-response driven colitis remains ambiguous due to a series of studies with inconclusive results. Interestingly, we recently identified granulocyte-macrophage colony-stimulating factor (GM-CSF+) T cells to be promoted by interleukin-7 (IL-7) signaling and controlled by the activating protein-1 transcription factor family member basic leucine zipper transcription factor ATF-like (BATF) as critical mediators of intestinal GvHD in mice. Given the dual role of BATF, the contribution of IL-23-mediated signaling within donor T cells and bona fide Th17 cells remains to be delineated from the regulation of GM-CSF+ T cells in the absence of BATF. Here, we found in a complete MHC class I-mismatched model that genetic inactivation of the IL-23 receptor (IL-23R) or the transcription factor retinoic acid-related orphan receptor gamma t (RORγt) within donor T cells similarly ablated Th17 cell formation in vivo but preserved the T cells' ability to induce intestinal GvHD in a compared to wild-type controls indistinguishable manner. Importantly, RORγt-independent manifestation of intestinal GvHD was completely dependent on BATF-regulated GM-CSF+ T cells as BATF/RORγt double-deficient T cells failed to induce colitis and the antibody-mediated blockage of IL-7/IL-7R interaction and GM-CSF significantly diminished signs of intestinal GvHD elicited by RORγt-deficient donor T cells. Finally, in analogy to our murine studies, colonic RORC expression levels inversely correlated with the presence of GvHD in allo-HSCT patients. Together, this study provides a crucial example of a BATF-dependent, however, IL-23R signaling- and RORγt-, i.e., Th17 fate-independent regulation of a colitogenic T cell population critically impacting the current understanding of intestinal GvHD.
EVALuna2:34273

Targeting the innate repair receptor axis via erythropoietin or pyroglutamate helix B surface peptide attenuates hemolytic-uremic syndrome in mice - Dennhardt, Sophie; Pirschel, Wiebke; Wissuwa, Bianka; Imhof, Diana; Daniel, Christoph; Kielstein, Jan T.; Hennig-Pauka, Isabel; Amann, Kerstin Ute; Gunzer, Florian; Coldewey, Sina M. (Frontiers in Immunology, 2022)
Hemolytic-uremic syndrome (HUS) can occur as a systemic complication of infections with Shiga toxin (Stx)-producing Escherichia coli and is characterized by microangiopathic hemolytic anemia and acute kidney injury. Hitherto, therapy has been limited to organ-supportive strategies. Erythropoietin (EPO) stimulates erythropoiesis and is approved for the treatment of certain forms of anemia, but not for HUS-associated hemolytic anemia. EPO and its non-hematopoietic analog pyroglutamate helix B surface peptide (pHBSP) have been shown to mediate tissue protection via an innate repair receptor (IRR) that is pharmacologically distinct from the erythropoiesis-mediating receptor (EPO-R). Here, we investigated the changes in endogenous EPO levels in patients with HUS and in piglets and mice subjected to preclinical HUS models. We found that endogenous EPO was elevated in plasma of humans, piglets, and mice with HUS, regardless of species and degree of anemia, suggesting that EPO signaling plays a role in HUS pathology. Therefore, we aimed to examine the therapeutic potential of EPO and pHBSP in mice with Stx-induced HUS. Administration of EPO or pHBSP improved 7-day survival and attenuated renal oxidative stress but did not significantly reduce renal dysfunction and injury in the employed model. pHBSP, but not EPO, attenuated renal nitrosative stress and reduced tubular dedifferentiation. In conclusion, targeting the EPO-R/IRR axis reduced mortality and renal oxidative stress in murine HUS without occurrence of thromboembolic complications or other adverse side effects. We therefore suggest that repurposing EPO for the treatment of patients with hemolytic anemia in HUS should be systematically investigated in future clinical trials.
CRIS-Team Scopus Importer:2022-10-21
Keywords: erythropoietin; hemolytic-uremic syndrome; mice; microangiopathic hemolytic anemia; pyroglutamate helix B surface peptide; shiga toxin; thrombotic microangiopathy

The Babylonian confusion in describing chronic changes in renal allografts - Kemmner, Stephan; Büttner-Herold, Maike; Heemann, Uwe; Amann, Kerstin Ute; Schmaderer, Christoph (Minerva Urologica e Nefrologica, 2017)
EVALuna2:25543

The Case | A 74-year-old liver transplant recipient with nephrotic-range proteinuria - Bohnert, Bernhard N.; Büttner-Herold, Maike; Amann, Kerstin Ute; Schork, Anja; Birkenfeld, Andreas L.; Guthoff, Martina; Heyne, Nils; Nadalin, Silvio; Artunc, Ferruh (Kidney International, 2021)
CRIS-Team Scopus Importer:2021-03-26

The complement system-a "hot topic" not only for kidney diseases - Amann, Kerstin Ute; Daniel, Christoph; Büttner-Herold, Maike (Pathologe, 2020)
Increasing interest in the role of the complement system in systemic and renal disease is based on new pathophysiological and therapeutic insights of the recent past and particularly in genetic analyses in children with atypical hemolytic uremic syndrome (aHUS). aHUS is the prototypical systemic disease associated with excessive activation of the alternative complement pathway and manifests in the kidney, but also in other organs as thrombotic microangiopathy (TMA). Pathomechanisms discovered to induce the overactivation of the alternative complement pathway in aHUS led to the first successful therapeutic application of a C5b9 inhibitor. This suppression of the terminal complement cascade succeeded in inhibiting local tissue damage. Thereafter, thanks to advanced modern technologies, further systemic and renal diseases associated with mutations or auto-antibodies targeting the complement pathway were identified. Hereby, disease onset is frequently associated with an additional trigger, e.g. infection or hormonal alterations/imbalances, against the background of a pre-existing predisposition of the patient. Due to the growing understanding of the regulation, and thus the possibility of therapeutic modulation of the different complement pathways, and due to the increasing availability of a variety of drugs inhibiting the complement system, interest in complement-mediated systemic and renal disease has been steadily increasing, making it a "hot-topic" in medicine in recent years.
CRIS-Team WoS Importer:2020-04-10

The dipeptidyl peptidase 4 inhibitor linagliptin ameliorates renal injury and accelerated resolution in a rat model of crescentic nephritis - Mayer, Anna-Lena; Scheitacker, Iris; Ebert, Nadja; Klein, Thomas; Amann, Kerstin Ute; Daniel, Christoph (British Journal of Pharmacology, 2021)
Background and Purpose: Dipeptidyl peptidase 4 (DPP-4) inhibitors are a class of oral glucose-lowering drugs used in the treatment of type 2 diabetes. In a pilot study using human kidney biopsies, we observed high DPP-4 expression in early crescent formation. This glomerular lesion occurs in different kidney diseases and is a hallmark in the pathogenesis of renal dysfunction. Therefore, we investigated the potential involvement of DPP-4 in the pathogenesis of nephritis induced by anti-glomerular basement membrane (GBM) antibody in rats. Experimental Approach: Linagliptin and vehicle were used to treat anti-GBM nephritis in a 2- and 8-week regimen, that is either preventive or therapeutic (treatment started 7 days or 4 weeks after disease induction). Kidney function, morphologic changes, inflammation and fibrosis were monitored. Key Results: In the long-term experiment, linagliptin preventive treatment in anti-GBM nephritic rats significantly reduced the number of crescents, glomerulosclerosis, tubular injury and renal fibrosis, compared with those in untreated nephritic rats. Both linagliptin regimes significantly lowered the number of Pax8+ cells on the glomerular tuft in anti-GBM nephritis, indicating accelerated resolution of the cellular crescents. The linagliptin treatment did not change the podocyte stress in both therapeutic groups. Therapeutic intervention with linagliptin resulted in weaker amelioration of renal disease on Week 8 than did preventive intervention. Conclusion and Implications: DPP-4 inhibition with linagliptin ameliorates renal injury in a rat model of anti-GBM, indicating that linagliptin not only is a secure therapy in diabetes but also can improve resolution of glomerular injury and healing in non-diabetic renal disease.
CRIS-Team Scopus Importer:2021-02-12
Keywords: crescent formation; DPP-4 inhibitor; fibrosis; non-diabetic renal disease

The EMT transcription factor ZEB1 governs a fitness-promoting but vulnerable DNA replication stress response. - Schuhwerk, Harald; Kleemann, Julia; Gupta, Pooja; van Roey, Ruthger; Armstark, Isabell; Kreileder, Martina; Feldker, Nora; Ramesh, Vignesh; Hajjaj, Yussuf; Fuchs, Kathrin; Mahapatro, Mousumi; Hribersek, Mojca; et al. (Cell Reports, 2022)
The DNA damage response (DDR) and epithelial-to-mesenchymal transition (EMT) are two crucial cellular programs in cancer biology. While the DDR orchestrates cell-cycle progression, DNA repair, and cell death, EMT promotes invasiveness, cellular plasticity, and intratumor heterogeneity. Therapeutic targeting of EMT transcription factors, such as ZEB1, remains challenging, but tumor-promoting DDR alterations elicit specific vulnerabilities. Using multi-omics, inhibitors, and high-content microscopy, we discover a chemoresistant ZEB1-high-expressing sub-population (ZEB1hi) with co-rewired cell-cycle progression and proficient DDR across tumor entities. ZEB1 stimulates accelerated S-phase entry via CDK6, inflicting endogenous DNA replication stress. However, DDR buildups involving constitutive MRE11-dependent fork resection allow homeostatic cycling and enrichment of ZEB1hi cells during transforming growth factor β (TGF-β)-induced EMT and chemotherapy. Thus, ZEB1 promotes G1/S transition to launch a progressive DDR benefitting stress tolerance, which concurrently manifests a targetable vulnerability in chemoresistant ZEB1hi cells. Our study thus highlights the translationally relevant intercept of the DDR and EMT.
EVALuna2:512403

The endocardial expression of ADGRG6 (Gpr126) is necessary for survival in mouse and sufficient to drive trabeculation in zebrafish - Musa, Gentian; Srivastava, S.; Engel, Felix (2018)
EVALuna2:34443

The expanding functional roles and signaling mechanisms of adhesion G protein–coupled receptors - Morgan, Rory K.; Anderson, Garret R.; Araç, Demet; Aust, Gabriela; Balenga, Nariman; Boucard, Antony; Bridges, James P.; Engel, Felix; Formstone, Caroline J.; Glitsch, Maike D.; Gray, Ryan S.; Hall, Randy A.; et al. (Annals of the New York Academy of Sciences, 2019)
The adhesion class of G protein–coupled receptors (GPCRs) is the second largest family of GPCRs (33 members in humans). Adhesion GPCRs (aGPCRs) are defined by a large extracellular N-terminal region that is linked to a C-terminal seven transmembrane (7TM) domain via a GPCR-autoproteolysis inducing (GAIN) domain containing a GPCR proteolytic site (GPS). Most aGPCRs undergo autoproteolysis at the GPS motif, but the cleaved fragments stay closely associated, with the N-terminal fragment (NTF) bound to the 7TM of the C-terminal fragment (CTF). The NTFs of most aGPCRs contain domains known to be involved in cell–cell adhesion, while the CTFs are involved in classical G protein signaling, as well as other intracellular signaling. In this workshop report, we review the most recent findings on the biology, signaling mechanisms, and physiological functions of aGPCRs.
CRIS-Team Scopus Importer:2019-06-28
Keywords: adhesion G protein–coupled receptor; cancer; development; immunology; mechanosensation; neurobiology; signal transduction; structural biology

The extracellular matrix protein fibronectin promotes metanephric kidney development - Skoczynski, Kathrin; Kraus, Andre; Daniel, Christoph; Büttner-Herold, Maike; Amann, Kerstin Ute; Schiffer, Mario; Hermann, Kristina; Herrnberger-Eimer, Leonie; Tamm, Ernst R.; Buchholz, Björn (Pflügers Archiv: European Journal of Physiology, 2024)
Complex interactions of the branching ureteric bud (UB) and surrounding mesenchymal cells during metanephric kidney development determine the final number of nephrons. Impaired nephron endowment predisposes to arterial hypertension and chronic kidney disease. In the kidney, extracellular matrix (ECM) proteins are usually regarded as acellular scaffolds or as the common histological end-point of chronic kidney diseases. Since only little is known about their physiological role in kidney development, we aimed for analyzing the expression and role of fibronectin. In mouse, fibronectin was expressed during all stages of kidney development with significant changes over time. At embryonic day (E) 12.5 and E13.5, fibronectin lined the UB epithelium, which became less pronounced at E16.5 and then switched to a glomerular expression in the postnatal and adult kidneys. Similar results were obtained in human kidneys. Deletion of fibronectin at E13.5 in cultured metanephric mouse kidneys resulted in reduced kidney sizes and impaired glomerulogenesis following reduced cell proliferation and branching of the UB epithelium. Fibronectin colocalized with alpha 8 integrin and fibronectin loss caused a reduction in alpha 8 integrin expression, release of glial-derived neurotrophic factor and expression of Wnt11, both of which are promoters of UB branching. In conclusion, the ECM protein fibronectin acts as a regulator of kidney development and is a determinant of the final nephron number.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Alpha 8 integrin; Branching; Fibronectin; Kidney development; Nephron number

The focal adhesion protein β-parvin controls cardiomyocyte shape and sarcomere assembly in response to mechanical load - Thievessen, Ingo; Suhr, Frank; Vergarajauregui, Silvia; Böttcher, Ralph T.; Brixius, Klara; Rosenberger, Georg; Fleischmann, Bernd K.; Ghanem, Alexander; Krüger, Marcus; Engel, Felix; Fabry, Ben; Bloch, Wilhelm; et al. (Current Biology, 2022)
Physiological and pathological cardiac stress induced by exercise and hypertension, respectively, increase the hemodynamic load for the heart and trigger specific hypertrophic signals in cardiomyocytes leading to adaptive or maladaptive cardiac hypertrophy responses involving a mechanosensitive remodeling of the contractile cytoskeleton. Integrins sense load and have been implicated in cardiac hypertrophy, but how they discriminate between the two types of cardiac stress and translate mechanical loads into specific cytoskeletal signaling pathways is not clear. Here, we report that the focal adhesion protein β-parvin is highly expressed in cardiomyocytes and facilitates the formation of cell protrusions, the serial assembly of newly synthesized sarcomeres, and the hypertrophic growth of neonatal rat ventricular cardiomyocytes (NRVCs) in vitro. In addition, physiological mechanical loading of NRVCs by either the application of cyclic, uni-axial stretch, or culture on physiologically stiff substrates promotes NRVC elongation in a β-parvin-dependent manner, which is achieved by binding of β-parvin to α/β-PIX, which in turn activates Rac1. Importantly, loss-of-function studies in mice also revealed that β-parvin is essential for the exercise-induced cardiac hypertrophy response in vivo. Our results identify β-parvin as a novel mechano-responsive signaling hub in hypertrophic cardiomyocytes that drives cell elongation in response to physiological mechanical loads.
CRIS-Team Scopus Importer:2022-08-05
Keywords: affixin; cardiac hypertrophy; integrin-linked kinase; mechanotransduction; Rac1; sarcomere assembly; β-parvin

The heart and vascular system in dialysis - Wanner, Christoph; Amann, Kerstin Ute; Shoji, Tetsuo (Lancet, 2016)
The heart and the vascular tree undergo major structural and functional changes when kidney function declines and renal replacement therapy is required. The many cardiovascular risk factors and adaptive changes the heart undergoes include left ventricular hypertrophy and dilatation with concomitant systolic and diastolic dysfunction. Myocardial fibrosis is the consequence of impaired angio-adaptation, reduced capillary angiogenesis, myocyte-capillary mismatch, and myocardial micro-arteriopathy. The vascular tree can be affected by both atherosclerosis and arteriosclerosis with both lipid rich plaques and abundant media calcification. Development of cardiac and vascular disease is rapid, especially in young patients, and the phenotype resembles all aspects of an accelerated ageing process and latent cardiac failure. The major cause of left ventricular hypertrophy and failure and the most common problem directly affecting myocardial function is fluid overload and, usually, hypertension. In situations of stress, such as intradialytic hypotension and hypoxaemia, the hearts of these patients are more vulnerable to developing cardiac arrest, especially when such episodes occur frequently. As a result, cardiac and vascular mortality are several times higher in dialysis patients than in the general population. Trials investigating one pharmacological intervention (eg, statins) have shown limitations. Pragmatic designs for large trials on cardio-active interventions are mandatory for adequate cardioprotective renal replacement therapy.
EVALuna2:25515

The IKZF1–IRF4/IRF5 axis controls polarization of myeloma-associated macrophages - Mougiakakos, Dimitrios; Bach, Christian; Böttcher, Martin; Beier, Fabian; Röhner, Linda; Stoll, Andrej; Rehli, Michael; Gebhard, Claudia; Lischer, Christopher; Eberhardt, Martin; Vera, Julio; Büttner-Herold, Maike; et al. (Cancer Immunology Research, 2021)
The bone marrow niche has a pivotal role in progression, survival, and drug resistance of multiple myeloma cells. Therefore, it is important to develop means for targeting the multiple myeloma bone marrow microenvironment. Myeloma-associated macrophages (MAM) in the bone marrow niche are M2 like. They provide nurturing signals to multiple myeloma cells and promote immune escape. Reprogramming M2-like macrophages toward a tumoricidal M1 phenotype represents an intriguing therapeutic strategy. This is especially interesting in view of the successful use of mAbs against multiple myeloma cells, as these therapies hold the potential to trigger macrophage-mediated phagocytosis and cytotoxicity. In this study, we observed that MAMs derived from patients treated with the immunomodulatory drug (IMiD) lenalidomide skewed phenotypically and functionally toward an M1 phenotype. Lenalidomide is known to exert its beneficial effects by modulating the CRBN-CRL4 E3 ligase to ubiquitinate and degrade the transcription factor IKAROS family zinc finger 1 (IKZF1). In M2-like MAMs, we observed enhanced IKZF1 levels that vanished through treatment with lenalidomide, yielding MAMs with a bioenergetic profile, T-cell stimulatory properties, and loss of tumor-promoting capabilities that resemble M1 cells. We also provide evidence that IMiDs interfere epigenetically, via degradation of IKZF1, with IFN regulatory factors 4 and 5, which in turn alters the balance of M1/M2 polarization. We validated our observations in vivo using the CrbnI391V mouse model that recapitulates the IMiD-triggered IKZF1 degradation. These data show a role for IKZF1 in macrophage polarization and can provide explanations for the clinical benefits observed when combining IMiDs with therapeutic antibodies. See related Spotlight on p. 254
CRIS-Team Scopus Importer:2021-03-19

The Kidney Donor Profile Index (KDPI) Correlates With Histopathologic Findings in Post-reperfusion Baseline Biopsies and Predicts Kidney Transplant Outcome - Bachmann, Quirin; Haberfellner, Flora; Büttner-Herold, Maike; Torrez, Carlos; Haller, Bernhard; Assfalg, Volker; Renders, Lutz; Amann, Kerstin Ute; Heemann, Uwe; Schmaderer, Christoph; Kemmner, Stephan (Frontiers in Medicine, 2022)
BackgroundThe increasing organ shortage in kidney transplantation leads to the necessity to use kidneys previously considered unsuitable for transplantation. Numerous studies illustrate the need for a better decision guidance rather than only the classification into kidneys from standard or expanded criteria donors referred to as SCD/ECD-classification. The kidney donor profile index (KDPI) exhibits a score utilizing a much higher number of donor characteristics. Moreover, graft biopsies provide an opportunity to assess organ quality. MethodsIn a single center analysis 383 kidney transplantations (277 after deceased and 106 after living donation) performed between January 1st, 2006, and December 31st, 2016, retrospectively underwent SCD/ECD and KDPI scoring. Thereby, the quality of deceased donor kidneys was assessed by using the KDPI and the living donor kidneys by using the living KDPI, in the further analysis merged as (L)KDPI. Baseline biopsies taken 10 min after the onset of reperfusion were reviewed for chronic and acute lesions. Survival analyses were performed using Kaplan-Meier analysis and Cox proportional hazards analysis within a 5-year follow-up. ResultsThe (L)KDPI correlated with glomerulosclerosis (r = 0.30, p < 0.001), arteriosclerosis (r = 0.33, p < 0.001), interstitial fibrosis, and tubular atrophy (r = 0.28, p < 0.001) as well as the extent of acute tubular injury (r = 0.20, p < 0.001). The C-statistic of the (L)KDPI concerning 5-year death censored graft survival was 0.692. Around 48% of ECD-kidneys were classified as (L)KDPI<85%. In a multivariate Cox proportional hazard analysis including (preformed) panel reactive antibodies, cold ischemia time, (L)KDPI, and SCD/ECD-classification, the (L)KDPI was significantly associated with risk of graft loss (hazard ratio per 10% increase in (L)KDPI: 1.185, 95% confidence interval: 1.033-1.360, p = 0.025). Survival analysis revealed decreased death censored (p < 0.001) and non-death censored (p < 0.001) graft survival in kidneys with an increasing (L)KDPI divided into groups of <35, 35-85, and >85%, respectively. ConclusionWith a higher granularity compared to the SCD/ECD-classification the (L)KDPI is a promising tool to judge graft quality. The correlation with chronic and acute histological lesions in post-reperfusion kidney biopsies underlines the descriptive value of the (L)KDPI. However, its prognostic value is limited and underlines the urgent need for a more precise prognostic tool adopted to European kidney transplant conditions.
CRIS-Team WoS Importer:2022-05-27

The lysyl oxidases LOX and LOXL2 are necessary and sufficient to repress E-cadherin in Hypoxia: Insights into cellular transformation processes mediated by HIF-1 - Schietke, Ruth; Warnecke, Christina; Wacker, Ingrid; Schödel, Johannes; Mole, David R.; Campean, Valentina; Amann, Kerstin Ute; Goppelt-Strübe, Margarete; Behrens, Jürgen; Eckardt, Kai-Uwe; Wiesener, Michael Sean (Journal of Biological Chemistry, 2010)
Hypoxia has been shown to promote tumor metastasis and lead to therapy resistance. Recent work has demonstrated that hypoxia represses E-cadherin expression, a hallmark of epithelial to mesenchymal transition, which is believed to amplify tumor aggressiveness. The molecular mechanism of E-cadherin repression is unknown, yet lysyl oxidases have been implicated to be involved. Gene expression of lysyl oxidase (LOX) and the related LOX-like 2 (LOXL2) is strongly induced by hypoxia. In addition to the previously demonstrated LOX, we characterize LOXL2 as a direct transcriptional target of HIF-1. We demonstrate that activation of lysyl oxidases is required and sufficient for hypoxic repression of E-cadherin, which mediates cellular transformation and takes effect in cellular invasion assays. Our data support a molecular pathway from hypoxia to cellular transformation. It includes up-regulation of HIF and subsequent transcriptional induction of LOX and LOXL2, which repress E-cadherin and induce epithelial to mesenchymal transition. Lysyl oxidases could be an attractive molecular target for cancers of epithelial origin, in particular because they are partly extracellular. © 2010 by The American Society for Biochemistry and Molecular Biology, Inc.
CRIS-Team Scopus Importer:2024-05-13

The marine triterpene glycoside frondoside A exhibits activity in vitro and in vivo in prostate cancer - Dyshlovoy, Sergey A.; Menchinskaya, Ekaterina S.; Venz, Simone; Rast, Stefanie; Amann, Kerstin Ute; Hauschild, Jessica; Otte, Katharina; Kalinin, Vladimir I.; Silchenko, Alexandra S.; Avilov, Sergey A.; Alsdorf, Winfried; Madanchi, Ramin; et al. (International Journal of Cancer, 2016)
Despite recent advances in the treatment of metastatic castration-resistant prostate cancer (CRPC), outcome of patients remains poor due to the development of drug resistance. Thus, new drugs are urgently needed. We investigated efficacy, toxicity and mechanism of action of marine triterpene glycoside frondoside A (FrA) using CRPC cell lines in vitro and in vivo. FrA revealed high efficacy in human prostate cancer cells, while non-malignant cells were less sensitive. Remarkably, proliferation and colony formation of cells resistant to enzalutamide and abiraterone (due to the androgen receptor splice variant AR-V7) were also significantly inhibited by FrA. The marine compound caused cell type specific cell cycle arrest and induction of caspase-dependent or -independent apoptosis. Up-regulation or induction of several pro-apoptotic proteins (Bax, Bad, PTEN), cleavage of PARP and caspase-3 and down-regulation of anti-apoptotic proteins (survivin and Bcl-2) were detected in treated cells. Global proteome analysis revealed regulation of proteins involved in formation of metastases, tumor cell invasion, and apoptosis, like keratin 81, CrkII, IL-1? and cathepsin B. Inhibition of pro-survival autophagy was observed following FrA exposure. In vivo, FrA inhibited tumor growth of PC-3 and DU145 cells with a notable reduction of lung metastasis, as well as circulating tumor cells in the peripheral blood. Increased lymphocyte counts of treated animals might indicate an immune modulating effect of FrA. In conclusion, our results suggest that FrA is a promising new drug for the treatment of mCRPC. Induction of apoptosis, inhibition of pro-survival autophagy, and immune modulatory effects are suspected modes of actions.
EVALuna2:25513

The multiple signaling modalities of adhesion G protein-coupled receptor GPR126 in development - Patra, Chinmoy; Monk, Kelly R.; Engel, Felix (Receptors & Clinical Investigation, 2014)
The G protein-coupled receptor (GPCR) superfamily is the largest known receptor family in the human genome. Although the family of adhesion GPCRs comprises the second largest sub-family, their function is poorly understood. Here, we review the current knowledge about the adhesion GPCR family member GPR126. GPR126 possesses a signal peptide, a 7TM domain homologous to secretin-like GPCRs, a GPS motif and an extended N-terminus containing a CUB (Complement, Uegf, Bmp1) domain, a PTX (Pentraxin) domain, a hormone binding domain and 27 putative N-glycosylation sites. Knockdown and knockout experiments in zebrafish and mice have demonstrated that Gpr126 plays an essential role in neural, cardiac and ear development. In addition, genome-wide association studies have implicated variations at the GPR126 locus in obstructive pulmonary dysfunction, in scoliosis and as a determinant of trunk length and body height. Gpr126 appears to exert its function depending on the organ system via G protein- and/or N-terminus-dependent signaling. Here, we review the current knowledge about Gpr126, which, due to the variety of its functions and its multiple signaling modalities, provides a model adhesion GPCR to understand general functional concepts utilized by adhesion GPCRs.
EVALuna2:25482

The Myocardium in Renal Failure - Amann, Kerstin Ute (Springer International Publishing, 2020)
Patients with chronic kidney disease (CKD) suffer disproportionately from cardiovascular (cv) complications and specifically death from cardiac causes. Although the pathogenesis of this exceedingly high cv morbidity and mortality is not well understood, specific structural and functional alterations of the myocardium have been described which can contribute to the increased burden of cv disease in these patients. In the following some of these specific aspects will be discussed.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Angioadaptation; Capillary supply; CKD; Coronary arteries; Fibrosis; Heart; Hypertrophy; Myocardium

The new semisynthetic cardenolide analog 3β-[2-(1-amantadine)-1-on-ethylamine]-digitoxigenin (AMANTADIG) efficiently suppresses cell growth in human leukemia and urologic tumor cell lines - Nolte, Elke; Sobel, Anna; Wach, Sven; Hertlein, Heidi; Ebert, Nadja; Müller-Uri, Frieder; Slany, Robert; Taubert, Helge; Wullich, Bernd; Kreis, Wolfgang (Anticancer Research, 2015)
Background/Aim: The use of cardenolides in the treatment of cardiac insufficiency is well-established. However, the potential of cardenolides in tumor therapy has not been comprehensively studied. The aim of the present study was to characterize the cytotoxic effects of the new semisynthetic cardenolide analog AMANTADIG (3β-[2-(1-amantadine)-1- on-ethylamine]-digitoxigenin), and the cardenolide digitoxin on leukemia and urological tumor cell lines. Materials and Methods: The anti-proliferative effects of AMANTADIG and digitoxin on leukemia and urological cancer cell lines were analyzed using (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) tetrazolium reduction viability assay. Results: AMANTADIG and digitoxin exhibited antiproliferative activities against the leukemia cell lines in the low nanomolar range. The prostate cancer and renal cell carcinoma cell lines were equally sensitive to AMANTADIG and digitoxin, however, the leukemia cell lines were more sensitive to both cardenolides. Conclusion: The new cardenolide analog AMANTADIG appears effective in cell growth inhibition of leukemia and urological tumor cell lines.
Keywords: 3β-[2-(1-Amantadine)-1-on-ethylamine]-digitoxigenin; AMANTADIG; Cardenolide analog; Human leukemia cells; Human urological cancer cells; Porcine cerebral cortex Na+/K+-ATPase

The Phenotypic Spectrum of Nephropathies Associated with Mutations in Diacylglycerol Kinase? - Azukaitis, Karolis; Simkova, Eva; Majid, Mohammad Abdul; Galiano, Matthias; Benz, Kerstin; Amann, Kerstin Ute; Bockmeyer, Clemens; Gajjar, Radha; Meyers, Kevin E.; Cheong, Hae Ii; Lange-Sperandio, Baerbel; Jungraithnnayr, Therese; et al. (Journal of the American Society of Nephrology, 2017)
The recent discovery of mutations in the gene encoding diacylglycerol kinase ? (DGKE) identified a novel pathophysiologic mechanism leading to HUS and/or MPGN. We report ten new patients from eight unrelated kindreds with DGKE nephropathy. We combined these cases with all previously published cases to characterize the phenotypic spectrum and outcomes of this new disease entity. Most patients presented with HUS accompanied by proteinuria, whereas a subset of patients exhibited clinical and histologic patterns of MPGN without TMA. We also report the first two patients with clinical and histologic HUS/MPGN overlap. DGKE-HUS typically manifested in the first year of life but was not exclusively limited to infancy, and viral triggers frequently preceded HUS episodes. We observed signs of complement activation in some patients with DGKE-HUS, but the role of complement activation remains unclear. Most patients developed a slowly progressive proteinuric nephropathy: 80% of patients did not have ESRD within 10 years of diagnosis. Many patients experienced HUS remission without specific treatment, and a few patients experienced HUS recurrence despite complete suppression of the complement pathway. Five patients received renal allografts, with no post-transplant recurrence reported. In conclusion, we did not observe a clear genotype-phenotype correlation in patients with DGKE nephropathy, suggesting additional factors mediating phenotypic heterogeneity. Furthermore, the benefits of anti-complement therapy are questionable but renal transplant may be a feasible option in the treatment of patients with this condition.
EVALuna2:25541

The Prognostic and Predictive Significance of Tumor-Infiltrating Memory T Cells Is Reversed in High-Risk HNSCC - Hartan, Rebekka; Schnellhardt, Sören; Büttner-Herold, Maike; Daniel, Christoph; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Cells, 2022)
Tumor-infiltrating CD45RO+ memory T cells have unanimously been described as a positive prognostic factor in head and neck squamous cell carcinomas (HNSCCs). Here, we investigated the long-term prognostic relevance of CD45RO+ memory T cells in HNSCC with special regard to the influence of clinical characteristics. Pre-treatment biopsy samples from 306 patients with predominantly advanced HNSCC were analyzed. Immunohistochemistry was used to stain tissue microarrays for CD45RO+ memory T cells. CD45RO cell densities were semi-automatically registered and used for survival analysis. High CD45RO+ cell densities were clearly associated with prolonged overall survival (OS) and recurrence-free survival as well as no evidence of disease status after 10 years (p < 0.05). In contrast, the prognostic significance of tumor-infiltrating memory T cells was completely reversed in high-risk groups: in poorly differentiated tumors (G3, G4) and in cases with lymph node involvement (N+), high memory T cell densities correlated with reduced 10-year OS (p < 0.05). In conclusion, an increased density of tumor-infiltrating CD45RO+ cells in HNSCC can be a positive as well as a negative prognostic factor, depending on disease stage and histological grade. Therefore, if CD45RO+ cell density is to be used as a prognostic biomarker, further clinical characteristics must be considered.
CRIS-Team WoS Importer:2022-07-08
Keywords: CD45RO; head and neck cancer; memory T cells; prognostic value; reversal of prognostic value

The Prognostic Value of FoxP3+Tumour-Infiltrating Lymphocytes in Rectal Cancer Depends on Immune Phenotypes Defined by CD8+Cytotoxic T Cell Density - Schnellhardt, Sören; Hirneth, Johannes; Büttner-Herold, Maike; Daniel, Christoph; Haderlein, Marlen; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Frontiers in Immunology, 2022)
Tumour-infiltrating FoxP3+ regulatory T cells have been identified as both positive and negative prognostic factors in colorectal cancer (CRC) and rectal cancer (RC). In this study we investigated whether immune phenotypes, defined by CD8+ cytotoxic T cell density, may influence the prognostic association of FoxP3+ T cell densities in RC. Tissue microarrays from 154 rectal cancer resections were immunohistochemically double stained for CD8 and FoxP3. CD8+ and FoxP3+ cell densities were measured in the stromal and intraepithelial compartment. Stromal FoxP3+ cell densities were not associated with 10-year overall survival (OS). In the "immune-desert" phenotype, defined by very low stromal CD8+ cell density, a high density of stromal FoxP3+ T cells displayed a tendency towards an association with decreased 10-year OS (p = 0.179). In "inflamed" tumours, defined by high intraepithelial CD8+ T cell infiltration, the opposite was the case and high stromal FoxP3+ T cell densities were a positive prognostic factor (p = 0.048). Additionally, patients with an increased FoxP3/CD8 cell density ratio demonstrated a strong trend towards decreased 10-year OS (p = 0.066). These contrasting findings suggest functional heterogeneity within the group of FoxP3+ T cells. They are consistent with experimental studies which reported suppressive and non-suppressive populations of FoxP3+ T cells in CRC. Furthermore, our study demonstrates that CD8 immunohistochemistry may act as an instrument to identify tumours infiltrated by possibly functionally differing FoxP3+ T cell subtypes.
CRIS-Team WoS Importer:2022-02-18

The proteasome inhibitor bortezomib depletes plasma cells and protects mice with lupus-like disease from nephritis - Neubert, Kirsten; Meister, Silke; Moser, Katrin; Weisel, Florian; Maseda, Damian; Amann, Kerstin Ute; Wiethe, Carsten; Winkler, Thomas; Kalden, Joachim; Manz, Rudolf A.; Voll, Reinhard E. (Nature Medicine, 2008)
Autoantibody-mediated diseases like myasthenia gravis, autoimmune hemolytic anemia and systemic lupus erythematosus represent a therapeutic challenge. In particular, long-lived plasma cells producing autoantibodies resist current therapeutic and experimental approaches. Recently, we showed that the sensitivity of myeloma cells toward proteasome inhibitors directly correlates with their immunoglobulin synthesis rates. Therefore, we hypothesized that normal plasma cells are also hypersensitive to proteasome inhibition owing to their extremely high amount of protein biosynthesis. Here we show that the proteasome inhibitor bortezomib, which is approved for the treatment of multiple myeloma, eliminates both short- and long-lived plasma cells by activation of the terminal unfolded protein response. Treatment with bortezomib depleted plasma cells producing antibodies to double-stranded DNA, eliminated autoantibody production, ameliorated glomerulonephritis and prolonged survival of two mouse strains with lupus-like disease, NZB/W F1 and MRL/lpr mice. Hence, the elimination of autoreactive plasma cells by proteasome inhibitors might represent a new treatment strategy for antibody-mediated diseases. © 2008 Nature Publishing Grou

The protective effect of prolyl-hydroxylase inhibition against renal ischaemia requires application prior to ischaemia but is superior to EPO treatment - Wang, Zhendi; Schley, Gunnar; Türkoglu, Gazi; Burzlaff, Nicolai; Amann, Kerstin Ute; Willam, Carsten; Eckardt, Kai-Uwe; Bernhardt, Wanja M. (Nephrology Dialysis Transplantation, 2012)
Background. Inhibition of the HIF regulating prolyl hydroxylation domain (PHDs) proteins prior to renal injury (preconditioning) has been shown to protect the kidney via activation of hypoxia-inducible transcription factors (HIF). Application of erythropoietin (EPO), one of the HIF target genes, has also been shown to be nephroprotective, and it remains unclear to what extent the effect of HIF induction is mediated by EPO. It is also unknown whether HIF activation after the onset of ischaemia (postconditioning) is still able to protect the kidney. Methods. Using a rat model of renal ischaemia-reperfusion injury, animals were treated with the PHD inhibitor (PHD-I) 2-(1-chloro-4- hydroxyisoquinoline-3-carboxamido) acetate (ICA), vehicle (Veh) or recombinant human EPO (300 IU/ kg) 6 h (ICA or Veh) or 30 min (EPO) prior to ischaemia (preconditioning) or with ICA prior to reperfusion (postconditioning). Renal function was assessed at baseline, 24 h and 72 h. After 72 h, kidneys were processed for histology and morphometric analysis. HIF immunohistochemistry and real-time polymerase chain reaction for HIF target genes, including EPO, were performed to evaluate ICA effects. Results. ICA treatment resulted in stabilization of HIF-1α and -2α and up-regulation of HIF target genes in a dosedependent manner. Preconditional activation of HIF by ICA significantly improved serum creatinine levels and renal morphology in comparison to Veh (P < 0.05), while postconditional ICA treatment was ineffective. EPO therapy improved tissue morphology but had no impact on the course of serum creatinine. Conclusion. These findings are in line with the concept that PHD-Is exert their protective effects through accumulation of HIF target gene products, with time requirements for increased transcription and translation of HIF-dependent genes, and suggest that their renoprotective effect is not predominately mediated by EPO. © 2011 The Author.

The pseudokinase MLKL mediates programmed hepatocellular necrosis independently of RIPK3 during hepatitis - Lopez Posadas, Rocío; Becker, Christoph; Günther, Claudia; Tenzer, Stefan; Amann, Kerstin Ute; Billmeier, Ulrike; Atreya, Raja; Fiorino, Gionata; Vetrano, Stefania; Danese, Silvio; Ekici, Arif Bülent; Wirtz, Stefan; et al. (Journal of Clinical Investigation, 2016)
Although necrosis and necroinflammation are central features of many liver diseases, the role of programmed necrosis in the context of inflammation-dependent hepatocellular death remains to be fully determined. Here, we have demonstrated that the pseudokinase mixed lineage kinase domain-like protein (MLKL), which plays a key role in the execution of receptor-interacting protein (RIP) kinase-dependent necroptosis, is upregulated and activated in human autoimmune hepatitis and in a murine model of inflammation-dependent hepatitis. Using genetic and pharmacologic approaches, we determined that hepatocellular necrosis in experimental hepatitis is driven by an MLKL-dependent pathway that occurs independently of RIPK3. Moreover, we have provided evidence that the cytotoxic activity of the proinflammatory cytokine IFN-? in hepatic inflammation is strongly connected to induction of MLKL expression via activation of the transcription factor STAT1. In summary, our results reveal a pathway for MLKL-dependent programmed necrosis that is executed in the absence of RIPK3 and potentially drives the pathogenesis of severe liver diseases.
EVALuna2:2178

The role of filamins in mechanically stressed podocytes - Greiten, Jonas K.; Kliewe, Felix; Schnarre, Annabel; Artelt, Nadine; Schröder, Sindy; Rogge, Henrik; Amann, Kerstin Ute; Daniel, Christoph; Lindenmeyer, Maja T.; Cohen, Clemens D.; Endlich, Karlhans; Endlich, Nicole (The FASEB Journal, 2021)
Glomerular hypertension induces mechanical load to podocytes, often resulting in podocyte detachment and the development of glomerulosclerosis. Although it is well known that podocytes are mechanosensitive, the mechanosensors and mechanotransducers are still unknown. Since filamin A, an actin-binding protein, is already described to be a mechanosensor and mechanotransducer, we hypothesized that filamins could be important for the outside-in signaling as well as the actin cytoskeleton of podocytes under mechanical stress. In this study, we demonstrate that filamin A is the main isoform of the filamin family that is expressed in cultured podocytes. Together with filamin B, filamin A was significantly up-regulated during mechanical stretch (3 days, 0.5 Hz, and 5% extension). To study the role of filamin A in cultured podocytes under mechanical stress, filamin A was knocked down (Flna KD) by specific siRNA. Additionally, we established a filamin A knockout podocyte cell line (Flna KO) by CRISPR/Cas9. Knockdown and knockout of filamin A influenced the expression of synaptopodin, a podocyte-specific protein, focal adhesions as well as the morphology of the actin cytoskeleton. Moreover, the cell motility of Flna KO podocytes was significantly increased. Since the knockout of filamin A has had no effect on cell adhesion of podocytes during mechanical stress, we simultaneously knocked down the expression of filamin A and B. Thereby, we observed a significant loss of podocytes during mechanical stress indicating a compensatory mechanism. Analyzing hypertensive mice kidneys as well as biopsies of patients suffering from diabetic nephropathy, we found an up-regulation of filamin A in podocytes in contrast to the control. In summary, filamin A and B mediate matrix-actin cytoskeleton interactions which are essential for the adaptation of cultured podocyte to mechanical stress.
CRIS-Team Scopus Importer:2021-04-30
Keywords: diabetic nephropathy; Flna; mechanical load; mechanosensor; mechanotransducer

The Role of Palladin in Podocytes - Artelt, Nadine; Ludwig, Tim A.; Rogge, Henrik; Kavvadas, Panagiotis; Siegerist, Florian; Blumenthal, Antje; Van Den Brandt, Jens; Otey, Carol A.; Bang, Marie-Louise; Amann, Kerstin Ute; Chadjichristos, Christos E.; Chatziantoniou, Christos; et al. (Journal of the American Society of Nephrology, 2018)
Background Podocyte loss and effacement of interdigitating podocyte foot processes are the major cause of a leaky filtration barrier and ESRD. Because the complex three-dimensional morphology of podocytes depends on the actin cytoskeleton, we studied the role in podocytes of the actin bundling protein palladin, which is highly expressed therein.Methods We knocked down palladin in cultured podocytes by siRNA transfection or in zebrafish embryos by morpholino injection and studied the effects by immunofluorescence and live imaging. We also investigated kidneys of mice with podocyte-specific knockout of palladin (PodoPalld-/- mice) by immunofluorescence and ultrastructural analysis and kidney biopsy specimens from patients by immunostaining for palladin.Results Compared with control-treated podocytes, palladin-knockdown podocytes had reduced actin filament staining, smaller focal adhesions, and downregulation of the podocyte-specific proteins synaptopodin and α-actinin-4. Furthermore, palladin-knockdown podocytes were more susceptible to disruption of the actin cytoskeleton with cytochalasin D, latrunculin A, or jasplakinolide and showed altered migration dynamics. In zebrafish embryos, palladin knockdown compromised the morphology and dynamics of epithelial cells at an early developmental stage. Compared with PodoPalld+/+ controls, PodoPalld-/- mice developed glomeruli with a disturbed morphology, an enlarged subpodocyte space, mild effacement, and significantly reduced expression of nephrin and vinculin. Furthermore, nephrotoxic serum injection led to significantly higher levels of proteinuria in PodoPalld-/- mice than in controls. Kidney biopsy specimens from patients with diabetic nephropathy and FSGS showed downregulation of palladin in podocytes as well.Conclusions Palladin has an important role in podocyte function in vitro and in vivo.
EVALuna2:34432

The transcription factor Dach1 is essential for podocyte function - Endlich, Nicole; Kliewe, Felix; Kindt, Frances; Schmidt, Katharina; Kotb, Ahmedm.; Artelt, Nadine; Lindenmeyer, Maja T.; Cohen, Clemens D.; Doering, Franziska; Kuss, Andreas W.; Amann, Kerstin Ute; Moeller, Marcus J.; et al. (Journal of Cellular and Molecular Medicine, 2018)
Dedifferentiation and loss of podocytes are the major cause of chronic kidney disease. Dach1, a transcription factor that is essential for cell fate, was found in genome-wide association studies to be associated with the glomerular filtration rate. We found that podocytes express high levels of Dach1 in vivo and to a much lower extent in vitro. Parietal epithelial cells (PECs) that are still under debate to be a type of progenitor cell for podocytes expressed Dach1 only at low levels. The transfection of PECs with a plasmid encoding for Dach1 induced the expression of synaptopodin, a podocyte-specific protein, demonstrated by immunocytochemistry and Western blot. Furthermore, synaptopodin was located along actin fibres in a punctate pattern in Dach1-expressing PECs comparable with differentiated podocytes. Moreover, dedifferentiating podocytes of isolated glomeruli showed a significant reduction in the expression of Dach1 together with synaptopodin after 9 days in cell culture. To study the role of Dach1 in vivo, we used the zebrafish larva as an animal model. Knockdown of the zebrafish ortholog Dachd by morpholino injection into fertilized eggs resulted in a severe renal phenotype. The glomeruli of the zebrafish larvae showed morphological changes of the glomerulus accompanied by down-regulation of nephrin and leakage of the filtration barrier. Interestingly, glomeruli of biopsies from patients suffering from diabetic nephropathy showed also a significant reduction of Dach1 and synaptopodin in contrast to control biopsies. Taken together, Dach1 is a transcription factor that is important for podocyte differentiation and proper kidney function.
EVALuna2:34433

The TRPC5 receptor as pharmacological target for pain and metabolic disease - Khare, Pragyanshu; Chand, Jagdish; Ptakova, Alexandra; Liguori, Renato; Ferrazzi, Fulvia; Bishnoi, Mahendra; Vlachova, Viktorie; Zimmermann, Katharina (Pharmacology & Therapeutics, 2024)
The transient receptor potential canonical (TRPC) channels are a group of highly homologous nonselective cation channels from the larger TRP channel family. They have the ability to form homo- and heteromers with varying degrees of calcium (Ca2+) permeability and signalling properties. TRPC5 is the one cold-sensitive among them and likewise facilitates the influx of extracellular Ca2+ into cells to modulate neuronal depolarization and integrate various intracellular signalling pathways. Recent research with cryo-electron microscopy revealed its structure, along with clear insight into downstream signalling and protein-protein interaction sites. Investigations using global and conditional deficient mice revealed the involvement of TRPC5 in metabolic diseases, energy balance, thermosensation and conditions such as osteoarthritis, rheumatoid arthritis, and inflammatory pain including opioid-induced hyperalgesia and hyperalgesia following tooth decay and pulpitis. This review provides an update on recent advances in our understanding of the role of TRPC5 with focus on metabolic diseases and pain.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Calcium homeostasis; Energy expenditure; Glucose homeostasis; Inflammatory pain; Metabolism; TRPC5

Thrombospondin-1 is a major activator of TGF-β in fibrotic renal disease in the rat in vivo - Daniel, Christoph; Wiede, Julia; Krutzsch, Henry C.; Ribeiro, Solange M. F.; Roberts, David D.; Murphy-Ullrich, Joanne E.; Hugo, Christian (Kidney International, 2004)
Background. Transforming growth factor-β (TGF-β), a profibrotic cytokine involved in many scarring processes, has to be activated extracellularly before it can bind to its receptors. Thrombospondin 1 (TSP1), a multifunctional matricellular glycoprotein, has been identified as an activator of TGF-β in in vitro systems and during mouse postnatal development in vivo. TSP1 is expressed de novo in many inflammatory disease processes, including glomerular disease. Methods. In this study we investigated whether peptides specifically interfering with the activation process of TGF-β by TSP1 may be able to block activation of TGF-β in an in vivo model of mesangial proliferative glomerulonephritis. Results. Continuous intravenous infusion of blocking peptide by minipumps significantly reduced expression of active TGF-β in glomeruli on day 7 of disease as indicated by immunohistochemistry, bioassay, and activation of the TGF-β signal transduction pathway, while total TGF-β expression was unchanged. Inhibition of glomerular TGF-β activation was accompanied by a decrease of glomerular extracellular matrix accumulation and proteinuria, but was without effect on mesangial cell proliferation or influx of monocytes/macrophages. Conclusion. TSP1 is a major endogenous activator of TGF-β in experimental inflammatory glomerular disease. Drugs interfering with the activation of TGF-β by locally produced TSP1 may be considered as a future specific treatment of scarring kidney disease.
Created from Fastlane, Scopus look-up
Keywords: Extracellular matrix; Glomerulonephritis; TGF-β activation; Thrombospondin-1

Thrombospondin-1 is an endogenous activator of TGF-β in experimental diabetic nephropathy in vivo - Daniel, Christoph; Schaub, Kathrin; Amann, Kerstin Ute; Lawler, Jack; Hugo, Christian (Diabetes, 2007)
OBJECTIVE - Transforming growth factor-β (TGF-β), the central cytokine responsible for the development of diabetic nephropathy, is usually secreted as a latent procytokine complex that has to be activated before it can bind to its receptors. Recent studies by our group demonstrated that thrombospondin-1 (TSP-1) is the major activator of latent TGF-β in experimental glomerulonephritis in the rat, but its role in diabetic nephropathy in vivo is unknown. RESEARCH DESIGN AND METHODS - Type 1 diabetes was induced in wild-type (n = 27) and TSP-1-deficient mice (n = 36) via streptozotocin injection, and diabetic nephropathy was investigated after 7, 9.5, and 20 weeks. Renal histology, TGF-β activation, matrix accumulation, and inflammation were assessed by immunohistology. Expression of fibronectin and TGF-β was evaluated using real-time PCR. Furthermore, functional parameters were examined. RESULTS - In TSP-1-deficient compared with wild-type mice, the amount of active TGF-β within glomeruli was significantly lower, as indicated by staining with specific antibodies against active TGF-β or the TGF-β signaling molecule phospho-smad2/3 or the typical TGF-β target gene product plasminogen activator inhibitor-1. In contrast, the amount of glomerular total TGF-β remained unchanged. The development of diabetic nephropathy was attenuated in TSP-1-deficient mice as demonstrated by a significant reduction of glomerulosclerosis, glomerular matrix accumulation, podocyte injury, renal infiltration with inflammatory cells, and renal functional parameters. CONCLUSIONS - We conclude that TSP-1 is an important activator of TGF-β in diabetic nephropathy in vivo. TSP-1-blocking therapies may be considered a promising future treatment option for diabetic nephropathy. © 2007 by the American Diabetes Association.
Created from Fastlane, Scopus look-up

Thrombospondin 2 functions as an endogenous regulator of angiogenesis and inflammation in experimental glomerulonephritis in mice - Daniel, Christoph; Amann, Kerstin Ute; Hohenstein, Bernd; Bornstein, Paul; Hugo, Christian (Journal of the American Society of Nephrology, 2007)
The role of thrombospondin 2 (TSP2) was investigated in an anti-glomerular basement membrane (GBM) nephritis model that compared TSP2-null mice with wild-type (WT) controls. TSP2-null mice were analyzed for kidney function, renal cortical matrix expansion, influx of inflammatory cells, proliferation, and apoptosis, as well as for capillary rarefaction after induction of anti-GBM disease. Whereas the renal cortex of normal control WT mice did not show any detectable TSP2 staining above background, TSP2 protein expression was clearly upregulated in anti-GBM disease. TSP2 deficiency led to an accelerated and enhanced inflammatory response, as indicated by the influx of CD4+ and CD8a+ cells and monocytes/macrophages. Glomerular fibrin deposition and a matrix-remodeling response were also observed, as indicated by collagens I and IV staining and a proliferative response within the renal interstitium. These changes were accompanied by increased matrix metalloproteinase 2 activity and enhanced α-smooth muscle actin staining in the TSP2-null mice. Neither a compensatory increase in TSP1 nor increased phosphorylation of Smad 2/3, an indicator for TGF-β activity, was observed. The proliferative response of the peritubular endothelium was accelerated and enhanced, leading to a reversal of capillary rarefaction in TSP2-null mice, whereas interstitial cell death was equivalent to that in WT mice. In conclusion, the lack of the matricellular protein TSP2 in mice accelerates and enhances several responses to renal injury and reveals an important role for TSP2 as a major endogenous antiangiogenic and matrix metalloproteinase 2-regulating factor in renal disease. Copyright © 2007 by the American Society of Nephrology.
Created from Fastlane, Scopus look-up

Thrombospondin-2 therapy ameliorates experimental glomerulonephritis via inhibition of cell proliferation, inflammation, and TGF-β activation - Daniel, Christoph; Wagner, Andrea; Hohenstein, Bernd; Hugo, Christian (American Journal of Physiology-Renal Physiology, 2009)
We recently identified thrombospondin-2 (TSP-2) as an endogenous regulator of matrix remodelling and inflammation in experimental kidney disease by studying TSP-2-deficient mice. In this study, we asked whether systemic TSP-2 overexpression via thigh muscle transfection is able to ameliorate the time course of the anti-Thy1 glomerulonephritis model. After induction of anti-Thy1 nephritis, rats were transfected either with an overexpression plasmid for TSP-2 or lacZ as a control. Biopsies, urine, and blood samples were taken on days 1, 3, and 6 after disease induction. Muscular overexpression of TSP-2 reduced glomerular transforming growth factor (TGF)-β activation and glomerular extracellular matrix formation as determined by collagen IV and fibronectin. In addition, activation of mesangial cells to the myofibroblast-like phenotype was also significantly decreased in TSP-2-overexpressing animals. TSP-2 overexpression inhibited both glomerular endothelial and mesangial cell proliferation, resulting in a reduced glomerular cell number and glomerular tuft area. The inflammatory response, as monitored by T cells and antigen-presenting cells, was reduced significantly by TSP-2 overexpression, but influx of macrophages was unchanged. These data demonstrate TSP-2 as a potential therapeutic agent to inhibit the glomerular proliferative and inflammatory response as well as TGF-β activation and extracellular matrix accumulation in experimental mesangial proliferative glomerulonephritis. Copyright © 2009 the American Physiological Society.
Created from Fastlane, Scopus look-up
Keywords: Extracellular matrix; Glomerulonephritis; Proliferation; Thrombospondin-2; Transforming growth factor-β activation

Thrombospondin in renal disease - Hugo, Christian; Daniel, Christoph (Nephron Experimental Nephrology, 2009)
Thrombospondins (TSPs) are multifunctional matricellular glycoproteins which are involved in the regulation of angiogenesis, proliferation, apoptosis, the NO-cGMP-dependent protein kinase pathway and transforming growth factor (TGF) β activation. The TSP family consists of 5 members, but currently only data on effects of TSP-1 and TSP-2 in renal disease are available. Both TSPs are hardly expressed within the healthy renal cortex and can be upregulated during renal disease. Using different animal models for renal disease, TSP-1 and -2 were found to be important regulators of pathophysiological changes during renal disease with similar and contrary effects. TSP-1 is a major activator for TGF-β resulting in profibrotic effects in the injured kidney. In contrast, TSP-2 lacks the ability for its activation. Proapoptotic actions of TSP-1 were found during renal ischemia/reperfusion injury. While TSP-1 exerts proinflammatory actions, the currently available data for TSP-2 propose anti-inflammatory effects for this molecule. Both TSPs are known angiogenesis inhibitors, which could be proved for TSP-2, but antiangiogenic effects for TSP-1 were only evident by treatment with TSP-1 peptides in renal disease. In addition, TSP-2 can inhibit cell proliferation and matrix metalloproteinase 2 activity. © 2009 S. Karger AG, Basel.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis inhibitor; Thrombospondin

TIMP-2 and IGFBP7 in human kidney biopsies in renal disease - Schanz, Moritz; Kimmel, Martin; Alscher, Mark Dominik; Amann, Kerstin Ute; Daniel, Christoph (Clinical Kidney Journal, 2023)
Background Tissue inhibitor of matrix metalloproteinase-2 (TIMP-2) and insulin-like growth factor binding protein 7 (IGFBP7) are markers of tubular stress and urinary [TIMP-2]*[IGFBP7] is an established biomarker for risk assessment of acute kidney injury. There are no studies of expression profiles or localization of these markers in human renal tissue with confirmed renal disease. Methods We analysed 37 kidney biopsies of patients with renal disease and 10 non-diseased control biopsies for TIMP-2 and IGFBP7 expression using immunohistochemistry. Changes in glomerular morphology were evaluated by a semi-quantitative glomerulosclerosis score (GSI) and tubular interstitial changes were graded by the tubular injury score (TSI) using periodic acid-Schiff-stained paraffin sections. Interstitial fibrosis and tubular atrophy (IF/TA) were graded according to the Banff classification. Urinary [TIMP-2]*[IGFBP7] was collected at the time of biopsy. Results TIMP-2 and IGFBP7 had significantly greater expression in kidney biopsies from patients with renal disease compared with control tissue, especially in the tubular compartment. Here, IGFBP7 was detected in proximal and distal tubules while TIMP-2 was predominantly localized in the collecting ducts. Renal injury significantly correlated with staining intensity for TIMP-2 and IGFBP7: GSI weakly correlated with glomerular TIMP-2 (r = 0.36) and IGFBP7 (r = 0.35) and TSI correlated with tubular TIMP-2 (r = 0.41) and IGFBP7 (r = 0.43). Urinary [TIMP-2]*[IGFBP7] correlated weakly with the histopathological damage score but not with glomerular and tubular expression. Conclusion Our findings underline the role of TIMP-2/IGFBP7 as an unspecific marker of renal injury that is already in use for early detection of acute kidney injury.
CRIS-Team WoS Importer:2023-03-31

Toward a Better Understanding of the Atypical Features of Chronic Graft-Versus-Host Disease: A Report from the 2020 National Institutes of Health Consensus Project Task Force - Cuvelier, Geoffrey D.E.; Schoettler, Michelle; Buxbaum, Nataliya P.; Pinal-Fernandez, Iago; Schmalzing, Marc; Distler, Jörg; Penack, Olaf; Santomasso, Bianca D.; Zeiser, Robert; Angstwurm, Klemens; MacDonald, Kelli P.A.; Kimberly, W. Taylor; et al. (Transplantation and Cellular Therapy, 2022)
Alloreactive and autoimmune responses after allogeneic hematopoietic cell transplantation can occur in nonclassical chronic graft-versus-host disease (chronic GVHD) tissues and organ systems or manifest in atypical ways in classical organs commonly affected by chronic GVHD. The National Institutes of Health (NIH) consensus projects were developed to improve understanding and classification of the clinical features and diagnostic criteria for chronic GVHD. Although still speculative whether atypical manifestations are entirely due to chronic GVHD, these manifestations remain poorly captured by the current NIH consensus project criteria. Examples include chronic GVHD impacting the hematopoietic system as immune mediated cytopenias, endothelial dysfunction, or as atypical features in the musculoskeletal system, central and peripheral nervous system, kidneys, and serous membranes. These purported chronic GVHD features may contribute significantly to patient morbidity and mortality. Most of the atypical chronic GVHD features have received little study, particularly within multi-institutional and prospective studies, limiting our understanding of their frequency, pathogenesis, and relation to chronic GVHD. This NIH consensus project task force report provides an update on what is known and not known about the atypical manifestations of chronic GVHD while outlining a research framework for future studies to be undertaken within the next 3 to 7 years. We also provide provisional diagnostic criteria for each atypical manifestation, along with practical investigation strategies for clinicians managing patients with atypical chronic GVHD features.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Atypical; Chronic graft-versus-host disease; National Institutes of Health Consensus Project Task Force

Towards regenerating the mammalian heart: challenges in evaluating experimentally induced adult mammalian cardiomyocyte proliferation - Zebrowski, David; Becker, Robert; Engel, Felix (American Journal of Physiology-Heart and Circulatory Physiology, 2016)
In recent years, there has been a dramatic increase in research aimed at regenerating the mammalian heart by promoting endogenous cardiomyocyte proliferation. Despite many encouraging successes, it remains unclear if we are any closer to achieving levels of mammalian cardiomyocyte proliferation for regeneration as seen during zebrafish regeneration. Furthermore, current cardiac regenerative approaches do not clarify whether the induced cardiomyocyte proliferation is an epiphenomena or responsible for the observed improvement in cardiac function. Moreover, due to the lack of standardized protocols to determine cardiomyocyte proliferation in vivo, it remains unclear if one mammalian regenerative factor is more effective than another. Here, we discuss current methods to identify and evaluate factors for the induction of cardiomyocyte proliferation and challenges therein. Addressing challenges in evaluating adult cardiomyocyte proliferation will assist in determining 1) which regenerative factors should be pursued in large animal studies; 2) if a particular level of cell cycle regulation presents a better therapeutic target than another (e.g., mitogenic receptors vs. cyclins); and 3) which combinatorial approaches offer the greatest likelihood of success. As more and more regenerative studies come to pass, progress will require a system that not only can evaluate efficacy in an objective manner but can also consolidate observations in a meaningful way.
EVALuna2:25528

Tracking cell turnover in human brain using 15N-thymidine imaging mass spectrometry - Röder, Sebastian; Bonnin, Elisa A.; Wu, Ting Di; Guerquin-Kern, Jean Luc; Jabari, Samir; Brandner, Sebastian; Eyüpoglu, Ilker Yasin; Gollwitzer, Stephanie; Hamer, Hajo; Gerner, Stefan; Döppner, Thorsten R.; Rummel, Christoph; et al. (Frontiers in Neuroscience, 2023)
Microcephaly is often caused by an impairment of the generation of neurons in the brain, a process referred to as neurogenesis. While most neurogenesis in mammals occurs during brain development, it thought to continue to take place through adulthood in selected regions of the mammalian brain, notably the hippocampus. However, the generality of neurogenesis in the adult brain has been controversial. While studies in mice and rats have provided compelling evidence for neurogenesis occurring in the adult rodent hippocampus, the lack of applicability in humans of key methods to demonstrate neurogenesis has led to an intense debate about the existence and, in particular, the magnitude of neurogenesis in the adult human brain. Here, we demonstrate the applicability of a powerful method to address this debate, that is, the in vivo labeling of adult human patients with 15N-thymidine, a non-hazardous form of thymidine, an approach without any clinical harm or ethical concerns. 15N-thymidine incorporation into newly synthesized DNA of specific cells was quantified at the single-cell level with subcellular resolution by Multiple-isotype imaging mass spectrometry (MIMS) of brain tissue resected for medical reasons. Two adult human patients, a glioblastoma patient and a patient with drug-refractory right temporal lobe epilepsy, were infused for 24 h with 15N-thymidine. Detection of 15N-positive leukocyte nuclei in blood samples from these patients confirmed previous findings by others and demonstrated the appropriateness of this approach to search for the generation of new cells in the adult human brain. 15N-positive neural cells were easily identified in the glioblastoma tissue sample, and the range of the 15N signal suggested that cells that underwent S-phase fully or partially during the 24 h in vivo labeling period, as well as cells generated therefrom, were detected. In contrast, within the hippocampus tissue resected from the epilepsy patient, none of the 2,000 dentate gyrus neurons analyzed was positive for 15N-thymidine uptake, consistent with the notion that the rate of neurogenesis in the adult human hippocampus is rather low. Of note, the likelihood of detecting neurogenesis was reduced because of (i) the low number of cells analyzed, (ii) the fact that hippocampal tissue was explored that may have had reduced neurogenesis due to epilepsy, and (iii) the labeling period of 24 h which may have been too short to capture quiescent neural stem cells. Yet, overall, our approach to enrich NeuN-labeled neuronal nuclei by FACS prior to MIMS analysis provides a promising strategy to quantify even low rates of neurogenesis in the adult human hippocampus after in vivo15N-thymidine infusion. From a general point of view and regarding future perspectives, the in vivo labeling of humans with 15N-thymidine followed by MIMS analysis of brain tissue constitutes a novel approach to study mitotically active cells and their progeny in the brain, and thus allows a broad spectrum of studies of brain physiology and pathology, including microcephaly.
CRIS-Team Scopus Importer:2023-11-03
Keywords: adult; cell turnover; DNA-labeling; glioblastoma; hippocampus; Nano-SIMS; neurogenesis

Transvascular kidney biopsy in adolescent patients-safe alternative to open procedures - Utsch, Boris; Hoppe, Hanno; Dittrich, Katalin; Amann, Kerstin Ute; Gugger, Mathias; Tschumi, Sibylle; Galiano, Matthias; Plank, Christian Georg; Rascher, Wolfgang; Schmid, Axel; Uder, Michael; Dötsch, Jörg (Clinical Kidney Journal, 2021)
CRIS-Team WoS Importer:2021-05-21

Transvenous renal transplant biopsy via a transfemoral approach - Schmid, Axel; Jacobi, Johannes; Kuefner, M. A.; Lell, Michael; Wüst, Wolfgang; Mayer-Kadner, I.; Benz, Kerstin; Schmid, Matthias; Amann, Kerstin Ute; Uder, Michael (American Journal of Transplantation, 2013)
Percutaneous renal biopsy (PRB) of kidney transplants might be prevented by an elevated risk of bleeding or limited access to the allograft. In the following, we describe our initial experience with 71 transvenous renal transplant biopsies in 53 consecutive patients with unexplained reduced graft function who were considered unsuitable candidates for PRB (4.2% of all renal transplant biopsies at our institution). Biopsies were performed via the ipsilateral femoral vein with a renal biopsy set designed for transjugular renal biopsy (TJRB) of native kidneys. Positioning of the biopsy system within the transplant vein was achievable in 58 of 71 (81.7%) procedures. The specimen contained a median of 10 glomeruli (range 0-38). Tissue was considered as adequate for diagnosis in 56 of 57 (98.2%) biopsies. With respect to BANFF 50.9% of the specimen were adequate (>10 glomeruli), 47.4% marginally adequate (1-9 glomeruli) and 1.8% inadequate (no glomeruli). After implementation of real-time assessment all specimen contained glomeruli. One of the fifty-eight (1.8%) procedure-related major complications occurred (hydronephrosis requiring nephrostomy due to gross hematuria). Transfemoral renal transplant biopsy (TFRTB) is feasible and appears to be safe compared to PRB. It offers a useful new alternative for histological evaluation of graft dysfunction in selected patients with contraindications to PRB. The authors report on an experience using transvenous renal transplant biopsy to enable histological evaluation in patients unsuitable for percutaneous transplant biopsy. © 2013 The American Society of Transplantation and the American Society of Transplant Surgeons.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Kidney transplant; percutaneous renal transplant biopsy; renal allograft; renal transplant biopsy; transjugular renal biopsy; transvenous biopsy

Treatment of Membranous Nephropathy in Patients With THSD7A Antibodies Using Immunoadsorption - Weinmann-Menke, Julia; Holtz, Stefan; Sollinger, Daniel; Dörken, Mara; Boedecker, Simone; Schamberger, Beate; Pfister, Frederick; Amann, Kerstin Ute; Lutz, Jens (American Journal of Kidney Diseases, 2019)
Antibodies against THSD7A (thrombospondin type 1 domain-containing protein 7A) have been proposed to play a causal role in the development of nephrotic syndrome in patients with THSD7A antibody–positive membranous nephropathy. We hypothesized that removal of these antibodies from plasma could lead to a rapid reduction in proteinuria. Using immunoadsorption to reduce THSD7A antibodies led to a rapid reduction in proteinuria in 2 patients with THSD7A antibody–positive membranous nephropathy. Moreover, our findings support and strengthen the pathogenic role of the antibodies in the development of nephrotic syndrome in patients with THSD7A antibody–positive membranous nephropathy. Taken together, these 2 cases suggest that immunoadsorption could be a useful tool in the treatment of patients with THSD7A antibody–positive membranous nephropathy.
CRIS-Team Scopus Importer:2019-08-30
Keywords: autoantibodies; case report; immunoadsorption; kidney biopsy; malignancy-associated MN; membranous nephropathy (MN); nephrotic syndrome (NS); proteinuria; THSD7A (thrombospondin type 1 domain-containing protein 7A); urinary protein-creatinine ratio (UPCR)

Tumor-associated macrophages in classical Hodgkin lymphoma: hormetic relationship to outcome - Werner, Laura; Dreyer, Johannes H.; Hartmann, David; Barros, Mário Henrique M.; Büttner-Herold, Maike; Grittner, Ulrike; Niedobitek, Gerald (Scientific Reports, 2020)
Commonly attributed to the prevalence of M2 macrophages, tumor-associated macrophages (TAM) are linked to poor outcome in Hodgkin lymphoma (HL). MYC is supposed to control the expression of M2-specific genes in macrophages, and deficiency in MYC-positive macrophages inhibits tumor growth in mouse models. To verify this hypothesis for HL, seventy-six samples were subjected to immunohistochemical double staining using CD68 or CD163 macrophage-specific antibodies and a reagent detecting MYC. For each cell population, labelled cells were grouped according to low, intermediate and high numbers and related to disease-free survival (DFS) and overall survival (OS). MYC+ cells accounted for 21% and 18% of CD68+ and CD163+ cells, respectively. Numbers of MYC− macrophages were significantly higher in EBV+ cases while no differences were observed for MYC+ macrophages between EBV+ and EBV− cases. Cases with highest numbers of macrophages usually showed worst DFS and OS. In most scenarios, intermediate numbers of macrophages were associated with better outcome than very low or very high numbers. Our observations are reminiscent of the “hormesis hypothesis” and suggest that a relative lack of TAM may allow HL growth while macrophages display an inhibitory effect with increasing numbers. Above a certain threshold, TAM may again support tumor growth.
CRIS-Team Scopus Importer:2020-06-19

Tumor-Associated Neutrophils Are a Negative Prognostic Factor in Early Luminal Breast Cancers Lacking Immunosuppressive Macrophage Recruitment - Schmidt, Eva; Distel, Luitpold; Erber, Ramona; Büttner-Herold, Maike; Rosahl, Marie-Charlotte; Ott, Oliver; Strnad, Vratislav; Hack, Carolin; Hartmann, Arndt; Hecht, Markus; Fietkau, Rainer; Schnellhardt, Sören (Cancers, 2024)
Background: Tumor-associated neutrophils (TANs) are important modulators of the tumor microenvironment with opposing functions that can promote and inhibit tumor progression. The prognostic role of TANs in early luminal breast cancer is unclear. Methods: A total of 144 patients were treated for early-stage hormone-receptor-positive breast cancer as part of an Accelerated Partial Breast Irradiation (APBI) phase II trial. Resection samples from multiple locations were processed into tissue microarrays and sections thereof immunohistochemically stained for CD66b+ neutrophils. CD66b+ neutrophil density was measured separately in the stromal and intraepithelial compartment. Results: High stromal and intraepithelial CD66b+ TAN density was a negative prognostic factor in central tumor samples. In addition, neutrophil density in adjacent normal breast tissue and lymph node samples also correlated with reduced disease-free survival. TAN density correlated with CD163+ M2-like tumor-associated macrophage (TAM) density, which we analyzed in a previous study. TANs were a negative prognostic factor in tumors with an elevated M1/M2 TAM ratio, while this impact on patient outcome was lost in tumors with a low M1/M2 ratio. A combined multivariate analysis of TAM and TAN density revealed that only TAM polarization status was an independent prognostic factor. Conclusions: CD66b+ neutrophils were a negative prognostic factor in early-stage luminal breast cancer in single-marker analysis. Combined analysis with TAMs could be necessary to correctly evaluate their prognostic impact in future studies. TAN recruitment might act as a compensatory mechanism of immunoevasion and disease progression in tumors that are unable to sufficiently attract and polarize TAMs.
CRIS-Team Scopus Importer:2024-10-11
Keywords: breast cancer; CD66b; luminal; tumor-associated macrophages; tumor-associated neutrophils

Tumor grade-titude: XGBoost radiomics paves the way for RCC classification - Ellmann, Stephan; von Rohr, Felicitas; Komina, Selim; Bayerl, Nadine; Amann, Kerstin Ute; Polifka, Iris; Hartmann, Arndt; Sikic, Danijel; Wullich, Bernd; Uder, Michael; Bäuerle, Tobias (European Journal of Radiology, 2025)
This study aimed to develop and evaluate a non-invasive XGBoost-based machine learning model using radiomic features extracted from pre-treatment CT images to differentiate grade 4 renal cell carcinoma (RCC) from lower-grade tumours. A total of 102 RCC patients who underwent contrast-enhanced CT scans were included in the analysis. Radiomic features were extracted, and a two-step feature selection methodology was applied to identify the most relevant features for classification. The XGBoost model demonstrated high performance in both training (AUC = 0.87) and testing (AUC = 0.92) sets, with no significant difference between the two (p = 0.521). The model also exhibited high sensitivity, specificity, positive predictive value, and negative predictive value. The selected radiomic features captured both the distribution of intensity values and spatial relationships, which may provide valuable insights for personalized treatment decision-making. Our findings suggest that the XGBoost model has the potential to be integrated into clinical workflows to facilitate personalized adjuvant immunotherapy decision-making, ultimately improving patient outcomes. Further research is needed to validate the model in larger, multicentre cohorts and explore the potential of combining radiomic features with other clinical and molecular data.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Computed tomography (CT); Diagnostic performance; Feature extraction; Machine learning; Personalized immunotherapy; Radiomics; Renal cell carcinoma (RCC); Treatment decision-making; Tumor grading

Tumor Infiltrating Inflammatory Cells as a prognostic Factor in Glioblastoma - Schnellhardt, Sören; Zorob, Alexander; Polat, B.; Lisowski, D.; Daniel, Christoph; Monoranu, C-M; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Tumor-infiltrating Memory T Cells in Head and Neck Tumors: An ambivalent prognostic Factor - Hartan, R.; Schnellhardt, Sören; Büttner-Herold, Maike; Daniel, Christoph; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Tumor–Stroma Ratio in Colorectal Cancer—Comparison between Human Estimation and Automated Assessment - Firmbach, Daniel; Benz, Michaela; Kuritcyn, Petr; Bruns, Volker; Lang-Schwarz, Corinna; Stübs, Frederik; Merkel, Susanne; Leikauf, Leah-Sophie; Braunschweig, Anna Lea; Oldenburger, Angelika; Gloßner, Laura; Abele, Niklas; et al. (Cancers, 2023)
The tumor–stroma ratio (TSR) has been repeatedly shown to be a prognostic factor for survival prediction of different cancer types. However, an objective and reliable determination of the tumor–stroma ratio remains challenging. We present an easily adaptable deep learning model for accurately segmenting tumor regions in hematoxylin and eosin (H&E)-stained whole slide images (WSIs) of colon cancer patients into five distinct classes (tumor, stroma, necrosis, mucus, and background). The tumor–stroma ratio can be determined in the presence of necrotic or mucinous areas. We employ a few-shot model, eventually aiming for the easy adaptability of our approach to related segmentation tasks or other primaries, and compare the results to a well-established state-of-the art approach (U-Net). Both models achieve similar results with an overall accuracy of 86.5% and 86.7%, respectively, indicating that the adaptability does not lead to a significant decrease in accuracy. Moreover, we comprehensively compare with TSR estimates of human observers and examine in detail discrepancies and inter-rater reliability. Adding a second survey for segmentation quality on top of a first survey for TSR estimation, we found that TSR estimations of human observers are not as reliable a ground truth as previously thought.
CRIS-Team Scopus Importer:2023-06-09
Keywords: colorectal cancer; deep learning; few-shot learning; image analysis; segmentation; tumor–stroma ratio; U-Net

Tumour-infiltrating inflammatory cells in early breast cancer: An underrated prognostic and predictive factor? - Schnellhardt, Sören; Erber, Ramona; Büttner-Herold, Maike; Rosahl, Marie Charlotte; Ott, Oliver; Strnad, Vratislav; Beckmann, Matthias; King, Lillian; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (International Journal of Molecular Sciences, 2020)
The role of tumour-infiltrating inflammatory cells (TIICs) in the disease progression of hormone-receptor-positive breast cancer (HR+ BC) is largely unclear since it is generally regarded as the least immunogenic BC subtype. This study investigated the prognostic significance of CD1a+ dendritic cells, CD20+ B cells, CD45RO+ memory T cells and CD4+ T-helper cells in HR+ BC. One hundred and forty-six patients were treated for early stage, distant-metastases-free HR+ BC in an accelerated partial breast irradiation (APBI) phase II trial. Immunohistochemistry was used to double-stain two adjoining sets of tissue microarrays from pre-RT (radiotherapy) tumour resection samples for CD1a/CD20 and CD45RO/CD4. Cell densities of CD1a+, CD20+, CD45RO+ and CD4+ TIICs in the stromal and intraepithelial compartment were registered semiautomatically. High densities of CD20+ and CD4+ TIICs were strongly associated with reduced disease-free survival (DFS), while high stromal CD45RO+ TIIC densities were indicators of subsequent successful treatment. An immunoscore based on CD20+ and CD45RO+ TIIC densities identified three different risk groups (p < 0.001). Thus, contrary to current assumptions, intratumoural immune cell composition might be an important prognostic indicator and a possible contributing factor in the outcome of HR+ BC and should be the subject of further research. Specifically, B-cell infiltration entailed an increased relapse rate and could play an important role in disease progression.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Accelerated partial breast irradiation; Breast cancer; CD1a; CD20; CD4; CD45RO; Hormone receptor positive; Immunoscore; Prognosis; TIL

TWEAK-Fn14 Cytokine-Receptor Axis: A New Player of Myocardial Remodeling and Cardiac Failure - Novoyatleva, Tatyana; Sajjad, Amna; Engel, Felix (Frontiers in Immunology, 2014)
Tumor necrosis factor (TNF) has been firmly established as a pathogenic factor in heart failure, a significant socio-economic burden. In this review, we will explore the role of other members of the TNF/TNF receptor superfamily (TNFSF/TNFRSF) in cardiovascular diseases (CVDs) focusing on TWEAK and its receptor Fn14, new players in myocardial remodeling and heart failure. The TWEAK/Fn14 pathway controls a variety of cellular activities such as proliferation, differentiation, and apoptosis and has diverse biological functions in pathological mechanisms like inflammation and fibrosis that are associated with CVDs. Furthermore, it has recently been shown that the TWEAK/Fn14 axis is a positive regulator of cardiac hypertrophy and that deletion of Fn14 receptor protects from right heart fibrosis and dysfunction. We discuss the potential use of the TWEAK/Fn14 axis as biomarker for CVDs as well as therapeutic target for future treatment of human heart failure based on supporting data from animal models and in vitro studies. Collectively, existing data strongly suggest the TWEAK/Fn14 axis as a potential new therapeutic target for achieving cardiac protection in patients with CVDs.
EVALuna2:25479

Under-expression of ?8 integrin aggravates experimental atherosclerosis - Menendez-Castro, Carlos; Cordasic, Nada; Neureiter, Daniel; Amann, Kerstin Ute; Marek, Ines; Volkert, Gudrun; Stintzing, Sebastian; Jahn, Angelika; Rascher, Wolfgang; Hilgers, Karl Friedrich; Hartner, Andrea (Journal of Pathology, 2015)
Integrins play an important role in vascular biology. The ?8 integrin chain attenuates smooth muscle cell migration but its functional role in the development of atherosclerosis is unclear. Therefore, we studied the contribution of ?8 integrin to atherosclerosis and vascular remodelling. We hypothesized that ?8 integrin expression is reduced in atherosclerotic lesions, and that its under-expression leads to a more severe course of atherosclerosis. ?8 Integrin was detected by immunohistochemistry and qPCR and ?8 integrin-deficient mice were used to induce two models of atherosclerotic lesions. First, ligation of the carotid artery led to medial thickening and neointima formation, which was quantified in carotid cross-sections. Second, after crossing into ApoE-deficient mice, the formation of advanced vascular lesions with atherosclerotic plaques was quantified in aortic en face preparations stained with Sudan IV. Parameters of renal physiology and histopathology were assessed: ?8 integrin was detected in the media of human and murine vascular tissue and was down-regulated in arteries with advanced atherosclerotic lesions. In ?8 integrin-deficient mice (?8(-/-) ) as well as ?8(+/-) and ?8(+/+) littermates, carotid artery ligation increased media:lumen ratios in all genotypes, with higher values in ligated ?8(-/-) and ?8(+/-) compared to ligated ?8(+/+) animals. Carotid artery ligation increased smooth muscle cell number in the media of ?8(+/+) mice and, more prominently, of ?8(-/-) or ?8(+/-) mice. On an ApoE(-/-) background, ?8(+/-) and ?8(-/-) mice developed more atherosclerotic plaques than ?8(+/+) mice. ?8 Integrin expression was reduced in ?8(+/-) animals. Renal damage with increased serum creatinine and glomerulosclerosis was detected in ?8(-/-) mice only. Thus, under-expression of ?8 integrin aggravates vascular lesions, while a complete loss of ?8 integrin results in reduced renal mass and additional renal disease in the presence of generalized atherosclerosis. Our data support the hypothesis that integrin ?8?1 has a protective role in arterial remodelling and atherosclerosis. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
EVALuna2:3752

Update on monoclonal gammopathy of renal significance [Neues zur monoklonalen Gammopathie renaler Signifikanz] - Büttner-Herold, Maike; Pfister, F.; Amann, Kerstin Ute (Nephrologe, 2019)
The term monoclonal gammopathy of renal significance (MGRS) was recently introduced for glomerular or tubulointerstitial renal diseases that are induced by a monoclonal immunoglobulin (MIg) in the setting of a monoclonal gammopathy of uncertain significance (MGUS) which is regarded as a benign condition. Most of these MIg-associated renal diseases result from direct deposition of nephrotoxic immunoglobulins or their fragments, i. e. light and heavy chain fragments. Hereby, the nature and exact location of the immunoglobulin deposition defines the disease so that apart from light microscopy, immunohistochemistry and/or immunofluorescence and electron microscopy are of utmost importance in the workup of kidney biopsies. It is assumed that at least some members of the MGRS group of diseases, irrespective of the underlying disease, are associated with a higher progression rate which may be one reason for MGRS being considered as an indication for antineoplastic therapy.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Biopsy; Electron microscopy; Immunohistochemistry; Kidney; Paraproteinemias

Uremic mouse model to study vascular calcification and “inflamm-aging” - Tölle, Markus; Henkel, Cornelia; Herrmann, Jaqueline; Daniel, Christoph; Babic, Milen; Xia, Mengdi; Schulz, Anna M.; Amann, Kerstin Ute; van der Giet, Markus; Schuchardt, Mirjam (Journal of Molecular Medicine, 2022)
Calcification and chronic inflammation of the vascular wall is a high-risk factor for cardiovascular mortality, especially in patients with chronic uremia. For the reduction or prevention of rapid disease progression, no specific treatment options are currently available. This study aimed to evaluate an adenine-based uremic mouse model for studying medial vessel calcification and senescence-associated secretory phenotype (SASP) changes of aortic tissue to unravel molecular pathogenesis and provide a model for therapy testing. The dietary adenine administration induced a stable and similar degree of chronic uremia in DBA2/N mice with an increase of uremia blood markers such as blood urea nitrogen, calcium, creatinine, alkaline phosphatase, and parathyroid hormone. Also, renal fibrosis and crystal deposits were detected upon adenine feeding. The uremic condition is related to a moderate to severe medial vessel calcification and subsequent elastin disorganization. In addition, expression of osteogenic markers as Bmp-2 and its transcription factor Sox-9 as well as p21 as senescence marker were increased in uremic mice compared to controls. Pro-inflammatory uremic proteins such as serum amyloid A, interleukin (Il)-1β, and Il-6 increased. This novel model of chronic uremia provides a simple method for investigation of signaling pathways in vascular inflammation and calcification and therefore offers an experimental basis for the development of potential therapeutic intervention studies. Graphical abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2022-08-12
Keywords: Calcification; Cardiovascular; Chronic inflammation; Chronic renal insufficiency; Inflammation; Vascular calcification

Urinary peptidomic liquid biopsy for non-invasive differential diagnosis of chronic kidney disease. - Mavrogeorgis, Emmanouil; He, Tianlin; Mischak, Harald; Latosinska, Agnieszka; Vlahou, Antonia; Schanstra, Joost P.; Catanese, Lorenzo; Amann, Kerstin Ute; Huber, Tobias B.; Beige, Joachim; Rupprecht, Harald D.; Siwy, Justyna (Nephrology Dialysis Transplantation, 2024)
BACKGROUND AND HYPOTHESIS: Specific urinary peptides hold information on disease pathophysiology, which, in combination with artificial intelligence, could enable non-invasive assessment of chronic kidney disease (CKD) aetiology. Existing approaches are generally specific for the diagnosis of single aetiologies. We present the development of models able to simultaneously distinguish and spatially visualize multiple CKD aetiologies. METHODS: The urinary peptide data of 1850 healthy control (HC) and CKD [diabetic kidney disease (DKD), immunoglobulin A nephropathy (IgAN) and vasculitis] participants were extracted from the Human Urinary Proteome Database. Uniform manifold approximation and projection (UMAP) coupled to a support vector machine algorithm was used to generate multi-peptide models to perform binary (DKD, HC) and multiclass (DKD, HC, IgAN, vasculitis) classifications. This pipeline was compared with the current state-of-the-art single-aetiology CKD urinary peptide models. RESULTS: In an independent test set, the developed models achieved 90.35% and 70.13% overall predictive accuracies, respectively, for the binary and the multiclass classifications. Omitting the UMAP step led to improved predictive accuracies (96.14% and 85.06%, respectively). As expected, the HC class was distinguished with the highest accuracy. The different classes displayed a tendency to form distinct clusters in the 3D space based on their disease state. CONCLUSION: Urinary peptide data present an effective basis for CKD aetiology differentiation using machine learning models. Although adding the UMAP step to the models did not improve prediction accuracy, it may provide a unique visualization advantage. Additional studies are warranted to further validate the pipeline's clinical potential as well as to expand it to other CKD aetiologies and also other diseases.
EVALuna2:540388

Validation of the 'Inflammatory Bowel Disease-Distribution, Chronicity, Activity [IBD-DCA] Score' for Ulcerative Colitis and Crohn ' s Disease - Lang-Schwarz, Corinna; Angeloni, Miriam; Agaimy, Abbas; Atreya, Raja; Becker, Christoph; Dregelies, Theresa; Danese, Silvio; Flejou, Jean-Francois; Gassler, Nikolaus; Grabsch, Heike; Hartmann, Arndt; Kamaradova, Katerina; et al. (Journal of Crohns & Colitis, 2021)
Background and Aims: Histological scoring plays a key role in the assessment of disease activity in ulcerative colitis [UC] and is also important in Crohns disease [CD]. Currently, there is no common scoring available for UC and CD. We aimed to validate the Inflammatory Bowel Disease [IBD]-Distribution [D], Chronicity [C], Activity [A] score [IBD-DCA score] for histological disease activity assessment in IBD.
CRIS-Team WoS Importer:2021-11-12

Vascular Calcification in Chronic Kidney Disease: The Role of Inflammation - Benz, Kerstin; Hilgers, Karl Friedrich; Daniel, Christoph; Amann, Kerstin Ute (International Journal of Nephrology, 2018)
Cardiovascular complications are extremely frequent in patients with chronic kidney disease (CKD) and death from cardiac causes is the most common cause of death in this particular population. Cardiovascular disease is approximately 3 times more frequent in patients with CKD than in other known cardiovascular risk groups and cardiovascular mortality is approximately 10-fold more frequent in patients on dialysis compared to the age- and sex-matched segments of the nonrenal population. Among other structural and functional factors advanced calcification of atherosclerotic plaques as well as of the arterial and venous media has been described as potentially relevant for this high cardiovascular morbidity and mortality. One potential explanation for this exceedingly high vascular calcification in animal models as well as in patients with CKD increased systemic and most importantly local (micro)inflammation that has been shown to favor the development of calcifying particles by multiple ways. Of note, local vascular upregulation of proinflammatory and proosteogenic molecules is already present at early stages of CKD and may thus be operative for vascular calcification. In addition, increased expression of costimulatory molecules and mast cells has also been documented in patients with CKD pointing to a more inflammatory and potentially less stable phenotype of coronary atherosclerotic plaques in CKD.
EVALuna2:35397

Vascular inflammation and media calcification are already present in early stages of chronic kidney disease - Benz, Kerstin; Varga, Ildiko; Neureiter, Daniel; Campean, Valentina; Daniel, Christoph; Heim, Christian; Reimann, Albrecht; Weyand, Michael; Hilgers, Karl Friedrich; Amann, Kerstin Ute (Cardiovascular Pathology, 2017)
While patients with chronic kidney disease (CKD) have a high prevalence of classical coronary risk factors, there is increasing evidence that atherosclerosis is different in renal compared to nonrenal patients. Therefore, the present study compares changes in different vessels obtained at cardiac surgery between patients with early and advanced CKD and nonrenal control patients.Fifty patients undergoing cardiac bypass surgery were divided into three groups: (i) 24 control patients with creatinine <1.3mg/dl, (ii) 14 patients with early CKD (creatinine 1.3-2.0mg/dl), and (iii) 12 patients with advanced CKD (creatinine >2.0mg/dl). Aorta, arteria mammaria interna, and vena saphena (V. saphena) were analyzed using morphometry, Kossa stain for vascular calcification, and immunohistochemistry for markers of inflammation and proosteogenic differentiation of vascular smooth muscle cells (VSMCs). Thereby, aortic wall thickness and calcification score of aortic intima and of V. saphena were significantly higher in advanced CKD patients than in nonrenal control patients, whereas significant vascular inflammation and proosteogenic dedifferentiation of VSMC and calcification of the aortic media were already present in early CKD. Interestingly, marked calcification of the V. saphena magna was seen in advanced CKD. Of note, calcium-phosphate product correlated well with markers of inflammation, but not with calcification itself.Early stages of CKD are already associated with local up-regulation of proinflammatory and proosteogenic molecules in the vascular wall and calcification of the aortic media. These findings point to the importance of local microinflammation in CKD and may shed new light on the potentially overestimated role of the calcium-phosphate product for vessel calcification.
EVALuna2:3941

Vascularisation for cardiac tissue engineering: the extracellular matrix - Patra, Chinmoy; Boccaccini, Aldo R.; Engel, Felix (Thrombosis and Haemostasis, 2015)
Cardiovascular diseases present a major socio-economic burden. One major problem underlying most cardiovascular and congenital heart diseases is the irreversible loss of contractile heart muscle cells, the cardiomyocytes. To reverse damage incurred by myocardial infarction or by surgical correction of cardiac malformations, the loss of cardiac tissue with a thickness of a few millimetres needs to be compensated. A promising approach to this issue is cardiac tissue engineering. In this review we focus on the problem of in vitro vascularisation as implantation of cardiac patches consisting of more than three layers of cardiomyocytes (>100 mu m thick) already results in necrosis. We explain the need for vascularisation and elaborate on the importance to include non-myocytes in order to generate functional vascularised cardiac tissue. We discuss the potential of extracellular matrix molecules in promoting vascularisation and introduce nephronectin as an, example of a new promising candidate. Finally, we discuss current biomaterial-based approaches including micropatterning, electrospinning, 3D micro-manufacturing technology and porogens. Collectively, the current literature supports the notion that cardiac tissue engineering is a realistic option for future treatment of paediatric and adult patients with cardiac disease.
Keywords: Heart; vascularisation; coronary vasculature; tissue engineering; extracellular matrix

Vascular occlusion by neutrophil extracellular traps in COVID-19 - Leppkes, Moritz; Knopf, Jasmin; Naschberger, Elisabeth; Lindemann, Aylin; Singh, Jeeshan; Herrmann, Irmgard; Stürzl, Michael; Staats, Léonie; Mahajan, Aparna; Kremer, Anita; Amann, Kerstin Ute; Evert, Katja; et al. (EBioMedicine, 2020)
Background: Coronavirus induced disease 2019 (COVID-19) can be complicated by severe organ damage leading to dysfunction of the lungs and other organs. The processes that trigger organ damage in COVID-19 are incompletely understood. Methods: Samples were donated from hospitalized patients. Sera, plasma, and autopsy-derived tissue sections were examined employing flow cytometry, enzyme-linked immunosorbent assays, and immunohistochemistry. Patient findings: Here, we show that severe COVID-19 is characterized by a highly pronounced formation of neutrophil extracellular traps (NETs) inside the micro-vessels. Intravascular aggregation of NETs leads to rapid occlusion of the affected vessels, disturbed microcirculation, and organ damage. In severe COVID-19, neutrophil granulocytes are strongly activated and adopt a so-called low-density phenotype, prone to spontaneously form NETs. In accordance, markers indicating NET turnover are consistently increased in COVID-19 and linked to disease severity. Histopathology of the lungs and other organs from COVID-19 patients showed congestions of numerous micro-vessels by aggregated NETs associated with endothelial damage. Interpretation: These data suggest that organ dysfunction in severe COVID-19 is associated with excessive NET formation and vascular damage. Funding: Deutsche Forschungsgemeinschaft (DFG), EU, Volkswagen-Stiftung
CRIS-Team Scopus Importer:2020-08-14
Keywords: Aggregated neutrophil extracellular traps; Coagulopathy; Endothelialitis; Immunothrombosis; SARS-CoV-2

Vasodilator-stimulated phosphoprotein-deficient mice demonstrate increased platelet activation but improved renal endothelial preservation and regeneration in passive nephrotoxic nephritis. - Hohenstein, Bernd; Kasperek, Laura; Kobelt, Dieter-Johannes; Daniel, Christoph; Gambaryan, Stepan; Renne, Thomas; Walter, Ulrich; Amann, Kerstin Ute; Hugo, Christian (Journal of the American Society of Nephrology, 2005)
Vasodilator-stimulated phosphoprotein (VASP), an actin cytoskeletal protein, is expressed in various cell types including renal cells. In vitro studies provide evidence for a role of VASP regarding platelet activation, cell adhesion, migration, and capillary formation. The in vivo role of VASP was investigated in experimental inflammatory renal disease. Kidneys of healthy VASP deficient (-/-) and wild-type (wt) mice were compared regarding morphology and functional parameters. Passive nephrotoxic nephritis was induced in 28 VASP -/- and 28 wt mice; kidneys were harvested; and tissues were analyzed by morphometric, immunohistochemical, and electron microscopic techniques on days 3, 7, 14, and 28. The time course of disease in VASP -/- mice differed substantially and biphasically from that in wt controls. Early on, VASP -/- mice demonstrated increased platelet influx associated with augmented glomerular and tubulointerstitial inflammation and sclerosis. Whereas renal disease continuously worsened up to day 28 in wt controls, renal disease in VASP -/- mice hardly progressed after day 3 as assessed by various injury indices. This long-term improvement of renal histology in VASP -/-compared with wt mice was associated with remarkable capillary preservation/regeneration up to day 28 mediated via an increased proliferative and a reduced apoptotic activity of VASP-negative peritubular endothelial cells. Despite an enhanced injury response early on, VASP -/- mice are protected from long-term progression of nephrotoxic nephritis, which is associated with improved renal endothelial cell preservation and regeneration. Copyright © 2005 by the American Society of Nephrology.
UnivIS-Import:2017-03-24:Pub.2005.med.MKIPIII.MKIPLA.vasodi

Vitamin D-dependent induction of cathelicidin in human macrophages results in cytotoxicity against high-grade B cell lymphoma - Bruns, Heiko; Büttner, Maike; Fabri, Mario; Mougiakakos, Dimitrios; Bittenbring, Joerg T.; Hoffmann, Markus; Beier, Fabian; Pasemann, Shirin; Jitschin, Regina; Hofmann, Andreas D.; Neumann, Frank; Daniel, Christoph; et al. (Science Translational Medicine, 2015)
Infiltration by macrophages represents a characteristic morphological hallmark in high-grade lymphatic malignancies such as Burkitt's lymphoma (BL). Although macrophages can, in principle, target neoplastic cells and mediate antibody-dependent cellular cytotoxicity (ADCC), tumor-associated macrophages (TAMs) regularly fail to exert direct cytotoxic functions. The underlying mechanisms responsible for this observation remain unclear. We demonstrate that inflammatory M1 macrophages kill proliferating high-grade B cell lymphoma cells by releasing the antimicrobial peptide cathelicidin in a vitamin D-dependent fashion. We show that cathelicidin directly induces cell death by targeting mitochondria of BL cells. In contrast, anti-inflammatory M2 macrophages and M2-like TAMs in BL exhibit an altered vitamin D metabolism, resulting in a reduced production of cathelicidin and consequently in inability to lyse BL cells. However, treatment of M2 macrophages with the bioactive form of vitamin D, 1,25D3, or a vitamin D receptor agonist effectively induces cathelicidin production and triggers tumoricidal activity against BL cells. Furthermore, rituximab-mediated cytotoxicity of vitamin D-treated M2 macrophages is cathelicidin-dependent. Finally, vitamin D treatment of 25-hydroxyvitamin D (25D)-deficient volunteers in vivo or primary TAMs in vitro improves rituximab-mediated ADCC against B cell lymphoma cells. These data indicate that activation of the vitamin D signaling pathway activates antitumor activity of TAMs and improves the efficacy of ADC
EVALuna2:13103

Whole-exome sequencing identifies mutations of TBC1D1 encoding a Rab-GTPase-activating protein in patients with congenital anomalies of the kidneys and urinary tract (CAKUT) - Kosfeld, Anne; Kreuzer, Martin; Daniel, Christoph; Brand, Frank; Schaefer, Anne-Kathrin; Chadt, Alexandra; Weiss, Anna-Carina; Riehmer, Vera; Jeanpierre, Cecile; Klintschar, Michael; Braesen, Jan Hinrich; Amann, Kerstin Ute; et al. (Human genetics, 2016)
Congenital anomalies of the kidneys and urinary tract (CAKUT) are genetically highly heterogeneous leaving most cases unclear after mutational analysis of the around 30 causative genes known so far. Assuming that phenotypes frequently showing dominant inheritance, such as CAKUT, can be caused by de novo mutations, de novo analysis of whole-exome sequencing data was done on two patient-parent-trios to identify novel CAKUT genes. In one case, we detected a heterozygous de novo frameshift variant in TBC1D1 encoding a Rab-GTPase-activating protein regulating glucose transporter GLUT4 translocation. Sequence analysis of 100 further CAKUT cases yielded three novel or rare inherited heterozygous TBC1D1 missense variants predicted to be pathogenic. TBC1D1 mutations affected Ser237-phosphorylation or protein stability and thereby act as hypomorphs. Tbc1d1 showed widespread expression in the developing murine urogenital system. A mild CAKUT spectrum phenotype, including anomalies observed in patients carrying TBC1D1 mutations, was found in kidneys of some Tbc1d1 (-/-) mice. Significantly reduced Glut4 levels were detected in kidneys of Tbc1d1 (-/-) mice and the dysplastic kidney of a TBC1D1 mutation carrier versus controls. TBC1D1 and SLC2A4 encoding GLUT4 were highly expressed in human fetal kidney. The patient with the truncating TBC1D1 mutation showed evidence for insulin resistance. These data demonstrate heterozygous deactivating TBC1D1 mutations in CAKUT patients with a similar renal and ureteral phenotype, and provide evidence that TBC1D1 mutations may contribute to CAKUT pathogenesis, possibly via a role in glucose homeostasis.
EVALuna2:25497

WT1-dependent sulfatase expression maintains the normal glomerular filtration barrier - Schumacher, Valerie A.; Schlötzer-Schrehardt, Ursula; Karumanchi, S. Ananth; Shi, Xiaofeng; Zaia, Joseph; Jeruschke, Stefanie; Zhang, Dongsheng; Pavenstaedt, Hermann; Drenckhan, Astrid; Amann, Kerstin Ute; Ng, Carrie; Hartwig, Sunny; et al. (Journal of the American Society of Nephrology, 2011)
Paracrine signaling between podocytes and glomerular endothelial cells through vascular endothelial growth factor A (VEGFA) maintains a functional glomerular filtration barrier. Heparan sulfate proteoglycans (HSPGs), located on the cell surface or in the extracellular matrix, bind signaling molecules such as VEGFA and affect their local concentrations, but whether modulation of these moieties promotes normal crosstalk between podocytes and endothelial cells is unknown. Here, we found that the transcription factor Wilms' Tumor 1 (WT1) modulates VEGFA and FGF2 signaling by increasing the expression of the 6-O-endosulfatases Sulf1 and Sulf2, which remodel the heparan sulfate 6-O-sulfation pattern in the extracellular matrix. Mice deficient in both Sulf1 and Sulf2 developed age-dependent proteinuria as a result of ultrastructural abnormalities in podocytes and endothelial cells, a phenotype similar to that observed in children with WT1 mutations and in Wt1(+/-) mice. These kidney defects associated with a decreased distribution of VEGFA in the glomerular basement membrane and on endothelial cells. Collectively, these data suggest that WT1-dependent sulfatase expression plays a critical role in maintaining the glomerular filtration barrier by modulating the bioavailability of growth factors, thereby promoting normal crosstalk between podocytes and endothelial cell
EVALuna2:21045

Zeb1 mediates EMT/plasticity-associated ferroptosis sensitivity in cancer cells by regulating lipogenic enzyme expression and phospholipid composition - Schwab, Annemarie; Rao, Zhigang; Zhang, Jie; Gollowitzer, André; Siebenkäs, Katharina; Bindel, Nino; D’Avanzo, Elisabetta; van Roey, Ruthger; Hajjaj, Yussuf; Özel, Ece; Armstark, Isabell; Bereuter, Leonhard; et al. (Nature Cell Biology, 2024)
Therapy resistance and metastasis, the most fatal steps in cancer, are often triggered by a (partial) activation of the epithelial–mesenchymal transition (EMT) programme. A mesenchymal phenotype predisposes to ferroptosis, a cell death pathway exerted by an iron and oxygen-radical-mediated peroxidation of phospholipids containing polyunsaturated fatty acids. We here show that various forms of EMT activation, including TGFβ stimulation and acquired therapy resistance, increase ferroptosis susceptibility in cancer cells, which depends on the EMT transcription factor Zeb1. We demonstrate that Zeb1 increases the ratio of phospholipids containing pro-ferroptotic polyunsaturated fatty acids over cyto-protective monounsaturated fatty acids by modulating the differential expression of the underlying crucial enzymes stearoyl-Co-A desaturase 1 (SCD), fatty acid synthase (FASN), fatty acid desaturase 2 (FADS2), elongation of very long-chain fatty acid 5 (ELOVL5) and long-chain acyl-CoA synthetase 4 (ACSL4). Pharmacological inhibition of selected lipogenic enzymes (SCD and FADS2) allows the manipulation of ferroptosis sensitivity preferentially in high-Zeb1-expressing cancer cells. Our data are of potential translational relevance and suggest a combination of ferroptosis activators and SCD inhibitors for the treatment of aggressive cancers expressing high Zeb1.
CRIS-Team Scopus Importer:2024-08-02

Zoledronate causes a systemic shift of macrophage polarization towards M1 in vivo - Weber, Manuel; Homm, Andi; Müller, Stefan; Frey, Silke; Amann, Kerstin Ute; Ries, Jutta; Geppert, Carol-Immanuel; Preidl, Raimund; Möst, Tobias; Kämmerer, Peer W.; Kesting, Marco Rainer; Wehrhan, Falk (International Journal of Molecular Sciences, 2021)
Background: Immunomodulatory properties of bisphosphonates (BP) are suggested to contribute to the development of medication‐associated osteonecrosis of the jaw (MRONJ). Further-more, bisphosphonate‐derived immune modulation might contribute to the anti‐metastatic effect observed in breast cancer patients. Macrophages are potential candidates for the mediation of immunomodulatory effects of bisphosphonates. The study aimed to investigate the influence of bisphosphonates alone and in combination with surgical trauma on systemic macrophage polarization (M1 vs. M2) using an in vivo rat model. Methods: A total of 120 animals were divided into four groups. Groups 2 and 4 were treated with 8 × 40 μg/kg body weight of the BP Zoledronate i.p. (week 0–7). Groups 3 and 4 were exposed to surgical trauma (week 8, tooth extraction + tibia fracture), whereas in Group 1 neither medication nor surgical trauma was applied. After 8, 10, 12 and 16 weeks, skin, lung and spleen were immunohistochemically examined for macrophage polarization via expression analysis of CD68, CD163 and iNOS using a tissue microarray (TMA). Results: A significant shift of macrophage polarization towards M1 was observed in skin, spleen and lung tissue of animals, with and without surgical trauma, treated with BP when compared to those without BP application. Surgical trauma did not cause a significant increase towards M1 polarization. Conclusions: BP application leads to a systemic pro‐inflammatory situation in vivo, independent of surgical trauma, as evidenced by the shift in macrophage polarization towards M1 in various somatic tissues. This provides a possible explanation for the clinically observed anti‐tumor effect of bisphosphonates and might also contribute to pathogenesis of MRONJ.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Antiresorptives; Bisphosphonate; Immune modulation; M1; M2; Macrophage polarization; Zoledronate

Zoledronate Shifts Macrophage Polarization towards M1 in Vivo - An Animal Study on Wistar Rats - Weber, Manuel; Amann, Kerstin Ute; Homm, Andi; Müller, Stefan; Ries, Jutta; Geppert, Carol-Immanuel; Preidl, Raimund; Kesting, Marco Rainer; Wehrhan, Falk (2020)
EVALuna2:216186

Zymogen-locked mutant prostasin (Prss8) leads to incomplete proteolytic activation of the epithelial sodium channel (ENaC) and severely compromises triamterene tolerance in mice - Essigke, Daniel; Ilyaskin, Alexandr; Wörn, Matthias; Bohnert, Bernhard N.; Xiao, Mengyun; Daniel, Christoph; Amann, Kerstin Ute; Birkenfeld, Andreas L.; Szabo, Roman; Bugge, Thomas H.; Korbmacher, Christoph; Artunc, Ferruh (Acta physiologica (Oxford, England), 2021)
Aim: The serine protease prostasin (Prss8) is expressed in the distal tubule and stimulates proteolytic activation of the epithelial sodium channel (ENaC) in co-expression experiments in vitro. The aim of this study was to explore the role of prostasin in proteolytic ENaC activation in the kidney in vivo. Methods: We used genetically modified knockin mice carrying a Prss8 mutation abolishing proteolytic activity (Prss8-S238A) or a mutation leading to a zymogen-locked state (Prss8-R44Q). Mice were challenged with low sodium diet and diuretics. Regulation of ENaC activity by Prss8-S238A and Prss8-R44Q was studied in vitro using the Xenopus laevis oocyte expression system. Results: Co-expression of murine ENaC with Prss8-wt or Prss8-S238A in oocytes caused maximal proteolytic ENaC activation, whereas ENaC was activated only partially in oocytes co-expressing Prss8-R44Q. This was paralleled by a reduced proteolytic activity at the cell surface of Prss8-R44Q expressing oocytes. Sodium conservation under low sodium diet was preserved in Prss8-S238A and Prss8-R44Q mice but with higher plasma aldosterone concentrations in Prss8-R44Q mice. Treatment with the ENaC inhibitor triamterene over four days was tolerated in Prss8-wt and Prss8-S238A mice, whereas Prss8-R44Q mice developed salt wasting and severe weight loss associated with hyperkalemia and acidosis consistent with impaired ENaC function and renal failure. Conclusion: Unlike proteolytically inactive Prss8-S238A, zymogen-locked Prss8-R44Q produces incomplete proteolytic ENaC activation in vitro and causes a severe renal phenotype in mice treated with the ENaC inhibitor triamterene. This indicates that Prss8 plays a role in proteolytic ENaC activation and renal function independent of its proteolytic activity.
CRIS-Team Scopus Importer:2021-03-19
Keywords: ENaC; epithelial sodium channel; Prostasin; Prss8; Prss8-R44Q; Prss8-S238A

Zyxin is important for the stability and function of podocytes, especially during mechanical stretch - Kliewe, Felix; Siegerist, Florian; Hammer, Elke; Al-Hasani, Jaafar; Amling, Theodor Rolf Jakob; Hollemann, Jonas Zeno Eddy; Schindler, Maximilian; Drenic, Vedran; Simm, Stefan; Amann, Kerstin Ute; Daniel, Christoph; Lindenmeyer, Maja; et al. (Communications Biology, 2024)
Podocyte detachment due to mechanical stress is a common issue in hypertension-induced kidney disease. This study highlights the role of zyxin for podocyte stability and function. We have found that zyxin is significantly up-regulated in podocytes after mechanical stretch and relocalizes from focal adhesions to actin filaments. In zyxin knockout podocytes, we found that the loss of zyxin reduced the expression of vinculin and VASP as well as the expression of matrix proteins, such as fibronectin. This suggests that zyxin is a central player in the translation of mechanical forces in podocytes. In vivo, zyxin is highly up-regulated in patients suffering from diabetic nephropathy and in hypertensive DOCA-salt treated mice. Furthermore, zyxin loss in mice resulted in proteinuria and effacement of podocyte foot processes that was measured by super resolution microscopy. This highlights the essential role of zyxin for podocyte maintenance in vitro and in vivo, especially under mechanical stretch.
CRIS-Team Scopus Importer:2024-04-19

β2-microglobulin triggers NLRP3 inflammasome activation in tumor-associated macrophages to promote multiple myeloma progression - Hofbauer, Daniel; Mougiakakos, Dimitrios; Broggini, Luca; Zaiss, Mario; Büttner-Herold, Maike; Bach, Christian; Spriewald, Bernd; Neumann, Frank; Bisht, Savita; Nolting, Jens; Zeiser, Robert; Hamarsheh, Shaima'a; et al. (Immunity, 2021)
As substantial constituents of the multiple myeloma (MM) microenvironment, pro-inflammatory macrophages have emerged as key promoters of disease progression, bone destruction, and immune impairment. We identify beta-2-microglobulin (β2m) as a driver in initiating inflammation in myeloma-associated macrophages (MAMs). Lysosomal accumulation of phagocytosed β2m promotes β2m amyloid aggregation in MAMs, resulting in lysosomal rupture and ultimately production of active interleukin-1β (IL-1β) and IL-18. This process depends on activation of the NLRP3 inflammasome after β2m accumulation, as macrophages from NLRP3-deficient mice lack efficient β2m-induced IL-1β production. Moreover, depletion or silencing of β2m in MM cells abrogates inflammasome activation in a murine MM model. Finally, we demonstrate that disruption of NLRP3 or IL-18 diminishes tumor growth and osteolytic bone destruction normally promoted by β2m-induced inflammasome signaling. Our results provide mechanistic evidence for β2m's role as an NLRP3 inflammasome activator during MM pathogenesis. Moreover, inhibition of NLRP3 represents a potential therapeutic approach in MM.
CRIS-Team Scopus Importer:2021-08-13
Keywords: inflammation; macrophages; multiple myeloma; NLRP3; phagocytosis; tumor-associated macrophages

Autoimmune glomerulonephritis in a multiple sclerosis patient after cladribine treatment - Schoenfelder, Kristina; Schuh, Helene; Pfister, Frederick; Kraemer, Julia; Eisenberger, Ute; Skuljec, Jelena; Hackert, Jana; Ruck, Tobias; Pfeuffer, Steffen; Fleischer, Michael; Gaeckler, Anja; Hagenacker, Tim; et al. (Multiple sclerosis journal, 2021)
Background: Oral cladribine is an approved disease-modifying drug for the treatment of relapsing multiple sclerosis. In controlled clinical trials as well as in post marketing safety assessments, autoimmune conditions have not yet been reported as a specific side effect of cladribine. Objective and Results: Here, we report a case of anti-glomerular basement membrane antibody-mediated glomerulonephritis that occurred shortly after the fourth cladribine treatment cycle. Conclusion: Neurologists should be attentive to the development of secondary autoimmunity in cladribine-treated patients.
CRIS-Team WoS Importer:2021-08-06

Early effects of a high-caloric diet and physical exercise on brain volumetry and behavior: a combined MRI and histology study in mice - Sack, Markus; Lenz, Jenny N.; Jakovcevski, Mira; Biedermann, Sarah V.; Falfán-Melgoza, Claudia; Deussing, Jan; Bielohuby, Maximilian; Bidlingmaier, Martin; Pfister, Frederik; Stalla, Günter K.; Sartorius, Alexander; Gass, Peter; et al. (Brain Imaging and Behavior, 2016)
Excessive intake of high-caloric diets as well as subsequent development of obesity and diabetes mellitus may exert a wide range of unfavorable effects on the central nervous system (CNS) in the long-term. The potentially harmful effects of such diets were suggested to be mitigated by physical exercise. Here, we conducted a study investigating early effects of a cafeteria-diet on gray and white brain matter volume by means of voxel-based morphometry (VBM) and region-of-interest (ROI) analysis. Half of the mice performed voluntary wheel running to study if regular physical exercise prevents unfavorable effects of a cafeteria-diet. In addition, histological analyses for myelination and neurogenesis were performed. As expected, wheel running resulted in a significant increase of gray matter volume in the CA1-3 areas, the dentate gyrus and stratum granulosum of the hippocampus in the VBM analysis, while a positive effect of the cafeteria-diet was shown for the whole hippocampal CA1-3 area only in the ROI analysis, indicating a regional volume effect. It was earlier found that hippocampal neurogenesis may be related to volume increases after exercise. Interestingly, while running resulted in a significant increase in neurogenesis assessed by doublecortin (DCX)-labeling, this was not true for cafeteria diet. This indicates different underlying mechanisms for gray matter increase. Moreover, animals receiving cafeteria diet only showed mild deficits in long-term memory assessed by the puzzle-box paradigm, while executive functioning and short term memory were not affected. Our data therefore highlight that high caloric diet impacts on the brain and behavior. Physical exercise seems not to interact with these mechanisms.
EVALuna2:25552

Heterozygous COL4A3 Variants in Histologically Diagnosed Focal Segmental Glomerulosclerosis - Braunisch, Matthias C.; Buttner-Herold, Maike; Guenthner, Roman; Satanovskij, Robin; Riedhammer, Korbinian M.; Herr, Pierre-Maurice; Klein, Hanns-Georg; Wahl, Dagmar; Kuechle, Claudius; Renders, Lutz; Heemann, Uwe; Schmaderer, Christoph; et al. (Frontiers in Pediatrics, 2018)
Introduction: Steroid-resistant nephrotic syndrome (SRNS) is one of the most frequent causes for chronic kidney disease in childhood. In 30% of these cases a genetic cause can be identified. The histological finding in SRNS is often focal segmental glomerulosclerosis (FSGS). In rare cases, however, pathogenic variants in genes associated with Alport syndrome can be identified in patients with the histological finding of FSGS. Materials and Methods: Clinical information was collected out of clinical reports and medical history. Focused molecular genetic analysis included sequencing of COL4A5 and COL4A3 in the index patient. Segregation analysis of identified variants was performed in the parents and children of the index patient. Results: The female index patient developed mild proteinuria and microscopic hematuria in childhood (12 years of age). The histological examination of the kidney biopsies performed at the age of 21, 28, and 32 years showed findings partly compatible with FSGS. However, immunosuppressive treatment of the index patient did not lead to a sufficient reduction of in part nephrotic-range proteinuria. After the patient developed hearing impairment at the age of 34 years and her daughter was diagnosed with microscopic hematuria at the age of 6 years, re-examination of the index's kidney biopsies by electron microscopy revealed textural changes of glomerular basement membrane compatible with Alport syndrome. Molecular genetic analysis identified two missense variants in COL4A3 in a compound heterozygous state with maternal and paternal inheritance. One of them is a novel variant that was also found in the 6 year old daughter of the index patient who presented with microscopic hematuria. Discussion: We were able to show that a novel variant combined with a previously described variant in compound heterozygous state resulted in a phenotype that was histologically associated with FSGS. Molecular genetic analysis therefore can be essential to solve difficult cases that show an unusual appearance and therefore improve diagnostic accuracy. Additionally, unnecessary and inefficient treatment with multiple side effects can be avoided.
EVALuna2:34436

The Case | A 78-year-old woman with acute kidney injury and hemolytic anemia - Zecher, Daniel; Banas, Bernhard; Büttner-Herold, Maike; Kirschfink, Michael; Zipfel, Peter F. (Kidney International, 2019)
EVALuna2:35499